Interactions between local glaciers and adjacent grounded Ross Sea ice in the Royal Society Range, Antarctica - Miles, Maraina; Hall, Brenda; Denton, George (Quaternary Science Reviews, 2024)
The Antarctic Ice Sheet (AIS) has the potential to exert a major control on future global sea level. Here, we gain insight into the response of the Antarctic Ice Sheet (AIS) to changing climate through assessment of ice-sheet behavior during and since the Last Glacial Maximum (LGM) along the western coast of McMurdo Sound. We examine whether expansion of grounded ice in this sector of the Ross Embayment during the last glaciation was caused by increased flux from East Antarctic outlets and local glaciers or was produced by marine influences, such as lowered sea level or reduced melting of submarine grounded ice. During the LGM, grounded ice derived from the Ross Sea deposited a well-defined drift sheet along the Royal Society headlands on the western coast of McMurdo Sound. Twenty-six new radiocarbon dates of subfossil algae within this drift sheet suggest that the ice sheet was at its maximum extent by at least ∼18.4 ka and maintained this position for about five thousand years. Cross-cutting relationships show that local alpine glaciers did not contribute to the grounded ice but rather fluctuated asynchronously. This same relationship held true during the penultimate glaciation, dated to roughly 137–191 ka with 10Be exposure ages. An explanation for this out-of-phase relationship is that different mechanisms controlled their respective extents. Because they lack significant surface melting ablation zones, the local alpine glaciers, which largely terminate on land, were driven by changes in accumulation. These glaciers likely expanded during warmer times when accumulation was higher. In contrast, marine factors, such as global sea-level change and/or subglacial melting, controlled ice fluctuations in the Ross Embayment, including McMurdo Sound, leading to advance during the LGM.
Keywords: Alpine glaciers; Antarctica; Be exposure age dating; Last glacial maximum; radiocarbon; Ross Sea

Authigenic uranium deposition in the glacial North Atlantic: Implications for changes in oxygenation, carbon storage, and deep water-mass geometry - Zhou, Y.; McManus, J. F. (Quaternary Science Reviews, 2023)
Oxygen in the ocean has essential ecological and climatic functions, and can be an important indicator of deep-ocean ventilation and carbon storage. Previous studies are divided on whether the subsurface North Atlantic, which today is well-oxygenated, had higher or lower oxygen levels during the Last Glacial Maximum (LGM). Crucially, the limited number of previous reconstructions precludes any conclusions regarding basin-wide patterns in past changes in oxygenation. Authigenic uranium in deep-sea sediments is a sensitive redox tracer that can shed light on bottom water oxygen. Here, we leverage published and new U- and Th-series isotope measurements from North Atlantic sediments to calculate the mass accumulation rate of authigenic uranium (aU MAR) during the Holocene and the LGM. We find that greater aU burial, reflecting lower-than-Holocene oxygen levels and correspondingly greater respired carbon storage, were persistent features of the LGM in the deep North Atlantic. The eastern basin was substantially less well-oxygenated than the western basin. This zonal contrast is possibly related to the farther advance and greater infilling to the east of the mid-Atlantic Ridge of deep waters originating from the Southern Ocean. An alternative explanation is the different residence time in the two basins of deep waters originating from the subpolar North Atlantic. Previous compilations of two nutrient tracers, δ13C and CdW, are consistent with the varying-deep-circulation interpretation of our aU MAR dataset. The observed threshold behavior of aU or the pattern of export productivity, especially at high latitudes, may also have enhanced this west-east difference.
Keywords: Authigenic uranium; Bottom water oxygen; Last glacial maximum; North Atlantic

Earthquake-enhanced dissolved carbon cycles in ultra-deep ocean sediments - Chu, Mengfan; Bao, Rui; Strasser, Michael; Ikehara, Ken; Everest, Jez; Maeda, Lena; Hochmuth, Katharina; Xu, Li; McNichol, Ann; Bellanova, Piero; Rasbury, Troy; Kölling, Martin; et al. (Nature Communications, 2023)
Hadal trenches are unique geological and ecological systems located along subduction zones. Earthquake-triggered turbidites act as efficient transport pathways of organic carbon (OC), yet remineralization and transformation of OC in these systems are not comprehensively understood. Here we measure concentrations and stable- and radiocarbon isotope signatures of dissolved organic and inorganic carbon (DOC, DIC) in the subsurface sediment interstitial water along the Japan Trench axis collected during the IODP Expedition 386. We find accumulation and aging of DOC and DIC in the subsurface sediments, which we interpret as enhanced production of labile dissolved carbon owing to earthquake-triggered turbidites, which supports intensive microbial methanogenesis in the trench sediments. The residual dissolved carbon accumulates in deep subsurface sediments and may continue to fuel the deep biosphere. Tectonic events can therefore enhance carbon accumulation and stimulate carbon transformation in plate convergent trench systems, which may accelerate carbon export into the subduction zones., Earthquakes enhance dissolved carbon production and fuel the microbial activities in hadal trench subsurface sediments, and ultimately strengthen carbon accumulation and transformation in the subduction zones.

Lake Dynamics Modulate the Air Temperature Variability Recorded by Sedimentary Aquatic Biomarkers: A Holocene Case Study From Western Greenland - Cluett, A. A.; Thomas, E. K.; McKay, N. P.; Cowling, O. C.; Castañeda, I. S.; Morrill, C. (Journal of Geophysical Research: Biogeosciences, 2023)
Quantitative temperature reconstructions from lacustrine organic geochemical proxies including branched glycerol dialkyl glycerol tetraethers (brGDGTs) and alkenones provide key constraints on past continental climates. However, estimation of air temperatures from proxies can be impacted by non-stationarity in the relationships between seasonal air and water temperatures, a factor not yet examined in strongly seasonal high-latitude settings. We pair downcore analyses of brGDGTs and alkenones measured on the same samples through the Holocene with forward-modeled proxy values based on thermodynamic lake model simulations for a western Greenland lake. The measured brGDGT distributions suggest that stable autochthonous (aquatic) production overpowers allochthonous inputs for most samples, justifying the use of the lake model to interpret temperature-driven changes. Conventional calibration of alkenones (detected only after 5.5 thousand years BP) suggests substantially larger temperature variations than conventional calibration of brGDGTs. Comparison of proxy measurements to forward-modeled values suggests variations in brGDGT distributions monotonically reflect multi-decadal summer air temperatures changes, although the length of the ice-free season dampens the influence of air temperatures on water temperatures. Drivers of alkenone variability remain less clear; potential influences include small changes in the seasonality of proxy production or biases toward specific years, both underlain by non-linearity in water-air temperature sensitivity during relevant seasonal windows. We demonstrate that implied temperature variability can differ substantially between proxies because of differences in air-water temperature sensitivity during windows of proxy synthesis without necessitating threshold behavior in the lake or local climate, and recommend that future studies incorporate lake modeling to constrain this uncertainty.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1029/2022JG007106
Keywords: Alkenone; Arctic; biogeochemical proxies; brGDGT; data-model comparison; proxy system modeling

Machine learning based anomaly detection for sedimentological data: Application to a Holocene multi-proxy paleoenvironmental reconstruction from Laguna Boquita, Jalisco, Mexico - Bianchette, Thomas A.; Pandey, Vijitashwa; Mollan, Calahan; Hall, Sawyer; McCloskey, Terrence A.; Liu, Kam-biu (Marine Geology, 2023)
Paleoenvironmental reconstructions are critical to determine past climatological and hydrological conditions, such as sea-level rise (SLR) and extreme events including hurricanes and tsunamis. While established quantitative methods, such as principal components analysis and discriminant analysis, have effectively aided reconstructions by demarcating stratigraphic zones, they suffer from limitations due to the underlying assumptions (linearity, normality). Here, we introduce the machine learning technique anomaly detection for sedimentological reconstructions, capable of objectively pinpointing events (anomalies) in sediment cores. We tested this technique on five sediment cores extracted from Laguna Boquita, located along the Pacific coast of Mexico. Each core was subjected to high resolution loss-on-ignition, while the most representative core (core 1) was deemed the training core and scanned with a handheld XRF unit. In general, the sediment cores were dominated by thick units of peat and/or clay, and most cores contained sand layers. This reconstruction represents many environmental settings, ranging from a sandy terrestrial environment (∼6830- ∼ 6370 cal yr BP), organic-rich wetland (∼6370- ∼ 5170 cal yr BP), and clastic-rich backbarrier lagoon (∼5170 cal yr BP to present). The anomaly detection technique proved effective in marking many events, including marine transgression, evidence of SLR, transitions separating dominant depositional environments, and, perhaps most notably, a faded blue clay layer with minimal LOI variability that may represent a shift in backbarrier water level. The anomaly detection also registered anomalies when events were not visually distinct nor present in the LOI datasets (false positives), which represent sediment core sections that require further investigation with multiple proxies. However, anomaly detection failed to register anomalies in certain core sections that should have registered as events due to their distinct nature. Future efforts will look to improve anomaly detection by choosing different train cores and adding additional proxy datasets.
Keywords: Loss-on-ignition; Machine learning; Paleoclimate; peat; Radiocarbon dating; x-ray fluorescence

More Frequent Hurricane Passage Across the Bahamian Archipelago During the Little Ice Age - Winkler, T. S.; van Hengstum, P. J.; Donnelly, J. P.; Wallace, E. J.; Albury, N. A.; D’Entremont, N.; Hawkes, A. D.; Maio, C. V.; Roberts, J.; Sullivan, R. M.; Woodruff, J. D. (Paleoceanography and Paleoclimatology, 2023)
The year 2020 Common Era (CE) experienced the highest number of named tropical cyclones in the Atlantic Ocean since 1850 CE, but the short instrumental record makes it challenging to assess if this level of activity is statistically meaningful. Here, we present two near-annually resolved hurricane reconstructions from sediment archived in two blue holes located only 300 m apart on the northern margin of Grand Bahama. These two blue holes provide a replicated signal of hurricanes passing within a 50–100 km radius over the last 1,800 years, and the long-term reconstructions document multiple 50-to-150-year intervals when hurricane frequency was significantly higher than it has been over the last 100 years. These two records were first merged into a single stack, and then compiled with five other high-resolution reconstructions from across the Bahamian Archipelago to form a single 1500-year record of Bahamian hurricane frequency. This new Bahamian Compilation documents more hurricanes passing ∼75°W from 21°N to 26°N during the Little Ice Age (LIA; 1300–1850 CE) relative to the prior millennium and the last 170 years. The US Eastern Seaboard also experienced heightened hurricane activity during the LIA, whereas the Gulf of Mexico and Southern Caribbean were inactive. This suggests that despite a globally cooler climate, regional climate conditions during the LIA remained favorable for cyclogenesis and intensification along certain Atlantic hurricane pathways. Perhaps heightened Sahel rainfall during the LIA indicates an increase in African Easterly waves, which in turn possibly seeded more tropical cyclones in the Atlantic Main Development Region.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1029/2023PA004623
Keywords: Bahamas; Carbonate; common era; hurricanes; Paleoclimate; sedimentology

Refractory Dissolved Organic Matter has Similar Chemical Characteristics but Different Radiocarbon Signatures With Depth in the Marine Water Column - White, Margot E.; Nguyen, Tran B.; Koester, Irina; Lardie Gaylord, Mary C.; Beman, J. Michael; Smith, Kenneth L.; McNichol, Ann P.; Beaupré, Steven R.; Aluwihare, Lihini I. (Global Biogeochemical Cycles, 2023)
The >5,000-year radiocarbon age (14C-age) of much of the 630 ± 30 Pg C oceanic dissolved organic carbon (DOC) reservoir remains an enigma in the marine carbon cycle. The fact that DOC is significantly older than dissolved inorganic carbon at every depth in the ocean forms the basis of our current framing of the marine DOC cycle, where some component persists over multiple cycles of ocean mixing. As a result, 14C-depleted, aged DOC is hypothesized to be present as a uniform reservoir with a constant 14C signature and concentration throughout the water column. However, key requirements of this model, including direct observations of DOC with similar 14C signatures in the surface and deep ocean, have never been met. Despite decades of research, the distribution of Δ14C values in marine DOC remains a mystery. Here, we applied a thermal fractionation method to compare operationally defined refractory DOC (RDOC) from different depths in the North Pacific Ocean. We found that RDOC shares chemical characteristics (as recorded by OC bond strength) throughout the water column but does not share the same 14C signature. Our results support one part of the current paradigm—that RDOC is comprised of structurally related components throughout the ocean that form a “background” reservoir. However, in contrast to the current paradigm, our results are consistent with a vertical concentration gradient and a vertical and inter-ocean Δ14C gradient for RDOC. The observed Δ14C gradient is compatible with the potential addition of pre-aged DOC to the upper ocean.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1029/2022GB007603
Keywords: marine dissolved organic matter; radiocarbon; ramped pyrolysis oxidation

A Tropical Cocktail of Organic Matter Sources: Variability in Supraglacial and Glacier Outflow Dissolved Organic Matter Composition and Age Across the Ecuadorian Andes - Holt, Amy D.; Kellerman, Anne M.; Battin, Tom. I.; McKenna, Amy M.; Hood, Eran; Andino, Patricio; Crespo-Pérez, Verónica; Peter, Hannes; Schön, Martina; De Staercke, Vincent; Styllas, Michail; Tolosano, Matteo; et al. (Journal of Geophysical Research: Biogeosciences, 2023)
The biogeochemistry of rapidly retreating Andean glaciers is poorly understood, and Ecuadorian glacier dissolved organic matter (DOM) composition is unknown. This study examined molecular composition and carbon isotopes of DOM from supraglacial and outflow streams (n = 5 and 14, respectively) across five ice capped volcanoes in Ecuador. Compositional metrics were paired with streamwater isotope analyses (δ18O) to assess if outflow DOM composition was associated with regional precipitation gradients and thus an atmospheric origin of glacier DOM. Ecuadorian glacier outflows exported ancient, biolabile dissolved organic carbon (DOC), and DOM contained a high relative abundance (RA) of aliphatic and peptide-like compounds (≥27%RA). Outflows were consistently more depleted in Δ14C-DOC (i.e., older) compared to supraglacial streams (mean −195.2 and −61.3‰ respectively), perhaps due to integration of spatially heterogenous and variably aged DOM pools across the supraglacial environment, or incorporation of aged subglacial OM as runoff was routed to the outflow. Across Ecuador, Δ14C-DOC enrichment was associated with decreased aromaticity of DOM, due to increased contributions of organic matter (OM) from microbial processes or atmospheric deposition of recently fixed and subsequently degraded OM (e.g., biomass burning byproducts). There was a regional gradient between glacier outflow DOM composition and streamwater δ18O, suggesting covariation between regional precipitation gradients and the DOM exported from glacier outflows. Ultimately, this highlights that atmospheric deposition may exert a control on glacier outflow DOM composition, suggesting regional air circulation patterns and precipitation sources in part determine the origins and quality of OM exported from glacier environments.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1029/2022JG007188
Keywords: cryosphere; dissolved organic carbon; Dissolved organic matter; Ecuador; FT-ICR MS; glaciers; δ13C-DOC; Δ14C-DOC

A 4000-year paleoenvironmental reconstruction and extreme event record from Laguna Nuxco, Guerrero, Mexico - Bianchette, Thomas A.; Liu, Kam-biu; McCloskey, Terrence A. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2022)
Reconstructing paleoenvironments on Mexico's Pacific coast is crucial to determine past climate conditions and natural hazard periodicities, vital for predicting future activities. Two sediment cores extracted from Laguna Nuxco, a coastal lagoon in Guerrero, were analyzed to provide a 4000-year paleoenvironmental record. Sediments dominated by shelly clay with low water and organic content, high carbonate content, low Ti/Ca ratio and the presence of Anomalocardia subrugosa suggest that a sheltered bay existed from ~4000–~1300 cal yr BP. During this stage, intermittent beach ridge gaps facilitated the deposition of storm-induced shell deposits, likely from tropical cyclones. Frequent thick shell hash deposition toward the top of the lithologic unit indicates heightened storminess likely from an increase in ENSO activity. An intense tropical cyclone, or perhaps multiple storms during an active period deposited a thick shell hash layer at ~1500 cal yr BP, which helped strengthen the beach ridge system and lead to the modern lagoon phase (~1300 cal yr BP to present), as suggested by the presence of Mytella sp. A more isolated lagoon with significant terrestrial sediment input was reflected by the predominance of lagoonal clay with decreased shell and carbonate contents, increased water and organic contents, and increased Ti/Ca ratio. A quiet period with lower tropical cyclone activity occurred from 1300 to 800 cal yr BP and from 300 cal yr BP to the present, as inferred from no or relatively few shell hash deposits, respectively. A period of hyperactivity occurred from 800 to 300 cal yr BP, as evidenced by seven shell hash layers. During the modern lagoon phase, shell hash deposition was not caused by marine inundation processes, but rather ‘blowout’ events driven by intense precipitation during heightened ENSO activity. Findings shed additional light on Late Holocene environmental changes in a dynamic coastal zone related to regional controlling factors such as tropical cyclone activity, ENSO, and beach ridge development.

Baobabs at the edge: 90-year dynamics of climate variability, growth, resilience, and evolutionary legacy effects - Mayne, Diana H.; Karimi, Nisa; Cruywagen, Elsie M.; Cole, Patrick; Goodall, Victoria (Frontiers in Forests and Global Change, 2022)
Climate variability and resilience remain gaps in tree research, challenged by the interacting factors in climate change, long-term resilience and the influence of evolutionary legacy effects. In a multidisciplinary approach using 90-year (1930–2020) climate-growth data, we investigated the dynamics of climate variability on growth and resilience of the tropical African baobab (Adansonia digitata) at the range edge in climate-variable, southeast Africa. The main driver of climate variability, ENSO (El Niño-Southern Oscillation), triggered 83% of droughts exacerbated by positive Indian Ocean Dipole (pIOD) events. Growth over 90 years was positively correlated with maximum temperature and increased after the 1976–1977 Global Warming Shift. The influence of warming was compromised by climate variability and extreme events. Although growth is a measure of adaptive capacity, accelerated growth over the past 20 years contrasted with dehydration, canopy dieback and a novel Didymella pathogen. Resilience was contingent on high genetic diversity (polyploidy and heterozygosity) and Neotropical legacy effects of stem water storage and longevity trade-offs of low growth, recruitment and reproduction. The evolution of resprouting in disturbed, fire-prone ecosystems and bark regeneration increased recovery from disturbance. As resource opportunists, baobabs adopted a fast-slow survival strategy. Rainfall and warming enhanced growth while low and variable rainfall favoured a conservative, low growth-higher survival strategy. Low rainfall, climate extremes and topography increased mortality risk. Mortality was higher at lower elevations on site and regionally. Low growth may conserve the baobab in climate warming but the southern hemisphere tropics is one of two identified global hotspots with amplified hot years. The heightened disturbance predicted from increased climate variability, hot droughts and landfalling tropical cyclones magnifies mortality risk for “Africa’s favourite tree.”

Carbon Accumulation, Flux, and Fate in Stordalen Mire, a Permafrost Peatland in Transition - Holmes, M. E.; Crill, P. M.; Burnett, W. C.; McCalley, C. K.; Wilson, R. M.; Frolking, S.; Chang, K.‐Y.; Riley, W. J.; Varner, R. K.; Hodgkins, S. B.; McNichol, A. P.; Saleska, S. R.; et al. (Global Biogeochemical Cycles, 2022)
Stordalen Mire is a peatland in the discontinuous permafrost zone in arctic Sweden that exhibits a habitat gradient from permafrost palsa, to Sphagnum bog underlain by permafrost, to Eriophorum‐dominated fully thawed fen. We used three independent approaches to evaluate the annual, multi‐decadal, and millennial apparent carbon accumulation rates (aCAR) across this gradient: seven years of direct semi‐continuous measurement of CO2 and CH4 exchange, and 21 core profiles for 210Pb and 14C peat dating. Year‐round chamber measurements indicated net carbon balance of −13 ± 8, −49 ± 15, and −91 ± 43 g C m−2 y−1 for the years 2012–2018 in palsa, bog, and fen, respectively. Methane emission offset 2%, 7%, and 17% of the CO2 uptake rate across this gradient. Recent aCAR indicates higher C accumulation rates in surface peats in the palsa and bog compared to current CO2 fluxes, but these assessments are more similar in the fen. aCAR increased from low millennial‐scale levels (17–29 g C m−2 y−1) to moderate aCAR of the past century (72–81 g C m−2 y−1) to higher recent aCAR of 90–147 g C m−2 y−1. Recent permafrost collapse, greater inundation and vegetation response has made the landscape a stronger CO2 sink, but this CO2 sink is increasingly offset by rising CH4 emissions, dominated by modern carbon as determined by 14C. The higher CH4 emissions result in higher net CO2‐equivalent emissions, indicating that radiative forcing of this mire and similar permafrost ecosystems will exert a warming influence on future climate. Stordalen Mire, a permafrost peatland, has become a stronger carbon sink due to shifts in vegetation and inundation accompanying thaw This stronger carbon sink is offset by an increase in methane emission, resulting in higher net CO2‐equivalent emissions Analysis of respiration products indicates that methane emission from the fen and bog are dominated by modern carbon Stordalen Mire, a permafrost peatland, has become a stronger carbon sink due to shifts in vegetation and inundation accompanying thaw This stronger carbon sink is offset by an increase in methane emission, resulting in higher net CO2‐equivalent emissions Analysis of respiration products indicates that methane emission from the fen and bog are dominated by modern carbon

Community practice and religion at an Early Islamic cemetery in highland Central Asia - Bullion, Elissa; Maksudov, Farhod; Henry, Edward R.; Merkle, Ann; Frachetti, Michael (Antiquity, 2022)
Archaeological studies of Early Islamic communities in Central Asia have focused on lowland urban communities. Here, the authors report on recent geophysical survey and excavation of an Early Islamic cemetery at Tashbulak in south-eastern Uzbekistan. AMS dating places the establishment of the cemetery in the mid-eighth century AD, making it one of the earliest Islamic burial grounds documented in Central Asia. Burials at Tashbulak conform to Islamic prescriptions for grave form and body deposition. The consistency in ritual suggests the existence of a funerary community of practice, challenging narratives of Islamic conversion in peripheral areas as a process of slow diffusion and emphasising the importance of archaeological approaches for documenting the diversity of Early Islamic communities.

Contemporary sources dominate carbonaceous aerosol on the North Slope of Alaska - Moffett, Claire E.; Mehra, Manisha; Barrett, Tate E.; Gunsch, Matthew J.; Pratt, Kerri A.; Sheesley, Rebecca J. (Science of The Total Environment, 2022)
As the Arctic continues to change and warm rapidly, it is increasingly important to understand the organic carbon (OC) contribution to Arctic aerosol. Biogenic sources of primary and secondary OC in the Arctic will be impacted by climate change, including warming temperatures and earlier snow and ice melt. This study focuses on identifying potential sources and regional influences on the seasonal concentration of organic aerosol through analysis of chemical and isotopic composition. Aerosol samples were collected at two sites on the North Slope of Alaska (Utqiaġvik, UQK, and Oliktok Point, OLK, which is in an Arctic oilfield) over three summers from 2015 to 2017. The elemental carbon (EC) trends at each site were used to understand local combustion influences. Local sources drove EC concentrations at Oliktok Point, where high EC was attributed to oil and gas extraction activity, including diesel combustion emissions. Utqiaġvik had very low EC in the summer. OC was more similar in concentration and well correlated between the two sites with high contributions of contemporary carbon by radiocarbon apportionment (UQK = 74%, OLK = 63%), which could include both marine and terrestrial sources of contemporary carbon (e.g. primary and secondary biogenic, biomass burning and/or associated SOA, and bioaerosols). OC concentrations are strongly correlated to maximum ambient temperatures on the NSA during the summer, which may have implications for predicting future OC aerosol concentrations in a warming Arctic. Biomass burning was determined to be an episodic influence at both sites, based on interpretation of combined aerosol composition, air mass trajectories, and remote sensing of smoke plumes. The results from this study overall strongly suggests contribution from regional sources of contemporary organic aerosol on the NSA, but additional analysis is needed to better constrain contributions from both biogenic sources (terrestrial and/or marine) and bioaerosol to better understand temperature-related aerosol processes in the Arctic.

Cultural Keystone Places and the Chumash Landscapes of Kumqaq’, Point Conception, California - Rick, Torben C.; Braje, Todd J.; Graham, Lain; Easterday, Kelly; Hofman, Courtney A.; Holguin, Brian E.; Mychajliw, Alexis M.; Reeder-Myers, Leslie A.; Reynolds, Mark D. (American Antiquity, 2022)
The places in which people live and spend time are steeped in history, memory, and meaning from the intersection of daily life, environmental interactions, cultural practices, and ritual. Geologic features, plants, animals, and ecosystems merge with these cultural histories, forming critical parts of the landscape and areas of “high cultural salience,” or “cultural keystone places” (CKPs). We identify Kumqaq’ (Point Conception) and the surrounding area in California as a Chumash CKP. Ethnohistoric accounts and contemporary Chumash community members have long demonstrated the importance of Point Conception in Chumash worldview and identity, whereas biologists, ecologists, and conservationists reference the area's rich biodiversity and significance as a biogeographical boundary. Recent archaeological survey of the coastline surrounding Kumqaq’ highlights these connections, identifying over 50 archaeological sites—including shell middens, villages, lithic scatters, and rock art—with at least 9,000 years of occupation. Ongoing collaborations among archaeologists, the Nature Conservancy, and Chumash community members help document and understand the long-term linkages between cultural and biological diversity and how integrating these perspectives can help ensure the resilience of this nexus of human and natural history in the Anthropocene future.

The dynamics of warming during the last deglaciation in high-elevation regions of Eastern Equatorial Africa - Garelick, Sloane; Russell, James; Richards, Adin; Smith, Jamila; Kelly, Meredith; Anderson, Nathan; Jackson, Margaret S.; Doughty, Alice; Nakileza, Bob; Ivory, Sarah; Dee, Sylvia; Marshall, Charlie (Quaternary Science Reviews, 2022)
Tropical mountain environments, such as the Rwenzori Mountains in equatorial Africa, are thought to be particularly sensitive to climate change. Ongoing warming in the Rwenzori is impacting local environments and communities through glacial retreat, fires, and flooding. Paleoclimate reconstructions from elsewhere in Africa suggest considerable warming accompanied glacier retreat during the last glacial termination, from ∼21 thousand years before present (ka) through the early to mid-Holocene. Quantifying these changes has been difficult but could help to assess future impacts in the Rwenzori. Here, we present a ∼21 thousand-year (kyr) temperature reconstruction based on the relative abundance of branched glycerol dialkyl glycerol tetraethers (brGDGTs) from Lake Mahoma (2,990 m above sea level; m asl) in the Rwenzori Mountains, Uganda. Our record, paired with existing Rwenzori glacial moraine 10Be exposure ages, suggests that deglacial warming and glacial retreat began by ∼20 ka and accelerated at ∼18–18.5 ka. The timing of the onset of rapid warming matches the timing of the post-glacial rise in radiative forcing from atmospheric greenhouse gases (GHGs) from Antarctic ice cores (Brook et al., 1996; Marcott et al., 2014; Monnin et al., 2004; Schilt et al., 2010). Our temperature reconstruction registers ∼4.9 °C warming from the Last Glacial Maximum (LGM) to the late Holocene. This increase is larger than the average ∼2-4 °C warming observed in records from lower elevation sites in tropical East Africa, but similar to that observed at other high-elevation sites in this region. The increased warming at higher elevations thus confirms that the temperature lapse rate steepened during the LGM over this region. Our results also indicate ∼3 °C of warming during the mid-Holocene relative to the late Holocene. This suggests that the freezing-level height rose above Rwenzori summit elevations at that time, likely causing complete deglaciation of the Rwenzori Mountains from ∼5 to 7 ka. The mid-Holocene is thus a potential analog for the glacial and environmental changes that these mountains are likely to experience in the coming decades. Overall, the timing and magnitude of temperature change observed in our record has important implications for climate model projections of future warming in tropical Africa.

Geochemistry and Provenance of Springs in a Baja California Sur Mountain Catchment - Lerback, Jory C.; Bowen, Brenda B.; Humphrey, C. E.; Fernandez, Diego. P.; Bernau, Jeremiah A.; Macfarlan, Shane J.; Schniter, Eric; Garcia, J. J. (Groundwater, 2022)
Fractured rock aquifers cover much of Earth's surface and are important mountain sites for groundwater recharge but are poorly understood. To investigate groundwater systematics of a fractured-dominated aquifer in Baja California Sur, Mexico, we examined the spatial patterns of aquifer recharge and connectivity using the geochemistry of springs. We evaluate a range of geochemical data within the context of two endmember hypotheses describing spatial recharge patterns and fracture connectivity. Hypothesis 1 is that the aquifer system is segmented, and springs are fed by local recharge. Hypothesis 2 is that the aquifer system is well connected, with dominant recharge occurring in the higher elevations. The study site is a small <15 km2 catchment. Thirty-four distinct springs and two wells were identified in the study area, and 24 of these sites were sampled for geochemical analyses along an elevation gradient and canyon transect. These analyses included major ion composition, trace element and strontium isotopes, δ18 O and δ2 H isotopes, radiocarbon, and tritium. δ18 O and δ2 H isotopes suggest that the precipitation feeding the groundwater system has at least two distinct sources. Carbon isotopes showed a change along the canyon transect, suggesting that shorter flowpaths feed springs in the top of the transect, and longer flowpaths discharge near the bottom. Geochemical interpretations support a combination of the two proposed hypotheses. Understanding of the connectivity and provenance of these springs is significant as they are the primary source of water for the communities that inhabit this region and may be impacted by changes in recharge and use.

The giant 1960 tsunami in the context of a 6000‐year record of paleotsunamis and coastal evolution in south‐central Chile - Matos‐Llavona, Pedro I.; Ely, Lisa L.; MacInnes, Breanyn; Dura, Tina; Cisternas, Marco A.; Bourgeois, Joanne; Bruce, David; DePaolis, Jessica; Dolcimascolo, Alexander; Horton, Benjamin P.; Melnick, Daniel; Nelson, Alan R.; et al. (Earth Surface Processes and Landforms, 2022)
The tsunami associated with the giant 9.5 Mw 1960 Chile earthquake deposited an extensive sand layer above organic‐rich soils near Queule (39.3°S, 73.2°W), south‐central Chile. Using the 1960 tsunami deposits, together with eye‐witness observations and numerical simulations of tsunami inundation, we tested the tsunami inundation sensitivity of the site to different earthquake slip distributions. Stratigraphically below the 1960 deposit are two additional widespread sand layers interpreted as tsunami deposits with maximum ages of 4960–4520 and 5930–5740 cal BP. This >4500‐year gap of tsunami deposits preserved in the stratigraphic record is inconsistent with written and geological records of large tsunamis in south‐central Chile in 1575, 1837, and possibly 1737. We explain this discrepancy by: (1) poor preservation of tsunami deposits due to reduced accommodation space from relative sea‐level fall during the late Holocene; (2) recently evolved coastal geomorphology that increased sediment availability for tsunami deposit formation in 1960; and/or (3) the possibility that the 1960 tsunami was significantly larger at this particular location than other tsunamis in the past >4500 years. Our research illustrates the complexities of reconstructing a complete stratigraphic record of past tsunamis from a single site for tsunami hazard assessment. The coastal geomorphology near Queule, Chile preserves evidence of the giant Mw 9.51960 Chile earthquake and two buried paleotsunami deposits within the last 6000 years. Using the 1960 tsunami deposits, eye‐witness observations, and numerical simulations of tsunami inundation, we tested the sensitivity of the site to different earthquake slip distributions. We consider the role of coastal geomorphic evolution, sea‐level history, and tsunami magnitude in the preservation of paleotsunami depositional records.

Indian monsoon variability during the past ∼8.5 cal kyr as recorded in the sediments of the northeastern Arabian Sea - Ravichandran, M.; Gupta, Anil K.; Mohan, K.; Tiwari, Sameer K.; Lakshumanan, C.; Panigrahi, M.K. (Quaternary International, 2022)
We analyzed benthic and planktic foraminifera, total organic carbon and stable isotopes ratios of carbon and oxygen from 100 samples of marine sediment Core ABP, 25/03, off Gujarat in the northeastern Arabian Sea. Factor and cluster analyses of thirty highest-ranked benthic foraminifer species enabled to identify seven biofacies in the study sequence characterizing major changes in deep-sea environments during the past ∼8.5 cal kyr. The benthic foraminiferal data has been combined with population abundances of upwelling indicator planktic foraminifer Globigerina bulloides and mixed layer species from Core ABP, 25/03 and compared with that from ODP Hole 723A and Core ABP, 25/02, western and eastern Arabian Sea, respectively. A major change in benthic foraminifera occurs during ∼8.5 to 6 cal kyr BP, when the summer monsoon was stronger whereas during 6 to 2 cal kyr BP, the data suggest a weak summer monsoon. Planktic foraminifer Globigerina bulloides does not show any significant trend in the study core, but deep thermocline species Neogloboquadrina dutertrei and mixed layer species show significant trend with an inverse correlation with the TOC. This core records high TOC from ∼6.5 to 4 cal kyr BP and during the last 2 cal kyr and low TOC during ∼8.5 to 6.5 cal kyr BP and 4 to 2 cal kyr BP. It is interesting to note intervals of high mixed layer species coincide with high Neogloboquadrina dutertrei percentages and low TOC values at Core ABP, 25/03 during 8.5 to 6.5 cal kyr BP.The faunal data is supported by carbon and oxygen isotope ratios (δ13C and δ18O) of shells of benthic foraminifer Cibicides spp. to strengthen our understanding of changes in the eastern Arabian Sea since ∼8.5 cal kyr BP.

In-phase millennial-scale glacier changes in the tropics and North Atlantic regions during the HoloceneAbstract - Jomelli, V.; Swingedouw, D.; Vuille, M.; Favier, V.; Goehring, B.; Shakun, J.; Braucher, R.; Schimmelpfennig, I.; Menviel, L.; Rabatel, A.; Martin, L. C. P.; Blard, P.-H.; et al. (Nature Communications, 2022)
Based on new and published cosmic-ray exposure chronologies, we show that glacier extent in the tropical Andes and the north Atlantic regions (TANAR) varied in-phase on millennial timescales during the Holocene, distinct from other regions. Glaciers experienced an early Holocene maximum extent, followed by a strong mid-Holocene retreat and a re-advance in the late Holocene. We further explore the potential forcing of TANAR glacier variations using transient climate simulations. Since the Atlantic Meridional Overturning Circulation (AMOC) evolution is poorly represented in these transient simulations, we develop a semi-empirical model to estimate the “AMOC-corrected” temperature and precipitation footprint at regional scales. We show that variations in the AMOC strength during the Holocene are consistent with the observed glacier changes. Our findings highlight the need to better constrain past AMOC behavior, as it may be an important driver of TANAR glacier variations during the Holocene, superimposed on other forcing mechanisms.

Late Holocene Paleomagnetic Secular Variation in the Chukchi Sea, Arctic Ocean - West, Gabriel; Nilsson, Andreas; Geels, Alexis; Jakobsson, Martin; Moros, Matthias; Muschitiello, Francesco; Pearce, Christof; Snowball, Ian; O’Regan, Matt (Geochemistry, Geophysics, Geosystems, 2022)
The geomagnetic field behavior in polar regions remains poorly understood and documented. Although a number of Late Holocene paleomagnetic secular variation (PSV) records exist from marginal settings of the Amerasian Basin in the Arctic Ocean, their age control often relies on a handful of radiocarbon dates to constrain ages over the past 4,200 years. Here we present well-dated Late Holocene PSV records from two sediment cores recovered from the Chukchi Sea, Arctic Ocean. The records are dated using 26 14C measurements, with local marine reservoir corrections calibrated using tephra layers from the 3.6 cal ka BP Aniakchak eruption in Northern Alaska. These 14C-based chronologies are extended into the post-bomb era using caesium-137 dating, and mercury isochrons. Paleomagnetic measurements and rock magnetic analyses reveal stable characteristic remanent magnetization directions, and a magnetic mineralogy dominated by low-coercivity minerals. The PSV records conform well to global spherical harmonic field model outputs. Centennial to millennial scale directional features are synchronous between the cores and other Western Arctic records from the area. Due to the robust chronology, these new high-resolution PSV records provide a valuable contribution to the characterization of geomagnetic field behavior in the Arctic over the past few thousand years, and can aid in developing age models for suitable sediments found in this region.

Mangrove Peat Radiocarbon Ages From Snipe and Swan Key, FL - Khan, Nicole S; Toth, Lauren T; Moyer, Ryan P; Shaw, Jaimie E; Capar, Paulina; Kemp, Andrew C; Engelhart, Simon E; Horton, Benjamin P (U.S. Geological Survey, 2022)
In 2016, researchers collected cores of mangrove peat from two islands in the Florida Keys: Snipe Key (24.679°N, 81.653°W) and Swan Key (25.349N, 80.251W) (Fig. 1). This data release contains the radiocarbon ages and associated data for peat samples analyzed throughout the two cores. These data were used by Khan and others (in preparation) to reconstruct the millennial-scale sea level variability of the two locations.
Medium: csv,xlsx Type: dataset
Keywords: core analysis; push coring; Radiometric Dating

Not all permafrost microbiomes are created equal: Influence of permafrost thaw on the soil microbiome in a laboratory incubation study - Barbato, R.A.; Jones, R.M.; Douglas, T.A.; Doherty, S.J.; Messan, K.; Foley, K.L.; Perkins, E.J.; Thurston, A.K.; Garcia-Reyero, N. (Soil Biology and Biochemistry, 2022)
Permafrost is thawing at unprecedented rates, significantly altering landscapes and ecosystem trajectories by changing subsurface conditions, vegetation characteristics, and soil properties. Dormant microbes become active as temperatures rise and permafrost soils warm and thaw. To determine the effects of sample location and warming on the permafrost microbiome, we collected permafrost from five distinct locations within the Cold Regions Research and Engineering Laboratory's Permafrost Tunnel (PT) near Fairbanks, Alaska and warmed them in a laboratory incubation study. Heterotrophic respiration was continuously monitored and metagenomes were analyzed at select incubation temperatures. Under frozen conditions, microbial respiration rates from different PT locations were similar, ranging from 2 to 12 mg C–CO2 kg−1 d−1. During thaw, respiration increased in samples from three PT locations, but remained stable for two locations. Analysis of the shotgun metagenomes showed how the microbial communities and their potential function changed as a function of location and incubation temperature. This indicates a differential response of permafrost microbes based on their origin. These findings have important implications for developing accurate forecasts of microbial community assemblages during thaw in that location should be considered as a strong influencing factor.

Oceanic passage of hurricanes across Cay Sal Bank in The Bahamas over the last 530 years - Winkler, Tyler S.; van Hengstum, Peter J.; Donnelly, Jeffrey P.; Wallace, Elizabeth J.; D'Entremont, Nicole; Hawkes, Andrea D.; Maio, Christopher V.; Sullivan, Richard M.; Woodruff, Jonathan D. (Marine Geology, 2022)
Islands across the Bahamian Archipelago have been devastated by five major hurricanes from 2010 to 2020 CE, including Category 5 Hurricane Dorian in 2019 that inundated parts of Abaco and Grand Bahama with up to 4 m of surge, killing 84 people and leaving >245 others missing. Up to 1 m relative sea-level rise is estimated for The Bahamas by 2100 CE, which could enhance flooding from weaker storms (<Category 3) in low-lying coastal areas. Problematically, Bahamian hurricane activity is highly spatially-heterogenous over the last 170 years, meaning that long-term regional hurricane frequency remains poorly constrained, especially for weaker Category 1–2 events that are less-likely to be detected by most sediment-based paleo-hurricane reconstructions. We present a 530-year record of hurricane passage from Hine's Blue Hole on Cay Sal Bank, The Bahamas. Hine's Hole has an accumulation rate of 2–3.2 cm/yr, making it among the highest-resolution hurricane reconstructions to date. Unlike many paleo-hurricane reconstruction sites, Hine's Hole is not surrounded by coastal landmasses that can dampen currents and waves produced by hurricanes, so it archives most ≥Category 1 hurricanes passing within 115 km during the 170-year instrumental record (1850 CE-present) and may also document intense tropical or winter storms. Hine's Hole archives ~16 intense storms per century from 1850 to 2016 CE, but documents three periods from 1505 to 1530 CE, 1570 to 1620 CE, and ~ 1710 to 1875 CE with over twice as many intense storms per century. These active periods correspond to other high-resolution reconstructions from the Bahamian Archipelago and Florida Keys, but the magnitude of the increase is much higher given that Hine's Hole archives evidence of weaker and more distal storms. As such, this reconstruction provides unprecedented insight into changes in hurricane activity within the pre-industrial climate system and demonstrates that recurrence intervals based on the 170-year instrumental record can severely underestimate the threat hurricanes pose certain localities.

Oceanographic and climatic influences on Trooz Glacier, Antarctica during the Holocene - Totten, Rebecca L.; Fonseca, Adlai Nathanael Reuel; Wellner, Julia Smith; Munoz, Yuribia P.; Anderson, John B.; Tobin, Thomas S.; Lehrmann, Asmara A. (Quaternary Science Reviews, 2022)
To evaluate the significance of recent widespread glacial recession in the Antarctic Peninsula, it is imperative to extend the limited instrumented record of glacier change with long sedimentary archives of the Holocene. Reconstructing glacial histories that capture the variability of environments in the Antarctic Peninsula will enable better constraint of ocean and climate forcings on regional glacial stability. Two sediment cores are analyzed from the 2007 RV/IB N.B. Palmer cruise to Collins Bay, the embayment immediately offshore Trooz Glacier on the Graham Land coast, and provide an archive to test controls on long-term stability of outlet glaciers in an open bay setting. Radiocarbon and Lead-210 (a short-lived radioisotope) age-depth models provide a timeline for Trooz Glacier behavior and associated oceanographic changes over the last 10,000 years. Magnetic susceptibility, grain size, diatom assemblage, total organic carbon, nitrogen, and stable isotopes of organic carbon are utilized as proxies for changing glacial and ocean conditions. Outer Collins Bay deglaciated by ∼10000 cal yr B.P. Diatom abundance and organic content signal productivity increase during further glacial recession from ∼8900 to 6100 cal yr B.P., which coincided with upwelling of relatively warm Circumpolar Deep Water into the bay. High productivity, characterized by Thalassiosira antarctica-dominated diatom assemblages with prominence of Fragilariopsis kerguelensis, indicate open marine conditions with incursion of offshore currents into the bay from ∼6100 to 760 cal yr B.P. A sharp decrease in organic content, diatom abundance, and grain size indicate more sea ice and ice-tongue/ice-canopy advance from ∼760 to 240 cal yr B.P., when the floating ice canopy in outer Collins Bay retreated to near its present-day position and productivity increased. During the period of the 1950's to 1990's, Trooz Glacier was one of only two Antarctic Peninsula glaciers that advanced slightly. Over the Holocene, oceanographic forcing dominated the long-term stability of Trooz Glacier due to its open aspect, and it is unknown how Trooz Glacier will respond to continued influence of Circumpolar Deep Water in the future. Understanding ocean forcings on glacial stability, together with other local controls like drainage basin configuration and bay geometry, should help contextualize the modern retreat and improve prediction of glacial response to prevalent Circumpolar Deep Water circulation in this dynamic region.

Optimization of the LLNL/CAMS gas-accepting ion source and 1 MV compact AMS for natural abundance radiocarbon analysis of CO2 - Broek, Taylor A. B.; Moreland, Kimber C.; Ognibene, Ted J.; McFarlane, Karis J.; Brown, Thomas A. (Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms, 2022)
The Lawrence Livermore National Laboratory – Center for Accelerator Mass Spectrometry (LLNL/CAMS) 1 MV AMS system was converted from a biomedical AMS instrument to a natural abundance 14C spectrometer. The system is equipped with a gas-accepting hybrid ion source capable of measuring both solid (graphite) and gaseous (CO2) samples. Here we describe a series of experiments intended to establish and optimize 14CO2 measurement capabilities at natural abundance levels. A maximum instantaneous ionization efficiency of 8 % was achieved with 3 % CO2 in helium at a flow rate of approximately 220 µL/min (3.5 µg C/min). For modern materials (e.g., OX I) we measured an average of 240 ± 50 14C counts/µg C, equivalent to a total system efficiency of approximately 3 %. Experimental CO2 samples with F14C values ranging from 0.20 to 1.05 measured as both graphite and directly as CO2 gas produced equivalent values with an average offset of < 2σ.
Keywords: Accelerator mass spectrometry; CO; Gas-accepting ion source; radiocarbon

Over a third of groundwater in USA public-supply aquifers is Anthropocene-age and susceptible to surface contamination - Jurgens, Bryant C.; Faulkner, Kirsten; McMahon, Peter B.; Hunt, Andrew G.; Casile, Gerolamo; Young, Megan B.; Belitz, Kenneth (Communications Earth & Environment, 2022)
The distribution of groundwater age is useful for evaluating the susceptibility and sustainability of groundwater resources. Here, we compute the aquifer-scale cumulative distribution function to characterize the age distribution for 21 Principal Aquifers that account for ~80% of public-supply pumping in the United States. The aquifer-scale cumulative distribution function for each Principal Aquifer was derived from an ensemble of modeled age distributions (~60 samples per aquifer) based on multiple tracers: tritium, tritiogenic helium-3, sulfur hexafluoride, chlorofluorocarbons, carbon-14, and radiogenic helium-4. Nationally, the groundwater is 38% Anthropocene (since 1953), 34% Holocene (75 – 11,800 years ago), and 28% Pleistocene (>11,800 years ago). The Anthropocene fraction ranges from <5 to 100%, indicating a wide range in susceptibility to land-surface contamination. The Pleistocene fraction of groundwater exceeds 50% in 7 eastern aquifers that are predominately confined. The Holocene fraction of groundwater exceeds 50% in 5 western aquifers that are predominately unconfined. The sustainability of pumping from these Principal Aquifers depends on rates of recharge and release of groundwater stored in fine-grained layers.
Keywords: Environmental impact; hydrology; Sustainability

Radiocarbon measurement of CO2 from carbonate minerals using a hybrid gas ion source with an open split interface - Longworth, Brett E.; Burton, Joshua R.; Pendleton, Simon L.; Moser, Sydney D.; Roberts, Mark L.; Kurz, Mark D. (Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms, 2022)
We have developed a method for measuring radiocarbon in carbonate minerals as CO2 gas via a NEC MCSNICS hybrid sputter gas ion source (HGIS). The method uses helium as a carrier gas to displace CO2 from sample vials to an open split, where a glass capillary samples the mixture for delivery directly to the HGIS. This method skips the gas transfer and quantification steps used in a closed inlet HGIS system, simplifying sample measurement. Samples larger than 8 mg carbonate can be measured. Results from measurements of consensus standards (TIRI I, IAEA C2, and an internal modern shell standard), and samples from a marine core (F14C = 0.4–1.15) show that the method agrees well with traditional AMS measurement of the same samples as graphite, and that the 1σ uncertainty is about 1%. We discuss advantages and disadvantages of continuous flow sample introduction, and the effect of reduced precision on calibrated age-depth models produced using gas-source data.
Keywords: Carbonate; Hybrid gas ion source; radiocarbon

Rapid Degradation of Cellulose Diacetate by Marine MicrobesRapid Degradation of Cellulose Diacetate by Marine Microbes - Mazzotta, Michael G.; Reddy, Christopher M.; Ward, Collin P. (Environmental Science & Technology Letters, 2022)
The persistence of cellulose diacetate (CDA), a biobased plastic used in textiles and single-use consumer products, in the ocean is currently unknown. Here, we probe the disintegration and degradation of CDA-based materials (25 mu m films, 510 mu m foam, and 97 g/m2 fabric) by marine microbes in a continuous flow seawater mesocosm. Photographic evidence and mass loss measurements demonstrate that CDA-based materials disintegrate in months. Disintegration is marked by the increasing esterase and cellulase activity of the biofilm community, suggesting that marine microbes degrade CDA. The natural abundance stable (13C) and radiocarbon (14C) isotopic signature of carbon dioxide respired during short-term bottle incubations confirms the rapid degradation of both acetyl and cellulosic components of CDA by seawater microbial communities. These findings challenge the paradigm set by governmental agencies and advocacy groups that CDA-based materials persist in the ocean for decades, and represent a positive step toward identifying highutility, biobased plastics with low environmental persistence.
Keywords: ACETATE; BIODEGRADATION

Reconciling the apparent absence of a Last Glacial Maximum alpine glacial advance, Yukon Territory, Canada, through cosmogenic beryllium-10 and carbon-14 measurements - Goehring, Brent M.; Menounos, Brian; Osborn, Gerald; Hawkins, Adam; Ward, Brent (Geochronology, 2022)
We present a new in situ produced cosmogenic beryllium-10 and carbon-14 nuclide chronology from two sets (outer and inner) of alpine glacier moraines from the Grey Hunter massif of southern Yukon Territory, Canada. The chronology of moraines deposited by alpine glaciers outside the limits of the Last Glacial Maximum (LGM) ice sheets potentially provides a less-ambiguous archive of mass balance, and hence climate, than can be inferred from the extents of ice sheets themselves. Results for both nuclides are inconclusive for the outer moraines, with evidence for pre-LGM deposition (beryllium-10) and Holocene deposition (carbon-14). Beryllium-10 results from the inner moraine are suggestive of canonical LGM deposition but with relatively high scatter. Conversely, in situ carbon-14 results from the inner moraines are tightly clustered and suggestive of terminal Younger Dryas deposition. We explore plausible scenarios leading to the observed differences between nuclides and find that the most parsimonious explanation for the outer moraines is that of pre-LGM deposition, but many of the sampled boulder surfaces were not exhumed from within the moraine until the Holocene. Our results thus imply that the inner and outer moraines sampled pre- and post-date the canonical LGM and that moraines dating to the LGM are lacking likely due to overriding by the subsequent Late Glacial/earliest Holocene advance.

Relative sea-level change in South Florida during the past ~5000 years - Khan, Nicole S.; Ashe, Erica; Moyer, Ryan P.; Kemp, Andrew C.; Engelhart, Simon E.; Brain, Matthew J.; Toth, Lauren T.; Chappel, Amanda; Christie, Margaret; Kopp, Robert E.; Horton, Benjamin P. (Global and Planetary Change, 2022)
A paucity of detailed relative sea-level (RSL) reconstructions from low latitudes hinders efforts to understand the global, regional, and local processes that cause RSL change. We reconstruct RSL change during the past ~5 ka using cores of mangrove peat at two sites (Snipe Key and Swan Key) in the Florida Keys. Remote sensing and field surveys established the relationship between peat-forming mangroves and tidal elevation in South Florida. Core chronologies are developed from age-depth models applied to 72 radiocarbon dates (39 mangrove wood macrofossils and 33 fine-fraction bulk peat). RSL rose 3.7 m at Snipe Key and 5.0 m at Swan Key in the past 5 ka, with both sites recording the fastest century-scale rate of RSL rise since ~1900 CE (~2.1 mm/a). We demonstrate that it is feasible to produce near-continuous reconstructions of RSL from mangrove peat in regions with a microtidal regime and accommodation space created by millennial-scale RSL rise. Decomposition of RSL trends from a network of reconstructions across South Florida using a spatio-temporal model suggests that Snipe Key was representative of regional RSL trends, but Swan Key was influenced by an additional local-scale process acting over at least the past five millennia. Geotechnical analysis of modern and buried mangrove peat indicates that sediment compaction is not the local-scale process responsible for the exaggerated RSL rise at Swan Key. The substantial difference in RSL between two nearby sites highlights the critical need for within-region replication of RSL reconstructions to avoid misattribution of sea-level trends, which could also have implications for geophysical modeling studies using RSL data for model tuning and validation.
Keywords: Holocene; mangrove; Proxy reconstruction; Reproducibility; sea level

Sediment Accumulation and Carbon Burial in Four Hadal Trench Systems - Oguri, Kazumasa; Masqué, Pere; Zabel, Matthias; Stewart, Heather A.; MacKinnon, Gillian; Rowden, Ashley A.; Berg, Peter; Wenzhöfer, Frank; Glud, Ronnie N. (Journal of Geophysical Research: Biogeosciences, 2022)
Hadal trenches are considered to act as depocenters for organic material, although pathways for the material transport and deposition rates are poorly constrained. Here we assess focusing, deposition and accumulation of material and organic carbon in four hadal trench systems underlying different surface ocean productivities; the eutrophic Atacama and Kuril-Kamchatka trenches, the mesotrophic Kermadec trench and the oligotrophic Mariana Trench. The study is based on the distributions of naturally occurring 210Pbex, 137Cs and total organic carbon from recovered sediment cores and by applying previously quantified benthic mineralization rates. Periods of steady deposition and discreet mass-wasting deposits were identified from the profiles and the latter were associated with historic recorded seismic events in the respective regions. During periods without mass wasting, the estimated focusing factors along trench axes were elevated, suggesting more or less continuous downslope focusing of material towards the interior of the trenches. The estimated organic carbon deposition rates during these periods exhibited extensive site-specific variability, but were generally similar to values encountered at much shallower settings such as continental slopes and margins. Organic carbon deposition rates during periods of steady deposition were not mirrored by surface ocean productivity, but appeared confounded by local bathymetry. The inclusion of deposition mediated by mass-wasting events enhanced the sediment and organic carbon accumulations for the past ∼150 years by up to a factor of ∼4. Thus, due to intensified downslope material focusing and infrequent mass-wasting events, hadal trenches are important sites for deposition and sequestration of organic carbon in the deep sea.
e2022JG006814 2022JG006814
Keywords: focusing factor; Hadal trench; mass accumulation rate; mass-wasting event; organic carbon deposition rate; radionuclides

Sediment organic matter compositional changes in a tropical rift lake as a function of water depth and distance from shore - Kruger, Brittany R.; Werne, Josef P.; Minor, Elizabeth C. (Organic Geochemistry, 2022)
Little is known of modern carbon cycling in East African rift lakes. These large tropical systems with anoxic bottom waters can act as test cases for carbon cycling under future climate change scenarios as well as key sediment repositories for paleolimnology studies and fossil fuel generation. This study is the first to combine stable and radiocarbon isotopic information on bulk sediment and biomarkers (n-alcohols) in an African rift lake by investigating surface sediments collected on a nearshore to offshore transect in northern Lake Malawi. This study is also the first to report radiocarbon content in water column particulate organic, dissolved organic and inorganic carbon from an African rift lake. General surface-sediment trends with increasing water depth were an increase in %TOC, and decreases in grain size, δ13C and C/N. Carbon radioisotope analyses showed that bulk sedimentary organic matter was modern across the transect. Biomarker data indicated a primarily aquatic origin for sedimentary organic matter at offshore sites; terrestrial material dominated the n-alcohol signature closest to the shore. Protokerogen stable isotope signatures were similar, and radiocarbon was somewhat depleted relative to bulk sediment organic matter. As compared to bulk organic matter, lipids were 13C-depleted throughout the sampling transect and 14C-depleted at the most nearshore location. This indicates an aged lipid carbon source and likely significant diagenetic alteration of modern sources prior to deposition in nearshore sediments, perhaps a combination of soil erosion, in-river processing, sediment resuspension and mobilization, and preferential degradation of younger organic matter in the oxic nearshore region.
Keywords: -Alcohols; C/N ratio; carbon isotopes; Lake Malawi; Protokerogen; radiocarbon; Sedimentary organic carbon

Synergy between Sunlight, Titanium Dioxide, and Microbes Enhances Cellulose Diacetate Degradation in the Ocean - Walsh, Anna N.; Mazzotta, Michael G.; Nelson, Taylor F.; Reddy, Christopher M.; Ward, Collin P. (Environmental Science & Technology, 2022)
Sunlight chemically transforms marine plastics into a suite of products, with formulation─the specific mixture of polymers and additives─driving rates and products. However, the effect of light-driven transformations on subsequent microbial lability is poorly understood. Here, we examined the interplay between photochemical and biological degradation of fabrics made from cellulose diacetate (CDA), a biobased polymer used commonly in consumer products. We also examined the influence of ∼1% titanium dioxide (TiO2), a common pigment and photocatalyst. We sequentially exposed CDA to simulated sunlight and native marine microbes to understand how photodegradation influences metabolic rates and pathways. Nuclear magnetic resonance spectroscopy revealed that sunlight initiated chain scission reactions, reducing CDA’s average molecular weight. Natural abundance carbon isotope measurements demonstrated that chain scission ultimately yields CO2, a newly identified abiotic loss term of CDA in the environment. Measurements of fabric mass loss and enzymatic activities in seawater implied that photodegradation enhanced biodegradation by performing steps typically facilitated by cellulase. TiO2 accelerated CDA photodegradation, expediting biodegradation. Collectively, these findings (i) underline the importance of formulation in plastic’s environmental fate and (ii) suggest that overlooking synergy between photochemical and biological degradation may lead to overestimates of marine plastic persistence.
Publisher: American Chemical Society

Use of δ18Oatm in dating a Tibetan ice core record of Holocene/Late Glacial climate - Thompson, Lonnie G.; Severinghaus, Jeffrey P.; Yao, Tandong; Davis, Mary E.; Mosley-Thompson, Ellen; Beaudon, Emilie; Sierra-Hernández, M. Roxana; Porter, Stacy E. (Proceedings of the National Academy of Sciences, 2022)
Ice cores from the northwestern Tibetan Plateau (NWTP) contain long records of regional climate variability, but refrozen meltwater and dust in these cores has hampered development of robust timescales. Here, we introduce an approach to dating the ice via the isotopic composition of atmospheric O2 in air bubbles (δ18Oatm), along with annual layer counting and radiocarbon dating. We provide a robust chronology for water isotope records (δ18Oice and d-excess) from three ice cores from the Guliya ice cap in the NWTP. The measurement of δ18Oatm, although common in polar ice core timescales, has rarely been used on ice cores from low-latitude, high-altitude glaciers due to (1) low air pressure, (2) the common presence of refrozen melt that adds dissolved gases and reduces the amount of air available for analysis, and (3) the respiratory consumption of molecular oxygen (O2) by micro-organisms in the ice, which fractionates the δ18O of O2 from the atmospheric value. Here, we make corrections for melt and respiration to address these complications. The resulting records of water isotopes from the Guliya ice cores reveal climatic variations over the last 15,000 y, the timings of which correspond to those observed in independently dated lake and speleothem records and confirm that the Guliya ice cap existed before the Holocene. The millennial-scale drivers of δ18Oice are complex and temporally variable; however, Guliya δ18Oice values since the mid-20th century are the highest since the beginning of the Holocene and have increased with regional air temperature.
Publisher: Proceedings of the National Academy of Sciences

Younger Dryas and early Holocene climate in south Greenland inferred from oxygen isotopes of chironomids, aquatic Moss, and Moss cellulose - Puleo, Peter J. K.; Masterson, Andrew L.; Medeiros, Andrew S.; Schellinger, Grace; Steigleder, Regan; Woodroffe, Sarah; Osburn, Magdalena R.; Axford, Yarrow (Quaternary Science Reviews, 2022)
Ice core records have long indicated that the Younger Dryas began and ended with large, abrupt climate shifts over Greenland. Key climatic features remain unknown, including the magnitude of warming during the Younger Dryas-Holocene transition along with the seasonality and spatial variability of Younger Dryas climate changes across Greenland. Here, we use geochemical and paleoecological proxies from lake sediments at Lake N14 in south Greenland to address these outstanding questions. Radiocarbon dating and diatom assemblages confirm early deglaciation and isolation of Lake N14 before ∼13,600 cal yr BP, consistent with previous work. Oxygen isotope ratios (δ18O) of chironomid head capsules, bulk aquatic moss, and aquatic moss-derived cellulose are used to reconstruct oxygen isotopes of past lake water and annual precipitation. Oxygen isotope proxies indicate annual precipitation δ18O values increased by 5.9–7.7‰ at the end of the Younger Dryas. Following the Younger Dryas, moss and cellulose δ18O values show a clear decline in precipitation δ18O values of 2–3‰ from ∼11,540–11,340 cal yr BP that may correspond with the Preboreal Oscillation. Reconstructed precipitation δ18O values then gradually increased from 11,300–10,100 cal yr BP. All three aquatic organic materials register similar shifts in precipitation δ18O values over time, and they closely parallel the δ18O shifts observed in ice cores. This evidence strongly supports the utility of these methods for reconstructing lake water δ18O, and furthermore precipitation δ18O values where lake water reflects precipitation. The relatively large shift in isotopic composition of precipitation at Lake N14 suggests that shifts in temperature, precipitation seasonality, and/or moisture sources at the end of the Younger Dryas were even larger in south Greenland than they were in central Greenland, most likely because of the proximity to major changes in North Atlantic Ocean circulation. The annual air temperature change estimated at Lake N14 at the end of the Younger Dryas is also very large (∼18 ± 7 °C) compared to the summer warming previously inferred from chironomid species assemblages there (∼6 °C). This indicates that the strongest warming at the end of the Younger Dryas occurred in the winter season, consistent with past observations of intensified Younger Dryas seasonality at Lake N14 and elsewhere in Greenland.
Keywords: Chironomids; Deglaciation; diatoms; Greenland; Holocene; Micropaleontology; paleoclimatology; paleolimnology; Stable isotopes; Younger Dryas

Climate control on terrestrial biospheric carbon turnover - Eglinton, Timothy I.; Galy, Valier V.; Hemingway, Jordon D.; Feng, Xiaojuan; Bao, Hongyan; Blattmann, Thomas M.; Dickens, Angela F.; Gies, Hannah; Giosan, Liviu; Haghipour, Negar; Hou, Pengfei; Lupker, Maarten; et al. (Proceedings of the National Academy of Sciences, 2021)
Terrestrial vegetation and soils hold three times more carbon than the atmosphere. Much debate concerns how anthropogenic activity will perturb these surface reservoirs, potentially exacerbating ongoing changes to the climate system. Uncertainties specifically persist in extrapolating point-source observations to ecosystem-scale budgets and fluxes, which require consideration of vertical and lateral processes on multiple temporal and spatial scales. To explore controls on organic carbon (OC) turnover at the river basin scale, we present radiocarbon (C-14) ages on two groups of molecular tracers of plant-derived carbon-leaf-wax lipids and lignin phenols-from a globally distributed suite of rivers. We find significant negative relationships between the C-14 age of these biomarkers and mean annual temperature and precipitation. Moreover, riverine biospheric-carbon ages scale proportionally with basin-wide soil carbon turnover times and soil C-14 ages, implicating OC cycling within soils as a primary control on exported biomarker ages and revealing a broad distribution of soil OC reactivities. The ubiquitous occurrence of a long-lived soil OC pool suggests soil OC is globally vulnerable to perturbations by future temperature and precipitation increase. Scaling of riverine biospheric-carbon ages with soil OC turnover shows the former can constrain the sensitivity of carbon dynamics to environmental controls on broad spatial scales. Extracting this information from fluvially dominated sedimentary sequences may inform past variations in soil OC turnover in response to anthropogenic and/or climate perturbations. In turn, monitoring riverine OC composition may help detect future climate-change-induced perturbations of soil OC turnover and stocks.
Keywords: Carbon cycle; carbon turnover times; fluvial carbon; plant biomarkers; radiocarbon

Enhanced iceberg discharge in the western North Atlantic during all Heinrich events of the last glaciation - Zhou, Yuxin; McManus, Jerry F.; Jacobel, Allison W.; Costa, Kassandra M.; Wang, Shouyi; Alvarez Caraveo, Blanca (Earth and Planetary Science Letters, 2021)
A series of catastrophic iceberg and meltwater discharges to the North Atlantic, termed Heinrich events, punctuated the last ice age. During Heinrich events, coarse terrigenous debris released from the drifting icebergs was preserved in deep-sea sediments, serving as an indicator of iceberg passage. Quantifying the vertical flux of ice-rafted debris (IRD) in open-ocean settings can resolve questions regarding the timing and spatial variation in ice sheet calving intensity. In this study, 230Thxs-based IRD flux throughout the last glacial period was measured in a deep-sea sediment core from the western North Atlantic, and complemented by data spanning 0-32 ka from a sediment core in the Labrador Sea. The cores were recovered from sites downstream from Hudson Strait, a likely conduit for icebergs calving from the Laurentide ice sheet (LIS). We compare our results with equivalent existing data from the eastern North Atlantic and show that the two cores in our study have higher IRD fluxes during all Heinrich events, notably including events H3 (∼31 ka) and H6 (∼60 ka). This study demonstrates that the LIS played a role in all Heinrich events, and raises the likelihood that a single mechanism can account for the genesis of these events.
Keywords: Heinrich event; IRD flux; thorium normalization; western north atlantic

Event-dominated transport, provenance, and burial of organic carbon in the Japan Trench - Schwestermann, T.; Eglinton, T.I.; Haghipour, N.; McNichol, A.P.; Ikehara, K.; Strasser, M. (Earth and Planetary Science Letters, 2021)
The delivery of organic carbon (OC) to the ocean's deepest trenches in the hadal zone is poorly understood, but may be important for the carbon cycle, contain crucial information on sediment provenance and event-related transport processes, and provide age constraints on stratigraphic sequences in this terminal sink. In this study, we systematically characterize bulk organic matter (OM) and OC signatures (TOC/TN, delta C-13, C-14), as well as those from application of serial thermal oxidation (ramped pyrolysis/oxidation) of sediment cores recovered along an entire hadal trench encompassing high stratigraphic resolution records spanning nearly 2000 years of deposition. We analyze two cores from the southern and northern Japan Trench, where submarine canyon systems link shelf with trench. We compare results with previously published data from the central Japan Trench, where canyon systems are absent. Our analyses enable refined dating of the stratigraphic record and indicate that event deposits arise from remobilization of relatively surficial sediment coupled with deeper erosion along turbidity current pathways in the southern and central study site and from canyon flushing events in the northern study site. Furthermore, our findings indicate deposition of predominantly marine OC within hemipelagic background sediment as well as associated with event deposits along the entire trench axis. This implies that canyon systems flanking the Japan Trench do not serve as a short-circuit for injection of terrestrial OC to the hadal zone, and that tropical cyclones are not major agents for sediment and carbon transfer into this trench system. These findings further support previous Japan Trench studies interpreting that event deposits originate from the landward trench slope and are earthquake-triggered. The very low terrestrial OC input into the Japan Trench can be explained by the significant distance between trench and hinterland (>180 km), and the physiography of the canyons that do not connect to coast and river systems. We suggest that detailed analyzes of long sedimentary records are essential to understand OC transfer, deposition and burial in hadal trenches. (C) 2021 The Author(s). Published by Elsevier B.V.
Keywords: carbon isotopes; carbon provenance; carbon transfer; hadal zone event-stratigraphy; Japan Trench; ramped Pyr/Ox

Evidence of humans in North America during the Last Glacial Maximum - Bennett, Matthew R.; Bustos, David; Pigati, Jeffrey S.; Springer, Kathleen B.; Urban, Thomas M.; Holliday, Vance T.; Reynolds, Sally C.; Budka, Marcin; Honke, Jeffrey S.; Hudson, Adam M.; Fenerty, Brendan; Connelly, Clare; et al. (Science, 2021)
Archaeologists and researchers in allied fields have long sought to understand human colonization of North America. Questions remain about when and how people migrated, where they originated, and how their arrival affected the established fauna and landscape. Here, we present evidence from excavated surfaces in White Sands National Park (New Mexico, United States), where multiple in situ human footprints are stratigraphically constrained and bracketed by seed layers that yield calibrated radiocarbon ages between ~23 and 21 thousand years ago. These findings confirm the presence of humans in North America during the Last Glacial Maximum, adding evidence to the antiquity of human colonization of the Americas and providing a temporal range extension for the coexistence of early inhabitants and Pleistocene megafauna.
Publisher: American Association for the Advancement of Science

Lacustrine leaf wax hydrogen isotopes indicate strong regional climate feedbacks in Beringia since the last ice age - Daniels, W.C.; Russell, J.M.; Morrill, C.; Longo, W.M.; Giblin, A.E.; Holland-Stergar, P.; Welker, J.M.; Wen, X.; Hu, A.; Huang, Y. (Quaternary Science Reviews, 2021)

A maximum rupture model for the central and southern Cascadia subduction zone—reassessing ages for coastal evidence of megathrust earthquakes and tsunamis - Nelson, Alan R.; DuRoss, Christopher B.; Witter, Robert C.; Kelsey, Harvey M.; Engelhart, Simon E.; Mahan, Shannon A.; Gray, Harrison J.; Hawkes, Andrea D.; Horton, Benjamin P.; Padgett, Jason S. (Quaternary Science Reviews, 2021)
A new history of great earthquakes (and their tsunamis) for the central and southern Cascadia subduction zone shows more frequent (17 in the past 6700 yr) megathrust ruptures than previous coastal chronologies. The history is based on along-strike correlations of Bayesian age models derived from evaluation of 554 radiocarbon ages that date earthquake evidence at 14 coastal sites. We reconstruct a history that accounts for all dated stratigraphic evidence with the fewest possible ruptures by evaluating the sequence of age models for earthquake or tsunami contacts at each site, comparing the degree of temporal overlap of correlated site age models, considering evidence for closely spaced earthquakes at four sites, and hypothesizing only maximum-length megathrust ruptures. For the past 6700 yr, recurrence for all earthquakes is 370e420 yr. But correlations suggest that ruptures at-1.5 ka and-1.1 ka were of limited extent (<400 km). If so, post-3-ka recurrence for ruptures extending throughout central and southern Cascadia is 510e540 yr. But the range in the times between earthquakes is large: two instances may be-50 yr, whereas the longest are-550 and-850 yr. The closely spaced ruptures about 1.6 ka may illustrate a pattern common at subduction zones of a long gap ending with a great earthquake rupturing much of the subduction zone, shortly followed by a rupture of more limited extent. The ruptures of limited extent support the continued inclusion of magnitude-8 earthquakes, with longer ruptures near magnitude 9, in assessments of seismic hazard in the region.

Molluscan aminostratigraphy of the US Mid-Atlantic Quaternary coastal system: Implications for onshore-offshore correlation, paleochannel and barrier island evolution, and local late Quaternary sea-level history - Wehmiller, John F.; Brothers, Laura L.; Ramsey, Kelvin W.; Foster, David S.; Mattheus, C.R.; Hein, Christopher J.; Shawler, Justin L. (Quaternary Geochronology, 2021)
The Quaternary record of the US Mid-Atlantic coastal system includes onshore emergent late Pleistocene shoreline deposits, offshore inner shelf and barrier island units, and paleovalleys formed during multiple glacial stage sea-level lowstands. The geochronology of this coastal system is based on uranium series, radiocarbon, amino acid racemization (AAR), and optically stimulated luminescence (OSL) methods. We report over 600 mollusk AAR results from 93 sites between northeastern North Carolina and the central New Jersey shelf, representing samples from both onshore cores or outcrops, sub-barrier and offshore cores, and transported shells from barrier island beaches. AAR age estimates are constrained by paired C-14 analyses on specific shells and associated U-series coral ages from onshore sites. AAR data from offshore cores are interpreted in the context of detailed seismic stratigraphy. The distribution of Pleistocene-age shells on the island beaches is linked to the distribution of inner shelf or sub-barrier source units. Age mixing over a range of time-scales (similar to 1 ka to similar to 100 ka) is identified by AAR results from onshore, beach, and shelf collections, often contributing insights into the processes forming individual barrier islands. The regional aminostratigraphic framework identifies a widespread late Pleistocene (Marine Isotope Stage 5) aminozone, with isolated records of middle and early Pleistocene deposition. AAR results provide age estimates for the timing of formation of the three major paleochannels that underlie the Delmarva Peninsula: Persimmon Point paleochannel >= 800 ka; Exmore paleochannel similar to 400-500 ka (MIS 12); and Eastville paleochannel > 125 ka (MIS 6). The results demonstrate the value of synthesizing abundant AAR chronologic data across various coastal environments, integrating multiple distinct geologic studies. The ages and elevations of the Quaternary units are important for current hypotheses about relative sea level history and crustal dynamics in the region, which was likely influenced by the Laurentide ice sheet, the margin just similar to 400 km to the north.

Permafrost Organic Carbon Turnover and Export Into a High‐Arctic Fjord: A Case Study From Svalbard Using Compound‐specific C-14 Analysis - Kusch, Stephanie; Rethemeyer, Janet; Ransby, Daniela; Mollenhauer, Gesine (Journal of Geophysical Research: Biogeosciences, 2021)

Planktic foraminiferal changes in the western Mediterranean Anthropocene - Pallacks, Sven; Ziveri, Patrizia; Martrat, Belén; Mortyn, P. Graham; Grelaud, Michael; Schiebel, Ralf; Incarbona, Alessandro; Garcia-Orellana, Jordi; Anglada-Ortiz, Griselda (Global and Planetary Change, 2021)

Plastic Formulation is an Emerging Control of Its Photochemical Fate in the Ocean - Walsh, Anna N.; Reddy, Christopher M.; Niles, Sydney F.; McKenna, Amy M.; Hansel, Colleen M.; Ward, Collin P. (Environmental Science & Technology, 2021)
Sunlight exposure is a control of long-term plastic fate in the environment that converts plastic into oxygenated products spanning the polymer, dissolved, and gas phases. However, our understanding of how plastic formulation influences the amount and composition of these photoproducts remains incomplete. Here, we characterized the initial formulations and resulting dissolved photoproducts of four single-use consumer polyethylene (PE) bags from major retailers and one pure PE film. Consumer PE bags contained 15–36% inorganic additives, primarily calcium carbonate (13–34%) and titanium dioxide (TiO2; 1–2%). Sunlight exposure consistently increased production of dissolved organic carbon (DOC) relative to leaching in the dark (3- to 80-fold). All consumer PE bags produced more DOC during sunlight exposure than the pure PE (1.2- to 2.0-fold). The DOC leached after sunlight exposure increasingly reflected the 13C and 14C isotopic composition of the plastic. Ultrahigh resolution Fourier transform ion cyclotron resonance mass spectrometry revealed that sunlight exposure substantially increased the number of DOC formulas detected (1.1- to 50-fold). TiO2-containing bags photochemically degraded into the most compositionally similar DOC, with 68–94% of photoproduced formulas in common with at least one other TiO2-containing bag. Conversely, only 28% of photoproduced formulas from the pure PE were detected in photoproduced DOC from the consumer PE. Overall, these findings suggest that plastic formulation, especially TiO2, plays a determining role in the amount and composition of DOC generated by sunlight. Consequently, studies on pure, unweathered polymers may not accurately represent the fates and impacts of the plastics entering the ocean.

RADIOCARBON IN DISSOLVED ORGANIC CARBON BY UV OXIDATION: PROCEDURES AND BLANK CHARACTERIZATION AT NOSAMSABSTRACT - Xu, Li; Roberts, Mark L; Elder, Kathryn L; Kurz, Mark D; McNichol, Ann P; Reddy, Christopher M; Ward, Collin P; Hanke, Ulrich M (Radiocarbon, 2021)
This study describes a procedural blank assessment of the ultraviolet photochemical oxidation (UV oxidation) method that is used to measure carbon isotopes of dissolved organic carbon (DOC) at the National Ocean Sciences Accelerator Mass Spectrometry Facility (NOSAMS). A retrospective compilation of Fm and δ 13 C results for secondary standards (OX-II, glycine) between 2009 and 2018 indicated that a revised blank correction was required to bring results in line with accepted values. The application of a best-fit mass-balance correction yielded a procedural blank of 22.0 ± 6.0 μg C with Fm of 0.30 ± 0.20 and δ 13 C of-32.0 ± 3.0‰ for this period, which was notably higher and more variable than previously reported. Changes to the procedure, specifically elimination of higher organic carbon reagents and improved sample and reactor handling, reduced the blank to 11.0 ± 2.75 μg C, with Fm of 0.14 ± 0.10 and δ 13 C of-31.0 ± 5.5‰. A thorough determination of the entire sample processing blank is required to ensure accurate isotopic compositions of seawater DOC using the UV oxidation method. Additional efforts are needed to further reduce the procedural blank so that smaller DOC samples can be analyzed, and to increase sample throughput.
Keywords: blank; dissolved organic carbon; radiocarbon; UV oxidation

Soil Organic Carbon Development and Turnover in Natural and Disturbed Salt Marsh Environments - Luk, Sheron Y.; Todd‐Brown, Katherine; Eagle, Meagan; McNichol, Ann P.; Sanderman, Jonathan; Gosselin, Kelsey; Spivak, Amanda C. (Geophysical Research Letters, 2021)
Salt marsh survival with sea-level rise (SLR) increasingly relies on soil organic carbon (SOC) accumulation and preservation. Using a novel combination of geochemical approaches, we characterized fine SOC (≤1 mm) supporting marsh elevation maintenance. Overlaying thermal reactivity, source (δ13C), and age (F14C) information demonstrates several processes contributing to soil development: marsh grass production, redeposition of eroded material, and microbial reworking. Redeposition of old carbon, likely from creekbanks, represented ∼9%–17% of shallow SOC (≤26 cm). Soils stored marsh grass-derived compounds with a range of reactivities that were reworked over centuries-to-millennia. Decomposition decreases SOC thermal reactivity throughout the soil column while the decades-long disturbance of ponding accelerated this shift in surface horizons. Empirically derived estimates of SOC turnover based on geochemical composition spanned a wide range (640–9,951 years) and have the potential to inform predictions of marsh ecosystem evolution.

Aquifer-Scale Observations of Iron Redox Transformations in Arsenic-Impacted Environments to Predict Future Contamination - Nghiem, Athena A.; Shen, Yating; Stahl, Mason; Sun, Jing; Haque, Ezazul; DeYoung, Beck; Nguyen, Khue N.; Thi Mai, Tran; Trang, Pham Thi Kim; Pham, Hung Viet; Mailloux, Brian; Harvey, Charles F.; et al. (Environmental Science & Technology Letters, 2020)
Iron oxides control the mobility of a host of contaminants in aquifer systems, and the microbial reduction of iron oxides in the subsurface is linked to high levels of arsenic in groundwater that affects greater than 150 million people globally. Paired observations of groundwater and solid-phase aquifer composition are critical to understand spatial and temporal trends in contamination and effectively manage changing water resources, yet field-representative mineralogical data are sparse across redox gradients relevant to arsenic contamination. We characterize iron mineralogy using X-ray absorption spectroscopy across a natural gradient of groundwater arsenic contamination in Vietnam. Hierarchical cluster analysis classifies sediments into meaningful groups delineating weathering and redox changes, diagnostic of depositional history, in this first direct characterization of redox transformations in the field. Notably, these groupings reveal a signature of iron minerals undergoing active reduction before the onset of arsenic contamination in groundwater. Pleistocene sediments undergoing postdepositional reduction may be more extensive than previously recognized due to previous misclassification. By upscaling to similar environments in South and Southeast Asia via multinomial logistic regression modeling, we show that active iron reduction, and therefore susceptibility to future arsenic contamination, is more widely distributed in presumably pristine aquifers than anticipated.
Keywords: BANGLADESH; BENGAL BASIN; groundwater; PLEISTOCENE AQUIFER; POLLUTION; RELEASE; RIVER DELTA; Sediment; TRANSPORT; VIETNAM

Arsenic contamination of Bangladesh aquifers exacerbated by clay layers - Mihajlov, Ivan; Mozumder, M. Rajib H.; Bostick, Benjamín C.; Stute, Martin; Mailloux, Brian J.; Knappett, Peter S. K.; Choudhury, Imtiaz; Ahmed, Kazi Matin; Schlosser, Peter; van Geen, Alexander (Nature Communications, 2020)
Confining clay layers typically protect groundwater aquifers against downward intrusion of contaminants. In the context of groundwater arsenic in Bangladesh, we challenge this notion here by showing that organic carbon drawn from a clay layer into a low-arsenic pre-Holocene (>12 kyr-old) aquifer promotes the reductive dissolution of iron oxides and the release of arsenic. The finding explains a steady rise in arsenic concentrations in a pre-Holocene aquifer below such a clay layer and the repeated failure of a structurally sound community well. Tritium measurements indicate that groundwater from the affected depth interval (40–50 m) was recharged >60 years ago. Deeper (55–65 m) groundwater in the same pre-Holocene aquifer was recharged only 10–50 years ago but is still low in arsenic. Proximity to a confining clay layer that expels organic carbon as an indirect response to groundwater pumping, rather than directly accelerated recharge, caused arsenic contamination of this pre-Holocene aquifer.

Asian summer monsoon influence on chemical weathering and sediment provenance determined by clay mineral analysis from the Indus Submarine Canyon - Li, Yuting; Clift, Peter D.; Murray, Richard W.; Exnicios, Elise; Ireland, Thomas; Böning, Philipp (Quaternary Research, 2020)
Clay minerals from the Indus Canyon and eastern clinoform since ~12 ka are uniformly rich in smectite and illite, similar to those from the Holocene Indus flood plains. A systematic enrichment of smectite in the proximal delta compared to the canyon and eastern clinoform argues for preferential capture of smectite close to the river mouth since ~12 ka. There is a rapid shift to a more smectite-rich assemblage in the canyon and eastern clinoform after ~5 ka. This change is probably caused by a change in sediment source, with less direct flux from the Himalaya and more erosion of older, weathered, smectite-rich sediment from the Indus River flood plains, driven by incision of the Indus and its tributaries into the floodplain as summer monsoon rains weakened. This influx of smectite is consistent with lower kaolinite/smectite values since ~5 ka. The onset of large-scale agricultural activities since ~5 ka, especially starting with the Harappan Civilization, may also have enhanced incision and erosion of floodplain sediments over the same time period. This study reports for the first time how monsoon strength variations since ~12 ka affected the clay mineral assemblages and sediment provenance in a major submarine canyon.
Keywords: Clay minerals; Holocene; monsoon; Provenance; Reworking; Submarine canyon

Carbon Cycling in the World's Deepest Blue Hole - Yao, P.; Wang, X. C.; Bianchi, T. S.; Yang, Z. S.; Fu, L.; Zhang, X. H.; Chen, L.; Zhao, B.; Morrison, E. S.; Shields, M. R.; Liu, Y. N.; Bi, N. S.; et al. (Journal of Geophysical Research: Biogeosciences, 2020)
Blue holes are unique geomorphological features with steep biogeochemical gradients and distinctive microbial communities. Carbon cycling in blue holes, however, remains poorly understood. Here we describe potential mechanisms of dissolved carbon cycling in the world's deepest blue hole, the Yongle Blue Hole (YBH), which was recently discovered in the South China Sea. In the YBH, we found some of the lowest concentrations (e.g., 22 μM) and oldest ages (e.g., 6,810 years before present) of dissolved organic carbon, as well as the highest concentrations (e.g., 3,090 μM) and the oldest ages (e.g., 8,270 years before present) of dissolved inorganic carbon observed in oceanic waters. Sharp gradients of dissolved oxygen, H2S, and CH4 and changes in bacterially mediated sulfur cycling with depth indicated that sulfur‐ and/or methane‐based metabolisms are closely linked to carbon cycling in the YBH. Our results showed that the YBH is a unique and easily accessible natural laboratory for examining carbon cycling in anoxic systems, which has potential for understanding carbon dynamics in both paleo and modern oceans—particularly in the context of global change.
Keywords: anoxia; carbon cycling; dissolved carbon; radiocarbon; sulfur cycling; Yongle blue hole

Carbon isotope forensics for methane source identification - Coffin, Richard; Mueller, James (Remediation Journal, 2020)
Methane (CH4) in ecosystems originates from ancient petroleum formed deep within the earth and/or via microbial fermentation of organic carbon and subsequent reduction of carbon dioxide (CO2). Given the complexity of different ecosystems, origins of CH4 present can be difficult to determine. This issue was realized in a situation where an antimethanogenic in situ chemical reduction (ISCR) remedial amendment containing organic carbon plus zero‐valent iron was applied to treat chlorinated solvents in groundwater at a former dry cleaner facility. The technology rapidly and effectively reduced the concentration of tetrachloroethene in groundwater thus meeting project goals without the stoichiometric accumulation of catabolites such as trichloroethene (TCE), cis‐1,2‐dichloroethene, or vinyl chloride and without excessive methanogenesis (e.g., <2 mg/L) in the treated area. However, approximately 9 months after treatment, increased levels of CH4 (from 5 to 10 mg/L) were observed downgradient from the treated area. The applied remedial amendment contained approximately 60% (weight basis) fermentation organic carbon and was therefore a potential source of this CH4. However, there was <500 mg/L total organic carbon in groundwater emanating from the upgradient treatment area which was unlikely sufficient to produce that much CH4. Moreover, the soil gas also contained benzene, toluene, ethylbenzene, and xylenes and other gasoline constituents. These data suggested that the presence of three gasoline/diesel underground storage tanks that were previously closed in place with no active remediation performed could be the source of elevated CH4. Thirdly, there were sewer lines, utilities, multiple gasoline stations, and industrial activities in the immediate area. With an initial assumption that CH4 source(s) could include the ISCR amendment over stimulation of production, gasoline sourced CH4 from nearby leaking lines, or sewage from local fractured pipes, carbon isotope analyses—radiocarbon (Δ14C) and stable carbon (δ13C)—were coupled with CH4 and CO2 concentration data from groundwater samples to determine the origin of respired carbon. The δ13C range for carbon sources respired in the process would be approximately −26.5‰ to −33.0‰ for the ISCR amendment and total petroleum hydrocarbons (TPH) residuals, respectively. Δ14C is approximately 0‰ and −999‰ for the ISCR amendment (young carbon) and TPH (old carbon), respectively. The isotopic signature of respired gasses confirmed that elevated CH4 downgradient of the treated area originated primarily from sewer gasses (or fermentation of liquids released from sewer lines). This study provides an overview of the capability to apply carbon isotope geochemistry to confirmation of remedial protocols and sources of anthropogenic carbon pools that conclusively identify the origin of CH4 in a complex ecosystem undergoing a remedial action.

Chapter 30 - Radiocarbon dating of tsunami and storm deposits - Kelsey, Harvey M.; Witter, Robert C. (Geological Records of Tsunamis and Other Extreme Waves, 2020)
Radiocarbon age determinations can be an expedient and accurate means to assign age to deposits of tsunami or storm origin. Essential to the process of incorporating radiocarbon age determinations in tsunami or coastal storm investigations is an awareness on the part of the investigator that a sample will always return an age from a laboratory, but only carefully selected samples inform deposit age. Samples that inform deposit age are of two fundamentally different sample types, in-growth-position samples and detrital samples. For both in-growth-position samples and detrital samples, stratigraphic context is the critical information needed to evaluate how well sample age can constrain deposit age. Well constrained deposit ages require bracketing samples collected to provide both maximum and minimum limiting ages for the deposit(s) of interest. Therefore, sampling should be carried out with the intention of multiple sample submissions for age in order to optimize the potential for acquiring closely limiting ages. If there are multiple age determinations within a stratigraphic sequence that contains tsunami or storm deposits, then the calibrated radiocarbon ages can be, and should be, framed within a Bayesian model structure to better constrain deposit ages. Such models can be further improved by the incorporation of independent stratigraphic age information.
Keywords: Dating coastal storm deposits; Dating tsunami deposits; Modeling approaches for dating tsunami deposits; Radiocarbon dating; Sampling tsunami deposits; Tsunami Deposits; Tsunami sand

Clumped Isotopes Link Older Carbon Substrates With Slower Rates of Methanogenesis in Northern Lakes - Douglas, Peter M. J.; Gonzalez Moguel, Regina; Walter Anthony, Katey M.; Wik, Martin; Crill, Patrick M.; Dawson, Katherine S.; Smith, Derek A.; Yanay, Ella; Lloyd, Max K.; Stolper, Daniel A.; Eiler, John M.; Sessions, Alex L. (Geophysical Research Letters, 2020)
The release of long‐stored carbon from thawed permafrost could fuel increased methanogenesis in northern lakes, but it remains unclear whether old carbon substrates released from permafrost are metabolized as rapidly by methanogenic microbial communities as recently produced organic carbon. Here, we apply methane (CH4) clumped isotope (Δ18) and 14C measurements to test whether rates of methanogenesis are related to carbon substrate age. Results from culture experiments indicate that Δ18 values are negatively correlated with CH4 production rate. Measurements of ebullition samples from thermokarst lakes in Alaska and glacial lakes in Sweden indicate strong negative correlations between CH4 Δ18 and the fraction modern carbon. These correlations imply that CH4 derived from older carbon substrates is produced relatively slowly. Relative rates of methanogenesis, as inferred from Δ18 values, are not positively correlated with CH4 flux estimates, highlighting the likely importance of environmental variables other than CH4 production rates in controlling ebullition fluxes.
Keywords: clumped isotopes; ebullition flux; lakes; methane; permafrost; radiocarbon

Deep Equatorial Pacific Ocean Oxygenation and Atmospheric CO2 Over The Last Ice Age - Marcantonio, Franco; Hostak, Ryan; Hertzberg, Jennifer E.; Schmidt, Matthew W. (Scientific Reports, 2020)
Ventilation of carbon stored in the deep ocean is thought to play an important role in atmospheric CO2 increases associated with Pleistocene deglaciations. The presence of this respired carbon has been recorded by an array of paleoceanographic proxies from various locations across the global ocean. Here we present a new sediment core from the Eastern Equatorial Pacific (EEP) Ocean spanning the last 180,000 years and reconstruct high-resolution 230Th-derived fluxes of 232Th and excess barium, along with redox-sensitive uranium concentrations to examine past variations in dust delivery, export productivity, and bottom-water oxygenation, respectively. Our bottom-water oxygenation record is compared to other similar high-resolution records from across the Pacific and in the Southern Ocean. We suggest that the deep Pacific is a site of respired carbon storage associated with periods of decreased global atmospheric CO2 concentration during the LGM, confirming the conclusions from a wealth of previous studies. However, our study is the first to show a similar relationship beyond the last glacial, extending to at least 70,000 years

Effects of agricultural and tillage practices on isotopic signatures and fluxes of organic and inorganic carbon in headwater streams - Kelsey, Scott A.; Grottoli, Andrea G.; Bauer, James E.; Lorenz, Klaus; Lal, Rattan; Matsui, Yohei; Huey-Sanders, Teresa M. (Aquatic Sciences, 2020)

Efficient preservation of young terrestrial organic carbon in sandy turbidity-current depositsAbstract - Hage, S.; Galy, V.V.; Cartigny, M.J.B.; Acikalin, S.; Clare, M.A.; Gröcke, D.R.; Hilton, R.G.; Hunt, J.E.; Lintern, D.G.; McGhee, C.A.; Parsons, D.R.; Stacey, C.D.; et al. (Geology, 2020)
Burial of terrestrial biospheric particulate organic carbon in marine sediments removes CO2 from the atmosphere, regulating climate over geologic time scales. Rivers deliver terrestrial organic carbon to the sea, while turbidity currents transport river sediment further offshore. Previous studies have suggested that most organic carbon resides in muddy marine sediment. However, turbidity currents can carry a significant component of coarser sediment, which is commonly assumed to be organic carbon poor. Here, using data from a Canadian fjord, we show that young woody debris can be rapidly buried in sandy layers of turbidity current deposits (turbidites). These layers have organic carbon contents 10× higher than the overlying mud layer, and overall, woody debris makes up >70% of the organic carbon preserved in the deposits. Burial of woody debris in sands overlain by mud caps reduces their exposure to oxygen, increasing organic carbon burial efficiency. Sandy turbidity current channels are common in fjords and the deep sea; hence we suggest that previous global organic carbon burial budgets may have been underestimated.

Groundwater as a major source of dissolved organic matter to Arctic coastal waters - Connolly, Craig T.; Cardenas, M. Bayani; Burkart, Greta A.; Spencer, Robert G. M.; McClelland, James W. (Nature Communications, 2020)
Groundwater is projected to become an increasing source of freshwater and nutrients to the Arctic Ocean as permafrost thaws, yet few studies have quantified groundwater inputs to Arctic coastal waters under contemporary conditions. New measurements along the Alaska Beaufort Sea coast show that dissolved organic carbon and nitrogen (DOC and DON) concentrations in supra-permafrost groundwater (SPGW) near the land-sea interface are up to two orders of magnitude higher than in rivers. This dissolved organic matter (DOM) is sourced from readily leachable organic matter in surface soils and deeper centuries-to millennia-old soils that extend into thawing permafrost. SPGW delivers approximately 400–2100 m3 of freshwater, 14–71 kg of DOC, and 1–4 kg of DON to the coastal ocean per km of shoreline per day during late summer. These substantial fluxes are expected to increase as massive stocks of frozen organic matter in permafrost are liberated in a warming Arctic.

Holocene earthquake history and slip rate of the southern Teton fault, Wyoming, USAAbstract - DuRoss, Christopher B.; Gold, Ryan D.; Briggs, Richard W.; Delano, Jaime E.; Ostenaa, Dean A.; Zellman, Mark S.; Cholewinski, Nicole; Wittke, Seth J.; Mahan, Shannon A. (GSA Bulletin, 2020)
The 72-km-long Teton normal fault bounds the eastern base of the Teton Range in northwestern Wyoming, USA. Although geomorphic surfaces along the fault record latest Pleistocene to Holocene fault movement, the postglacial earthquake history of the fault has remained enigmatic. We excavated a paleoseismic trench at the Buffalo Bowl site along the southernmost part of the fault to determine its Holocene rupture history and slip rate. At the site, ∼6.3 m of displacement postdates an early Holocene (ca. 10.5 ka) alluvial-fan surface. We document evidence of three surface-faulting earthquakes based on packages of scarp-derived colluvium that postdate the alluvial-fan units. Bayesian modeling of radiocarbon and luminescence ages yields earthquake times of ca. 9.9 ka, ca. 7.1 ka, and ca. 4.6 ka, forming the longest, most complete paleoseismic record of the Teton fault. We integrate these data with a displaced deglacial surface 4 km NE at Granite Canyon to calculate a postglacial to mid-Holocene (14.4–4.6 ka) slip rate of ∼1.1 mm/yr. Our analysis also suggests that the postglacial to early Holocene (14.4–9.9 ka) slip rate exceeds the Holocene (9.9–4.6 ka) rate by a factor of ∼2 (maximum of 3); however, a uniform rate for the fault is possible considering the 95% slip-rate errors. The ∼5 k.y. elapsed time since the last rupture of the southernmost Teton fault implies a current slip deficit of ∼4–5 m, which is possibly explained by spatially/temporally incomplete paleoseismic data, irregular earthquake recurrence, and/or variable per-event displacement. Our study emphasizes the importance of minimizing slip-rate uncertainties by integrating paleoseismic and geomorphic data sets and capturing multiple earthquake cycles.

Holocene Rupture History of the Central Teton Fault at Leigh Lake, Grand Teton National Park, WyomingABSTRACT - Zellman, Mark S.; DuRoss, Christopher B.; Thackray, Glenn D.; Personius, Stephen F.; Reitman, Nadine G.; Mahan, Shannon A.; Brossy, Cooper C. (Bulletin of the Seismological Society of America, 2020)
Prominent scarps on Pinedale glacial surfaces along the eastern base of the Teton Range confirm latest Pleistocene to Holocene surface‐faulting earthquakes on the Teton fault, but the timing of these events is only broadly constrained by a single previous paleoseismic study. We excavated two trenches at the Leigh Lake site near the center of the Teton fault to address open questions about earthquake timing and rupture length. Structural and stratigraphic evidence indicates two surface‐faulting earthquakes at the site that postdate deglacial sediments dated by radiocarbon and optically stimulated luminescence to ∼10–11  ka⁠. Earthquake LL2 occurred at ∼10.0  ka (9.7–10.4 ka; 95% confidence range) and LL1 at ∼5.9  ka (4.8–7.1 ka; 95%). LL2 predates an earthquake at ∼8  ka identified in the previous paleoseismic investigation at Granite Canyon. LL1 corresponds to the most recent Granite Canyon earthquake at ∼4.7–7.9  ka (95% confidence range). Our results are consistent with the previously documented long‐elapsed time since the most recent Teton fault rupture and expand the fault’s earthquake history into the early Holocen

Holocene sedimentation in a blue hole surrounded by carbonate tidal flats in The Bahamas: Autogenic versus allogenic processes - van Hengstum, Peter J.; Winkler, Tyler S.; Tamalavage, Anne E.; Sullivan, Richard M.; Little, Shawna N.; MacDonald, Dana; Donnelly, Jeffrey P.; Albury, Nancy A. (Marine Geology, 2020)
The sediment in North Atlantic blue holes preserves paleoclimate records. However, accurate paleoclimate reconstructions require an improved understanding of allogenic versus autogenic processes controlling blue hole sedimentation. Here we provide a detailed case study of the Holocene stratigraphy within Freshwater River Blue Hole, which is currently surrounded by carbonate tidal flats in the northern Bahamas (Abaco Island). During the Holocene, concomitant coastal aquifer elevation and relative sea-level rise controlled internal blue hole depositional environments. The general Holocene facies succession observed is: (i) basal detrital and freshwater peat, (ii) palustrine to lacustrine marl, (iii) algal sapropel, and finally (iv) bedded carbonate mud. During the middle Holocene when groundwater levels were lower, small changes in accommodation space that were inherited from the bedrock surface below (<1 m) were able to promote significant lateral facies changes. Multiple cores are needed to characterize these lateral facies changes. Hydrographic characteristics of the coastal aquifer (e.g., vertical position, stratification, salinity) relative to the blue hole benthos exert a fundamental control on (a) benthic flora and meiofauna (e.g., charophytes, ostracodes, foraminifera, gastropods) and (b) organic matter production and preservation from pelagic productivity. Over the last 5000 years, water column stratification in Freshwater River Blue Hole was interrupted on millennial to sub-decadal timescales , which are potentially linked to changing aquifer recharge and rainfall. Lastly, historical intense hurricanes passing closely to the west of the site may have promoted deposition of coarse beds at the site. However, the lack of carbonate tidal flat microfaunal remains (foraminifera: Peneroplis) within these coarse intervals indicates that Freshwater River Blue Hole does not preserve a reliable record of hurricane-induced overwash deposition from the carbonate tidal flats during the last 2300 years.
Keywords: Carbonate tidal flats; carbonates; North Atlantic Bahamas; sinkhole

Holocene temperature and landscape history of southwest Greenland inferred from isotope and geochemical lake sediment proxies - Lasher, G. Everett; Axford, Yarrow; Masterson, Andrew L.; Berman, Karalyn; Larocca, Laura J. (Quaternary Science Reviews, 2020)
Terrestrial temperature reconstructions from the ice-free margins of Greenland are critical for constraining the sensitivity of the Greenland ice sheet to past climate change. Numerous investigations have clarified the glacial history of southwest Greenland in recent decades; however, very few local quantitative temperature reconstructions exist as context for changes in the cryosphere. We examine sedimentary records from two lakes south of Nuuk, Greenland (informally named lakes T1 and T2), and investigate millennial scale Holocene climate change using a multi-proxy approach. Changes in X-Ray fluorescence spectroscopy (XRF), δ15N, δ13C and biogenic silica concentrations of bulk lake sediments mark the transition from a marine environment to isolated lakes as relative sea level fell in the early Holocene. δ18O values of subfossil insects (chironomids) from lakes T1 and T2 decreased by 2–3‰ from c. 8.8 ka BP (minimum limiting age for the onset of lacustrine sediment deposition in lake T2; ka BP = thousands of years before 1950) to 1 ka BP. Existing isotope-independent temperature reconstructions from the west coast of Greenland suggest that these changes in δ18O values accompanied gradual cooling of 2–4 °C, concomitant with decreasing summer insolation. There is widespread regional evidence that this cooling resulted in progressive regrowth of local glaciers and of the ice sheet. The regional consensus on the magnitude of this temperature change indicates that the local, modern modeled temperature - precipitation δ18O relationship cannot be used to quantify millennial-scale temperature changes at these sites through the Holocene. This reinforces that studies utilizing δ18O-based proxies to infer temperature change should carefully assess local isotope-temperature relationships over space and time.
Keywords: Chironomids; glaciers; Greenland; Isolation basins; lake sediments; oxygen isotopes; Paleotemperatures; Stable isotopes

The Hooskanaden Landslide: historic and recent surge behavior of an active earthflow on the Oregon Coast - Alberti, Stefano; Senogles, Andrew; Kingen, Kara; Booth, Adam; Castro, Pete; DeKoekkoek, Jill; Glover-Cutter, Kira; Mohney, Curran; Olsen, Michael; Leshchinsky, Ben (Landslides, 2020)
This paper presents an analysis of the Hooskanaden Landslide, an earthflow, which experienced a dramatic surge event beginning on February 24, 2019, closing US Highway 101 near mile point 343.5 for nearly 2 weeks. This ~ 1 km long surge event resulted in horizontal displacements of up to 45 m and uplift of 6 m at the toe located on a gravel beach adjacent to the Pacific Ocean. The Hooskanaden Landslide, likely active since the eighteenth century, exhibits regular activity with a recurrence interval of major surge events of approximately every 20 years, transitioning from slow to relatively rapid velocities. During the 2019 event, maximum displacement rates of approximately 60 cm/h were observed, slowly decreasing to 15 cm/h for a sustained period of approximately 2 weeks before the eventual return to baseline conditions (< 0.02 cm/h).

Insolation and greenhouse gases drove Holocene winter and spring warming in Arctic Alaska - Longo, William M.; Huang, Yongsong; Russell, James M.; Morrill, Carrie; Daniels, William C.; Giblin, Anne E.; Crowther, Josue (Quaternary Science Reviews, 2020)
Global surface temperature changes and their drivers during the Holocene Epoch remain controversial. Syntheses of proxy data indicate that global mean annual temperature declined from the mid-Holocene until the Pre-industrial Era, a trend linked to decreasing Northern Hemisphere summer insolation. In contrast, global climate models simulate increasing mean annual temperatures driven by retreating ice sheets and increasing greenhouse gas concentrations. This proxy-model disagreement may originate from a warm season bias in Northern Hemisphere proxy reconstructions, highlighting the need for new proxies that quantify cold season temperature, especially in Arctic regions that were devoid of continental ice sheets during the Holocene. Here, we present a new 16,000-year winter-spring temperature reconstruction derived from the unsaturation ratio of alkenones (U-3(7)K) in a continuous sedimentary sequence from Lake E5, northern Alaska. We employ a thermodynamic lake model to convert alkenone-inferred lake temperatures into winter-spring air temperature anomalies and we contextualize our proxy reconstruction with climate model output from the region. Our reconstruction shows that winter-spring temperatures warmed rapidly during the deglaciation at 16 and 14 thousand years before present and continued to warm gradually throughout the middle and late Holocene (0.12-0.28 degrees C/thousand years) in concert with regional sea surface temperature and sea ice records. Our results are consistent with climate model simulations and we attribute Holocene warming to rising winter-spring insolation, radiative forcing from rising greenhouse gas concentrations and regional feedbacks. Our reconstructed cold season warming equaled or exceeded summer cooling according to a regional synthesis of temperature records, suggesting that seasonal biases in temperature reconstructions may account for proxy-model disagreements in Holocene temperature trends from Eastern Beringia. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Alkenone; Beringia; Continental biomarkers; Holocene; North America; paleoclimatology; paleolimnology; Proxy data-model comparison; seasonality; Temperature reconstruction

Late glacial and Holocene paleoenvironments in the midcontinent United States, inferred from Geneva Lake leaf wax, ostracode valve, and bulk sediment chemistry - Puleo, Peter J.K.; Axford, Yarrow; McFarlin, Jamie M.; Curry, B. Brandon; Barklage, Mitchell; Osburn, Magdalena R. (Quaternary Science Reviews, 2020)
Geneva Lake in Wisconsin, USA, is > 20,000 years old and contains a 30-m thick lacustrine sediment record of mid-continent North American climate and environmental change. Here we describe a sediment record from Geneva Lake spanning the past 14,500 years. From scanning X-ray fluorescence, organic C and N concentrations and isotopes, X-ray diffraction, magnetic susceptibility, and grain size of bulk sediments, we infer changes in sediment sources over time including: abrupt decline in inputs of remobilized loess ∼13,400 cal yr BP followed by a gradual transition to organic-rich marl deposition by ∼10,400 cal yr BP as the landscape stabilized following a period of permafrost thaw and vegetation development; deposition of a minerogenic unit at ∼8,200 cal yr BP that may record enhanced eolian activity during the widespread “8.2 ka event; ” and elevated zinc, lead, and arsenic from human activities following regional industrialization. Within the Holocene marl, we also use isotopic (δ18O and δ13C) and trace metal ratio (Sr/Ca and Mg/Ca) analyses of ostracode valves paired with concentrations and hydrogen isotopic composition (δ2H) of leaf wax n-alkanes to infer climate and hydrological change. Groundwater had a large but declining influence on lake water chemistry from 11,800 to 9,700 cal yr BP, precluding inferences of regional climate from our lacustrine proxies during this period. δ2H values of terrestrial n-C29 alkanes show little variability from 9,700 to present, indicating the average isotopic composition of local precipitation was relatively stable, reflecting stable condensation temperatures and source. In contrast, a gradual trend towards more δ18O- and δ2H-depleted lake water and lower lake water Sr/Ca from 9700 cal yr BP to present suggest decreasing evaporation of lake water and increasing precipitation amounts throughout the Holocene and resulting shorter lake water residence times. Lake water Mg/Ca variations over the past 9,700 years broadly parallel regional pollen-based reconstructions of summer temperatures. Neither Mg/Ca nor terrestrial leaf wax δ2H suggest long-term directional shifts in temperature at this site through the middle to late Holocene, as climate became wetter. It appears that precipitation isotopes did not track local temperatures on millennial timescales in this part of mid-continent North America through the Holocene, and instead may have covaried with changes in Northern Hemisphere latitudinal temperature gradients driven by large Arctic temperature changes.
Keywords: Holocene; Inorganic geochemistry; Loess; North America; Organic geochemistry; paleoclimatology; paleolimnology; Pleistocene; sedimentology; Stable isotopes

A late Holocene subfossil Atlantic white cedar tree-ring chronology from the northeastern United States - Pearl, Jessie K.; Anchukaitis, Kevin J.; Donnelly, Jeffrey P.; Pearson, Charlotte; Pederson, Neil; Lardie Gaylord, Mary C.; McNichol, Ann P.; Cook, Edward R.; Zimmermann, George L. (Quaternary Science Reviews, 2020)
Tree-rings provide precise annually dated climate information, but their application can be limited by the relatively short lifespan of many trees. To overcome this limitation, tree-ring records can be extended over longer time periods by connecting living trees with older “sub-fossil” trees, which can provide information on longer timescales throughout the Holocene. These long chronologies are proxy records of past climate, provide precise chronological information for extreme events, and give insight into the range of natural climate variability prior to the instrumental period. In the densely populated northeastern United States, few tree-ring records are longer than 500 years, and there are no millennial-length tree-ring chronologies for the region. Here, we use a combination of standard dendrochronological and radiocarbon techniques, including use of the 774 CE radiocarbon excursion, to generate an absolutely dated 2500 year-long tree ring record from living, archaeological, and subfossil Atlantic white cedar (Chamaecyparis thyoides) found in the coastal northeastern United States. Our chronology demonstrates the potential to develop multi-millennial Chamaecyparis thyoides tree-ring records to address previously unanswered questions regarding late Holocene hydroclimate, extreme events, and temperature variability in New England.
Keywords: coastal; Geomorphology; Holocene; North America; paleoclimatology; radiogenic isotopes; Tree-rings

Minimum limiting deglacial ages for the out-of-phase Saginaw Lobe of the Laurentide Ice Sheet using optically stimulated luminescence (OSL) and radiocarbon methods - Fisher, Timothy G.; Dziekan, Mitchell R.; McDonald, Jennifer; Lepper, Kenneth; Loope, Henry M.; McCarthy, Francine M.G.; Curry, B. Brandon (Quaternary Research, 2020)
Twenty-four new optically stimulated luminescence (OSL) and radiocarbon ages from sediment cores in nine lakes associated with the Shipshewana and Sturgis moraines in northern Indiana and southern Michigan estimate when recession of the Saginaw Lobe of the Laurentide Ice Sheet was underway in the southern Great Lakes region, USA. Average OSL ages of 23.4 ± 2.2 ka for the Shipshewana Moraine and 19.7 ± 2.2 ka for the Sturgis Moraine are considered minimum limiting deglacial ages for these recessional moraines. The much younger radiocarbon ages are consistent with other regional radiocarbon ages from lakes, and record climate amelioration around ~16.5 cal ka BP. Early recession of the interlobate Saginaw Lobe was well underway by 23.4 ± 2.2 ka, when the adjacent Lake Michigan and Huron-Erie lobes were a few hundred kilometers farther south and near their maximum southerly limits. The results provide the first time constraints when sediment from the Lake Michigan and Huron-Erie lobes began filling the accommodation space left by the Saginaw Lobe. The difference between the oldest radiocarbon and OSL age is 7400 yr for the Shipshewana Moraine and 3400 yr for the Sturgis Moraine.
Keywords: Deglaciation; Lake sediment cores; OSL dating; Radiocarbon lag; Saginaw Lobe; Sturgis Moraine

Neotectonic and Paleoseismic Analysis of the Northwest Extent of Holocene Surface Deformation along the Meers Fault, OklahomaABSTRACT - Hornsby, Kristofer T.; Streig, Ashley R.; Bennett, Scott E. K.; Chang, Jefferson C.; Mahan, Shannon (Bulletin of the Seismological Society of America, 2020)
The Meers fault (Oklahoma) is one of few seismogenic structures with evidence for Holocene surface rupture in the stable continental region of North America. The 37-kilometer-long southeast section of the full 54-kilometer-long Meers fault is interpreted to be Holocene active. The 17-kilometer-long northwest section is considered Quaternary active, but not Holocene active.We reevaluate surface expression and earthquake timing of the northwest Meers fault to improve seismic source characterization.We use airborne light detection and ranging and historical stereo paired aerial photos to evaluate the fault scarp and local fault zone geomorphology. In the northwest, complex surface deformation includes fault splays, subtle monoclinal warping, and a minor change in fault strike. We interpret that the along strike transition from surface faulting on the southeast Meers fault to surface folding on the northwest Meers fault occurs at the lithologic contact between Permian Post Oak conglomerate and Hennessey shale. We excavated a paleoseismic trench to evaluate the timing of surface-deforming earthquakes on the northwest section of the fault. The excavation revealed weathered Permian Hennessey shale and an ∼1–2-meter-thick veneer of Holocene alluvial deposits that were progressively deformed during two surface-folding earthquakes likely related to blind fault rupture beneath the site. Repeated onlapping to overlapping stratigraphic sequences and associated unconformities are intimately related to folding events along the monocline. OxCal paleoearthquake age modeling indicates that earthquakes occurred 4704–3109 yr B.P. and 5955–4744 yr B.P., and that part of the northwest section of the Meers fault is Holocene active. We find the Holocene-active section of the Meers fault should be lengthened 6.1 km to the northwest, to a total Holocene-active fault length of 43 km. Empirical scaling relationships between surface rupture length and magnitude reveal that the fault could generate an Mw 7.0 earthquake.

A new 30,000-year chronology for rapidly deposited sediments on the Lomonosov Ridge using bulk radiocarbon dating and probabilistic stratigraphic alignment - Muschitiello, Francesco; O'Regan, Matt; Martens, Jannik; West, Gabriel; Gustafsson, Örjan; Jakobsson, Martin (Geochronology, 2020)
We present a new marine chronostratigraphy from a high-accumulation rate Arctic Ocean core at the intersection of the Lomonosov Ridge and the Siberian margin, spanning the last ∼ 30 kyr. The chronology was derived using a combination of bulk 14C dating and stratigraphic correlation to Greenland ice-core records. This was achieved by applying an appositely developed Markov chain Monte Carlo algorithm for Bayesian probabilistic alignment of proxy records. The algorithm simulates depositionally realistic alignments that are consistent with the available radiocarbon age estimates and allows deriving uncertainty bands associated with the inferred alignment. Current composite chronologies from this region are reasonably consistent with our age model during the Holocene and the later part of deglaciation. However, prior to ∼ 14 kyr BP they yield too old age estimates with offsets that linearly increase up to ∼ 40 kyr near the onset of Marine Isotope Stage (MIS) 2. Our results challenge the robustness of previous regional chronostratigraphies and provide a new stratotype for correlation of sediment cores from this sector of the Lomonosov Ridge and East Siberian slope. In particular, they call for a re-interpretation of events in recent sea-ice proxy reconstructions (Xiao et al., 2015) inaccurately attributed to MIS 3 and the Last Glacial Maximum.

Origin of Groundwater Arsenic in a Rural Pleistocene Aquifer in Bangladesh Depressurized by Distal Municipal Pumping - Mozumder, M. R. H.; Michael, H. A.; Mihajlov, I.; Khan, M. R.; Knappett, P. S. K.; Bostick, B. C.; Mailloux, B. J.; Ahmed, K. M.; Choudhury, I.; Koffman, T.; Ellis, T.; Whaley‐Martin, K.; et al. (Water Resources Research, 2020)
Across South Asia, millions of villagers have reduced their exposure to high‐arsenic (As) groundwater by switching to low‐As wells. Isotopic tracers and flow modeling are used in this study to understand the groundwater flow system of a semi‐confined aquifer of Pleistocene (>10 kyr) age in Bangladesh that is generally low in As but has been perturbed by massive pumping at a distance of about 25 km for the municipal water supply of Dhaka. A 10‐ to 15‐m‐thick clay aquitard caps much of the intermediate aquifer (>40‐ to 90‐m depth) in the 3‐km2 study area, with some interruptions by younger channel sand deposits indicative of river scouring. Hydraulic heads in the intermediate aquifer below the clay‐capped areas are 1–2 m lower than in the high‐As shallow aquifer above the clay layer. In contrast, similar heads in the shallow and intermediate aquifer are observed where the clay layer is missing. The head distribution suggests a pattern of downward flow through interruptions in the aquitard and lateral advection from the sandy areas to the confined portion of the aquifer. The interpreted flow system is consistent with 3H‐3He ages, stable isotope data, and groundwater flow modeling. Lateral flow could explain an association of elevated As with high methane concentrations within layers of gray sand below certain clay‐capped portions of the Pleistocene aquifer. An influx of dissolved organic carbon from the clay layer itself leading to a reduction of initially orange sands has also likely contributed to the rise of As.
Keywords: Arsenic; Dhaka Bangladesh; groundwater pumping; modeling

A refined age calibrated paleosecular variation and relative paleointensity stack for the NW Barents Sea: Implication for geomagnetic field behavior during the Holocene - Caricchi, C.; Sagnotti, L.; Campuzano, S.A.; Lucchi, R.G.; MacrÌ, P.; Rebesco, M.; Camerlenghi, A. (Quaternary Science Reviews, 2020)
Reconstruction of Paleomagnetic Secular Variation (PSV) of the geomagnetic field is fundamental both to assess geodynamo models and to obtain age constraints for rocks, sediments and archaeological material. We present refined age-calibrated Holocene PSV and relative paleointensity (RPI) stack curves derived from Arctic marine sediments (Northwestern Barents Sea). The Holocene sections of four sedimentary cores were correlated on the basis of paleomagnetic trends and age models, and stacked. The resultant composite PSV and RPI Holocene records (NBS stack) and the reconstructed Holocene Virtual Geomagnetic Pole (VGP) path were evaluated in comparison with the most recent paleomagnetic stack curves and geomagnetic field models. The data indicate that during the Holocene time, the VGPs moved within the superficial projection of the inner core tangent cylinder, with the exception of short time intervals around 5600 and 3200 cal yr BP when VGPs extended to lower latitudes. These deviations might reflect regional geomagnetic features, such as persistent geomagnetic flux lobes at core-mantle boundary. Our data confirm that the large VGP shift observed around 5600 cal yr BP is the result of an increased radial magnetic field at the core-mantle boundary over North America, whilst the VGP shift around 3200 cal yr BP represents a major swing to middle latitudes toward the Middle East and might be associated to a regional high paleointensity peak, known as Levantine Iron Age Anomaly (LIAA).
Keywords: Arctic region; Barents Sea; Geomagnetic paleosecular variation; Holocene; marine sediment cores; Paleomagnetism; Relative paleointensity

Resolving sea ice dynamics in the north-western Ross Sea during the last 2.6 ka: From seasonal to millennial timescales - Tesi, T.; Belt, S.T.; Gariboldi, K.; Muschitiello, F.; Smik, L.; Finocchiaro, F.; Giglio, F.; Colizza, E.; Gazzurra, G.; Giordano, P.; Morigi, C.; Capotondi, L.; et al. (Quaternary Science Reviews, 2020)
Time-series analyses of satellite images reveal that sea ice extent in the Ross Sea has experienced significant changes over the last 40 years, likely triggered by large-scale atmospheric anomalies. However, resolving how sea ice in the Ross Sea has changed over longer timeframes has until now remained more elusive. Here we used a laminated sediment piston core (14.6 m) collected from the Edisto inlet (Western Ross Sea) to reconstruct fast ice dynamics over the last 2.6 ka. Our goal was to first understand the climate expression of selected well-defined sediment laminae and then use these characteristics for reconstructing past sea ice behaviour across the whole sedimentary sequence. We used the recently established sea ice diatom biomarker proxy IPSO25 in combination with diatom census counts and bulk analyses. Analyses performed on a suite of discrete laminae revealed statistically significant differences between dark and light laminae reflecting different depositional conditions. Based on their respective biogeochemical fingerprints, we infer that dark laminae accumulated during sea ice thaws in early summer. Under these conditions, laminae contain relatively high concentrations of IPSO25 and display an enriched δ13C composition for the bulk organic matter (OM). While diatom assemblages in dark laminae are relatively homogenous, as the thaw continues later in the summer, Corethron pennatum becomes the dominant diatom species, resulting in the formation of light laminae characterized by low IPSO25 concentrations. Since C. pennatum can migrate vertically through the water column to uptake nutrients and avoid competition in oligotrophic waters, its high concentration likely reflects stratified and ice-free surface waters typical of late summer. Down-core trends show that the correlation between sediment brightness and geochemical fingerprint (i.e., IPSO25 and δ13C) holds throughout the record. Based on the knowledge gained at lamina level, our down-core high-resolution reconstruction shows that the summer fast ice coverage changed dramatically during the late Holocene. Specifically, we conclude that the Edisto inlet experienced regular early summer opening between 2.6 ka, and ca. 0.7 ka, after which, coastal fast ice persisted during summer months and ice-free conditions became less frequent. Comparison with previous regional ice core data suggests that the sudden cooling recorded over the Victoria Land Coast region since 0.7 ka might potentially explain our observation of persistent summer fast ice in the Western Ross Sea. Our study has shown that multi-proxy data derived from laminated sediments can provide hitherto unknown detail regarding past summer sea ice dynamics in coastal Antarctic regions.
Keywords: Fast ice; IPSO25; Laminated sediments; Ross Sea; Sea ice

The southern Gulf of Mexico: A baseline radiocarbon isoscape of surface sediments and isotopic excursions at depth - Bosman, Samantha H.; Schwing, Patrick T.; Larson, Rebekka A.; Wildermann, Natalie E.; Brooks, Gregg R.; Romero, Isabel C.; Sanchez-Cabeza, Joan-Albert; Ruiz-Fernández, Ana Carolina; Machain-Castillo, Maria Luisa; Gracia, Adolfo; Escobar-Briones, Elva; Murawski, Steven A.; et al. (PLOS ONE, 2020)
The southern Gulf of Mexico (sGoM) is home to an extensive oil recovery and development infrastructure. In addition, the basin harbors sites of submarine hydrocarbon seepage and receives terrestrial inputs from bordering rivers. We used stable carbon, nitrogen, and radiocarbon analyses of bulk sediment organic matter to define the current baseline isoscapes of surface sediments in the sGoM and determined which factors might influence them. These baseline surface isoscapes will be useful for accessing future environmental impacts. We also examined the region for influence of hydrocarbon deposition in the sedimentary record that might be associated with hydrocarbon recovery, spillage and seepage, as was found in the northern Gulf of Mexico (nGoM) following the Deepwater Horizon (DWH) oil spill in 2010. In 1979, the sGoM experienced a major oil spill, Ixtoc 1. Surface sediment δ13C values ranged from -22.4‰ to -19.9‰, while Δ14C values ranged from -337.1‰ to -69.2‰. Sediment δ15N values ranged from 2.8‰ to 7.2‰, while the %C on a carbonate-free basis ranged in value of 0.65% to 3.89% and %N ranged in value of 0.09% to 0.49%. Spatial trends for δ13C and Δ14C were driven by water depth and distance from the coastline, while spatial trends for δ15N were driven by location (latitude and longitude). Location and distance from the coastline were significantly correlated with %C and %N. At depth in two of twenty (10%) core profiles, we found negative δ13C and Δ14C excursions from baseline values in bulk sedimentary organic material, consistent with either oil-residue deposition or terrestrial inputs, but likely the latter. We then used 210Pb dating on those two profiles to determine the time in which the excursion-containing horizons were deposited. Despite the large spill in 1979, no evidence of hydrocarbon residue remained in the sediments from this specific time period.
Keywords: Gulf of Mexico; hydrocarbons; Oil spills; Oils; Petroleum; Sediment

Spatial and temporal variability in Mediterranean climate over the last millennium from vermetid isotope records and CMIP5/PMIP3 models - Amitai, Yael; Yam, Ruth; Montagna, Paolo; Devoti, Saverio; Correa, Matthias López; Shemesh, Aldo (Global and Planetary Change, 2020)
Stable isotope compositions of oxygen (delta O-18) and carbon (delta C-1(3)) of the aragonite skeleton of the reef-building gastropod Dendropoma petreaum provide high-resolution records of the Mediterranean climate over the last millennium. In particular, the isotopic composition of vermetid cores collected from the west and east Mediterranean reveals that the different regions have had distinct thermal and primary production behaviors throughout the last millennium. The rate of warming in the recent Industrial Period is variable among the different regions of the Mediterranean Sea. The delta O-18-derived Sea Surface Temperature (SST) anomalies show that the Eastern Mediterranean surface temperature is increasing much more rapidly than in the Western Mediterranean. Additionally, the signals of the Little Ice Age and of the Medieval Climate Anomaly are more apparent in the western and in the central Mediterranean while they are almost absent in the eastern Mediterranean. We aim to reconcile the SST temporal and spatial pattern with the variability of the North Atlantic Oscillation (NAO) and the South Asian Monsoon (SAM) climate systems by analyzing coupled atmosphere-ocean models from the CMIP5/PMIP3 projects that simulate the global climate of the past 1000 years. We show that even though the NAO is more dominant in the western Mediterranean SST, its latitudinal movement, on a centennial time scale, is evident in the eastern Mediterranean SST signal. We also discuss the Atlantic water inflow role in the observed similarities of the surface productivity signals and the Suess effect that prevail the Industrial Period signal in all regions of the Mediterranean.

Yellowstone's Old Faithful Geyser Shut Down by a Severe Thirteenth Century Drought - Hurwitz, Shaul; King, John C.; Pederson, Gregory T.; Martin, Justin T.; Damby, David E.; Manga, Michael; Hungerford, Jefferson D. G.; Peek, Sara (Geophysical Research Letters, 2020)
To characterize eruption activity of the iconic Old Faithful Geyser in Yellowstone National Park over past centuries, we obtained 41 new radiocarbon dates of mineralized wood preserved in the mound of silica that precipitated from erupted waters. Trees do not grow on active geyser mounds, implying that trees grew on the Old Faithful Geyser mound during a protracted period of eruption quiescence. Rooted stumps and root crowns located on higher parts of the mound are evidence that at the time of tree growth, the geyser mound closely resembled its current appearance. The range of calibrated radiocarbon dates (1233–1362 CE) is coincident with a series of severe multidecadal regional droughts toward the end of the Medieval Climate Anomaly, prior to the onset of the Little Ice Age. Climate models project increasingly severe droughts by mid-21st century, suggesting that geyser eruptions could become less frequent or completely cease.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1029/2020GL089871
Keywords: drought; Medieval Climate Anomaly; mineralization; Old Faithful Geyser; radiocarbon; Yellowstone

Annual radiocarbon measurements in a century-old European beech tree (Fagus sylvatica) from coastal northeastern North America - Gaylord, Mary C. Lardie; Longworth, Brett E.; Murphy, Keelan; Cobb, Caroline; McNichol, Ann P. (NUCLEAR INSTRUMENTS & METHODS IN PHYSICS RESEARCH SECTION B-BEAM INTERACTIONS WITH MATERIALS AND ATOMS, 2019)
Radiocarbon (C-14) concentrations of annual tree rings from an European beech tree (Fagus sylvatica) from Woods Hole, MA, USA were analyzed at National Ocean Sciences Accelerator Mass Spectrometry facility (NOSAMS) to construct a C-14 bomb curve record from northeastern North America. The C-14 concentration rises from a pre bomb (1895-1955) average of Fraction Modern ((FC)-C-14) = 0.9764 to a peak of 1.8639 in 1964. After 1964, (FC)-C-14 gradually decreases to 1.0611 in 2014. The annual tree-ring radiocarbon content agrees with the atmospheric radiocarbon content of the Northern Hemisphere and is very similar to the radiocarbon concentration of a red oak (Quercus rubra) tree located in Bear Mountain State Park in New York, USA. Infra-annual tree-ring pairs did not produce evidence of a seasonal effect on the radiocarbon concentration, but there were few samples and more study is warranted.

CO2-dependent carbon isotope fractionation in Archaea, Part II: The marine water column - Hurley, Sarah J.; Close, Hilary G.; Elling, Felix J.; Jasper, Claire E.; Gospodinova, Kalina; McNichol, Ann P.; Pearson, Ann (GEOCHIMICA ET COSMOCHIMICA ACTA, 2019)
Stable carbon isotope ratios of archaeal glycerol dibiphytanyl glycerol tetraether (GDGT) lipids have been proposed as a proxy to infer past changes in the carbon isotope composition (delta C-13) of dissolved inorganic carbon (DIC). The premise for paleo-delta C-13(DIC) reconstructions from GDGTs is based on observations of relatively constant delta C-13(GDGT) values in recent depositional environments. Marine Thaumarchaeota, thought to be the dominant source of GDGTs to marine sediments, fix inorganic carbon using the 3-hydroxypropionate/4-hydroxybutyrate (3HP/4HB) pathway, which is specific to HCO3- as the substrate. Bicarbonate-dependent autotrophy has been the basis for predicting that the stable carbon isotopic composition of GDGTs (delta C-13(GDGT)) should vary in parallel with water column delta C-13(DIC) values, because HCO3- is by far the dominant fraction of DIC in modern seawater. However, this relationship has never been systematically tested. Here we examine the carbon isotopic composition of GDGTs from four water column profiles in the Southwest and Equatorial Atlantic Ocean. Values of delta C-13(GDGT) increase with depth in the water column, in contrast to the characteristic decrease in delta C-13(DIC) values. These divergent trends imply a decrease in the observed total biosynthetic isotope effect (epsilon(Ar)) with depth, i.e., the offset between delta(13)(DIC) and delta C-13(GDGT) is not constant. Instead, we find that values of epsilon(Ar) specifically correlate with oceanographic variables associated with extent of organic remineralization, decreasing as CO2 concentration increases. This observed relationship is consistent in both magnitude and direction with the results of an isotope flux-balance model for Thaumarchaeota that suggests epsilon(Ar) should be sensitive to growth rate (mu) and CO2 availability under conditions of atmospheric pCO(2) < 4 times the pre-anthropogenic Holocene level. Further tests of the sensitivity of epsilon(Ar) to u and CO2 in the modern marine environment will be essential to exploring the potential for a new, archaeal lipid-derived pCO(2) paleobarometer. (C) 2019 Elsevier Ltd. All rights reserved.

Coral Skeleton δ15N as a Tracer of Historic Nutrient Loading to a Coral Reef in Maui, Hawaii - Murray, Joseph; Prouty, Nancy G.; Peek, Sara; Paytan, Adina (Scientific Reports, 2019)
Excess nutrient loading to nearshore environments has been linked to declining water quality and ecosystem health. Macro-algal blooms, eutrophication, and reduction in coral cover have been observed in West Maui, Hawaii, and linked to nutrient inputs from coastal submarine groundwater seeps. Here, we present a forty-year record of nitrogen isotopes (δ15N) of intra-crystalline coral skeletal organic matter in three coral cores collected at this site and evaluate the record in terms of changes in nitrogen sources. Our results show a dramatic increase in coral δ15N values after 1995, corresponding with the implementation of biological nutrient removal at the nearby Lahaina Wastewater Reclamation Facility (LWRF). High δ15N values are known to be strongly indicative of denitrification and sewage effluent, corroborating a previously suggested link between local wastewater injection and degradation of the reef environment. This record demonstrates the power of coral skeletal δ15N as a tool for evaluating nutrient dynamics within coral reef environments.

Discovery of an Extensive Deep-Sea Fossil Serpulid Reef Associated With a Cold Seep, Santa Monica Basin, CaliforniaTable_1.docx - Georgieva, Magdalena N.; Paull, Charles K.; Little, Crispin T. S.; McGann, Mary; Sahy, Diana; Condon, Daniel; Lundsten, Lonny; Pewsey, Jack; Caress, David W.; Vrijenhoek, Robert C. (Frontiers in Marine Science, 2019)
Multibeam bathymetric mapping of the Santa Monica Basin in the eastern Pacific has revealed the existence of a number of elevated bathymetric features, or mounds, harboring cold seep communities. During 2013–2014, mounds at ∼600 m water depth were observed for the first time and sampled by Monterey Bay Aquarium Research Institute’s ROV Doc Ricketts. Active cold seeps were found, but surprisingly one of these mounds was characterized by massive deposits composed of fossil serpulid worm tubes (Annelida: Serpulidae) exhibiting various states of mineralization by authigenic carbonate. No living serpulids with equivalent tube morphologies were found at the site; hence the mound was termed “Fossil Hill.” In the present study, the identity of the fossil serpulids and associated fossil community, the ages of fossils and authigenic carbonates, the formation of the fossil serpulid aggregation, and the geological structure of the mound are explored. Results indicate that the tubes were most likely made by a deep-sea serpulid lineage, with radiocarbon dating suggesting that they have a very recent origin during the Late Pleistocene, specifically to the Last Glacial Maximum ∼20,000 years ago. Additional U-Th analyses of authigenic carbonates mostly corroborate the radiocarbon dates, and also indicate that seepage was occurring while the tubes were being formed. We also document similar, older deposits along the approximate trajectory of the San Pedro Basin Fault. We suggest that the serpulid tube facies formed in situ, and that the vast aggregation of these tubes at Fossil Hill is likely due to a combination of optimal physical environmental conditions and chemosynthetic production, which may have been particularly intense as a result of sea-level lowstand during the Last Glacial Maximum.

Examining Coastal Dynamics and Archaeological Site Evidence at a Drowned Cirque Basin Influenced by Earthquakes and Little Ice Age Glaciation - Maio, Christopher V.; Crowell, Aron L.; Sullivan, Richard M.; Buzard, Richard M.; Whitley, Matthew A.; Bogardus, Reyce C.; Wit, Cary W. de (Journal of Coastal Research, 2019)
This study contributes baseline information regarding the framework geology, drivers of coastal change, and archaeological record along the fjord-indented coastlines of southcentral Alaska. Field data were collected in July 2015 from James Lagoon, a 30-m-deep drowned cirque valley adjacent to McCarty Fjord in the Nuka Bay region of Kenai Fjords National Park. A 1790 CE terminal moraine deposited by McCarty Glacier extends across the cirque opening and delimits the lagoon. Acoustic surveys of the lagoon reveal bedrock overlain by deltaic, lacustrine, and marine facies containing beds that indicate past submarine landslides. Lagoon and marsh sediment cores contain coarse sand horizons interbedded with silt and peat, evidence of repeated low-frequency, high-intensity events. The largest of the event beds in the marine cores occurs near the surface and is likely associated with the 1964 Great Alaska Earthquake (moment magnitude 9.2). Trees killed during the 1964 earthquake fringe the coastline and indicate ∼2 m of coseismic subsidence. Radiocarbon ages of five exposed subfossil stumps indicate two pre-1964 subsidence events occurring between 1710 and 1789 and 1078 and 1125 median probability calendar year CE (cal CE). A Sugpiaq culture archaeological site dated to 1565 cal CE existed on the western shore of James Lagoon in the interval between these two events, possibly for proximity to an ice floe harbor seal rookery at McCarty Glacier. Archaeological site elevation above mean high water at James Lagoon and around Nuka Bay is inversely related to the extent of cumulative site erosion caused by coastal submergence during the last two great earthquakes. These combined findings lay the groundwork for future research and provide context to ongoing coastal hazards and their effects on cultural resources.

First record of the extinct ground sloth, Megalonyx jeffersonii, (Xenarthra, Megalonychidae) from New York and contributions to its paleoecology - McDonald, H. Gregory; Feranec, Robert S.; Miller, Norton (Quaternary International, 2019)
The first record of the Jefferson ground sloth, Megalonyx jeffersonii, in New York is reported. The specimen consists of a partial synsacrum recovered from a peat deposit near Newburgh, Orange County. Compared to other synsacra of Megalonyx, the number of vertebrae is anomalous with one less caudal vertebra than expected. Stable isotope analysis of the bone shows a δ13C value of 20.5‰ and implies a diet of only C3 plants. The specimen has a radiocarbon date of 11,450 ± 55 BP indicating the presence of this taxon in the region immediately prior to the extinction of the North American Pleistocene megafauna.
Keywords: Megalonyx jeffersonii; New York; Stable isotopes; Synsacrum

Four centuries of vegetation change in the mid-elevation Andean forests of Ecuador - Huisman, Seringe N.; Bush, Mark B.; McMichael, Crystal N. H. (Vegetation History and Archaeobotany, 2019)
Mid-elevation Andean ecosystems have immense species richness and endemism. Taxonomic composition is known to change through time on the eastern slopes of the Andes as a result of climatic change and disturbance events, both natural and by human actions. Fossil phytoliths can capture local scale vegetation changes, especially among monocotyledonous plants. Phytolith production is high in grasses and palms, plant groups that are particularly sensitive to climatic changes and disturbance events in Andean ecosystems. Here, we reconstruct four centuries of local-scale vegetation change and the corresponding fire history from lake sediment records retrieved from Lagunas Cormorán and Chimerella, located at ca. 1,700 m a.s.l. in the mid-elevation Andean forests of eastern Ecuador. The charcoal analysis of the lake sediments showed no sign of past fires, and no evidence of cultivation was found at either lake. The phytolith assemblages indicated changes in the relative abundances of palms, grasses and trees over the last few centuries, suggesting that mid-elevation Andean phytolith assemblages are sensitive to local scale vegetation dynamics. The largest change in vegetation occurred at the end of the Little Ice Age, at which point the diversity of palm phytoliths decreases. These phytolith assemblages are probably responding to changes in the cloud base position through time, which strongly influences the distributions of many plants and animals.

Four Major Holocene Earthquakes on the Reelfoot Fault Recorded by Sackungen in the New Madrid Seismic Zone, USA - Gold, Ryan D.; DuRoss, Christopher B.; Delano, Jaime E.; Jibson, Randall W.; Briggs, Richard W.; Mahan, Shannon A.; Williams, Robert A.; Corbett, D. Reide (Journal of Geophysical Research: Solid Earth, 2019)
Three sequences of well‐documented, major ~M7+ earthquakes (1811–1812, ~1450, and ~900 CE) in the New Madrid seismic zone, USA, contribute significantly to seismic hazard in the region. However, it is unknown whether this <550‐year recurrence interval has been constant throughout the Holocene given limited geomorphic evidence of prior earthquakes. We extend the record of paleoearthquakes along the Reelfoot fault via investigation of ridgetop gravitational failure features, interpreted as sackungen. The sackungen occur in bluffs along the eastern margin of the Mississippi River floodplain and are concentrated near (<15 km) the southwest dipping Reelfoot reverse fault. A paleoseismic trench excavated across sackungen at the Paw Paw site exposed four packages of colluvial sediment that postdate 30‐ to 11‐ka Peoria Loess. We interpret the colluvial packages to have been deposited following episodic failure of the sackungen as a result of strong ground motions from the following sequence of earthquakes: event 4, 1640 ± 1730 BCE; event 3, 270 ± 670 CE; event 2, 1430 ± 380 CE; and event 1, 1810 ± 50 CE (2 sigma). Event timing corresponds to previously documented earthquakes and represents the longest archive of paleoearthquakes on the Reelfoot fault. If the trenched sackungen record all major Reelfoot fault earthquakes, our observations in combination with prior investigations indicate a period of quiescence from at least 11 to 4.4 ka, followed by four major seismic events culminating in the 1811–1812 CE sequence. This clustered earthquake recurrence pattern helps place bounds on seismic hazard and geodynamic models in the New Madrid seismic zone.

Glacial geology and cosmogenic-nuclide exposure ages from the Tucker Glacier - Whitehall Glacier confluence, northern Victoria Land, Antarctica - Balco, Greg; Todd, Claire; Goehring, Brent M.; Moening-Swanson, Isaac; Nichols, Keir (American Journal of Science, 2019)
We describe glacial-geological observations and cosmogenic-nuclide exposure ages from the vicinity of the present grounding line of Tucker Glacier, a large alpine glacier flowing from the mountains of northern Victoria Land, East Antarctica, into the outer Ross Sea. These data are relevant for constraining the extent of ice sheet expansion and retreat in the Ross Sea, and associated eustatic sea level impact, between the Last Glacial Maximum (LGM) and the present. In addition, a terrestrial geological record of ice thickness change from this region could provide evidence for or against the hypothesis that rapid eustatic sea-level rise during meltwater pulse 1A (“MWP-1A”) at 14.6 ka was in part the result of rapid, large-scale thinning or breakup of a marine-based portion of the LGM ice sheet in the outer Ross Sea. Glacial-geological observations, exposure ages on glacial deposits, and a novel application of in-situ-produced cosmogenic 14C in quartz-bearing bedrock to identify the limits of LGM ice cover in the absence of direct geomorphic evidence, show that Tucker Glacier near its present grounding line was 300 to 350 m thicker than present during the LGM and thinned steadily between 17 to 5 ka. The largest possible rapid thickness change in the time period 14 to 15 ka that could be accommodated by the exposure-age data is ∼50 m, which is a small fraction of that predicted for the western Ross Sea by model simulations of the Antarctic contribution to MWP-1A. There do exist possible scenarios in which hypothesized marine ice sheet collapse in the outer Ross Sea during MWP-1A might not be recorded by ice thickness changes at Tucker Glacier. However, our record of ice thickness changes spanning this time period is the closest such record to the outer Ross Sea that is likely to exist, and it agrees with all exposure-age deglaciation chronologies from other regions of the Ross embayment in providing no evidence for such an event.
Keywords: Antarctica; cosmogenic-nuclide geochemistry; exposure-dating; glacial geology; Last glacial maximum; Ross Sea; Tucker Glacier; Victoria Land

Holocene paleodepositional changes reflected in the sedimentary microbiome of the Black Sea - More, Kuldeep D.; Giosan, Liviu; Grice, Kliti; Coolen, Marco J. L. (Geobiology, 2019)
Subsurface microbial communities are generally thought to be structured through in situ environmental conditions such as the availability of electron acceptors and donors and porosity, but recent studies suggest that the vertical distribution of a subset of subseafloor microbial taxa, which were present at the time of deposition, were selected by the paleodepositional environment. However, additional highly resolved temporal records of subsurface microbiomes and paired paleoenvironmental reconstructions are needed to justify this claim. Here, we performed a highly resolved shotgun metagenomics survey to study the taxonomic and functional diversity of the subsurface microbiome in Holocene sediments underlying the permanently stratified and anoxic Black Sea. Obligate aerobic bacteria made the largest contribution to the observed shifts in microbial communities associated with known Holocene climate stages and transitions. This suggests that the aerobic fraction of the subseafloor microbiome was seeded from the water column and did not undergo post-depositional selection. In contrast, obligate and facultative anaerobic bacteria showed the most significant response to the establishment of modern-day environmental conditions 5.2 ka ago that led to a major shift in planktonic communities and in the type of sequestered organic matter available for microbial degradation. No significant shift in the subseafloor microbiome was observed as a result of environmental changes that occurred shortly after the marine reconnection, 9 ka ago. This supports the general view that the marine reconnection was a gradual process. We conclude that a high-resolution analysis of downcore changes in the subseafloor microbiome can provide detailed insights into paleoenvironmental conditions and biogeochemical processes that occurred at the time of deposition.
Keywords: geomicrobiology; palaeo-environment; paleoecology; sedimentary metagenomes; subsurface microbiome; sulfur cycle.

Holocene Vegetation, Climate, and Carbon History on Western Kodiak Island, Alaska - Peteet, Dorothy M.; Nichols, Jonathan E.; Mann, Daniel H. (Frontiers in Earth Science, 2019)
At Phalarope Pond, western Kodiak Island, a multidisciplinary study using pollen and spores, macrofossils, stable isotopes, and carbon accumulation provides the Holocene vegetation and climate history following the deglaciation that began over 16,000 cal years ago (yr BP). Following a cold and dry Younger Dryas, a warm and wet early Holocene was characterized by abundant ferns in a sedge tundra environment with maximum carbon accumulation, similar to high latitude peatlands globally. About 8,700 cal yr BP sedge and ferns declined and climate remained warm as drier conditions prevailed, limiting carbon sequestration. The abrupt shift in D/H isotopes of about 60% indicates a shift to cooler conditions or a more distal moisture source. Neoglaciation beginning about 3,700 cal yr BP is evident from increases in Artemisia, Empetrum and Betula, signifying cooler conditions, while Alnus declines, paralleling regional trends.

A human role in Andean megafaunal extinction? - Raczka, M.F.; Mosblech, N.A.; Giosan, L.; Valencia, B.G.; Folcik, A.M.; Kingston, M.; Baskin, S.; Bush, M.B. (Quaternary Science Reviews, 2019)
A new fossil pollen, Sporormiella, and sediment chemistry record from Lake Llaviucu, Ecuador, spanning the period from 16,280–9000 years Before Present, provides a high-resolution record of paleoecological change in the high Andes. The deglacial transition from super-páramo through páramo grasslands, to Andean forest is traced, with near-modern systems being established by c. 11,900 years ago. It is suggested that forest elements probably existed in microrefugial populations close to the ice front. Sporormiella is used as a proxy for megafaunal abundance, and its decline to background levels is inferred to indicate a local extinction event at c. 12,800 years ago. About 1800 years prior to the extinction, charcoal becomes a regular sedimentary component in this very wet valley. An early date for human activity in the valley is suggested, with the direct implication of humans in the extinction of the megafauna.
Keywords: Andes; Deglaciation; Ecuador Extinction; Fossil pollen; Human arrival; Pleistocene megafauna; Sporormiella

Illuminating microbial species‐specific effects on organic matter remineralization in marine sediments - Mahmoudi, Nagissa; Enke, Tim N.; Beaupré, Steven R.; Teske, Andreas P.; Cordero, Otto X.; Pearson, Ann (Environmental Microbiology, 2019)

Implications of radiocarbon ages of organic and inorganic carbon in coastal lakes in Florida for establishing a reliable chronology for sediment-based paleoclimate reconstructionAbstract - Wang, Yang; Das, Oindrila; Xu, Xiaomei; Liu, Jin; Jahan, Shakura; Means, Guy H.; Donoghue, Joseph; Jiang, Shijun (Quaternary Research, 2019)
Coastal lake sediments are valuable paleoclimate archives provided that they can be accurately dated. Here, we report radiocarbon ages of bulk sediment organic matter (OM), plants, shells, particulate OM, and dissolved OM from coastal lakes in Florida. Bulk sediment OM yielded ages that are consistently older than contemporaneous plants and shells, indicating significant radiocarbon deficiencies in sedimentary OM in these lakes. The data show that the OM radiocarbon deficiency varies over time and with location, making it impossible to determine a proper correction factor for radiocarbon ages of bulk sediments from these lakes. As a result, we consider ages obtained from bulk sediment OM from these lakes unreliable. The age reversals in bulk sediment OM observed in the sediment cores are likely caused by rapid increases in erosion and sedimentation resulting from large storm events. The data also show that sedimentation rate can vary considerably within a given lake, implying that an age-depth model established for one core cannot be directly applied to other cores despite their close proximity. Analyses of shells from one of the lakes suggest that fresh/brackish-water shells may serve as a good substrate for radiocarbon dating owing to a small reservoir effect on inorganic carbon.

In situ cosmogenic 3He and 36Cl and radiocarbon dating of volcanic deposits refine the Pleistocene and Holocene eruption chronology of SW Peru - Bromley, Gordon R. M.; Thouret, Jean-Claude; Schimmelpfennig, Irene; Mariño, Jersy; Valdivia, David; Rademaker, Kurt; del Pilar Vivanco Lopez, Socorro; Team, ASTER; Aumaître, Georges; Bourlès, Didier; Keddadouche, Karim (Bulletin of Volcanology, 2019)
Constraining the age of young lavas, which generally fall outside the effective range of traditional geochronology methods, remains a key challenge in volcanology, limiting the development of high-resolution eruption chronologies. We present an in situ cosmogenic 3He and 36Cl surface-exposure chronology, alongside new minimum-limiting 14C ages, documenting young eruptions at five sites in the Western Cordillera, southern Peru. Four 3He-dated lavas on the Nevado Coropuna volcanic complex (hitherto thought to be dormant) indicate that the central dome cluster is young and potentially active; two Holocene lavas on the easternmost dome are the youngest directly dated lavas in Peru to date. East of Coropuna, lava domes and block-lava flows represent the most extensive output to date of Nevado Sabancaya, one of Peru’s most active volcanoes. Two 3He measurements confirm the Holocene age of these deposits and expand the chronology for one of the youngest major lava fields in Peru. 36Cl surface-exposure ages from the Purupurini dome cluster and Nevado Casiri document middle-late-Holocene episodes of effusive activity, while basal 14C ages from a lava-dammed wetland constrain an effusive eruption at Mina Arcata, north of Coropuna, to the late-glacial period. These new data advance the recent Western Cordillera volcanic record whilst demonstrating both the considerable potential and fundamental limitations of cosmogenic surface-exposure methods for such applications.

INFLUENCE OF DIFFERENT ACID TREATMENTS ON THE RADIOCARBON CONTENT SPECTRUM OF SEDIMENTARY ORGANIC MATTER DETERMINED BY RPO/ACCELERATOR MASS SPECTROMETRY - Bao, Rui; McNichol, Ann P.; Hemingway, Jordon D.; Gaylord, Mary C. Lardie; Eglinton, I, Timothy (RADIOCARBON, 2019)
In practice, obtaining radiocarbon (C-14) composition of organic matter (OM) in sediments requires first removing inorganic carbon (IC) by acid-treatment. Two common treatments are acid rinsing and fumigation. Resulting C-14 content obtained by different methods can differ, but underlying causes of these differences remain elusive. To assess the influence of different acid-treatments on C-14 content of sedimentary OM, we examine the variability in C-14 content for a range of marine and river sediments. By comparing results for unacidified and acidified sediments [HCl rinsing (Rinse(HCl)) and HCl fumigation (Fume(HCl))], we demonstrate that the two acid-treatments can affect C-14 content differentially. Our findings suggest that, for low-carbonate samples, Rinse(HCl) affects the Fm values due to loss of young labile organic carbon (OC). Fume(HCl) makes the Fm values for labile OC decrease, leaving the residual OC older. High-carbonate samples can lose relatively old organic components during Rinse(HCl), causing the Fm values of remaining OC to increase. Fume(HCl) can remove thermally labile, usually young, OC and reduce the Fm values. We suggest three factors should be taken into account when using acid to remove carbonate from sediments: IC abundance, proportions of labile and refractory OC, and environmental matrix.

Influence of Different Acid Treatments on the Radiocarbon Content Spectrum of Sedimentary Organic Matter Determined by RPO/Accelerator Mass SpectrometryABSTRACT - Bao, Rui; McNichol, Ann P; Hemingway, Jordon D; Lardie Gaylord, Mary C; Eglinton, Timothy I (Radiocarbon, 2019)
In practice, obtaining radiocarbon (C-14) composition of organic matter (OM) in sediments requires first removing inorganic carbon (IC) by acid-treatment. Two common treatments are acid rinsing and fumigation. Resulting C-14 content obtained by different methods can differ, but underlying causes of these differences remain elusive. To assess the influence of different acid-treatments on C-14 content of sedimentary OM, we examine the variability in C-14 content for a range of marine and river sediments. By comparing results for unacidified and acidified sediments [HCl rinsing (Rinse(HCl)) and HCl fumigation (Fume(HCl))], we demonstrate that the two acid-treatments can affect C-14 content differentially. Our findings suggest that, for low-carbonate samples, Rinse(HCl) affects the Fm values due to loss of young labile organic carbon (OC). Fume(HCl) makes the Fm values for labile OC decrease, leaving the residual OC older. High-carbonate samples can lose relatively old organic components during Rinse(HCl), causing the Fm values of remaining OC to increase. Fume(HCl) can remove thermally labile, usually young, OC and reduce the Fm values. We suggest three factors should be taken into account when using acid to remove carbonate from sediments: IC abundance, proportions of labile and refractory OC, and environmental matrix.

Legacy sediment storage in New England river valleys: Anthropogenic processes in a postglacial landscape - Johnson, Kaitlin M.; Snyder, Noah P.; Castle, Stephanie; Hopkins, Austin J.; Waltner, Mason; Merritts, Dorothy J.; Walter, Robert C. (Geomorphology, 2019)
Legacy sediment associated with erosion from land clearing is a common feature in river valleys of the unglaciated Mid-Atlantic Piedmont region. Here, we quantify the volume of legacy sediment storage in three watersheds in New England, a formerly glaciated region with similar history and intensity of forest clearing and milldam construction during the seventeenth to nineteenth centuries. We combine field observations of bank stratigraphy, radiocarbon dating, and mapping of terraces and floodplains using lidar digital elevation models and other GIS datasets. The 68 km2 South River watershed in western Massachusetts exhibits the most extensive evidence for legacy sediment storage. We visited 18 historic dam sites in the watershed and found field evidence for up to 2.2 m of fine sand and silt legacy sediment storage at 14 of the sites. In the 555 km2 Sheepscot River watershed in coastal Maine, we visited 13 historic dam sites and found likely legacy sediment up to 2.3 m thick at six of the dams. In the 171 km2 upper Charles River watershed in eastern Massachusetts, we investigated 14 dam sites, and found legacy sediment up to 1.8 m thick at two of them. Stratigraphically, we identified the base of fine-grained legacy sediment from a change to much coarser grain size (gravel at most sites) or to glacial lacustrine or marine deposits. Along the Sheepscot River, we observed cut timbers underlying historic sediment at several locations, likely associated with sawmill activities. Only at the Charles River were we able to radiocarbon date the underlying gravel layer (1281–1391 calibrated CE). At no site did we find a buried organic-rich Holocene soil, in contrast to the field relations commonly observed in the Mid-Atlantic region. We use lidar elevation data to map planar terrace extents in each watershed, estimate thickness of remaining legacy sediment found stored behind breached or removed milldams, and estimate volumes of remaining legacy sediment storage in valley bottoms for entire watersheds. The maximum volume of stored legacy sediment estimated for the South, Sheepscot, and upper Charles watersheds is 2.5 × 106 m3, 3.7 × 106 m3, and 2.6 × 104 m3, respectively. These volumes of legacy sediment can be translated to an equivalent thickness of soil eroded from each watershed: 37 mm, 7 mm, and 0.2 mm, respectively. We attribute the variation in presence and thickness of legacy sediment at the New England sites to the existence or absence of upstream sediment supply in the form of thick glacial deposits and to sinks such as lakes and wetlands along valley bottoms. Of the three study watersheds, the South River has the most extensive glacial sediments, fewest sinks, and the most legacy sediment in storage along the river corridor.
Keywords: Anthropogenic sediment; Legacy sedimen; Milldams

Mapping Isotopic and Dissolved Organic Matter Baselines in Waters and Sediments of the Gulf of Mexico - Chanton, Jeffrey P.; Jaggi, Aprami; Radović, Jagoš R.; Rosenheim, Brad E.; Walker, Brett D.; Larter, Stephen R.; Rogers, Kelsey; Bosman, Samantha; Oldenburg, Thomas B. P. (Springer International Publishing, 2019)
The Deepwater Horizon oil spill released petroleum hydrocarbons that were depleted in δ13C and Δ14C at depth into the Gulf of Mexico. Stable-carbon and radiocarbon isotopic values and high-resolution mass spectrometry were used to follow the distributions of this petroleum and to track its transformation into petrocarbon, a term used to describe crude oil or transformed crude oil following biodegradation, weathering, oxygenation, or loss of lighter components. The term petrocarbon includes oil- or methane-derived carbon assimilated or incorporated into microbial biomass or into the food web as well as degraded and undegraded petroleum constituents. Here we report (1) the increase in the relative abundance of oxygen-containing carbon compounds making up the dissolved organic matter (DOM) with increasing depth through the water column, indicating the biodegradation of DOM as it was transported to depth in the water column, (2) the finding of 14C depletion in DOM indicating petrocarbon inputs, and (3) the decrease and subsequent increase of 14C in the isotopic composition of sinking particles indicating the capture of petrocarbon in sediment traps. In addition, we discuss the 14C depletion of this material once it is sedimented to the seafloor and the implications for oil spill budgets of seafloor petrocarbon deposition.
Keywords: Dissolved organic matter; FTICR-MS; Gulf baselines; High-resolution mass spectrometry; organic carbon; radiocarbon; Ramped pyrolysis; Sediment organic matter

The Mighty Susquehanna—Extreme Floods in Eastern North America During the Past Two Millennia - Toomey, Michael; Cantwell, Meagan; Colman, Steven; Cronin, Thomas; Donnelly, Jeffrey; Giosan, Liviu; Heil, Clifford; Korty, Robert; Marot, Marci; Willard, Debra (Geophysical Research Letters, 2019)
The hazards posed by infrequent major floods to communities along the Susquehanna River and the ecological health of Chesapeake Bay remain largely unconstrained due to the short length of streamgage records. Here we develop a history of high‐flow events on the Susquehanna River during the late Holocene from flood deposits contained in MD99‐2209, a sediment core recovered in 26 m of water from Chesapeake Bay near Annapolis, Maryland, United States. We identify coarse‐grained deposits left by Hurricane Agnes (1972) and the Great Flood of 1936, as well as during three intervals that predate instrumental flood records (~1800–1500, 1300–1100, and 400–0 CE). Comparison to sedimentary proxy data (pollen and ostracode Mg/Ca ratios) from the same core site indicates that prehistoric flooding on the Susquehanna often accompanied cooler‐than‐usual winter/spring temperatures near Chesapeake Bay—typical of negative phases of the North Atlantic Oscillation and conditions thought to foster hurricane landfalls along the East Coast.

Millennial-scale fluctuations in water volume transported by the Tsushima Warm Current in the Japan Sea during the Holocene - Horikawa, Keiji; Kodaira, Tomohiro; Ikehara, Ken; Murayama, Masafumi; Zhang, Jing (Global and Planetary Change, 2019)
Cyclic changes in volume transport of the Tsushima Warm Current (TWC) have been argued from diatom records in the southern Japan Sea off the Japanese islands during the Holocene. Although this phenomenon has not yet been confirmed by various proxy data, determining whether or not these oceanographic changes occurred is crucial for clarifying the nature of oceanographic changes in the southern Japan Sea. Here, we conducted a coupled analysis of Mg/Ca ratios and oxygen isotopes (δ18O) in shallow-dwelling Neogloboquadrina incompta from 13 core-top sediments in southern Japan, and developed a new equation for Mg/Ca temperature calibration (Mg/Ca = 0.311 × exp (0.07 × T)) as a proxy for spring sea surface temperature (SST). Using the newly developed, species-specific Mg/Ca-paleothermometry, we reconstructed SST variability for the past 6800 years from core YK10-7-PC09 in the southern Japan Sea. The Mg/Ca-derived SST record clearly represented five warmer periods at 6200–6000, 4900–4500, 4200–3800, 2600–2100, and 900–400 cal. year BP, almost consistent with previously published diatom records. These warmer events also corresponded to the periods in which warm molluscan assemblages increased at the northern end of the TWC, suggesting that periods of higher SST can be seen as reflecting the increased volume transport of the TWC. We interpreted the results of a model study showing that higher solar irradiance provoked positive Arctic Oscillation (AO)-like spatial patterns and the negative phase of the Pacific Decadal Oscillation (PDO) to mean that increased (reduced) TWC volume transport on the multi-centennial to millennial time scales was caused by high (low) solar insolation via a potential link between AO and PDO. Given that larger and more frequent volcanic eruptions occurred in the mid Holocene than in the late Holocene, volcanic forcing on the TWC volume transport changes would have been more significant during the former, as seen in the highly variable SST from this period and distinct decreases in SST around ~5900 cal. year BP and ~6400 cal. year BP. The millennial-scale fluctuations seen in SSTs in the southern Japan Sea would have had a large impact on the evolution of vegetation and human adaptation in the northern Japanese islands, adjacent to the Japan Sea, over the last 6800 years.
Keywords: Holocene; Mg/Ca-derived; Neogloboquadrina incompta; sea-surface temperature; Solar forcing; The Japan Sea; Tsushima; Warm Current

New AMS Dates for Verteba Cave and Stable Isotope Evidence of Human Diet in The Holocene Forest-Steppe, UkraineABSTRACT - Ledogar, Sarah H; Karsten, Jordan K; Madden, Gwyn D; Schmidt, Ryan; Sokohatskyi, Mykhailo P; Feranec, Robert S (Radiocarbon, 2019)
Excavations at several locations in Verteba Cave have uncovered a large amount of human skeletal remains in association with faunal bones and Tripolye material culture. We aim to establish radiocarbon (14C) dates for eight sites and to evaluate whether these deposits are singular events, or slow accumulations over time. 14C measurements, along with stable carbon and nitrogen isotope data from human and faunal remains, were collected from 18 specimens. Stable isotope values were used to evaluate human and animal diet, and whether freshwater reservoir effects offset measured dates. We found diets of the sampled species had limited to no influence from freshwater resources. Human diet appears to be dominated by terrestrial plants and herbivores. Four new sites were identified as Eneolithic. Comparisons of dates from top and bottom strata for two sites (7 and 20) reveal coeval dates, and we suggest that these deposits represent discrete events rather than slow continuous use. Lastly, we identified dates from the Mesolithic (8490±45 BP, 8765±30 BP), Iron Age (2505±20 BP), Slavic state era (1315±25 BP), and Medieval Period (585±15 BP), demonstrating periodic use of the cave by humans prior to and after the Eneolithic.
Keywords: archaeometry; cave burials; Eastern Europe; funerary ritual; Tripolye culture

On the Origin of Aged Sedimentary Organic Matter Along a River‐Shelf‐Deep Ocean Transect - Bao, Rui; Zhao, Meixun; McNichol, Ann; Wu, Ying; Guo, Xinyu; Haghipour, Negar; Eglinton, Timothy I. (Journal of Geophysical Research: Biogeosciences, 2019)
To assess the influences of carbon sources and transport processes on the C-14 age of organic matter (OM) in continental margin sediments, we examined a suite of samples collected along a river-shelf-deep ocean transect in the East China Sea (ECS). Ramped pyrolysis-oxidiation was conducted on suspended particulate matter in the Yangtze River and on surface sediments from the ECS shelf and northern Okinawa Trough. C-14 ages were determined on OM decomposition products within different temperature windows. These measurements suggest that extensive amounts of pre-old (i.e., millennial age) organic carbon (OC) are subject to degradation within and beyond the Yangtze River Delta, and this process is accompanied by an exchange of terrestrial and marine OM. These results, combined with fatty acid concentration data, suggest that both the nature and extent of OM preservation/degradation as well as the modes of transport influence the C-14 ages of sedimentary OM. Additionally, we find that the age of (thermally) refractory OC increases during across-shelf transport and that the age offset between the lowest and highest temperature OC decomposition fractions also increases along the shelf-to-trough transect. Amplified interfraction spread or C-14 heterogeneity is the greatest in the Okinawa Trough. Aged sedimentary OM across the transect may be a consequence of several reasons including fossil OC input, selective degradation of younger OC, hydrodynamic sorting processes, and aging during lateral transport. Consequently, each of them should be considered in assessing the C-14 results of sedimentary OM and its implications for the carbon cycle and interpretation of sedimentary records.
Keywords: Carbon cycle; hydrodynamic processes; organic carbon; radiocarbon; sediments

Paleoseismic Investigation of the Levan and Fayette Segments of the Wasatch Fault Zone, Juab and Sanpete Counties, Utah - McDonald, Greg N.; Hiscock, Adam I.; Hylland, Micheal D. (Utah Geological Survey, 2019)

Petrocarbon evolution: Ramped pyrolysis/oxidation and isotopic studies of contaminated oil sediments from the Deepwater Horizon oil spill in the Gulf of Mexico - Rogers, Kelsey L.; Bosman, Samantha H.; Lardie-Gaylord, Mary; McNichol, Ann; Rosenheim, Brad E.; Montoya, Joseph P.; Chanton, Jeffrey P. (PLOS ONE, 2019)
Hydrocarbons released during the Deepwater Horizon (DWH) oil spill weathered due to exposure to oxygen, light, and microbes. During weathering, the hydrocarbons' reactivity and lability was altered, but it remained identifiable as "petrocarbon" due to its retention of the distinctive isotope signatures (C-14 and C-13) of petroleum. Relative to the initial estimates of the quantity of oil-residue deposited in Gulf sediments based on 2010-2011 data, the overall coverage and quantity of the fossil carbon on the seafloor has been attenuated. To analyze recovery of oil contaminated deep-sea sediments in the northern Gulf of Mexico we tracked the carbon isotopic composition (C-13 and C-14, radiocarbon) of bulk sedimentary organic carbon through time at 4 sites. Using ramped pyrolysis/oxidation, we determined the thermochemical stability of sediment organic matter at 5 sites, two of these in time series. There were clear differences between crude oil (which decomposed at a lower temperature during ramped oxidation), natural hydrocarbon seep sediment (decomposing at a higher temperature; Delta C-14 = -189 parts per thousand) and our control site (decomposing at a moderate temperature; Delta C-14 = -189 parts per thousand), in both the stability (ability to withstand ramped temperatures in oxic conditions) and carbon isotope signatures. We observed recovery toward our control site bulk Delta C-14 composition at sites further from the wellhead in similar to 4 years, whereas sites in closer proximity had longer recovery times. The thermographs also indicated temporal changes in the composition of contaminated sediment, with shifts towards higher temperature CO2 evolution over time at a site near the wellhead, and loss of higher temperature CO2 peaks at a more distant site.
Keywords: C-14 ANALYSES; MARINE SNOW; degradation; fractionation; organic-matter; POLYCYCLIC AROMATIC-HYDROCARBONS; MICROBIAL COMMUNITY RESPONSE; radiocarbon; STABLE CARBON; surface sediments

Salt marsh ecosystem restructuring enhances elevation resilience and carbon storage during accelerating relative sea-level rise - Gonneea, Meagan Eagle; Maio, Christopher V.; Kroeger, Kevin D.; Hawkes, Andrea D.; Mora, Jordan; Sullivan, Richard; Madsen, Stephanie; Buzard, Richard M.; Cahill, Niamh; Donnelly, Jeffrey P. (Estuarine, Coastal and Shelf Science, 2019)
Salt marshes respond to sea-level rise through a series of complex and dynamic bio-physical feedbacks. In this study, we found that sea-level rise triggered salt marsh habitat restructuring, with the associated vegetation changes enhancing salt marsh elevation resilience. A continuous record of marsh elevation relative to sea level that includes reconstruction of high-resolution, sub-decadal, marsh elevation over the past century, coupled with a lower-resolution 1500-year record, revealed that relative sea-level rose 1.5 ± 0.4 m, following local glacial isostatic adjustment (1.2 mm/yr). As sea-level rise has rapidly accelerated, the high marsh zone dropped 11 cm within the tidal frame since 1932, leading to greater inundation and a shift to flood- and salt-tolerant low marsh species. Once the marsh platform fell to the elevation favored by low-marsh Spartina alterniflora, the elevation stabilized relative to sea level. Currently low marsh accretion keeps pace with sea-level rise, while present day high marsh zones that have not transitioned to low marsh have a vertical accretion deficit. Greater biomass productivity, and an expanding subsurface accommodation space favorable for salt marsh organic matter preservation, provide a positive feed-back between sea-level rise and marsh platform elevation. Carbon storage was 46 ± 28 g C/m2/yr from 550 to 1800 CE, increasing to 129 ± 50 g C/m2/yr in the last decade. Enhanced carbon storage is controlled by vertical accretion rates, rather than soil carbon density, and is a direct response to anthropogenic eustatic sea-level rise, ultimately providing a negative feedback on climate warming.
Keywords: 14-Carbon; accretion; Carbon storage; Elevation; Salt marsh; Sea level index point; sea-level rise

Sea Level Rise Explains Changing Carbon Accumulation Rates in a Salt Marsh Over the Past Two Millennia - McTigue, Nathan; Davis, Jenny; Rodriguez, Antonio B.; McKee, Brent; Atencio, Anna; Currin, Carolyn (Journal of Geophysical Research: Biogeosciences, 2019)
High rates of carbon burial observed in wetland sediments have garnered attention as a potential “natural fix” to reduce the concentration of carbon dioxide (CO2) in Earth's atmosphere. A carbon accumulation rate (CAR) can be determined through various methods that integrate a carbon stock over different time periods, ranging from decades to millennia. Our goal was to assess how CAR changed over the lifespan of a salt marsh. We applied a geochronology to a series of salt marsh cores using both 14C and 210Pb markers to calculate CARs that were integrated between 35 and 2,460 years before present. CAR was 39 g C·m−2·year−1 when integrated over millennia but was upward of 148 g C·m−2·year−1 for the past century. We present additional evidence to account for this variability by linking it to changes in relative sea level rise (RSLR), where higher rates of RSLR were associated with higher CARs. Thus, the CAR calculated for a wetland should integrate timescales that capture the influence of contemporary RSLR. Therefore, caution should be exercised not to utilize a CAR calculated over inappropriately short or long timescales as a current assessment or forecasting tool for the climate change mitigation potential of a wetland.
Keywords: Carbon storage; Geochronology; Salt marsh; sea‐level rise

Sedimentary Data from Grand Bay, Alabama/Mississippi, 2014–2016 - Marot, Marci; Smith, Christopher G.; McCloskey, Terrence A.; Locker, Stanley D. (U.S. Geological Survey, 2019)
This data release is an archive of sedimentary field and laboratory analytical data collected in Grand Bay, Alabama/Mississippi from 2014-2016 by scientists from the U.S. Geological Survey St. Petersburg Coastal and Marine Science Center (USGS SPCMSC). This work, a component of the SPCMSC’s Sea-level and Storm Impacts on Estuarine Environments and Shorelines (SSIEES) project, provides the necessary data to quantify sedimentation rates and sediment sources for the marsh and estuary. The SSIEES project objective is to evaluate the exchange of sediment material between the marsh and estuary due to extreme storms and sea-level rise. Micropaleontological data from select cores and surface samples are available in Haller and others (2018, https://doi.org/10.5066/F7MC8X5F, https://doi.org/10.5066/F7445KSG). Single-beam bathymetry of Grand Bay proper and multi-beam bathymetry of several marsh-edge eroding shorelines are reported in Dewitt and others (2017, https://doi.org/10.3133/ds1070) and Stalk and others (2018, https://doi.org/10.5066/F7MC8Z9N), respectively. Subbottom and sidescan sonar data for Grand Bay proper are reported in Locker and others (2018, https://doi.org/10.5066/P9374DKQ). This publication includes data for the sediment cores and surface sediments taken in Grand Bay marsh and estuary during five sampling periods of this study, which were designated as USGS Field Activity Numbers (FAN) 2014-323-FA (project ID 14CCT01), 2015-315-FA (project ID 15CCT02), 2016-331-FA (project ID 16CCT03), 2016-348-FA (project ID 16CCT04), and 2016-358-FA (project ID 16CCT07). Data products include: GPS-derived site locations and elevations; core photographs, logs, and x-radiographs; lithologic, radiochemical, elemental composition, stable isotopic composition, and radiocarbon data; and Federal Geographic Data Committee (FGDC) metadata. Note: This data release was versioned on April 28, 2020. Please see the Suggested Citation section for details.

Selective Preservation of Coccolith Calcite in Ontong‐Java Plateau Sediments - Subhas, Adam V.; McCorkle, Daniel C.; Quizon, Alex; McNichol, Ann P.; Long, Matthew H. (Paleoceanography and Paleoclimatology, 2019)
Keywords: BIOMINERALIZATION; caco3 dissolution; CEARA RISE; dissolution kinetics; IN-SITU MEASUREMENTS; DEEP-SEA CARBONATES; PLANKTONIC-FORAMINIFERA; EQUATORIAL PACIFIC; surface sediments; WATER INTERFACE

Significance of Perylene for Source Allocation of Terrigenous Organic Matter in Aquatic SedimentsSignificance of Perylene for Source Allocation of Terrigenous Organic Matter in Aquatic Sediments - Hanke, Ulrich M.; Lima-Braun, Ana L.; Eglinton, Timothy I.; Donnelly, Jeffrey P.; Galy, Valier; Poussart, Pascale; Hughen, Konrad; McNichol, Ann P.; Xu, Li; Reddy, Christopher M. (Environmental Science & Technology, 2019)
Perylene is a frequently abundant, and sometimes the only polycyclic aromatic hydrocarbon (PAH) in aquatic sediments, but its origin has been subject of a longstanding debate in geochemical research and pollutant forensics because its historical record differs markedly from typical anthropogenic PAHs. Here we investigate whether perylene serves as a source-specific molecular marker of fungal activity in forest soils. We use a well-characterized sedimentary record (1735-1999) from the anoxic-bottom waters of the Pettaquamscutt River basin, RI to examine mass accumulation rates and isotope records of perylene, and compare them with total organic carbon and the anthropogenic PAH fluoranthene. We support our arguments with radiocarbon (14C) data of higher plant leaf-wax n-alkanoic acids. Isotope-mass balance-calculations of perylene and n-alkanoic acids indicate that ∼40% of sedimentary organic matter is of terrestrial origin. Further, both terrestrial markers are pre-aged on millennial time-scales prior to burial in sediments and are insensitive to elevated 14C concentrations following nuclear weapons testing in the mid-20th Century. Instead, changes coincide with enhanced erosional flux during urban sprawl. These findings suggest that perylene is definitely a product of soil-derived fungi, and a powerful chemical tracer to study the spatial and temporal connectivity between terrestrial and aquatic environments.

Sortable silt records of intermediate-depth circulation and sedimentation in the Southwest Labrador Sea since the Last Glacial Maximum - Hoffmann, Sharon S.; Dalsing, Risa E.; Murphy, Sarah C. (Quaternary Science Reviews, 2019)
The Labrador Sea is a vital region for the Atlantic Meridional Overturning Circulation (AMOC), where overflow waters from the Nordic Seas mix with locally produced Labrador Sea Water (LSW), before exiting to the interior of the Atlantic Ocean. The dynamical sedimentary proxy of mean sortable silt size () can give information on past changes in deep water circulation speed and the strength of AMOC. We have produced records from two core sites at depths between 1500 and 2000 m on the continental slope east of Newfoundland, to reconstruct changes in intermediate depth water circulation speed, including Glacial North Atlantic Intermediate Water and Labrador Sea Water over the past 22,000 years. Increases in appear to coincide with much of the deglaciation as well as the mid-late Holocene. End-member modeling suggests that ice-rafted debris (IRD) is an important factor in interpreting during the deglaciation. We find that a robust increase in is likely unrelated to IRD during the past 5 ka, and probably reflects increased flow at intermediate depths due to local production of LSW strengthening as Nordic Seas overflows weakened at this depth. Our results highlight both the complications of producing records in IRD-rich, slope environments and the promise that this proxy nevertheless has for reconstructing dynamical changes in deep ocean currents.
Keywords: Holocene; labrador sea; paleoceanography; Sedimentology-marine cores

Sources of carbon to suspended particulate organic matter in the northern Gulf of Mexico - Rogers, Kelsey L.; Bosman, Samantha H.; Weber, Sarah; Magen, Cedric; Montoya, Joseph P.; Chanton, Jeffrey P. (Elem Sci Anth, 2019)
Suspended particulate organic carbon (POCsusp) in the Gulf of Mexico is unique compared to other seas and oceans. In addition to surface primary production, isotopic analysis indicates that microbial cycling of oil and riverine inputs are primary sources of carbon to POCsusp in the Gulf. To characterize POCsusp from seep sites and non-seep north central Gulf (NCG) sites potentially affected by the Deepwater Horizon (DWH) spill, we analyzed 277 and 123 samples for δ13C and Δ1C signatures, respectively. Depth, partitioned into euphotic (300 m), was the main driver of spatial δ13C differences, with deep depths exhibiting 13C depletion. Both deep depths and proximity to sources of natural seepage resulted in 14C depletion. A two-endmember mixing model based on Δ14C indicated that sources to POCsusp were 14–29% fossil carbon at NCG sites and 19–57% at seep sites, with the balance being modern surface production. A six-component Bayesian mixing model MixSIAR, using both 13C and 14C, suggested that riverine inputs were an important carbon source to POCsusp contributing 34–46%. The influence of seeps was localized. Below the euphotic zone at seep sites, 46 ± 5% (n = 9) of the carbon in POCsusp was derived from environmentally degraded, transformed oil; away from seeps, transformed oil contributed 15 ± 4% (n = 39). We hypothesized that, at NCG sites removed from hydrocarbon seep sources, isotopic signatures would be depleted following the spill and then shift towards background-like enriched values over time. At deep depths we observed decreasing Δ14C signatures in POCsusp from 2010 to 2012, followed by isotopic enrichment from 2012 to 2014 and a subsequent recovery rate of 159‰ per year, consistent with this hypothesis and with biodegraded material from DWH hydrocarbons contributing to POCsusp.

Temperature-controlled tundra fire severity and frequency during the last millennium in the Yukon-Kuskokwim Delta, Alaska - Sae-Lim, Jarunetr; Russell, James M; Vachula, Richard S; Holmes, Robert M; Mann, Paul J; Schade, John D; Natali, Susan M (The Holocene, 2019)
Wildfire is an important disturbance to Arctic tundra ecosystems. In the coming decades, tundra fire frequency, intensity, and extent are projected to increase because of anthropogenic climate change. To more accurately predict the effects of climate change on tundra fire regimes, it is critical to have detailed knowledge of the natural frequency and extent of past wildfires and how they responded to past climate variability. We present analyses of fire frequency and temperature from a lake sediment core from the Yukon-Kuskokwim (YK) Delta. Our ca. 1000 macroscopic charcoal record shows more frequent but possibly less severe tundra fires during the first half of the last millennium, whereas less frequent, possibly more severe fires characterize the latter half. Our temperature reconstruction, based on distributional changes of branched glycerol dialkyl glycerol tetraethers (brGDGTs), shows slightly warmer conditions from ca. AD 1000 to 1500, and cooler conditions thereafter (ca. AD 1500 to 2000), suggesting that fire frequency increases when climate is relatively warmer in this region. When wildfires occur more frequently, fire severity may decrease because of limited biomass (fuel source) accumulating between fires. The data suggest that tundra ecosystems are highly sensitive to climate change, and that a warmer climate, which is predicted to develop in the near future, will result in more frequent tundra wildfires.
Keywords: alaska; Arctic; charcoal; glycerol dialkyl glycerol tetraethers (GDGTs); late-holocene; Paleoclimate; Paleofire

Temporal constraints on lateral organic matter transport along a coastal mud belt - Bao, Rui; Zhao, Meixun; McNichol, Ann; Galy, Valier; McIntyre, Cameron; Haghipour, Negar; Eglinton, Timothy I. (Organic Geochemistry, 2019)
Constraints on timescales of lateral transport of sedimentary organic carbon (OC) over continental shelves and associated influences on the distribution and abundance of OC remain sparse. Preferential degradation of labile, young OC during lateral transport results in apparent “diagenetic aging” of OC. Additionally, sediment translocation can also result in “transport time-associated aging” of associated organic matter (OM) as a function of the lateral transport time (LTT). Here, we use a coupled thermal decomposition and radiocarbon (14C) approach to constrain timescales of lateral transport and concomitant loss of OC associated with different grain size fractions of sediments collected from two locations ∼275 km apart along a dispersal pathway on the inner shelf of the East China Sea. The 14C age contrasts between corresponding thermal fractions are used to distinguish these two components of sedimentary OM “aging”. To minimize interferences from hydrodynamic sorting and diagenetic aging of OC accompanying lateral transport, we assess 14C age differences of decomposition products from the most thermally-refractory OC components associated with specific grain size fractions between locations. We show that LTTs vary among different grain size fractions, and examine relationships between LTTs and sedimentary OC loss in order to assess the decomposition of OC as a consequence of lateral transport. We suggest that the decomposition of OC associated with protracted lateral transport exerts a strong influence on OC burial efficiency, with broad implications for carbon cycling over continental shelves.
Keywords: 14C aging; Continental shelf seas; East China Sea; Mud belt; organic matter; Sediment resuspension

Temporal deconvolution of vascular plant-derived fatty acids exported from terrestrial watersheds - Vonk, Jorien E.; Drenzek, Nicholas J.; Hughen, Konrad A.; Stanley, Rachel H.R.; McIntyre, Cameron; çon, Daniel B.; Giosan, Liviu; Southon, John R.; Santos, Guaciara M.; Druffel, Ellen R.M.; Andersson, August A.; öld, Martin; et al. (Geochimica et Cosmochimica Acta, 2019)
Relatively little is known about the amount of time that lapses between the photosynthetic fixation of carbon by vascular land plants and its incorporation into the marine sedimentary record, yet the dynamics of terrestrial carbon sequestration have important implications for the carbon cycle. Vascular plant carbon may encounter multiple potential intermediate storage pools and transport trajectories, and the age of vascular plant carbon accumulating in marine sediments will reflect these different pre-depositional histories. Here, we examine down-core C-14 profiles of higher plant leaf wax-derived fatty acids isolated from high fidelity sedimentary sequences spanning the so-called "bomb-spike", and encompassing a ca. 60-degree latitudinal gradient from tropical (Cariaco Basin), temperate (Saanich Inlet), and polar (Mackenzie Delta) watersheds to constrain integrated vascular plant carbon storage/transport times ("residence times"). Using a modeling framework, we find that, in addition to a "young" (conditionally defined as < 50 y) carbon pool, an old pool of compounds comprises 49 to 78 % of the fractional contribution of organic carbon (OC) and exhibits variable ages reflective of the environmental setting. For the Mackenzie Delta sediments, we find a mean age of the old pool of 28 ky (+/- 9.4, standard deviation), indicating extensive pre-aging in permafrost soils, whereas the old pools in Saanich Inlet and Cariaco Basin sediments are younger, 7.9 (+/- 5.0) and 2.4 (+/- 0.50) to 3.2 (+/- 0.54) ky, respectively, indicating less protracted storage in terrestrial reservoirs. The "young" pool showed clear annual contributions for Saanich Inlet and Mackenzie Delta sediments (comprising 24% and 16% of this pool, respectively), likely reflecting episodic transport of OC from steep hillside slopes surrounding Saanich Inlet and annual spring flood deposition in the Mackenzie Delta, respectively. Contributions of 5-10 year old OC to the Cariaco Basin show a short delay of OC inflow, potentially related to transport time to the offshore basin. Modeling results also indicate that the Mackenzie Delta has an influx of young but decadal material (20-30 years of age), pointing to the presence of an intermediate reservoir. Overall, these results show that a significant fraction of vascular plant C undergoes pre-aging in terrestrial reservoirs prior to accumulation in deltaic and marine sediments. The age distribution, reflecting both storage and transport times, likely depends on landscape-specific factors such as local topography, hydrographic characteristics, and mean annual temperature of the catchment, all of which affect the degree of soil buildup and preservation. We show that catchment-specific carbon residence times across landscapes can vary by an order of magnitude, with important implications both for carbon cycle studies and for the interpretation of molecular terrestrial paleoclimate records preserved in sedimentary sequences.
Keywords: british-columbia; CARIACO BASIN; compound-specific radiocarbon; MACKENZIE DELTA; marine-sediments; odp leg 169s; saanich inlet; SANTA-MONICA BASIN; SOIL ORGANIC-MATTER; TROPICAL VEGETATION

Testing the Utility of Geochemical Proxies to Reconstruct Holocene Coastal Environments and Relative Sea Level: A Case Study from Hungry Bay, Bermuda - Kemp, Andrew C.; Vane, Christopher H.; Khan, Nicole S.; Ellison, Joanna C.; Engelhart, Simon E.; Horton, Benjamin P.; Nikitina, Daria; Smith, Struan R.; Rodrigues, Lisa J.; Moyer, Ryan P. (Open Quaternary, 2019)
On low-lying, tropical and sub-tropical coastlines freshwater marshes may be replaced by salt‑tolerant mangroves in response to relative sea-level rise. Pollen analysis of radiocarbon‑dated sediment cores showed that such a change occurred in Hungry Bay, Bermuda during the late Holocene. This well-established paleoenvironmental trajectory provides an opportunity to explore if geochemical proxies (bulk-sediment δ13C and Rock-Eval pyrolysis) can reconstruct known environmental changes and relative sea level. We characterized surface sediment from depositional environments in Bermuda (freshwater wetlands, saline mangroves, and wrack composed of Sargassum natans macroalgae) using geochemical measurements and demonstrate that a multi-proxy approach can objectively distinguish among these environments. However, application of these techniques to the transgressive sediment succession beneath Hungry Bay suggests that freshwater peat and mangrove peat cannot be reliably distinguished in the sedimentary record, possibly because of post‑depositional convergence of geochemical characteristics on decadal to multi‑century timescales and/or the relatively small number of modern samples analyzed. Sediment that includes substantial contributions from Sargassum is readily identified by geochemistry, but has a limited spatial extent. Radiocarbon dating indicates that beginning at –700 CE, episodic marine incursions into Hungry Bay (e.g., during storms) carried Sargassum that accumulated as wrack and thickened through repeated depositional events until ~300 CE. It took a further ~550 years for a peat‑forming mangrove community to colonize Hungry Bay, which then accumulated sediment rapidly, but likely out of equilibrium with regional relative sea-level rise.
Keywords: mangrove; radiocarbon; Rock-Eval pyrolysis; Sargassum; δ13C

Timescales of water-quality change in a karst aquifer, south-central Texas - Musgrove, M.; Solder, J. E.; Opsahl, S. P.; Wilson, J. T. (Journal of Hydrology X, 2019)
Understanding the drivers and timescales over which groundwater quality changes informs groundwater management, use, and protection. To better understand timescales of water-quality change over short (daily to monthly) and long (seasonal to decadal) timescales, the U.S. Geological Survey’s National Water-Quality Assessment (NAWQA) Enhanced Trends Network (ETN) program instrumented and sampled three wells in the Edwards aquifer in south-central Texas. The wells were instrumented to provide high-frequency continuous (subhourly) water-quality data (temperature, pH, specific conductance, and dissolved oxygen), which were augmented by the collection of discrete samples (about 6 per year) for a range of geochemical constituents (including selected isotopes and age tracers). ETN data (2013–2017) are considered with data from additional sites for the same time period, and also historical records (over more than 80 years) of climatic and hydrologic conditions. During the four-year study, hydrologic conditions transitioned from very dry to very wet. Sites in the updip/unconfined part of the aquifer showed notable changes in water level and geochemistry (1) in response to rainfall/recharge events, and (2) over the multiyear dry/wet cycle. Sites in the downdip/confined part of the aquifer showed changes in water level/spring discharge over similar timescales, although the response is more muted. Geochemistry at the downdip/confined sites, however, varied slowly and minimally, indicating that the geochemical response of the deeper aquifer is decoupled from recent hydrologic responses. Changes at the updip/unconfined sites reflect mixing with recent recharge, whereas the downdip/confined sites were dominated by mineral-solution reactions resulting from longer (decadal) residence times. Mean groundwater ages interpreted from measured age tracers and lumped parameter models range from 7 to >700 years (where mixed with premodern downdip water) but were mostly modern. The aquifer is characterized by updip-to-downdip trends in geochemistry with respect to water-rock interaction and groundwater age. Fourier spectral analysis of historical records indicate hydrologic variability has occurred at dominant periods of 30 and 15 years; in conjunction with age tracers, these results provide insight into timescales at which the aquifer’s public supply is vulnerable to changes in the water quality of recharge.
Keywords: Edwards aquifer; Groundwater age; Karst; Trends; Water quality

The Utility of Stable and Radioisotopes in Fish Tissues as Biogeochemical Tracers of Marine Oil Spill Food Web Effects - Patterson III, William F.; Chanton, Jeffery P.; Hollander, David J.; Goddard, Ethan A.; Barnett, Beverly K.; Tarnecki, Joseph H. (Springer International Publishing, 2019)
Direct exposure to petroleum compounds was widely reported for a variety of taxa following the DWH. Evidence of exposure ranged from oiling of skin, shells, or feathers, depending on the taxa, to observation of ingested oil in small translucent, invertebrates, to biomarkers of petroleum compounds within an organism’s tissues, such as PAHs in the hepatopancreas of invertebrates or the liver of fishes, or metabolic products of PAH catabolism in the bile of various vertebrate taxa. Development of natural biogeochemical tracers to examine indirect effects, especially over long (months to years) time scales, can be much more problematic. In this chapter, we describe the utility of employing stable isotopes and radioisotopes to 1) examine whether food web effects can be inferred from shifts in stable isotope values measured in vertebrate taxa; 2) examine the assimilation and trophic transfer of petrocarbon in marine food webs; and, 3) serve as long-term biogeochemical tracers either of petrocarbon assimilation or trophic shifts that are indicative of food web effects of marine oil spills. Data and analyses are largely drawn from DWH-related studies but with broader implications to marine oil spills in general.
Keywords: Petrocarbon; radiocarbon; Reef fish; Stable isotopes

On the Age and Origin of Lake Ejagham, Cameroon, and Its Endemic FishesAbstract - Curt Stager, Jay; Alton, Kenneth; Martin, Christopher H.; King, David T.; Petruny, Lucille W.; Wiltse, Brendan; Livingstone, Daniel A. (Quaternary Research, 2018)
Lake Ejagham is a small, shallow lake in Cameroon, West Africa, which supports five endemic species of cichlid fishes in two distinct lineages. Genetic evidence suggests a relatively young age for the species flocks, but supporting geologic evidence has thus far been unavailable. Here we present diatom, geochemical, mineralogical, and radiocarbon data from two sediment cores that provide new insights into the age and origin of Lake Ejagham and its endemic fishes. Radiocarbon ages at the base of the longer core indicate that the lake formed approximately 9 ka ago, and the diatom record of the shorter core suggests that hydroclimate variability during the last 3 millennia was similar to that of other lakes in Cameroon and Ghana. These findings establish a maximum age of ca. 9 cal ka BP for the lake and its endemic species and suggest that repeated cichlid speciation in two distinct lineages occurred rapidly within the lake. Local geology and West African paleoclimate records argue against a volcanic, chemical, or climatic origin for Lake Ejagham. Although not conclusive, the morphometry of the lake and possible signs of impact-induced effects on quartz grains are instead more suggestive of a bolide impact.
Keywords: Africa; cameroon; Cichlid; Diatom; evolution; Lake Ejagham; Speciation; West African monsoon

Aging and Molecular Changes of Dissolved Organic Matter Between Two Deep Oceanic End-Members - Bercovici, S. K.; Koch, B. P.; Lechtenfeld, O. J.; McCallister, S. L.; Schmitt-Kopplin, P.; Hansell, D. A. (Global Biogeochemical Cycles, 2018)
The global ocean contains a massive reservoir of dissolved organic carbon (DOC), rivaling the atmosphere's pool of CO2. The most recalcitrant fractions have mean radiocarbon ages of ~4,000 years in the Atlantic to ~6,000 years in the Pacific. Knowing the radiocarbon signatures of DOC and the molecular composition of dissolved organic matter (DOM) is crucial to develop understanding of the persistence and lifetime of the DOC pool. In this research, we collected samples from the deep North Pacific in August 2013 (aboard the RV Melville) to couple the Δ14C content of solid‐phase‐extracted DOM (Δ14C‐SPE‐DOM) with its molecular composition in the ocean's oldest deep waters. We find that deep waters in this region held a mean Δ14C‐SPE‐DOM value of −554 ± 9‰ (~6,400 14C years), substantially more depleted than that in the deep Atlantic, which held a mean Δ14C‐SPE‐DOM value of −445 ± 5‰. While we find a more degraded molecular composition of DOM in the deep Pacific than the deep Atlantic, the molecular formulae within the Island of Stability (Lechtenfeld et al., 2014, https://doi.org/10.1016/j.gca.2013.11.009), are largely retained. These results imply that a fraction of deep DOM is resistant to removal and present in both the deep Atlantic and Pacific Oceans.

A centuries-long delay between a paleo-ice-shelf collapse and grounding-line retreat in the Whales Deep Basin, eastern Ross Sea, Antarctica - Bart, Philip J.; DeCesare, Matthew; Rosenheim, Brad E.; Majewski, Wojceich; McGlannan, Austin (Scientific Reports, 2018)
Recent thinning and loss of Antarctic ice shelves has been followed by near synchronous acceleration of ice flow that may eventually lead to sustained deflation and significant contraction in the extent of grounded and floating ice. Here, we present radiocarbon dates from foraminifera that constrain the time elapsed between a previously described paleo-ice-shelf collapse and the subsequent major grounding-line retreat in the Whales Deep Basin (WDB) of eastern Ross Sea. The dates indicate that West Antarctic Ice Sheet (WAIS) grounding-line retreat from the continental shelf edge was underway prior to 14.7 ± 0.4 cal kyr BP. A paleo-ice-shelf collapse occurred at 12.3 ± 0.2 cal kyr BP. The grounding position was maintained on the outer-continental shelf until at least 11.5 ± 0.3 cal kyr BP before experiencing a 200-km retreat. Given the age uncertainties, the major grounding-line retreat lagged ice-shelf collapse by at least two centuries and by as much as fourteen centuries. In the WDB, the centuries-long delay in the retreat of grounded ice was partly due to rapid aggradational stacking of an unusually large volume of grounding-zone-wedge sediment as ice-stream discharge accelerated following ice-shelf collapse. This new deglacial reconstruction shows that ongoing changes to ice shelves may trigger complex dynamics whose consequences are realized only after a significant lag.

Climatic control of Mississippi River flood hazard amplified by river engineering - Munoz, Samuel E.; Giosan, Liviu; Therrell, Matthew D.; Remo, Jonathan W. F.; Shen, Zhixiong; Sullivan, Richard M.; Wiman, Charlotte; O’Donnell, Michelle; Donnelly, Jeffrey P. (Nature, 2018)
Over the past century, many of the world’s major rivers have been modified for the purposes of flood mitigation, power generation and commercial navigation1. Engineering modifications to the Mississippi River system have altered the river’s sediment levels and channel morphology2, but the influence of these modifications on flood hazard is debated3,4,5. Detecting and attributing changes in river discharge is challenging because instrumental streamflow records are often too short to evaluate the range of natural hydrological variability before the establishment of flood mitigation infrastructure. Here we show that multi-decadal trends of flood hazard on the lower Mississippi River are strongly modulated by dynamical modes of climate variability, particularly the El Niño–Southern Oscillation and the Atlantic Multidecadal Oscillation, but that the artificial channelization (confinement to a straightened channel) has greatly amplified flood magnitudes over the past century. Our results, based on a multi-proxy reconstruction of flood frequency and magnitude spanning the past 500 years, reveal that the magnitude of the 100-year flood (a flood with a 1 per cent chance of being exceeded in any year) has increased by 20 per cent over those five centuries, with about 75 per cent of this increase attributed to river engineering. We conclude that the interaction of human alterations to the Mississippi River system with dynamical modes of climate variability has elevated the current flood hazard to levels that are unprecedented within the past five centuries.

Combining Conflicting Bayesian Models to Develop Paleoseismic Records: An Example from the Wasatch Fault Zone, Utah - DuRoss, Christopher B.; Bennett, Scott E. K.; Briggs, Richard W.; Personius, Stephen F.; Gold, Ryan D.; Reitman, Nadine G.; Hiscock, Adam I.; Mahan, Shannon A. (Bulletin of the Seismological Society of America, 2018)
Bayesian statistical analyses of paleoseismic data result in the probabilistic determination of earthquake times using geochronological data evaluated in the context of a stratigraphic model. However, a fundamental problem in paleoseismology is how to use the Bayesian approach to model sparse and/or conflicting geochronological datasets, such as those derived from sites exhibiting episodic sedimentary and pedogenic processes in moderate‐ to high‐energy environments (e.g., a normal‐faulted alluvial fan). Using paleoseismic data for the Corner Canyon site on the Salt Lake City segment of the Wasatch fault zone (Utah), we develop an approach by which multiple Bayesian models are combined to generate an earthquake history at a site. This approach accommodates mutually exclusive interpretations of the geochronological data and thereby limits the influence of sparse data, stratigraphically inconsistent ages, or a single, subjective model interpretation. For the Corner Canyon site, we integrate four OxCal Bayesian models to generate a chronology of six events between ∼4.8 and ∼0.5  ka. Late Holocene (post‐5 ka) mean recurrence and vertical slip‐rate estimates are ∼0.9  ky (0.7–1.0 ky; 95% confidence) and 1.1  mm/yr (0.8–1.7  mm/yr range), respectively. Although our method increases the uncertainty in the timing of individual earthquakes, it more objectively accounts for potential geochronological errors and different interpretations of stratigraphic age control. By relaxing the need to select a single age model, our approach yields more accurate earthquake‐timing results that will better facilitate evaluations of along‐fault event correlation and earthquake rupture length.

Data Constraints on Glacial Atlantic Water Mass Geometry and Properties - Oppo, Delia W.; Gebbie, Geoffrey; Huang, Kuo‐Fang; Curry, William B.; Marchitto, Thomas M.; Pietro, Kathryn R. (Paleoceanography and Paleoclimatology, 2018)
The chemical composition of benthic foraminifera from marine sediment cores provides information on how glacial subsurface water properties differed from modern, but separating the influence of changes in the origin and end‐member properties of subsurface water from changes in flows and mixing is challenging. Spatial gaps in coverage of glacial data add to the uncertainty. Here we present new data from cores collected from the Demerara Rise in the western tropical North Atlantic, including cores from the modern tropical phosphate maximum at Antarctic Intermediate Water (AAIW) depths. The results suggest lower phosphate concentration and higher carbonate saturation state within the phosphate maximum than modern despite similar carbon isotope values, consistent with less accumulation of respired nutrients and carbon, and reduced air‐sea gas exchange in source waters to the region. An inversion of new and published glacial data confirms these inferences and further suggests that lower preformed nutrients in AAIW, and partial replacement of this still relatively high‐nutrient AAIW with nutrient‐depleted, carbonate‐rich waters sourced from the region of the modern‐day northern subtropics, also contributed to the observed changes. The results suggest that glacial preformed and remineralized phosphate were lower throughout the upper Atlantic, but deep phosphate concentration was higher. The inversion, which relies on the fidelity of the paleoceanographic data, suggests that the partial replacement of North Atlantic sourced deep water by Southern Ocean Water was largely responsible for the apparent deep North Atlantic phosphate increase, rather than greater remineralization.

Dimensions of Radiocarbon Variability within Sedimentary Organic MatterABSTRACT - Bao, Rui; McNichol, Ann P; McIntyre, Cameron P; Xu, Li; Eglinton, Timothy I (Radiocarbon, 2018)
Organic carbon (OC) radiocarbon (14C) signatures in marine surface sediments are highly variable and the causes of this heterogeneity remain ambiguous. Here, we present results from a detailed 14C-based investigation of an Arabian Sea sediment, including measurements on organic matter (OM) in bulk sediment, specific grain size fractions, and OC decomposition products from ramped-pyrolysis-oxidation (RPO). Our results show that 14C ages of OM increase with increasing grain size, suggesting that grain size is an important factor controlling the 14C heterogeneity in marine sediments. Analysis of RPO decomposition products from different grain size fractions reveals an overall increase in age of corresponding thermal fractions from finer to coarser fractions. We suggest that hydrodynamic properties of sediment grains exert the important control on the 14C age distribution of OM among grain size fractions. We propose a conceptual model to account for this dimensionality in 14C variability that invokes two predominant modes of OM preservation within different grain size fractions of Arabian Sea sediment: finer (<63 μm) fractions are influenced by OM-mineral grain aggregation processes, giving rise to relatively uniform 14C ages, whereas OM preserved in coarser (>63 μm) fractions includes materials encapsulated within microfossils and/or entrained fossil (14C-depleted) OC hosted in detrital mineral grains. Our findings highlight the value of RPO for assessment of 14C age variability in sedimentary OC, and for assessing mechanisms of OM preservation in aquatic sediments.
Keywords: arabian sea; grain size; hydrodynamic processes; organicmatter; radiocarbon; ramped pyrolysis-oxidation

Drought in the northern Bahamas from 3300 to 2500 years ago - van Hengstum, Peter J.; Maale, Gerhard; Donnelly, Jeffrey P.; Albury, Nancy A.; Onac, Bogdan P.; Sullivan, Richard M.; Winkler, Tyler S.; Tamalavage, Anne E.; MacDonald, Dana (Quaternary Science Reviews, 2018)
Intensification and western displacement of the North Atlantic Subtropical High (NASH) is projected for this century, which can decrease Caribbean and southeastern American rainfall on seasonal and annual timescales. However, additional hydroclimate records are needed from the northern Caribbean to understand the long-term behavior of the NASH, and better forecast its future behavior. Here we present a multi-proxy sinkhole lake reconstruction from a carbonate island that is proximal to the NASH (Abaco Island, The Bahamas). The reconstruction indicates the northern Bahamas experienced a drought from ∼3300 to ∼2500 Cal yrs BP, which coincides with evidence from other hydroclimate and oceanographic records (e.g., Africa, Caribbean, and South America) for a synchronous southern displacement of the Intertropical Convergence Zone and North Atlantic Hadley Cell. The specific cause of the hydroclimate change in the northeastern Caribbean region from ∼3300 to 2500 Cal yrs BP was probably coeval southern or western displacement of the NASH, which would have increased northeastern Caribbean exposure to subsiding air from higher altitudes.

Early Holocene sea level in the Canadian Beaufort Sea constrained by radiocarbon dates from a deep borehole in the Mackenzie Trough, Arctic Canada - O'Regan, Matt; Coxall, Helen; Hill, Philip; Hilton, Robert; Muschitiello, Francesco; Swärd, Henrik (Boreas, 2018)
Deglacial and Holocene relative sea level (RSL) in the Canadian Beaufort Sea was influenced by the timing and extent of glacial ice in the Mackenzie River corridor and adjacent coastal plains. Considerable evidence indicates extensive ice cover in this region of northwestern Canada during the Late Wisconsinan. However, no absolute ages exist to constrain maximum RSL lowering before the late Holocene (4.2–0 ka). In 1984, the Geological Survey of Canada drilled an 81.5‐m‐deep borehole in the western Mackenzie Trough at 45 m water depth (MTW01). The lower 52.5 m of the borehole was interpreted as a deltaic progradational sequence deposited during a period of rising sea level. The upper 29 m was described as foraminifer‐bearing marine sediments deposited after transgression of the site, when RSL rose above ~−74 m. Here, we present radiocarbon measurements from MTW01, acquired from benthic foraminifera, mollusc fragments and particulate organic carbon in the >63 μm fraction (POC>63 μm) in an attempt to constrain the chronology of sediments within this borehole and date the timing of transgression. The deepest carbonate macrofossil was acquired from 8 m above the transgressive surface (equivalent to 21 m b.s.l.), where mollusc fragments returned a date of 9400 +180–260 cal. a BP (2σ). This provides the oldest constraint on Holocene sea‐level lowering in the region, and implies that transgression at this site occurred prior to the early Holocene. Ages obtained from the lower 52.5 m of the borehole are limited to POC>63 μm samples. These indicate that progradational sediments were deposited rapidly after 24 820 +390–380 cal. a BP (2σ). Due to the incorporation of older reworked organic matter, the actual age of progradation is likely to be younger, occurring after Late Wisconsinan glacial ice retreated from the coast.

The effect of sample drying temperature on marine particulate organic carbon composition - Rosengard, Sarah Z.; Lam, Phoebe J.; McNichol, Ann P.; Johnson, Carl G.; Galy, Valier V. (Limnology and Oceanography: Methods, 2018)
Compositional changes in marine particulate organic carbon (POC) throughout the water column trace important processes that underlie the biological pump's efficiency. While labor‐intensive, particle sampling efforts offer potential to expand the empirical POC archive at different stages in the water column, provided that organic composition is sufficiently preserved between sampling and analysis. The standard procedure for preserving organic matter composition in marine samples is to immediately store particles at −80°C to −20°C until they can be freeze‐dried for analysis. This report investigates the effect of warmer drying and storage temperatures on POC composition, which applies to the majority of POC samples collected in the field without intention for organic analysis. Particle samples collected off Woods Hole, Massachusetts were immediately dried at 56°C, at room temperature, or stored in a freezer until freeze‐drying. Results show that oven‐ and air‐drying did not shift the bulk composition (i.e., carbon and nitrogen content and stable isotope composition) of POC in the samples relative to freeze‐drying. Similarly, warmer drying temperatures did not affect POC thermal stability, as inferred by ramped pyrolysis/oxidation, a growing technique that uses a continuous temperature ramp to differentiate components of organic carbon by their decomposition temperature. Oven‐ and air‐drying did depress lipid abundances relative to freeze‐drying, the extent of which depended on compound size and structure. The data suggest that field samples dried at room temperatures and 56°C are appropriate for assessing bulk POC composition and thermal stability, but physical mechanisms such as molecular volatilization bias their lipid composition.

Effects of the Younger Dryas climate event recorded in sediment near the western Irish seaboard - Wood, Bill L.; Williams, D. Michael; Murray, John (Geological Journal, 2018)
Results of analyses of a shallow marine sediment vibrocore from the Atlantic seafloor just west of the Aran Islands, western Ireland, are presented. The sediments range from ~16,000 to younger than 9,000 cal BP in age, based on 14C dating of foraminifers and molluscs. One sample within the core is dated at 12804 ± 125 cal BP and lies a very short distance stratigraphically below a conspicuous horizon containing isolated pebbles and sand‐size clasts, in what is an otherwise fine‐grained sequence of sediment. These outsized clasts are interpreted to be ice‐rafted debris. Approximately coeval with this horizon, the diversity and abundance of foraminifers decrease significantly and the foraminifer Nonionellina labradorica makes its first appearance in the core sediment. Stable isotope analysis shows a significant increase in values of δ18O approaching the horizon containing ice‐rafted debris. These results show the effects of a relatively sudden cooling of this part of the Atlantic Ocean at middle latitudes coincident with, or just after, the onset of the Younger Dryas event and demonstrate the extent of floating icebergs and probable later pack ice as a result of this temperature decrease.
Keywords: Atlantic Ocean; Foraminifers; Holocene; ice rafted debris; Ireland; sediment core; Younger Dryas

The Effects of Tropical Cyclone-Generated Deposition on the Sustainability of the Pearl River Marsh, Louisiana: The Importance of the Geologic FrameworkPresentation_1.PPTX - McCloskey, Terrence A.; Smith, Christopher G.; Liu, Kam-biu; Nelson, Paul R. (Frontiers in Ecology and Evolution, 2018)
Shoreline retreat is a tremendously important issue along the coast of the northern Gulf of Mexico, especially in Louisiana. Although this marine transgression results from a variety of causes, the crucial factor is the difference between marsh surface elevation and rising sea levels. In most cases, the primary cause of a marsh's inability to keep up with sea level is the lack of input of inorganic material. Although tropical cyclones provide an important source of such sediment, little effort has been made to determine the point of origin of the deposited material. In this study we use sedimentary, geochemical and biogeochemical data to identify the bed of the Pearl River and/or Lake Borgne as the source of a ~5 cm thick clastic layer deposited on the surface of the Pearl River marsh on the Louisiana/Mississippi border. Radiochemical chronologies and sedimentary evidence indicate that this layer was associated with the passage of Hurricane Katrina in 2005. As this material would otherwise have been lost to the system, this deposition indicates a net gain to marsh surface elevation. Accretion rates, determined from 137Cs and 14C profiles and the use of the Katrina layer as a stratigraphic marker, indicate that short-term (~50 years) rates are as much as an order of magnitude higher than the long- term (1000s of years) rates. We suggest that the marsh's geologic setting in an incised river valley with steep vertical constraints and a large fluvial discharge, promotes rapid accretion rates, with rates accelerating as the sea moves inland, due to extended hydroperiods and the input of clastic material from both the marine and terrestrial sides. These rates are especially large when compared to accretion occurring in the more common open marshes fringing the Gulf that lack fluvial input. The difference is particularly large when related to marsh recovery/regrowth following the deposition of thick hurricane-generated clastic layers. Given the number of similar incised river valleys along the Gulf Coast, we believe that understanding the processes controlling marsh accretion in such environments is essential in evaluating marsh sustainability on a regional basis.

Evidence for Stable Holocene Basin‐Scale Overturning Circulation Despite Variable Currents Along the Deep Western Boundary of the North Atlantic Ocean - Hoffmann, Sharon S.; McManus, Jerry F.; Swank, Emerson (Geophysical Research Letters, 2018)
While substantial changes in thermohaline circulation related to deglacial climate variability are well established, the role of this circulation in Holocene climate variability remains uncertain. Here we use two dynamical proxies, 231Pa/230Th ratios and mean sortable silt size ( urn:x-wiley:00948276:media:grl58406:grl58406-math-0001), to reconstruct Holocene bottom water circulation at the intermediate‐depth Carolina Slope. We find no substantial change in deep current speed or 231Pa export at this site during the Holocene, suggesting consistent 231Pa export via the Deep Western Boundary Current. urn:x-wiley:00948276:media:grl58406:grl58406-math-0002 shows increasing millennial‐scale variability in the middle‐late Holocene, which may reflect Labrador Sea Water contribution to current speed. We conclude that deepwater export from the North Atlantic has remained remarkably stable during the Holocene, decoupled from changing rates of specific water masses, while production of these water masses varied at millennial to centennial time scales. The persistence of the large‐scale overturning may reflect the ocean's stabilizing influence on Holocene climate.
Keywords: chemical tracers; interglacial; Radioactivity and radioisotopes; sedimentation (1861); thermohaline

Faunal and stable isotopic analyses of benthic foraminifera from the Southeast Seep on Kimki Ridge offshore southern California, USA - McGann, Mary; Conrad, James E. (Deep Sea Research Part II: Topical Studies in Oceanography, 2018)
We investigated the benthic foraminiferal faunal and stable carbon and oxygen isotopic composition of a 15-cm push core (NA075-092b) obtained on a Telepresence-Enabled cruise to the Southeast Seep on Kimki Ridge offshore southern California. The seep core was taken at a depth of 973 m in the vicinity of a Beggiatoa bacterial mat and vesicomyid clams (Calyptogena) and compared to previously published data of living assemblages from ~ 714 m, four reference cores obtained at ~ 1030 m, and another one at 739 m. All of the reference sites are also from the Inner Continental Borderland but with no evidence of methane seepage. No endemic species were found at the seep site and most of the taxa recovered there have been reported previously from other seep or low oxygen environments. Q- and R-mode cluster analyses clearly illustrated differences in the faunal assemblages of the seep and non-seep sites. The living assemblage at Southeast Seep was characterized by abundant Takayanagia delicata, Cassidulina translucens, and Spiroplectammina biformis, whereas the non-seep San Pedro Basin reference assemblage was comprised primarily of Chilostomella oolina and Globobulimina pacifica. Density and species richness were lower at the seep site compared to the non-seep site, reflecting the harsher living conditions there. The dead assemblage at the seep site was dominated by Gyroidina turgida compared to Cassidulina translucens at the ~ 1030 m non-seep site and Cassidulina translucens, Pseudoparrella pacifica, and Takayanagia delicata at the 739 m non-seep site. Density was three times lower at Southeast Seep than at the non-seep sites of comparable water depth but species richness was ~ 30% higher. Stable carbon isotopic values were considerably depleted in the seep samples compared to the non-seep samples, with a progression from lightest to heaviest average δ13C values evident at the seep site reflecting microhabitat preference and vital effect: the deep infaunal species of Globobulimina, the shallow infaunal species Uvigerina peregrina, the epifaunal species Cibicidoides wuellerstorfi, and the shallow infaunal but aragonite-shelled species Hoeglundina elegans. The δ13C values downcore among each benthic species indicates ongoing fluid seepage through at least the last 3800 cal yr B.P. at Southeast Seep. Besides the continual local seepage, evidence from δ13C values of planktic foraminifera in the seep core suggest two pulses of methane (at 3000 and 3700 cal yr B.P.) were released that were large enough to influence much of the water column. Paired benthic and planktic foraminiferal stable oxygen isotope records provide evidence that there were no paleoenvironmental changes such as increased bottom-water temperature or changes in oxygen isotopic composition of bottom and pore waters during this 3800-year record to induce the methane releases. Instead, Southeast Seep appears to be the result of local faulting providing pathways for fluid to flow to the seafloor at a fault stepover or transpressional bend in the regional strike-slip system.
Keywords: Beggiatoa; benthic foraminifera; Calyptogena; Kimki Ridge; Santa Catalina Basin; Southeast Seep; Southern California; stable carbon isotopes

Holocene mountain glacier history in the Sukkertoppen Iskappe area, southwest Greenland - Schweinsberg, Avriel D.; Briner, Jason P.; Miller, Gifford H.; Lifton, Nathaniel A.; Bennike, Ole; Graham, Brandon L. (Quaternary Science Reviews, 2018)
Mountain glaciers and ice caps (GIC) independent of the Greenland Ice Sheet respond rapidly to climate variations and records of their past extent provide information on the natural envelope of climate variability. Here, we use a multi-proxy approach that combines proglacial lake sediment analysis, cosmogenic nuclide surface-exposure dating (in situ 10Be and 14C), and radiocarbon dating of recently ice-entombed moss to generate a centennial-scale record of Holocene GIC fluctuations in southwestern Greenland. Following local deglaciation ∼10-9 ka, sediments from proglacial Crash Lake record a glacier advance at ∼9 ka that is indistinguishable from nearby ice sheet moraines, implying a synchronous response of GIC and the Greenland Ice Sheet to a centennial-scale climate event. Following this local glacier advance, GIC experienced net recession until ∼4.6 ka. Radiocarbon ages of in situ moss (n = 29) and Crash Lake sediments reveal intervals of glacier expansion at ∼1.8, 1.2 and 0.7 ka that are superimposed on an overall trend of net glacier expansion throughout the late Holocene. In situ 14C concentrations from bedrock adjacent to radiocarbon-dated moss samples further constrain the duration of ice cover through the Holocene in this region. We find that our glacier-size proxy records during the past ∼4 ka are broadly consistent with relatively lower temperatures recorded in GISP2 and occur during, or following, intervals of volcanic perturbations. Thus, we speculate that volcanic activity, although less frequent and intense than in the early Holocene and during the Little Ice Age, may have led to centennial-scale variability imprinted on net glacier expansion due to decreasing summer insolation through the late Holocene.
Keywords: Cosmogenic in situ 14C; Glacier fluctuations; Greenland; Holocene; lake sediment; Neoglaciation

How Could a Freshwater Swamp Produce a Chemical Signature Characteristic of a Saltmarsh?How Could a Freshwater Swamp Produce a Chemical Signature Characteristic of a Saltmarsh? - McCloskey, Terrence A.; Smith, Christopher G.; Liu, Kam-biu; Marot, Marci; Haller, Christian (ACS Earth and Space Chemistry, 2018)
Reduction–oxidation (redox) reaction conditions, which are of great importance for the soil chemistry of coastal marshes, can be temporally dynamic. We present a transect of cores from northwest Florida wherein radical postdepositional changes in the redox regime has created atypical geochemical profiles at the bottom of the sedimentary column. The stratigraphy is consistent along the transect, consisting of, from the bottom upward, carbonate bedrock, a gray clay, an organic mud section, a dense clay layer, and an upper organic mud unit representing the current saltwater marsh. However, the geochemical signature of the lower organic mud unit suggests pervasive redox reactions, although the interval has been identified as representing a freshwater marsh, an unlikely environment for such conditions. Analyses indicate that this discrepancy results from postdepositional diagenesis driven by millennial-scale environmental parameters. Rising sea level that led to the deposition of the capping clay layer, created anaerobic conditions in the freshwater swamp interval, and isolated it hydrologically from the rest of the sediment column. The subsequent infiltration of marine water into this organic material led to sulfate reduction, the buildup of H2S and FeS, and anoxic conditions. Continued sulfidation eventually resulted in euxinic conditions, as evidenced by elevated levels of Fe, S, and especially Mo, the diagnostic marker of euxinia. Because this chemical transformation occurred long after the original deposition the geochemical signature does not reflect soil chemistry at the time of deposition and cannot be used to infer syn-depositional environmental conditions, emphasizing the importance of recognizing diagenetic processes in paleoenvironmental studies.
Keywords: anoxic; diagenesis; euxinic; florida; Molybdenum; reactions; redox; XRF

The Impact of Aquifer Flushing on Groundwater Arsenic Across a 35‐km Transect Perpendicular to the Upper Brahmaputra River in Assam, India - Choudhury, R.; Nath, B.; Khan, M. R.; Mahanta, C.; Ellis, T.; Geen, A. (Water Resources Research, 2018)
Well testing in the floodplain of the Brahmaputra River in Golaghat and Jorhat districts of Assam, India, shows that groundwater arsenic (As) concentrations increase with distance from the river. To establish the origin of this pattern, an additional 900 wells <60‐m deep were tested for As and nine sites were drilled along a 35‐km transect perpendicular to the river. The field data show no relation between groundwater As concentrations ranging from <1 to 660 μg/L along the transect and (a) As concentrations of <1–5 mg/kg in cuttings of aquifer sand recovered while drilling or (b) the degree of reduction of iron oxides in these cuttings. The drilling indicates, however, a marked increase in the thickness of a clay layer capping the aquifer starting from <1–5 m near the river to over 60 m at the most distant site toward the base of the Naga foothills. Organic radiocarbon ages of 18–46 kyr obtained from all but one of 13 clay samples indicate pre‐Holocene deposition of the underlying sands across the entire transect. Radiocarbon ages of dissolved inorganic carbon of 0.2, 4.7, and 17.8 kyr were measured in groundwater from three monitoring wells installed to 30–60‐m depth at distances of 10, 20, and 40 km from the river, respectively. A conceptual groundwater flow model consistent with monitored heads and groundwater ages suggests that thick clay layers capping the aquifer further from the river inhibited flushing of the aquifer and, as a result, preserved higher As levels in groundwater.
Keywords: aquifer flushing; Arsenic; groundwater; South Asia

Mangrove sediment carbon stocks along an elevation gradient: Influence of the late Holocene marine regression (New Caledonia) - Jacotot, Adrien; Marchand, Cyril; Rosenheim, Brad E.; Domack, Eugene W.; Allenbach, Michel (Marine Geology, 2018)
Among blue carbon ecosystems, mangroves are very efficient in storing carbon in their sediments over decadal to millennial time scales. However, this ability varies with numerous parameters, including climate and sea-level variations. In New Caledonia, mangrove ecosystems develop in semi-arid conditions with a typical zonation: Rhizophora spp. colonize the seaward side of the intertidal area, while Avicennia marina develops at higher elevations, just below the salt-flat. Within this context, we determined both the quantity (organic carbon content and carbon stocks) and the characteristics (carbon over nitrogen ratios (C/N), stable carbon and nitrogen isotopes, radiocarbon age) of the organic matter stored beneath each mangrove stands. Carbon stocks were determined down to different limits with depth: approximate extension of the root systems, one-meter depth, and the hard substrate. Within the extension of the root systems, the sediment carbon stock was lower than 100 MgC ha−1 regardless of the mangrove species. This low value resulted directly from the dry climate that limits mangrove productivity. At depth beneath every zone, a buried layer enriched in mangrove-derived organic matter, with C/N values around 40 and δ13C values around −26‰ was observed. This layer likely resulted from a sea-level high stand during the late Holocene that allowed a long period of stability of the mangrove, slowly accumulating organic matter within the sediment. In this buried layer, the carbon stock was higher than in the upper sediment and reached up to 665, 255 and 300 MgC ha−1 in the salt-flat zone, the A. marina stand and the R. spp. stand, respectively. The highest stock, determined beneath the salt-flat, was suggested to be related to a period of sea-level stability that lasted ~3000 years, whereas beneath the other zones, which are at lower elevations, mangrove colonization was more recent and the sea-level was continuously decreasing till recently. Sea-level variations, and, specifically current sea-level rise, may strongly influence mangrove development due to their migration along the tidal elevation gradient to maintain the biotic conditions needed for their development.
Keywords: Blue carbon; carbon isotopes; carbon sequestration; Coastal wetlands; Sea-level change; Semi-arid mangrove forest

Millennial-scale variations in dustiness recorded in Mid-Atlantic sediments from 0 to 70 ka - Middleton, Jennifer L.; Mukhopadhyay, Sujoy; Langmuir, Charles H.; McManus, Jerry F.; Huybers, Peter J. (Earth and Planetary Science Letters, 2018)
Sedimentary records of dust deposition in the subtropical Atlantic provide important constraints on millennial- and orbital-scale variability in atmospheric circulation and North African aridity. Constant flux proxies, such as extraterrestrial helium-3, yield dust flux records that are independent of the biases caused by lateral sediment transport and limited resolution that may be associated with age-model-derived mass accumulation rates. However, Atlantic dust records constrained using constant flux proxies are sparsely distributed and generally limited to the past 20 ka. Here we extend the Atlantic record of North African dust deposition to 70 ka using extraterrestrial helium-3 and measurements of titanium, thorium, and terrigenous helium-4 in two sediment cores collected at 26°N and 29°N on the Mid-Atlantic Ridge and compare results to model estimates for dust deposition in the subtropical North Atlantic. Dust proxy fluxes between 26°N and 29°N are well correlated, despite variability in lateral sediment transport, and underscore the utility of extraterrestrial helium-3 for constraining millennial-scale variability in dust deposition. Similarities between Mid-Atlantic dust flux trends and those observed along the Northwest African margin corroborate previous interpretations of dust flux variability over the past 20 ka and suggest that long distance transport and depositional processes do not overly obscure the signal of North African dust emissions. The 70 ka Mid-Atlantic record reveals a slight increase in North African dustiness from Marine Isotope Stage 4 through the Last Glacial Maximum and a dramatic decrease in dustiness associated with the African Humid Period. On the millennial-scale, the new records exhibit brief dust maxima coincident with North Atlantic cold periods such as the Younger Dryas, and multiple Heinrich Stadials. The correlation between Mid-Atlantic dust fluxes and previous constraints on North African aridity is high. However, precipitation exerts less control on dust flux variability prior to the African Humid Period, when wind variability governs dust emissions from consistently dry dust source regions. Thus, the Mid-Atlantic dust record supports the hypothesis that both aridity and wind strength drive dust flux variability across changing climatic conditions.
Keywords: helium-3; mass accumulation rate; mineral dust; North Africa; Subtropical North Atlantic; thorium-232

Organic Carbon Aging During Across‐Shelf Transport - Bao, Rui; Uchida, Masao; Zhao, Meixun; Haghipour, Negar; Montlucon, Daniel; McNichol, Ann; Wacker, Lukas; Hayes, John M.; Eglinton, Timothy I. (Geophysical Research Letters, 2018)
Compound-specific radiocarbon analysis (CSRA) was performed on different grain-size fractions of surficial sediments to examine and compare lateral transport times (LTTs) of organic carbon. 14C aging of long-chain leaf wax fatty acids along two dispersal pathways of fluvially-derived material on adjacent continental margins implies LTTs over distances of ~30 to 500 km that range from hundreds to thousands of years. The magnitude of aging differs among grain size fractions. Our finding suggests that LTTs vary both temporally and spatially as a function of the specific properties of different continental shelf settings. Observations suggest that 14C aging is widespread during lateral transport over continental shelves, with hydrodynamic particle sorting inducing age variations among organic components residing in different grain sizes. Consideration of these phenomena is of importance for understanding carbon cycle processes and interpretation on sedimentary records on continental margins.

Organic matter sources and lateral sedimentation in a Bahamian karst basin (sinkhole) over the late Holocene: Influence of local vegetation and climate - Tamalavage, Anne E.; van Hengstum, Peter J.; Louchouarn, Patrick; Molodtsov, Sergey; Kaiser, Karl; Donnelly, Jeffrey P.; Albury, Nancy A.; Fall, Patricia L. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2018)
Karst basins (e.g., blueholes, sinkholes) accumulate well-preserved sedimentary successions that provide transformative paleoclimatic and paleoenvironmental information. However, the sedimentary processes within these basins are not yet fully understood. Here we present stable carbon isotopic values (δ13Corg) and C:N ratios of bulk organic matter in well-dated sediment cores from Blackwood Sinkhole (Abaco, The Bahamas) to investigate the changing flux of organic matter into the sinkhole during the late Holocene. The provenance of preserved organic matter changed through the late Holocene between three primary sources, as determined by three-endmember mixing modeling: wetland organic matter from the adjacent epikarst surface, authigenic primary productivity in the oligohaline meteoric lens, and terrestrial organic matter from the surrounding landscape. Expansion of wetlands on the adjacent epikarst surface played a critical role by increasing the flux of wetland organic matter to the sinkhole, especially during the last 1000 years. Hurricanes and regional rainfall may have mediated organic matter delivery to the benthos, either through hampering wetland development (prior to 1000 cal yr BP) or by changing dissolved nutrient concentrations available in the basin for primary producers. These results demonstrate that organic matter provenance in karst basins is not constant through time, and is significantly dependent upon both landscape vegetation on the epikarst surface and changing hydrographic conditions that impacts nutrient availability to primary producers.
Keywords: Caribbean; Karst; Mixing model; Stable isotopes; Subtropical landscape

Paleomagnetism and rock magnetism from sediments along a continental shelf-to-slope transect in the NW Barents Sea: Implications for geomagnetic and depositional changes during the past 15 thousand years - Caricchi, C.; Lucchi, R.G.; Sagnotti, L.; MacrÌ, P.; Morigi, C.; Melis, R.; Caffau, M.; Rebesco, M.; Hanebuth, T.J.J. (Global and Planetary Change, 2018)
Paleomagnetic and rock magnetic data were measured on glaciomarine silty-clay successions along an E-W sediment-core transect across the continental shelf and slope of the Kveithola paleo-ice stream system (south of Svalbard, north-western Barents Sea), representing a stratigraphic interval spanning the last deglaciation and the Holocene. The records indicate that magnetite is the main magnetic mineral and that magnetic minerals are distinctly less abundant on the shelf than at the continental slope. The paleomagnetic properties allow for the reconstruction of a well-defined characteristic remanent magnetization (ChRM) throughout the sedimentary successions. The stratigraphic trends of rock magnetic and paleomagnetic parameters are used for a shelf-slope core correlation and sediment facies analysis is applied for depositional processes reconstruction. The new paleomagnetic records compare to the PSV and RPI variation predicted for the core sites by a simulation using the global geomagnetic field variation models SHA.DIF.14k and CALS7K.2 and closest PSV and RPI regional stack curves. The elaborated dataset, corroborated by available 14C ages, provides a fundamental chronological framework to constrain the coupling of shelf-slope sedimentary processes and environmental changes in the NW Barents Sea region during and after deglaciation.
Keywords: Barents Sea; Kveithola glacial trough; Paleomagnetism; Rock magnetism

Paleoseismic Results from the Alpine Site, Wasatch Fault Zone: Timing and Displacement Data for Six Holocene Earthquakes at the Salt Lake City–Provo Segment Boundary - Bennett, S. E. K.; DuRoss, C. B.; Gold, R. D.; Briggs, R. W.; Personius, S. F.; Reitman, N. G.; Devore, J. R.; Hiscock, A. I.; Mahan, S. A.; Gray, H. J.; Gunnarson, S.; Stephenson, W. J.; et al. (Bulletin of the Seismological Society of America, 2018)
To improve the characterization of Holocene earthquakes on the Wasatch fault zone (WFZ), we conducted light detection and ranging (lidar)‐based neotectonic mapping and excavated a paleoseismic trench across an 8‐m‐high fault scarp near Alpine, Utah, located <1  km south of the boundary between the Salt Lake City and Provo segments (SLCS and PS). We document evidence for six paleoearthquakes (AL6–AL1) from scarp‐derived colluvial wedges and crosscutting relations. A ground‐penetrating radar survey across the scarp resolved fault‐zone width, but not paleoearthquake stratigraphy. Bayesian (OxCal) modeling of 13 radiocarbon and 13 optically stimulated luminescence ages indicates that six earthquakes occurred ∼6.2–0.4  ka. Interseismic recurrence ranges from 0.2 to 1.8 ky (mean 1.2 ky). We estimate 6.5±0.7  m of cumulative vertical tectonic displacement across the ≥14‐m‐wide fault zone used near‐field observations of scarp‐derived colluvial‐wedge thicknesses, antithetic faulting, and graben backtilting. This is similar to our independent estimate of 6.5±0.5  m using far‐field observations of the offset ground surface and correlation of alluvial‐fan stratigraphy across the WFZ. These results suggest that colluvial‐wedge thickness at the Alpine site approximates one‐half the original west‐facing fault scarp height. Per‐event vertical displacements range from 0.8 to 1.2 m (mean 1.1 m), which we use to estimate surface rupture lengths that may exceed 50 km from earthquakes as large as moment magnitude (Mw) ∼7.0. The late Holocene average vertical slip rate is 0.9  mm/yr (0.7–1.2  mm/yr range). Earthquake frequency has increased in the past ∼1  ky, whereas displacement per event has been similar for the past ∼6  ky, suggesting that strain accumulation is not the sole factor that controls the frequency and size of earthquakes at the SLCS–PS segment boundary. These findings can be used for a more nuanced characterization of earthquakes at the SLCS–PS boundary and improve earthquake hazard assessments along the Wasatch Front.

The Potential Impact of Hydrocarbons on Mussels in Port au Port Bay, Newfoundland - Cook, Melissa C.; May, Adam; Kohl, Lucas; Van Biesen, Geert; Parrish, Christopher C.; Morrill, Penny L. (Elsevier, 2018)
Since 2012, the scallop fishery in Port au Port Bay, Newfoundland, Canada has experienced a drastic decline, while no decline was observed in adjacent St. George's Bay. Local fishermen have raised concerns about an abandoned oil exploration well in the Port au Port Bay. This study investigated the potential impact of petroleum hydrocarbons on sediments and blue mussels [Mytilus edulis] (a proxy organism for scallops) in the area. Sediments from both bays were characterized for their hydrocarbons and compared to potential petroleum hydrocarbon sources. Mussels were analysed for health indices and their 14C content. The results showed that the concentration of hydrocarbons found in the sediments of the fishing ground was within the range of unpolluted marine sediments and that the hydrocarbons present were likely from a mixture of sources. The health indices of the mussels in Port au Port Bay were similar to the health indices of mussels in St. George's Bay and the 14C content of the mussels from both bays was modern. These data suggest that the Port au Port fishing ground was not solely contaminated from crude oil leaking from an oil exploration well, that the mussels were not contaminated with petroleum hydrocarbons, and that Port au Port mussels were just as healthy as the mussels of St. George's Bay. Therefore, whatever caused the scallop decline was most likely scallop- and bay-specific. During this study a fast and efficient method for extracting petroleum hydrocarbons from sediment using accelerated solvent extraction with integrated silica gel was developed.
Keywords: Health indices; Hydrocarbon contamination; Mussels; Petroleum; Scallops

Pronounced summer warming in northwest Greenland during the Holocene and Last Interglacial - McFarlin, Jamie M.; Axford, Yarrow; Osburn, Magdalena R.; Kelly, Meredith A.; Osterberg, Erich C.; Farnsworth, Lauren B. (Proceedings of the National Academy of Sciences, 2018)
Projections of future rates of mass loss from the Greenland Ice Sheet are highly uncertain because its sensitivity to warming is unclear. Geologic reconstructions of Quaternary interglacials can illustrate how the ice sheet responded during past warm periods, providing insights into ice sheet behavior and important tests for data-model comparisons. However, paleoclimate records from Greenland are limited: Early Holocene peak warmth has been quantified at only a few sites, and terrestrial sedimentary records of prior interglacials are exceptionally rare due to glacial erosion during the last glacial period. Here, we discuss findings from a lacustrine archive that records both the Holocene and the Last Interglacial (LIG) from Greenland, allowing for direct comparison between two interglacials. Sedimentary chironomid assemblages indicate peak July temperatures 4.0 to 7.0 °C warmer than modern during the Early Holocene maximum in summer insolation. Chaoborus and chironomids in LIG sediments indicate July temperatures at least 5.5 to 8.5 °C warmer than modern. These estimates indicate pronounced warming in northwest Greenland during both interglacials. This helps explain dramatic ice sheet thinning at Camp Century in northwest Greenland during the Early Holocene and, for the LIG, aligns with controversial estimates of Eemian warming from ice core data retrieved in northern Greenland. Converging geologic evidence for strong LIG warming is challenging to reconcile with inferred Greenland Ice Sheet extent during the LIG, and the two appear incompatible in many models of ice sheet evolution. An increase in LIG snowfall could help resolve this problem, pointing to the need for hydroclimate reconstructions from the region.

Radiocarbon and Stable Isotope Evidence for Changes in Sediment Mixing in the North Pacific over the Past 30 kyrAbstract - Costa, Kassandra M; McManus, Jerry F; Anderson, Robert F (Radiocarbon, 2018)
Deep-sea sediment mixing by bioturbation is ubiquitous on the seafloor, and it can be an important influence on the fidelity of paleoceanographic records. Bioturbation can be difficult to quantify, especially in the past, but diffusive models based on radioactive tracer profiles have provided a relatively successful approach. However, a singular, constant mixing regime is unlikely to prevail in a region where dynamic oceanographic changes in the bottom water environment are a consequence of paleoclimatic variability. In this study, foraminiferal stable isotopes, radiocarbon (14C) dating, and 230Th fluxes are utilized to understand the sediment mixing history in the easternmost region of the North Pacific. In the uppermost sediment, a 12,000-yr offset between planktonic foraminifera species N. incompta and G. bulloides is observed that coincides with age plateaus at 2000–2500 yr for N. incompta and 15,000–16,000 yr for G. bulloides despite coincident glacial-interglacial shifts in δ18O of benthic species. These age plateaus, particularly for G. bulloides, are a result of changing foraminiferal abundance related to assemblage shifts and carbonate preservation changes since the last glacial period, providing a window into the extent of mixing in the past. The 14C and stable isotope results can be simulated using an iterative model that couples these changes in foraminiferal abundance with variability in mixing depth over time. The best-fit model output suggests that the deepest, or most intense, mixing of the past 30,000 yr (30 kyr) may have occurred during the Holocene. Even though changes in mixing affect the 14C and δ18O of planktonic species that have dramatically varying abundance, substantial age control is nevertheless provided by δ18O measurements on the more consistently abundant benthic foraminifera Uvigerina, thus allowing the construction of a reliable chronology for these cores.
Keywords: bioturbation; north pacific; radiocarbon; Stable isotopes

Radiocarbon Content of Dissolved Organic Carbon in the South Indian Ocean - Bercovici, S. K.; McNichol, A. P.; Xu, L.; Hansell, D. A. (Geophysical Research Letters, 2018)
We report four profiles of the radiocarbon content of dissolved organic carbon (DOC) spanning the South Indian Ocean (SIO), ranging from the Polar Front (56°S) to the subtropics (29°S). Surface waters held mean DOC Δ14C values of −426 ± 6‰ (~4,400 14C years) at the Polar Front and DOC Δ14C values of −252 ± 22‰ (~2,000 14C years) in the subtropics. At depth, Circumpolar Deep Waters held DOC Δ14C values of −491 ± 13‰ (~5,400 years), while values in Indian Deep Water were more depleted, holding DOC Δ14C values of −503 ± 8‰ (~5,600 14C years). High‐salinity North Atlantic Deep Water intruding into the deep SIO had a distinctly less depleted DOC Δ14C value of −481 ± 8‰ (~5,100 14C years). We use multiple linear regression to assess the dynamics of DOC Δ14C values in the deep Indian Ocean, finding that their distribution is characteristic of water masses in that region.
Keywords: dissolved organic carbon; indian ocean; radiocarbon

Recent occupation by Adélie Penguins (Pygoscelis adeliae) at Hope Bay and Seymour Island and the ‘northern enigma’ in the Antarctic Peninsula - Emslie, Steven D.; McKenzie, Ashley; Marti, Lucas J.; Santos, Mercedes (Polar Biology, 2018)
We excavated active and abandoned Adélie Penguin (Pygoscelis adeliae) colonies at Seymour Island and Hope Bay, Antarctic Peninsula, to determine an occupation history for this species at these sites. Previous research at Hope Bay has indicated an occupation there since the middle Holocene, based on a sediment record from Lake Boeckella. Excavations revealed only shallow and relatively fresh ornithogenic soils in the active colonies at the two localities. At least 53 abandoned pebble mounds were located at Hope Bay of which nine were excavated and four were sampled by probing to recover organic remains to determine their age. Radiocarbon dating of egg membrane, feather, and bone from both sites revealed a young occupation dating to less than ~600 years after correcting for the marine carbon reservoir effect. The mismatch in the geologic record of Adélie Penguin occupation in the northern Antarctic Peninsula, including Lake Boeckella sediments and geologic deposits and lake sediments on King George Island, with more direct evidence of breeding colonies from ornithogenic soils from active and abandoned colonies is hereby referred to as the ‘northern enigma’ as it does not occur in other regions of Antarctica including the southern Antarctic Peninsula, East Antarctica, or the Ross Sea, where the penguin record extends to the early to middle Holocene and matches well with the geologic record of deglaciation and penguin occupation. As yet, there is no convincing explanation for the ‘northern enigma’.

Remobilization of old permafrost carbon to Chukchi Sea sediments during the end of the last deglaciation - Martens, Jannik; Wild, Birgit; Pearce, Christof; Tesi, Tommaso; Andersson, August; Broder, Lisa; O’Regan, Matt; Jakobsson, Martin; Sköld, Martin; Gemery, Laura; Cronin, Thomas M.; Semiletov, Igor; et al. (Global Biogeochemical Cycles, 2018)
Climate warming is expected to destabilize permafrost carbon (PF‐C) by thaw‐erosion and deepening of the seasonally thawed active layer and thereby promote PF‐C mineralization to CO2 and CH4. A similar PF‐C remobilization might have contributed to the increase in atmospheric CO2 during deglacial warming after the last glacial maximum. Using carbon isotopes and terrestrial biomarkers (Δ14C, δ13C, and lignin phenols), this study quantifies deposition of terrestrial carbon originating from permafrost in sediments from the Chukchi Sea (core SWERUS‐L2‐4‐PC1). The sediment core reconstructs remobilization of permafrost carbon during the late Allerød warm period starting at 13,000 cal years before present (BP), the Younger Dryas, and the early Holocene warming until 11,000 cal years BP and compares this period with the late Holocene, from 3,650 years BP until present. Dual‐carbon‐isotope‐based source apportionment demonstrates that Ice Complex Deposit—ice‐ and carbon‐rich permafrost from the late Pleistocene (also referred to as Yedoma)—was the dominant source of organic carbon (66 ± 8%; mean ± standard deviation) to sediments during the end of the deglaciation, with fluxes more than twice as high (8.0 ± 4.6 g·m−2·year−1) as in the late Holocene (3.1 ± 1.0 g·m−2·year−1). These results are consistent with late deglacial PF‐C remobilization observed in a Laptev Sea record, yet in contrast with PF‐C sources, which at that location were dominated by active layer material from the Lena River watershed. Release of dormant PF‐C from erosion of coastal permafrost during the end of the last deglaciation indicates vulnerability of Ice Complex Deposit in response to future warming and sea level changes.
Keywords: carbon isotope; climate change feedback; coastal erosion; Deglaciation; past carbon cycling; permafrost

The rise and fall of an ancient Adélie penguin ‘supercolony’ at Cape Adare, Antarctica - Emslie, Steven D.; McKenzie, Ashley; Patterson, William P. (Royal Society Open Science, 2018)
We report new discoveries and radiocarbon dates on active and abandoned Adélie penguin (Pygoscelis adeliae) colonies at Cape Adare, Antarctica. This colony, first established at approximately 2000 BP (calendar years before present, i.e. 1950), is currently the largest for this species with approximately 338 000 breeding pairs, most located on low-lying Ridley Beach. We hypothesize that this colony first formed after fast ice began blocking open-water access by breeding penguins to the Scott Coast in the southern Ross Sea during a cooling period also at approximately 2000 BP. Our results suggest that the new colony at Cape Adare continued to grow, expanding to a large upper terrace above Ridley Beach, until it exceeded approximately 500 000 breeding pairs (a ‘supercolony’) by approximately 1200 BP. The high marine productivity associated with the Ross Sea polynya and continental shelf break supported this growth, but the colony collapsed to its present size for unknown reasons after approximately 1200 BP. Ridley Beach will probably be abandoned in the near future due to rising sea level in this region. We predict that penguins will retreat to higher elevations at Cape Adare and that the Scott Coast will be reoccupied by breeding penguins as fast ice continues to dissipate earlier each summer, restoring open-water access to beaches there.
Keywords: population movement; Pygoscelis adeliae; Ross Sea; sea level rise; Stable isotopes

The role of sediment compaction and groundwater withdrawal in local sea-level rise, Sandy Hook, New Jersey, USA - Johnson, Christopher S.; Miller, Kenneth G.; Browning, James V.; Kopp, Robert E.; Khan, Nicole S.; Fan, Ying; Stanford, Scott D.; Horton, Benjamin P. (Quaternary Science Reviews, 2018)
The rate of relative sea-level (RSL) rise at Sandy Hook, NJ (4.0 ± 0.5 mm/yr) was higher than The Battery, NY (3.0 ± 0.3 mm/yr) from 1900 to 2012 despite being separated by just 26 km. The difference cannot be explained by differential glacial isostatic adjustment (GIA; 1.4 ± 0.4 and 1.3 ± 0.4 mm/yr RSL rise, respectively) alone. We estimate the contribution of sediment compaction to subsidence at Sandy Hook using high-resolution grain size, percent organic matter, and porosity data from three upper Quaternary (≤13,350 cal yr) cores. The organic matter content (<2%) is too low to contribute to local subsidence. However, numerical modeling of the grain size-depth-age-porosity relationship indicates that compaction of deglacial silts likely reduced the column thickness by 10–20% over the past 13,350 cal yrs. While compaction rates were high immediately after the main silt deposition (13,350–13,150 cal yrs BP), rates decreased exponentially after deposition to an average 20th century rate of 0.16 mm/yr (90% Confidence Interval (C.I.), 0.06–0.32 mm/yr). The remaining ∼0.7 mm/yr (90% C.I. 0.3–1.2 mm/yr) difference in subsidence between Sandy Hook and The Battery is likely due to anthropogenic groundwater withdrawal. Historical data from Fort Hancock wells (2 km to the southeast of the Sandy Hook tide gauge) and previous regional work show that local and regional water extraction lowered the water levels in the aquifers underlying Sandy Hook. We suggest that the modern order of contribution to subsidence (highest to lowest) appears to be GIA, local/regional groundwater extraction, and compaction of thick Quaternary silts.
Keywords: Marginal marine; North America; numerical modeling; Quaternary; Sea-level change; sedimentology

Seafloor fluid seeps on Kimki Ridge, offshore southern California: Links to active strike-slip faulting - Conrad, James E.; Prouty, Nancy G.; Walton, Maureen A.L.; Kluesner, Jared W.; Maier, Katherine L.; McGann, Mary; Brothers, Daniel S.; Roland, Emily C.; Dartnell, Peter (Deep Sea Research Part II: Topical Studies in Oceanography, 2018)
The Kimki Ridge fluid seeps are located in western Catalina Basin about 60 km southwest of the southern California mainland and at a water depth of approximately 1100 m. Multichannel seismic reflection profiles collected by the U.S. Geological Survey (USGS) in 2014 show acoustic transparency within the Kimki Ridge, suggesting the possibility of fluid seeps and possible sub-seafloor fluid pathways. Subsequent multibeam bathymetric and backscatter intensity data collected during a cooperative University of Washington/USGS cruise in early 2016 show subtle seafloor buildups with high acoustic backscatter (reflectivity) in three places along Kimki Ridge, supporting the existence of fluid seepage. A Remotely Operated Vehicle (ROV) dive, conducted as part of the Nautilus Exploration Program, took place in August 2016 to confirm the presence of these previously unknown seeps and document their characteristics as well as those of any associated biological communities. Two of the three seeps were explored by ROV, and showed abundant evidence of fluid seepage, including characteristic algal mats, chemosynthetic clams, and authigenic carbonate formation. The seeps are comprised of carbonate buildups 1–3 m thick and 300–500 m across. Within these areas, we interpret broad crater-like depressions 30–50 m across and 1–2 m deep to be individual seep vents. The seep areas appear to be broad zones of diffuse seepage that support chemosynthetic biologic communities; however, active venting was not observed. Geochemical analyses of rock samples collected from the seeps indicate microbially driven anaerobic oxidation of methane at or near the sediment water interface. Seismic-reflection profiles show chimney-like fluid pathways along the limbs and in the axis of the fold forming Kimki Ridge, and evidence of methane in shallow sediments can be traced into the adjacent Catalina Basin. A system of closely spaced faults located at the axis of the Kimki Ridge anticline may serve as pathways to allow fluid flow to the seafloor. Our data are consistent with other studies that suggest that transpression is an important component in the formation and localization of fluid seeps in a strike-slip setting, implying that seep formation may be a common occurrence at fault stepovers or transpressional bends in strike-slip systems.
Keywords: California Inner Continental Borderland; E/V Nautilus; Faulting; methane; Seepages

Spatiotemporal Variation of the Quality, Origin, and Age of Particulate Organic Matter Transported by the Yangtze River (Changjiang) - Wu, Ying; Eglinton, Timothy I.; Zhang, Jing; Montluçon, Daniel B. (Journal of Geophysical Research: Biogeosciences, 2018)
Information on the age dynamics of particulate organic matter (POM) in large river systems is currently sparse and represents an important knowledge gap in our understanding of the global carbon cycle. Here we examine variations in organic geochemical characteristics of suspended sediments from the Changjiang (Yangtze River) system collected between 1997 and 2010. Higher particulate organic carbon content (POC%) values were observed in the middle reach, especially after 2003, and are attributed to the increase of in situ (aquatic) primary production associated with decreased total suspended matter concentrations. Corresponding C-14 values from depth profiles taken in 2009 and 2010 indicate spatial and temporal variations in POC sources within the basin. Two isotopic mass balance approaches were explored to quantitatively apportion different sources of Changjiang POM. Results indicate that contributions of biomass and pre-aged soil organic matter are dominant, regardless of hydrological conditions, with soil-derived organic carbon comprising 17-56% of POC based on a Monte Carlo three-end-member mixing model. In contrast, binary mixing model calculations suggest that up to 80% of POC (2009 samples only) derived from biospheric sources. The emplacement of the Three Gorges Dam and resulting trapping of sediment from the upper reach of the watershed resulted in a modification of POM C-14 ages in the reservoir. With the resulting decline in sediment load and increase in the proportion of modern POC in the lower reach, these changes in POM flux and composition of the Changjiang have significant implications for downstream carbon cycle processes.
Keywords: Changjiang; organic carbon; radiocarbon; suspended particulate matter; Three Gorges Dam

Tectonically-triggered sediment and carbon export to the Hadal zone - Bao, Rui; Strasser, Michael; McNichol, Ann P.; Haghipour, Negar; McIntyre, Cameron; Wefer, Gerold; Eglinton, Timothy I. (Nature Communications, 2018)
Sediments in deep ocean trenches may contain crucial information on past earthquake history and constitute important sites of carbon burial. Here we present 14C data on bulk organic carbon (OC) and its thermal decomposition fractions produced by ramped pyrolysis/oxidation for a core retrieved from the >7.5 km-deep Japan Trench. High-resolution 14C measurements, coupled with distinctive thermogram characteristics of OC, reveal hemipelagic sedimentation interrupted by episodic deposition of pre-aged OC in the trench. Low δ13C values and diverse 14C ages of thermal fractions imply that the latter material originates from the adjacent margin, and the co-occurrence of pre-aged OC with intervals corresponding to known earthquake events implies tectonically triggered, gravity-flow-driven supply. We show that 14C ages of thermal fractions can yield valuable chronological constraints on sedimentary sequences. Our findings shed new light on links between tectonically driven sedimentological processes and marine carbon cycling, with implications for carbon dynamics in hadal environments.

Tropical peatland carbon storage linked to global latitudinal trends in peat recalcitrance - Hodgkins, Suzanne B.; Richardson, Curtis J.; Dommain, René; Wang, Hongjun; Glaser, Paul H.; Verbeke, Brittany; Winkler, B. Rose; Cobb, Alexander R.; Rich, Virginia I.; Missilmani, Malak; Flanagan, Neal; Ho, Mengchi; et al. (Nature Communications, 2018)
Peatlands represent large terrestrial carbon banks. Given that most peat accumulates in boreal regions, where low temperatures and water saturation preserve organic matter, the existence of peat in (sub)tropical regions remains enigmatic. Here we examined peat and plant chemistry across a latitudinal transect from the Arctic to the tropics. Near-surface low-latitude peat has lower carbohydrate and greater aromatic content than near-surface high-latitude peat, creating a reduced oxidation state and resulting recalcitrance. This recalcitrance allows peat to persist in the (sub)tropics despite warm temperatures. Because we observed similar declines in carbohydrate content with depth in high-latitude peat, our data explain recent field-scale deep peat warming experiments in which catotelm (deeper) peat remained stable despite temperature increases up to 9 °C. We suggest that high-latitude deep peat reservoirs may be stabilized in the face of climate change by their ultimately lower carbohydrate and higher aromatic composition, similar to tropical peats.

The 3.6 ka Aniakchak tephra in the Arctic Ocean: a constraint on the Holocene radiocarbon reservoir age in the Chukchi Sea - Pearce, Christof; Varhelyi, Aron; Wastegård, Stefan; Muschitiello, Francesco; Barrientos, Natalia; O'Regan, Matt; Cronin, Thomas M.; Gemery, Laura; Semiletov, Igor; Backman, Jan; Jakobsson, Martin (Climate of the Past, 2017)
The caldera-forming eruption of the Aniakchak volcano in the Aleutian Range on the Alaskan Peninsula at 3.6 cal kyr BP was one of the largest Holocene eruptions worldwide. The resulting ash is found as a visible sediment layer in several Alaskan sites and as a cryptotephra on Newfoundland and Greenland. This large geographic distribution, combined with the fact that the eruption is relatively well constrained in time using radiocarbon dating of lake sediments and annual layer counts in ice cores, makes it an excellent stratigraphic marker for dating and correlating mid–late Holocene sediment and paleoclimate records. This study presents the outcome of a targeted search for the Aniakchak tephra in a marine sediment core from the Arctic Ocean, namely Core SWERUS-L2-2-PC1 (2PC), raised from 57 m water depth in Herald Canyon, western Chukchi Sea. High concentrations of tephra shards, with a geochemical signature matching that of Aniakchak ash, were observed across a more than 1.5 m long sediment sequence. Since the primary input of volcanic ash is through atmospheric transport, and assuming that bioturbation can account for mixing up to ca. 10 cm of the marine sediment deposited at the coring site, the broad signal is interpreted as sustained reworking at the sediment source input. The isochron is therefore placed at the base of the sudden increase in tephra concentrations rather than at the maximum concentration. This interpretation of major reworking is strengthened by analysis of grain size distribution which points to ice rafting as an important secondary transport mechanism of volcanic ash. Combined with radiocarbon dates on mollusks in the same sediment core, the volcanic marker is used to calculate a marine radiocarbon reservoir age offset ΔR = 477 ± 60 years. This relatively high value may be explained by the major influence of typically "carbon-old" Pacific waters, and it agrees well with recent estimates of ΔR along the northwest Alaskan coast, possibly indicating stable oceanographic conditions during the second half of the Holocene. Our use of a volcanic absolute age marker to obtain the marine reservoir age offset is the first of its kind in the Arctic Ocean and provides an important framework for improving chronologies and correlating marine sediment archives in this region. Core 2PC has a high sediment accumulation rate averaging 200 cm kyr throughout the last 4000 years, and the chronology presented here provides a solid base for high-resolution reconstructions of late Holocene climate and ocean variability in the Chukchi Sea.

A 7000-year history of coastal environmental changes from Mexico’s Pacific coast: A multi-proxy record from Laguna Mitla, Guerrero - Bianchette, Thomas A; McCloskey, Terrence A; Liu, Kam-biu (The Holocene, 2017)
The lack of multi-millennial multi-proxy paleoenvironmental reconstructions from Mexico’s Pacific coast has limited our understanding of the regional response to climate change and sea-level rise. A 479-cm core covering the last 6900 years was extracted from Laguna Mitla in the state of Guerrero on Mexico’s Pacific coast. Beginning as a Rhizophora-dominated salt pan ~6900 yr BP, at ~6500 yr BP, the site transitioned to a mangrove swamp dominated by Laguncularia, which lasted about 300 years. The beach barrier formed from ~6200 to 5200 yr BP, during which time, the site existed as an intermittently sheltered bay, the result of large, rapid changes in wave energy associated with the shifting barrier location and changes in stability. After the beach barrier was stabilized at ~5200 yr BP, water level at the coring site became a function of precipitation rather than sea level. Since that time, deposition has alternated between peat, laid down in a mangrove swamp, and clay intervals characterized by high concentrations of titanium and a predominantly regional pollen signal, representing open-water lagoon phases. Seven periods of increased water level, varying in duration, occurred during the backbarrier period, with El Niño-Southern Oscillation (ENSO) likely the main climatic mechanism causing these periodic shifts in the paleo-precipitation levels. We suggest that the deepest water levels detected over the last ~3200 years correlate with periods of increased ENSO activity. The spatial distribution of tropical cyclone rainfall, which represents a significant percentage of total annual precipitation along Mexico’s Pacific coast, may explain the inconsistencies between our record and paleoclimatic records from Mexico’s interior, but more work is needed to test this hypothesis.
Keywords: El Nino-Southern Oscillation; Laguna Mitla; mangroves; Pacific coast of Mexico; Paleoclimate; paleoenvironmental reconstruction; pollen; Sediment; tropical cyclones; x-ray fluorescence

Allochthonous sources and dynamic cycling of ocean dissolved organic carbon revealed by carbon isotopes - Zigah, Prosper K.; McNichol, Ann P.; Xu, Li; Johnson, Carl; Santinelli, Chiara; Karl, David M.; Repeta, Daniel J. (GEOPHYSICAL RESEARCH LETTERS, 2017)
We present concentration and isotopic profiles of total, size, and polarity fractionated dissolved organic carbon (DOC) from Station ALOHA (A Long-term Oligotrophic Habitat Assessment), an oligotrophic site in the North Pacific Ocean. The data show that, between the surface and 3500 m, low molecular weight (LMW) hydrophilic DOC, LMW hydrophobic DOC, and high molecular weight (HMW) DOC constitute 22-33%, 45-52%, and 23-35% of DOC, respectively. LMW hydrophilic DOC is more isotopically depleted (delta C-13 of -23.9 parts per thousand to -31.5 parts per thousand and Delta C-14 of -304 parts per thousand to -795 parts per thousand; mean age of 2850 to 15000 years) than the LMW hydrophobic DOC (delta C-13 of -22 parts per thousand to -23 parts per thousand and Delta C-14 of -270 parts per thousand to -568 parts per thousand; 2470 to 6680 years) and HMW DOC (delta C-13 of similar to-21 parts per thousand and Delta C-14 of -24 parts per thousand to -294 parts per thousand; 135-2700 years). Our analyses suggest that a large fraction of DOC may be derived from allochthonous sources such as terrestrial and hydrothermal DOC and cycle on much longer time scales of > 10000 years or enter the ocean as preaged carbon.
Keywords: ATLANTIC BIGHT; BLACK CARBON; C-14; HUMIC SUBSTANCES; MATTER; NORTH PACIFIC-OCEAN; RADIOCARBON ANALYSIS; SARGASSO SEA; SEAWATER; SPECTROMETRY

Anthropogenic CO2 accumulation and uptake rates in the Pacific Ocean based on changes in the C-13/C-12 of dissolved inorganic carbon - Quay, P.; Sonnerup, R.; Munro, D.; Sweeney, C. (GLOBAL BIOGEOCHEMICAL CYCLES, 2017)
The anthropogenic CO2 accumulation rate for the Pacific Ocean was estimated from the decrease in C-13 of the dissolved inorganic carbon measured on six World Ocean Circulation Experiment cruises during the 1990s and repeated during Climate Variability and Predictability in the 2000s. A mean depth-integrated anthropogenic C-13 change of -8320mdecade(-1) was estimated for the basin by using the multiple linear regression approach. The largest anthropogenic C-13 decreases occurred between 40 degrees S and 60 degrees S, whereas the smallest decreases occurred in the Southern Ocean and subpolar North Pacific. A mean anthropogenic CO2 accumulation rate of 0.410.13molCm(-2)yr(-1) (0.820.26PgCyr(-1)) was determined based on observed C-13 changes and is in agreement with previous observation- and model-based estimates. The mean dissolved inorganic carbon DIC13 inventory change of -178 +/- 43 parts per thousand molm(-2)decade(-1) was primarily the result of air-sea CO2 exchange acting on the measured air-sea C-13 disequilibrium of similar to-1.2 +/- 0.1 parts per thousand. Regional differences between the DIC13 inventory change and air-sea (CO2)-C-13 flux yielded net anthropogenic CO2 uptake rates (independent of pCO(2)) that ranged from similar to 0 to 1molm(-2)yr(-1) and basin-wide mean of 1.2 +/- 1.5PgCyr(-1). High rates of surface ocean DIC increase and C-13 decrease observed in the Drake Passage (53 degrees S-60 degrees S) support above average anthropogenic CO2 accumulation since 2005. Observed C-13 changes in the Pacific Ocean indicate that ocean transport significantly impacted the anthropogenic CO2 distribution and illustrate the utility of C-13 as a tracer to unravel the processes controlling the present and future accumulation of anth ropogenic CO2 in the ocean.
Keywords: anthropogenic change; C-12; C-13; CO2; Pacific Ocean

Assessing the Blank Carbon Contribution, Isotope Mass Balance, and Kinetic Isotope Fractionation of the Ramped Pyrolysis/Oxidation Instrument at NOSAMS - Hemingway, Jordon D; Galy, Valier V; Gagnon, Alan R; Grant, Katherine E; Rosengard, Sarah Z; Soulet, Guillaume; Zigah, Prosper K; McNichol, Ann P (Radiocarbon, 2017)
We estimate the blank carbon mass over the course of a typical Ramped PyrOx (RPO) analysis (150-1000 degrees C; 5 degrees C x min(-1)) to be (3.7 +/- 0.6) mu g C with an Fm value of 0.555 +/- 0.042 and a delta C-13 value of (-29.0 +/- 0.1)parts per thousand VPDB. Additionally, we provide equations for RPO Fm and delta C-13 blank corrections, including associated error propagation. By comparing RPO mass-weighted mean and independently measured bulk delta C-13 values for a compilation of environmental samples and standard reference materials (SRMs), we observe a small yet consistent delta C-13 depletion within the RPO instrument (mean-bulk: mu = -0.8 parts per thousand; +/- 1 sigma = 0.9 parts per thousand; n = 66). In contrast, because they are fractionation-corrected by definition, mass-weighted mean Fm values accurately match bulk measurements (mean-bulk: mu = 0.005; +/- 1 sigma = 0.014; n = 36). Lastly, we show there exists no significant intra-sample delta C-13 variability across carbonate SRM peaks, indicating minimal mass-dependent kinetic isotope fractionation during RPO analysis. These data are best explained by a difference in activation energy between C-13- and C-12-containing compounds ((13-12)Delta E) of 0.3-1.8 J x mol(-1), indicating that blank and mass-balance corrected RPO delta C-13 values accurately retain carbon source isotope signals to within 1-2 parts per thousand.
Keywords: Ramped PyrOx; blank assessment; kinetic fractionation

Biological and physical controls on the flux and characteristics of sinking particles on the Northwest Atlantic margin - Hwang, Jeomshik; Manganini, Steven J.; Park, JongJin; çon, Daniel B.; Toole, John M.; Eglinton, Timothy I. (Journal of Geophysical Research: Oceans, 2017)
Biogenic matter characteristics and radiocarbon contents of organic carbon (OC) were examined on sinking particle samples intercepted at three nominal depths of 1000 m, 2000 m, and 3000 m (similar to 50 m above the seafloor) during a 3 year sediment trap program on the New England slope in the Northwest Atlantic. We have sought to characterize the sources of sinking particles in the context of vertical export of biogenic particles from the overlying water column and lateral supply of resuspended sediment particles from adjacent margin sediments. High aluminum (Al) abundances and low OC radiocarbon contents indicated contributions from resuspended sediment which was greatest at 3000 m but also significant at shallower depths. The benthic source (i.e., laterally supplied resuspended sediment) of opal appears negligible based on the absence of a correlation with Al fluxes. In comparison, CaCO3 fluxes at 3000 m showed a positive correlation with Al fluxes. Benthic sources accounted for 42 similar to 63% of the sinking particle flux based on radiocarbon mass balance and the relationship between Al flux and CaCO3 flux. Episodic pulses of Al at 3000 m were significantly correlated with the near-bottom current at a nearby hydrographic mooring site, implying the importance of current variability in lateral particle transport. However, Al fluxes at 1000 m and 2000 m were coherent but differed from those at 3000 m, implying more than one mode of lateral supply of particles in the water column.

Carbonization, differential preservation, and sampling biases in domestication studies: An erect knotweed ( Polygonum erectum L.) case study - Mueller, Natalie G. (Journal of Archaeological Science: Reports, 2017)
Population morphometrics can be employed to explore the process of domestication, but only after accounting for biases introduced by taphonomic processes and sampling. For every cultivated plant, the challenges associated with carbonization, differential preservation, and sampling bias are different, as are the morphological characteristics of interest in domestication studies. This case study establishes correction factors and sampling parameters for assessing morphological indicators of domestication in erect knotweed (Polygonum erectum L.), an annual plant that was cultivated by Indigenous people in Eastern North America for about 2500 years. Documenting the unique domestication syndrome of erect knotweed creates three different sets of taphonomic and sampling problems that need to be addressed through experimentation and modeling: 1) Assess the morphometric effects of carbonization; 2) assess the effects of differential preservation; and 3) assess the effects of sampling error. The results of this study can be used by other analysts to identify domesticated assemblages of erect knotweed. These analyses also have implications for studies of plant domestication from the morphology of archaeological assemblages in general, especially when nominal variables are used to differentiate wild from domesticated populations (for example, the presence/absence of an abscission scar in cereals or the seed coat texture of chenopods).

Changes in glacial meltwater alter algal communities in lakes of Scoresby Sund, Renland, East Greenland throughout the Holocene: Abrupt reorganizations began 1000 years before present - Slemmons, Krista EH; Medford, Aaron; Hall, Brenda L; Stone, Jeffery R; McGowan, Suzanne; Lowell, Thomas; Kelly, Meredith; Saros, Jasmine E (The Holocene, 2017)
We investigated the response of lake algal communities to changes in glacial meltwater from the Renland Ice Cap (Greenland) through the Holocene to assess whether influxes always elicit consistent responses or novel responses. We measured sedimentary algal pigments in two proximal lakes, snow-fed Raven and glacier- and snow-fed Bunny Lake, and diatom community structure and turnover in Bunny Lake. Diatom data were not available in Raven Lake. We also modeled lake-level change in Bunny Lake to identify how glacial meltwater may have altered diatom habitat availability through time. Through a series of glacier advances and retreats over the Holocene, the algal response in Bunny Lake was relatively constant until approximately 1015 yr BP, after which there were major changes in sedimentary algal remains. Algal pigment concentrations sharply declined, and diatom species richness increased. Diatom community structure underwent three reorganizations. Until 1015 yr BP, assemblages were dominated by Pinnularia braunii and Aulacoseira pffaffiana. However, approximately 1015–480 yr BP, these species declined and Tabellaria flocculosa and Hannaea arcus became a significant component of the assemblage. Approximately 440 yr BP, A. pfaffiana increased along with species indicating elevated nitrogen. In contrast, the algal pigment records from nearby snow-fed Raven Lake showed different and minimal change through time. Our results suggest that changes in the magnitude and composition of meltwater in our two study lakes were unique over the last 1000 yr BP and elicited a non-linear threshold response absent during other periods of glacier advance and retreat. Deciphering the degree to which glaciers structure algal communities over time has strong implications for lakes as glaciers continue to recede.
Keywords: climate; Diatom; East Greenland; glacier; Holocene; Lake level

Climate-related response of dust flux to the central equatorial Pacific over the past 150 kyr - Jacobel, A.W.; McManus, J.F.; Anderson, R.F.; Winckler, G. (Earth and Planetary Science Letters, 2017)
High resolution paleoclimate records from low latitudes are critical for understanding the role of the tropics in transmitting and generating feedbacks for high-latitude climate change on glacial–interglacial and millennial timescales. Here we present three new records of 230Thxs,0-normalized 232Th-derived dust fluxes from the central equatorial Pacific spanning the last 150 kyr at millennial-resolution. All three dust flux records share the “sawtooth” pattern characteristic of glacial–interglacial cycles in ice volume, confirming a coherent response to global climate forcing on long timescales. These records permit a detailed examination of millennial variability in tropical dust fluxes related to abrupt perturbations in oceanic and atmospheric circulation. Increases in dust flux in association with at least six of the longest Greenland stadials provide evidence that abrupt, high-latitude climate oscillations influenced the atmospheric aerosol load in the equatorial Pacific, with implications for both direct and indirect effects on the tropical energy balance. Our latitudinal transect of cores captures shifts in the position of the Intertropical Convergence Zone (ITCZ) in response to variations in the interhemispheric thermal gradient associated with cooling in Greenland and bipolar seesaw warming in Antarctica. These observations demonstrate that changes in the energy and hydrologic balance of the tropics were repeated features of the penultimate deglaciation, last glacial inception and last glacial cycle, and highlight the role of the tropical atmosphere as a dynamic and responsive component of Earth's climate system.
Keywords: abrupt climate change; dust; equatorial pacific; Intertropical Convergence Zone; stadial events

Coastal Research LibraryCoastline Changes of the Baltic Sea from South to EastConstraints of Radiocarbon Dating in Southeastern Baltic Lagoons: Assessing the Vital Effects - Bitinas, Albertas; žeika, Jonas; Buynevich, Ilya V.; šytė, Aldona; Molodkov, Anatoly; ė, Alma (Coastline Changes of the Baltic Sea from South to East, 2017)
During the past decades, a suite of radiocarbon (14C), infrared optically stimulated luminescence (IR-OSL), and electron spin resonance (ESR) dates were compiled on a variety of materials from the Curonian and Vistula lagoons and spits of the southeastern Baltic Sea. These dated materials generally included lagoon sediments and mollusc shells, along with samples of fossil fish remains, peat, wood, and water bicarbonates. A growing number of 14C dates (conventional and AMS) demonstrates disparities and contradictions with the associated IR-OSL dates and palaeobotanical investigations of contemporary materials. Detailed analyses of 14C, IR-OSL and ESR chronologies and experimental 14C dating of modern live molluscs and water bicarbonates from the Curonian Lagoon and its main tributary – Nemunas-Neris River system – reveals a substantial influx of “old” carbonates into the lagoon. As a result, the uncertainty of reservoir effect added a considerable error to the 14C ages. Moreover, fossil molluscs of the same species extracted from boreholes and outcrops yield significantly younger ages (up to several millennia) than the enclosing sediments. Both of these trends – aging and rejuvenation – highlight an urgent need for constraining the local reservoir correction (ΔR). Several scenarios are presented to explain the impact of vital effects on radiocarbon chronology of carbonates and to offer strategies to account for them in future studies.
Keywords: Curonian lagoon; ESR; IR-OSL; Molluscs; radiocarbon; Reservoir effect; Vistula lagoon

Compilation of geophysical, geochronological, and geochemical evidence indicates a rapid Mediterranean-derived submergence of the Black Sea's shelf and subsequent substantial salinification in the early Holocene - Yanchilina, Anastasia G.; Ryan, William B.F.; McManus, Jerry F.; Dimitrov, Petko; Dimitrov, Dimitar; Slavova, Krasimira; Filipova-Marinova, Mariana (Marine Geology, 2017)
Our knowledge of rate and processes in which semi-enclosed environments alternate from lacustrine to marine is commonly limited because of the paucity of specific proxies for sea level and salinity. Here we investigate the timing, rate, and key mechanisms involved in the transformation of the previously isolated Black Sea-Lake to the modern partly-enclosed marine sea using a suite of geophysical, geochemical, and geochronological methods. Cores were collected in transects across shelves of Ukraine, Romania, Bulgaria, and Turkey. Biogenic carbonate from these cores was analyzed for radiocarbon and strontium, oxygen, and carbon isotopes. Strontium results indicate that the submergence of the Black Sea shelf at 9300 calendar years BP was caused by the ingress of Mediterranean water and was abrupt, taking < 40 years. The seismic reflection profiles show a uniform drape of subsequent sediment over aeolian dunes indicating a drowning with no time for erosion accompanying the submergence. Moisture measurements beneath the uniform drape indicate that the shelf was dry before submergence and the shoreline of the Preboreal lake may have regressed to beyond 120 mbsl. Mollusks colonized the newly submerged substrate of the inner shelf at the same time as they colonized the outer shelf. The succession of mollusk species with shells whose strontium isotope composition has a marine component indicates a rising salinity. The transformation of the lake to a sea is affirmed by increases in the shells' strontium and oxygen isotopic ratios towards the external ocean value. Radiocarbon years are calibrated to calendar years by tuning the oxygen and carbon isotope composition of the mollusk record to that of the U/Th dated Sofular Cave stalagmites. The match shows a reduction of the lake's prior high reservoir age accompanying the inflow of the Mediterranean water. In 900 years the salinity reached a threshold that excluded all previous Black Sea lacustrine fauna. These results imply that any substantial postglacial submergence of the Black Sea shelves did not occur prior to entry of Mediterranean water.
Keywords: Black Sea; Black Sea transgression; Isotope geochemistry; Lake transgression; Marine-lake connections; paleoceanography; paleosalinity; Reflection profiles

Comprehensive radiocarbon analysis of benzene polycarboxylic acids (BPCAs) derived from pyrogenic carbon in environmental samples - Hanke, U M; Wacker, L; Haghipour, N; Schmidt, M W I; Eglinton, T I; McIntyre, C P (Radiocarbon, 2017)
Compound-specific radiocarbon analysis (CSRA) of benzene polycarboxylic acids (BPCAs) yields molecular-level, source-specific information necessary to constrain isotopic signatures of pyrogenic carbon. However, the purification of individual BPCAs requires a multistep procedure that typically results in only microgram quantities of the target analyte(s). Such small samples are highly susceptible to contamination by extraneous carbon, which needs to be minimized and carefully accounted for in order to yield accurate results. Here, we undertook comprehensive characterization and quantification of contamination associated with molecular radiocarbon (14C) BPCA analyses through systematic processing of multiple authentic standards with both fossil and modern 14C signatures at various concentrations. Using this approach, we precisely apportion the contribution of extraneous carbon with respect to the four implemented subprocedures. Assuming a constant source and quantity of extraneous carbon we correct and statistically evaluate uncertainties in resulting 14C data. Subsequently, we examine the results of triplicate analyses of reference materials representing four different environmental matrices (sediment, soil, aerosol, riverine natural organic matter) and apportion their BPCA sources in terms of carbon residues derived from biomass or fossil fuel combustion. This comprehensive approach to CSRA facilitates retrieval of robust 14C data, with application in environmental studies of the continuum of pyrogenic carbon.

Constraining the sources and cycling of dissolved organic carbon in a large oligotrophic lake using radiocarbon analyses - Prosper K. Zigah; Elizabeth C. Minor; Ann P. McNichol; Li Xu; Josef P. Werne (Geochimica et Cosmochimica Acta, 2017)
Abstract We measured the concentrations and isotopic compositions of solid phase extracted (SPE) dissolved organic carbon (DOC) and high molecular weight (HMW) \{DOC\} and their constituent organic components in order to better constrain the sources and cycling of \{DOC\} in a large oligotrophic lacustrine system (Lake Superior, North America). \{SPE\} \{DOC\} constituted a significant proportion (41-71%) of the lake \{DOC\} relative to \{HMW\} \{DOC\} (10-13%). Substantial contribution of 14C-depleted components to both \{SPE\} \{DOC\} (Δ14C = 25 to 43‰) and \{HMW\} \{DOC\} (Δ14C = 22 to 32‰) was evident during spring mixing, and depressed their radiocarbon values relative to the lake dissolved inorganic carbon (DIC; Δ14C ∼ 59‰). There was preferential removal of 14C-depleted (older) and thermally recalcitrant components from \{HMW\} \{DOC\} and \{SPE\} \{DOC\} in the summer. Contemporary photoautotrophic addition to \{HMW\} \{DOC\} was observed during summer stratification in contrast to \{SPE\} DOC, which decreased in concentration during stratification. Serial thermal oxidation radiocarbon analysis revealed a diversity of sources (both contemporary and older) within the \{SPE\} DOC, and also showed distinct components within the \{HMW\} DOC. The thermally labile components of \{HMW\} \{DOC\} were 14C-enriched and are attributed to heteropolysaccharides (HPS), peptides/amide and amino sugars (AMS) relative to the thermally recalcitrant components reflecting the presence of older material, perhaps carboxylic-rich alicyclic molecules (CRAM). The solvent extractable lipid-like fraction of \{HMW\} \{DOC\} was very 14C-depleted (as old as 1270-2320 14C years) relative to the substances isolated by acid hydrolysis of \{HMW\} DOC. Our data constrain relative influences of contemporary \{DOC\} and old DOC, and \{DOC\} cycling in a modern freshwater ecosystem.
Keywords: atmospheric co2; Carbohydrate-like substance; Carboxylic-rich alicyclic molecules (CRAM); Contemporary DOC; dissolved inorganic carbon; dissolved organic carbon; Freshwater carbon cycling; Heteropolysaccharides (HPS); High molecular weight DOC; Lake Superior; Lipid-like fraction; Old DOC; Oligotrophic lake; Protein-like substance; radiocarbon; Serial thermal oxidation; Solid phase extracted DOC; Stable isotope; Unhydrolysable material

Coupling of the Intertropical Convergence Zone and Southern Hemisphere mid-latitude climate during the early to mid-Holocene - Mariani, Michela; Fletcher, Michael-Shawn; Drysdale, Russell N.; Saunders, Krystyna M.; Heijnis, Henk; Jacobsen, Geraldine; Zawadzki, Atun (Geology, 2017)
Conceptual models predict a tight coupling between the Intertropical Convergence Zone (ITCZ) and the Southern Westerly Winds (SWW) in response to glacial-interglacial transitions, yet little is known about this relationship under Holocene boundary conditions. Here we present a synthesis of Holocene pollen data from the southwest Pacific mid-latitudes that tracks changes in the SWW. Comparison of our SWW paleoclimate records with data tracking the ITCZ, oceanic circulation, and insolation reveals clearly synchronous and in-phase ITCZ-SWW dynamics between 12 and 5 ka, indicating a tight coupling between the tropics and southern mid-latitudes in response to ocean circulation and insolation. An apparent decoupling of the SWW and ITCZ in the Pacific region after 5 ka is attributable to the overriding influence of the El Niño–Southern Oscillation (ENSO) over the proxy data.

The De Long Trough: a newly discovered glacial trough on the East Siberian continental margin - O'Regan, Matt; Backman, Jan; Barrientos, Natalia; Cronin, Thomas M.; Gemery, Laura; Kirchner, Nina; Mayer, Larry A.; Nilsson, Johan; Noormets, Riko; Pearce, Christof; Semiletov, Igor; Stranne, Christian; et al. (Climate of the Past, 2017)
Ice sheets extending over parts of the East Siberian continental shelf have been proposed for the last glacial period and during the larger Pleistocene glaciations. The sparse data available over this sector of the Arctic Ocean have left the timing, extent and even existence of these ice sheets largely unresolved. Here we present new geophysical mapping and sediment coring data from the East Siberian shelf and slope collected during the 2014 SWERUS-C3 expedition (SWERUS-C3: Swedish – Russian – US Arctic Ocean Investigation of Climate-Cryosphere-Carbon Interactions). The multibeam bathymetry and chirp sub-bottom profiles reveal a set of glacial landforms that include grounding zone formations along the outer continental shelf, seaward of which lies a  >  65 m thick sequence of glacio-genic debris flows. The glacial landforms are interpreted to lie at the seaward end of a glacial trough – the first to be reported on the East Siberian margin, here referred to as the De Long Trough because of its location due north of the De Long Islands. Stratigraphy and dating of sediment cores show that a drape of acoustically laminated sediments covering the glacial deposits is older than ∼ 50 cal kyr BP. This provides direct evidence for extensive glacial activity on the Siberian shelf that predates the Last Glacial Maximum and most likely occurred during the Saalian (Marine Isotope Stage (MIS) 6).

Deglaciation and ice shelf development at the northeast margin of the Laurentide Ice Sheet during the Younger Dryas chronozone - Furze, Mark F. A.; ńkowski, Anna J.; McNeely, Morgan A.; Bennett, Robbie; Cage, Alix G. (Boreas, 2017)
Core 2011804-0010 from easternmost Lancaster Sound provides important insights into deglacial timing and style at the marine margin of the NE Laurentide Ice Sheet (LIS). Spanning 13.2–11.0 cal. ka BP and investigated for ice-rafted debris (IRD), foraminifera, biogenic silica and total organic carbon, the stratigraphy comprises a lithofacies progression from proximal grounding line and sub-ice shelf environments to open glaciomarine deposition; a sequence similar to deposits from Antarctic ice shelves. These results are the first marine evidence of a former ice shelf in the eastern Northwest Passage and are consistent with a preceding phase of ice streaming in eastern Lancaster Sound. Initial glacial float-off and retreat occurred >13.2 cal. ka BP, followed by formation of an extensive deglacial ice shelf during the Younger Dryas, which acted to stabilize the retreating margin of the NE LIS until 12.5 cal. ka BP. IRD analyses of sub-ice shelf facies indicate initial high input from source areas on northern Baffin Island delivered to Lancaster Sound by a tributary ice stream in Admiralty Inlet. After ice shelf break-up, Bylot Island became the dominant source area. Foraminifera are dominated by characteristic ice-proximal glaciomarine benthics (Cassidulina reniforme, Elphidium excavatum f. clavata), complemented by advected Atlantic water (Cassidulina neoteretis, Neogloboquadrina pachyderma) and enhanced current indicators (Lobatula lobatula). The biostratigraphy further supports the ice shelf model, with advection of sparse faunas beneath the ice shelf, followed by increased productivity under open water glaciomarine conditions. The absence of Holocene sediments in the core suggests that the uppermost deposits were removed, most likely due to mass transport resulting from the site's proximity to modern tidewater glacier margins. Collectively, this study presents important new constraints on the deglacial behaviour of the NE Laurentide Ice Sheet, with implications for past ice sheet stability, ice-rafted sediment delivery, and ice−ocean interactions in this complex archipelago setting.

Documenting domestication in a lost crop (Polygonum erectum L.): evolutionary bet-hedgers under cultivation - Mueller, Natalie G. (Vegetation History and Archaeobotany, 2017)
This study uses morphometrics and digital image analysis to document domestication syndrome in an annual seed crop, Polygonum erectum L. (erect knotweed), which was cultivated by Native Americans for c. 2,500 years in eastern North America. This plant is one of several seed crops referred to as the Eastern Agricultural Complex, a pre-maize agricultural system that supported societies in a core area centred on the central Mississippi valley for millennia. The extinct domesticated subspecies P. erectum ssp. watsoniae N. G. Muell. described here, exhibits some classic markers of domestication, including larger fruits and reduced germination inhibitors in comparison to its wild progenitor. Domesticated P. erectum also exhibits greatly reduced germination heteromorphism. Germination heteromorphism is the classic example of evolutionary bet-hedging in plants: wild P. erectum sacrifices maximum fitness per generation for a reduction in fitness variance over many generations. It does so by producing two different types of fruits: ones that germinate immediately in the spring after they are produced (smooth morphs), and ones that remain in the soil seed bank for one or more growing seasons before germinating (tubercled morphs). Tubercled morphs allow populations to recover after adverse events. Under cultivation, the selective pressures that maintained this strategy were relaxed as humans saved seeds and created predictable microenvironments for seedlings, resulting in homogenous harvests and reliable germination for ancient farmers.
Keywords: Domestication; Eastern Agricultural Complex; Evolutionary bet-hedging; Morphometrics; Origins of agriculture

Dynamics of marsh-mangrove ecotone since the mid-Holocene: A palynological study of mangrove encroachment and sea level rise in the Shark River Estuary, Florida - Yao, Qiang; Liu, Kam-biu (PLOS ONE, 2017)
Sea level rise and the associated inland shift of the marsh-mangrove ecotone in south Florida have raised many scientific and management concerns in recent years. Holocene paleoecological records can provide an important baseline to shed light on the long-term dynamics of vegetation changes across this ecotone in the past, which is needed to predict the future. In this study, we present palynological, X-ray fluorescence, and loss-on ignition data from four sedimentary cores recovered from a 20-km marine-to-freshwater transect along the Shark River Estuary, southwest Everglades, to document the patterns and processes of coastal vegetation changes in response to sea level rise since the mid-Holocene. Our record indicates that freshwater marsh progressively replaced marl prairies at the Shark River Estuary between 5700 and 4400 cal yr BP. As marine transgression continued, marine influence reached the threshold necessary for mangroves to establish at the current mouth of the Shark River Slough at 3800 cal yr BP. During the next 3000 years, although sea level rise in the Western North Atlantic slowed down to 0.4 mm/yr, a spatial and temporal gradient was evident as the marsh-mangrove ecotone shifted inland by 20 km from 3800 to 800 cal yr BP, accompanied by a gradual landward replacement of freshwater marsh by mangrove forest. If sea level continues to rise at 2.33 mm/yr in the 21st century in south Florida, it is possible that marine influence will reach the threshold for mangroves to establish in the central Everglades, and we could expect a much more aggressive mangrove encroachment toward the northern and interior parts of south Florida in the next few centuries.

Equilibrium line altitudes along the Andes during the Last millennium: Paleoclimatic implications - Sagredo, Esteban A; Lowell, Thomas V; Kelly, Meredith A; Rupper, Summer; Aravena, Juan Carlos; Ward, Dylan J; Malone, Andrew GO (The Holocene, 2017)
Deciphering the climate changes that influenced the glacial fluctuations of the last millennium requires documenting the spatial and temporal patterns of these glacial events. Here, we estimate the change in equilibrium line altitudes (ELAs) between the most prominent glacial advance of the last millennium and the present for four alpine glaciers located in different climatic regimes along the Andes. For each glacier, we reconstruct scenarios of climatic conditions (temperature and precipitation anomalies) that accommodate the observed ELA changes. We focus on the following glaciers: an alpine glacier in the Cordillera Vilcanota (13°S), Tapado glacier (30°S), Cipreses glacier (34°S), and Tranquilo glacier (47°S). Our results show that the range of possible temperature and precipitation anomalies that accommodate the observed ELA changes overlap significantly at three of the four sites (i.e. Vilcanota, Cipreses, and Tranquilo). Only Tapado glacier exhibits a set of climate anomalies that differs from the other three sites. Assuming no change in precipitation, the estimated ELA changes require a cooling of at least 0.7°C in the Cordillera Vilcanota, 1.0°C at Tapado glacier, 0.6°C at Cipreses glacier, and 0.7°C at Tranquilo glacier. Conversely, assuming no change in temperature, the estimated ELA changes are explained by increases in precipitation exceeding 0.52 m yr−1 (64% of the annual precipitation) in the Cordillera Vilcanota, 0.31 m yr−1 (89%) at Tapado glacier, 0.22 m yr−1 (27%) at Cipreses glacier, and 0.3 m yr−1 (27%) at Tranquilo glacier. By mapping the ELA changes and modeling the potential climate forcing across diverse climate settings, we aim to contribute toward documenting the spatial variability of climate conditions during the last millennium, a key step to decipher the mechanisms underlying the glacial fluctuation that occurred during this period.
Keywords: Andes; equilibrium line altitude; glacial fluctuations; glacial reconstruction; Holocene; last millennium

Evidence for coseismic subsidence events in a southern California coastal saltmarsh - Leeper, Robert; Rhodes, Brady; Kirby, Matthew; Scharer, Katherine; Carlin, Joseph; Hemphill-Haley, Eileen; Avnaim-Katav, Simona; MacDonald, Glen; Starratt, Scott; Aranda, Angela (Scientific Reports, 2017)
Paleoenvironmental records from a southern California coastal saltmarsh reveal evidence for repeated late Holocene coseismic subsidence events. Field analysis of sediment gouge cores established discrete lithostratigraphic units extend across the wetland. Detailed sediment analyses reveal abrupt changes in lithology, percent total organic matter, grain size, and magnetic susceptibility. Microfossil analyses indicate that predominantly freshwater deposits bury relic intertidal deposits at three distinct depths. Radiocarbon dating indicates that the three burial events occurred in the last 2000 calendar years. Two of the three events are contemporaneous with large-magnitude paleoearthquakes along the Newport-Inglewood/Rose Canyon fault system. From these data, we infer that during large magnitude earthquakes a step-over along the fault zone results in the vertical displacement of an approximately 5-km2 area that is consistent with the footprint of an estuary identified in pre-development maps. These findings provide insight on the evolution of the saltmarsh, coseismic deformation and earthquake recurrence in a wide area of southern California, and sensitive habitat already threatened by eustatic sea level rise.
Keywords: Geomorphology; Natural hazards; Structural geology; tectonics

Evolutionary “Bet-Hedgers” under Cultivation: Investigating the Domestication of Erect Knotweed (Polygonum erectum L.) using Growth Experiments - Mueller, Natalie G. (Human Ecology, 2017)
Evolutionary “bet-hedging” refers to situations in which organisms sacrifice mean fitness for a reduction in fitness variance over time. Germination heteromorphism is the quintessential and most well understood bet-hedging strategy. It has evolved in many different plants, including the wild progenitors of some crops. Erect knotweed (Polygonum erectum L.), an annual seed crop, was cultivated in Eastern North America between c. 3000–600 BP. By c. 900 BP, cultivation had produced a domesticated subspecies with greatly reduced germination heteromorphism. Field observations and greenhouse experiments suggest that cultivation eliminated the selective pressures that maintain the bet-hedging strategy in erect knotweed, while humans also directly selected for seeds that germinated reliably and for seedlings with rapid early growth. The protection provided to erect knotweed under cultivation explains the domestication syndrome that has been observed in some archaeological assemblages. Dormancy provides seeds a means of escaping adverse conditions in time, while dispersal provides an escape in space. Farmers relaxed selective pressures that maintained dormancy in erect knotweed by acting as seed dispersers, spreading disturbance-adapted plants to predictable and protected environments, and by saving and exchanging seed stock. Experimental data also indicate that adaptive transgenerational plasticity may have been working against the expression of domestication syndrome in this case.
Keywords: Domestication; Eastern agricultural complex North America; Erect knotweed; Evolutionary bet-hedging; Experimental archaeology

Extended late Holocene relative sea-level histories for North Carolina, \{USA\} - Andrew C. Kemp; Jessica J. Kegel; Stephen J. Culver; Donald C. Barber; David J. Mallinson; Eduardo Leorri; Christopher E. Bernhardt; Niamh Cahill; Stanley R. Riggs; Anna L. Woodson; Ryan P. Mulligan; Benjamin P. Horton (Quaternary Science Reviews, 2017)
Abstract We produced ∼3000-year long relative sea-level (RSL) histories for two sites in North Carolina (USA) using foraminifera preserved in new and existing cores of dated salt-marsh sediment. At Cedar Island, \{RSL\} rose by ∼2.4 m during the past ∼3000 years compared to ∼3.3 m at Roanoke Island. This spatial difference arises primarily from differential \{GIA\} that caused late Holocene \{RSL\} rise to be 0.1–0.2 mm/yr faster at Roanoke Island than at Cedar Island. However, a non-linear difference in \{RSL\} between the two study regions (particularly from ∼0 \{CE\} to ∼1250 CE) indicates that additional local- to regional-scale processes drove centennial-scale \{RSL\} change in North Carolina. Therefore, the Cedar Island and Roanoke Island records should be considered as independent of one another. Between-site differences on sub-millennial timescales cannot be adequately explained by non-stationary tides, sediment compaction, or local sediment dynamics. We propose that a period of accelerating \{RSL\} rise from ∼600 \{CE\} to 1100 \{CE\} that is present at Roanoke Island (and other sites north of Cape Hatteras at least as far as Connecticut), but absent at Cedar Island (and other sites south of Cape Hatteras at least as far as northeastern Florida) is a local-to regional-scale effect of dynamic ocean and/or atmospheric circulation.
Keywords: Salt marsh

An Extinct Domesticated Subspecies of Erect Knotweed in Eastern North America: Polygonum erectum subsp. watsoniae (Polygonaceae) - Mueller, Natalie G. (Novon: A Journal for Botanical Nomenclature, 2017)
This paper provides a description of an extinct domesticated subspecies of erect knotweed (Polygonum erectum L.). Masses of erect knotweed achenes are often recovered from archaeological sites in eastern North America dating to ca. 3000–600 BP. Several paleoethnobotanical assemblages from the later part of this era (ca. 1000–600 BP) contain achenes that are outside the range of natural variation for erect knotweed. The most well preserved of these archaeological assemblages, a desiccated cache of achenes from the Whitney Bluff site, Arkansas (ca. 900 BP), is compared to four closely related species and subspecies of Polygonum L. The Whitney Bluff achenes are most similar to those of P. erectum, but differ from modern fruits of this species in three respects: (1) fruits are larger, (2) average pericarp thickness is reduced, and (3) fruit dimorphism is greatly reduced. These differences are typical of domestication syndrome in annual seed crops. The Whitney Bluff assemblage is described as the type specimen of a domesticated subspecies, P. erectum subsp. watsoniae N. G. Muell.
Keywords: Domestication; Eastern Agricultural Complex; fruit morphology; paleoethnobotany; Polygonum

Final Radiocarbon Investigation of Platland Tree, the Biggest African Baobab - Patrut, Adrian; Woodborne, Stephan; Patrut, Roxana T.; Rakosy, Laszlo; Hall, Grant; Ratiu, Ileana-Andreea; von Reden, Karl F. (Studia Universitatis Babeș-Bolyai Chemia, 2017)
The article discloses the main results of our new investigation of Platland tree, a.k.a. Sunland baobab, the largest known African baobab. Our recent research was motivated by the three successive splits of 2016 and 2017, which determined the collapse and demise of the stems that have built the main unit of the tree. According to our new findings concerning the architecture of large and old baobabs, we established that Platland tree has a double closed-ring shaped structure and consists of two units/rings that close two separate false cavities. The larger unit was composed of five fused stems, out of which four toppled and died, while the fifth stem is already broken. The smaller unit, which is still standing, consists of three fused stems. We also determined that the larger unit had an age of 800 yr, while the smaller unit is 1100 yr old.

The Growth Stop Phenomenon Of Baobabs (Adansonia Spp.) Identified By Radiocarbon DatingAbstract - Patrut, Adrian; Woodborne, Stephan; von Reden, Karl F; Hall, Grant; Patrut, Roxana T; Rakosy, Laszlo; Danthu, Pascal; Pock-Tsy, Jean-Michel Leong; Lowy, Daniel A; Margineanu, Dragos (Radiocarbon, 2017)
The article reports the growth stop phenomenon, which was documented only for baobabs, i.e. for trees belonging to the Adansonia genus. The identification of growth stop was enabled by radiocarbon dating, which allows a complex investigation of samples collected from the trunk/stems of baobabs. In several cases, the outermost rings of baobabs, which were close to the bark, were found to be old, with ages of several hundreds of years, instead of being very young. Dating results of samples collected from six baobabs are presented. For multistemmed baobabs, the growth stop may occur only for one or several stems. We identified four factors that may induce the growth stop: (i) stress determined by severe climate conditions, (ii) old age, (iii) the need to keep a stable internal architecture, and (iv) the collapse of stems that survive this trauma. Baobabs and their stems affected by growth stop may survive for several centuries, by continuing to produce leaves, flowers, and fruits. This phenomenon was associated with the capacity of baobabs to store large amounts of water in their trunks/stems in the rainy season. This reservoir of water is used during the dry season and allows the trees to survive prolonged drought periods.
Keywords: Age determination; AMS; growth stop; Radiocarbon dating; tropical trees

A high resolution record of rare earth element compositional changes from the mud deposit on the inner shelf of the East China Sea: Implications for paleoenvironmental changes - Mi, Beibei; Liu, Shengfa; Shi, Xuefa; Li, Xiaoyan; Pan, Hui-Juan; Chen, Min-Te; Wang, Xuchen (Quaternary International, 2017)
A paleoenvironmental reconstruction of the East China Sea (ECS) is presented using rare earth element (REE) analysis of sediments from Core MZ02, which was retrieved from the inner continental shelf's mud area. The analytic results show that the total REEs in the fine sediment vary between 137.76 μg/g and 231.53 μg/g with an average value of 187.69 μg/g. Obvious changes were found during the process of sedimentation. By comparing with the REE compositions from the potential provenances, the ratios of (La/Sm)ucc and (Gd/Yb)ucc revealed that the sediments were mainly derived from river detrital outputs of the Changjiang (Yangtze River), Minjiang and mountainous rivers from western Taiwan Island. The contributions of terrestrial materials from these three main provenances were controlled by sea level change and the Taiwan Warm Current (TWC)-Chinese Coastal Current (CCC) system, which is mainly driven by the East Asian monsoon. The high sedimentation rate during the transgression period between the late Pleistocene and early Holocene (13000–9800 a B.P.) was caused by a well-proportioned mixed provenance from Changjiang, western Taiwanese rivers and Minjiang sediments, due to the lower sea level and the location of the foreshore-nearshore face. Because of the stronger sediment reworking and erosion at the shelf edge during the early Holocene (9800–7300 a B.P.), the strengthening summer East Asian monsoon transported the Minjiang and western Taiwanese river material northeastward, and it became the main sediment source for fine sediments in the shallow sea region of the ECS, while the Changjiang provided a relatively minor amount of detrital sediment to the shelf. The increasing strength of the TWC might have played an important role in sediment dispersal and deposition on the ECS inner shelf during the period 7300–3500 a B.P., thus mountainous river material became the dominant sediment on the shelf of the ECS. Furthermore, the results indicate that the East Asian monsoon and the weakening of the TWC were linked to an abrupt increase in Changjiang-derived terrigenous detritus material since 3500 a B.P.; the source and sink pattern during this period is consistent with the modern sedimentation environment.
Keywords: East China Sea; Mud deposit; Paleoenvironmental; Provenance; Rare earth element; Sediment

Holocene sea ice variability driven by wind and polynya efficiency in the Ross Sea - Mezgec, K.; Stenni, B.; Crosta, X.; Masson-Delmotte, V.; Baroni, C.; Braida, M.; Ciardini, V.; Colizza, E.; Melis, R.; Salvatore, M. C.; Severi, M.; Scarchilli, C.; et al. (Nature Communications, 2017)
The causes of the recent increase in Antarctic sea ice extent, characterised by large regional contrasts and decadal variations, remain unclear. In the Ross Sea, where such a sea ice increase is reported, 50% of the sea ice is produced within wind-sustained latent-heat polynyas. Combining information from marine diatom records and sea salt sodium and water isotope ice core records, we here document contrasting patterns in sea ice variations between coastal and open sea areas in Western Ross Sea over the current interglacial period. Since about 3600 years before present, an increase in the efficiency of regional latent-heat polynyas resulted in more coastal sea ice, while sea ice extent decreased overall. These past changes coincide with remarkable optima or minima in the abundances of penguins, silverfish and seal remains, confirming the high sensitivity of marine ecosystems to environmental and especially coastal sea ice conditions.

Holocene temperatures and isotopes of precipitation in Northwest Greenland recorded in lacustrine organic materials - Lasher, G. Everett; Axford, Yarrow; McFarlin, Jamie M.; Kelly, Meredith A.; Osterberg, Erich C.; Berkelhammer, Max B. (Quaternary Science Reviews, 2017)
Reconstructions of Holocene lake water isotopic composition based upon subfossil aquatic organic material offer new insights into Arctic climate. We present quantitative estimates of warmth during the Holocene Thermal Maximum in northwest Greenland, inferred from oxygen isotopes of chironomid head capsules and aquatic moss preserved in lake sediments. delta O-18 values of chironomids from surface sediments of multiple Greenland lakes indicate that these subfossil remains record the delta O-18 values of the lake water in which they grow. Our lake water delta O-18 reconstruction is supported by downcore agreement with delta O-18 values in aquatic moss and chironomid remains. delta O-18 of both organic materials from Secret Lake decrease after 4 ka (ka = thousands of years ago) by 3 parts per thousand into the Neoglacial. We argue that lake water at Secret Lake primarily reflects precipitation delta O-18 values, which is strongly correlated with air temperature in NW Greenland, and that this signal is biased towards summer and early autumn conditions. Other factors may have influenced Secret Lake delta O-18 values through the Holocene, including evaporation of lake water and changing seasonality and source of precipitation. The maximum early Holocene summer and early autumn-biased temperature anomaly at Secret Lake is 2.5-4 degrees C warmer than present from 7.7 (the beginning of our record) to similar to 6 ka. The maximum late Holocene cold anomaly (which includes the Little Ice Age) is 1.5-3 degrees C colder than present. These ranges of possible temperature anomalies reflect uncertainty in the delta O-18 temperature relationship for precipitation at the study site through the Holocene. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Chironomids; Greenland; Holocene; paleoclimatology; paleolimnology; Stable isotopes

Holocene tephra succession of Puyehue-Cordón Caulle and Antillanca/Casablanca volcanic complexes, southern Andes (40–41°S) - J.A. Naranjo; B.S. Singer; B.R. Jicha; H. Moreno; L.E. Lara (Journal of Volcanology and Geothermal Research, 2017)
Abstract Puyehue-Cordón Caulle and Antillanca volcanic complexes are two of at least 50 active frontal arc volcanoes that define the 1400 km-long Southern Volcanic Zone of Chile. Holocene tephra deposits in Chile and Argentina (40–41°S) up to 100 km east of these volcanoes comprise at least five voluminous (  1 to   8 km3) pyroclastic-fall layers that preceded several recently deposited Cordón Caulle pumice fallouts. Field observations of proximal, medium, and distal facies of the deposits, in conjunction with geochronology and geochemistry of the volcanic complexes, indicate that three fall layers are derived from Puyehue volcano (Puyehue 1 and 2, and Mil Hojas), whereas two are sourced from the Antillanca complex (Playas Blanca-Negra, and Nahuel Huapi Tephra), 20 km to the south. The oldest tephra (calibrated 14C age 10.49 ± 0.12 ka, 2σ), found only at medium-distal facies, is deposited directly on granitic moraine boulders and consists of deeply weathered, orange dacitic pumice lapilli. The next prominent tephra at   7 ka comprises dacitic pumice and its age is equivalent to a rhyodacitic dome exposed in the Puyehue summit crater. Above these deposits there are phases of a complex eruption consisting of a conspicuous compositionally-zoned tephra. It also comprises a pyroclastic density current, together with lithic rich and scoriaceous fallout deposits. Mineralogical, geochemical, and Sr isotope evidence, plus the isopach maps, confirm that this sequence of eruptive events is sourced from Antillanca at 1932 ± 68 yrBP. The total volume of this eruptive sequence exceeds 8 km3, making it the largest Holocene eruption from either volcanic complex. This eruption was likely responsible for the destruction of an ancestral Antillanca volcano and the formation of a 4.5 km diameter caldera. A distinctive younger unit in the region is a voluminous rhyodacitic pumice fall (calibrated 14C age 1.11 ± 0.07 ka), above which a series of several alternating dark lithic and pumice lapilli beds accumulated. Correlation with proximal deposits indicates that the 1.11 ka eruption was derived from Puyehue and destroyed   3 km3 of rhyodacitic domes at this volcano summit. Historic explosive activity at the nascent Casablanca volcano and along Cordón Caulle, including the 2011–2012 eruption (  1 km3 of uncompacted pumice), the largest from this fissural zone, emphasizes an increased risk for volcanic hazards in central Chile and Argentina.
Keywords: Chile

Hydrologic controls on seasonal and inter-annual variability of Congo River particulate organic matter source and reservoir age - Hemingway, Jordon D.; Schefuß, Enno; Spencer, Robert G.M.; Dinga, Bienvenu Jean; Eglinton, Timothy I.; McIntyre, Cameron; Galy, Valier V. (Chemical Geology, 2017)
We present dissolved organic carbon (DOC) concentrations, particulate organic matter (POM) composition (δ13C, δ15N, ∆14C, N/C), and particulate glycerol dialkyl glycerol tetraether (GDGT) distributions from a 34-month time-series near the mouth of the Congo River. An end-member mixing model using δ13C and N/C indicates that exported POM is consistently dominated by C3 rainforest soil sources, with increasing contribution from C3 vegetation and decreasing contribution from phytoplankton at high discharge. Large C4 inputs are never observed despite covering ≈ 13% of the catchment. Low and variable ∆14C values during 2011 [annual mean = (− 148 ± 82) ‰], when discharge from left-bank tributaries located in the southern hemisphere reached record lows, likely reflect a bias toward pre-aged POM derived from the Cuvette Congolaise swamp forest. In contrast, ∆14C values were stable near − 50‰ between January and June 2013, when left-bank discharge was highest. We suggest that headwater POM is replaced and/or diluted by C3 vegetation and pre-aged soils during transit through the Cuvette Congolaise, whereas left-bank tributaries export significantly less pre-aged material. GDGT distributions provide further evidence for seasonal and inter-annual variability in soil provenance. The cyclization of branched tetraethers and the GDGT-0 to crenarchaeol ratio are positively correlated with discharge (r ≥ 0.70; p-value ≤ 4.3 × 10− 5) due to the incorporation of swamp-forest soils when discharge from right-bank tributaries located in the northern hemisphere is high. Both metrics reach record lows during 2013, supporting our interpretation of increased left-bank contribution at this time. We conclude that hydrologic variability is a major control of POM provenance in the Congo River Basin and that tropical wetlands can be a significant POM source despite their small geographic coverage.
Keywords: biomarkers; Congo River; GDGTs; Particulate organic matter; radiocarbon

Insights of Pb isotopic signature into the historical evolution and sources of Pb contamination in a sediment core of the southwestern Iberian Atlantic shelf - Mário Mil-Homens; Carlos Vale; Pedro Brito; Filipa Naughton; Teresa Drago; Joana Raimundo; Bárbara Anes; Sabine Schmidt; Miguel Caetano (Science of The Total Environment, 2017)
Abstract Stable Pb isotopic ratios and concentrations of Al, Cu and Pb were measured in a 5 m long sediment core (VC2B) retrieved at 96 m water depth in the southwestern Iberian Atlantic shelf. Five phases during the last 9.5 kyrs were identified, two of them (Roman Period and modern mining) marked by a decrease of 206Pb/207Pb ratios reflecting additional inputs of Pb derived from mining activities. The Roman Period was also characterized by high 208Pb/206Pb ratios suggesting the exploitation of the outcropping portion of the orebody intensely weathered when compared with the other formations later mined. The shift of 208Pb/206Pb ratios towards linearity took approximately 1.0 kyrs, which may mirror the time of environmental recovery from the impact of Roman mining activities. The application of a mixing model allowed the quantification of the contribution associated with anthropogenic mining activities to the shelf sediments. The maximum values of Pb contamination occurred in the 20th century. This study gives direct evidence of Pb and Cu exploitation over the last 2000 years. The stable Pb isotopic signatures point to legacy of mining activities that are still the prevailing metal source recorded in the southwestern Iberian Atlantic shelf sediments.
Keywords: Environment recovery

Insights of Pb isotopic signature into the historical evolution and sources of Pb contamination in a sediment core of the southwestern Iberian Atlantic shelf - Mil-Homens, ário; Vale, Carlos; Brito, Pedro; Naughton, Filipa; Drago, Teresa; Raimundo, Joana; Anes, árbara; Schmidt, Sabine; Caetano, Miguel (Science of The Total Environment, 2017)
Stable Pb isotopic ratios and concentrations of Al, Cu and Pb were measured in a 5 m long sediment core (VC2B) retrieved at 96 m water depth in the southwestern Iberian Atlantic shelf. Five phases during the last 9.5 kyrs were identified, two of them (Roman Period and modern mining) marked by a decrease of Pb-206/Pb-207 ratios reflecting additional inputs of Pb derived from mining activities. The Roman Period was also characterized by high Pb-208/Pb-206 ratios suggesting the exploitation of the outcropping portion of the orebody intensely weathered when compared with the other formations later mined. The shift of Pb-208/Pb-206 ratios towards linearity took approximately 1.0 kyrs, which may mirror the time of environmental recovery from the impact of Roman mining activities. The application of a mixing model allowed the quantification of the contribution associated with anthropogenic mining activities to the shelf sediments. The maximum values of Pb contamination occurred in the 20th century. This study gives direct evidence of Pb and Cu exploitation over the last 2000 years. The stable Pb isotopic signatures point to legacy of mining activities that are still the prevailing metal source recorded in the southwestern Iberian Atlantic shelf sediments.
Keywords: Environment recovery; Marine sediments; Pb isotopes; Roman and modem mining activities; Southwestern Iberian shelf; Temporal evolution

Investigation of Late Pleistocene and Holocene Activity in the San Gregorio Fault Zone on the Continental Slope North of Monterey Canyon, Offshore Central California - Maier, Katherine L.; Paull, Charles K.; Brothers, Daniel S.; Caress, David W.; McGann, Mary; Lundsten, Eve M.; Anderson, Krystle; Gwiazda, Roberto (Bulletin of the Seismological Society of America, 2017)
We provide an extensive high‐resolution geophysical, sediment core, and radiocarbon dataset to address late Pleistocene and Holocene fault activity of the San Gregorio fault zone (SGFZ), offshore central California. The SGFZ occurs primarily offshore in the San Andreas fault system and has been accommodating dextral strike‐slip motion between the Pacific and North American plates since the mid‐Miocene. Our study focuses on the SGFZ where it has been mapped through the continental slope north of Monterey Canyon. From 2009 to 2015, the Monterey Bay Aquarium Research Institute collected high‐resolution multibeam bathymetry and chirp sub‐bottom profiles using an autonomous underwater vehicle (AUV). Targeted samples were collected using a remotely operated vehicle (ROV) to provide radiocarbon age constraints. We integrate the high‐resolution geophysical data with radiocarbon dates to reveal Pleistocene seismic horizons vertically offset less than 5 m on nearly vertical faults. These faults are buried by continuous reflections deposited after ∼17.5  ka and likely following erosion during the last sea‐level lowstand ∼21  ka⁠, bracketing the age of faulting to ∼32–21  ka⁠. Clearly faulted horizons are only detected in a small area where mass wasting exhumed older strata to within ∼25  m of the seafloor. The lack of clearly faulted Holocene deposits and possible highly distributed faulting in the study area are consistent with previous interpretations that late Pleistocene and Holocene activity along the SGFZ may decrease to the south. This study illustrates the complexity of the SGFZ, offshore central California, and demonstrates the utility of very high‐resolution data from combined AUV (geophysical)–ROV (seabed sampling) surveys in offshore studies of fault activity.

Large-scale response of the Eastern Mediterranean thermohaline circulation to African monsoon intensification during sapropel S1 formation - T. Tesi; A. Asioli; D. Minisini; V. Maselli; G. Dalla Valle; F. Gamberi; L. Langone; A. Cattaneo; P. Montagna; F. Trincardi (Quaternary Science Reviews, 2017)
Abstract The formation of Eastern Mediterranean sapropels has periodically occurred during intensification of northern hemisphere monsoon precipitation over North Africa. However, the large-scale response of the Eastern Mediterranean thermohaline circulation during these monsoon-fuelled freshening episodes is poorly constrained. Here, we investigate the formation of the youngest sapropel (S1) along an across-slope transect in the Adriatic Sea. Foraminifera-based oxygen index, redox-sensitive elements and biogeochemical parameters reveal – for the first time – that the Adriatic \{S1\} was synchronous with the deposition of south-eastern Mediterranean \{S1\} beds. Proxies of paleo thermohaline currents indicate that the bottom-hugging North Adriatic Dense Water (NAdDW) suddenly decreased at the sapropel onset simultaneously with the maximum freshening of the Levantine Sea during the African Humid Period. We conclude that the lack of the “salty” Levantine Intermediate Water hampered the preconditioning of the northern Adriatic waters necessary for the \{NAdDW\} formation prior to the winter cooling. Consequently, a weak \{NAdDW\} limited in turn the Eastern Mediterranean Deep Water (EMDWAdriatic) formation with important consequences for the ventilation of the Ionian basin as well. Our results highlight the importance of the Adriatic for the deep water ventilation and the interdependence among the major eastern Mediterranean water masses whose destabilization exerted first-order control on \{S1\} deposition.
Keywords: Thermohaline circulation

Local and regional wildfire activity in central Maine (USA) during the past 900 years - Miller, Daniel R.; Castañeda, Isla S.; Bradley, Raymond S.; MacDonald, Dana (Journal of Paleolimnology, 2017)
Climatic and environmental change has a direct effect on wildfire frequencies and distributions throughout many regions of the world. Reconstructions from natural archives such as lake sediments can extend temporally limited historical records of regional wildfire activity over longer timescales through sedimentary charcoal analysis or examining polycyclic aromatic hydrocarbon (PAH) concentrations. To date, little work has been completed on sedimentary PAH distributions from lacustrine records in the Northeastern United States, making it difficult to assess how accurately PAHs trace fire activity in the region, the spatial scope of the signal (local vs. regional), or if certain compounds do a more adequate job of tracking fire than others. In this study, we examine PAHs and macrocharcoal from a varved sedimentary record from Basin Pond, Fayette, Maine (USA). We find that a drastic increase in the concentrations of 12 measured PAHs occurred during the nineteenth to twentieth centuries due to industrialization of the region. Additionally, elevated concentrations of the PAH retene were found to be coeval with known large-scale regional wildfire events that occurred in 1761–1762, 1825, and 1947 (A.D.). We used the ratio of the PAHs retene and chrysene to infer differences in biomass burning versus anthropogenic combustion sources because retene is associated with conifer resin whereas chrysene is associated with fossil fuel burning. Our new Basin Pond PAH records, along with a local signal of fire occurrence from charcoal analysis, offers the prospect of using this multi-proxy approach as a method for examining long-term wildfire frequency at both the local and regional scale in the Northeastern US.

Local glaciation in West Greenland linked to North Atlantic Ocean circulation during the Holocene - Schweinsberg, Avriel D.; Briner, Jason P.; Miller, Gifford H.; Bennike, Ole; Thomas, Elizabeth K. (Geology, 2017)
Recent observations indicate that ice-ocean interaction drives much of the recent increase in mass loss from the Greenland Ice Sheet; however, the role of ocean forcing in driving past glacier change is poorly understood. To extend the observational record and our understanding of the ocean-cryosphere link, we used a multi-proxy approach that combines new data from proglacial lake sediments, C-14-dated in situ moss that recently emerged from beneath cold-based ice caps, and Be-10 ages to reconstruct centennial-scale records of mountain glacier activity for the past similar to 10 k. y. in West Greenland. Proglacial lake sediment records and C-14 dating of moss indicate the onset of Neoglaciation in West Greenland at ca. 5 ka with substantial snowline lowering and glacier expansion at ca. 3.7 ka followed by additional ice expansion phases at ca. 2.9, ca. 1.7, and ca. 1.4 ka and during the Little Ice Age. We find that widespread glacier growth at ca. 3.7 ka in West Greenland coincides with marked cooling and reduced strength of the West Greenland Current in Disko Bugt. The transition to cooler ocean conditions at ca. 3.7 ka identified in Disko Bugt is registered by marine proxy data farther afield in East Greenland and on the northwestern Icelandic shelf, implying large-scale paleoceanographic changes across the North Atlantic during this interval. The similarity between glacier change on West Greenland and multiple marine and terrestrial records across the North Atlantic suggests that glaciers are strongly influenced by changes in ocean circulation and consequently implies that the ocean-cryosphere teleconnection is a persistent feature of the Arctic system.

Millennial-scale iron fertilization of the eastern equatorial Pacific over the past 100,000 years - Loveley, Matthew R.; Marcantonio, Franco; Wisler, Marilyn M.; Hertzberg, Jennifer E.; Schmidt, Matthew W.; Lyle, Mitchell (Nature Geoscience, 2017)
The eastern equatorial Pacific Ocean plays a crucial role in global climate, as it is a substantial source of CO2 to the atmosphere and accounts for a significant portion of global new export productivity. Here we present a 100,000-year sediment core from the eastern equatorial Pacific, and reconstruct dust flux, export productivity and bottom-water oxygenation using excess-230Th-derived fluxes of 232Th and barium, and authigenic uranium concentrations, respectively. We find that during the last glacial period (71,000 to 41,000 years ago), increased delivery of dust to the eastern equatorial Pacific was coeval with North Atlantic Heinrich stadial events. Millennial-scale pulses of increased dust flux coincided with episodes of heightened biological productivity, suggesting that dissolution of dust released iron that promoted ocean fertilization. We also find that periods of low atmospheric CO2 concentrations were associated with suboxic conditions and increased storage of respired carbon in the deep eastern equatorial Pacific. Increases in CO2 concentrations during the deglaciation are coincident with increases in deep Pacific and Southern Ocean water oxygenation levels. We suggest that deep-ocean ventilation was a primary control on CO2 outgassing in this region, with superimposed pulses of high productivity providing a negative feedback.

Open-File ReportOpen-File ReportDeepwater Program: Lophelia II, continuing ecological research on deep-sea corals and deep-reef habitats in the Gulf of Mexico - Demopoulos, Amanda W.J.; Ross, Steve W.; Kellogg, Christina A.; Morrison, Cheryl L.; Nizinski, Martha S.; Prouty, Nancy G.; Bourque, Jill R.; Galkiewicz, Julie P.; Gray, Michael A.; Springmann, Marcus J.; Coykendall, D. Katharine; Miller, Andrew; et al. (2017)
The deep sea is a rich environment composed of diverse habitat types. While deep-sea coral habitats have been discovered within each ocean basin, knowledge about the ecology of these habitats and associated inhabitants continues to grow. This report presents information and results from the Lophelia II project that examined deep-sea coral habitats in the Gulf of Mexico. The Lophelia II project focused on Lophelia pertusa habitats along the continental slope, at depths ranging from 300 to 1,000 meters. The chapters are authored by several scientists from the U.S. Geological Survey, National Oceanic and Atmospheric Administration, University of North Carolina Wilmington, and Florida State University who examined the community ecology (from microbes to fishes), deep-sea coral age, growth, and reproduction, and population connectivity of deep-sea corals and inhabitants. Data from these studies are presented in the chapters and appendixes of the report as well as in journal publications. This study was conducted by the Ecosystems Mission Area of the U.S. Geological Survey to meet information needs identified by the Bureau of Ocean Energy Management.

Paleohydrology of China Lake basin and the context of early human occupation in the northwestern Mojave Desert, USA - Rosenthal, Jeffrey S.; Meyer, Jack; Palacios-Fest, Manuel R.; Young, D. Craig; Ugan, Andrew; Byrd, Brian F.; Gobalet, Ken; Giacomo, Jason (Quaternary Science Reviews, 2017)
Considerable prior research has focused on the interconnected pluvial basins of Owens Lake and Searles Lake, resulting in a long record of paleohydrological change in the lower Owens River system. However, the published record is poorly resolved or contradictory for the period encompassing the terminal Pleistocene (22,000 to 11,600 cal BP) and early Holocene (11,600-8200 cal BP). This has resulted in conflicting interpretations about the timing of lacustrine high stands within the intermediate basin of China Lake, which harbors one of the most extensive records of early human occupation in the western Great Basin and California. Here, we report a broad range of radiocarbon-dated paleoenvironmental evidence, including lacustrine deposits and shoreline features, tufa outcrops, and mollusk, ostracode, and fish bone assemblages, as well as spring and other groundwater-related deposits (a.k.a. "black mats") from throughout China Lake basin, its outlet, and inflow drainages. Based on 98 radiocarbon dates, we develop independent evidence for five significant lake-level oscillations between 18,000 and 13,000 cal BP, and document the persistence of groundwater-fed wetlands from the beginning of the Younger Dryas through the early Holocene (12,900-8200 cal BP); including the transition from ground-water fed lake to freshwater marsh between about 13,000 and 12,600 cal BP. Results of this study support and refine existing evidence that shows rapid, high-amplitude oscillations in the water balance of the Owens River system during the terminal Pleistocene, and suggest widespread human use of China Lake basin began during the Younger Dryas.

Pleistocene iceberg dynamics on the west Svalbard margin: Evidence from bathymetric and sub-bottom profiler data - Fang Zhao; Timothy A. Minshull; Anya J. Crocker; Julian A. Dowdeswell; Shiguo Wu; Simon M. Soryal (Quaternary Science Reviews, 2017)
Abstract Large icebergs leave evidence of their drift via ploughing of the seabed, thereby providing a geological record of episodes of calving from thick ice sheets. We interpret large-scale curvilinear depressions on the western Svalbard margin as ploughmarks produced by the keels of icebergs that grounded on the seafloor as they drifted through this area. Iceberg ploughmarks were identified at modern water depths between 300 m and 1000 m and in two distinct stratigraphic units. Combining data from sediment cores with seismic stratigraphy from sub-bottom profiler data suggests that the ploughmarks developed in two phases: (1) during Marine Isotope Stage (MIS) 6; and (2) during \{MIS\} 2, indicating the presence of large drifting icebergs on the western Svalbard margin during both the Late Saalian and Late Weichselian glaciations. Sediment-core data along the western Svalbard margin indicate a sharp increase in mass-transported sediments dated at 23.7 ± 0.2 ka, consistent with the \{MIS\} 2 age of the younger iceberg-ploughed surface. The ploughmarks are oriented in two main directions: SW-NE and S-N. S-N oriented ploughmarks, which shallow to the north, indicate iceberg drift from the south with a SW–NE component marking the zone of splitting of the West Spitsbergen Current (WSC) into the Yermak Slope Current (YSC) and North Spitsbergen Current (NSC). Large \{MIS\} 6 and \{MIS\} 2 icebergs most likely had an Arctic Ocean source. We suggest that these icebergs probably left the Arctic Ocean southward through Fram Strait and circulated within the Norwegian-Greenland Sea before being transported northwards along the Svalbard margin by the WSC. An additional likely source of icebergs to the western Svalbard margin during \{MIS\} 2 was the ice-sheet terminating in the western Barents Sea, from which icebergs drifted northward.
Keywords: Pleistocene

Proceedings of the International Ocean Discovery ProgramExpedition 357 methods - Früh-Green, G.L.; Orcutt, B.N.; Green, S.L.; Cotterill, C.; Morgan, S.; Akizawa, N.; Bayrakci, G.; Behrmann, J.-H.; Boschi, C.; Brazleton, W.J.; Cannat, M.; Dunkel, K.G.; et al. (International Ocean Discovery Program, 2017)

Quantifying bamboo coral growth rate nonlinearity with the radiocarbon bomb spike: A new model for paleoceanographic chronology development - Frenkel, M.M.; LaVigne, M.; Miller, H.R.; Hill, T.M.; McNichol, A.; Gaylord, M. Lardie (Deep Sea Research Part I: Oceanographic Research Papers, 2017)
Bamboo corals, long-lived cold water gorgonin octocorals, offer unique paleoceanographic archives of the intermediate ocean. These Isididae corals are characterized by alternating gorgonin nodes and high Mg-calcite internodes, which synchronously extend radially. Bamboo coral calcite internodes have been utilized to obtain geochemical proxy data, however, growth rate uncertainty has made it difficult to construct precise chronologies for these corals. Previous studies have relied upon a single tie point from records of the anthropogenic Δ14C bomb spike preserved in the gorgonin nodes of live-collected corals to calculate a mean radial extension rate for the outer ~50 years of skeletal growth. Bamboo coral chronologies are typically constructed by applying this mean extension rate to the entire coral record, assuming constant radial extension with coral age. In this study, we aim to test this underlying assumption by analyzing the organic nodes of six California margin bamboo corals at high enough resolution (<0.5 mm) to identify the Δ14C bomb spike, including two tie points at 1957 and 1970, plus the coral collection date (2007.5) for four samples. Radial extension rates between tie points ranged from 10 to 204 µm/year, with a decrease in growth rate evident between the 1957–1970 and 1970–2007.5 periods for all four corals. A negative correlation between growth rate and coral radius (r =−0.7; p=0.04) was determined for multiple bamboo coral taxa and individuals from the California margin, demonstrating a decline in radial extension rate with specimen age and size. To provide a mechanistic basis for these observations, a simple mathematical model was developed based on the assumption of a constant increase in circular cross sectional area with time to quantify this decline in radial extension rate with coral size between chronological tie points. Applying the area-based model to our Δ14C bomb spike time series from individual corals improves chronology accuracy for all live-collected corals with complete Δ14C bomb spikes. Hence, this study provides paleoceanographers utilizing bamboo corals with a method for reducing age model uncertainty within the anthropogenic bomb spike era (~1957-present). Chronological uncertainty is larger for the earliest portion of coral growth, particularly for skeleton precipitated prior to bomb spike tie points, meaning age estimations for samples living before 1957 remain uncertain. Combining this technique with additional chronological markers could improve age models for an entire bamboo coral. Finally, the relative consistency in growth rate in similarly-aged corals of the same depth and location supports the hypothesis that skeletal growth may be limited by local environmental conditions.
Keywords: 14C nuclear bomb spike; Bamboo coral; Chronologies; Gorgonin; Growth rate; paleoceanography; radiocarbon

Reconstructing Common Era relative sea-level change on the Gulf Coast of Florida - Gerlach, Matthew J.; Engelhart, Simon E.; Kemp, Andrew C.; Moyer, Ryan P.; Smoak, Joseph M.; Bernhardt, Christopher E.; Cahill, Niamh (Marine Geology, 2017)
To address a paucity of Common Era data in the Gulf of Mexico, we reconstructed ~ 1.1 m of relative sea-level (RSL) rise over the past ~ 2000 years at Little Manatee River (Gulf Coast of Florida, USA). We applied a regional-scale foraminiferal transfer function to fossil assemblages preserved in a core of salt-marsh peat and organic silt that was dated using radiocarbon and recognition of pollution, 137Cs and pollen chronohorizons. Our proxy reconstruction was combined with tide-gauge data from four nearby sites spanning 1913–2014 CE. Application of an Errors-in-Variables Integrated Gaussian Process (EIV-IGP) model to the combined proxy and instrumental dataset demonstrates that RSL fell from ~ 350 to 100 BCE, before rising continuously to present. This initial RSL fall was likely the result of local-scale processes (e.g., silting up of a tidal flat or shallow sub-tidal shoal) as salt-marsh development at the site began. Since ~ 0 CE, we consider the reconstruction to be representative of regional-scale RSL trends. We removed a linear rate of 0.3 mm/yr from the RSL record using the EIV-IGP model to estimate climate-driven sea-level trends and to facilitate comparison among sites. This analysis demonstrates that since ~ 0 CE sea level did not deviate significantly from zero until accelerating continuously from ~ 1500 CE to present. Sea level was rising at 1.33 mm/yr in 1900 CE and accelerated until 2014 CE when a rate of 2.02 mm/yr was attained, which is the fastest, century-scale trend in the ~ 2000-year record. Comparison to existing reconstructions from the Gulf coast of Louisiana and the Atlantic coast of northern Florida reveal similar sea-level histories at all three sites. We explored the influence of compaction and fluvial processes on our reconstruction and concluded that compaction was likely insignificant. Fluvial processes were also likely insignificant, but further proxy evidence is needed to fully test this hypothesis. Our results indicate that no significant Common Era sea-level changes took place on the Gulf and southeastern Atlantic U.S. coasts until the onset of modern sea-level rise in the late 19th century.

Records of continental slope sediment flow morphodynamic responses to gradient and active faulting from integrated AUV and ROV data, offshore Palos Verdes, southern California Borderland - Maier, Katherine L.; Brothers, Daniel S.; Paull, Charles K.; McGann, Mary; Caress, David W.; Conrad, James E. (Marine Geology, 2017)
Variations in seabed gradient are widely acknowledged to influence deep-water deposition, but are often difficult to measure in sufficient detail from both modern and ancient examples. On the continental slope offshore Los Angeles, California, autonomous underwater vehicle, remotely operated vehicle, and shipboard methods were used to collect a dense grid of high-resolution multibeam bathymetry, chirp sub-bottom profiles, and targeted sediment core samples that demonstrate the influence of seafloor gradient on sediment accumulation, depositional environment, grain size of deposits, and seafloor morphology. In this setting, restraining and releasing bends along the active right-lateral Palos Verdes Fault create and maintain variations in seafloor gradient. Holocene down-slope flows appear to have been generated by slope failure, primarily on the uppermost slope (~ 100–200 m water depth). Turbidity currents created a low relief (< 10 m) channel, up-slope migrating sediment waves (λ = ~ 100 m, h ≤ 2 m), and a series of depocenters that have accumulated up to 4 m of Holocene sediment. Sediment waves increase in wavelength and decrease in wave height with decreasing gradient. Integrated analysis of high-resolution datasets provides quantification of morphodynamic sensitivity to seafloor gradients acting throughout deep-water depositional systems. These results help to bridge gaps in scale between existing deep-sea and experimental datasets and may provide constraints for future numerical modeling studies.
Keywords: Deep-water channel; Gradient; Holocene; Sediment waves; Turbidite Fault

Reversible adsorption and flushing of arsenic in a shallow, Holocene aquifer of Bangladesh - Kathleen A. Radloff; Yan Zheng; Martin Stute; Beth Weinman; Benjamin Bostick; Ivan Mihajlov; Margaret Bounds; M.Moshiur Rahman; M.Rezaul Huq; Kazi M. Ahmed; Peter Schlosser; Alexander van Geen (Applied Geochemistry, 2017)
Abstract The spatial heterogeneity of dissolved arsenic (As) concentrations in shallow groundwater of the Bengal Basin has been attributed to transport of As (and reactive carbon) from external sources or to the release of As from within grey sand formations. We explore the latter scenario in this detailed hydrological and geochemical study along a 300 m transect of a shallow aquifer extending from a groundwater recharge area within a sandy channel bar to its discharge into a nearby stream. Within the 10–20 m depth range, groundwater ages along the transect determined by the 3H–3He method increase from <10 yr in the recharge area to a maximum of 40 yr towards the stream. Concentrations of groundwater As within the same grey sands increase from 10 to 100 to ∼500 μg/L along this transect. Evidence of reversible adsorption of As between the groundwater and sediment was obtained from a series of push–pull experiments, traditional batch adsorption experiments, and the accidental flooding of a shallow monitoring well. Assuming reversible adsorption and a distribution coefficient, Kd, of 0.15–1.5 L/kg inferred from these observations, a simple flushing model shows that the increase in As concentrations with depth and groundwater age at this site, and at other sites in the Bengal and Red River Basins, can be attributed to the evolution of the aquifer over 100–1000 years as aquifer sands are gradually flushed of their initial As content. A wide range of As concentrations can thus be maintained in groundwater with increases with depth governed by the history of flushing and local recharge rates, without external inputs of reactive carbon or As from other sources.
Environmental and Health Roles of Geogenic Arsenic
Keywords: Push–pull tests

Seasonal variability in the source and composition of particulate matter in the depositional zone of Baltimore Canyon, U.S. Mid-Atlantic Bight - Prouty, N.G.; Mienis, F.; Campbell-Swarzenski, P.; Roark, E.B.; Davies, A.J.; Robertson, C.M.; Duineveld, G.; Ross, S.W.; Rhode, M.; Demopoulos, A.W.J. (Deep Sea Research Part I: Oceanographic Research Papers, 2017)
Submarine canyons are often hotspots of biomass due to enhanced productivity and funneling of organic matter of marine and terrestrial origin. However, most deep-sea canyons remain poorly studied in terms of their role as conduits of terrestrial and marine particles. A multi-tracer geochemical investigation of particles collected yearlong by a sediment trap in Baltimore Canyon on the US Mid-Atlantic Bight (MAB) revealed temporal variability in source, transport, and fate of particulate matter. Both organic biomarker composition (sterol and n-alkanes) and bulk characteristics (δ13C, Δ14C, Chl-a) suggest that while on average the annual contribution of terrestrial and marine organic matter sources are similar, 42% and 52% respectively, marine sources dominate. Elevated Chlorophyll-a and sterol concentrations during the spring sampling period highlight a seasonal influx of relatively fresh phytodetritus. In addition, the contemporaneous increase in the particle reactive micronutrients cadmium (Cd) and molybdenum (Mo) in the spring suggest increased scavenging, aggregation, and sinking of phytodetrital biomass in response to enhanced surface production within the nutricline. While tidally driven currents within the canyon resuspend sediment between 200 and 600 m, resulting in the formation of a nepheloid layer rich in lithogenic material, near-bed sediment remobilization in the canyon depositional zone was minimal. Instead, vertical transport and lateral transport across the continental margin were the dominant processes driving seasonal input of particulate matter. In turn, seasonal variability in deposited particulate organic matter is likely linked to benthic faunal composition and ecosystem scale carbon cycling.
Keywords: Deep-sea ecosystems; Geochemical analyses; organic matter; sediment trap; Submarine canyons

Sequential bioavailability of sedimentary organic matter to heterotrophic bacteria - Mahmoudi, Nagissa; é, Steven R.; Steen, Andrew D.; Pearson, Ann (Environmental Microbiology, 2017)
Aquatic sediments harbour diverse microbial communities that mediate organic matter degradation and influence biogeochemical cycles. The pool of bioavailable carbon continuously changes as a result of abiotic processes and microbial activity. It remains unclear how microbial communities respond to heterogeneous organic matrices and how this ultimately affects heterotrophic respiration. To explore the relationships between the degradation of mixed carbon substrates and microbial activity, we incubated batches of organic-rich sediments in a novel bioreactor (IsoCaRB) that permitted continuous observations of CO2 production rates, as well as sequential sampling of isotopic signatures (δ13C, Δ14C), microbial community structure and diversity, and extracellular enzyme activity. Our results indicated that lower molecular weight (MW), labile, phytoplankton-derived compounds were degraded first, followed by petroleum-derived exogenous pollutants, and finally by higher MW polymeric plant material. This shift in utilization coincided with a community succession and increased extracellular enzyme activities. Thus, sequential utilization of different carbon pools induced changes at both the community and cellular level, shifting community composition, enzyme activity, respiration rates, and residual organic matter reactivity. Our results provide novel insight into the accessibility of sedimentary organic matter and demonstrate how bioavailability of natural organic substrates may affect the function and composition of heterotrophic bacterial populations.

A Terminal Pleistocene/Early Holocene Environmental Record and Fluted Point from Twain Harte, California - Moratto, Michael J.; Davis, Owen K.; Davis-King, Shelly; Meyer, Jack; Rosenthal, Jeffrey; Sylwester, Laurie (PaleoAmerica, 2017)
Although more than 500 Clovis points have been found at no fewer than 60 locations in California, the age of these points remains problematic. Here we report stratified deposits more than 3 meters deep at a site in the central Sierra Nevada from which a Clovis point was recovered in 1969. Five radiocarbon (14C) dates provide temporal control for terminal Pleistocene and early Holocene strata at the site, including the sediments in which the point reposed. We also report the analysis of pollen samples from these strata. Our research indicates that the Clovis point most likely dates to ∼11,900–11,400 cal yr BP. We interpret this, in the context of other fluted-point discoveries, to mean that Clovis lithic technology evidently persisted longer in the Far West than it did elsewhere in the U.S.
Keywords: California prehistory; Clovis chronology; Geomorphology; palynology; terminal Pleistocene/early Holocene

Timing and magnitude of early to middle Holocene warming in East Greenland inferred from chironomids - Axford, Yarrow; Levy, Laura B.; Kelly, Meredith A.; Francis, Donna R.; Hall, Brenda L.; Langdon, Peter G.; Lowell, Thomas V. (Boreas, 2017)
Much of Greenland experienced summers warmer than present in parts of the early to middle Holocene, during a precession‐driven positive anomaly in summer insolation. However, the magnitude of that warmth remains poorly known, and its timing and spatial pattern are uncertain. Here we describe the first quantitative Holocene palaeotemperature reconstruction from central East Greenland based upon insect (chironomid) assemblages preserved in lake sediments. We postulate that landscapes like our study site, characterized by minimal soil and vegetation development through the Holocene and thus little influenced by some important secondary gradients, are especially well suited to the use of chironomids to reconstruct Holocene temperatures. The inferred timing of warmth at our study site near Scoresby Sund agrees well with other nearby evidence, including glacial geological reconstructions and temperatures inferred from precipitation isotopes at Renland ice cap, supporting the use of chironomids to reconstruct temperatures at this site. We infer highest temperatures from c. 10 to 5.5 ka, followed by gradual cooling after 5.5 ka and progressively colder and less productive conditions after 3.5 ka. Models based upon two independent training sets yield similar inferred temperature trends, and suggest an average summer temperature anomaly from c. 10 to 5.5 ka of 3 to 4 °C relative to the preindustrial last millennium. The estimated overall rate of Neoglacial cooling averaged over the period from 5.5 to 0.5 ka was 0.6 to 0.8 °C per thousand years, more than twice the rate previously estimated for the Arctic as a whole. Given strong apparent spatial variability in Holocene climate around the Arctic, and the utility of palaeoclimate data for improving climate and ice‐sheet models, it should be a priority to further quantify past temperature changes around the margins of the Greenland Ice Sheet, where few quantitative reconstructions exist and future warming will affect global sea level.

The tropical lapse rate steepened during the Last Glacial Maximum - Loomis, Shannon E.; Russell, James M.; Verschuren, Dirk; Morrill, Carrie; De Cort, Gijs; Sinninghe Damsté, Jaap S.; Olago, Daniel; Eggermont, Hilde; Street-Perrott, F. Alayne; Kelly, Meredith A. (Science Advances, 2017)
The gradient of air temperature with elevation (the temperature lapse rate) in the tropics is predicted to become less steep during the coming century as surface temperature rises, enhancing the threat of warming in high-mountain environments. However, the sensitivity of the lapse rate to climate change is uncertain because of poor constraints on high-elevation temperature during past climate states. We present a 25,000-year temperature reconstruction from Mount Kenya, East Africa, which demonstrates that cooling during the Last Glacial Maximum was amplified with elevation and hence that the lapse rate was significantly steeper than today. Comparison of our data with paleoclimate simulations indicates that state-of-the-art models underestimate this lapse-rate change. Consequently, future high-elevation tropical warming may be even greater than predicted.

Turning up the Heat on Organic Matter to Track Carbon - McNichol, Ann; Rosenheim, Brad; Galy, Valier (Eos, 2017)
Keywords: Antarctic sediments; Foraminifera; radiocarbon; stable carbon isotopes

Utility of salt-marsh foraminifera, testate amoebae and bulk-sediment δ13C values as sea-level indicators in Newfoundland, Canada - Kemp, Andrew C.; Wright, Alexander J.; Barnett, Robert L.; Hawkes, Andrea D.; Charman, Dan J.; Sameshima, Colby; King, Alexandra N.; Mooney, Hailey C.; Edwards, Robin J.; Horton, Benjamin P.; van de Plassche, Orson (Marine Micropaleontology, 2017)
We investigated the utility of foraminifera, testate amoebae and bulk-sediment δ13C measurements for reconstructing Holocene relative sea level from sequences of salt-marsh sediment in Newfoundland, Canada. Modern, surface sediment was collected along transects from low to supra-tidal elevations in eastern (at Placentia) and western (at Hynes Brook and Big River) Newfoundland. Consistent with previous work, low-diversity assemblages of foraminifera display an almost binary division into a higher salt-marsh assemblage dominated by Jadammina macrescens and Balticammina pseudomacrescens and a lower salt-marsh assemblage comprised of Miliammina fusca. This pattern and composition resembles those identified at other high latitude sites with cool climates and confirms that foraminifera are sea-level indicators. The lowest occurrence of testate amoebae was at approximately mean higher high water. The composition of high salt-marsh testate amoebae assemblages (Centropyxis cassis type, Trinema spp., Tracheleuglypha dentata type, and Euglypha spp.) in Newfoundland was similar to elsewhere in the North Atlantic, but preservation bias favors removal of species with idiosomic tests over those with xenosomic tests. The mixed high salt-marsh plant community in Newfoundland results in bulk surface-sediment δ13C values that are typical of C3 plants, making them indistinguishable from freshwater sediment. Therefore we propose that the utility of this proxy for reconstructing RSL in eastern North America is restricted to the coastline between Chesapeake Bay and southern Nova Scotia. Using a simple, multi-proxy approach to establish that samples in three radiocarbon-dated sediment cores formed between the lowest occurrence of testate amoebae and the highest occurrence of foraminifera, we generated three example late Holocene sea-level index points at Hynes Brook.

What on Earth Have We Been Burning? Deciphering Sedimentary Records of Pyrogenic CarbonWhat on Earth Have We Been Burning? Deciphering Sedimentary Records of Pyrogenic Carbon - Hanke, Ulrich M.; Reddy, Christopher M.; Braun, Ana L. L.; Coppola, Alysha I.; Haghipour, Negar; McIntyre, Cameron P.; Wacker, Lukas; Xu, Li; McNichol, Ann P.; Abiven, Samuel; Schmidt, Michael W. I.; Eglinton, Timothy I. (Environmental Science & Technology, 2017)
Humans have interacted with fire for thousands of years, yet the utilization of fossil fuels marked the beginning of a new era. Ubiquitous in the environment, pyrogenic carbon (PyC) arises from incomplete combustion of biomass and fossil fuels, forming a continuum of condensed aromatic structures. Here, we develop and evaluate 14C records for two complementary PyC molecular markers, benzene polycarboxylic acids (BPCAs) and polycyclic aromatic hydrocarbons (PAHs), preserved in aquatic sediments from a suburban and a remote catchment in the United States (U.S.) from the mid-1700s to 1998. Results show that the majority of PyC stems from local sources and is transferred to aquatic sedimentary archives on subdecadal to millennial time scales. Whereas a small portion stems from near-contemporaneous production and sedimentation, the majority of PyC (∼90%) experiences delayed transmission due to “preaging” on millennial time scales in catchment soils prior to its ultimate deposition. BPCAs (soot) and PAHs (precursors of soot) trace fossil fuel-derived PyC. Both markers parallel historical records of the consumption of fossil fuels in the U.S., yet never account for more than 19% total PyC. This study demonstrates that isotopic characterization of multiple tracers is necessary to constrain histories and inventories of PyC and that sequestration of PyC can markedly lag its production.

Younger-Dryas cooling and sea-ice feedbacks were prominent features of the Pleistocene-Holocene transition in Arctic Alaska - Gaglioti, Benjamin V.; Mann, Daniel H.; Wooller, Matthew J.; Jones, Benjamin M.; Wiles, Gregory C.; Groves, Pamela; Kunz, Michael L.; Baughman, Carson A.; Reanier, Richard E. (Quaternary Science Reviews, 2017)
Declining sea-ice extent is currently amplifying climate warming in the Arctic. Instrumental records at high latitudes are too short-term to provide sufficient historical context for these trends, so paleoclimate archives are needed to better understand the functioning of the sea ice-albedo feedback. Here we use the oxygen isotope values of wood cellulose in living and sub-fossil willow shrubs (δ18Owc) (Salix spp.) that have been radiocarbon-dated (14C) to produce a multi-millennial record of climatic change on Alaska's North Slope during the Pleistocene-Holocene transition (13,500–7500 calibrated 14C years before present; 13.5–7.5 ka). We first analyzed the spatial and temporal patterns of δ18Owc in living willows growing at upland sites and found that over the last 30 years δ18Owc values in individual growth rings correlate with local summer temperature and inter-annual variations in summer sea-ice extent. Deglacial δ18Owc values from 145 samples of subfossil willows clearly record the Allerød warm period (∼13.2 ka), the Younger Dryas cold period (12.9–11.7 ka), and the Holocene Thermal Maximum (11.7–9.0 ka). The magnitudes of isotopic changes over these rapid climate oscillations were ∼4.5‰, which is about 60% of the differences in δ18Owc between those willows growing during the last glacial period and today. Modeling of isotope-precipitation relationships based on Rayleigh distillation processes suggests that during the Younger Dryas these large shifts in δ18Owc values were caused by interactions between local temperature and changes in evaporative moisture sources, the latter controlled by sea ice extent in the Arctic Ocean and Bering Sea. Based on these results and on the effects that sea-ice have on climate today, we infer that ocean-derived feedbacks amplified temperature changes and enhanced precipitation in coastal regions of Arctic Alaska during warm times in the past. Today, isotope values in willows on the North Slope of Alaska are similar to those growing during the warmest times of the Pleistocene-Holocene transition, which were times of widespread permafrost thaw and striking ecological changes.
Keywords: alaska; Arctic; Bering Strait; Climate change; dendrochronology; north pacific; oxygen isotopes; Paleoclimate; Sea ice; Younger Dryas

10Be dating reveals early-middle Holocene age of the Drygalski Moraines in central West Greenland - Sandra L. Cronauer; Jason P. Briner; Samuel E. Kelley; Susan R.H. Zimmerman; Mathieu Morlighem (Quaternary Science Reviews, 2016)
Abstract We reconstruct the history of the Greenland Ice Sheet margin on the Nuussuaq Peninsula in central West Greenland through the Holocene using lake sediment analysis and cosmogenic 10Be exposure dating of the prominent Drygalski Moraines. Erratics perched on bedrock outboard of the Drygalski Moraines constrain local deglaciation to ∼9.9 ± 0.6 ka (n = 2). Three Drygalski Moraine crests yield mean 10Be ages of 8.6 ± 0.4 ka (n = 2), 8.5 ± 0.2 ka (n = 3), and 7.6 ± 0.1 ka (n = 2) from outer to inner. Perched erratics between the inner two moraines average 7.8 ± 0.1 ka (n = 2) and are consistent with the moraine ages. Sediments from a proglacial lake with a catchment area extending an estimated 2 km beneath (inland of) the present ice sheet terminus constrain an ice sheet minimum extent from 5.4 ka to 0.6 ka. The moraine chronology paired with the lake sediment stratigraphy reveals that the ice margin likely remained within ∼2 km of its present position from ∼9.9 to 5.4 ka. This unexpected early Holocene stability, preceded by rapid ice retreat and followed by minimum ice extent between ∼5.4 and 0.6 ka, contrasts with many records of early Holocene warmth and the Northern Hemisphere summer insolation maximum. We suggest ice margin stability may instead be tied to adjacent ocean temperatures, which reached an optimum in the middle Holocene.
Special Issue: \{PAST\} Gateways (Palaeo-Arctic Spatial and Temporal Gateways)
Keywords: Holocene

Age of the Mt. Ortles ice cores, the Tyrolean Iceman and glaciation of the highest summit of South Tyrol since the Northern Hemisphere Climatic Optimum - Gabrielli, Paolo; Barbante, Carlo; Bertagna, Giuliano; ó, Michele; Binder, Daniel; Carton, Alberto; Carturan, Luca; Cazorzi, Federico; Cozzi, Giulio; Dalla Fontana, Giancarlo; Davis, Mary; De Blasi, Fabrizio; et al. (The Cryosphere, 2016)
In 2011 four ice cores were extracted from the summit of Alto dell’Ortles (3859 m), the highest glacier of South Tyrol in the Italian Alps. This drilling site is located only 37 km southwest from where the Tyrolean Iceman, ∼5.3 kyrs old, was discovered emerging from the ablating ice field of Tisenjoch (3210 m, near the Italian–Austrian border) in 1991. The excellent preservation of this mummy suggested that the Tyrolean Iceman was continuously embedded in prehistoric ice and that additional ancient ice was likely preserved elsewhere in South Tyrol. Dating of the ice cores from Alto dell’Ortles based on 210Pb, tritium, beta activity and 14C determinations, combined with an empirical model (COPRA), provides evidence for a chronologically ordered ice stratigraphy from the modern glacier surface down to the bottom ice layers with an age of ∼7 kyrs, which confirms the hypothesis. Our results indicate that the drilling site has continuously been glaciated on frozen bedrock since ∼7 kyrs BP. Absence of older ice on the highest glacier of South Tyrol is consistent with the removal of basal ice from bedrock during the Northern Hemisphere Climatic Optimum (6–9 kyrs BP), the warmest interval in the European Alps during the Holocene. Borehole inclinometric measurements of the current glacier flow combined with surface ground penetration radar (GPR) measurements indicate that, due to the sustained atmospheric warming since the 1980s, an acceleration of the glacier Alto dell’Ortles flow has just recently begun. Given the stratigraphic chronological continuity of the Mt. Ortles cores over millennia, it can be argued that this behaviour has been unprecedented at this location since the Northern Hemisphere Climatic Optimum.

Arctic Deltaic Lake Sediments As Recorders of Fluvial Organic Matter Deposition - Vonk, Jorien E.; Dickens, Angela F.; Giosan, Liviu; Hussain, Zainab A.; Kim, Bokyung; Zipper, Samuel C.; Holmes, Robert M.; Montluçon, Daniel B.; Galy, Valier; Eglinton, Timothy I. (2016)
Arctic deltas are dynamic and vulnerable regions that play a key role in land-ocean interactions and the global carbon cycle. Delta lakes may provide valuable historical records of the quality and quantity of fluvial fluxes, parameters that are challenging to investigate in these remote regions. Here we study lakes from across the Mackenzie Delta, Arctic Canada, that receive fluvial sediments from the Mackenzie River when spring flood water levels rise above natural levees. We compare downcore lake sediments with suspended sediments collected during the spring flood, using bulk (% organic carbon, % total nitrogen, 13C, 14C) and molecular organic geochemistry (lignin, leaf waxes). High-resolution age models (137Cs, 210Pb) of downcore lake sediment records (n=11) along with lamina counting on high-resolution radiographs show sediment deposition frequencies ranging between annually to every 15 years. Down-core geochemical variability in a representative delta lake sediment core is consistent with historical variability in spring flood hydrology (variability in peak discharge, ice jamming, peak water levels). Comparison with earlier published Mackenzie River depth profiles shows that (i) lake sediments reflect the riverine surface suspended load, and (ii) hydrodynamic sorting patterns related to spring flood characteristics are reflected in the lake sediments. Bulk and molecular geochemistry of suspended particulate matter from the spring flood peak and lake sediments are relatively similar showing a mixture of modern higher-plant derived material, older terrestrial permafrost material, and old rock-derived material. This suggests that deltaic lake sedimentary records hold great promise as recorders of past (century-scale) riverine fluxes and may prove instrumental in shedding light on past behaviour of arctic rivers, as well as how they respond to a changing climate.

Comparison of eastern tropical Pacific TEX 86 and Globigerinoides ruber Mg/Ca derived sea surface temperatures: Insights from the Holocene and Last Glacial Maximum - Hertzberg, Jennifer E.; Schmidt, Matthew W.; Bianchi, Thomas S.; Smith, Richard W.; Shields, Michael R.; Marcantonio, Franco (Earth and Planetary Science Letters, 2016)
The use of the TEX86TEX86 temperature proxy has thus far come to differing results as to whether TEX86TEX86 temperatures are representative of surface or subsurface conditions. In addition, although TEX86TEX86 temperatures might reflect sea surface temperatures based on core-top (Holocene) values, this relationship might not hold further back in time. Here, we investigate the TEX86TEX86 temperature proxy by comparing TEX86TEX86 temperatures to Mg/Ca temperatures of multiple species of planktonic foraminifera for two sites in the eastern tropical Pacific (on the Cocos and Carnegie Ridges) across the Holocene and Last Glacial Maximum. Core-top and Holocene View the MathML sourceTEX86H temperatures at both study regions agree well, within error, with the Mg/Ca temperatures of Globigerinoides ruber , a surface dwelling planktonic foraminifera. However, during the Last Glacial Maximum, View the MathML sourceTEX86H temperatures are more representative of upper thermocline temperatures, and are offset from G. ruber Mg/Ca temperatures by 5.8 °C and 2.9 °C on the Cocos Ridge and Carnegie Ridge, respectively. This offset between proxies cannot be reconciled by using different TEX86TEX86 temperature calibrations, and instead, we suggest that the offset is due to a deeper export depth of GDGTs at the LGM. We also compare the degree of glacial cooling at both sites based on both temperature proxies, and find that View the MathML sourceTEX86H temperatures greatly overestimate glacial cooling, especially on the Cocos Ridge. This study has important implications for applying the TEX86TEX86 paleothermometer in the eastern tropical Pacific.
Keywords: Foraminifera; Holocene; LGM; Pacific Ocean; Mg/Ca; TEX86TEX86

Complex coastal change in response to autogenic basin infilling: An example from a sub-tropical Holocene strandplain - Hein, Christopher J.; FitzGerald, Duncan M.; de Souza, Luis H. P.; Georgiou, Ioannis Y.; Buynevich, Ilya V.; Klein, Antonio H. da F.; de Menezes, ão Thadeu; Cleary, William J.; Scolaro, Thelma L. (Sedimentology, 2016)
Thick bay-fill sequences that often culminate in strandplain development serve as important sedimentary archives of land–ocean interaction, although distinguishing between internal and external forcings is an ongoing challenge. This study employs sediment cores, ground-penetrating radar surveys, radiocarbon dates, palaeogeographic reconstructions and hydrodynamic modelling to explore the role of autogenic processes – notably a reduction in wave energy in response to coastal embayment infilling – in coastal evolution and shoreline morphodynamics. Following a regional 2 to 4 m highstand at ca 5·8 ka, the 75 km2 Tijucas Strandplain in southern Brazil built from fluvial sediments deposited into a semi-enclosed bay. Holocene regressive deposits are underlain by fluvial sands and a Pleistocene transgressive–regressive sequence, and backed by a highstand barrier-island. The strandplain is immediately underlain by 5 to 16 m of seaward-thickening, fluvially derived, Holocene-age, basin-fill mud. Several trends are observed from the landward (oldest) to the seaward (youngest) sections of the strandplain: (i) the upper shoreface and foreshore become finer and thinner and shift from sand-dominated to mud-dominated; (ii) beachface slopes decrease from >11° to ca 7°; and (iii) progradation rates increase from 0·4 to 1·8 m yr−1. Hydrodynamic modelling demonstrates a correlation between progressive shoaling of Tijucas Bay driven by sea-level fall and sediment infilling and a decrease in onshore wave-energy transport from 18 to 4 kW m−1. The combination of allogenic (sediment supply, falling relative sea-level and geology) and autogenic (decrease in wave energy due to bay shoaling) processes drove the development of a regressive system with characteristics that are rare, if not unique, in the Holocene and rock records. These findings demonstrate the complexities in architecture styles of highstand and regressive systems tracts. Furthermore, this article highlights the diverse internal and external processes and feedbacks responsible for the development of these intricate marginal marine sedimentary systems.

Controls on the stable isotope compositions of travertine from hyperalkaline springs in Oman: Insights from clumped isotope measurements - E.S. Falk; W. Guo; A.N. Paukert; J.M. Matter; E.M. Mervine; P.B. Kelemen (Geochimica et Cosmochimica Acta, 2016)
Abstract Carbonate formation at hyperalkaline springs is typical of serpentinization in peridotite massifs worldwide. These travertines have long been known to exhibit large variations in their carbon and oxygen isotope compositions, extending from apparent equilibrium values to highly depleted values. However, the exact causes of these variations are not well constrained. We analyzed a suite of well-characterized fresh carbonate precipitates and travertines associated with hyperalkaline springs in the peridotite section of the Samail ophiolite, Sultanate of Oman, and found their clumped isotope compositions vary systematically with formation environments. Based on these findings, we identified four main processes controlling the stable isotope compositions of these carbonates. These include hydroxylation of CO2, partial isotope equilibration of dissolved inorganic carbon, mixing between isotopically distinct carbonate end-members, and post-depositional recrystallization. Most notably, in fresh crystalline films on the surface of hyperalkaline springs and in some fresh carbonate precipitates from the bottom of hyperalkaline pools, we observed large enrichments in Δ47 (up to ∼0.2‰ above expected equilibrium values) which accompany depletions in δ18O and δ13C, yielding about 0.01‰ increase in Δ47 and 1.1‰ decrease in δ13C for every 1‰ decrease in δ18O, relative to expected equilibrium values. This disequilibrium trend, also reflected in preserved travertines ranging in age from modern to ∼40,000 years old, is interpreted to arise mainly from the isotope effects associated with the hydroxylation of \{CO2\} in high-pH fluids and agrees with our first-order theoretical estimation. In addition, in some fresh carbonate precipitates from the bottom of hyperalkaline pools and in subsamples of one preserved travertine terrace, we observed additional enrichments in Δ47 at intermediate δ13C and δ18O, consistent with mixing between isotopically distinct carbonate end-members. Our results suggest that carbonate clumped isotope analysis can be a valuable tool for identifying and distinguishing processes not readily apparent from the carbonate bulk stable isotope compositions alone, e.g., kinetic effects or mixing of different carbonate end-members, which can significantly alter both the apparent formation temperatures and apparent radiocarbon ages. The isotope trends observed in these travertine samples could be applied more broadly to identify extinct hyperalkaline springs in terrestrial and extraterrestrial environments, to better constrain the formation conditions and post-depositional alteration of hyperalkaline spring carbonates, and to extract potential paleoclimate information.
Keywords: Carbonate

Controls on the stratigraphic framework and paleoenvironmental change within a Holocene estuarine system: Pamlico Sound, North Carolina, USA - Nicholas Zaremba; David J. Mallinson; Eduardo Leorri; Stephen Culver; Stanley Riggs; Ryan Mulligan; Eric Horsman; Siddhartha Mitra (Marine Geology, 2016)
Abstract This study examines the Holocene stratigraphic record and paleoenvironmental evolution of a large estuarine system, at high temporal and spatial resolution, in the context of changing climate, sea level, and hydrodynamics. New data are used to examine two time periods of increased marine influence within Pamlico Sound in northeastern North Carolina interpreted to be the result of extensive barrier island segmentation synchronous with periods of rapid climate change during the late Holocene. The study reveals the controls on the stratigraphic development and the highly dynamic character of the coastal system in response to climate, and sea-level change as it interacts with paleotopography. These findings can be used to inform projections of future environmental changes. Estuarine waters occupied paleovalleys in the Pamlico Sound region as early as ca. 7500 cal \{BP\} and Pleistocene interfluves separated the paleovalleys from the Atlantic Ocean until ca. 5500 cal BP, when they were flooded by rising sealevel forming the broad, shallow Pamlico Sound. Initial barrier islands and shoals likely formed sometime between 5500 and 5000 cal BP, providing the geomorphic setting for continued estuarine conditions behind the barriers. At ca. 4000 cal BP, an increase in marine influence and sand content is detected in multiple cores, and is correlated to seismic data within the Pamlico Sound basin. This change is interpreted to be the result of increased segmentation of barrier islands (thus a greater number of inlets, or wider inlets), which is consistent with a rapid transgression seen in other areas of the U.S. east coast. The segmentation may have been partially facilitated by a rapid increase in lagoonal area and tidal prism by overtopping of interfluves. Greater barrier island continuity is evident from 3500 to 1200 cal BP, as indicated by muddy deposits with low brackish estuarine foraminiferal assemblages. At ca. 1200 cal BP, seismic, sedimentological and micropaleontological data suggest an increase in wave and current energy and marine influence throughout southeastern Pamlico Sound. These changes are interpreted to represent extensive segmentation of the barrier islands during the Medieval Climate Anomaly (MCA). Since ca. 500 cal BP, the Pamlico Sound system has returned to a more restricted state, as inlets have closed. Currently only three major inlets segment the Outer Banks, the barrier island system fronting Pamlico Sound, but warming climate and increasing rates of sea-level rise suggest that another episode of barrier island segmentation began about a half century ago and appears that it may extend into the near future.
Keywords: Coastal geology

Coral Reefs of the WorldCoral Reefs of the Eastern Tropical PacificHolocene Reef Development in the Eastern Tropical Pacific - Toth, Lauren T.; Macintyre, Ian G.; Aronson, Richard B. (Springer Netherlands, 2016)
Contrary to early assessments, the eastern tropical Pacific (ETP) is not devoid of well-developed reefs. Significant accumulations of Holocene reef framework are present throughout the region, although they tend to be poorly consolidated, lack the submarine cementation common on most reefs elsewhere in the world, and are subject to considerable bioerosion. These reef frameworks began accreting as early as 7000 years ago. The thickest accumulations of Pocillopora frameworks occur in coastal areas of Mexico, Costa Rica, Panama, and Colombia, but reefs composed of massive corals—species of Porites, Pavona, or Gardineroseris—are present throughout the region. Reef development in the ETP is limited by a variety of characteristics of the physical environment. Because of high turbidity in most areas, reef development is generally restricted to less than ~10 m depth. The spatial extent of reefs in the ETP is also limited from the combined influences of wave action and upwelling. Most reefs in the ETP are only a few hectares in size and the best-developed reefs generally occur in areas sheltered from strong oceanic influence. Upwelling also influences long-term trends in reef development in the region. There does not appear to be a significant impact of upwelling on the millennial-scale growth rates of Panamanian reefs; however, reefs in upwelling environments typically have thinner frameworks than nearby reefs in non-upwelling environments. Furthermore, upwelling may have contributed to a historic shutdown of reef development in Costa Rica and Panama. Although both ecological and oceanographic disturbances have had some impact on the long-term development of reefs in the ETP, the most important control on reef development in this region throughout the Holocene has most likely been the El Niño–Southern Oscillation (ENSO). ENSO activity—especially that of the 1982–83 and 1997–98 El Niño events—has shaped the landscape of coral reefs across the ETP both in recent decades and in the past. Reefs in Pacific Panama and Costa Rica experienced a 2500-year hiatus in vertical growth beginning ~4100 years ago as a result of enhanced ENSO activity. Although the degree of framework accumulation and rate of reef accretion in some parts of the ETP are more similar to that of the western Atlantic than previously thought, the region still remains a marginal environment for reef development. Given the dominant role that climatic variability has played in controlling reef development in the past, the future of reefs in the ETP under accelerating climate change remains uncertain.
Keywords: El Niño; Latin American reefs; paleoecology; Reef accretion; Southern Oscillation; Upwelling

Differences in coastal subsidence in southern Oregon (USA) during at least six prehistoric megathrust earthquakes - Milker, Yvonne; Nelson, Alan R.; Horton, Benjamin P.; Engelhart, Simon E.; Bradley, Lee-Ann; Witter, Robert C. (Quaternary Science Reviews, 2016)
Stratigraphic, sedimentologic (including CT 3D X-ray tomography scans), foraminiferal, and radiocarbon analyses show that at least six of seven abrupt peat-to-mud contacts in cores from a tidal marsh at Talbot Creek (South Slough, Coos Bay), record sudden subsidence (relative sea-level rise) during great megathrust earthquakes at the Cascadia subduction zone. Data for one contact are insufficient to infer whether or not it records a great earthquake—it may also have formed through local, non-seismic, hydrographic processes. To estimate the amount of subsidence marked by each contact, we expanded a previous regional modern foraminiferal dataset to 174 samples from six Oregon estuaries. Using a transfer function derived from the new dataset, estimates of coseismic subsidence across the six earthquake contacts vary from 0.31 m to 0.75 m. Comparison of subsidence estimates for three contacts in adjacent cores shows within-site differences of ≤0.10 m, about half the ±0.22 m error, although some estimates may be minimums due to uncertain ecological preferences for Balticammina pseudomacrescens in brackish environments and almost monospecific assemblages of Miliammina fusca on tidal flats. We also account for the influence of taphonomic processes, such as infiltration of mud with mixed foraminiferal assemblages into peat, on subsidence estimates. Comparisons of our subsidence estimates with values for correlative contacts at other Oregon sites suggest that some of our estimates are minimums and that Cascadia's megathrust earthquake ruptures have been heterogeneous over the past 3500 years.
Keywords: Cascadia subduction zone; Coseismic subsidence; Megathrust earthquakes; Paleoseismology; Salt-marsh foraminifera; Sea-level change; Transfer functions

Distributions and accumulation rates of polycyclic aromatic hydrocarbons in the northern Gulf of Mexico sediments - Puspa L. Adhikari; Kanchan Maiti; Edward B. Overton; Brad E. Rosenheim; Brian D. Marx (Environmental Pollution, 2016)
Abstract Sediment samples collected from shelf, slope and interior basin of the northern Gulf of Mexico during 2011–2013, 1–3 years after the Deepwater Horizon (DWH) oil spill, were utilized to characterize \{PAH\} pollution history, in this region. Results indicate that the concentrations of surface ΣPAH43 and their accumulation rates vary between 44 and 160 ng g−1 and 6–55 ng cm−2 y−1, respectively. ΣPAH43 concentration profiles, accumulation rates and Δ14C values are significantly altered only for the sediments in the immediate vicinity of the \{DWH\} wellhead. This shows that the impact of \{DWH\} oil input on deep-sea sediments was generally limited to the area close to the spill site. Further, the \{PAHs\} source diagnostic analyses suggest a noticeable change in \{PAHs\} composition from higher to lower molecular weight dominance which reflects a change in source of \{PAHs\} in the past three years, back to the background composition. Results indicate low to moderate levels of \{PAH\} pollution in this region at present, which are unlikely to cause adverse effects on benthic communities.
Keywords: Radiocarbon (Δ14C)

Effects of seafloor diagenesis on planktic foraminiferal radiocarbon ages - Wycech, Jody; Kelly, D. Clay; Marcott, Shaun (GEOLOGY, 2016)
Radiocarbon (C-14) ages obtained from planktic foraminiferal calcite are a mainstay for reconstructing ocean-climate change and carbon cycle dynamics of the past 30 k.y., yet the effects of diagenesis on this vital chronometer are poorly constrained. Here, we address this shortcoming by comparing C-14 ages and trace element ratios (Mg/Ca, Mn/Ca) of planktic foraminifera with white, opaque shells deemed well preserved by traditional standards to those with exquisitely preserved translucent shells. Results support a diagenetic mechanism as opaque shells yield C-14 ages invariably older and trace element ratios consistently higher than those of translucent shells. Radiocarbon age offsets are particularly pronounced in mono-specific samples taken from stratigraphic horizons proximal to the delta O-18 maximum marking the Last Glacial Maximum (LGM) and the subsequent deglacial. Radiocarbon-based calendar ages of translucent shells from the two intervals are congruent with the established age ranges for these climate events, whereas those of co-occurring opaque shells overestimate the LGM and deglacial by 8-15 k.y. and 14-22 k.y., respectively. These results demonstrate that the use of translucent foraminifera enhances reproducibility and accuracy of C-14 ages by minimizing the deleterious effects of diagenesis. This study serves as a cautionary tale since white, opaque foraminifera are common in pelagic sediments, and C-14 ages derived from their ostensibly well-preserved shells can lead to discrepancies in the timing of Quaternary climate events and ocean circulation reconstructions.

Evidence of multiple thermokarst lake generations from an 11 800-year-old permafrost core on the northern Seward Peninsula, Alaska - Lenz, Josefine; Wetterich, Sebastian; Jones, Benjamin M.; Meyer, Hanno; Bobrov, Anatoly; Grosse, Guido (Boreas, 2016)
Permafrost degradation influences the morphology, biogeochemical cycling and hydrology of Arctic landscapes over a range of time scales. To reconstruct temporal patterns of early to late Holocene permafrost and thermokarst dynamics, site-specific palaeo-records are needed. Here we present a multi-proxy study of a 350-cm-long permafrost core from a drained lake basin on the northern Seward Peninsula, Alaska, revealing Lateglacial to Holocene thermokarst lake dynamics in a central location of Beringia. Use of radiocarbon dating, micropalaeontology (ostracods and testaceans), sedimentology (grain-size analyses, magnetic susceptibility, tephra analyses), geochemistry (total nitrogen and carbon, total organic carbon, δ13Corg) and stable water isotopes (δ18O, δD, d excess) of ground ice allowed the reconstruction of several distinct thermokarst lake phases. These include a pre-lacustrine environment at the base of the core characterized by the Devil Mountain Maar tephra (22 800±280 cal. a BP, Unit A), which has vertically subsided in places due to subsequent development of a deep thermokarst lake that initiated around 11 800 cal. a BP (Unit B). At about 9000 cal. a BP this lake transitioned from a stable depositional environment to a very dynamic lake system (Unit C) characterized by fluctuating lake levels, potentially intermediate wetland development, and expansion and erosion of shore deposits. Complete drainage of this lake occurred at 1060 cal. a BP, including post-drainage sediment freezing from the top down to 154 cm and gradual accumulation of terrestrial peat (Unit D), as well as uniform upward talik refreezing. This core-based reconstruction of multiple thermokarst lake generations since 11 800 cal. a BP improves our understanding of the temporal scales of thermokarst lake development from initiation to drainage, demonstrates complex landscape evolution in the ice-rich permafrost regions of Central Beringia during the Lateglacial and Holocene, and enhances our understanding of biogeochemical cycles in thermokarst-affected regions of the Arctic.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/bor.12186

Factors influencing 14C concentrations of algal and archaeal lipids and their associated sea surface temperature proxies in the Black Sea - Stephanie Kusch; Janet Rethemeyer; Ellen C. Hopmans; Lukas Wacker; Gesine Mollenhauer (Geochimica et Cosmochimica Acta, 2016)
Abstract Understanding the preservation and deposition history of organic molecules is crucial for the understanding of paleoenvironmental information contained in their abundance ratios such as Uk′37 and \{TEX86\} used as proxies for sea surface temperature (SST). Based on their relatively high refractivity, alkenones and glycerol dialkyl glycerol tetraethers (GDGTs) can survive postdepositional processes like lateral transport, potentially causing inferred \{SSTs\} to be misleading. Likewise, selective preservation of alkenones and \{GDGTs\} may cause biases of the \{SST\} proxies themselves and can lead to decoupling of both proxy records. Here we report compound-specific radiocarbon data of marine biomarkers including alkenones, GDGTs, and low molecular weight (LMW) n-fatty acids from Black Sea sediments deposited under different redox regimes to evaluate the potentially differential preservation of both biomarker classes and its effect on the \{SST\} indices Uk′37 and TEX86. The decadal Δ14C values of alkenones, GDGTs, and \{LMW\} n-fatty acids indicate similar preservation under oxic, suboxic, and anoxic redox regimes and no contribution of pre-aged compounds, e.g., by lateral supply. Moreover, similar 14C concentrations of crenarchaeol, alkenones, and \{LMW\} n-fatty acids imply that the thaumarchaeotal \{GDGTs\} preserved in these sediments are produced in the euphotic zone rather than in subsurface/thermocline waters. However, we observe biomarker-based \{SSTs\} that strongly deviate (ΔSST up to 8.4 °C) from in situ measured mean annual \{SSTs\} in the Black Sea. This is not due to redox-dependent differential biomarker preservation as implied by their Δ14C values and spatial \{SST\} pattern. Since contributions from different sources can largely be excluded, the deviation of the Uk′37 and \{TEX86\} proxy-derived \{SSTs\} from in situ \{SSTs\} requires further study of phylogenetic and other yet unknown environmental controls on alkenone and \{GDGT\} lipid distributions in the Black Sea.
Keywords: sea surface temperature proxies; TEX86; Uk37; Uk′37

Footprint of roman and modern mining activities in a sediment core from the southwestern Iberian Atlantic shelf - Mário Mil-Homens; Carlos Vale; Filipa Naughton; Pedro Brito; Teresa Drago; Bárbara Anes; Joana Raimundo; Sabine Schmidt; Miguel Caetano (Science of The Total Environment, 2016)
Abstract A 5-m long sediment core (VC2B), retrieved in the Southwestern Iberian Atlantic shelf, at 96 m water depth, was used to assess major changes in climate and human activities during the last 9.7 kyrs. Analytical measurements included sedimentological (mean grain size, and the contents of sand, silt and clay), geochemical (major, minor, trace and rare earth elements; REEs) and chronological (210Pb and 14C) parameters. Two episodes of increment of fine-grained particles, occurring at 3050 \{BCE\} and 1350 CE, suggest the retreat of the coast line to the present level and the beginning of a wetter phase associated with the “Little Ice Age”. The North American Shale Composite (NASC)-normalized REE-pattern detected in the shelf is similar to that found in the Guadiana estuarine sediments. The possibility of this estuary as a contributor to the sediment load deposited in the adjacent coastal zone was indicated. Trace elements were significantly correlated with Al until 1850 CE, pointing that grain-size rules its distribution in sediments. The depth variation of As, Cu and Pb enrichment factors relative to background values shows two periods of intense human activity that can be mainly linked to mining: (i) across the Roman Period, marked by low enrichments; and (ii) starting on the second half of the 19th century until nowadays with significantly increased enrichments, especially of Pb and Cu. In addition to As, Cu and Pb, this period is also marked by high enrichments of Hg and Zn. Despite the decrease/closure of sulphide massive deposits mining exploitation (e.g., São Domingos, Las Herrerias) during the second half of the 20th century, results showed ongoing input of Pb, Cu, As, Hg and Zn to coastal sediments. Thus, the legacy of contamination by these elements, mainly from leaching of slags and tailings, and remobilization/reworking of contaminated estuarine sediments, is still recorded in marine sediments.
Keywords: mining activities; Rare earth elements

Geochemical characterization of inorganic residues on plaster floors from a Maya palace complex at Actuncan, Belize - Lisa J. LeCount; E. Christian Wells; Thomas R. Jamison; David W. Mixter (Journal of Archaeological Science: Reports, 2016)
Abstract This report describes the results of a geochemical analysis using a mild acid extraction and inductively coupled plasma-mass spectroscopy of 198 samples from plaster surfaces at the palace complex at Actuncan, a prehispanic Maya city located in a karst landscape of western Belize. Archeologists working in the Maya region of Central America often refer to many different kinds of building complexes as “palaces” without a clear understanding of how they functioned. Often, the rooms inside these structures are devoid of features and artifacts, making it difficult to infer how they were used. Geochemical characterization of inorganic residues on plaster floors as a means of prospecting for activity areas is therefore critical for studying the function and meaning of ancient Maya palaces. At Actuncan, due to the high degree of preservation of many of the floors, overlying plaster surfaces were able to be sampled, thus informing not only how the buildings were used, but how their uses changed over time. Multivariate quantitative modeling and spatial interpolation of the chemical data demonstrate that a variety of domestic, ritual, and possibly administrative activities took place in the palace complex, a finding that challenges previous assessments of palaces as primarily royal residential compounds.
Keywords: Belize

Holocene climate variability from the lake sediment core in Schirmacher Oasis region, East Antarctica: Multiproxy approach - Pawan Govil; Abhijit Mazumder; Rajesh Asthana; Anoop Tiwari; Ravi Mishra (Quaternary International, 2016)
Abstract A 1.62 m sediment core was retrieved from one of the landlocked freshwater lakes (L-6) in the Schirmacher Oasis (SO), East Antarctica during the 24th Indian Antarctic Expedition (2004–2006). The sediment core samples were analyzed for Total Organic Carbon (TOC), Biogenic Silica (BSi), grain size and elemental concentration ratios (Mg/Ca and Mn/Fe). The sediment core represents the time period of last ∼11.6 cal ka \{BP\} as ascertained by \{AMS\} 14C radiocarbon dates. The sedimentation accumulation rate variation of ∼13.6 cm/ka from ∼11.6 to ∼10 cal ka \{BP\} reveals a warm phase followed by a low sedimentation accumulation rate of ∼2.9 cm/ka from ∼10 ka \{BP\} to ∼3.1 ka BP, indicating a cold period in the region. The sedimentation accumulation rate again increased from ∼3.1 cal ka \{BP\} to recent with a maximum of ∼88 cm/ka which reveals the initiation of glacier retreat or ice-free conditions in the study area. The Total Organic Carbon (TOC) is <2% from ∼10 to ∼3.1 cal ka \{BP\} indicating a prolonged colder phase in the study area. However, elevated TOC, \{BSi\} and Mg/Ca ratio since ∼3.1 cal ka \{BP\} to recent points indicates towards ice-free conditions (continental ice sheet retreat) and subsequently high productivity in the region. Moreover, the productivity was higher at the Pleistocene–Holocene boundary as evidenced by the Mg/CA, Mn/Fe ratio and Biogenic Silica (BSi). The present study identified a colder phase (or re-advancement of continental ice sheet) during the early to mid-Holocene and initiation of ice-free or continental ice-sheet retreat during the late Holocene and their implications on the productivity changes.
Keywords: Freshwater lakes

Hydrothermal iron flux variability following rapid sea level changes - Middleton, Jennifer L.; Langmuir, Charles H.; Mukhopadhyay, Sujoy; McManus, Jerry F.; Mitrovica, Jerry X. (GEOPHYSICAL RESEARCH LETTERS, 2016)
Sea level changes associated with Pleistocene glacial cycles have been hypothesized to modulate melt production and hydrothermal activity at ocean ridges, yet little is known about fluctuations in hydrothermal circulation on time scales longer than a few millennia. We present a high-resolution record of hydrothermal activity over the past 50 ka using elemental flux data from a new sediment core from the Mir zone of the TAG hydrothermal field at 26 degrees N on the Mid-Atlantic Ridge. Mir sediments reveal sixfold to eightfold increases in hydrothermal iron and copper deposition during the Last Glacial Maximum, followed by a rapid decline during the sea level rise associated with deglaciation. Our results, along with previous observations from Pacific and Atlantic spreading centers, indicate that rapid sea level changes influence hydrothermal output on mid-ocean ridges. Thus, climate variability may discretize volcanic processing of the solid Earth on millennial time scales and subsequently stimulate variability in biogeochemical interactions with volcanic systems.

IsoCaRB: A novel bioreactor system to characterize the lability and natural carbon isotopic (C-14, C-13) signatures of microbially respired organic matter - Beaupré, Steven R.; Mahmoudi, Nagissa; Pearson, Ann (LIMNOLOGY AND OCEANOGRAPHY-METHODS, 2016)
Organic matter is the dominant pool of reduced carbon in marine and freshwater systems. Mineralization of organic matter is largely attributed to complex and diverse microbial communities that mediate degradation and ultimately yield the terminal respiratory product, carbon dioxide (CO2). The factors that constrain the lability and degradation of organic matter remain unclear, but they involve a complex interplay between structural and chemical properties of the compounds, physical properties of the matrices, and the functional potential of the microorganisms that are present. To investigate these relationships, we developed a novel bioreactor system-called Isotopic Carbon Respirometer-Bioreactor (IsoCaRB)-that permits real-time monitoring of microbial CO2 production rates and collects sequential samples of this CO2 for off-line isotopic analyses (C-13, C-14). Application of this system to organic-rich sediments from Salt Pond, MA reveals that organic matter is oxidized both abiotically and microbially, and that the pattern of microbial respiration by the native sediment community is complex, accessing different carbon substrates over the course of incubation. Isotopic measurements show modern organic matter of progressively older ages (<= ca. 50 yr) is consumed, and this material has variable origins (salt marsh grasses, terrestrial, and marine organic matter). Collectively, the IsoCaRB system provides coupled insights into the sources, ages, and inherent biological and abiotic reactivity of natural organic matter.

Large deglacial shifts of the Pacific Intertropical Convergence Zone - Jacobel, A. W.; McManus, J. F.; Anderson, R. F.; Winckler, G. (Nature Communications, 2016)
The position of the Intertropical Convergence Zone (ITCZ) is sensitive to changes in the balance of heat between the hemispheres which has fundamental implications for tropical hydrology and atmospheric circulation. Although the ITCZ is thought to experience the largest shifts in position during deglacial stadial events, the magnitude of shifts has proven difficult to reconstruct, in part because of a paucity of high-resolution records, particularly those including spatial components. Here we track the position of the ITCZ from 150 to 110 ka at three sites in the central equatorial Pacific at sub-millennial time resolution. Our results provide evidence of large, abrupt changes in tropical climate during the penultimate deglaciation, coincident with North Atlantic Heinrich Stadial 11 (∼136–129 ka). We identify this event both as a Northern Hemisphere increase in aeolian dust and as a shift in the mean position of the ITCZ a minimum of 4° southwards at 160° W.

Late Quaternary evolution of Lago Castor (Chile, 45.6°S): Timing of the deglaciation in northern Patagonia and evolution of the southern westerlies during the last 17 kyr - Maarten Van Daele; Sébastien Bertrand; Inka Meyer; Jasper Moernaut; Willem Vandoorne; Giuseppe Siani; Niels Tanghe; Zakaria Ghazoui; Mario Pino; Roberto Urrutia; Marc De Batist (Quaternary Science Reviews, 2016)
Abstract Even though Patagonia is ideally located to study climate of the southern mid-latitudes, many questions on the late Quaternary climate evolution remain unresolved. The timing of maximum glacier extent is still uncertain in vast areas, and the postglacial evolution of the Southern Westerly Wind Belt (SWWB) remains highly debated. Here, we study the sedimentary infill of a glacigenic lake (Lago Castor; 45.6°S, 71.8°W) located at the leeside of the Andes in Chilean Patagonia to i) reconstruct the deglacial evolution of the eastern flank of the Patagonian Ice Sheet (PIS), and ii) discuss postglacial changes in wind strength at a critical location where westerly wind records are critically lacking. A dense grid of high-resolution reflection-seismic data was used to reconstruct the large-scale infill history of the lake, and a radiocarbon dated sediment core penetrating all lacustrine seismic units, was retrieved. Results indicate that the deglaciation of the lake basin and its catchment occurred no later than ∼28 cal kyr \{BP\} (i.e. an early LGM), but possibly even already after \{MIS\} 4. Afterwards, the Lago Castor area was covered by a large proglacial lake that drained – possibly through an outburst flood – when the \{PIS\} outlet glaciers retreated to a critical location. Subsequently, very dry conditions caused the lake to desiccate, as evidenced by an unconformity visible on the seismic profiles and in the sediment core. This dry period likely resulted from the increased orographic effect of the PIS-covered Andes, accompanied by weaker westerlies. From ∼20 kyr \{BP\} onwards, the combination of a shrinking \{PIS\} and a southward shift of the \{SWWB\} resulted in increased precipitation, which caused the lake level to rise. After ∼17 cal kyr BP, lake sedimentation was more directly influenced by the southern westerlies, with the formation of sediment drifts resulting from strong bottom current during periods of intense westerly winds. Our results suggest a progressive increase in wind strength at 46°S from 11.2 to 4.5 cal kyr BP, which supports the hypothesis that the \{SWWB\} broadened during the early and middle Holocene.
Keywords: Sediment drift

Micropaleontologic record of Pliocene and Quaternary paleoenvironments in the southern Albemarle Embayment, North Carolina, U.S.A - Stephen J. Culver; Kathleen M. Farrell; David J. Mallinson; Debra A. Willard; Benjamin P. Horton; Stanley R. Riggs; E. Robert Thieler; John F. Wehmiller; Peter R. Parham; Jessica Pierson Moore; Scott W. Snyder; Caroline Hillier (Palaeogeography, Palaeoclimatology, Palaeoecology, 2016)
Abstract The Albemarle Embayment, a Cenozoic depositional basin on the Atlantic coast of the USA, is an ideal setting to understand the temporal and spatial variation of eustatic sea-level fluctuations, glacio-hydro-isostasy, tectonics, subsidence, environments and sedimentation patterns of a passive margin Quaternary section. A NE–SW transect of cores and seismic data in the southern Albemarle Embayment were analyzed using micropaleontologic (foraminifera, diatoms, pollen), sedimentologic, stratigraphic, and geochronologic data to reconstruct the paleoenvironmental evolution and paleoclimates in the nearly 90 m thick Quaternary section. The study area is a very low gradient Quaternary landscape that is cross-cut by several Pleistocene incised valleys; a Holocene barrier island complex forms its eastern margin. In the subsurface, the Albemarle Embayment is bordered to the north by the Norfolk Arch and to the south by the depositionally-constructed Cape Lookout High, which is positioned on the northern flank of the structural Carolina Platform. The Quaternary section overlies mid-Pliocene carbonates in three cores; the contact rises in elevation towards the Cape Lookout High. Fossils and sediment characteristics suggest a subtropical, shallow, high energy marine environment during the Pliocene. Overlying units include incomplete Pleistocene, clastic, transgressive-regressive (T-R) deposits. These have similar ages and stratigraphic signatures as the T-R cycles in the central and north-central Albemarle Embayment, although mid-Pleistocene deposits may be older in the southern region. The bulk of the early and mid-Pleistocene record consists of inner to mid-shelf sand and muddy sand. In contrast, late Pleistocene sands are of inner shelf origin, reflecting the infilling of the basin. Lowstand paleovalleys, with fluvial, wetland and estuarine fill, dissect the early, mid- and late Pleistocene marine units; their locations reflect antecedent topography. Holocene sediments were deposited in shoreface and barrier island environments. Quaternary foraminiferal assemblages in the southern Albemarle Embayment exhibit greater species richness than those in the central and north-central embayment reflecting the presence of a major biogeographic boundary at the same location as the modern biogeographic boundary at Cape Hatteras.
Keywords: Holocene

No iron fertilization in the equatorial Pacific Ocean during the last ice age - Costa, K. M.; McManus, J. F.; Anderson, R. F.; Ren, H.; Sigman, D. M.; Winckler, G.; Fleisher, M. Q.; Marcantonio, F.; Ravelo, A. C. (Nature, 2016)
The equatorial Pacific Ocean is one of the major high-nutrient, low-chlorophyll regions in the global ocean. In such regions, the consumption of the available macro-nutrients such as nitrate and phosphate is thought to be limited in part by the low abundance of the critical micro-nutrient iron1. Greater atmospheric dust deposition2 could have fertilized the equatorial Pacific with iron during the last ice age—the Last Glacial Period (LGP)—but the effect of increased ice-age dust fluxes on primary productivity in the equatorial Pacific remains uncertain3, 4, 5, 6. Here we present meridional transects of dust (derived from the 232Th proxy), phytoplankton productivity (using opal, 231Pa/230Th and excess Ba), and the degree of nitrate consumption (using foraminifera-bound δ15N) from six cores in the central equatorial Pacific for the Holocene (0–10,000 years ago) and the LGP (17,000–27,000 years ago). We find that, although dust deposition in the central equatorial Pacific was two to three times greater in the LGP than in the Holocene, productivity was the same or lower, and the degree of nitrate consumption was the same. These biogeochemical findings suggest that the relatively greater ice-age dust fluxes were not large enough to provide substantial iron fertilization to the central equatorial Pacific. This may have been because the absolute rate of dust deposition in the LGP (although greater than the Holocene rate) was very low. The lower productivity coupled with unchanged nitrate consumption suggests that the subsurface major nutrient concentrations were lower in the central equatorial Pacific during the LGP. As these nutrients are today dominantly sourced from the Subantarctic Zone of the Southern Ocean, we propose that the central equatorial Pacific data are consistent with more nutrient consumption in the Subantarctic Zone, possibly owing to iron fertilization as a result of higher absolute dust fluxes in this region7, 8. Thus, ice-age iron fertilization in the Subantarctic Zone would have ultimately worked to lower, not raise, equatorial Pacific productivity.
Keywords: Biogeochemistry; Palaeoceanography

Organic matter cycling across the sulfate-methane transition zone of the Santa Barbara Basin, California Borderland - Komada, Tomoko; Burdige, David J.; Li, Huan-Lei; Magen, édric; Chanton, Jeffrey P.; Cada, Abraham K. (Geochimica et Cosmochimica Acta, 2016)
Consumption of sulfate (SO42−) in the sulfate-methane transition zone (SMTZ) has often been considered to be due solely to anaerobic oxidation of methane (AOM). However, recent studies show SO42− fluxes into the SMTZ that exceed methane (CH4) fluxes, thereby challenging this conceptual model. Co-occurrence of organoclastic SO42− reduction (oSR) with AOM in the SMTZ has been hypothesized to be the cause for this flux imbalance, but conclusive evidence is lacking. To address this knowledge gap, we investigated organic matter cycling in the SMTZ of the organic-rich sediments of the Santa Barbara Basin, California Borderland, and examined the occurrence of oSR within this zone using bulk solute profiles and Δ14C and δ13C values of selected carbon pools. We also tested the hypothesis that the SMTZ acts as an oxidation front not just for CH4, but also for dissolved organic carbon (DOC) that is produced below the SMTZ and migrates upward. Mass balance calculations for the SMTZ based on reaction stoichiometry and Δ14C and δ13C values of associated carbon fluxes indicate that ∼35–45% of total SO42− reduction in the SMTZ occurs via oSR, with the remainder attributable to AOM. The δ13C value of net DOC production is distinct from that of the fraction of bulk POC undergoing degradation, suggesting that pore-water DOC represents a compositionally unique slice of the metabolizable POC pool. DOC diffusing upward at 450 cm is virtually free of 14C and contain low levels of short-chain organic acids. Radiocarbon mass balance shows that >30% of this pre-aged, and presumably refractory, DOC is removed from the pore waters within or immediately below the SMTZ. Although the SMTZ does not appear to be a major net DOC oxidation front, these results show that DOC dynamics provide unique insights into organic matter processing in these subsurface sediments.

Palaeoclimatic changes in Kveithola, Svalbard, during the Late Pleistocene deglaciation and Holocene: Evidences from microfossil and sedimentary records - Katia Carbonara; Karin Mezgec; Gabriella Varagona; Maria Elena Musco; Renata Giulia Lucchi; Giuliana Villa; Caterina Morigi; Romana Melis; Mauro Caffau (Palaeogeography, Palaeoclimatology, Palaeoecology, 2016)
Abstract Climate changes are reflected in the Arctic ecosystem history over different timescales. We use a multi proxy-based approach for palaeoenvironmental and palaeoclimatic reconstructions, conducted on sediment cores, compared with summer insolation and Greenland ice core δ18O data in order to establish a framework for climate changes from Late Pleistocene to late Holocene. Our dataset includes the results compiled from a sediment core, collected on the middle slope of the Kveithola Trough Mouth Fan (South of Svalbard) during the \{CORIBAR\} cruise (2013). The studied core presents remarkable lithological and magnetic susceptibility similarities with cores recovered in the same area during the \{SVAIS\} (2007) and the OGS-EGLACOM cruise (2008), allowing the construction of the age model. The results indicate that during the last 14.5 cal ky \{BP\} advances and retreats of the Svalbard Barents Sea Ice Sheet were strictly linked to the interplay of Atlantic and Arctic water inflows to the study area. During the deglaciation, from the Last Glacial Maximum to the onset of the Holocene, the climate underwent a series of abrupt changes including the Bølling-Allerød warm interstadial and the Younger Dryas cold event. During the early Holocene, the investigated area was dominated by enhanced warm Atlantic water inflow, which was concomitant with summer insolation increase, characterizing the Holocene Thermal Maximum. Conversely, the late Holocene was governed by deteriorating climatic conditions, with predominant Arctic/Polar water inflow on the surface water masses off Western Svalbard, possibly associated with summer insolation decline due to orbital forcing.
Keywords: Clay minerals

Parent material influence on soil response to vegetation change, Southeastern Minnesota, U.S.A. - Joseph A. Mason; Peter M. Jacobs; Kristine E. Gruley; Paul Reyerson; Paul R. Hanson (Geoderma, 2016)
Abstract Soil morphology changes dramatically across the former transition from forest to grassland in the Midwestern U.S.A. That vegetation boundary shifted as a result of Holocene climatic change and fire suppression following Euroamerican settlement, but the timescale of soil response to those vegetation changes and the factors that influence it are poorly known. On steep colluvial slopes of southeastern Minnesota, Mollisols with thick, dark A horizons typically associated with grassland are found today under deciduous forest. Soils with much thinner and/or lighter-colored A horizons occur immediately up- and downslope of the forest-covered Mollisols. Most of the soils with thick A horizons are not in topographic settings found to favor organic matter accumulation in other landscapes. Principal component analysis highlights important axes of textural and mineralogical variation among horizons of these soils, often related to parent material properties. Soils with and without thick A horizons are separated along one principal component heavily loaded by high pH, reflecting the presence of dolomite fragments in the hillslope sediment that soils with thick, dark A horizons formed in. Stable C isotope analysis reveals that the Mollisols with thick, dark A horizons under forest had C input from vegetation with abundant \{C4\} grasses in the past. Public land survey data also indicate replacement of grassland or savanna by forest since 1854 on colluvial slopes where forest-covered Mollisols occur today. We propose that the soils with thick, dark A horizons under forest today reflect a lagged response to vegetation change, from grassland or savanna to closed forest. Their thick A horizons and some C4-derived organic matter may be preserved because dolomite weathering releases abundant Ca++ and Mg++ that favor aggregation and organic matter stabilization. Soils with thin A horizons just up- or downslope may also have formed partly under grasses, but have responded more quickly and/or more substantially to vegetation change.
Keywords: Parent material

RAPID C-14 ANALYSIS OF DISSOLVED ORGANIC CARBON IN NON-SALINE WATERS - Lang, Susan Q.; McIntyre, Cameron P.; Bernasconi, Stefano M.; Fruh-Green, Gretchen L.; Voss, Britta M.; Eglinton, Timothy I.; Wacker, Lukas (RADIOCARBON, 2016)
The radiocarbon content of dissolved organic carbon (DOC) in rivers, lakes, and other non-saline waters can provide valuable information on carbon cycling dynamics in the environment. DOC is typically prepared for C-14 analysis by accelerator mass spectrometry (AMS) either by ultraviolet (UV) oxidation or by freeze-drying and sealed tube combustion. We present here a new method for the rapid analysis of C-14 of DOC using wet chemical oxidation (WCO) and automated headspace sampling of CO2. The approach is an adaption of recently developed methods using aqueous persulfate oxidant to determine the delta C-13 of DOC in non-saline water samples and the C-14 content of volatile organic acids. One advantage of the current method over UV oxidation is higher throughput: 22 samples and 10 processing standards can be prepared in one day and analyzed in a second day, allowing a full suite of C-14 processing standards and blanks to be run in conjunction with samples. A second advantage is that there is less potential for cross-contamination between samples.
Keywords: carbon-cycling; dissolved organic carbon; method development; wet chemical oxidation

Rapid extraction of dissolved inorganic carbon from seawater and groundwater samples for radiocarbon dating - Gospodinova, K.; McNichol, A. P.; Gagnon, A.; Walter, S. R. Shah (LIMNOLOGY AND OCEANOGRAPHY-METHODS, 2016)
We designed and developed a system to efficiently extract dissolved inorganic carbon (DIC) from seawater and groundwater samples for radiocarbon dating. The Rapid Extraction of Dissolved Inorganic Carbon System (REDICS) utilizes a gas-permeable polymer membrane contactor to extract the DIC from an acidified water sample in the form of carbon dioxide (CO2), introduce it to a helium gas stream, cryogenically isolate it, and store it for stable and radiocarbon isotope analysis. The REDICS system offers multiple advantages to the DIC extraction method which has been used for the last several decades at the National Ocean Sciences Accelerator Mass Spectrometry Facility (NOSAMS) at the Woods Hole Oceanographic Institution, including faster DIC extraction, streamlined analysis, and minimized set-up and prep time. The system was tested using sodium carbonate and seawater standards, duplicates of which were also processed on the water stripping line (WSL) at NOSAMS. The results demonstrate that the system successfully extracts, quantifies, and stores more than 99% of the DIC in less than 20 min. Stable and radiocarbon isotope analysis demonstrated system precision of 0.04 parts per thousand and 7.8 parts per thousand, respectively. A Sargasso Sea depth profile was used to further validate the system. The results show high precision for both stable and radiocarbon analysis with pooled standard deviations of 0.02 parts per thousand and 5.6 parts per thousand, respectively. A comparison between the REDICS and WSL analyses indicates a good accuracy for both stable and radio-isotope analysis.

Recent and Holocene climate change controls on vegetation and carbon accumulation in Alaskan coastal muskegs - Dorothy M. Peteet; Jonathan E. Nichols; Christopher M. Moy; Alicia McGeachy; Max Perez (Quaternary Science Reviews, 2016)
Abstract Pollen, spore, macrofossil and carbon data from a peatland near Cordova, Alaska, reveal insights into the climate–vegetation–carbon interactions from the initiation of the Holocene, c. the last 11.5 ka, to the present (1 ka = 1000 calibrated years before present where 0 = 1950 CE). The Holocene period is characterized by early deposition of gyttja in a pond environment with aquatics such as Nuphar polysepalum and Potamogeton, and a significant regional presence of Alnus crispa subsp. sinuata. Carbon accumulation (50 g/m2/a) was high for a short interval in the early Holocene when Sphagnum peat accumulated, but was followed by a major decline to 13 g/m2/a from 7 to 3.7 ka when Cyperaceae and ericads such as Rhododendron (formerly Ledum) groenlandicum expanded. This shift to sedge growth is representative of many peatlands throughout the south-central region of Alaska, and indicates a drier, more evaporative environment with a large decline in carbon storage. The subsequent return to Sphagnum peat after 4 ka in the Neoglacial represents a widespread shift to moister, cooler conditions, which favored a resurgence of ericads, such as Andromeda polifolia, and increased carbon accumulation rate. The sustained Alnus expansion visible in the top 10 cm of the peat profile is correlative with glacial retreat and warming of the region in the last century, and suggests this colonization will continue as temperature increases and ice melts.
Keywords: Alnus

Records of continental slope sediment flow morphodynamic responses to gradient and active faulting from integrated AUV and ROV data, offshore Palos Verdes, southern California Borderland - Katherine L. Maier; Daniel S. Brothers; Charles K. Paull; Mary McGann; David W. Caress; James E. Conrad (Marine Geology, 2016)
Abstract Variations in seabed gradient are widely acknowledged to influence deep-water deposition, but are often difficult to measure in sufficient detail from both modern and ancient examples. On the continental slope offshore Los Angeles, California, autonomous underwater vehicle, remotely operated vehicle, and shipboard methods were used to collect a dense grid of high-resolution multibeam bathymetry, chirp sub-bottom profiles, and targeted sediment core samples that demonstrate the influence of seafloor gradient on sediment accumulation, depositional environment, grain size of deposits, and seafloor morphology. In this setting, restraining and releasing bends along the active right-lateral Palos Verdes Fault create and maintain variations in seafloor gradient. Holocene down-slope flows appear to have been generated by slope failure, primarily on the uppermost slope (  100–200 m water depth). Turbidity currents created a low relief (< 10 m) channel, up-slope migrating sediment waves (λ =   100 m, h ≤ 2 m), and a series of depocenters that have accumulated up to 4 m of Holocene sediment. Sediment waves increase in wavelength and decrease in wave height with decreasing gradient. Integrated analysis of high-resolution datasets provides quantification of morphodynamic sensitivity to seafloor gradients acting throughout deep-water depositional systems. These results help to bridge gaps in scale between existing deep-sea and experimental datasets and may provide constraints for future numerical modeling studies.
Keywords: Fault

Seasonal variability of stable carbon isotopes (δ13CDIC) in the Skagerrak and the Baltic Sea: Distinguishing between mixing and biological productivity - Helena L. Filipsson; Daniel C. McCorkle; Andreas Mackensen; Joan M. Bernhard; Lars S. Andersson; Lars-Johan Naustvoll; Angela M. Caballero-Alfonso; Kjell Nordberg; Didrik S. Danielssen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2016)
Abstract We documented the annual cycle of the carbon isotopic composition of dissolved inorganic carbon (δ13CDIC) in the water columns of the Skagerrak and Baltic Sea to obtain an increased understanding of the processes involved controlling the carbon isotopic distribution in shelf seas. The lowest δ13CDIC values (− 4.9‰) were found in the low-oxygen, brackish Baltic bottom water whereas the highest values (+ 1.8‰) were observed in the surface water of the Skagerrak during late summer. Photosynthesis drove the high δ13CDIC values (between 1.0 and 1.8‰) noted in the surface waters of both the Skagerrak and the Baltic. The δ13CDIC values below the halocline in the Baltic reflect mixing of brackish water and the more saline water from the Skagerrak, and foremost organic matter remineralization processes that release significant amounts of low-δ13C CO2. Similarly, in the stagnant fjord basins, little deep water exchange and the degradation of terrestrial and marine organic matter set the δ13C composition. Deep-water renewal in the fjord basins resulted in rapid increases of the δ13CDIC on the order of 1‰, whereas remineralization processes caused a decrease in δ13CDIC of 0.1–0.3‰ per month depending on location. The combined effects of water mixing and remineralization processes (estimated using apparent oxygen utilization (AOU) values) yielded the expression: δ13CDIC = 0.032 ∗ S − 0.01 ∗ \{AOU\} − 0.12 for the Baltic – Skagerrak region at water depths below the halocline.
Keywords: Time-series

Sediment dynamics and hydrographic conditions during storm passage, Waquoit Bay, Massachusetts - Christopher V. Maio; Jeffrey P. Donnelly; Richard Sullivan; Stephanie M. Madsen; Christopher R. Weidman; Allen M. Gontz; Vitalii A. Sheremet (Marine Geology, 2016)
Abstract The impact of storm events on the sediment dynamics of the shallow groundwater fed estuaries of Cape Cod, Massachusetts, \{USA\} is little understood. To address this, the objectives of this study are to assess sediment dynamics during storm passage and determine whether shallow back-barrier lagoons like Waquoit Bay have the preservation potential for a sedimentary archive of hurricanes. When setting out in this study, it was unclear whether paleotempestological methods could be applied successfully to cores collected from the landward reaches of shallow estuaries of southern New England. Water level and bottom current data using Arm-and-Float tide gauges and SeaHorse Tilt Current Meters was collected during Tropical Storm Irene (2011) and coupled with storm surge modeling projections to better elucidate storm-induced sediment transport mechanisms. Three sediment cores were collected at the head of Waquoit Bay, located 2.8 km from the barrier beach. Grain size analysis of sediment cores was conducted with a laser particle size analyzer at 1 cm increments in order to identify coarse grain anomalies, which can act as a storm event proxy. Bayesian statistics were applied to develop age models of two of the cores based on three Pb pollution chronomarkers and 21 continuous flow 14C \{AMS\} ages. The results yield variable sediment accumulation rates between 2 mm/yr to 10 mm/yr, with significantly higher rates occurring in the upper 1 m of sediments. Grain size results are highly variable, and contain numerous large amplitude, short duration fluctuations suggesting that during storm passage coarse sand is deposited in the coring site. The sensitivity of the site to both tropical and extratropical storm events, uncertainties in the age model, and the multiple sediment sources and transport pathways limits the utility of using the Waquoit sediments to determine long-term hurricane frequencies. Results nonetheless provide insights into how extreme storm events impact coastal lagoons.
Keywords: Sediment transport

Sedimentation, stratigraphy and physical properties of sediment on the Juan de Fuca Ridge - K.M. Costa; J.F. McManus; B. Boulahanis; S.M. Carbotte; G. Winckler; P.J. Huybers; C.H. Langmuir (Marine Geology, 2016)
Abstract Sedimentation near mid-ocean ridges may differ from pelagic sedimentation due to the influence of the ridges' rough topography on sediment deposition and transport. This study explores whether the near-ridge environment responds to glacial-interglacial changes in climate and oceanography. New benthic δ18O, radiocarbon, multi-sensor track, and physical property (sedimentation rates, density, magnetic susceptibility) data for seven cores on the Juan de Fuca Ridge provide multiple records covering the past 700,000 years of oceanographic history of the Northeast Pacific Ocean. Systematic variations in sediment density and coarse fraction correspond to glacial-interglacial cycles identified in benthic δ18O, and these observations may provide a framework for mapping the δ18O chronostratigraphy via sediment density to other locations on the Juan de Fuca Ridge and beyond. Sedimentation rates generally range from 0.5 to 3 cm/kyr, with background pelagic sedimentation rates close to 1 cm/kyr. Variability in sedimentation rates close to the ridge likely reflects remobilization of sediment caused by the high relief of the ridge bathymetry. Sedimentation patterns primarily reflect divergence of sedimentation rates with distance from the ridge axis and glacial-interglacial variation in sedimentation that may reflect carbonate preservation cycles as well as preferential remobilization of fine material.
Keywords: Oxygen isotope stratigraphy

Stability of peatland carbon to rising temperatures - Wilson, R. M.; Hopple, A. M.; Tfaily, M. M.; Sebestyen, S. D.; Schadt, C. W.; Pfeifer-Meister, L.; Medvedeff, C.; McFarlane, K. J.; Kostka, J. E.; Kolton, M.; Kolka, R.K.; Kluber, L. A.; et al. (Nature Communications, 2016)
Peatlands contain one-third of soil carbon (C), mostly buried in deep, saturated anoxic zones (catotelm). The response of catotelm C to climate forcing is uncertain, because prior experiments have focused on surface warming. We show that deep peat heating of a 2 m-thick peat column results in an exponential increase in CH4 emissions. However, this response is due solely to surface processes and not degradation of catotelm peat. Incubations show that only the top 20–30 cm of peat from experimental plots have higher CH4 production rates at elevated temperatures. Radiocarbon analyses demonstrate that CH4 and CO2 are produced primarily from decomposition of surface-derived modern photosynthate, not catotelm C. There are no differences in microbial abundances, dissolved organic matter concentrations or degradative enzyme activities among treatments. These results suggest that although surface peat will respond to increasing temperature, the large reservoir of catotelm C is stable under current anoxic conditions.

Stratigraphy, morphology, and geochemistry of late Quaternary buried soils on the High Plains of southwestern Kansas, USA - Anthony L. Layzell; Rolfe D. Mandel; Tammy M. Rittenour; Jon J. Smith; R. Hunter Harlow; Greg A. Ludvigson (CATENA, 2016)
Abstract This study investigated two stratigraphic sequences that record the complex interplay of sedimentation and pedogenesis over the past ca. 84 ka on the High Plains of southwestern Kansas. Up to eight eolian sand and loess units with associated soils were identified in two cores collected from an upland setting. Soil morphological and geochemical data were used to quantitatively assess and compare soil development between multiple buried soils. Chronostratigraphic relationships indicate that 1) loess and eolian sands were episodically deposited during late Marine Isotope Stage (MIS) 5 (ca. 84–70 ka), 2) the Sangamon soil at this site formed between \{MIS\} 3/4 (ca. 70–52 ka), which is consistent with age estimates for renewed Sangamon pedogenesis in the Mississippi River valley, and 3) soil development in the Gilman Canyon Formation began at ca. 44 ka and continued until at least 29.2 ka. Multiple lines of evidence, including grain-size distributions, structure, clay content, and chemical weathering index data, indicate that the morphology and chemistry of the Ak horizon developed in the Gilman Canyon Formation is a product of cumulization by slow loess additions. Similar evidence suggests that cumulization processes are also responsible for the morphology and chemistry of other buried soils in the stratigraphic sequence. Overall, loess inputs during pedogenesis complicate the quantification of weathering processes in these soils.
Keywords: Sangamon soil

Subsurface Evidence of Storm-Driven Breaching along a Transgressing Barrier System, Cape Cod, U.S.A. - Maio, Christopher V.; Gontz, Allen M.; Sullivan, Richard M.; Madsen, Stephanie M.; Weidman, Christopher R.; Donnelly, Jeffrey P. (Journal of Coastal Research, 2016)
Relict and historic tidal channels buried within coastal barriers provide a geologic signature of environmental change, thus enhancing our understanding of how barrier systems respond to extreme storm events. Earliest maps from 1846 depict three inlets along the Waquoit Bay barrier system located on Cape Cod, Massachusetts. These channels were not depicted on maps after 1846, and we lack any information pertaining to them before 1846. The principle objective of this study was to identify the location and map the internal geometry and channel-fill configuration of the buried inlet structures using geophysical and sedimentological data acquisition methods. This was done by collecting 6.2 km of shore-parallel ground-penetrating radar data and five sediment cores ranging in depth from 4 to 5 m. The sediment cores allowed for the ground truthing of the ground-penetrating radar data and provided six samples for radiocarbon dating. The 13 paleochannels identified ranged in depths from 1.3 to 3.7 m below the present beach surface. These appeared in the radar imagery as broad U-shaped cut-and-fill features incised into adjacent barrier facies. The 13 paleochannels composed 24% of the barrier lithosome totaling 704 m in length. Individual channels were primarily less than 65 m in length and between 2.5 and 1.3 m in depth, although an additional 275-m-wide, 3.7-m-deep channel sequence was imaged and likely represents a major and long-lived paleochannel. The results will contribute toward deciphering the evolution of the Waquoit system and identify areas vulnerable to storm-driven coastal change.
Keywords: coastal change; Coastal evolution; ground-penetrating radar; marine transgression; overwash; paleochannel; paleogeography; South Cape Beach

Time in tortoiseshell: a bomb radiocarbon-validated chronology in sea turtle scutes - Van Houtan, K. S.; Andrews, A. H.; Jones, T. T.; Murakawa, S. K. K.; Hagemann, M. E. (Proceedings of the Royal Society of London B: Biological Sciences, 2016)
Some of the most basic questions of sea turtle life history are also the most elusive. Many uncertainties surround lifespan, growth rates, maturity and spatial structure, yet these are critical factors in assessing population status. Here we examine the keratinized hard tissues of the hawksbill (Eretmochelys imbricata) carapace and use bomb radiocarbon dating to estimate growth and maturity. Scutes have an established dietary record, yet the large keratin deposits of hawksbills evoke a reliable chronology. We sectioned, polished and imaged posterior marginal scutes from 36 individual hawksbills representing all life stages, several Pacific populations and spanning eight decades. We counted the apparent growth lines, microsampled along growth contours and calibrated Δ14C values to reference coral series. We fit von Bertalanffy growth function (VBGF) models to the results, producing a range of age estimates for each turtle. We find Hawaii hawksbills deposit eight growth lines annually (range 5–14), with model ensembles producing a somatic growth parameter (k) of 0.13 (range 0.1–0.2) and first breeding at 29 years (range 23–36). Recent bomb radiocarbon values also suggest declining trophic status. Together, our results may reflect long-term changes in the benthic community structure of Hawaii reefs, and possibly shed light on the critical population status for Hawaii hawksbills.
Van Houtan, Kyle SAndrews, Allen HJones, T ToddMurakawa, Shawn K KHagemann, Molly EengResearch Support, U.S. Gov't, Non-P.H.S.England2016/01/08 06:00Proc Biol Sci. 2016 Jan 13;283(1822). pii: 20152220. doi: 10.1098/rspb.2015.2220.

Tracing subarctic Pacific water masses with benthic foraminiferal stable isotopes during the \{LGM\} and late Pleistocene - Mea S. Cook; A. Christina Ravelo; Alan Mix; Ian M. Nesbitt; Nari V. Miller (Deep Sea Research Part II: Topical Studies in Oceanography, 2016)
Abstract As the largest ocean basin, the Pacific helps to set the global climate state, since its circulation affects mean ocean properties, air–sea partitioning of carbon dioxide, and the distribution of global oceanic poleward heat transport. There is evidence that during the Last Glacial Maximum (LGM) the subarctic Pacific contained a better-ventilated, relatively fresh intermediate water mass above  2000 m that may have formed locally. The source and spatial extent of this water mass is not known, nor do we know how formation of this water mass varied during Pleistocene glaciations with different orbital and ice sheet boundary conditions. Here we present a 0.5 My multi-species benthic stable isotope record from Site \{U1345\} (1008 m) on the northern Bering slope and a 1.0 My record from \{U1339\} (1868 m) from the Umnak Plateau in the southeastern basin. We find that the relatively well-ventilated low-δ18O intermediate water reaches 1000 m in the Bering Sea during MIS2, but that the hydrographic divide between this water mass and poorly-ventilated deep water was shallower than 1000 m for earlier glaciations. We also compare Bering Sea piston core and İODP\} Expedition 323 Uvigerina data from the Holocene and \{LGM\} with the modern hydrography, and to previously published profiles from the Okhotsk Sea and Emperor Seamounts. We find that the carbon and oxygen stable isotope signatures of well-ventilated water in the Bering and Okhotsk Seas are distinct, suggesting that there may have been intermediate water formation in both basins during the LGM.
Plio-Pleistocene Paleoceanography of the Bering Sea
Keywords: Ocean circulation

Tracing the intrusion of fossil carbon into coastal Louisiana macrofauna using natural 14C and 13C abundances - Wilson, Rachel M.; Cherrier, Jennifer; Sarkodee-Adoo, Judith; Bosman, Samantha; Mickle, Alejandra; Chanton, Jeffrey P. (Deep Sea Research Part II: Topical Studies in Oceanography, 2016)
The Deepwater Horizon oil spill released a large volume of 13C and radiocarbon depleted organic matter to the northern Gulf of Mexico. Evidence of petroleum-derived carbon entering the offshore planktonic foodweb, as well as widespread oiling of coastal areas documented in previous studies suggests that hydrocarbons could have entered the near shore foodweb. To test this hypothesis, we measured radiocarbon (Δ14C%) and stable carbon isotopes (δ13C) in an assortment of fish tissue, invertebrate tissue and shell samples collected within a year of the spill at seven sites from Louisiana to Florida USA across the northern Gulf of Mexico. We observed a west–east gradient with the most depleted radiocarbon values found in Terrebonne Bay, Louisana and increasingly enriched radiocarbon values in organisms collected at sites to the east. Depleted radiocarbon values as low as −10% in invertebrate soft tissue from Terrebonne suggest assimilation of fossil carbon (2.8±1.2%), consistent with the hypothesis that organic matter from petrochemical reservoirs released during the Deepwater Horizon spill entered the coastal food web to a limited extent. Further there was a significant correlation between radiocarbon and δ13C values in invertebrate tissue consistent with this hypothesis. Both oyster tissue and hard head catfish tissue collected in impacted areas of coastal Louisiana were significantly depleted in 14C and 13C relative to organisms collected in the unaffected Apalachicola Bay, Florida (p<0.014). Alternative explanations for these results include the influence of chronic hydrocarbon pollution along the western gulf coast or that the organisms ingest carbon derived from 14C depleted organic matter mobilized during the erosion of coastal marshes in southern Louisiana.

Variations in microbial carbon sources and cycling in the deep continental subsurface - Danielle N. Simkus; Greg F. Slater; Barbara Sherwood Lollar; Kenna Wilkie; Thomas L. Kieft; Cara Magnabosco; Maggie C.Y. Lau; Michael J. Pullin; Sarah B. Hendrickson; K. Eric Wommack; Eric G. Sakowski; Esta van Heerden; et al. (Geochimica et Cosmochimica Acta, 2016)
Abstract Deep continental subsurface fracture water systems, ranging from 1.1 to 3.3 km below land surface (kmbls), were investigated to characterize the indigenous microorganisms and elucidate microbial carbon sources and their cycling. Analysis of phospholipid fatty acid (PLFA) abundances and direct cell counts detected varying biomass that was not correlated with depth. Compound-specific carbon isotope analyses (δ13C and Δ14C) of the phospholipid fatty acids (PLFAs) and carbon substrates combined with genomic analyses did identify, however, distinct carbon sources and cycles between the two depth ranges studied. In the shallower boreholes at circa 1 kmbls, isotopic evidence indicated microbial incorporation of biogenic \{CH4\} by the in situ microbial community. At the shallowest site, 1.05 kmbls in Driefontein mine, this process clearly dominated the isotopic signal. At slightly deeper depths, 1.34 kmbls in Beatrix mine, the isotopic data indicated the incorporation of both biogenic \{CH4\} and dissolved inorganic carbon (DIC) derived from \{CH4\} oxidation. In both of these cases, molecular genetic analysis indicated that methanogenic and methanotrophic organisms together comprised a small component (<5%) of the microbial community. Thus, it appears that a relatively minor component of the prokaryotic community is supporting a much larger overall bacterial community in these samples. In the samples collected from >3 kmbls in Tau Tona mine (TT107, \{TT109\} Bh2), the \{CH4\} had an isotopic signature suggesting a predominantly abiogenic origin with minor inputs from microbial methanogenesis. In these samples, the isotopic enrichments (δ13C and Δ14C) of the \{PLFAs\} relative to \{CH4\} were consistent with little incorporation of \{CH4\} into the biomass. The most 13C-enriched \{PLFAs\} were observed in \{TT107\} where the dominant CO2-fixation pathway was the acetyl-CoA pathway by non-acetogenic bacteria. The differences in the δ13C of the \{PLFAs\} and the \{DIC\} and \{DOC\} for \{TT109\} Bh2 were ∼−24‰ and 0‰, respectively. The dominant CO2-fixation pathways were 3-HP/4-HB cycle > acetyl-CoA pathway > reductive pentose phosphate cycle.

AMS radiocarbon dating of very large Grandidier’s baobabs (Adansonia grandidieri) - Patrut, Adrian; von Reden, Karl F.; Danthu, Pascal; Leong Pock-Tsy, Jean-Michel; Rakosy, Laszlo; Patrut, Roxana T.; Lowy, Daniel A.; Margineanu, Dragos (Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms, 2015)
The article reports the AMS radiocarbon investigation of the two largest known Adansonia grandidieri specimens. The two baobabs, which are named Tsitakakoike and Pregnant baobab, are located in Southwestern Madagascar, near Andombiro. A third specimen from this area, the House baobab, was also investigated. According to measurements, Tsitakakoike is the biggest individual above ground level of all Adansonia species. The House baobab was selected for its exposed structure, which is identical to the closed ring-shaped structure with false cavities identified by us in large and old Adansonia digitata specimens. According to our research, Tsitakakoike and the Pregnant baobab have multi-stemmed cylindrical trunks which are mainly hollow; the two very large baobabs also possess a ring-shaped structure. The radiocarbon dates of the oldest wood samples collected from the large trunks were 1274 ± 20 bp for Tsitakakoike and 930 ± 20 bp for the Pregnant baobab. According to their original positions and to the architectures of the two A. grandidieri, the ages of Tsitakakoike and Pregnant baobab would be between 1300 and 1500 years. Therefore, A. grandidieri becomes the third Adansonia species with individuals that can live over 1000 years, according to accurate dating results.
Cu2hzTimes Cited:2Cited References Count:20

Ancient population genomics and the study of evolution - Parks, M.; Subramanian, S.; Baroni, C.; Salvatore, M. C.; Zhang, G.; Millar, C. D.; Lambert, D. M. (Philosophical Transactions of the Royal Society B: Biological Sciences, 2015)
Recently, the study of ancient DNA (aDNA) has been greatly enhanced by the development of second-generation DNA sequencing technologies and targeted enrichment strategies. These developments have allowed the recovery of several complete ancient genomes, a result that would have been considered virtually impossible only a decade ago. Prior to these developments, aDNA research was largely focused on the recovery of short DNA sequences and their use in the study of phylogenetic relationships, molecular rates, species identification and population structure. However, it is now possible to sequence a large number of modern and ancient complete genomes from a single species and thereby study the genomic patterns of evolutionary change over time. Such a study would herald the beginnings of ancient population genomics and its use in the study of evolution. Species that are amenable to such large-scale studies warrant increased research effort. We report here progress on a population genomic study of the Adélie penguin (Pygoscelis adeliae). This species is ideally suited to ancient population genomic research because both modern and ancient samples are abundant in the permafrost conditions of Antarctica. This species will enable us to directly address many of the fundamental questions in ecology and evolution.

Applications and limitations of U–Th disequilibria systematics for determining ages of carbonate alteration minerals in peridotite - Mervine, Evelyn M.; Sims, Kenneth W.W.; Humphris, Susan E.; Kelemen, Peter B. (Chemical Geology, 2015)
238U–234U–230Th dating was conducted on carbonate alteration minerals in the peridotite layer of the Samail Ophiolite, Sultanate of Oman, in order to assess the applicability of U-series dating techniques to these types of Quaternary terrestrial carbonates and also to further constrain natural rates of carbonation of the peridotite. Due to their low U concentrations and relatively high Th/U ratios, Samail carbonates are challenging to date with the 230Th technique because of the sensitivity of ages to corrections for initial 230Th. Uncorrected 230Th ages for Ca-rich travertines are consistently older than previously obtained 14C ages. However, geologically reasonable initial 230Th corrections bring the two sets of ages into concordance. This age concordance suggests that the travertines are generally closed systems, adding a level of credence to the reliability of previously obtained 14C ages. In contrast, uncorrected 230Th ages for Mg-rich carbonate veins are generally younger than previously obtained 14C ages. These young ages are interpreted in terms of remobilization of hexavalent U, which is subsequently deposited as tetravalent U by reduced serpentinization fluids. Two Mg-rich carbonate veins sampled at a roadcut have near-equilibrium (230Th/238U) and (234U/238U) values, which indicate that these veins are > 375,000 years in age, consistent with their “14C dead” (> 50,000 years BP) ages. The variable young and old ages for these Mg-rich carbonate veins indicate that carbonation of the peridotite layer of the Samail Ophiolite is an ongoing process and that there have been multiple generations of subsurface carbonate vein formation. Overall, this study provides insights into some of the challenges associated with applying U-series dating methods to Quaternary terrestrial carbonates, in particular carbonate alteration minerals in peridotites, and highlights some areas where there is room for improvement, such as obtaining better constraints on the isotopic composition of admixed detritus, and also some advantages, such as the ability to identify open system behavior not apparent from 14C dating and stable C and O isotopic analysis alone.

Climate forcing of unprecedented intense-hurricane activity in the last 2000 years - Donnelly, Jeffrey P.; Hawkes, Andrea D.; Lane, Philip; MacDonald, Dana; Shuman, Bryan N.; Toomey, Michael R.; van Hengstum, Peter J.; Woodruff, Jonathan D. (EARTHS FUTURE, 2015)
How climate controls hurricane variability has critical implications for society is not well understood. In part, our understanding is hampered by the short and incomplete observational hurricane record. Here we present a synthesis of intense-hurricane activity from the western North Atlantic over the past two millennia, which is supported by a new, exceptionally well-resolved record from Salt Pond, Massachusetts (USA). At Salt Pond, three coarse grained event beds deposited in the historical interval are consistent with severe hurricanes in 1991 (Bob), 1675, and 1635 C.E., and provide modern analogs for 32 other prehistoric event beds. Two intervals of heightened frequency of event bed deposition between 1400 and 1675 C.E. (10 events) and 150 and 1150 C.E. (23 events), represent the local expression of coherent regional patterns in intense-hurricane-induced event beds. Our synthesis indicates that much of the western North Atlantic appears to have been active between 250 and 1150 C.E., with high levels of activity persisting in the Caribbean and Gulf of Mexico until 1400 C.E. This interval was one with relatively warm sea surface temperatures (SSTs) in the main development region (MDR). A shift in activity to the North American east coast occurred ca. 1400 C.E., with more frequent severe hurricane strikes recorded from The Bahamas to New England between 1400 and 1675 C.E. A warm SST anomaly along the western North Atlantic, rather than within the MDR, likely contributed to the later active interval being restricted to the east coast.
Keywords: Climate change; common era; Holocene; sea surface temperature; tropical cyclones

Comparing dust flux records from the Subarctic North Pacific and Greenland: Implications for atmospheric transport to Greenland and for the application of dust as a chronostratigraphic tool - Serno, Sascha; Winckler, Gisela; Anderson, Robert F.; Maier, Edith; Ren, Haojia; Gersonde, Rainer; Haug, Gerald H. (PALEOCEANOGRAPHY, 2015)
We present a new record of eolian dust flux to the western Subarctic North Pacific (SNP) covering the past 27,000years based on a core from the Detroit Seamount. Comparing the SNP dust record to the North Greenland Ice Core Project (NGRIP) ice core record shows significant differences in the amplitude of dust changes to the two regions during the last deglaciation, while the timing of abrupt changes is synchronous. If dust deposition in the SNP faithfully records its mobilization in East Asian source regions, then the difference in the relative amplitude must reflect climate-related changes in atmospheric dust transport to Greenland. Based on the synchronicity in the timing of dust changes in the SNP and Greenland, we tie abrupt deglacial transitions in the Th-230-normalized He-4 flux record to corresponding transitions in the well-dated NGRIP dust flux record to provide a new chronostratigraphic technique for marine sediments from the SNP. Results from this technique are complemented by radiocarbon dating, which allows us to independently constrain radiocarbon paleoreservoir ages. We find paleoreservoir ages of 745140years at 11,653year B.P., 680228years at 14,630year B.P., and 790498years at 23,290year B.P. Our reconstructed paleoreservoir ages are consistent with modern surface water reservoir ages in the western SNP. Good temporal synchronicity between eolian dust records from the Subantarctic Atlantic and equatorial Pacific and the ice core record from Antarctica supports the reliability of the proposed dust tuning method to be used more widely in other global ocean regions.
Keywords: atmospheric circulation; chronostratigrapy; eolian dust; helium-4; paleoreservoir age; Subarctic North Pacific

Forces driving late Pleistocene (ca. 77–12 ka) landscape evolution in the Cimarron River valley, southwestern Kansas - Layzell, Anthony L.; Mandel, Rolfe D.; Ludvigson, Greg A.; Rittenour, Tammy M.; Smith, Jon J. (Quaternary Research, 2015)
This study presents stratigraphic, geomorphic, and paleoenvironmental (δ13C) data that provide insight into the late Pleistocene landscape evolution of the Cimarron River valley in the High Plains of southwestern Kansas. Two distinct valley fills (T-1 and T-2) were investigated. Three soils occur in the T-2 fill and five in the T-1 fill, all indicating periods of landscape stability or slow sedimentation. Of particular interest are two cumulic soils dating to ca. 48–28 and 13–12.5 ka. δ13C values are consistent with regional paleoenvironmental proxy data that indicate the prevalence of warm, dry conditions at these times. The Cimarron River is interpreted to have responded to these climatic changes and to local base level control. Specifically, aggradation occurred during cool, wet periods and slow sedimentation with cumulic soil formation occurred under warmer, drier climates. Significant valley incision (~ 25 m) by ca. 28 ka likely resulted from a lowering of local base level caused by deep-seated dissolution of Permian evaporite deposits.

Glacial-interglacial changes in central tropical Pacific surface seawater property gradients - Lynch-Stieglitz, Jean; Polissar, Pratigya J.; Jacobel, Allison W.; Hovan, Steven A.; Pockalny, Robert A.; Lyle, Mitchell; Murray, Richard W.; Ravelo, A. Christina; Bova, Samantha C.; Dunlea, Ann G.; Ford, Heather L.; Hertzberg, Jennifer E.; et al. (Paleoceanography, 2015)
Much uncertainty exists about the state of the oceanic and atmospheric circulation in the tropical Pacific over the last glacial cycle. Studies have been hampered by the fact that sediment cores suitable for study were concentrated in the western and eastern parts of the tropical Pacific, with little information from the central tropical Pacific. Here we present information from a suite of sediment cores collected from the Line Islands Ridge in the central tropical Pacific, which show sedimentation rates and stratigraphies suitable for paleoceanographic investigations. Based on the radiocarbon and oxygen isotope measurements on the planktonic foraminifera Globigerinoides ruber, we construct preliminary age models for selected cores and show that the gradient in the oxygen isotope ratio of G. ruber between the equator and 8°N is enhanced during glacial stages relative to interglacial stages. This stronger gradient could reflect enhanced equatorial cooling (perhaps reflecting a stronger Walker circulation) or an enhanced salinity gradient (perhaps reflecting increased rainfall in the central tropical Pacific).

Late Holocene precipitation variability recorded in the sediments of Reloncaví Fjord (41°S, 72°W), Chile - Rebolledo, Lorena; Lange, Carina B.; Bertrand, Sébastien; Muñoz, Praxedes; Salamanca, Marco; Lazo, Pablo; Iriarte, José L.; Vargas, Gabriel; Pantoja, Silvio; Dezileau, Laurent (Quaternary Research, 2015)
We present reconstructions of late Holocene changes in the source of organic matter and siliceous export production in the Relocanví Fjord (41°S, 72°W), Northern Chilean Patagonia, based on organic carbon content, δ13Corg, N/C ratio, diatom assemblages and biogenic silica contents from three sediment cores. The age models are based on a combination of 210Pb profiles, AMS 14C dating, and on the first occurrence of the diatom Rhizosolenia setigera f. pungens, as a stratigraphic marker in the fjords. The cores span the last 300 to 700 yr. Diatoms dominate the siliceous assemblages in the three cores (98% on average). Our results suggest that precipitation seasonality in the region of Reloncaví was high in CE 1300–1400 and CE 1700–1850, with a clear decreasing trend since CE 1850. The latter trend is in agreement with instrumental records and tree-ring reconstructions. These fluctuations seem to be associated with the Southern Annular Mode (SAM).
Co0ceTimes Cited:1Cited References Count:93

Marine record of Holocene climate, ocean, and cryosphere interactions: Herbert Sound, James Ross Island, Antarctica - Minzoni, Rebecca Totten; Anderson, John B.; Fernandez, Rodrigo; Wellner, Julia Smith (Quaternary Science Reviews, 2015)
The sediment record offshore James Ross Island, northeast Antarctic Peninsula presents an unparalleled opportunity to directly compare marine and terrestrial climate records spanning the Holocene in maritime Antarctica. An 11 m drill core was collected between Herbert Sound and Croft Bay as part of the SHALDRIL NBP-0502 initiative and produced the southernmost sediment record from the eastern side of the AP. Thirty-eight radiocarbon ages are used to construct an age model of centennial-scale resolution. Multi-proxy records, including magnetic susceptibility, pebble content, particle size, total organic carbon, and diatom assemblages, were interrogated in the context of nearby Holocene-age ice core, lake, and drift records from James Ross Island. Differences in the timing and expression of Holocene events reflect marine controls on tidewater glaciers, such as water mass configurations and sea ice. Glacial behavior mimics ice core paleotemperatures during the Holocene, with the exception of distinct ocean warming events. Herbert Sound was fully occupied by grounded ice during the Last Glacial Maximum, and experienced rapid lift-off, followed by a floating ice phase. The canopy of floating ice receded by 10 ± 2.4 cal kyr BP, presumably in response to Early Holocene warming. Herbert Sound and Croft Bay fully deglaciated by 7.2 cal kyr BP, when the Mid Holocene Hypsithermal commenced and the sound became open and productive. An extreme peak in productivity ∼6.1 cal kyr BP indicates an oceanic warming event that is not reflected in atmospheric temperature or lacustrine sediment records. Increase in sea ice cover and ice rafting mark the onset of the Neoglacial ∼2.5 cal kyr BP, when pronounced atmospheric cooling is documented in the James Ross Island ice core. Our comparison facilitates more holistic understanding of atmosphere-ocean-cryosphere interactions that may aid predictions of glacial response to future warming and sea-level scenarios.
Keywords: Antarctic Peninsula; diatoms; Holocene; paleoceanography; paleoclimatology

Multimolecular tracers of terrestrial carbon transfer across the pan-Arctic: C-14 characteristics of sedimentary carbon components and their environmental controls - Feng, Xiaojuan; Gustafsson, Örjan; Holmes, R. Max; Vonk, Jorien E.; van Dongen, Bart E.; Semiletov, Igor P.; Dudarev, Oleg V.; Yunker, Mark B.; Macdonald, Robie W.; Wacker, Lukas; Montluçon, Daniel B.; Eglinton, Timothy I. (GLOBAL BIOGEOCHEMICAL CYCLES, 2015)
Distinguishing the sources, ages, and fate of various terrestrial organic carbon (OC) pools mobilized from heterogeneous Arctic landscapes is key to assessing climatic impacts on the fluvial release of carbon from permafrost. Through molecular C-14 measurements, including novel analyses of suberin- and/or cutin-derived diacids (DAs) and hydroxy fatty acids (FAs), we compared the radiocarbon characteristics of a comprehensive suite of terrestrial markers (including plant wax lipids, cutin, suberin, lignin, and hydroxy phenols) in the sedimentary particles from nine major arctic and subarctic rivers in order to establish a benchmark assessment of the mobilization patterns of terrestrial OC pools across the pan-Arctic. Terrestrial lipids, including suberin-derived longer-chain DAs (C-24,C-26,C-28), plant wax FAs (C(24,26,2)8), and n-alkanes (C-27,C-29,C-31), incorporated significant inputs of aged carbon, presumably from deeper soil horizons. Mobilization and translocation of these ``old{''} terrestrial carbon components was dependent on nonlinear processes associated with permafrost distributions. By contrast, shorter-chain (C-16,C-18) DAs and lignin phenols (as well as hydroxy phenols in rivers outside eastern Eurasian Arctic) were much more enriched in C-14, suggesting incorporation of relatively young carbon supplied by runoff processes from recent vegetation debris and surface layers. Furthermore, the radiocarbon content of terrestrial markers is heavily influenced by specific OC sources and degradation status. Overall, multitracer molecular C-14 analysis sheds new light on the mobilization of terrestrial OC from arctic watersheds. Our findings of distinct ages for various terrestrial carbon components may aid in elucidating fate of different terrestrial OC pools in the face of increasing arctic permafrost thaw.

A post-glacial relative sea-level curve from Fiordland, New Zealand - Dlabola, E. K.; Wilson, G. S.; Gorman, A. R.; Riesselman, C. R.; Moy, C. M. (Global and Planetary Change, 2015)
The modern fjords of southwest New Zealand were previously stranded lakes isolated from the Tasman Sea by bedrock and moraine sills following the retreat of glaciers at the Last Glacial Maximum. The isolated lake basins were subsequently inundated with sea water when sea-level rise overtopped the sills. A record of the lacustrine-to-marine environmental transition is preserved in the fjord basin sediments and is identified in two New Zealand fjords with high-resolution seismic data and paleoenvironmental analysis of sediment cores. Seismic data are used to constrain the maximum sill depth and microfossil assemblages are used to track the lacustrine-to-marine transition. Chronology is based on fourteen radiocarbon ages. A relative sea-level curve for Fiordland, New Zealand is constructed based on sill depths and age constraints on the marine incursion. The sea-level curve allows insights into estimated uplift rates for Fiordland during the Holocene. From a lowstand of at least 107 mbsl 14,750 yr ago, these data reveal a stepwise transgression. Meltwater Pulse 1b is identified between 12,400 and 11,400 yr ago, with a second acceleration in sea-level rise observed 9700 yr ago. This record contributes a new sea-level curve for a mid-latitude (45°S) Southern Hemisphere location as well as new evidence for Meltwater Pulse 1b.

Quantification of refractory organic material in Amazon mudbanks of the French Guiana Coast - Williams, Elizabeth K.; Rosenheim, Brad E.; Allison, Mead; McNichol, Ann P.; Xu, Li (Marine Geology, 2015)
Sub-oxic overturning mudbanks originating in the Amazon outlet and traveling northwestward along the coast of South America store 3.5 Tg organic carbon on the Amazon shelf, annually. The predominance of old soil carbon burial associated with the sediment has been supported by relatively old bulk radiocarbon ages (~ 2200–3200 14C y) reported, but this amount has yet to be quantified for this dynamic setting. Here, we employ ramped pyrolysis radiocarbon dating to mudbank sediments from three cores to further constrain the amount of refractory sedimentary organic carbon present. Using radiocarbon age as a proxy for reactivity, we find that at least 36% of this organic carbon is pre-aged refractory terrestrial organic carbon, likely sourced from terrestrial soils and averaging ages of 16,100 ± 300 14C y. This implies significant preservation of pre-aged terrestrial soil material in this marine environment despite the mobility and oxygen availability in the muds. Concurrently, an average of 77% of this organic material is aged over 1000 14C y, consistent with previous estimates that the majority of organic carbon buried along the shelf is refractory. Analyses of extracted lignin phenols and terrestrial humic acids also support this preservation of refractory terrestrial material. These data indicate that sediment discharged from the Amazon River may preserve refractory terrestrial carbon in marine sediments at a minimum of 3.1 Tg C/y, which is more efficient than originally thought.

Sedimentation Pulse in the NE Gulf of Mexico following the 2010 DWH Blowout - Brooks, Gregg R.; Larson, Rebekka A.; Schwing, Patrick T.; Romero, Isabel; Moore, Christopher; Reichart, Gert-Jan; Jilbert, Tom; Chanton, Jeff P.; Hastings, David W.; Overholt, Will A.; Marks, Kala P.; Kostka, Joel E.; et al. (PLOS ONE, 2015)
The objective of this study was to investigate the impacts of the Deepwater Horizon (DWH) oil discharge at the seafloor as recorded in bottom sediments of the DeSoto Canyon region in the northeastern Gulf of Mexico. Through a close coupling of sedimentological, geochemical, and biological approaches, multiple independent lines of evidence from 11 sites sampled in November/December 2010 revealed that the upper ~1 cm depth interval is distinct from underlying sediments and results indicate that particles originated at the sea surface. Consistent dissimilarities in grain size over the surficial ~1 cm of sediments correspond to excess 234Th depths, which indicates a lack of vertical mixing (bioturbation), suggesting the entire layer was deposited within a 4–5 month period. Further, a time series from four deep-sea sites sampled up to three additional times over the following two years revealed that excess 234Th depths, accumulation rates, and 234Th inventories decreased rapidly, within a few to several months after initial coring. The interpretation of a rapid sedimentation pulse is corroborated by stratification in solid phase Mn, which is linked to diagenesis and redox change, and the dramatic decrease in benthic formanifera density that was recorded in surficial sediments. Results are consistent with a brief depositional pulse that was also reported in previous studies of sediments, and marine snow formation in surface waters closer to the wellhead during the summer and fall of 2010. Although sediment input from the Mississippi River and advective transport may influence sedimentation on the seafloor in the DeSoto Canyon region, we conclude based on multidisciplinary evidence that the sedimentation pulse in late 2010 is the product of marine snow formation and is likely linked to the DWH discharge.

Source-age dynamics of estuarine particulate organic matter using fatty acid delta C-13 and Delta C-14 composition - McIntosh, Hadley A.; McNichol, Ann P.; Xu, Li; Canuel, Elizabeth A. (Limnology and Oceanography, 2015)
This study used a multiproxy approach to elucidate the source and age composition of estuarine particulate organic matter (POM) using bulk stable isotopes (C-13(POC)), fatty acid (FA) biomarkers, and compound specific isotopic analyses in surface waters along the Delaware River and Bay (Delaware Estuary, hereafter). C-13 values of FA (C-13(FA)) ranged more widely (-30.9 parts per thousand to -21.8 parts per thousand) than C-13(POC) (-27.5 parts per thousand to -23.5 parts per thousand), providing greater insight about POM sources along the estuary. C-13 values of C-16:0 phospholipid FA (primarily, aquatic sources) increased along the salinity gradient (-29.8 parts per thousand to -23.4 parts per thousand), while C-13(FA) values of long-chain neutral fatty acid (terrestrial sources) decreased (-28.6 parts per thousand to -30.9 parts per thousand). C-13(FA) values for C-18's FA indicated the importance of marsh-derived organic matter within Delaware Estuary. Compound specific radiocarbon analysis showed the heterogeneous age structure of FA associated with POM (FA(POM)). C-14 ages of FA ranged from modern (postbomb) to 1790BP; aged FA (120BP to 1700BP) derived primarily from the watershed, whereas modern FA were produced within Delaware Estuary. C-14 ages of short-chain FA (aquatic sources) reflected differences in the age of dissolved inorganic carbon along the estuary and had older C-14 ages at the river end-member. C-14 ages of FA from terrigenous sources were older than water and sediment residence times indicating this source derived from the watershed. This study is the first to document the complex age distribution of FA(POM) along the estuarine salinity gradient and shows that inorganic carbon sources, watershed inputs and autochthonous production contribute to variation in the ages of POM.
PT: J; TC: 0; UT: WOS:000351126500020

Ultra-Small Graphitization Reactors for Ultra-Microscale C-14 Analysis at the National Ocean Sciences Accelerator Mass Spectrometry (Nosams) Facility - Walter, Sunita R. Shah; Gagnon, Alan R.; Roberts, Mark L.; McNichol, Ann P.; Gaylord, Mary C. Lardie; Klein, Elizabeth (Radiocarbon, 2015)
In response to the increasing demand for C-14 analysis of samples containing less than 25 mu g C, ultra-small graphitization reactors with an internal volume of similar to 0.8 mL were developed at NOSAMS. For samples containing 6 to 25 mu g C, these reactors convert CO2 to graphitic carbon in approximately 30 min. Although we continue to refine reaction conditions to improve yield, the reactors produce graphite targets that are successfully measured by AMS. Graphite targets produced with the ultra-small reactors are measured by using the Cs sputter source on the CFAMS instrument at NOSAMS where beam current was proportional to sample mass. We investigated the contribution of blank carbon from the ultra-small reactors and estimate it to be 0.3 +/- 0.1 mu g C with an Fm value of 0.43 +/- 0.3. We also describe equations for blank correction and propagation of error associated with this correction. With a few exceptions for samples in the range of 6 to 7 mu g C, we show that corrected Fm values agree with expected Fm values within uncertainty for samples containing 6-100 mu g C.
PT: J; TC: 1; UT: WOS:000351052600009

What do benthic ? 13 C and ? 18 O data tell us about Atlantic circulation during Heinrich Stadial 1? - Oppo, Delia W.; Curry, William B.; McManus, Jerry F. (Paleoceanography, 2015)
Approximately synchronous with the onset of Heinrich Stadial 1 (HS1), δ13C decreased throughout most of the upper (~1000–2500 m) Atlantic, and at some deeper North Atlantic sites. This early deglacial δ13C decrease has been alternatively attributed to a reduced fraction of high-δ13C North Atlantic Deep Water (NADW) or to a decrease in the NADW δ13C source value. Here we present new benthic δ18O and δ13C records from three relatively shallow (~1450–1650 m) subpolar Northeast Atlantic cores. With published data from other cores, these data form a depth transect (~1200–3900 m) in the subpolar Northeast Atlantic. We compare Last Glacial Maximum (LGM) and HS1 data from this transect with data from a depth transect of cores from the Brazil Margin. The largest LGM-to-HS1 decreases in both benthic δ13C and δ18O occurred in upper waters containing the highest NADW fraction during the LGM. We show that the δ13C decrease can be explained entirely by a lower NADW δ13C source value, entirely by a decrease in the proportion of NADW relative to Southern Ocean Water, or by a combination of these mechanisms. However, building on insights from model simulations, we hypothesize that reduced ventilation due to a weakened but still active Atlantic Meridional Overturning Circulation also contributed to the low δ13C values in the upper North Atlantic. We suggest that the benthic δ18O gradients above ~2300 m at both core transects indicate the depth to which heat and North Atlantic deglacial freshwater had mixed into the subsurface ocean by early HS1.

A 2000-yr reconstruction of air temperature in the Great Basin of the United States with specific reference to the Medieval Climatic Anomaly - Reinemann, Scott A.; Porinchu, David F.; MacDonald, Glen M.; Mark, Bryan G.; DeGrand, James Q. (Quaternary Research, 2014)
A sediment core representing the past two millennia was recovered from Stella Lake in the Snake Range of the central Great Basin in Nevada. The core was analyzed for sub-fossil chironomids and sediment organic content. A quantitative reconstruction of mean July air temperature (MJAT) was developed using a regional training set and a chironomid-based WA-PLS inference model (r2jack = 0.55, RMSEP = 0.9°C). The chironomid-based MJAT reconstruction suggests that the interval between AD 900 and AD 1300, corresponding to the Medieval Climate Anomaly (MCA), was characterized by MJAT elevated 1.0°C above the subsequent Little Ice Age (LIA), but likely not as warm as recent conditions. Comparison of the Stella Lake temperature reconstruction to previously published paleoclimate records from this region indicates that the temperature fluctuations inferred to have occurred at Stella Lake between AD 900 and AD 1300 correspond to regional records documenting hydroclimate variability during the MCA interval. The Stella Lake record provides evidence that elevated summer temperature contributed to the increased aridity that characterized the western United States during the MCA.
Aq8ljTimes Cited:0Cited References Count:70

Advection and scavenging controls of Pa/Th in the northern NE Atlantic - Roberts, Natalie L.; McManus, Jerry F.; Piotrowski, Alexander M.; McCave, I. Nicholas (Paleoceanography, 2014)
Over the last 2 decades, significant advances have been made in reconstructing past rates of ocean circulation using sedimentary proxies for the dynamics of abyssal waters. In this study we combine the use of two rate proxies, sortable silt grain size, and sedimentary 231Pa/230Th, measured on a depth transect of deep-sea sediment cores from the northern NE Atlantic, to investigate ocean circulation changes during the last deglacial. We find that at two deep sites, the core-top 231Pa/230Th ratios reflect Holocene circulation rates, while during Heinrich Stadial 1, the deglacial ratios peaked as the sortable silt grain size decreased, reflecting a general circulation slowdown. However, the peak 231Pa/230Th significantly exceeded the production ratio in both cores, indicating that 231Pa/230Th was only partially controlled by ocean circulation at these sites. This is supported by a record of 231Pa/230Th from an intermediate water depth site, where values also peaked during Heinrich Stadial 1, but were consistently above the production ratio over the last 24 ka, reflecting high scavenging below productive surface waters. At our study sites, we find that preserved sediment component fluxes cannot be used to distinguish between a scavenging or circulation control, although they are consistent with a circulation influence, since the core at intermediate depth with the highest 231Pa/230Th recorded the lowest particle fluxes. Reconstruction of advection rate using 231Pa/230Th in this region is complicated by high productivity, but the data nevertheless contain important information on past deep ocean circulation.

Carbonation rates of peridotite in the Samail Ophiolite, Sultanate of Oman, constrained through 14C dating and stable isotopes - Mervine, Evelyn M.; Humphris, Susan E.; Sims, Kenneth W. W.; Kelemen, Peter B.; W. J. Jenkins (Geochimica et Cosmochimica Acta, 2014)
Detailed 14C dating as well as stable C and O isotope analyses were conducted on carbonates formed during alteration of the peridotite layer of the Samail Ophiolite, Sultanate of Oman. 14C results obtained in this and previous studies indicate that surface travertines range in age from modern to >45,000 yr BP, indicating long-term deposition and preservation. Travertine deposition rates in two localities were ∼0.1 to 0.3 mm/yr between ∼30,000 and 45,000 yr BP. Using an estimate of total travertine area, this would result in a maximum of ∼1000 to 3000 m3/yr of travertine being deposited throughout the ophiolite during this time period. This travertine deposition would have sequestered a maximum of ∼1 to 3 × 106 kg CO2/yr. Ca-rich carbonate veins that are associated with the surface travertine deposits have ages ranging from ∼4000 to 36,000 yr BP (average: 15,000 yr BP). Mg-rich carbonate veins exposed in outcrops have ages ranging from ∼8000 to 45,000 yr BP (average: 35,000 yr BP). Detailed sampling from numerous locations (3 locations in this study and 10 locations in the previous studies) indicates that no carbonate veins from the natural peridotite weathering surface are older than the ∼50,000 yr BP dating limit of 14C. However, 14C dating of Mg-rich carbonate veins from three roadcut exposures (Qafeefah, Fanja, and Al-Wuqbah) indicates that a significant number of roadcut veins are 14C dead (>50,000 yr BP). A location weighted average indicates that ∼40% of veins sampled at the three roadcuts are 14C dead. An average including veins sampled at both roadcuts and outcrops indicates that overall ∼8% of Mg-rich carbonate veins are 14C dead. Mg-rich carbonate veins are estimated to sequester on the order of 107 kg CO2/yr throughout the ophiolite.

Centennial-to-millennial hydrologic trends and variability along the North Atlantic Coast, USA, during the Holocene - Newby, Paige E.; Shuman, Bryan N.; Donnelly, Jeffrey P.; Karnauskas, Kristopher B.; Marsicek, Jeremiah (Geophysical Research Letters, 2014)
Geophysical and sedimentary records from five lakes in Massachusetts reveal regionally coherent hydrologic variability during the Holocene. All of the lakes have risen since ~9.0 ka, but multicentury droughts after 5.6 ka repeatedly lowered their water levels. Quantified water level histories from the three best-studied lakes share >70% of their reconstructed variance. Four prominent low-water phases at 4.9–4.6, 4.2–3.9, 2.9–2.1, and 1.3–1.2 ka were synchronous across coastal lakes, even after accounting for age uncertainties. The droughts also affected sites up to ~200 km inland, but water level changes at 5.6–4.9 ka appear out of phase between inland and coastal lakes. During the enhanced multicentury variability after ~5.6 ka, droughts coincided with cooling in Greenland and may indicate circulation changes across the North Atlantic region. Overall, the records demonstrate that current water levels are exceptionally high and confirm the sensitivity of water resources in the northeast U.S. to climate change.

Deciphering microbial carbon substrates in PAH contaminated sediments using phospholipid fatty acids, and compound specific δ13C and Δ14C - Morrill, Penny L.; Szponar, Natalie; Johnston, Mathew; Marvin, Chris; Slater, Gregory F. (Organic Geochemistry, 2014)
Stable and radiogenic carbon isotopes (δ13C and Δ14C) of organic compounds and phospholipid fatty acids (PLFAs), as well as polycyclic aromatic hydrocarbon (PAH) ratios were used to determine sources and fates of organic contaminants in highly contaminated, and less contaminated sediments of Hamilton Harbour. The highly contaminated sediments had an order of magnitude more total petroleum hydrocarbons (TPHs) compared to the less contaminated sediments. The TPHs extracted from both sites were depleted in 14C (average Δ14C of −775‰ and −973‰, for Sites 1 and 2, respectively) consistent with inputs of fossil derived contaminants. Fossil carbon also contributed to the unextractable residue (Δ14C = −503 ± 55‰) in the sediment at the highly contaminated site relative to the less contaminated site (Δ14C = −132 ± 2‰) indicating inputs of fossil carbon not derived from petroleum or PAHs. Diagnostic PAH ratios (e.g. PAH:NaP between 0.01 and 1), and less negative δ13C (−25.6 ± 0.2‰) of the unextractable residue indicated that a coal derived source was the most likely source of these inputs. Despite the presence of this fossil carbon, there was little evidence of utilization of ancient carbon by the microbial community. The Δ14C of PLFAs from the highly contaminated site were slightly more 14C depleted (Δ14C = −138 ± 20‰) relative to the PLFAs from the less contaminated site (Δ14C = −77 ± 42‰), demonstrating some microbial metabolism of older carbon; however, the majority of the carbon metabolized was modern at both sites, indicating that there was minimal natural attenuation via bioremediation of fossil fuel organic contaminants.

Deglacial ?18O and hydrologic variability in the tropical Pacific and Indian Oceans - Gibbons, Fern T.; Oppo, Delia W.; Mohtadi, Mahyar; Rosenthal, Yair; Cheng, Jun; Liu, Zhengyu; Linsley, Braddock K. (Earth and Planetary Science Letters, 2014)
Evidence from geologic archives suggests that there were large changes in the tropical hydrologic cycle associated with the two prominent northern hemisphere deglacial cooling events, Heinrich Stadial 1 (HS1; ∼19 to 15 kyr BP; kyr BP = 1000 yr before present) and the Younger Dryas (∼12.9 to 11.7 kyr BP). These hydrologic shifts have been alternatively attributed to high and low latitude origin. Here, we present a new record of hydrologic variability based on planktic foraminifera-derived δ18O of seawater (δ18Osw) estimates from a sediment core from the tropical Eastern Indian Ocean, and using 12 additional δ18Osw records, construct a single record of the dominant mode of tropical Eastern Equatorial Pacific and Indo-Pacific Warm Pool (IPWP) hydrologic variability. We show that deglacial hydrologic shifts parallel variations in the reconstructed interhemispheric temperature gradient, suggesting a strong response to variations in the Atlantic Meridional Overturning Circulation and the attendant heat redistribution. A transient model simulation of the last deglaciation suggests that hydrologic changes, including a southward shift in the Intertropical Convergence Zone (ITCZ) which likely occurred during these northern hemisphere cold events, coupled with oceanic advection and mixing, resulted in increased salinity in the Indonesian region of the IPWP and the eastern tropical Pacific, which is recorded by the δ18Osw proxy. Based on our observations and modeling results we suggest the interhemispheric temperature gradient directly controls the tropical hydrologic cycle on these time scales, which in turn mediates poleward atmospheric heat transport.
Keywords: Deglaciation; Eastern Equatorial Pacific; heat transport; Indo-Pacific; δ18O of seawater

Delta growth and river valleys: the influence of climate and sea level changes on the South Adriatic shelf (Mediterranean Sea) - Maselli, V.; Trincardi, F.; Asioli, A.; Ceregato, A.; Rizzetto, F.; Taviani, M. (Quaternary Science Reviews, 2014)
Incised valleys across continental margins represent the response of fluvial systems to changes in their equilibrium dynamics, mainly driven by base level fall forced by glacial–eustatic cycles. The Manfredonia Incised Valley formed during the last glacial sea level lowstand, when most of the southern Adriatic shelf was sub-aerially exposed but the outer shelf remained under water. The pronounced upstream deepening of the valley is ascribed to river incision of the MIS5e highstand coastal prism and related subaqueous clinoform under the influence of MIS5-4 sea level fluctuations, while the downstream shallowing and narrowing mainly reflects the impact of increased rates of sea level fall at the MIS3-2 transition on a flatter mid-outer shelf. Until 15 ka BP, the valley fed an asymmetric delta confined to the mid-outer shelf, testifying that continental and deep marine systems remained disconnected during the lowstand. Sea level rise reached the inner shelf during the Early Holocene, drowning the valley and leading to the formation of a sheltered embayment confined toward the land: at this time part of the incision remained underfilled with a marked bathymetric expression. This mini-basin was rapidly filled by sandy bayhead deltas, prograding from both the northern and southern sides of the valley. In this environment, protected by marine reworking and where sediment dispersal was less effective, the accommodation space was reduced and autogenic processes forced the formation of multiple and coalescing delta lobes. Bayhead delta progradations occurred in few centuries, between 8 and 7.2 ka cal BP, confirming the recent hypothesis that in this area the valley was filled during the formation of sapropel S1. This proximal valley fill, representing the very shallow-water equivalent of the cm-thick sapropel layers accumulated offshore in the deeper southern Adriatic basin, is of key importance in following the signature of the sapropel in a facies-tract ideally from the shoreline to the abyss.

Gas hydrate destabilization and methane release events in the Krishna–Godavari Basin, Bay of Bengal - Joshi, R. K.; Mazumdar, A.; Peketi, A.; Ramamurty, P. B.; Naik, B. G.; Kocherla, M.; Carvalho, Mary Ann; Mahalakshmi, P.; Dewangan, P.; Ramana, M. V. (Marine and Petroleum Geology, 2014)
Methane release events have been linked to global warming, alteration of the carbon cycle and influence on biota. However, unequivocal evidence of paleomethane release events are limited. We report several negative carbon stable isotope excursions in planktic and benthic foraminifera in a core (MD161-8) from the Krishna-Godavari (K–G) Basin, Bay of Bengal. The most negative δ13C spikes are recorded during the marine isotope stages MIS-4 and at the transition of MIS-5 to 4. Occurrence of highly 13C depleted (average δ13C = −48 ± 2.4‰ VPDB) authigenic high magnesian calcite are also reported within this time window from the core MD161-8. In the present work an unequivocal explanation for the observed 13C depletion in the marine planktic and benthic foraminifera is difficult to achieve solely from the optical/electron microscopy or C–O stable isotope ratio analyses due to possible influence of diagenetic alteration. We attribute the observed episodic methane expulsion events, as inferred from the negative δ13C excursions and earlier reports on the occurrence chemosynthetic bivalves and Mo concentration anomaly to the destabilization of the base of gas hydrate stability zone (BGHSZ). Sea level drop and shale tectonics induced focused fluid flow are the two possible causes of hydrate destabilization discussed here. Shale tectonics were possibly responsible for creating fault systems which acted as the conduit for gas flow through the sediment column and subsequent seepage. Shale and salt tectonics in the passive continental margins being a globally observed phenomenon, its role as an important driving force for enhanced methane emission needs detailed investigation to understand the climatic perturbations through geologic time. Additional evidence of methane emission from site MD161-15 further supports the link between shale tectonics and methane emission.
AAy4wyTimes Cited:2Cited References Count:97

A Geochemical Approach to Determine Sources and Movement of Saline Groundwater in a Coastal Aquifer - Anders, Robert; Mendez, Gregory O.; Futa, Kiyoto; Danskin, Wesley R. (Groundwater, 2014)
Geochemical evaluation of the sources and movement of saline groundwater in coastal aquifers can aid in the initial mapping of the subsurface when geological information is unavailable. Chloride concentrations of groundwater in a coastal aquifer near San Diego, California, range from about 57 to 39,400 mg/L. On the basis of relative proportions of major-ions, the chemical composition is classified as Na-Ca-Cl-SO4, Na-Cl, or Na-Ca-Cl type water. ?2H and ?18O values range from ?47.7? to ?12.8? and from ?7.0? to ?1.2?, respectively. The isotopically depleted groundwater occurs in the deeper part of the coastal aquifer, and the isotopically enriched groundwater occurs in zones of sea water intrusion. 87Sr/86Sr ratios range from about 0.7050 to 0.7090, and differ between shallower and deeper flow paths in the coastal aquifer. 3H and 14C analyses indicate that most of the groundwater was recharged many thousands of years ago. The analysis of multiple chemical and isotopic tracers indicates that the sources and movement of saline groundwater in the San Diego coastal aquifer are dominated by: (1) recharge of local precipitation in relatively shallow parts of the flow system; (2) regional flow of recharge of higher-elevation precipitation along deep flow paths that freshen a previously saline aquifer; and (3) intrusion of sea water that entered the aquifer primarily during premodern times. Two northwest-to-southeast trending sections show the spatial distribution of the different geochemical groups and suggest the subsurface in the coastal aquifer can be separated into two predominant hydrostratigraphic layers.

Holocene earthquakes and right-lateral slip on the left-lateral Darrington-Devils Mountain fault zone, northern Puget Sound, Washington - Personius, S. F.; Briggs, R. W.; Nelson, A. R.; Schermer, E. R.; Maharrey, J. Z.; Sherrod, B. L.; Spaulding, S. A.; Bradley, L.-A. (Geosphere, 2014)
Sources of seismic hazard in the Puget Sound region of northwestern Washington include deep earthquakes associated with the Cascadia subduction zone, and shallow earthquakes associated with some of the numerous crustal (upper-plate) faults that crisscross the region. Our paleoseismic investigations on one of the more prominent crustal faults, the Darrington–Devils Mountain fault zone, included trenching of fault scarps developed on latest Pleistocene glacial sediments and analysis of cores from an adjacent wetland near Lake Creek, 14 km southeast of Mount Vernon, Washington. Trench excavations revealed evidence of a single earthquake, radiocarbon dated to ca. 2 ka, but extensive burrowing and root mixing of sediments within 50–100 cm of the ground surface may have destroyed evidence of other earthquakes. Cores in a small wetland adjacent to our trench site provided stratigraphic evidence (formation of a laterally extensive, prograding wedge of hillslope colluvium) of an earthquake ca. 2 ka, which we interpret to be the same earthquake documented in the trenches. A similar colluvial wedge lower in the wetland section provides possible evidence for a second earthquake dated to ca. 8 ka. Three-dimensional trenching techniques revealed evidence for 2.2 ± 1.1 m of right-lateral offset of a glacial outwash channel margin, and 45–70 cm of north-side-up vertical separation across the fault zone. These offsets indicate a net slip vector of 2.3 ± 1.1 m, plunging 14° west on a 286°-striking, 90°-dipping fault plane. The dominant right-lateral sense of slip is supported by the presence of numerous Riedel R shears preserved in two of our trenches, and probable right-lateral offset of a distinctive bedrock fault zone in a third trench. Holocene north-side-up, right-lateral oblique slip is opposite the south-side-up, left-lateral oblique sense of slip inferred from geologic mapping of Eocene and older rocks along the fault zone. The cause of this slip reversal is unknown but may be related to clockwise rotation of the Darrington–Devils Mountain fault zone into a position more favorable to right-lateral slip in the modern N-S compressional stress field.

Holocene Indian Ocean tsunami history in Sri Lanka - Jackson, Kelly L.; Eberli, Gregor P.; Amelung, Falk; McFadden, Melany A.; Moore, Andrew L.; Rankey, Eugene C.; Jayasena, H. A. H. (Geology, 2014)
Sediment cores from Karagan Lagoon in southeastern Sri Lanka retrieved deposits from the A.D. 2004 Indian Ocean tsunami and older similar deposits that provide evidence for a tsunami 2417 +/- 152 cal. (calendar) yr B.P. to 2925 +/- 98 cal. yr B.P., and for six tsunamis between 4064 +/- 128 cal. yr B.P. and 6665 +/- 110 cal. yr B.P., a period for which the sediment record appears continuous. Radiocarbon dating indicates that the recurrence interval is variable, ranging from 181-517 yr to 1045 +/- 334 yr, with a mean recurrence interval of 434 +/- 40 yr during the ca. 4000-7000 cal. yr B.P. continuous interval. Assuming that these tsunamis were generated by giant earthquakes along the Sumatra-Andaman subduction zone, a reasonable assumption for this far-field transoceanic location, this record extends the giant-earthquake history for the Indian Ocean region. The longest recurrence interval of more than 1000 yr implies that earthquakes along the subduction zone may reach twice the size of the 2004 earthquake.

Holocene sea-surface temperature variability in the Chilean fjord region - Caniupán, Magaly; Lamy, Frank; Lange, Carina B.; Kaiser, Jérôme; Kilian, Rolf; Arz, Helge W.; León, Tania; Mollenhauer, Gesine; Sandoval, Susana; De Pol-Holz, Ricardo; Pantoja, Silvio; Wellner, Julia; et al. (Quaternary Research, 2014)
Here we provide three new Holocene (11–0 cal ka BP) alkenone-derived sea surface temperature (SST) records from the southernmost Chilean fjord region (50–53°S). SST estimates may be biased towards summer temperature in this region, as revealed by a large set of surface sediments. The Holocene records show consistently warmer than present-day SSTs except for the past ~ 0.6 cal ka BP. However, they do not exhibit an early Holocene temperature optimum as registered further north off Chile and in Antarctica. This may have resulted from a combination of factors including decreased inflow of warmer open marine waters due to lower sea-level stands, enhanced advection of colder and fresher inner fjord waters, and stronger westerly winds. During the mid-Holocene, pronounced short-term variations of up to 2.5°C and a cooling centered at ~ 5 cal ka BP, which coincides with the first Neoglacial glacier advance in the Southern Andes, are recorded. The latest Holocene is characterized by two pronounced cold events centered at ~ 0.6 and 0.25 cal ka BP, i.e., during the Little Ice Age. These cold events have lower amplitudes in the offshore records, suggesting an amplification of the SST signal in the inner fjords.

Indonesian vegetation response to changes in rainfall seasonality over the past 25,000 years - Dubois, Nathalie; Oppo, Delia W.; Galy, Valier V.; Mohtadi, Mahyar; van der Kaars, Sander; Tierney, Jessica E.; Rosenthal, Yair; Eglinton, Timothy I.; L?ckge, Andreas; Linsley, Braddock K. (Nature Geoscience, 2014)
The hydrologic response to climate forcing in the Indo-Pacific warm pool region has varied spatially over the past 25,000 years1, 2, 3, 4, 5. For example, drier conditions are inferred on Java and Borneo for the period following the end of the Last Glacial Maximum, whereas wetter conditions are reconstructed for northwest Australia4. The response of vegetation to these past rainfall variations is poorly constrained. Using a suite of 30 surface marine sediment samples from throughout the Indo-Pacific warm pool, we demonstrate that today the stable isotopic composition of vascular plant fatty acids (δ13Cfa) reflects the regional vegetation composition. This in turn is controlled by the seasonality of rainfall consistent with dry season water stress6. Applying this proxy in a sediment core from offshore northeast Borneo, we show broadly similar vegetation cover during the Last Glacial Maximum and the Holocene, suggesting that, despite generally drier glacial conditions1, 7, there was no pronounced dry season. In contrast, δ13Cfa and pollen data from a core off the coast of Sumba indicate an expansion of C4 herbs during the most recent glaciation, implying enhanced aridity and water stress during the dry season. Holocene vegetation trends are also consistent with a response to dry season water stress. We therefore conclude that vegetation in tropical monsoon regions is susceptible to increases in water stress arising from an enhanced seasonality of rainfall, as has occurred8 in past decades.
Keywords: Palaeoclimate; Palaeoecology

Inferring local to regional changes in forest composition from Holocene macrofossils and pollen of a small lake in central Upper Michigan - Jackson, Stephen T.; Booth, Robert K.; Reeves, Kelly; Andersen, Jennifer Jewell; Minckley, Thomas A.; Jones, Rachel A. (Quaternary Science Reviews, 2014)
Vegetational response to climatic change involves processes of population and community dynamics within local stands, which scale up to landscape-level changes in vegetation composition and broad-scale changes in species distributions. Understanding these dynamics poses a critical challenge to paleoecological explanation, because of the broad range of scales at which these dynamics take place and interact. We present an 8600-year paleoecological record of local and regional changes in forest composition from a small (2.6 ha) lake in central Upper Michigan. Plant macrofossils provide a spatially precise record of local forest composition, while pollen data provide a spatially integrated record of regional vegetational changes. Temporal patterns among different macrofossil types within species show overall coherence, indicating that changes in macrofossil abundance generally record changes in local tree abundance. Temporal patterns in macrofossil sequences correspond to patterns in pollen sequences, indicating that local changes contributed to the large-scale changes in the surrounding region. The pollen and macrofossil records show nearly continuous turnover in vegetation composition throughout the past 8600 years; the longest period without major compositional change was ca 1600 years, and dynamics at multidecadal to multicentennial scales are observed during many periods. Coordinated application of temporally precise sequences of pollen and macrofossil data at multiple sites can support inferences concerning vegetation dynamics at multiple spatial and temporal scales, and test mechanistic hypotheses.

An investigation of size-fractionated organic matter from Lake Superior and a tributary stream using radiocarbon, stable isotopes and NMR - Zigah, Prosper K.; Minor, Elizabeth C.; Abdulla, Hussain A. N.; Werne, Josef P.; Hatcher, Patrick G. (Geochimica et Cosmochimica Acta, 2014)
This study investigated the concentration and isotopic composition of different size fractions of organic matter (OM) in Lake Superior and in one of its many tributary streams and rivers (Amity Creek, Duluth, Minnesota, USA). Structural compositional drivers of the Δ14C of high molecular weight (HMW, >1 kDa) dissolved organic carbon (DOC) in the lake were also evaluated. Low molecular weight (LMW, 0.7 μm) was generally 13C-depleted (−29 ± 1.2‰) relative to “bulk” (<0.7 μm) DOC (−26.4 ± 0.7‰), “init” (<0.2 μm) DOC (−26.6 ± 0.8‰), HMW DOC (−26.9 ± 0.3‰) and LMW DOC (−26.5 ± 0.9‰), and had more variable 14C content (Δ14C of −94‰ to 53‰; 735 years BP to modern) than the other size fractions. Init DOC (Δ14C of 17–59‰), HMW DOC (Δ14C of 23–64‰) and LMW DOC (Δ14C of 16–62‰) all reflected contemporary (modern) radiocarbon signatures. Bulk DOC (Δ14C of −19‰ to 57‰; 90 years BP to modern) had modern radiocarbon values in the offshore sites (Δ14C of 2–57‰) with pre-aged samples (Δ14C of −8‰ to −19‰) seen at the nearshore site. HMW DOM was relatively N-poor (C:N of 12–19) compared to particulate organic matter (POM, C:N of 8–10) revealing either a more diagenetically altered state or contrasting sources. 13C NMR data showed that biochemical composition of HMW DOC in Lake Superior was dominated by carbohydrates (53–65%) with only trace aromatic components (2–4%). Structurally complex components such as heteropolysaccharides (HPS), amide/peptides and amino sugars (AMS) constitute 75–84% of HMW DOC whereas carboxylic-rich alicyclic molecules (CRAM) made up 16–25% of HMW DOC in the lake. Combined HPS and AMS, O-alkyl carbohydrate carbon, and total carbohydrate carbon contents were significantly positively correlated to the Δ14C of HMW DOC suggesting they contribute a contemporary 14C-enriched component to the HMW DOC in the lake. In contrast, CRAM and aliphatic carbons were significantly inversely correlated with Δ14C of HMW DOC implying that these represent 14C-depleted (older) components of HMW DOC in the lake. At Amity Creek, storm events led to larger loads of bulk DOC and POC, which were both 14C-enriched (modern). However, in baseflow conditions 14C-depleted bulk DOC and POC were exported. LMW DOC from the creek was considerably 14C-depleted compared to concurrent HMW DOC.

An investigation of size-fractionated organic matter from Lake Superior and a tributary stream using radiocarbon, stable isotopes and NMR - Zigah, Prosper K.; Minor, Elizabeth C.; Abdulla, Hussain A.N.; Werne, Josef P.; Hatcher, Patrick G. (Geochimica et Cosmochimica Acta, 2014)

Late Holocene marine transgression and the drowning of a coastal forest: Lessons from the past, Cape Cod, Massachusetts, USA - Maio, Christopher V.; Gontz, Allen M.; Weidman, Christopher R.; Donnelly, Jeffrey P. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2014)
Extra-tropical storms in the spring of 2010 swept the New England coastline resulting in significant erosion along South Cape Beach, a barrier system located on Cape Cod, Massachusetts. The erosion revealed 111 subfossil stumps and a preserved peat outcrop. We hypothesize that the stumps represent an ancient Eastern Red cedar, Juniperus virginiana, stand growing in a back-barrier environment and drowned by episodic storm events and moderate rates of sea-level rise. Stumps, bivalves, and organic sediments, were radiocarbon dated using traditional and continuous-flow Atomic Mass Spectroscopy methods. Six sediment cores elucidated subsurface stratigraphy and environmental setting. Subfossil stumps ranged in age from 413 ± 80 to 1239 ± 53 calibrated years before present. We assume that this age represents the time at which the ancient trees were drowned by marine waters. Based on elevation and age, an 826 year rate of submergence was calculated at 0.73 mm/yr with an R2 value of 0.47. Core stratigraphy, microfossil assemblages, and radiocarbon ages indicate a dynamic barrier environment with frequent overwash and breaching events occurring during the past 500 years. Shoreline change analysis showed that between 1846 and 2008, the shoreline retreated landward by 70 m at a long-term rate of 0.43 m/yr. Future increases in the rate of sea-level rise, coupled with episodic storm events, will lead to the destruction of terrestrial environments at rate orders of magnitude greater than that during the time of the paleoforest.

Late Holocene sedimentation in a high Arctic coastal setting: Simpson Lagoon and Colville Delta, Alaska - Hanna, Andrea J. M.; Allison, Mead A.; Bianchi, Thomas S.; Marcantonio, Franco; Goff, John A. (Continental Shelf Research, 2014)
Arctic coastal environments near major river outfalls, like Simpson Lagoon, Alaska and the adjacent Colville River Delta, potentially contain high-resolution sediment records useful in elucidating late Holocene Arctic sediment transport pathways and coupled terrestrial-ocean evidence of paleoclimate variability. This study utilizes a multi-tracer geochronology approach (137Cs, 239,240Pu, and 14C) tailored for high-latitude environments to determine the age models for cores collected from Simpson Lagoon, and to date seismic boundaries in shallow acoustic reflection data (CHIRP) to examine late Holocene infill patterns. Modern (~100 y) sediment accumulation rates range from 5 m of late Holocene interbedded sediments, likely derived primarily from the Colville River, with onset of accumulation occurring prior to ~3500 y BP. A paleo-high in central Simpson Lagoon, separating the two depocenters, was subaerially exposed prior to ~600 y BP. The millimeters-per-year sedimentation rates across the lagoon, coupled with the undisturbed, interbedded sediment record, indicate that these settings hold great potential to develop new Arctic paleoenvironmental records.

The late Quaternary environmental evolution of marine Arctic Canada: Barrow Strait to Lancaster Sound - Pieńkowski, Anna J.; England, John H.; Furze, Mark F. A.; MacLean, Brian; Blasco, Steve (Quaternary Science Reviews, 2014)
A marine sediment core from the east-central Canadian Arctic Archipelago (Core 86027-154; 74° 22.01′N 89° 51.26′W; 329 m water depth), studied by a multiproxy approach [lithostratigraphy, biogeochemistry, micropalaeontology (dinoflagellate cysts, other non-pollen palynomorphs, benthic and planktonic foraminifera, ostracods)], and encompassing 14 AMS 14C dates, provides valuable insights into regional deglacial to Holocene palaeoenvironments. Six palaeoenvironmental zones are recognized, based on prominent changes in the litho- and biostratigraphy. The waterlain diamicton of Zone I records immediate deglaciation, being derived from lift-off and calving of previously grounded glacial ice. Though deglacial timing is complicated by the sparsity of dating materials and the Portlandia Effect, age–depth model extrapolation places deglaciation at 11.54 cal ka BP. Zone II (11.5–11.0 cal ka BP) represents a distinct progression from initially ice-proximal to increasingly ice-distal conditions, interrupted by an interval of pervasive sea-ice (11.4–11.2 cal ka BP). Noteworthy biological activity commences in Zone III (11.0–9.7 cal ka BP) with a prominent signal of planktonic foraminifera (Neogloboquadrina pachyderma). This likely signifies penetration of deeper, Atlantic-derived water through the central Canadian Arctic Archipelago upon deglaciation, facilitated by the greater, glacioisostatically-induced water depths (+80 m), and implies separation of Laurentide and Innuitian ice sheets by ∼11.0 cal ka BP. Zone IV (9.7–7.2 cal ka BP) records ameliorated, biologically favourable conditions with reduced seasonal sea-ice accompanied by high microfossil species diversity and the presence of subpolar taxa. Zone V (7.2–6.5 cal ka BP) signals the exclusion of Atlantic-derived water, concomitant with increasing sea-ice, simultaneously representing the termination of the dynamic deglacial to early Holocene environments (zones I–IV). Conditions similar to modern typified by uniform sediment characteristics, present-day microfossil assemblage structures, and sparse benthic foraminifera were established by 5.6 cal ka BP (Zone VI).

Late Quaternary sedimentary record and Holocene channel avulsions of the Jamuna and Old Brahmaputra River valleys in the upper Bengal delta plain - Pickering, Jennifer L.; Goodbred, Steven L.; Reitz, Meredith D.; Hartzog, Thomas R.; Mondal, Dhiman R.; Hossain, Md Saddam (Tropical Rivers of South and South-east Asia: Landscape evolution, morphodynamics and hazards, 2014)
The first Holocene stratigraphic record of river-channel occupation and switching between the Brahmaputra–Jamuna and Old Brahmaputra paleovalleys is presented here. Motivated by the Brahmaputra River's historic avulsion from the Old Brahmaputra channel to its present-day Jamuna course, we have obtained sediment and radiocarbon samples from 41 boreholes along a 120 km transect crossing these two braided-river valleys. The stratigraphy along this transect reveals sand-dominated Holocene channel systems, each bound by remnant, mud-capped Pleistocene stratigraphy. Using sediment lithology and bulk strontium concentration as a provenance indicator, we define the geometry and channel-occupation history of each paleovalley. The western Brahmaputra–Jamuna valley is broad and somewhat deeper compared with the Old Brahmaputra valley, the latter actually comprising a composite of two narrower sub-valleys bifurcated by an antecedent topographic remnant. The gently sloped valley margins (slope: 0.002 to 0.007) and high width-to-thickness ratio (W/T: ~ 1000) of the Brahmaputra–Jamuna valley suggest that it was filled primarily through lateral channel migration and the reworking of braidbelt and overbank deposits. Conversely, the two Old Brahmaputra sub-valleys have comparatively steeper valley margins (slope: 0.007 to 0.022) and lower width-to-thickness ratios (W/T: ~ 125 and ~ 250), indicating that these were filled primarily through vertical aggradation of channel sands. We attribute this disparity in valley geometry and fill processes to the different occupation histories for each valley. In this case, the much larger Brahmaputra–Jamuna valley represents the principal, if not singular, river course during the last lowstand of sea-level, with a prominent gravel lag underlying the valley. In contrast the smaller Old Brahmaputra valleys do not appear to have been present, or at least well developed, at the last lowstand. Rather these courses were first occupied during the early Holocene transgression, and we infer that the river had been previously excluded from this region by the relatively higher elevation between the Madhupur Terrace and the Shillong Massif. We also demonstrate that the Brahmaputra River experienced 3–4 major avulsions during the Holocene, with considerably longer occupation times within the principal Brahmaputra–Jamuna valley. Together these observations indicate that occupation history and antecedent topography have been important controls on river course mobility and avulsion behavior.

Microbial biomarkers support organic carbon transport from methane-rich Amazon wetlands to the shelf and deep sea fan during recent and glacial climate conditions - Wagner, Thomas; Kallweit, Wiebke; Talbot, Helen M.; Mollenhauer, Gesine; Boom, Arnoud; Zabel, Matthias (Organic Geochemistry, 2014)
We have investigated the delivery of terrestrial organic carbon (OC) to the Amazon shelf and deep sea fan based on soil marker bacteriohopanepolyols (BHPs; adenosylhopane and related compounds) and branched glycerol dialkyl glycerol tetraethers (GDGTs), as well as on 14C dating of bulk organic matter. The microbial biomarker records show persistent burial of terrestrial OC, evidenced by almost constant and high BIT values (0.6) and soil marker BHP concentration [80–230 μg/g TOC (total OC)] on the late Holocene shelf and even higher BIT values (0.8–0.9), but lower and more variable soil-marker BHP concentration (40–100 μg/g TOC), on the past glacial deep sea fan. Radiocarbon data show that OC on the shelf is 3–4 kyr older than corresponding bivalve shells, emphasizing the presence of old carbon in this setting. We observe comparable and unexpectedly invariant BHP composition in both marine sediment records, with a remarkably high relative abundance of C-35 amino BHPs including compounds specific for aerobic methane oxidation on the shelf (avg. 50% of all BHPs) and the fan (avg. 40%). Notably, these marine BHP signatures are strikingly similar to those of a methane-producing floodplain area in one of the Amazonian wetland (várzea) regions. The observation indicates that BHPs in the marine sediments may have initially been produced within wetland regions of the Amazon basin and may therefore document persistent export from terrestrial wetland regions, with subsequent re-working in the marine environment, both during recent and past glacial climate conditions.

Mid- to Late-Holocene Australian–Indonesian summer monsoon variability - Steinke, Stephan; Mohtadi, Mahyar; Prange, Matthias; Varma, Vidya; Pittauerova, Daniela; Fischer, Helmut W. (Quaternary Science Reviews, 2014)
The Australian–Indonesian monsoon has a governing influence on the agricultural practices and livelihood in the highly populated islands of Indonesia. However, little is known about the factors that have influenced past monsoon activity in southern Indonesia. Here, we present a ∼6000 years high-resolution record of Australian-Indonesian summer monsoon (AISM) rainfall variations based on bulk sediment element analysis in a sediment archive retrieved offshore northwest Sumba Island (Indonesia). The record suggests lower riverine detrital supply and hence weaker AISM rainfall between 6000 yr BP and ∼3000 yr BP compared to the Late Holocene. We find a distinct shift in terrigenous sediment supply at around 2800 yr BP indicating a reorganization of the AISM from a drier Mid Holocene to a wetter Late Holocene in southern Indonesia. The abrupt increase in rainfall at around 2800 yr BP coincides with a grand solar minimum. An increase in southern Indonesian rainfall in response to a solar minimum is consistent with climate model simulations that provide a possible explanation of the underlying mechanism responsible for the monsoonal shift. We conclude that variations in solar activity play a significant role in monsoonal rainfall variability at multi-decadal and longer timescales. The combined effect of orbital and solar forcing explains important details in the temporal evolution of AISM rainfall during the last 6000 years. By contrast, we find neither evidence for volcanic forcing of AISM variability nor for a control by long-term variations in the El Niño-Southern Oscillation (ENSO).

North Atlantic forcing of tropical Indian Ocean climate - Mohtadi, Mahyar; Prange, Matthias; Oppo, Delia W.; De Pol-Holz, Ricardo; Merkel, Ute; Zhang, Xiao; Steinke, Stephan; ückge, Andreas (Nature, 2014)
The response of the tropical climate in the Indian Ocean realm to abrupt climate change events in the North Atlantic Ocean is contentious. Repositioning of the intertropical convergence zone is thought to have been responsible for changes in tropical hydroclimate during North Atlantic cold spells1, 2, 3, 4, 5, but the dearth of high-resolution records outside the monsoon realm in the Indian Ocean precludes a full understanding of this remote relationship and its underlying mechanisms. Here we show that slowdowns of the Atlantic meridional overturning circulation during Heinrich stadials and the Younger Dryas stadial affected the tropical Indian Ocean hydroclimate through changes to the Hadley circulation including a southward shift in the rising branch (the intertropical convergence zone) and an overall weakening over the southern Indian Ocean. Our results are based on new, high-resolution sea surface temperature and seawater oxygen isotope records of well-dated sedimentary archives from the tropical eastern Indian Ocean for the past 45,000 years, combined with climate model simulations of Atlantic circulation slowdown under Marine Isotope Stages 2 and 3 boundary conditions. Similar conditions in the east and west of the basin rule out a zonal dipole structure as the dominant forcing of the tropical Indian Ocean hydroclimate of millennial-scale events. Results from our simulations and proxy data suggest dry conditions in the northern Indian Ocean realm and wet and warm conditions in the southern realm during North Atlantic cold spells.
Keywords: Palaeoceanography; Palaeoclimate

Particle sorting during sediment redistribution processes and the effect on 230 Th-normalized mass accumulation rates - Marcantonio, Franco; Lyle, Mitchell; Ibrahim, Rami (Geophysical Research Letters, 2014)
The 230Th method of determining mass accumulation rates (MARs) assumes that little to no fractionation occurs during sediment redistribution processes at the seafloor. We examine 230Th inventories in radiocarbon-dated multicore sediments from paired winnowed and focused sites at Cocos and Carnegie Ridges, Panama Basin. Radiocarbon-derived sand MARs, which likely represent the vertical rain of particles poorly transported by bottom currents, are similar at each of the paired sites but are different using 230Th normalization. 230Th-normalized MARs are about 60% lower at focused sites and likely underestimate vertical MARs, while the reverse is true for winnowed sites. We hypothesize that size fractionation occurs most frequently at lower current velocities, resulting in the coarse fraction being left behind and primarily the fine 230Th-rich grains being transported downslope. 230Th-normalization works well for recording fine-grained (detrital and opal), but not coarse-grained (carbonate), fluxes in regions that have undergone sediment redistribution.

Phylogeny and phylogeography of functional genes shared among seven terrestrial subsurface metagenomes reveal N-cycling and microbial evolutionary relationships - Lau, Maggie C. Y.; Cameron, Connor; Magnabosco, Cara; Brown, C. Titus; Schilkey, Faye; Grim, Sharon; Hendrickson, Sarah; Pullin, Michael; Lollar, Barbara Sherwood; Van Heerden, Esta; Kieft, Thomas L.; Onstott, Tullis C. (FRONTIERS IN MICROBIOLOGY, 2014)
Comparative studies on community phylogenetics and phylogeography of microorganisms living in extreme environments are rare. Terrestrial subsurface habitats are valuable for studying microbial biogeographical patterns due to their isolation and the restricted dispersal mechanisms. Since the taxonomic identity of a microorganism does not always correspond well with its functional role in a particular community, the use of taxonomic assignments or patterns may give limited inference on how microbial functions are affected by historical, geographical and environmental factors. With seven metagenomic libraries generated from fracture water samples collected from five South African mines, this study was carried out to (1) screen for ubiquitous functions or pathways of biogeochemical cycling of CH4, S, and N; (2) to characterize the biodiversity represented by the common functional genes; (3) to investigate the subsurface biogeography as revealed by this subset of genes; and (4) to explore the possibility of using metagenomic data for evolutionary study. The ubiquitous functional genes are NarV, NPD, PAPS reductase, NifH, NifD, NifK, NifE, and NifN genes. Although these eight common functional genes were taxonomically and phylogenetically diverse and distinct from each other, the dissimilarity between samples did not correlate strongly with geographical or environmental parameters or residence time of the water. Por genes homologous to those of Thermodesulfovibrio yellowstonii detected in all metagenomes were deep lineages of Nitrospirae, suggesting that subsurface habitats have preserved ancestral genetic signatures that inform the study of the origin and evolution of prokaryotes.
Keywords: evolution; functional genes; N-cycle; phylogenetics; phylogeny; phylogeography; terrestrial subsurface

Pore-water chemistry of sediment cores off Mahanadi Basin, Bay of Bengal: Possible link to deep seated methane hydrate deposit - Mazumdar, A.; Peketi, A.; Joao, H. M.; Dewangan, P.; Ramprasad, T. (Marine and Petroleum Geology, 2014)
Organoclastic degradation and anaerobic oxidation of methane (AOM) are known to influence sulfate, methane and bicarbonate concentrations of sediment pore-waters. In this work we have analyzed the pore-fluid composition of three piston cores (36–39 m long) collected from water depths ranging from 1429 to 1691 m. We attribute the observed linear sulfate concentration profiles and (ΔCa + ΔAlk)/ΔSO42− ratios dominantly to anaerobic oxidation of methane (AOM) induced sulfate consumption. The gas rich layers just below the base of hydrate stability zone (BGHSZ) is the possible source of the enhanced diffusive flux of biogenic methane ( δ 13 C CH 4 ranging from −99.7 to −106.3‰ VPDB). Occurrences of disseminated gas hydrate in the Mahanadi Basin within the hydrate stability zone (210–220 m thick) supports the link between linear sulfate profile, high rate of AOM and hydrate occurrence.

Pre-aged plant waxes in tropical lake sediments and their influence on the chronology of molecular paleoclimate proxy records - Douglas, Peter M. J.; Pagani, Mark; Eglinton, Tim E.; Brenner, Mark; Hodell, David A.; Curtis, Jason H.; Ma, Keith; Breckenridge, Andy (Geochimica et Cosmochimica Acta, 2014)
Sedimentary records of plant-wax hydrogen (δDwax) and carbon (δ13Cwax) stable isotopes are increasingly applied to infer past climate change. Compound-specific radiocarbon analyses, however, indicate that long time lags can occur between the synthesis of plant waxes and their subsequent deposition in marginal marine sediments. The influence of these time lags on interpretations of plant-wax stable isotope records is presently unconstrained, and it is unclear whether such time lags also affect lacustrine sediments. We present compound-specific radiocarbon (14Cwax) data for n-alkanoic acid plant waxes (n-C26 to n-C30) from: 1) a sediment core from Lake Chichancanab, Yucatan Peninsula, Mexico, 2) soils in the Lake Chichancanab catchment, and 3) surface sediments from three other lakes in southeastern Mexico and northern Guatemala. 14Cwax ages in the surface sediments are consistently older than modern, and may be negatively correlated with mean annual precipitation and positively correlated with lake catchment area. 14Cwax ages in soils surrounding Lake Chichancanab increase with soil depth, consistent with deep, subsoil horizons being the primary source of lacustrine aged plant waxes, which are likely delivered to lake sediments through subsurface transport. Plant waxes in the Lake Chichancanab core are 350 to 1200 years older than corresponding ages of bulk sediment deposition, determined by 14C dates on terrestrial plant macrofossils in the core. A δDwax time series is in closer agreement with other regional proxy hydroclimate records when a plant-wax 14C age model is applied, as opposed to the macrofossil-based core chronology. Inverse modeling of plant-wax age distribution parameters suggests that plant waxes in the Lake Chichancanab sediment core derive predominantly from millennial-age soil carbon pools that exhibit relatively little age variance (< 200 years). Our findings demonstrate that high-temporal-resolution climate records inferred from stable isotope measures on plant waxes in lacustrine sediments may suffer from possible chronologic distortions as a consequence of long residence times of plant waxes in soils. They also underscore the importance of direct radiocarbon dating of these organic molecules.

Radiocarbon age-offsets in an arctic lake reveal the long-term response of permafrost carbon to climate change - Gaglioti, Benjamin V.; Mann, Daniel H.; Jones, Benjamin M.; Pohlman, John W.; Kunz, Michael L.; Wooller, Matthew J. (JOURNAL OF GEOPHYSICAL RESEARCH-BIOGEOSCIENCES, 2014)
Continued warming of the Arctic may cause permafrost to thaw and speed the decomposition of large stores of soil organic carbon (OC), thereby accentuating global warming. However, it is unclear if recent warming has raised the current rates of permafrost OC release to anomalous levels or to what extent soil carbon release is sensitive to climate forcing. Here we use a time series of radiocarbon age-offsets (C-14) between the bulk lake sediment and plant macrofossils deposited in an arctic lake as an archive for soil and permafrost OC release over the last 14,500 years. The lake traps and archives OC imported from the watershed and allows us to test whether prior warming events stimulated old carbon release and heightened age-offsets. Today, the age-offset (2ka; thousand of calibrated years before A.D. 1950) and the depositional rate of ancient OC from the watershed into the lake are relatively low and similar to those during the Younger Dryas cold interval (occurring 12.9-11.7ka). In contrast, age-offsets were higher (3.0-5.0ka) when summer air temperatures were warmer than present during the Holocene Thermal Maximum (11.7-9.0ka) and BOlling-AllerOd periods (14.5-12.9ka). During these warm times, permafrost thaw contributed to ancient OC depositional rates that were similar to 10 times greater than today. Although permafrost OC was vulnerable to climate warming in the past, we suggest surface soil organic horizons and peat are presently limiting summer thaw and carbon release. As a result, the temperature threshold to trigger widespread permafrost OC release is higher than during previous warming events.
Keywords: carbon cycling; lake sediment; paleoclimatology; permafrost; radiocarbon; Younger Dryas

Radiocarbon dating of planktonic foraminifer shells: A cautionary tale - Mekik, Figen (PALEOCEANOGRAPHY, 2014)
Sedimentation rate, bioturbation, winnowing, and calcite dissolution produce significant radiocarbon age offsets among multiple species of coexisting planktonic foraminifers and pteropod fragments. We compare the radiocarbon age of foraminifer species and pteropod fragments with estimates of percent calcite dissolved made with a sedimentary proxy (Globorotalia menardii fragmentation index-MFI) to delineate the effect of dissolution on radiocarbon age of foraminifers. Data from two core top transects on the Rio Grande Rise (RIO) and Ontong Java Plateau (OJP) and from down core sediments of varying sedimentation rates in the tropical Pacific (ME-27, MD98 2177, and MW91-9 56GGC) reveal that sediments with the greatest accumulation rates produce the least age offsets among coexisting species. Age offsets among coexisting foraminifers are about 3500 years on RIO, and 1000 years on OJP. Two core tops from RIO yield an age of the Last Glacial Maximum possibly due to mass displacement of younger sediments downslope. Foraminifer age increases with increasing dissolution and there is a consistent pattern of older foraminifer fragments coexisting with younger whole shells of the same species. The only exception is sediments which have experienced high dissolution where fragments are younger than whole shells. The age offset between fragments of G. menardii and its coexisting whole shells does not exceed the age offset among other coexisting foraminifer species in the same core tops.

Radiocarbon signatures and size–age–composition relationships of major organic matter pools within a unique California upwelling system - Walker, B. D.; Guilderson, T. P.; Okimura, K. M.; Peacock, M. B.; McCarthy, M. D. (Geochimica et Cosmochimica Acta, 2014)
Coastal upwelling zones are among the most productive regions in the world and play a major role in the global carbon cycle. Radiocarbon (as Δ14C) is a powerful tool for tracing the source and fate of suspended particulate and dissolved organic matter (POM, DOM), and has the potential to reconcile key carbon budgets within upwelling systems. However, the extent to which upwelling processes influence the Δ14C signature of surface DIC, or that of POM or DOM remains almost completely unknown. Here we present a time series of stable carbon (δ13C) and Δ14C isotopic data of major water column carbon pools, including dissolved inorganic carbon (DIC), large (0.7–500 μm) and small (0.1–100 μm) POM, and high molecular weight (HMW; ∼1 nm–0.1 μm) DOM from an upwelling center along the Big Sur coast. We show that DIC Δ14C values (ranging between +29‰ and −14‰) are strongly correlated to coastal upwelling processes, and that this 14C-signal readily propagates into both the POM and HMW DOM pool. However, the presence of negative POM and HMW DOM Δ14C values (ranging between +46‰ and −56‰, +6‰ and −123‰ and −1‰ and −150‰, respectively) suggests contributions of “pre-aged” OM, complicating the direct use of “bulk” Δ14C for tracing upwelling-derived carbon production/export. Using a triple-isotope mixing model (δ13C, δ15N, Δ14C) we estimate that 50–90% and 45–51% of large and small POM is newly-produced OM, while between 6–22% and 12–44% of large and small POM are derived from “pre-aged” re-suspended sediments. Finally, we observe quantitative relationships between OM size, composition (C:N ratio) and Δ14C within this upwelling system, possibly representing a new tool for modeling ocean C and N biogeochemical cycles.

Refining the link between the Holocene development of the Mississippi River Delta and the geologic evolution of Cat Island, MS: implications for delta-associated barrier islands - Miselis, Jennifer L.; Buster, Noreen A.; Kindinger, Jack L. (Marine Geology, 2014)
The geologic evolution of barrier islands is profoundly influenced by the nature of the deposits underlying them. Many researchers have speculated on the origin and evolution of Cat Island in Mississippi, but uncertainty remains about whether or not the island is underlain completely or in part by deposits associated with the past growth of the Mississippi River delta. In part, this is due to a lack of comprehensive geological information offshore of the island that could augment previous stratigraphic interpretations based on terrestrial borings. An extensive survey of Cat Island and its surrounding waters was conducted, including shallow-water geophysics (e.g., high-resolution chirp seismic, side-scan sonar, and swath and single-beam bathymetry) and both terrestrial and marine vibracoring. High-resolution seismic data and vibracores from south and east of the island show two horizontally laminated silt units; marine radiocarbon dates indicate that they are St. Bernard delta complex (SBDC) deposits. Furthermore, seismic data reveal that the SBDC deposits taper off toward the southern shoreline of Cat Island and to the west, morphology consistent with the distal edge of a delta complex. The sedimentology and extent of each unit suggest that the lower unit may have been deposited during an earlier period of continuous river flow while the upper unit may represent reduced or sporadic river flow. OSL dates from the island platform (beneath beach ridge complexes) indicate three stages of terrestrial evolution: island emergence resulting from relative sea-level rise (~ 5400 ybp) island aggradation via littoral transport (~ 2500–4000 ybp) and island degradation due to delta-mediated changes in wave direction (present– ~ 3600 ybp). Finally, the combination of terrestrial and marine data shows that portions of Cat Island that are lower in elevation than the central part of the island are younger and are likely underlain by a thin layer of deltaic sediments. This underscores the potential for increased future vulnerability of barrier islands that develop adjacent to major river delta complexes.

Seafloor fault ruptures along the North Anatolia Fault in the Marmara Sea, Turkey: Link with the adjacent basin turbidite record - McHugh, Cecilia M. G.; Braudy, Nicole; Çağatay, M. Namik; Sorlien, Christopher; Cormier, Marie-Helene; Seeber, Leonardo; Henry, Pierre (Marine Geology, 2014)
The relation between seafloor fault ruptures and the generation of turbidity currents was investigated to better understand the structural growth of tectonic basins with direct implications for earthquake hazard assessment. This study focuses on the Holocene earthquake record of transtensional basins in the Marmara Sea, Turkey, that are associated with the North Anatolian Fault system. The physical and chemical composition of three 10 m-long cores recovered from the Central Basin was studied at high-resolution and turbidite–homogenite units were identified. Turbidite–homogenite units (T–H units) are complex deposits that consist of a sharp basal contact and multiple fining upward beds of sand to coarse silt, above. All are capped by a 25 cm to 75 cm thick layer of medium to fine silt. A chronology developed from radiocarbon and short-lived radioisotopes allowed the correlation of these T–H units to the historical record of earthquakes that in Turkey goes back 2000 years. We found that the best location to recover the most complete sedimentation record is in the deepest part of a basin or “depocenter” where T–H units constitute ~ 80% of the sediments. A very good correlation was established between T–H units in Central Basin and proximal inferred historic epicentres along the central Marmara segment of the North Anatolia Fault that occurred in 1343, 860, 740, and 557 AD, and two more distal earthquakes that occurred in 268 and 1963 (or possibly1964). These sedimentation events can then be referred to as “seismo-turbidites”. The results when compared to findings from other transform basins in Marmara Sea reveal a very good correlation between T–H units and historic ruptures. Most importantly, there is a strong correlation between the inferred locations of historical earthquakes and the preservation of turbidite–homogenite units in the basin adjacent to the inferred rupture. The 740 AD earthquake correlates with T–H units in Izmit Gulf and Central Basin and could represent a multi-segment rupture of the NAF. Generally, T–H units appear to be clustered through the Holocene sections, suggesting temporal earthquake clustering in the Marmara Sea region. Such clustering may account for the lack of T–H units and hence large ruptures through the Central Basin since 1343.

Sedimentation patterns on a cold-water coral mound off Mauritania - Eisele, Markus; Frank, Norbert; Wienberg, Claudia; Titschack, Jürgen; Mienis, Furu; Beuck, Lydia; Tisnerat-Laborde, Nadine; Hebbeln, Dierk (Biology and Geology of Deep-Sea Coral Ecosystems: Proceedings of the Fifth International Symposium on Deep Sea Corals, 2014)
An unconformity-bound glacial sequence (135 cm thick) of a coral-bearing sediment core collected from the flank of a cold-water coral mound in the Banda Mound Province off Mauritania was analysed. In order to study the relation between coral framework growth and its filling by hemipelagic sediments, U-series dates obtained from the cold-water coral species Lophelia pertusa were compared to 14C dates of planktonic foraminifera of the surrounding matrix sediments. The coral ages, ranging from 45.1 to 32.3 ka BP, exhibit no clear depositional trend, while on the other hand the 14C dates of the matrix sediment provide ages within a much narrower time window of <3000 yrs (34.6–31.8 cal ka BP), corresponding to the latest phase of the coral growth period. In addition, high-resolution computer tomography data revealed a subdivision of the investigated sediment package into three distinct parts, defined by the portion and fragmentation of corals and associated macrofauna as well as in the density of the matrix sediments. Grain size spectra obtained on the matrix sediments show a homogeneous pattern throughout the core sediment package, with minor variations. These features are interpreted as indicators of redeposition. Based on the observed structures and the dating results, the sediments were interpreted as deposits of a mass wasting event, namely a debris flow. During this event, the sediment unit must have been entirely mixed; resulting in averaging of the foraminifera ages from the whole unit and giving randomly distributed coral ages. In this context, for the first time mass wasting is proposed to be a substantial process of mound progradation by exporting material from the mound top to the flanks. Hence, it may not only be an erosional feature but also widening the base of the mound, thus allowing further vertical mound growth.

Silicon isotopes indicate enhanced carbon export efficiency in the North Atlantic during deglaciation - Hendry, Katharine R.; Robinson, Laura F.; McManus, Jerry F.; Hays, James D. (Nature Communications, 2014)
Today’s Sargasso Sea is nutrient starved, except for episodic upwelling events caused by wind-driven winter mixing and eddies. Enhanced diatom opal burial in Sargasso Sea sediments indicates that silicic acid, a limiting nutrient today, may have been more available in subsurface waters during Heinrich Stadials, millennial-scale climate perturbations of the last glacial and deglaciation. Here we use the geochemistry of opal-forming organisms from different water depths to demonstrate changes in silicic acid supply and utilization during the most recent Heinrich Stadial. We suggest that during the early phase (17.5–18 ka), wind-driven upwelling replenished silicic acid to the subsurface, resulting in low Si utilization. By 17 ka, stratification reduced the surface silicic acid supply leading to increased Si utilization efficiency. This abrupt shift in Si cycling would have contributed to high regional carbon export efficiency during the recent Heinrich Stadial, despite being a period of increasing atmospheric CO2.
Keywords: Biogeochemistry; Cryospheric science; Ocean sciences

Submarine Paleoseismology Along Populated Transform Boundaries: The Enriquillo-Plantain-Garden Fault, Canal du Sud, Haiti, and the North Anatolian Fault, Marmara Sea, Turkey - McHugh, Cecilia M. G.; Seeber, Leonardo; Cormier, Marie-Helene; Hornbach, Matthew (OCEANOGRAPHY, 2014)
Continental transform boundaries cross heavily populated regions and are associated with destructive earthquakes worldwide. The devastating 1999 Turkey earthquakes and the offshore 2010 Haiti earthquake emphasized the urgent need to study the submerged segments of continental transforms. In response, the rapidly evolving field of submarine paleoseismology is focusing its attention on understanding the relationships between sedimentation, seafloor ruptures, and earthquake recurrence intervals along submarine faults. In Canal du Sud, Haiti, the 2010 earthquake-triggered sedimentation events were documented from nearshore to the deep basin by measuring the excess Th-234 in sediment cores. This radioisotope, with a half-life of 24 days, tracked mass wasting, turbidites, turbidite-homogenite units, and a sediment plume that remained in the water column for at least two months after the earthquake. However, the turbidite units in Canal du Sud, Haiti, provide an incomplete record of the region's earthquake history, likely because sedimentation rates are too low for sedimentation events to be triggered by all earthquakes. In contrast, in the Marmara Sea basins, there is very good correlation between turbidites and the historical record of earthquakes dating back 2,000 years. The difference between these correlations is likely related to both sedimentation rates and particulars of the ruptures. Future research along the Enriquillo-Plantain-Garden fault in Haiti and along similar low sedimentation plate boundaries should focus on multiple fault segments in order to obtain complete earthquake recurrence histories.

Subsurface Evidence of Storm-Driven Breaching along a Transgressing Barrier System, Cape Cod, USA - Maio, Christopher V.; Gontz, Allen M.; Sullivan, Richard M.; Madsen, Stephanie M.; Weidman, Christopher R.; Donnelly, Jeffrey P. (JOURNAL OF COASTAL RESEARCH, 2014)
Relict and historic tidal channels buried within coastal barriers provide a geologic signature of environmental change, thus enhancing our understanding of how barrier systems respond to extreme storm events. Earliest maps from 1846 depict three inlets along the Waquoit Bay barrier system located on Cape Cod, Massachusetts. These channels were not depicted on maps after 1846, and we lack any information pertaining to them before 1846. The principle objective of this study was to identify the location and map the internal geometry and channel-fill configuration of the buried inlet structures using geophysical and sedimentological data acquisition methods. This was done by collecting 6.2 km of shoreparallel ground-penetrating radar data and five sediment cores ranging in depth from 4 to 5 m. The sediment cores allowed for the ground truthing of the ground-penetrating radar data and provided six samples for radiocarbon dating. The 13 paleochannels identified ranged in depths from 1.3 to 3.7 m below the present beach surface. These appeared in the radar imagery as broad U-shaped cut-and-fill features incised into adjacent barrier facies. The 13 paleochannels composed 24% of the barrier lithosome totaling 704 m in length. Individual channels were primarily less than 65 m in length and between 2.5 and 1.3 m in depth, although an additional 275-m-wide, 3.7-m-deep channel sequence was imaged and likely represents a major and long-lived paleochannel. The results will contribute toward deciphering the evolution of the Waquoit system and identify areas vulnerable to storm-driven coastal change.
Keywords: coastal change; Coastal evolution; ground-penetrating radar; marine transgression; overwash; paleochannel; paleogeography; South Cape Beach

Temporal and spatial distributions of cold-water corals in the Drake Passage: Insights from the last 35,000 years - Margolin, Andrew R.; Robinson, Laura F.; Burke, Andrea; Waller, Rhian G.; Scanlon, Kathryn M.; Roberts, Mark L.; Auro, Maureen E.; van de Flierdt, Tina (Deep Sea Research Part II: Topical Studies in Oceanography, 2014)
Scleractinian corals have a global distribution ranging from shallow tropical seas to the depths of the Southern Ocean. Although this distribution is indicative of the corals having a tolerance to a wide spectrum of environmental conditions, individual species seem to be restricted to a much narrower range of ecosystem variables. One way to ascertain the tolerances of corals, with particular focus on the potential impacts of changing climate, is to reconstruct their growth history across a range of environmental regimes. This study examines the spatial and temporal distribution of the solitary scleractinian corals Desmophyllum dianthus, Gardineria antarctica, Balanophyllia malouinensis, Caryophyllia spp. and Flabellum spp. from five sites in the Drake Passage which cross the major frontal zones. A rapid reconnaissance radiocarbon method, cooupled with U-Th dating, extends the age range back more than 100 thousand. Within this age range there are distinct changes in the temporal and spatial distributions of these corals, both with depth and latitude, and on millennial timescales. Two major patterns that emerge are: 1) D. dianthus populations show clear variability in their occurrence through time depending on the latitudinal position within the Drake Passage. North of the Subantarctic Front, D. dianthus first appears in the late deglaciation (~17,000 years ago) and persists to today. South of the Polar Front, in contrast, populations existed during the glacial and early deglacial periods, with only few modern occurrences. A seamount site between the two fronts exhibits characteristics similar to both the north and south sites. This shift across the frontal zones within one species cannot yet be fully explained, but it is likely to be linked to changes in surface productivity, subsurface oxygen concentrations, and carbonate saturation state. 2) at locations where multiple genera were dated, clear differences in age and depth distribution of the populations provide clear evidence that each genus has unique environmental requirements to sustain its population.
id: 2278

Transfer of organic carbon through marine water columns to sediments - insights from stable and radiocarbon isotopes of lipid biomarkers - Wakeham, S. G.; McNichol, A. P. (Biogeosciences, 2014)
Compound-specific C-13 and C-14 compositions of diverse lipid biomarkers (fatty acids, alkenones, hydrocarbons, sterols and fatty alcohols) were measured in sinking particulate matter collected in sediment traps and from underlying surface sediments in the Black Sea, the Arabian Sea and the Ross Sea. The goal was to develop a multiparameter approach to constrain relative inputs of organic carbon (OC) from marine biomass, terrigenous vascular-plant and relict-kerogen sources. Using an isotope mass balance, we calculate that marine biomass in sediment trap material from the Black Sea and Arabian Sea accounted for 66-100% of OC, with lower terrigenous (3-8 %) and relict (4-16 %) contributions. Marine biomass in sediments constituted lower proportions of OC (66-90 %), with consequentially higher proportions of terrigenous and relict carbon (3-17 and 713 %, respectively). Ross Sea data were insufficient to allow similar mass balance calculations. These results suggest that, whereas particulate organic carbon is overwhelmingly marine in origin, pre-aged allochthonous terrigenous and relict OC become proportionally more important in sediments, consistent with pre-aged OC being better preserved during vertical transport to and burial at the seafloor than the upper-ocean-derived marine OC.
PT: J; TC: 0; UT: WOS:000346357100026

11,000 yrs of environmental change in the Northwest Passage: A multiproxy core record from central Parry Channel, Canadian High Arctic - Pieńkowski, A. J.; England, John H.; Furze, Mark F. A.; Blasco, Steve; Mudie, Peta J.; MacLean, Brian (Marine Geology, 2013)
Piston core 97022-004PC (74° 48.0′N 97°05.9′W; 267 m water depth) represents a rare paleoenvironmental archive from the understudied west-central Canadian Arctic Archipelago. Lithological, biogeochemical, and microfossil (dinoflagellate cysts, non-pollen palynomorphs, benthic and planktonic foraminifera) characteristics, in combination with a chronostratigraphy based on seventeen radiocarbon dates, show seven prominent paleoenvironmental episodes since the end of the last regional glaciation. The basal diamict (Zone I) records decoupling of previously grounded glacial ice, followed by ice-proximal conditions (Zone IIa) commencing at ~ 10.8 cal ka BP (age-depth model extrapolation). After an interval of pervasive sea-ice (Zone IIb), ice-distal conditions are established (Zone IIc). Although sparse microfossils are present in glaciomarine sediments (Zone II), noticeable biological activity with heightened abundances and diversities across all groups begins in the postglacial Zone III (10.3–10.0 cal ka BP) when planktonic foraminifera (Neogloboquadrina pachyderma) appear. As planktonics are excluded from the study area today (due to shallow inter-channel sills), this likely signals the inflow of relatively warm and saline Atlantic-derived Arctic Intermediate Water below 250 m, presumably facilitated by glacio-isostatically enhanced deglacial water depths. The subsequent Zone IV (10.0–7.0 cal ka BP), characterized by heightened biological productivity in both plankton and benthos and reduced seasonal sea-ice cover, may correspond to a previously proposed Holocene Thermal Maximum. This apparent amelioration ends by the mid Holocene (Zone V; 7.0–5.7 cal ka BP) when Arctic Intermediate Water is excluded from the study area and water depths approach modern values. High-Arctic conditions with seasonal sea-ice cover, a circulation dominated by Arctic Ocean Surface Water, and microfossil assemblages similar to modern are found from ~ 5.7 cal ka BP onwards (Zones VI–VII). As only minor environmental fluctuations are apparent during the late Holocene, shorter-term climatic episodes (e.g. Little Ice Age) are not recognized in this record.
id: 2343

14C and 13C characteristics of higher plant biomarkers in Washington margin surface sediments - Feng, Xiaojuan; Benitez-Nelson, Bryan C.; Montluçon, Daniel B.; Prahl, Fredrick G.; McNichol, Ann P.; Xu, Li; Repeta, Daniel J.; Eglinton, Timothy I. (Geochimica et Cosmochimica Acta, 2013)
Plant wax lipids and lignin phenols are the two most common classes of molecular markers that are used to trace vascular plant-derived OM in the marine environment. However, their 13C and 14C compositions have not been directly compared, which can be used to constrain the flux and attenuation of terrestrial carbon in marine environment. In this study, we describe a revised method of isolating individual lignin phenols from complex sedimentary matrices for 14C analysis using high pressure liquid chromatography (HPLC) and compare this approach to a method utilizing preparative capillary gas chromatography (PCGC). We then examine in detail the 13C and 14C compositions of plant wax lipids and lignin phenols in sediments from the inner and mid shelf of the Washington margin that are influenced by discharge of the Columbia River. Plant wax lipids (including n-alkanes, n-alkanoic (fatty) acids, n-alkanols, and n-aldehydes) displayed significant variability in both δ13C (−28.3‰ to −37.5‰) and Δ14C values (−204‰ to +2‰), suggesting varied inputs and/or continental storage and transport histories. In contrast, lignin phenols exhibited similar δ13C values (between −30‰ and −34‰) and a relatively narrow range of Δ14C values (−45‰ to −150‰; HPLC-based measurement) that were similar to, or younger than, bulk OM (−195‰ to −137‰). Moreover, lignin phenol 14C age correlated with the degradation characteristics of this terrestrial biopolymer in that vanillyl phenols were on average ∼500 years older than syringyl and cinnamyl phenols that degrade faster in soils and sediments. The isotopic characteristics, abundance, and distribution of lignin phenols in sediments suggest that they serve as promising tracers of recently biosynthesized terrestrial OM during supply to, and dispersal within the marine environment. Lignin phenol 14C measurements may also provide useful constraints on the vascular plant end member in isotopic mixing models for carbon source apportionment, and for interpretation of sedimentary records of past vegetation dynamics.
id: 2267

AMS radiocarbon investigation of the African baobab: Searching for the oldest tree - Patrut, Adrian; von Reden, Karl F.; Mayne, Diana H.; Lowy, Daniel A.; Patrut, Roxana T. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2013)
The Glencoe baobab, a very large specimen from South Africa, split twice in 2009. Several wood samples were collected from the eastern cavity, from the outer part of the main section and also from the largest broken segment which was connected to this section. These wood samples were processed and investigated by AMS radiocarbon dating. The radiocarbon date of the oldest sample was found to be 1838 +/- 21 BP, which corresponds to a calibrated age of 1835 +/- 40 years. Thus, the Glencoe baobab becomes the oldest dated baobab and also the oldest angiosperm tree with accurate dating results. The distribution of dating results revealed that the Glencoe baobab is a multi-generation tree, with several standing or collapsed and partially fused stems, showing different ages. (C) 2012 Elsevier B.V. All rights reserved.
id: 2246; PT: J; CT: 12th International Conference on Accelerator Mass Spectrometry (AMS); CY: MAR 20-25, 2011; CL: Wellington, NEW ZEALAND; TC: 0; UT: WOS:000313234300120

Anatomy of the La Jolla Submarine Canyon system; offshore southern California - Paull, C. K.; Caress, D. W.; Lundsten, E.; Gwiazda, R.; Anderson, K.; McGann, M.; Conrad, J.; Edwards, B.; Sumner, E. J. (Marine Geology, 2013)
An autonomous underwater vehicle (AUV) carrying a multibeam sonar and a chirp profiler was used to map sections of the seafloor within the La Jolla Canyon, offshore southern California, at sub-meter scales. Close-up observations and sampling were conducted during remotely operated vehicle (ROV) dives. Minisparker seismic-reflection profiles from a surface ship help to define the overall geometry of the La Jolla Canyon especially with respect to the pre-canyon host sediments. The floor of the axial channel is covered with unconsolidated sand similar to the sand on the shelf near the canyon head, lacks outcrops of the pre-canyon host strata, has an almost constant slope of 1.0° and is covered with trains of crescent shaped bedforms. The presence of modern plant material entombed within these sands confirms that the axial channel is presently active. The sand on the canyon floor liquefied during vibracore collection and flowed downslope, illustrating that the sediment filling the channel can easily fail even on this gentle slope. Data from the canyon walls help constrain the age of the canyon and extent of incision. Horizontal beds of moderately cohesive fine-grained sediments exposed on the steep canyon walls are consistently less than 1.232 million years old. The lateral continuity of seismic reflectors in minisparker profiles indicate that pre-canyon host strata extend uninterrupted from outside the canyon underneath some terraces within the canyon. Evidence of abandoned channels and point bar-like deposits are noticeably absent on the inside bend of channel meanders and in the subsurface of the terraces. While vibracores from the surface of terraces contain thin (
id: 2302

Annually Resolved Ice Core Records of Tropical Climate Variability over the Past similar to 1800 Years - Thompson, L. G.; Mosley-Thompson, E.; Davis, M. E.; Zagorodnov, V. S.; Howat, I. M.; Mikhatenko, V. N.; Lin, P. -N. (SCIENCE, 2013)
Ice cores from low Latitudes can provide a wealth of unique information about past climate in the tropics, but they are difficult to recover and few exist. Here, we report annually resolved ice core records from the Quelccaya ice cap (5670 meters above sea level) in Peru that extend back similar to 1800 years and provide a high-resolution record of climate variability there. Oxygen isotopic ratios (delta O-18) are linked to sea surface temperatures in the tropical eastern Pacific, whereas concentrations of ammonium and nitrate document the dominant role played by the migration of the Intertropical Convergence Zone in the region of the tropical Andes. Quetccaya continues to retreat and thin. Radiocarbon dates on wetland plants exposed along its retreating margins indicate that it has not been smaller for at least six millennia.

Assessing microbial carbon sources and potential PAH degradation using natural abundance 14C analysis - Mahmoudi, Nagissa; Fulthorpe, Roberta R.; Burns, Leanne; Mancini, Silvia; Slater, Greg F. (Environmental Pollution, 2013)
Natural abundance 14C analysis was applied to PLFAs collected from an industrial site in southern Ontario in order to assess microbial carbon sources and potential PAH biodegradation in soils. Δ14C of microbial phospholipid fatty acids (PLFA) at the site ranged from +54‰ to −697‰. Comparison of these values to surrounding carbon sources found that microbial carbon sources were derived primarily from vegetation and/or natural organic matter present in the soils rather than PAHs. This study highlights that microbes are able to utilize almost all available pools of organic matter including older pools which are thought to contain recalcitrant compounds. Furthermore, it shows that even with the presence of an active microbial community, there may be little biodegradation of PAHs. This study illustrates challenges in assessing microbial activity in the environment and the advantage of using natural abundance 14C analysis as a tool to elucidate microbial carbon sources.
id: 2268

C-14 and C-13 characteristics of higher plant biomarkers in Washington margin surface sediments - Feng, Xiaojuan; Benitez-Nelson, Bryan C.; Montluçon, Daniel B.; Prahl, Fredrick G.; McNichol, Ann P.; Xu, Li; Repeta, Daniel J.; Eglinton, Timothy I. (GEOCHIMICA ET COSMOCHIMICA ACTA, 2013)
Plant wax lipids and lignin phenols are the two most common classes of molecular markers that are used to trace vascular plant-derived OM in the marine environment. However, their C-13 and C-14 compositions have not been directly compared, which can be used to constrain the flux and attenuation of terrestrial carbon in marine environment. In this study, we describe a revised method of isolating individual lignin phenols from complex sedimentary matrices for C-14 analysis using high pressure liquid chromatography (HPLC) and compare this approach to a method utilizing preparative capillary gas chromatography (PCGC). We then examine in detail the C-13 and C-14 compositions of plant wax lipids and lignin phenols in sediments from the inner and mid shelf of the Washington margin that are influenced by discharge of the Columbia River. Plant wax lipids (including n-alkanes, n-alkanoic (fatty) acids, n-alkanols, and n-aldehydes) displayed significant variability in both delta C-13 (-28.3 parts per thousand to -37.5 parts per thousand) and Delta C-14 values (-204 parts per thousand to +2 parts per thousand), suggesting varied inputs and/or continental storage and transport histories. In contrast, lignin phenols exhibited similar delta C-13 values (between -30 parts per thousand and -34 parts per thousand) and a relatively narrow range of Delta C-14 values (-45 parts per thousand to -150 parts per thousand; HPLC-based measurement) that were similar to, or younger than, bulk OM (-195 parts per thousand to -137 parts per thousand). Moreover, lignin phenol C-14 age correlated with the degradation characteristics of this terrestrial biopolymer in that vanillyl phenols were on average similar to 500 years older than syringyl and cinnamyl phenols that degrade faster in soils and sediments. The isotopic characteristics, abundance, and distribution of lignin phenols in sediments suggest that they serve as promising tracers of recently biosynthesized terrestrial OM during supply to, and dispersal within the marine environment. Lignin phenol C-14 measurements may also provide useful constraints on the vascular plant end member in isotopic mixing models for carbon source apportionment, and for interpretation of sedimentary records of past vegetation dynamics. (C) 2012 Elsevier Ltd. All rights reserved.

A California Current bomb radiocarbon reference chronology and petrale sole (Eopsetta jordani) age validation - Haltuch, Melissa A.; Hamel, Owen S.; Piner, Kevin R.; McDonald, Patrick; Kastelle, Craig R.; Field, John C. (Canadian Journal of Fisheries and Aquatic Sciences, 2013)

Carbon isotopic characterization of hydrophobic dissolved organic carbon in rainwater - Avery Jr, G. Brooks; Biswas, K. Farhana; Mead, Ralph; Southwell, Melissa; Willey, Joan D.; Kieber, Robert J.; Mullaugh, Katherine M. (Atmospheric Environment, 2013)
The 14C and 13C content of the hydrophobic fraction (C18 extractable) of dissolved organic carbon (DOC) in Wilmington North Carolina USA rainwater was determined for six rain events to elucidate potential sources. A two end member mass-balance calculation indicated that 42–61% of the hydrophobic DOC was of fossil fuel origin compared to previously published values (4–24%) for bulk rain DOC indicating a strong anthropogenic contribution to the hydrophobic component. All fossil fuel derived organic carbon in the bulk DOC (∼15% fossil fuel derived) could be accounted for in the hydrophobic fraction (∼52% fossil fuel derived) which represents approximately 1/3 of the bulk DOC. The δ13C values of the hydrophobic DOC were consistent (−28.8 ± 0.9‰) similar to that for terrestrial and fossil fuel derived organic carbon. This is in contrast to previously published bulk rain DOC δ13C values that displayed a strong influence of air-mass back-trajectory with δ13C values ranging from −20.8‰ (typical of marine organic carbon) for marine air-mass back-trajectory rain to −28.2‰ (typical of terrestrial or fossil fuel derived organic carbon) for terrestrial air-mass back-trajectory rain. The combination of 14C and 13C isotopic data strongly suggests that a large fraction of hydrophobic organic material in rain comes from incompletely combusted fossil fuels. Changes in energy usage patterns and efforts to reduce fossil fuel emissions will alter the abundance of this hydrophobic material in the atmosphere which may impact the spectral distribution of sunlight reaching the earth's surface as well as the degree of oceanic primary productivity.
id: 2288

Carbon isotopic evidence for microbial control of carbon supply to Orca Basin at the seawater-brine interface - Shah, S. R.; Joye, S. B.; Brandes, J. A.; McNichol, A. P. (BIOGEOSCIENCES, 2013)
Orca Basin, an intraslope basin on the Texas-Louisiana continental slope, hosts a hypersaline, anoxic brine in its lowermost 200m in which limited microbial activity has been reported. This brine contains a large reservoir of reduced and aged carbon, and appears to be stable at decadal time scales: concentrations and isotopic composition of dissolved inorganic (DIC) and organic carbon (DOC) are similar to measurements made in the 1970s. Both DIC and DOC are more ``aged{''} within the brine pool than in overlying water, and the isotopic contrast between brine carbon and seawater carbon is much greater for DIC than DOC. While the stable carbon isotopic composition of brine DIC points towards a combination of methane and organic carbon remineralization as its source, radiocarbon and box model results point to the brine interface as the major source region for DIC, allowing for only limited oxidation of methane diffusing upwards from sediments. This conclusion is consistent with previous studies that identify the seawater-brine interface as the focus of microbial activity associated with Orca Basin brine. Isotopic similarities between DIC and DOC suggest a different relationship between these two carbon reservoirs than is typically observed in deep ocean basins. Radiocarbon values implicate the seawater-brine interface region as the likely source region for DOC to the brine as well as DIC.

Diagenetic changes in Lake Superior sediments as seen from FTIR and 2D correlation spectroscopy - Li, Hongyu; Minor, Elizabeth C.; Zigah, Prosper K. (Organic Geochemistry, 2013)
Isotopic and elemental analysis, Fourier transform infrared spectroscopy (FTIR), principal components analysis (PCA) and two dimensional (2D) correlation analysis, where core depth was used as perturbation, were used to study the diagenesis of organic matter (OM) in Lake Superior sediments. Changes in OM composition were examined at five lake stations over a depth range of 0–10 cm. PCA results show that depth-related changes among sites are similar, leading to an increased contribution from inorganic (and possibly refractory aromatic organic) components at each site, and a loss of contribution from other organic components. Synchronous spectra reveal that aliphatic esters and carbohydrates are degraded significantly with increasing depth, leading to an increased contribution from clay/biogenic silica/inactive carbohydrates. Asynchronous spectra show that, in general, carboxyl groups, including aliphatic ester and amide in protein, are degraded first, followed by a group of carbohydrates and then aromatic compounds and/or the SiO framework in clay and biogenic silica. Site dependent compositional variation occurs and appears to be influenced by topography and geology, e.g. the delivery of a larger load of terrestrial inorganic silicate minerals to certain sites and re-suspension/re-deposition, leading to less intensive down core variation at mid-lake central and eastern basin sites. The study demonstrates the usefulness of FTIR coupled with PCA and 2D correlation approaches for exploring structural changes in sedimentary material during diagenesis.
id: 2319

The Duxbury Sunken Forest-Constraints for Local, Late Holocene Environmental Changes Resulting from Marine Transgression, Duxbury Bay, Eastern Massachusetts, USA - Gontz, Allen M.; Maio, Christopher V.; Rueda, Laura (JOURNAL OF COASTAL RESEARCH, 2013)
The present marine transgression has forced geological and ecological zones vertically higher and landward since the late Pleistocene. A recent investigation in Duxbury Bay, Massachusetts, identified 18 Juniperus virginiana tree stumps emergent on an intertidal flat immediately seaward of a small marsh and pond situated between two eroding drumlins. The position of each stump was mapped with global positioning system (GPS), and its elevation with respect to mean lower low water was surveyed. Samples were selected from four stumps with elevations ranging from 2.03 and 0.75 m above mean lower low water for radiocarbon dating. The samples returned calibrated ages between 2219 +/- 94 and 2867 +/- 79 cal YBP, with the topographically highest sample returning the youngest date. Stump positions suggest a landscape gradient of 1.4 mm/yr between 2000 and 3000 cal YBP. The results are comparable with high-resolution studies of sea level in eastern Massachusetts for the same time period. Comparison of the youngest paleostumps with modern living trees suggests a dramatic change in the landscape gradient, an increase to 1.8 mm/yr. While this is contrary to sea-level studies nearby, it may represent an increase in the energetics of Duxbury Bay and resultant coastal erosion as the bay floods. The site can be used to put the impacts of changing sea-level rates into a landscape evolution framework.
Keywords: Cape Cod Bay; Coastal evolution; paleoforest; Radiocarbon dating; sea level; tree stumps

A gas-accepting ion source for Accelerator Mass Spectrometry: Progress and applications - Roberts, M. L.; von Reden, K. F.; Burton, J. R.; McIntyre, C. P.; Beaupre, S. R. (Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms, 2013)
The National Ocean Sciences Accelerator Mass Spectrometry (NOSAMS) facility at the Woods Hole Oceanographic Institution has developed an Accelerator Mass Spectrometry (AMS) system designed specifically for the analysis of 14C in a continuously flowing stream of carrier gas. A key part of the system is a gas-accepting microwave ion source. Recently, substantial progress has been made in the development of this source, having achieved ion currents rivaling that of a traditional graphite source (albeit at relatively low efficiency). Details and present performance of the gas source are given. Additionally, representative results obtained from coupling the source to both a gas chromatograph and gas bench are presented.
id: 2161

Great longevity of speckled hind ( Epinephelus drummondhayi), a deep-water grouper, with novel use of postbomb radiocarbon dating in the Gulf of Mexico - Andrews, Allen H.; Barnett, Beverly K.; Allman, Robert J.; Moyer, Ryan P.; Trowbridge, Hannah D.; Gillanders, Bronwyn (Canadian Journal of Fisheries and Aquatic Sciences, 2013)
Growth characteristics are poorly understood for speckled hind (Epinephelus drummondhayi), a tropical deep-water grouper of economic importance that is considered overfished. Age has been validated for early growth, but the validity of adult age estimates is unknown. A few studies of growth zones in otoliths have revealed maximum age estimates of 15–35 years, which have been uncritically assumed as longevity. To answer questions about adult age, bomb radiocarbon dating was used to provide validated age estimates. A novel aspect of this study was use of the postbomb radiocarbon decline period (ca. 1980–2004) to age younger fish, an approach that was validated with known-age otoliths. Bomb radiocarbon dating provided valid length-at-age estimates ranging from ∼5 years to more than 45 years. Age was unexpectedly greater than previous estimates for more than half the fish used in this study, and longevity may approach 60–80 years. This study extends the utility of bomb radiocarbon dating by more than 20 years and adds to the growing perspective that deep-water tropical fishes can be long-lived

Long-term variations in Iceland–Scotland overflow strength during the Holocene - Thornalley, D. J. R.; Blaschek, M.; Davies, F. J.; Praetorius, S.; Oppo, D. W.; McManus, J. F.; Hall, I. R.; Kleiven, H.; Renssen, H.; McCave, I. N. (Climate of the Past, 2013)
The overflow of deep water from the Nordic seas into the North Atlantic plays a critical role in global ocean circulation and climate. Approximately half of this overflow occurs via the Iceland–Scotland (I–S) overflow, yet the history of its strength throughout the Holocene (~ 0–11 700 yr ago, ka) is poorly constrained, with previous studies presenting apparently contradictory evidence regarding its long-term variability. Here, we provide a comprehensive reconstruction of I–S overflow strength throughout the Holocene using sediment grain size data from a depth transect of 13 cores from the Iceland Basin. Our data are consistent with the hypothesis that the main axis of the I–S overflow on the Iceland slope was shallower during the early Holocene, deepening to its present depth by ~ 7 ka. Our results also reveal weaker I–S overflow during the early and late Holocene, with maximum overflow strength occurring at ~ 7 ka, the time of a regional climate thermal maximum. Climate model simulations suggest a shoaling of deep convection in the Nordic seas during the early and late Holocene, consistent with our evidence for weaker I–S overflow during these intervals. Whereas the reduction in I–S overflow strength during the early Holocene likely resulted from melting remnant glacial ice sheets, the decline throughout the last 7000 yr was caused by an orbitally induced increase in the amount of Arctic sea ice entering the Nordic seas. Although the flux of Arctic sea ice to the Nordic seas is expected to decrease throughout the next century, model simulations predict that under high emissions scenarios, competing effects, such as warmer sea surface temperatures in the Nordic seas, will result in reduced deep convection, likely driving a weaker I–S overflow.

Middle Wisconsin glacial advance into the Appalachian Plateau, Sixmile Creek, Tompkins Co., NY - Karig, Daniel E.; Miller, Norton G. (Quaternary Research, 2013)
Areal mapping of the middle Wisconsin varved clay site along Sixmile Creek near Ithaca, New York, has revealed a much more widespread and varied array of sediments than previously thought. Lacustrine clays, some varved, are interbedded with sands and gravels interpreted as sub-aqueous fan deposits, and both are overlain by a deformation till. Nine radiocarbon dates indicate a 34–37 14C ka BP age for the lacustrine sediment, with the deformation till less than a few thousand years younger. Beneath this sequence is a deposit dated at ± 42 14C ka BP. Both strata represent a tundra climate with a mean July temperature of about 10°C. The Sixmile Creek deformation till must correlate with the 35 14C ka BP till along the Genesee River, 125 km to the NW, and defines a Cherrytree stade glacial advance into the Appalachian Plateau, much further south than what has generally been accepted. Such an advance would require drainage from a proglacial lake in the western Ontario basin to flow westward instead of northeastward. The Sixmile strata suggest a colder than accepted middle Wisconsin stage. Recent data indicate that this stage is one of progressive cooling, with large climatic fluctuations.

Mid-Late Holocene coastal environmental changes in southeastern Sri Lanka: New evidence for sea level variations in southern Bay of Bengal - Ranasinghe, R. N.; Ortiz, J. D.; Moore, A. L.; McAdoo, B.; Wells, N.; Siriwardana, C. H. E. R.; Wijesundara, D. T. D. S. (QUATERNARY INTERNATIONAL, 2013)
The 2004 Indian Ocean tsunami highlighted the need to better understand the dynamics of the South Asian coastlines. Very little knowledge on paleo-coastal variability hinders the development of a paleo-tsunami chronology of the western Bay of Bengal. Also, limited sea level records for the southern Bay of Bengal are remarkably different from rest of the Indian Ocean due to alternating highstands and lowstands during mid-late Holocene. This study was undertaken to recognize how the coastal environment in tectonically stable eastern and southeastern coasts of Sri Lanka changed during mid-late Holocene and to derive evidence of sea level variability. Sediment cores were collected from Kirinda and Panama estuaries, Okanda lagoon and Vakarai beach ridge plain, situated on the eastern and southeastern coasts of Sri Lanka. Physical and chemical variations in sediments, caused by the coastal environmental changes occurred due to fluctuating eustatic sea level, were determined using X-ray fluorescence, visible reflectance, magnetic susceptibility and grain size. Chronology of events were developed using AMS C-14 dates on bulk organic matter, wood, inorganic carbonate and mollusk shells. Results suggest that key periods of transition in the coastal environment in the studied area occurred between about 7300 and 3000 BP. Submergence of coastal environments by mid-Holocene transgression began around 7300 BP. Barrier development initiated at the end of the submergence phase around 4900 BP. Onset of beach ridge development in areas with high sediment supply took place around 4000 BP and continued later than 2400 BP. Marine influence ended around 3000 BP. These coastal environmental changes suggest that Holocene transgression, which started flooding southeastern coastal lowlands, either slowed or the sea level stabilized around 4900 BP. Sea level fell down to its present level at around 3000 BP by the subsequent slow regression. Some cores carry evidence for a possible pause in the transgression or a short lowstand that ended around 5200 BR (c) 2013 Elsevier Ltd and INQUA. All rights reserved.

Moisture and temperature changes associated with the mid-Holocene Tsuga decline in the northeastern United States - Marsicek, Jeremiah P.; Shuman, Bryan; Brewer, Simon; Foster, David R.; Oswald, W. Wyatt (Quaternary Science Reviews, 2013)
A decline of hemlock (Tsuga) populations at ca 5.5 ka (thousands of calibrated radiocarbon years before 1950 AD) stands out as the most abrupt vegetation change of the Holocene in North America, but remains poorly understood after decades of study. Recent analyses of fossil pollen have revealed a concurrent, abrupt oak (Quercus) decline and increases in the abundance of beech (Fagus) and pine (Pinus) on Cape Cod in eastern Massachusetts, but the replacement of drought-tolerant oaks by moisture-sensitive beeches appears inconsistent with low lake levels in the region at the same time. The oak and beech changes are also limited to coastal areas, and the coastal-inland differences require an explanation. Here, we develop a new lake-level reconstruction from Deep Pond, Cape Cod by using a transect of sediment cores and ground-penetrating radar (GPR) profiles to constrain the past elevations of the sandy, littoral zone of the pond. The reconstruction shows that a series of multi-century episodes of low water coincide with the abrupt hemlock and oak declines, and interrupt subsequent phases of hemlock recovery. The lake-level variations equal precipitation deficits of ∼100 mm superimposed on a Holocene long moisture increase of >400 mm. However, because moisture deficits do not easily explain the oak and beech changes, we also evaluate how the climate preferences of the regional vegetation changed over time by matching the fossil pollen assemblages from Deep Pond with their modern equivalents. Reconstructions of the precipitation requirements of the vegetation correlate well even in detail with the lake-level record (r = 0.88 at Deep Pond), and indicate close tracking of effective moisture (precipitation minus evapotranspiration) by the vegetation despite the abrupt species declines, which could have decoupled climate and vegetation trends. Reconstructions of the temperature preferences of the vegetation indicate that coastal sites may have cooled by 0.5–2.5 °C after ca 5.5 ka, while inland sites warmed by 0.5–1 °C. The change in coastal temperature preferences agrees with sea surface cooling in the western Atlantic Ocean of >1 °C. Consequently, the persistence of low hemlock abundance after 5.5 ka in the northeast U.S. may have resulted from oceanic changes that produced multi-century droughts and thus delayed the post-decline recovery of hemlock populations.

Molecular and isotopic insights into particulate organic carbon sources and dynamics in Jordan Basin, Gulf of Maine - Hwang, Jeomshik; Montluçon, Daniel B.; Pilskaln, Cynthia H.; Eglinton, Timothy I. (Continental Shelf Research, 2013)
The carbon isotope and lipid biomarker composition of suspended particles and surface sediment was measured to examine the impact of sediment supply, redistribution and post-depositional alteration processes on organic matter cycling in the Gulf of Maine, a semi-enclosed shelf sea in the northwest Atlantic. A beam attenuation profile revealed a >50 m-thick benthic nepheloid layer (BNL) in the Jordan Basin at the time of sampling (April 2006). The relatively low radiocarbon content of suspended particulate organic carbon (POC) in the BNL indicates that up to 82% of the POC in this layer was supplied from resuspension of sediment. The concentration of alkenones normalized to POC increased with increasing depth in the water column and was highest in the surface sediment. In contrast to these markers of surface ocean photoautotrophy, the vertical profiles for the concentration and composition of short-chain (C14–C18) n-alkanoic acids provided evidence for enhanced heterotrophic processes near the top of the BNL. Suspended POC samples from two depths within the BNL exhibited marked differences in radiocarbon content and fatty acid composition, suggesting that biological activity and associated processes within the BNL are vertically heterogeneous.

Old ages of two historical Romanian trees assessed by AMS radiocarbon dating - Patrut, Adrian; von Reden, Karl F.; Lowy, Daniel A.; Patrut, Roxana T.; Vaida, D. Lucian; Margineanu, Dragos (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2013)
Two large Romanian poplars are considered to be associated with significant historical events of the past. In order to verify these claims, wood samples collected from the broken trunks of the two poplars were radiocarbon dated by AMS. The oldest radiocarbon dates were found to be 275 +/- 20 bp for the black poplar of Mocod and 316 +/- 22 bp for the gray poplar of Rafaila. These values correspond to calibrated ages of 365 +/- 10 and 465 +/- 25 years, respectively. The dating results indicate old ages for the two trees, i.e., 455 years for the Mocod poplar and 560 years for the Rafaila poplar. Such age values validate historical information on the two large Romanian trees. (C) 2012 Elsevier B.V. All rights reserved.
id: 2245; PT: J; CT: 12th International Conference on Accelerator Mass Spectrometry (AMS); CY: MAR 20-25, 2011; CL: Wellington, NEW ZEALAND; TC: 0; UT: WOS:000313234300119

Paleoclimate changes of the last 1000 yr on the eastern Qinghai–Tibetan Plateau recorded by elemental, isotopic, and molecular organic matter proxies in sediment from glacial Lake Ximencuo - Pu, Yang; Nace, Trevor; Meyers, Philip A.; Zhang, Hucai; Wang, Yongli; Zhang, Chuanlun L.; Shao, Xiaohua (Palaeogeography, Palaeoclimatology, Palaeoecology, 2013)
Total organic carbon (Corg) and nitrogen (Ntot) concentrations and isotope compositions and n-alkane and n-alkan-ol molecular biomarker compositions were measured in two parallel sediment cores from Lake Ximencuo, a typical glacial lake on the eastern Qinghai–Tibetan Plateau (QTP), to reconstruct local climatic variations during the past 1000 yr. Concentrations of Corg and Ntot vary similarly with changes in precipitation recorded by tree rings in Dulan, northeastern QTP, indicating their close relation to precipitation. Carbon Preference Index (CPI) values of C22–C33 n-alkanes and C22–C28 n-alkan-1-ols and Average Chain Length (ACL) values of C27–C33 n-alkanes generally negatively correlate with δ13Corg and δ15Ntot and also vary comparably with the oxygen isotope temperature record from the Dunde ice core, northeastern QTP. These patterns indicate that high CPI values and negative shifts of the δ13Corg and δ15Ntot correspond to warmer conditions that favor the growth of vascular land plants and that lower values and positive shifts correspond to cooler conditions in the Lake Ximencuo locality. This observation contradicts previous interpretations from peat and modern soil studies that conclude that the CPI indices were controlled by microbial degradation under different climate conditions. Here we propose that the changes of organic matter sources under different climate regimes, combined with physiological adjustments of vascular plants to different air temperatures, might yield different CPI responses to climate changes in glacial plateau lakes. Air temperature and precipitation increases and decreases reconstructed in this 1000-yr study were generally independent of each other, but they both occurred at centennial or multi-centennial scales. The interaction between subtropical (Asian Monsoon) and mid-latitude (Westerly) atmospheric circulation systems probably dominated the local precipitation variations in the Lake Ximencuo catchment, whereas solar insolation, volcanism and greenhouse gas variations were likely responsible for the air temperature changes that are recorded in the lake sediments and that are consistent with regional temperature variations in the eastern QTP.
id: 2310

Persistent export of 231Pa from the deep central Arctic Ocean over the past 35,000 years - Hoffmann, Sharon S.; McManus, Jerry F.; Curry, William B.; Brown-Leger, L. Susan (Nature, 2013)
The Arctic Ocean has an important role in Earth’s climate, both through surface processes1 such as sea-ice formation and transport, and through the production and export of waters at depth that contribute to the global thermohaline circulation2, 3. Deciphering the deep Arctic Ocean’s palaeo-oceanographic history is a crucial part of understanding its role in climatic change. Here we show that sedimentary ratios of the radionuclides thorium-230 (230Th) and protactinium-231 (231Pa), which are produced in sea water and removed by particle scavenging on timescales of decades to centuries, respectively4, record consistent evidence for the export of 231Pa from the deep Arctic and may indicate continuous deep-water exchange between the Arctic and Atlantic oceans throughout the past 35,000 years. Seven well-dated box-core records provide a comprehensive overview of 231Pa and 230Th burial in Arctic sediments during glacial, deglacial and interglacial conditions. Sedimentary 231Pa/230Th ratios decrease nearly linearly with increasing water depth above the core sites, indicating efficient particle scavenging in the upper water column and greater influence of removal by lateral transport at depth. Although the measured 230Th burial is in balance with its production in Arctic sea water, integrated depth profiles for all time intervals reveal a deficit in 231Pa burial that can be balanced only by lateral export in the water column. Because no enhanced sink for 231Pa has yet been found in the Arctic, our records suggest that deep-water exchange through the Fram strait may export 231Pa. Such export may have continued for the past 35,000 years, suggesting a century-scale replacement time for deep waters in the Arctic Ocean since the most recent glaciation and a persistent contribution of Arctic waters to the global ocean circulation.
Keywords: Marine chemistry; Palaeoceanography; Palaeoclimate

Pleistocene sequence stratigraphy of the shallow continental shelf, offshore New Jersey: Constraints of Integrated Ocean Drilling Program Leg 313 core holes - Miller, Kenneth G.; Sugarman, Peter J.; Browning, James V.; Sheridan, Robert E.; Kulhanek, Denise K.; Monteverde, Donald H.; Wehmiller, John F.; Lombardi, Christopher; Feigenson, Mark D. (GEOSPHERE, 2013)
We used cores and logs from Integrated Ocean Drilling Program (IODP) Expedition 313 to generate biostratigraphic, lithofacies, biofacies, and geochemical data that constrain the ages and paleoenvironments of Pleistocene sequences. We integrate sequence stratigraphy on cores with new seismic stratigraphic data to interpret the Pleistocene history of the Hudson shelf valley and paleoenvironmental and sea-level changes on the inner to middle continental shelf. Improved age control compared to previous studies is provided by integrated calcareous nannofossil biostratigraphy, Sr isotopic stratigraphy, and amino acid racemization. We recognize four upper Pleistocene-Holocene sequences: sequence uP1 is correlated with Marine Isotope Chrons (MIC; ``chron{''} is the correct stratigraphic term for a time unit, not ``stage{''}) 7 or 5e, sequence uP2 with MIC 5c, sequence uP3 with MIC 5a, and sequence uP4 with the latest Pleistocene to Holocene (MIC 1-2). However, within our age resolution it is possible that sequences uP2 and uP3 correlate with MIC 4-3c and 3a, respectively, as suggested by previous studies. Lower Pleistocene sequences lP1 and lP2 likely correlate with peak interglacials (e. g., MIC 31 and MIC 45 or 47, respectively). Thus, we suggest that preservation of sequences occurs only during peak eustatic events (e. g., MIC 45 or 47, MIC 31, and MIC 5), unless they are preserved in eroded valleys. The architecture of the Pleistocene deposits at Sites M27 and M29 is one of thin remnants of highstand and transgressive systems tracts, with lowstand deposits only preserved in the thalwegs of incised valleys. Incised valleys at the bases of sequences uP3 (IODP Site M27) and uP2 (IODP Site M29) document more southward courses of the paleo-Hudson valley, compared to the more southeastward course of the MIC 1-2 paleo-Hudson valley. The patchy distribution of Pleistocene sequences beneath the New Jersey inner-middle continental shelf is due to low accommodation during an interval of large eustatic changes; this predicts that sequences in such settings will be discontinuous, patchy, and difficult to correlate, consistent with previous studies in Virginia and North Carolina.

Prominent bacterial heterotrophy and sources of C-13-depleted fatty acids to the interior Canada Basin - Shah, S. R.; Griffith, D. R.; Galy, V.; McNichol, A. P.; Eglinton, T. I. (BIOGEOSCIENCES, 2013)
In recent decades, the Canada Basin of the Arctic Ocean has experienced rapidly decreasing summer sea ice coverage and freshening of surface waters. It is unclear how these changes translate to deeper waters, particularly as our baseline understanding of organic carbon cycling in the deep basin is quite limited. In this study, we describe full-depth profiles of the abundance, distribution and carbon isotopic composition of fatty acids from suspended particulate matter at a seasonally ice-free station and a semi-permanently ice-covered station. Fatty acids, along with suspended particulate organic carbon (POC), are more concentrated and C-13-enriched under ice cover than in ice-free waters. But this influence, apparent at 50 m depth, does not propagate downward below 150m depth, likely due to the weak biological pump in the central Canada Basin. Branched fatty acids have delta C-13 values that are similar to suspended POC at all depths and are more C-13-enriched than even-numbered saturated fatty acids at depths above 3000 m. These are likely to be produced in situ by heterotrophic bacteria incorporating organic carbon that is isotopically similar to total suspended POC. Below surface waters, there is also the suggestion of a source of saturated even-numbered fatty acids which could represent contributions from laterally advected organic carbon and/or from chemoautotrophic bacteria. At 3000 m depth and below, a greater relative abundance of long-chain (C20-24), branched and unsaturated fatty acids is consistent with a stronger influence of re-suspended sedimentary organic carbon. At these deep depths, two individual fatty acids (C-12 and iso-C-17) are significantly depleted in C-13, allowing for the possibility that methane oxidizing bacteria contribute fatty acids, either directly to suspended particulate matter or to shallow sediments that are subsequently mobilized and incorporated into suspended particulate matter within the deep basin.

Radiocarbon Dating of Basal Peats Supports Separation of Lake Superior from Lakes Michigan-Huron about 1250 years ago - Yu, Shi-Yong; Colman, Steven M.; Milne, Glenn A. (Earth and Planetary Science Letters, 2013)
Lake Superior represents an important component of the aquatic ecosystem in North America. Along its south shore, ongoing lake-level rise, accelerated erosion, and wetland loss are major environmental concerns to coastal communities. A better prediction of the future of this shore requires placing the instrumental lake-level records in a geological context. However, our knowledge of the late-Holocene history of the world's largest freshwater body remains fragmentary. Here we present a sedimentary record of late-Holocene relative lake-level changes by dating transgressive basal peats resting directly on a sandy substrate along a bathymetric gradient in Bark Bay Slough, Wisconsin. Our record shows a moderate lake-level rise at 1.4±0.2 mm/yr from about 2200 to 1250 cal yr BP as a result of relatively slow differential uplift of Bark Bay relative to the controlling outlet at Port Huron. The rise accelerated to 2.3±0.2 mm/yr at about 1250 cal yr BP when Sault Ste. Marie emerged as the controlling outlet, thereby separating Superior from Lakes Michigan–Huron and giving rise to the modern hydrographic regime of the upper Great Lakes. The timing of this event in our record is about 1000 yr later than that estimated in most previous studies, but our data complement and confirm the younger age of lake separation inferred using a different methodology. Our results not only provide pertinent information for hydrological regulation, navigation operation, and infrastructural design in the upper Great Lakes, but also provide insight into freshwater wetland succession on flooded coasts.

Separation of Lake Superior from Lakes Michigan–Huron about 1250 yr ago - Yu, Shi-Yong; Colman, Steven M.; Milne, Glenn A. (Earth and Planetary Science Letters, 2013)
Lake Superior represents an important component of the aquatic ecosystem in North America. Along its south shore, ongoing lake-level rise, accelerated erosion, and wetland loss are major environmental concerns to coastal communities. A better prediction of the future of this shore requires placing the instrumental lake-level records in a geological context. However, our knowledge of the late-Holocene history of the world's largest freshwater body remains fragmentary. Here we present a sedimentary record of late-Holocene relative lake-level changes by dating transgressive basal peats resting directly on a sandy substrate along a bathymetric gradient in Bark Bay Slough, Wisconsin. Our record shows a moderate lake-level rise at 1.4±0.2 mm/yr from about 2200 to 1250 cal yr BP as a result of relatively slow differential uplift of Bark Bay relative to the controlling outlet at Port Huron. The rise accelerated to 2.3±0.2 mm/yr at about 1250 cal yr BP when Sault Ste. Marie emerged as the controlling outlet, thereby separating Superior from Lakes Michigan–Huron and giving rise to the modern hydrographic regime of the upper Great Lakes. The timing of this event in our record is about 1000 yr later than that postulated in most previous studies. Our results not only provide pertinent information for hydrological regulation, navigation operation, and infrastructural design in the upper Great Lakes, but also provide insight into freshwater wetland succession on flooded coasts.
id: 2336

Source, diagenesis, and fluxes of particulate organic carbon along the western Adriatic Sea (Mediterranean Sea) - Tesi, T.; Langone, L.; Giani, M.; Ravaioli, M.; Miserocchi, S. (Marine Geology, 2013)
In this study, we investigated the modern organic carbon (OC) cycling along the clinoform-shaped deposit that developed after the attainment of the modern sea-level in the Adriatic Sea (~ 5.5 kyr cal BP). Newly acquired data were combined with published results to characterize the (i) origin, (ii) diagenesis, and (iii) fluxes of OC along the Adriatic clinoform. δ13C, Δ14C, and lignin phenols were used to constrain the composition of OC accumulating in surface sediments. Sediment cores collected at different water depths were used to describe the early diagenesis during burial in different regions. In addition, on the basis of an extensive number of accumulation rates and OC data, we assessed the flux of OC to the seabed and its burial. Our results showed that terrigenous OC is the dominant OC source in the Po prodelta mainly in the form of pre-aged soil-derived OC and vascular plant fragments. Along the clinoform, both Δ14C and the concentration of lignin-derived phenols decreased with increasing distance from the Po prodelta indicating the influence of an additional pool of aged OC that gradually becomes more important because of its selective preservation during the sediment transport. As a result, degradation rates (k) decreased along the clinoform as a function of the sediment oxidative history. The calculated half-life of reactive OC (t1/2) was ~ 14.6 yrs in the Po prodelta whereas topset/forest deposits south of this region exhibited higher values, ~ 100 yrs, indicating the presence of refractory material. In the distal bottomset region, the t1/2 was particularly high ranging from ~ 255 to ~ 912 yrs. Because of the significant southward component of the sediment transport, the OC deposition in the southern surface sediments exceeded the local OC input via rivers (ratio deposition/input 1.2). Conversely, the northern Adriatic was characterized by a marked imbalance (ratio deposition/input 0.3–0.5). According to our calculations, the OC flux to the seabed along the clinoform was ~ 309 Gg of C per year whereas the OC burial was ~ 180 Gg of C per year, corresponding to an overall burial efficiency of ~ 59%.
id: 2335

Transient stratification as the cause of the North Pacific productivity spike during deglaciation - Lam, Phoebe J.; Robinson, Laura F.; Blusztajn, Jerzy; Li, Camille; Cook, Mea S.; McManus, Jerry F.; Keigwin, Lloyd D. (Nature Geoscience, 2013)
During the Bølling–Allerød warm period of the last deglaciation, about 14 kyr ago, there was a strong and pervasive spike in primary productivity in the North Pacific Ocean1. It has been suggested that this productivity event was caused by an influx of the micronutrient iron from surrounding continental shelves as they were flooded by sea-level rise2. Here we test this hypothesis by comparing numerous proxies of productivity with iron flux and provenance measured from a core from the subarctic Pacific Ocean. We find no evidence for an abrupt deglacial pulse of iron from any source at the time of peak productivity. Instead, we argue that the deglacial productivity peak was caused by two stepwise events. First, deep convection during early deglaciation increased nutrient supply to the surface but also increased the depth of the mixed layer, which pushed surface production deeper in the water column and induced light limitation. A subsequent input of meltwater from northern American ice sheets then stratified the water column, which relieved light limitation while leaving the surface waters enriched in nutrients. We conclude that iron plays, at most, a secondary role in controlling productivity during the glacial and deglacial periods in the subarctic Pacific Ocean.
Keywords: Biogeochemistry; Marine biology; Marine chemistry; Palaeoceanography

Carbon dynamics in the western Arctic Ocean: insights from full-depth carbon isotope profiles of DIC, DOC, and POC - Griffith, D. R.; McNichol, A. P.; Xu, L.; McLaughlin, F. A.; Macdonald, R. W.; Brown, K. A.; Eglinton, T. I. (Biogeosciences, 2012)
Arctic warming is projected to continue throughout the coming century. Yet, our currently limited understanding of the Arctic Ocean carbon cycle hinders our ability to predict how changing conditions will affect local Arctic ecosystems, regional carbon budgets, and global climate. We present here the first set of concurrent, full-depth, dual-isotope profiles for dissolved inorganic carbon (DIC), dissolved organic carbon (DOC), and suspended particulate organic carbon (POCsusp) at two sites in the Canada Basin of the Arctic Ocean. The carbon isotope composition of sinking and suspended POC in the Arctic contrasts strongly with open ocean Atlantic and Pacific sites, pointing to a combination of inputs to Arctic POCsusp at depth, including surface-derived organic carbon (OC), sorbed/advected OC, and OC derived from in situ DIC fixation. The latter process appears to be particularly important at intermediate depths, where mass balance calculations suggest that OC derived from in situ DIC fixation contributes up to 22% of POCsusp. As in other oceans, surface-derived OC is still a dominant source to Arctic POCsusp. Yet, we suggest that significantly smaller vertical POC fluxes in the Canada Basin make it possible to see evidence of DIC fixation in the POCsusp pool even at the bulk isotope level.
id: 2254; PT: J; TC: 4; UT: WOS:000302179500026

Characterization of soils beneath a Posidonia oceanica meadow - Serrano, O.; Mateo, M. A.; Renom, P.; Julià, R. (Geoderma, 2012)
The study of a 475 cm core (spanning 4316 y BP) sampled in a Posidonia oceanica meadow (Portlligat Bay, NW Mediterranean) allowed us to make the first detailed description of the soil below this endemic seagrass. The sediments under P. oceanica (often referred to as mat or matte) are low density (average bulk density of 0.69 g DW cm− 3) marine soils mainly composed of siliciclastic (46%) and biogenic carbonated (46%) fine-grained sediments (particles 1 mm) and finer organic matter (3% of SOM;
id: 2300

Chemical weathering and provenance evolution of Holocene–Recent sediments from the Western Indus Shelf, Northern Arabian Sea inferred from physical and mineralogical properties - Limmer, David R.; Köhler, Cornelia M.; Hillier, Stephen; Moreton, Steven G.; Tabrez, Ali R.; Clift, Peter D. (Marine Geology, 2012)
We present a multi-proxy mineral record based on X-ray diffraction and diffuse reflectance spectrophotometry analysis for two cores from the western Indus Shelf in order to reconstruct changing weathering intensities, sediment transport, and provenance variations since 13 ka. Core Indus-10 is located northwest of the Indus Canyon and exhibits fluctuations in smectite/(illite + chlorite) ratios that correlate with monsoon intensity. Higher smectite/(illite + chlorite) and lower illite crystallinity, normally associated with stronger weathering, peaked during the Early–Mid Holocene, the period of maximum summer monsoon. Hematite/goethite and magnetic susceptibility do not show clear co-variation, although they both increase at Indus-10 after 10 ka, as the monsoon weakened. At Indus-23, located on a clinoform just west of the canyon, hematite/goethite increased during a period of monsoon strengthening from 10 to 8 ka, consistent with increased seasonality and/or reworking of sediment deposited prior to or during the glacial maximum. After 2 ka terrigenous sediment accumulation rates in both cores increased together with redness and hematite/goethite, which we attribute to widespread cultivation of the floodplain triggering reworking, especially after 200 years ago. Over Holocene timescales sediment composition and mineralogy in two localities on the high-energy shelf were controlled by varying degrees of reworking, as well as climatically modulated chemical weathering.
id: 2271

Clay mineral variations in Holocene terrestrial sediments from the Indus Basin - Alizai, Anwar; Hillier, Stephen; Clift, Peter D.; Giosan, Liviu; Hurst, Andrew; VanLaningham, Sam; Macklin, Mark (Quaternary Research, 2012)
We employed X-ray diffraction methods to quantify clay mineral assemblages in the Indus Delta and flood plains since ~ 14 ka, spanning a period of strong climatic change. Assemblages are dominated by smectite and illite, with minor chlorite and kaolinite. Delta sediments integrate clays from across the basin and show increasing smectite input between 13 and 7.5 ka, indicating stronger chemical weathering as the summer monsoon intensified. Changes in clay mineralogy postdate changes in climate by 5–3 ka, reflecting the time needed for new clay minerals to form and be transported to the delta. Samples from the flood plains in Punjab show evidence for increased chemical weathering towards the top of the sections (6–
id: 2333

Composition and fate of gas and oil released to the water column during the Deepwater Horizon oil spill - Reddy, Christopher M.; Arey, J. Samuel; Seewald, Jeffrey S.; Sylva, Sean P.; Lemkau, Karin L.; Nelson, Robert K.; Carmichael, Catherine A.; McIntyre, Cameron P.; Fenwick, Judith; Ventura, G. Todd; Van Mooy, Benjamin A. S.; Camilli, Richard (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Quantitative information regarding the endmember composition of the gas and oil that flowed from the Macondo well during the Deepwater Horizon oil spill is essential for determining the oil flow rate, total oil volume released, and trajectories and fates of hydrocarbon components in the marine environment. Using isobaric gas-tight samplers, we collected discrete samples directly above the Macondo well on June 21, 2010, and analyzed the gas and oil. We found that the fluids flowing from the Macondo well had a gas-to-oil ratio of 1,600 standard cubic feet per petroleum barrel. Based on the measured endmember gas-to-oil ratio and the Federally estimated net liquid oil release of 4.1 million barrels, the total amount of C-1-C-5 hydrocarbons released to the water column was 1.7 x 10(11) g. The endmember gas and oil compositions then enabled us to study the fractionation of petroleum hydrocarbons in discrete water samples collected in June 2010 within a southwest trending hydrocarbon-enriched plume of neutrally buoyant water at a water depth of 1,100 m. The most abundant petroleum hydrocarbons larger than C-1-C-5 were benzene, toluene, ethylbenzene, and total xylenes at concentrations up to 78 mu gL(-1). Comparison of the endmember gas and oil composition with the composition of water column samples showed that the plume was preferentially enriched with water-soluble components, indicating that aqueous dissolution played a major role in plume formation, whereas the fates of relatively insoluble petroleum components were initially controlled by other processes.
id: 2247; PT: J; TC: 10; UT: WOS:000312605600028

Correction to" Isotopic characterization of aerosol organic carbon components over the eastern United States" (vol 117, D13303, 2012) - Wozniak, Andrew S.; Bauer, James E.; Dickhut, Rebecca M.; Xu, Li; McNichol, Ann P. (Journal of Geophysical Research-Atmospheres, 2012)
id: 2251; PT: J; TC: 0; UT: WOS:000307471700004

The deglacial to postglacial marine environments of SEBarrow Strait, Canadian Arctic Archipelago - Pieńkowski, A. J.; England, John H.; Furze, Mark F. A.; Marret, Fabienne; Eynaud, Frédérique; Vilks, Gustav; MacLean, Brian; Blasco, Steve; Scourse, James D. (Boreas, 2012)
Core 86027-144 (74°15.56?N, 91°14.21?W) represents a rare, continuous record of Late Pleistocene to Holocene sediments from High Arctic Canada extending from the end of the Last Glaciation. Based on microfossils (dinocysts, non-pollen palynomorphs, benthic and planktonic foraminifera), foraminiferal ?18O and ?13C, and sedimentology, seven palaeoenvironmental zones were identified. Zone I (>10.8?cal.?ka BP) records deglaciation, ice-sheet destabilization, float-off and subsequent break-up. Zone II (c.?10.8?10.4?cal.?ka BP) shows ice-proximal to ice-distal glaciomarine conditions, interrupted by pervasive land-fast sea-ice marked by a hiatus in coarse sediment deposition. Significant biological activity starts in Zone III (10.4?9.9?cal.?ka BP), where planktonic foraminifera (Neogloboquadrina pachyderma) suggest early oceanic throughflow. Surface waters flowed NW?SE; however, the deep-water origin remains unclear (potentially NW Arctic Ocean or Baffin Bay). Postglacial amelioration (open-water season greater than present) in Zone IV (9.9?7.8?cal.?ka BP) perhaps corresponds to the regional ?Holocene Thermal Maximum? previously proposed. A transitional period (Zone V; 7.8?6.7?cal. ka BP) of rapid environmental change fluctuating on a scale not observed today is marked by increasing sea-ice and reduced oceanic influence. This probably signals the exclusion of deeper Atlantic water owing to the glacio-isostatic shallowing of inter-island sills, coupled with generally cooling climate. Conditions analogous to those at present, with increased sea-ice and modern microfossil assemblages, commence at c. 6.7?cal.?ka BP (zones VI?VII). Although climate ultimately forces long-term environmental trends, core 86027-144 data imply that regional dynamics, especially changes in sea-level, exert a significant control on marine conditions throughout the Canadian Arctic Archipelago.
id: 2342

ENSO Drove 2500-Year Collapse of Eastern Pacific Coral Reefs - Toth, L. T.; Aronson, R. B.; Vollmer, S. V.; Hobbs, J. W.; Urrego, D. H.; Cheng, H.; Enochs, I. C.; Combosch, D. J.; van Woesik, R.; Macintyre, I. G. (Science, 2012)
Cores of coral reef frameworks along an upwelling gradient in Panamá show that reef ecosystems in the tropical eastern Pacific collapsed for 2500 years, representing as much as 40% of their history, beginning about 4000 years ago. The principal cause of this millennial-scale hiatus in reef growth was increased variability of the El Niño–Southern Oscillation (ENSO) and its coupling with the Intertropical Convergence Zone. The hiatus was a Pacific-wide phenomenon with an underlying climatology similar to probable scenarios for the next century. Global climate change is probably driving eastern Pacific reefs toward another regional collapse.

Evaluation of sediment trace metal records as paleoproductivity and paleoxygenation proxies in the upwelling center off Concepción, Chile (36°S) - Muñoz, Praxedes; Dezileau, Laurent; Lange, Carina; Cardenas, Lissette; Sellanes, Javier; Salamanca, Marco A.; Maldonado, Antonio (Variability of the coastal upwelling and coastal transition zones off central-southern Chile, 2012)
This study analyzes the records of several trace metals sensitive to redox conditions in continental shelf sediments off Concepción, Chile (36°S). The continental margin off Concepción (36°S; 73°W) lies beneath an important upwelling center characterized by high primary production rates and, consequently, high fluxes of organic matter. In spring and summer, this material settles to the seafloor where it decays, producing periods of very low oxygen content in bottom waters (1 mL L−1). The goals of this study were to determine the input of trace metals to the sediment and to decipher how this information can be used to reveal variations in primary productivity or bottom oxygenation. Gravity cores collected at two stations – VG06-2 over the mid-shelf station (88 m water depth, upper boundary of the oxygen minimum zone) and VG06-3 over the outer shelf (120 m water depth, within the oxygen minimum zone) – were sampled for high resolution profiles (1 cm) of trace metals, biogenic opal, stable isotopes, and total organic carbon. The results suggest that the variability in the trace metal distribution on the continental shelf off Concepción is determined by redox conditions and the organic carbon flux to the bottom. Some sections of the sediment cores from the outer shelf showed appreciable authigenic enrichment of U, Cd, and Mo (EF: 5–10, 2–5, and 10–16 respectively) along with heavier values of δ15N, suggesting periods of suboxic conditions. During these periods, fluxes of organic material to the bottom were higher, as indicated by elevated TOC and opal contents. Alternating periods of higher and lower trace metal contents were not observed mid-shelf as they were on the outer shelf. Rather, the mid-shelf samples showed authigenic enrichment of U, Cd, and Mo (EF: 1–6, 4–5, and 10–20, respectively) throughout the core except in a 10-cm-thick gray layer. In general, authigenic enrichment of U, Mo, and Cd occurred at both sites, coincident with olive green layers in the cores. These layers were associated with periods of elevated primary productivity and suboxic conditions. Such periods did not seem to last as long as the oxygenated periods, which had higher inputs of refractive detrital material, coincident with the occurrence of distinct gray sediment layers.
id: 2154

Geochemical and geological constraints on the composition of marine sediment pore fluid: Possible link to gas hydrate deposits - Mazumdar, A.; Joao, H. M.; Peketi, A.; Dewangan, P.; Kocherla, M.; Joshi, R. K.; Ramprasad, T. (Marine and Petroleum Geology, 2012)
Pore water sulfate consumption in marine sediments is controlled by microbially driven sulfate reduction via organo-clastic and methane oxidation processes. In this work, we present sediment pore fluid compositions of 10 long sediment cores and high resolution seismic data from the Krishna–Godavari (K–G) basin, Bay of Bengal. Our results show occurrence of transient (S and kink types) and steady state (quasi-linear) sulfate concentration profiles which are attributed partly to the anaerobic oxidation of methane ( δ 13 C CH 4 : −84.8 to −100.1‰ VPDB) and organo-clastic sulfate reduction. Influence of AOM on alkalinity is evident from the presence of authigenic carbonate layers with highly depleted carbon isotope ratios in core MD161-8. The authigenic carbonates represent the paleo-SMTZs and suggest marked fluctuation in vertical methane flux. Our geophysical data show the acoustic signatures of upward fluid migration from shallow sub-surface, whereas, coring during NGHP expedition-01 confirms the presence of sub-surface gas hydrate deposits in K–G basin which can be linked to deep methane sources. The geochemical analysis suggests that shallow methane source can be attributed to high burial flux of labile organic matter due to high sedimentation rate. Sampling sites with high methane flux from the shallow gas source are characterized by quasi-linear sulfate concentration profile and a shallow sulfate methane transition zone (SMTZ) and may not be necessarily linked to deeper gas hydrate deposits. In contrast, the deep methane source results in a transient kink type sulfate profile and a deeper SMTZ. We have observed a close link between the occurrence of gas hydrate and the S/kink type sulfate profile. We interpret the short lived ‘kink’ in the sulfate profiles as a result of recent enhancement in vertical methane flux possibly driven by reactivation of fault-fractures systems which provide the conduits for fluid flow.
id: 2306

Geological interpretation of a low-backscatter anomaly found on the New Jersey continental margin - Sweeney, Edward M.; Gardner, James V.; Johnson, Joel E.; Mayer, Larry A. (Marine Geology, 2012)
An enigmatic low-backscatter, acoustic anomaly occurs on the New Jersey continental margin between Hudson and Wilmington Canyon channels. The presence of the low-backscatter anomaly, as seen with 6.5- and 12-kHz data, indicates a change in the physical properties of the seafloor or near sub-surface. Analyses of seafloor and sub-surface acoustic data with previously collected sediment cores suggest the low-backscatter feature corresponds to an outcrop of older strata uncovered by erosion and non-deposition by the Western Boundary Undercurrent (WBUC). The decrease in backscatter strength is enhanced by the presence of gas in the sub-surface sediments found in the buried Chesapeake Drift.
id: 2328

Isotopic characterization of aerosol organic carbon components over the eastern United States - Wozniak, Andrew S.; Bauer, James E.; Dickhut, Rebecca M.; Xu, Li; McNichol, Ann P. (Journal of Geophysical Research-Atmospheres, 2012)
Carbon isotopic signatures (delta C-13, Delta C-14) of aerosol particulate matter total organic carbon (TOC) and operationally defined organic carbon (OC) components were measured in samples from two background sites in the eastern U. S. TOC and water-soluble OC (WSOC) delta C-13 values (-27 to -24 parts per thousand) indicated predominantly terrestrial C-3 plant and fossil derived sources. Total solvent extracts (TSE) and their aliphatic, aromatic, and polar OC components were depleted in delta C-13 (-30 to -26 parts per thousand) relative to TOC and WSOC. Delta C-14 signatures of aerosol TOC and TSE (-476 to +25 parts per thousand) suggest variable fossil contributions (similar to 5-50%) to these components. Aliphatic OC while comprising a small portion of the TOC (
id: 2252; PT: J; TC: 1; UT: WOS:000306237000001

An isotopic (Delta C-14, delta C-13, and delta N-15) investigation of the composition of particulate organic matter and zooplankton food sources in Lake Superior and across a size-gradient of aquatic systems - Zigah, P. K.; Minor, E. C.; Werne, J. P.; McCallister, S. Leigh (BIOGEOSCIENCES, 2012)
Food webs in aquatic systems can be supported both by carbon from recent local primary productivity and by carbon subsidies, such as material from terrestrial ecosystems, or past in situ primary productivity. The importance of these subsidies to respiration and biomass production remains a topic of debate. While some studies have reported that terrigenous organic carbon supports disproportionately high zooplankton production, others have suggested that phytoplankton preferentially support zooplankton production in aquatic ecosystems. Here we apply natural abundance radiocarbon (Delta C-14) and stable isotope (delta C-13, delta N-15) analyses to show that zooplankton in Lake Superior selectively incorporate recently fixed, locally produced (autochthonous) organic carbon even though other carbon sources are readily available. Estimates from Bayesian isotopic modeling based on Delta C-14 and delta C-13 values show that the average lake-wide median contributions of recent in-lake primary production and terrestrial, sedimentary, and bacterial organic carbon to the bulk POM in Lake Superior were 58%, 5%, 33%, and 3%, respectively. However, isotopic modeling estimates also show that recent in situ production contributed a disproportionately large amount (median, 91%) of the carbon in mesozooplankton biomass in Lake Superior. Although terrigenous organic carbon and old organic carbon from resuspended sediments were significant portions (median, 38%) of the available basal food resources, these contributed only a small amount to mesozooplankton biomass. Comparison of zooplankton food sources based on their radiocarbon composition showed that terrigenous organic carbon was relatively more important in rivers and small lakes, and the proportion of terrestrially derived material used by zooplankton correlated with the hydrologic residence time and the ratio of basin area to water surface area.

Loess mantle spatial variability and soil horizonation, southern Wisconsin, USA - Jacobs, Peter M.; Mason, Joseph A.; Hanson, Paul R. (Quaternary International, 2012)
Loess is an important Quaternary sediment that records evidence of landscape instability in sediment source areas and landscape stability in accumulation areas. In Wisconsin, USA loess mantles glaciogenic deposits dating to the last glaciation, but the landscape distribution and effects of the loess mantle on soil formation have received very little attention. This study investigates the influence of glacial landforms on the spatial pattern of loess thickness and how the presence or absence of a loess mantle overlying glaciogenic sediments has influenced soil profile morphology, namely thickness and nature of horizonation. Loess thickness follows systematic trends along hillslopes, with slope percentage explaining most loess thickness variation between summit and backslope positions. In the presence of a loess mantle, solum and Bt horizon thickness is proportional to the thickness of the loess mantle in well-drained profiles. In the absence of a loess mantle, landscape and sediment characteristics that control permeability and water throughflow appear to be the most important determinants of profile characteristics. The loess mantle modulates soil formation above the lithologic discontinuity with sandy calcareous glacial sediments by controlling soil water behavior and having physical and chemical characteristics conducive to transformation to soil genetic horizons.
id: 2151

The Medieval Climate Anomaly in the Iberian Peninsula reconstructed from marine and lake records - Moreno, Ana; Pérez, Ana; Frigola, Jaime; Nieto-Moreno, Vanesa; Rodrigo-Gámiz, Marta; Martrat, Belén; González-Sampériz, Penélope; Morellón, Mario; Martín-Puertas, Celia; Corella, Juan Pablo; Belmonte, Ánchel; Sancho, Carlos; et al. (Quaternary Science Reviews, 2012)
Selected multi-proxy and accurately dated marine and terrestrial records covering the past 2000 years in the Iberian Peninsula (IP) facilitated a comprehensive regional paleoclimate reconstruction for the Medieval Climate Anomaly (MCA: 900–1300 AD). The sequences enabled an integrated approach to land–sea comparisons and, despite local differences and some minor chronological inconsistencies, presented clear evidence that the MCA was a dry period in the Mediterranean IP. It was a period characterized by decreased lake levels, more xerophytic and heliophytic vegetation, a low frequency of floods, major Saharan eolian fluxes, and less fluvial input to marine basins. In contrast, reconstruction based on sequences from the Atlantic Ocean side of the peninsula indicated increased humidity. The data highlight the unique characteristics of the MCA relative to earlier (the Dark Ages, DA: ca 500–900 years AD) and subsequent (the Little Ice Age, LIA: 1300–1850 years AD) colder periods. The reconstruction supports the hypothesis of Trouet et al. (2009), that a persistent positive mode of the North Atlantic Oscillation (NAO) dominated the MCA.
id: 2334

Oxygen control on Holocene cold-water coral development in the eastern Mediterranean Sea - Fink, Hiske G.; Wienberg, Claudia; Hebbeln, Dierk; McGregor, Helen V.; Schmiedl, Gerhard; Taviani, Marco; Freiwald, André (Deep Sea Research Part I: Oceanographic Research Papers, 2012)
Continuous sedimentary records from an eastern Mediterranean cold-water coral ecosystem thriving in intermediate water depths (∼600 m) reveal a temporary extinction of cold-water corals during the Early to Mid Holocene from 11.4–5.9 cal kyr BP. Benthic foraminiferal assemblage analysis shows low-oxygen conditions of 2 ml l−1 during the same period, compared to bottom-water oxygen values of 4–5 ml l−1 before and after the coral-free interval. The timing of the corals' demise coincides with the sapropel S1 event, during which the deep eastern Mediterranean basin turned anoxic. Our results show that during the sapropel S1 event low oxygen conditions extended to the rather shallow depths of our study site in the Ionian Sea and caused the cold-water corals temporary extinction. This first evidence for the sensitivity of cold-water corals to low oceanic oxygen contents suggests that the projected expansion of tropical oxygen minimum zones resulting from global change will threaten cold-water coral ecosystems in low latitudes in the same way that ocean acidification will do in the higher latitudes.
id: 2140

Paleoenvironmental changes on the northeastern and southwestern Black Sea shelves during the Holocene - Ivanova, Elena V.; Murdmaa, Ivar O.; Karpuk, Maria S.; Schornikov, Eugene I.; Marret, Fabienne; Cronin, Thomas M.; Buynevich, Ilya V.; Platonova, Elena A. (Quaternary International, 2012)
Four paleoceanographic events are distinguished during the Holocene based on changes in macro- and microfossil assemblages studied from three sediment cores (Ak 521, 522, 2571) from the outer northeast shelf and from core MAR02-45 situated on the southwest shelf of the Black Sea, west to the Bosphorus. The lithology and fossils were previously studied from cores Ak 521 and Ak 522 and MAR02-45. However, high resolution ostracod analyses from the AMS-14C dated core, Ak 2571, allowed for a revision of the taxonomy and paleoecological interpretation of this microfaunal group on the NE shelf. Downcore changes in the relative abundance of the polyhaline ostracods are found to be contemporaneous in all three cores from the NE shelf. As a result, centennial-millennial scale fluctuations of the bottom-water salinity are resolved in the area. A broader scale examination of paleoenvironmental changes between the NE and SW shelves is also made and the surface to bottom salinity gradient is discussed. An uncalibrated radiocarbon based chronology is used throughout this paper to facilitate comparison with the regional chronostratigraphy of marine transgression and regressions in the Black Sea. The calibrated ages corrected for the changes in reservoir age through the Holocene are also provided. The first paleoceanographic event is associated with the pulse of Mediterranean water previously established at about 9.8–9.3 ka BP. This event is clearly observed in the SW region but not on the NE shelf due to a hiatus in the longest core, Ak 521. The second event is represented on both the NE and SW shelves as a replacement of brackish benthic fauna and surface phytoplankton with marine ones between 8.4 and 6.9 ka BP, indicating a gradual increase in salinity. The third event is marked by opposing trends in surface and bottom-water salinity changes. On the NE shelf, bottom-water salinity rose to modern values by ∼ 6.5 ka BP and then decreased within the interval ∼6.4–5.3 ka BP as recorded by the ostracod assemblages. On the SW shelf, surface-water salinity reached modern values by 5.6 ka BP and remained constant until present day as inferred from the dinoflagellate cyst assemblages. The fourth event is marked by a recurring increase in bottom-water salinity to modern values indicated by the polyhaline ostracod assemblages at ∼ 5.3 ka BP in the NE region, after which only minor salinity fluctuations are observed.
id: 2123

Pre-Columbian fire regimes in lowland tropical rainforests of southeastern Peru - McMichael, C. H.; Correa-Metrio, A.; Bush, M. B. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2012)
We document the fire history of the forests of a well-studied ecological research station (Los Amigos) in western Amazonia through soil charcoal analysis, and compare results with data from a nearby lake district known to have supported pre-Columbian human populations. We present novel methods of soil charcoal analysis that improve on its current limitations by accounting for variability in post-fire charcoal deposition, problematic age–depth relationships, and the presence of weathered or regionally-deposited charcoal particles that allow statistical comparisons of fire history characteristics between regions. The fire histories indicate that the research station experienced less intensive historical fire and pre-Columbian disturbance than the lake district. Dated charcoal particles indicated that while soil depth could not be used to predict fire age, fragments below 20 cm depth were generally older than 500 years. Frequent fires have not occurred in either region during the last 1000 years, but fire events in both regions were significantly synchronous from 1000 to 4000 cal. yr BP. The sampling design and methods that provide an ecologically and statistically valid avenue for comparing fire history characteristics between regions can be modified to suit other ecosystems. The results presented here establish confidence that the patterns and processes of the lowland tropical rainforests studied at Los Amigos are not affected by intense or recurrent historical fires. These data also suggest that forests of Madre de Dios, Peru are not post-successional remnants of a ‘cultural parkland’, as suggested by some Amazonian archeologists.
id: 2307

Radiocarbon and stable-isotope geochemistry of organic and inorganic carbon in Lake Superior - Zigah, Prosper K.; Minor, Elizabeth C.; Werne, Josef P. (GLOBAL BIOGEOCHEMICAL CYCLES, 2012)
We present a lake-wide investigation of Lake Superior carbon and organic matter biogeochemistry using radiocarbon, stable isotope, and carbon concentrations. Dissolved inorganic carbon (DIC) abundance in the lake was 121-122 Tg C, with offshore concentration and delta C-13 values being laterally homogenous and tightly coupled to the physical and thermal regime and biochemical processes. Offshore Delta C-14 of DIC (50-65%) exhibited lateral homogeneity and was more C-14 enriched than co-occurring atmospheric CO2 (similar to 38%); nearshore Delta C-14 of DIC (36-38%) was similar to atmospheric CO2. Dissolved organic carbon (DOC) abundance was 14.2-16.4 Tg C. DOC's concentration and delta C-13 were homogenous in June (mixed lake), but varied laterally during August (stratification) possibly due to spatial differences in lake productivity. Throughout sampling, DOC had modern radiocarbon values (14-58%) indicating a semilabile nature with a turnover time of <= 60 years. Lake particulate organic carbon (POC, 0.9-1.3 Tg C) was consistently C-13 depleted relative to DOC. The delta N-15 of epilimnetic particulate organic nitrogen shifted to more negative values during stratification possibly indicating greater use of nitrate (rather than ammonium) by phytoplankton in August. POC's radiocarbon was spatially heterogeneous (Delta C-14 range: 58% to - 303%), and generally C-14 depleted relative to DOC and DIC. POC C-14 depletion could not be accounted for by black carbon in the lake but, because of its spatial and temporal distribution, is attributed to sediment resuspension. The presence of old POC within the epilimnion of the open lake indicates possible benthic-pelagic coupling in the lake's organic carbon cycle; the ultimate fate of this old POC bears further investigation.

Radiocarbon evidence that carbon from the Deepwater Horizon spill entered the planktonic food web of the Gulf of Mexico - Chanton, J. P.; Cherrier, J.; Wilson, R. M.; Sarkodee-Adoo, J.; Bosman, S.; Mickle, A.; Graham, W. M. (ENVIRONMENTAL RESEARCH LETTERS, 2012)
The Deepwater Horizon (Macondo) oil spill released large volumes of oil and gas of distinct carbon isotopic composition to the northern Gulf of Mexico, allowing Graham et al (2010 Environ. Res. Lett. 5 045301) to use stable carbon isotopes (delta C-13) to infer the introduction of spilled oil into the planktonic food web. Surface ocean organic production and measured oil are separated by 5-7 parts per thousand in stable carbon isotope (delta C-13) space, while in radiocarbon (Delta C-14) space these two potential sources are separated by more than 1000 parts per thousand. Thus radiocarbon isotopes provide a more sensitive tracer by which to infer possible introduction of Macondo oil into the food web. We measured Delta C-14 and delta C-13 in plankton collected from within 100 km of the spill site as well as in coastal and offshore DIC (dissolved inorganic carbon or Sigma CO2) to constrain surface production values. On average, plankton values were depleted in C-14 relative to surface DIC, and we found a significant linear correlation between Delta C-14 and delta C-13 in plankton. Cumulatively, these results are consistent with the hypothesis that carbon released from the Deepwater Horizon spill contributed to the offshore planktonic food web. Our results support the findings of Graham et al (2010 Environ. Res. Lett. 5 045301), but we infer that methane input may be important.
Keywords: carbon isotope; Gulf oil spill; methane; petroleum hydrocarbon; radiocarbon

Radiocarbon evidence that carbon from the Deepwater Horizon spill entered the planktonic food web of the Gulf of Mexico - Chanton, J P; Cherrier, J; Wilson, R M; Sarkodee-Adoo, J; Bosman, S; Mickle, A; Graham, W M (Environmental Research Letters, 2012)
The Deepwater Horizon (Macondo) oil spill released large volumes of oil and gas of distinct carbon isotopic composition to the northern Gulf of Mexico, allowing Graham et al (2010 Environ. Res. Lett. 5 045301) to use stable carbon isotopes (δ13C) to infer the introduction of spilled oil into the planktonic food web. Surface ocean organic production and measured oil are separated by 5–7‰ in stable carbon isotope (δ13C) space, while in radiocarbon (Δ14C) space these two potential sources are separated by more than 1000‰. Thus radiocarbon isotopes provide a more sensitive tracer by which to infer possible introduction of Macondo oil into the food web. We measured Δ14C and δ13C in plankton collected from within 100 km of the spill site as well as in coastal and offshore DIC (dissolved inorganic carbon or ΣCO2) to constrain surface production values. On average, plankton values were depleted in 14C relative to surface DIC, and we found a significant linear correlation between Δ14C and δ13C in plankton. Cumulatively, these results are consistent with the hypothesis that carbon released from the Deepwater Horizon spill contributed to the offshore planktonic food web. Our results support the findings of Graham et al (2010 Environ. Res. Lett. 5 045301), but we infer that methane input may be important.

Radiocarbon Measurements in the Indian Ocean Aboard RVIB Nathaniel B. Palmer - Key, Robert M.; McNichol, Ann (Oceanography, 2012)
id: 2250; PT: J; TC: 0; SI: SI; UT: WOS:000308774600025

Sea surface temperature variability and sea-ice extent in the subarctic northwest Pacific during the past 15,000 years - Max, Lars; Riethdorf, Jan-Rainer; Tiedemann, Ralf; Smirnova, Maria; Lembke-Jene, Lester; Fahl, Kirsten; ürnberg, Dirk; Matul, Alexander; Mollenhauer, Gesine (Paleoceanography, 2012)
Past changes in North Pacific sea surface temperatures and sea-ice conditions are proposed to play a crucial role in deglacial climate development and ocean circulation but are less well known than from the North Atlantic. Here, we present new alkenone-based sea surface temperature records from the subarctic northwest Pacific and its marginal seas (Bering Sea and Sea of Okhotsk) for the time interval of the last 15 kyr, indicating millennial-scale sea surface temperature fluctuations similar to short-term deglacial climate oscillations known from Greenland ice core records. Past changes in sea-ice distribution are derived from relative percentage of specific diatom groups and qualitative assessment of the IP25biomarker related to sea-ice diatoms. The deglacial variability in sea-ice extent matches the sea surface temperature fluctuations. These fluctuations suggest a linkage to deglacial variations in Atlantic meridional overturning circulation and a close atmospheric coupling between the North Pacific and North Atlantic. During the Holocene the subarctic North Pacific is marked by complex sea surface temperature trends, which do not support the hypothesis of a Holocene seesaw in temperature development between the North Atlantic and the North Pacific.

Seasonal fluxes and source variation of organic carbon transported by two major Chinese Rivers: The Yellow River and Changjiang (Yangtze) River - Wang, Xuchen; Ma, Haiqing; Li, Ronghua; Song, Zhensu; Wu, Jinping (GLOBAL BIOGEOCHEMICAL CYCLES, 2012)
A one-year study was carried out to investigate the seasonal fluxes and source variation of organic carbon transported by two major Chinese rivers, the Yellow River and Changjiang. In 2009, the Yellow River and Changjiang transported 3.20 x 10(10) g and 1.58 x 10(12) g DOC and 3.89 x 10(11) g and 1.52 x 10(12) g POC, respectively. The dominant input of the terrestrial organic matter occurred during the high discharge period from June to July for the Yellow River and from June to August for Changjiang, accounting for 36-44% of the DOC and 72-86% of the POC transported by the two rivers in 2009. The Yellow River transported much higher concentrations of inorganic carbon than organic carbon, while a reverse trend was found in the Changjiang, indicating the different sources of carbon discharged by the two rivers. Using radiocarbon and stable carbon isotope measurements, we identified the different sources and seasonal variations of organic carbon transported by the Yellow River and Changjiang. The Yellow River carried old POC with radiocarbon ages ranging from 4000 to 8000 years, while POC transported by Changjiang had a relatively younger C-14 age ranging from 800 to 1060 years. The C-14 ages of DOC were relatively younger (305-1570 years) and showed less variation between the two rivers. The seasonal variations found in C-14 ages of DOC and POC indicate that a large fraction of recent-fixed labile organic carbon was transported by the two rivers in the spring and summer months. The different sources and seasonal variations in both fluxes and sources of organic carbon transported by the Yellow River and Changjiang could have an important influence on the biogeochemical cycle and ecosystems in the estuaries and adjacent coastal waters of the East China Sea.

A sedimentary-based history of hurricane strikes on the southern Caribbean coast of Nicaragua - McCloskey, Terrence Allen; Liu, Kam-biu (Quaternary Research, 2012)
Multi-millennial hurricane landfall records from the western North Atlantic indicate that landfall frequency has varied dramatically over time, punctuated by multi-centennial to millennial scale periods of hyperactivity. We extend the record geographically by presenting a paleostrike record inferred from a four-core transect from a marsh on the Caribbean coast of Nicaragua. Fossil pollen indicates that the site was a highly organic wetland from ~ 5400–4900 cal yr BP, at which time it became a shallow marine lagoon until ~ 2800 cal yr BP when it transitioned back into swamp/marsh, freshening over time, with the present fresh-to-brackish Typha marsh developing over the very recent past. Hurricane Joan, 1988, is recorded as a distinctive light-colored sand–silt–clay layer across the top of the transect, identifiable by abrupt shifts in color from the dark marsh deposits, increased grain size, and two upward-fining sequences, which are interpreted as representing the storm's traction and suspension loads. The six layers identified as hurricane-generated display temporal clustering, featuring a marked increase in landfall frequency ~ 800 cal yr BP. This pattern is anti-phase with the activity pattern previously identified from the northern Caribbean and the Atlantic coast of North America, thereby opposing the view that hyperactivity occurs simultaneously across the entire basin.
id: 2327

Small-scale lacustrine drifts in Lake Champlain, Vermont - Manley, Patricia L.; Manley, T. O.; Hayo, Kathryn; Cronin, Thomas (Journal of Great Lakes Research, 2012)
High resolution CHIRP (Compressed High Intensity Radar Pulse) seismic profiles reveal the presence of two lacustrine sediment drifts located in Lake Champlain's Juniper Deep. Both drifts are positive features composed of highly laminated sediments. Drift B sits on a basement high while Drift A is built on a trough-filling acoustically-transparent sediment unit inferred to be a mass-transport event. These drifts are oriented approximately north–south and are parallel to a steep ridge along the eastern shore of the basin. Drift A, located at the bottom of a structural trough, is classified as a confined, elongate drift that transitions northward to become a system of upslope asymmetric mudwaves. Drift B is perched atop a structural high to the west of Drift A and is classified as a detached elongate drift. Bottom current depositional control was investigated using Acoustic Doppler Current Profilers (ADCPs) located across Drift A. Sediment cores were taken at the crest and at the edges of the Drift A and were dated. Drift source, deposition, and evolution show that these drifts are formed by a water column shear with the highest deposition occurring along its crest and western flank and began developing circa 8700–8800 year BP.
id: 2179

Strengthening of the Northeast Monsoon over the Flores Sea, Indonesia, at the time of Heinrich event 1 - Muller, J.; McManus, J. F.; Oppo, D. W.; Francois, R. (Geology, 2012)
Paleoclimate evidence from South America and Asia has been interpreted to indicate that tropical rainfall migrated southward during the Northern Hemisphere cooling associated with Heinrich stadial 1 (HS1), an event of massive iceberg discharge to the North Atlantic ca. 18–15 ka. Although arid conditions associated with such a shift are well documented in southern Asia, as far south as Borneo, debate still exists regarding the precipitation response in southern Indonesia and Australia during HS1. This study utilizes concentrations of the long-lived nuclide 232Th as a proxy for detrital riverine input and 230Th normalization to estimate the history of preserved fluxes reaching the seafloor in the Flores Sea, located between southern Sulawesi and the Lesser Sunda Islands, Indonesia. Because the only source of 232Th to the ocean is continental minerals, this proxy is a robust indicator of continental weathering. The 230Th normalized burial fluxes of lithogenic and biogenic matter demonstrate that both detrital and biogenic fluxes in the Flores Sea were higher during HS1 than any other period in the past 22 k.y. High detrital fluxes indicate enhanced precipitation runoff from surrounding landmasses during a period of maximum southward shift of the Intertropical Convergence Zone. This study further constrains the northern limit of enhanced rainfall associated with a southward shift of Australian monsoon-related rainfall at the time of HS1 and highlights the value of 232Th as a proxy of continental input to deep-sea sediment records.

Test Drilling and Data Collection in the Calaveras County Portion of the Eastern San Joaquin Groundwater Subbasin, California , December 2009 – June 2011 - Metzger, L. F.; Izbicki, J. A.; Nawikas, J. M. (Open-File Report, 2012)

A two-dimensional, heart-cutting preparative gas chromatograph facilitates highly resolved single-compound isolations with utility towards compound-specific natural abundance radiocarbon (14C) analyses - Ball, Gregory Ian; Xu, Li; McNichol, Ann P.; Aluwihare, Lihini I. (Journal of Chromatography A, 2012)
Motivated by the need to develop clean, high purity preparative enrichments of individual compounds for micro-scale compound-specific natural abundance isotope and radiocarbon (14C) analyses, we describe a new, two-dimensional, heart-cutting, low-bleed, three-oven, single GC preparative system, demonstrate its resolving capabilities as applied to a typically complex environmental sample matrix, and investigate the robustness with which it preserves the authigenic 13C/12C and 14C/12C ratios of individual compounds it targets for preparative enrichment. The system is comprised of a programmable temperature vaporizing (PTV) inlet, a single GC oven, two modular, door-mounted, resistively heated low thermal mass (LTM) columns, a preparative fraction collector (PFC), and a Deans pneumatic switching device which facilitates heart-cutting between the system's 1° and 2° chromatographic dimensions. Further, the system's inlet and trapping parameters are optimized for the efficient preparative enrichment of the methyl ether and ester derivatives of the lignin phenol compound class. The lignin phenols include such compounds as the vanillyl and syringyl aldehydes, ethanones, and acids and are unrivaled biomarkers of terrestrial organic matter, some of which are also important components of fragrances and flavors. Using this suite of compounds, the suitability of this augmented preparative capillary GC (PCGC) system was investigated for micro-scale compound-specific (CS) stable isotope and natural abundance radiocarbon analyses (RA). Analysis of a >300 injection enrichment scheme reveals the instrument to fractionate 13C in predictable ways and to preserve the authigenic Δ14C of compounds it targets for preparative enrichment to within 6.7 ± 5.0‰, demonstrating the promising new utility of such systems towards micro-scale CSRA investigations for which clean and high resolution separation techniques are prerequisite.
id: 2152

Age determination of large live trees with inner cavities: radiocarbon dating of Platland tree, a giant African baobab - Patrut, Adrian; von Reden, Karl F.; Van Pelt, Robert; Mayne, Diana H.; Lowy, Daniel A.; Margineanu, Dragos (ANNALS OF FOREST SCIENCE, 2011)
Introduction For large trees without a continuous sequence of growth rings in their trunk, such as the African baobab (Adansonia digitata L.), the only accurate method for age determination is radiocarbon dating. As of today, this method was limited to dating samples collected from the remains of dead specimens. Methods Our research extends significantly the dating of such trees to large live specimens with inner cavities. The new approach is based on collecting samples from the cavities and their subsequent radiocarbon dating. Results The giant two-stemmed Platland tree, also known as Sunland baobab, was investigated by using this new approach. AMS radiocarbon dates of the oldest sample segments originating from the two inner cavities indicate that the large stem I (364.5 m(3)) is 750 +/- 75 years old, while the much smaller stem II (136.7 m(3)) has 1,060 +/- 75 years. Results also show that stem I is still growing very fast, while the older stem II slowed down consistently its growth over the past 250 years. The complete mapping of Platland tree determined an overall wood volume of 501.2 m(3). Conclusions Dating results demonstrate that the size-age relation cannot be used for estimating accurately the age of African baobabs.
Keywords: Accelerator mass spectrometry; Adansonia digitata; Age determination; Growth rate; Radiocarbon dating

Associated terrestrial and marine fossils in the late-glacial Presumpscot Formation, southern Maine, USA, and the marine reservoir effect on radiocarbon ages - Thompson, Woodrow B.; Griggs, Carol B.; Miller, Norton G.; Nelson, Robert E.; Weddle, Thomas K.; Kilian, Taylor M. (Quaternary Research, 2011)
Excavations in the late-glacial Presumpscot Formation at Portland, Maine, uncovered tree remains and other terrestrial organics associated with marine invertebrate shells in a landslide deposit. Buds of Populus balsamifera (balsam poplar) occurred with twigs of Picea glauca (white spruce) in the Presumpscot clay. Tree rings in Picea logs indicate that the trees all died during winter dormancy in the same year. Ring widths show patterns of variation indicating responses to environmental changes. Fossil mosses and insects represent a variety of species and wet to dry microsites. The late-glacial environment at the site was similar to that of today's Maine coast. Radiocarbon ages of 14 tree samples are 11,907 +/- 31 to 11,650 +/- 50 (14)C yr BP. Wiggle matching of dated tree-ring segments to radiocarbon calibration data sets dates the landslide occurrence at ca. 13,520 + 95/-20 cal yr BP. Ages of shells juxtaposed with the logs are 12,850 +/- 65 (14)C yr BP (Mytilus edulis) and 12,800 +/- 55 (14)C yr BP (Balanus sp.), indicating a marine reservoir age of about 1000 yr. Using this value to correct previously published radiocarbon ages reduces the discrepancy between the Maine deglaciation chronology and the varve-based chronology elsewhere in New England. (C) 2011 University of Washington. Published by Elsevier Inc. All rights reserved.
id: 2011; PT: J; UT: WOS:000290831500018

Bomb-produced radiocarbon validation of growth-increment crossdating allows marine paleoclimate reconstruction - Kastelle, Craig R.; Helser, Thomas E.; Black, Bryan A.; Stuckey, Matthew J.; C. Gillespie, Darlene; McArthur, Judy; Little, Diana; D. Charles, Karen; Khan, Reziah S. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2011)
The bivalve Pacific geoduck (Panopea generosa) has been used in the eastern North Pacific Ocean to create proxies for environmental factors such as temperature and oceanographic conditions. This type of research depends upon accurate age determination of Pacific geoducks, which historically was based on shell growth-increment counts. A recent study comparing age estimates generated by the dendrochronology (tree-ring science) procedure of crossdating to those estimated from growth-increment counts found a significant difference between the methods for geoduck older than 30 years. Compared to the traditional age determination method of counting growth increments, the crossdating method estimates a greater longevity in this species, with some individuals living in excess of 150 years. In the present study, the accuracy of each method was independently assessed using bomb-produced radiocarbon (14C) techniques. Specimens whose birth years were estimated to be within the era of the bomb-produced marine 14C increase and where the differences between ages estimated by the two methods were greatest were selected for 14C analysis. The difference between age estimates from traditional growth-increment counts and those from crossdating was evaluated using their respective 14C chronologies in comparisons to a reference chronology as a standard. The comparisons relied on Bayesian nonlinear models using Markov Chain Monte Carlo simulation. This method of analysis showed that with a 50% probability geoducks were aged correctly when using the crossdating method, compared to the growth increment counts which had a 50% probability of underestimating the age by 4 years. Therefore, the crossdated age estimates were found to be more accurate than increment counts. Furthermore, these results provide new confidence in using Pacific geoduck biochronologies for paleoclimate and paleoenvironmental reconstruction.
id: 2167

Climate related sea-level variations over the past two millennia - Kemp, A. C.; Horton, B. P.; Donnelly, J. P.; Mann, M. E.; Vermeer, M.; Rahmstorf, S. (Proc Natl Acad Sci U S A, 2011)
We present new sea-level reconstructions for the past 2100 y based on salt-marsh sedimentary sequences from the US Atlantic coast. The data from North Carolina reveal four phases of persistent sea-level change after correction for glacial isostatic adjustment. Sea level was stable from at least BC 100 until AD 950. Sea level then increased for 400 y at a rate of 0.6 mm/y, followed by a further period of stable, or slightly falling, sea level that persisted until the late 19th century. Since then, sea level has risen at an average rate of 2.1 mm/y, representing the steepest century-scale increase of the past two millennia. This rate was initiated between AD 1865 and 1892. Using an extended semiempirical modeling approach, we show that these sea-level changes are consistent with global temperature for at least the past millennium.
id: 853; Kemp, Andrew C Horton, Benjamin P Donnelly, Jeffrey P Mann, Michael E Vermeer, Martin Rahmstorf, Stefan Proc Natl Acad Sci U S A. 2011 Jul 5;108(27):11017-22. Epub 2011 Jun 20.3131350submittedY

The Deglacial Evolution of North Atlantic Deep Convection - Thornalley, David J. R.; Barker, Stephen; Broecker, Wallace S.; Elderfield, Henry; McCave, I. Nick (SCIENCE, 2011)
Deepwater formation in the North Atlantic by open-ocean convection is an essential component of the overturning circulation of the Atlantic Ocean, which helps regulate global climate. We use water-column radiocarbon reconstructions to examine changes in northeast Atlantic convection since the Last Glacial Maximum. During cold intervals, we infer a reduction in open-ocean convection and an associated incursion of an extremely radiocarbon (C-14)-depleted water mass, interpreted to be Antarctic Intermediate Water. Comparing the timing of deep convection changes in the northeast and northwest Atlantic, we suggest that, despite a strong control on Greenland temperature by northeast Atlantic convection, reduced open-ocean convection in both the northwest and northeast Atlantic is necessary to account for contemporaneous perturbations in atmospheric circulation.

Design and reality: Continuous-flow accelerator mass spectrometry (CFAMS) - von Reden, Karl F.; Roberts, Mark L.; McIntyre, Cameron P.; Burton, Joshua R. (Proceedings of the 10th European Conference on Accelerators in Applied Research and Technology (ECAART10), 2011)
In 2007 we published [1] the design of a novel accelerator mass spectrometry (AMS) system capable of analyzing gaseous samples injected continuously into a microwave plasma gas ion source. Obvious advantages of such a system are drastically reduced processing times and avoidance of potentially contaminating chemical preparation steps. Another paper in these proceedings will present the progress with the development of the microwave gas ion source that has since been built and tested at the National Ocean Sciences AMS Facility in Woods Hole [2]. In this paper we will review the original design and present updates, reflecting our recent encouraging experience with the system. A simple summary: large acceptance ion beam optics design is beneficial to accelerator mass spectrometry in general, but essential to AMS with plasma gas ion sources.
id: 2157

East–West similarities and differences in the surface and deep northern Arabian Sea records during the past 21 Kyr - Gupta, Anil K.; Mohan, K.; Sarkar, Sudipta; Clemens, Steven C.; Ravindra, Rasik; Uttam, Rajesh K. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2011)
This study analyses monsoon proxy Globigerina bulloides from Ocean Drilling Program (ODP) Hole 723A (western Arabian Sea) and Hole ABP-25, 02 (northeastern Arabian Sea) as well as dominant benthic foraminifera, pteropods, total organic carbon (TOC), Inorganic Carbon (IC) and stable isotope values of benthic foraminifera from Hole ABP-25, 02 to understand summer monsoon-driven changes in the western and eastern Arabian Sea and their impacts on deep-sea ventilation during the past 21 Kyr. We have also combined published TOC data from ODP Hole 724B to understand if deep-sea conditions in the Arabian Sea were same throughout the region during the studied interval. The summer monsoon was generally weaker during cold intervals including the Last Glacial Maximum, the Younger Dryas and the Bond events of the Holocene. From 20 to 10 Kyr, the deep northeastern Arabian Sea was better oxygenated with less organic carbon supply except during 14–12.5 Kyr when TOC values increased, indicating a weaker summer monsoon and a weak oxygen minimum zone (OMZ). The TOC values and the abundance of the eutrophic benthic foraminiferal species Bulimina aculeata, Melonis barleeanum and Uvigerina peregrina increased during the late Holocene whereas well-oxygenated, low organic carbon benthic species Sphaeroidina bulloides as well as pteropods decreased, indicating an intense OMZ and an increased supply of refractory organic material to the Arabian Sea. It is important to note that although the surface response to monsoon variability was more or less similar in the western and northeastern Arabian Sea, the deep-sea conditions show a marked contrast in the two regions during the past 21 Kyr.
id: 2100

Evidence of slumping/sliding in Krishna–Godavari offshore basin due to gas/fluid movements - Ramprasad, T.; Dewangan, P.; Ramana, M. V.; Mazumdar, A.; Karisiddaiah, S. M.; Ramya, E. R.; Sriram, G. (Occurrence and exploration of gas hydrate in the marginal seas and continental margin of the Asia, India and Oceania region Occurrence and exploration of gas hydrate in the marginal seas and continental margin of the Asia, India and Oceania region, 2011)
The Krishna–Godavari (KG) offshore basin is one of the promising petroliferous basins of the eastern continental margin of India. Drilling in this basin proved the presence of gas hydrate deposits in the shallow marine sediments beyond 750 m water depths, and provided lithologic and stratigraphic information. We obtained multibeam swath bathymetry covering an area of about 4500 km2 in water depths of 280–1800 m and about 1260 line km of high resolution seismic (HRS) records. The general lithology of midslope deposits is comprised of nannofossil-rich clay, nannofossil-bearing clay and foraminifera-bearing clay. The HRS records and bathymetry reveal evidence of slumping and sliding of the upper and midslope sediments, which result in mass transport deposits (MTD) in the northwestern part of the study area. These deposits exhibit 3–9.5 km widths and extend 10–13 km offshore. The boundaries of the MTDs are often demarcated by sharp truncation of finely layered sediments (FLS) and the MTDs are characterized by acoustically transparent zones in the HRS data. Average thickness of recent MTDs varies with depth, i.e., in the upper slope, the thickness is about 45 m, while in the lower slope it is about 60 m, and in deeper offshore locations they attain a maximum thickness of about 90 m. A direct indication for slumping and mass transportation of deposits is provided by the age reversal in 14C AMS dates observed in a sediment core located in the midslope region. Seismic profiling signatures provide indications of fluid/gas movement. We propose that the presence of steep topographic gradients, high sedimentation rates, a regional fault system, diapirism, fluid/gas movement, and neotectonic activity may have facilitated the slumping/sliding of the upper slope sediments in the KG offshore basin.
id: 2163

Evolution of a Pharaonic harbor on the Red Sea: Implications for coastal response to changes in sea level and climate - Hein, Christopher J.; FitzGerald, Duncan M.; Milne, Glenn A.; Bard, Kathryn; Fattovich, Rodolfo (GEOLOGY, 2011)
The evolution of coastal systems during the Holocene resulted from complex interactions and temporal shifts in the relative contribution of sea-level changes, climate change, and sedimentary processes. Along the Red Sea Coast, a 0.5-2 m highstand of sea level at 5 ka can be directly attributed to far-field effects resulting from the reduction in land ice following the last glacial maximum. At the ancient Egyptian harbor of Mersa/Wadi Gawasis, the site of the world's oldest archaeological evidence of long-distance seafaring, stratigraphic and geomorphologic evidence has been identified for this highstand. Here, wadi sediment input, enhanced by a period of wetter climate of the African Humid Period (early to mid-Holocene), forced the closure of coastal embayments, despite ongoing, relatively rapid sea-level rise. A stable, shallow bay persisted at Mersa/Wadi Gawasis as a result of coincidental aridization and a highstand of sea level during the mid-Holocene. This bay served as the primary harbor for ancient Egyptian trade along the Red Sea coast. During the late Holocene, shoreline progradation was dominated by sea-level fall, driven by isostatic processes. These results demonstrate the interplay of various global (sea level), regional (climate, sea level), and local (sedimentation, bathymetry) controls on the coastal evolution of the Red Sea and how these controls dictated the response of a complex civilization. Furthermore, they highlight the crucial role played by sedimentation in governing coastal response to changing sea levels.

Geology and Geoarchaeology of the Black Sea Region: Beyond the Flood Hypothesis - Buynevich, I. V.; Yanko-Hombach, V. V.; Gilbert, A. S.; and Martin, R. E. (Special papers (Geological Society of America), 2011)
id: 2127

Glacial to Holocene swings of the Australian-Indonesian monsoon - Mohtadi, Mahyar; Oppo, Delia W.; Steinke, Stephan; Stuut, Jan-Berend W.; De Pol-Holz, Ricardo; Hebbeln, Dierk; Lueckge, Andreas (Nature Geoscience, 2011)
The Australian-Indonesian monsoon is an important component of the climate system in the tropical Indo-Pacific region(1). However, its past variability, relation with northern and southern high-latitude climate and connection to the other Asian monsoon systems are poorly understood. Here we present high-resolution records of monsoon-controlled austral winter upwelling during the past 22,000 years, based on planktic foraminiferal oxygen isotopes and faunal composition in a sedimentary archive collected offshore southern Java. We show that glacial-interglacial variations in the Australian-Indonesian winter monsoon were in phase with the Indian summer monsoon system, consistent with their modern linkage through cross-equatorial surface winds. Likewise, millennial-scale variability of upwelling shares similar sign and timing with upwelling variability in the Arabian Sea. On the basis of element composition and grain-size distribution as precipitation-sensitive proxies in the same archive, we infer that (austral) summer monsoon rainfall was highest during the Bolling-Allerod period and the past 2,500 years. Our results indicate drier conditions during Heinrich Stadial 1 due to a southward shift of summer rainfall and a relatively weak Hadley cell south of the Equator. We suggest that the Australian-Indonesian summer and winter monsoon variability were closely linked to summer insolation and abrupt climate changes in the northern hemisphere.
id: 2012; PT: J; UT: WOS:000293277100016

Late glacial to Holocene sea-level changes in the Sea of Marmara: new evidence from high-resolution seismics and core studies - Eriş, Kürşad Kadir; Cagatay, M. N.; Akcer, Sena; Gasperini, Luca; Mart, Yosi (Geo-Marine Letters, 2011)
The late glacial to Holocene sedimentary record of the northern shelf of the Sea of Marmara (SoM) has been documented by detailed seismo-, chrono-, and biostratigraphic analyses using sub-bottom (Chirp) profiles and sediment cores. During MIS 3 and the main part of MIS 2 (60-15 (14)C ka b.p.), disconnection from the Mediterranean and Black seas together with a dry climate resulted in a regression in the SoM, when the Sea was transformed into a brackish lake. The river incisions below 105 m water depth along the northern shelf took place during the last glacial maximum, when the lake level was modulated by stillstands at -98 and -93 m. The post-glacial freshwater transgressive stage of the Marmara 'Lake' occurred between 15 and 13.5 (14)C ka b.p., leading to a rise in water level to -85 m by 13.0 (14)C ka b.p., as evidenced by broad wave-cut terraces along the northern shelf. Since 12 (14)C ka b.p., high-frequency sea-level fluctuations have been identified at the SoM entrance to the Strait of A degrees stanbul (SoI). Thus, wave-cut terraces have been recorded at water depths of -76 and -71 m that, according to an age model for core MD04-2750, have ages of 11.5 and 10.5 (14)C ka b.p., respectively. Ancient shoreline at -65 m along the northern shelf presumably formed soon after the Younger Dryas (YD) at ca. 10.1 (14)C ka b.p. Moreover, there is compelling evidence of Holocene outflow from the Sea of Marmara to the Black Sea. At the SoM entrance to the SoI, the existence of bioherms on the reflector surface together with abundant Brizalina spathulata and Protoglobulimina pupoides in a core suggests a return to higher salinities due to strong Mediterranean water incursion into the SoM at similar to 8.8 (14)C ka b.p. This finding is consistent with earlier suggestions that, after the YD, the Black Sea was flooded by outflow from the SoM as a result of global sea-level rise.
id: 2113; PT: J; TC: 0; J9: GEO-MAR LETT; UT: WOS:000286334700001

Late Holocene environmental conditions in Coronation Gulf, southwestern Canadian Arctic Archipelago: evidence from dinoflagellate cysts, other non-pollen palynomorphs, and pollen - Pieńkowski, A. J.; Mudie, Peta J.; England, John H.; Smith, John N.; Furze, Mark F. A. (Journal of Quaternary Science, 2011)
Boxcore 99LSSL-001 (68.095°?N, 114.186° W; 211?m water depth) from Coronation Gulf represents the first decadal-scale marine palynology and late Holocene sediment record for the southwestern part of the Northwest Passage. The record was studied for organic-walled microfossils (dinoflagellate cysts, non-pollen palynomorphs), pollen, terrestrial spores, and sediment characteristics. 210Pb, 137Cs, and three accelerator mass spectrometry 14C dates constrain the chronology. Three prominent palaeoenvironmental zones were identified. During the interval AD 1470?1680 (Zone I), the climate was warmer and wetter than at present, and environmental conditions were more favourable to biological activity and northward boreal forest migration, with reduced sea-ice and a longer open-water (growing) season. The interval AD 1680?1940 (Zone II) records sea-ice increase, and generally cool, polar conditions during the Little Ice Age. During AD 1940?2000 (Zone III), organic microfossils indicate an extended open-water season and decreased sea-ice, with suggested amelioration surpassing that of Zone I. Although more marine studies are needed to place this record into an appropriate context, the succession from ameliorated (Zone I) to cooler, sea-ice influenced conditions (Zone II) and finally to 20th-century warming (Zone III) corresponds well with several terrestrial climatic records from the neighbouring mainland and Victoria Island, and with lower-resolution marine records to the west. Copyright © 2011 John Wiley & Sons, Ltd.
id: 2344

Late Quaternary environmental change inferred from phytoliths and other soil-related proxies: Case studies from the central and southern Great Plains, USA - Cordova, Carlos E.; Johnson, William C.; Mandel, Rolfe D.; Palmer, Michael W. (Catena, 2011)
This study investigates stable carbon isotopes (delta(13)C), opal phytolith assemblages, burnt phytoliths, microscopic charcoal and Sporormiella spores from modern soils and paleosols in Kansas and Oklahoma. Grass and dicot phytoliths in combination with delta(13)C are used as proxies for reconstructing the structure of grasslands and woodlands. Burnt grass phytoliths and microscopic charcoal are evaluated as proxies for reconstructing paleofire incidence. Concentrations of the fungal spore Sporormiella are used as a proxy for assessing large herbivore activity. These proxies were tested on various modern grassland communities of the central and southern Great Plains, including areas with bison, cattle, and small herbivores, and areas under different fire frequencies. Opal phytolith assemblages and delta(13)C values show that before cal 11 ka, C(3) grasses and woody plants predominated in areas that today are dominated by C(4) grasses. The origin of the shortgrass prairie dates back to about cal 10 ka. The origin of the tallgrass prairie, however, is not clear as phytolith data show variable assemblages throughout the Holocene (mixed-grass, tallgrass, and tallgrass-woodland mosaic). Different proxies (burnt phytoliths vs. charcoal) reveal different fire frequencies, but it is apparent that microfossil evidence for fire incidence is closely related to the abundance of woody plants in the landscape. Before cal 12 ka, soils show somewhat elevated concentration of Spororrniella, but lower concentrations than the modern high-density bison and cattle grazing areas. Throughout the Holocene. Sporormiella frequencies are low, which suggests lower large ungulate densities and perhaps high mobility. (C) 2010 Elsevier B.V. All rights reserved.
id: 1992; PT: J; SI: SI; UT: WOS:000288642200002

The marine record of deglaciation of the South Shetland Islands, Antarctica since the Last Glacial Maximum - Simms, Alexander R.; Milliken, Kristy T.; Anderson, John B.; Wellner, Julia S. (Quaternary Science Reviews, 2011)
The marine geological record of the glacial-retreat history of the South Shetland Islands is derived from the integration of seismic data, core lithofacies, radiocarbon ages and geomorphological data from two study areas. On the northern shelf, we present one of the first published multibeam bathymetric images of the seafloor. This new image combined with descriptions of new and existing short sediment cores and high-resolution seismic data from the continental shelf north of King George Island are used to map a grounding zone wedge that marks the minimum seaward extent of the South Shetland Ice Cap during the Last Glacial Maximum. Seismic data, multibeam bathymetry, and sediment cores from Maxwell Bay, on the opposite side of King George Island, are used to provide further spatial constrains on the history of grounding and retreat of the ice cap along the southern margin of the South Shetland Islands. During the Last Glacial Maximum the South Shetland Ice Cap extended onto the outer continental shelf, some 50 km north of its present location. The ice grounded on the shelf in troughs in present water depths of almost 400 m. It had a minimum thickness of ∼570 m and was also grounded in the deepest part of fjords and straits between the islands. To the south, the ice cap extended seaward of the mouths of fjords and straits to the steep northern boundary of the Bransfield Strait. Sediment eroded from the fjords and straits was deposited in prominent fans that extend into the Bransfield Strait and show evidence for an ice shelf that covered the Bransfield Strait during the Last Glacial Maximum. A long drill core (SHALDRIL) in Maxwell Bay and several jumbo piston cores yielded carbonate material used to constrain the timing and spatial extent of glacial retreat within Maxwell Bay. The oldest glacimarine sediments in the fjord date back to ∼14.1 to ∼14.8 ka and suggest an initial deglaciation earlier than most previous studies of the South Shetland Islands. Upper Maxwell Bay was ice free by 9.1 ka and most of Maxwell Bay proper was ice free by 5.9 ka except for the smaller tributary fjords of Maxwell Bay. These smaller tributary fjords were ice free by 1.7 ka, but may have been ice free earlier but reoccupied by a neoglacial advance that ended approximately 1.7 ka.
id: 2181

Micropaleontologic record of Quaternary paleoenvironments in the Central Albemarle Embayment, North Carolina, U.S.A - Culver, Stephen J.; Farrell, Kathleen M.; Mallinson, David J.; Willard, Debra A.; Horton, Benjamin P.; Riggs, Stanley R.; Thieler, E. Robert; Wehmiller, John F.; Parham, Peter; Snyder, Scott W.; Hillier, Caroline (Palaeogeography, Palaeoclimatology, Palaeoecology, 2011)
To understand the temporal and spatial variation of eustatic sea-level fluctuations, glacio–hydro–isostacy, tectonics, subsidence, geologic environments and sedimentation patterns for the Quaternary of a passive continental margin, a nearly complete stratigraphic record that is fully integrated with a three dimensional chronostratigraphic framework, and paleoenvironmental information are necessary. The Albemarle Embayment, a Cenozoic regional depositional basin in eastern North Carolina located on the southeast Atlantic coast of the USA, is an ideal setting to unravel these dynamic, interrelated processes. Micropaleontological data, coupled with sedimentologic, chronostratigraphic and seismic data provide the bases for detailed interpretations of paleoenvironmental evolution and paleoclimates in the 90 m thick Quaternary record of the Albemarle Embayment. The data presented here come from a transect of cores drilled through a barrier island complex in the central Albemarle Embayment. This area sits in a ramp-like setting between late Pleistocene incised valleys. The data document the episodic infilling of the Albemarle Embayment throughout the Quaternary as a series of transgressive–regressive (T–R) cycles, characterized by inner shelf, midshelf, and shoreface assemblages, that overlie remnants of fluvial to estuarine valley-fill. Barrier island and marginal marine deposits have a low preservation potential. Inner to mid-shelf deposits of the early Pleistocene are overlain by similar middle Pleistocene shelf sediments in the south of the study area but entirely by inner shelf deposits in the north. Late Pleistocene marine sediments are of inner shelf origin and Holocene deposits are marginal marine in nature. Pleistocene marine sediments are incised, particularly in the northern half of the embayment by lowstand paleovalleys, partly filled by fluvial/floodplain deposits and in some cases, overlain by remnants of transgressive estuarine sediments. The shallowing through time of Quaternary sediments reflects the eastward progradational geometry of the continental shelf. The preservation potential of marginal marine deposits (barrier island, shoreface, backbarrier deposits) is not high, except in topographic lows associated with late Pleistocene paleovalleys and inlets because the current interglacial highstand has not yet reached its highest level. Given the documented increase in rate of relative sea-level rise in this region, shallow marine conditions are likely to return to the central Albemarle Embayment in the near future.
id: 2182

Paleoecology of mangroves along the Sibun River, Belize - Monacci, Natalie M.; Meier-Grünhagen, Ursula; Finney, Bruce P.; Behling, Hermann; Wooller, Matthew J. (Quaternary Research, 2011)
This study examines a sediment core (SR-63) from a mangrove ecosystem along the Sibun River in Belize, which is subject to both changes in sea-level and in the characteristics of the river's drainage basin. Radiocarbon dates from the core show a decreased sedimentation rate from ~ 6 ka to 1 cal ka BP and a marked change in lithology from primarily mangrove peat to fluvial-derived material at ~ 2.5 cal ka BP. Changes in the sedimentation rates observed in mangrove ecosystems offshore have previously been attributed to changes in relative sea-level and the rate of sea-level rise. Pollen analyses show a decreased abundance of Rhizophora (red mangrove) pollen and an increased abundance of Avicennia (black mangrove) pollen and non-mangrove pollen coeval with the decreased sedimentation rates. Elemental ratios ([N:C]a) and stable isotope analyses (δ15N and δ13C) show that changes in the composition of the organic material are also coeval with the change in lithology. The decrease in sedimentation rate at the site of core SR-63 and at offshore sites supports the idea that regional changes in hydrology occurred during the Holocene in Belize, influencing both mainland and offshore mangrove ecosystems.
id: 2099

Pontic-Baltic pathways for invasive aquatic species: geoarchaeological implications - Buynevich, I. V.; Damušytė, A.; Bitinas, A.; Olenin, S.; Mažeika, J.; Petrošius, R. (Geology and Geoarchaeology of the Black Sea Region: Beyond the Flood Hypothesis, 2011)
An accurate chronology for the exchange of aquatic species between water basins is important for paleoenvironmental reconstruction on both regional and continental scales. During the early Holocene, the range of zebra mussels, Dreissena polymorpha, was limited to the Black, Azov, Caspian, and Aral Seas, as well as the estuaries and lower and middle reaches of the Pontic-Caspian rivers. We present new findings that challenge the currently held view that this species migrated into the Baltic Sea watershed during the early 1800s through the canals joining the tributaries of rivers that drain into the Black and Baltic Sea basins. Geological investigations along the southeast Baltic Sea coast (Curonian and Vistula spits and lagoons) have uncovered shells of D. polymorpha that yielded radiocarbon ages older than 1000 radiocarbon yr B.P. We propose two scenarios to explain the new radiocarbon dates for D. polymorpha. The first scenario involves an anomalously large reservoir effect—as large as 600–800 yr—however, several lines of evidence cast doubt upon the validity of such a large reservoir correction. The second scenario that might explain the old zebra mussel ages is the earlier arrival of Dreissena polymorpha into the Baltic region. Natural exchange may have been facilitated by the proximity of the tributaries draining the Pontic and Baltic watersheds. Human-mediated transport is also considered in association with Viking voyages from the Baltic to the Black and Caspian Seas between A.D. 800 and 1000, and the riverine trade exchange during the Lithuanian expansion into the Pontic steppe in subsequent centuries. It is likely that both scenarios played a role, with implications for late Holocene biogeography and paleoecology of the Pontic-Caspian and Baltic basins.
id: 2122

The Posidonia oceanica marine sedimentary record: A Holocene archive of heavy metal pollution - Serrano, O.; Mateo, M. A.; Dueñas-Bohórquez, A.; Renom, P.; López-Sáez, J. A.; Martínez Cortizas, A. (Science of The Total Environment, 2011)
The study of a Posidonia oceanica mat (a peat-like marine sediment) core has provided a record of changes in heavy metal abundances (Fe, Mn, Ni, Cr, Cu, Pb, Cd, Zn, As and Al) since the Mid-Holocene (last 4470 yr) in Portlligat Bay (NW Mediterranean). Metal contents were determined in P. oceanica. Both, the concentration records and the results of principal components analysis showed that metal pollution in the studied bay started ca. 2800 yr BP and steadily increased until present. The increase in Fe, Cu, Pb, Cd, Zn and As concentrations since ca. 2800 yr BP and in particular during Greek (ca. 2680–2465 cal BP) and Roman (ca. 2150–1740 cal BP) times shows an early anthropogenic pollution rise in the bay, which might be associated with large- and short-scale cultural and technological development. In the last ca. 1000 yr the concentrations of heavy metals, mainly derived from anthropogenic activities, have significantly increased (e.g. from ~ 15 to 47 μg g− 1 for Pb, ~ 23 to 95 μg g− 1 for Zn and ~ 8 to 228 μg g− 1 for As). Our study demonstrates for the first time the uniqueness of P. oceanica meadows as long-term archives of abundances, patterns, and trends of heavy metals during the Late Holocene in Mediterranean coastal ecosystems.
id: 2098

Radiocarbon and 230Th data reveal rapid redistribution and temporal changes in sediment focussing at a North Atlantic drift - Mollenhauer, Gesine; McManus, Jerry F.; Wagner, Thomas; McCave, I. Nick; Eglinton, Timothy I. (Earth and Planetary Science Letters, 2011)
In locations of rapid sediment accumulation receiving substantial amounts of laterally transported material the timescales of transport and accurate quantification of the transported material are at the focus of intense research. Here we present radiocarbon data obtained on co-occurring planktic foraminifera, marine haptophyte biomarkers (alkenones) and total organic carbon (TOC) coupled with excess Thorium-230 (230Thxs) measurements on four sediment cores retrieved in 1649–2879m water depth from two such high accumulation drift deposits in the Northeast Atlantic, Björn and Gardar Drifts. While 230Thxs inventories imply strong sediment focussing, no age offsets are observed between planktic foraminifera and alkenones, suggesting that redistribution of sediments is rapid and occurs soon after formation of marine organic matter, or that transported material contains negligible amounts of alkenones. An isotopic mass balance calculation based on radiocarbon concentrations of co-occurring sediment components leads us to estimate that transported sediment components contain up to 12% of fossil organic matter that is free of or very poor in alkenones, but nevertheless appears to consist of a mixture of fresh and eroded fossil material. Considering all available constraints to characterize transported material, our results show that although focussing factors calculated from bulk sediment 230Thxs inventories may allow useful approximations of bulk redeposition, they do not provide a unique estimate of the amount of each laterally transported sediment component. Furthermore, our findings provide evidence that the occurrence of lateral sediment redistribution alone does not always hinder the use of multiple proxies but that individual sediment fractions are affected to variable extents by sediment focussing.

Radiocarbon and stable carbon isotopic insights into provenance and cycling of carbon in Lake Superior - Zigah, Prosper K.; Minor, Elizabeth C.; Werne, Josef P.; McCallister, S. Leigh (LIMNOLOGY AND OCEANOGRAPHY, 2011)
This study applies radiocarbon and stable carbon isotopic distributions to investigate carbon sources and cycling within Lake Superior. We report the radiocarbon (Delta C-14) and stable carbon isotope (delta C-13) values and the carbon concentrations within dissolved organic carbon (DOC), particulate organic carbon (POC), and dissolved inorganic carbon (DIC) in the lake's western basin water column. Samples were taken during spring mixing and late-summer thermal stratification over a 2-yr period (2007-2009). Distinct processes operating in the surface (photosynthesis) and deep waters (sediment resuspension and pore-water intrusion) control the relative contribution of modern and ancient DOC and POC in the water column. The terrigenous carbon input to the open lake POC varied from 13% +/- 4% during late summer stratification to 9% +/- 3% during spring mixing, with most of the terrestrial carbon being C-14-enriched (modern). The DIC reservoir cycles rapidly, with a bulk Delta C-14(DIC) value that records atmospheric radiocarbon levels from 3 yr prior to sampling. The DOC pool recycles on a longer time scale than does the DIC, with a DOC residence time of <= 60 yr. The suspended POC was in most cases older than co-occurring DOC, most likely as a result of resuspension of lake sediments.

Radiocarbon and Th-230 data reveal rapid redistribution and temporal changes in sediment focussing at a North Atlantic drift - Mollenhauer, Gesine; McManus, Jerry F.; Wagner, Thomas; McCave, I. Nick; Eglinton, Timothy I. (EARTH AND PLANETARY SCIENCE LETTERS, 2011)
In locations of rapid sediment accumulation receiving substantial amounts of laterally transported material the timescales of transport and accurate quantification of the transported material are at the focus of intense research. Here we present radiocarbon data obtained on co-occurring planktic foraminifera, marine haptophyte biomarkers (alkenones) and total organic carbon (TOC) coupled with excess Thorium-230 (Th-230(xs)) measurements on four sediment cores retrieved in 1649-2879 m water depth from two such high accumulation drift deposits in the Northeast Atlantic, Bjorn and Gardar Drifts. While Th-230(xs), inventories imply strong sediment focussing, no age offsets are observed between planktic foraminifera and alkenones, suggesting that redistribution of sediments is rapid and occurs soon after formation of marine organic matter, or that transported material contains negligible amounts of alkenones. An isotopic mass balance calculation based on radiocarbon concentrations of co-occurring sediment components leads us to estimate that transported sediment components contain up to 12% of fossil organic matter that is free of or very poor in alkenones, but nevertheless appears to consist of a mixture of fresh and eroded fossil material. Considering all available constraints to characterize transported material, our results show that although focussing factors calculated from bulk sediment Th-230(xs) inventories may allow useful approximations of bulk redeposition, they do not provide a unique estimate of the amount of each laterally transported sediment component. Furthermore, our findings provide evidence that the occurrence of lateral sediment redistribution alone does not always hinder the use of multiple proxies but that individual sediment fractions are affected to variable extents by sediment focussing. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: alkenones; compound-specific radiocarbon dating; drift sediments; focussing factors; Th-230(xs)

Rapid Holocene coastal change revealed by high-resolution micropaleontological analysis, Pamlico Sound, North Carolina, USA - Grand Pre, Candace; Culver, Stephen J.; Mallinson, David J.; Farrell, Kathleen M.; Corbett, D. Reide; Horton, Benjamin P.; Hillier, Caroline; Riggs, Stanley R.; Snyder, Scott W.; Buzas, Martin A. (Quaternary Research, 2011)
Foraminiferal analyses of 404 contiguous samples, supported by diatom, lithologic, geochronologic and seismic data, reveal both rapid and gradual Holocene paleoenvironmental changes in an 8.21-m vibracore taken from southern Pamlico Sound, North Carolina. Data record initial flooding of a latest Pleistocene river drainage and the formation of an estuary 9000 yr ago. Estuarine conditions were punctuated by two intervals of marine influence from approximately 4100 to 3700 and 1150 to 500 cal yr BP. Foraminiferal assemblages in the muddy sand facies that accumulated during these intervals contain many well-preserved benthic foraminiferal species, which occur today in open marine settings as deep as the mid shelf, and significant numbers of well-preserved planktonic foraminifera, some typical of Gulf Stream waters. We postulate that these marine-influenced units resulted from temporary destruction of the southern Outer Banks barrier islands by hurricanes. The second increase in marine influence is coeval with increased rate of sea-level rise and a peak in Atlantic tropical cyclone activity during the Medieval Climate Anomaly. This high-resolution analysis demonstrates the range of environmental variability and the rapidity of coastal change that can result from the interplay of changing climate, sea level and geomorphology in an estuarine setting.
id: 2164

Rapid radiocarbon ((14)C) analysis of coral and carbonate samples using a continuous-flow accelerator mass spectrometry (CFAMS) system - McIntyre, Cameron P.; Roberts, Mark L.; Burton, Joshua R.; McNichol, Ann P.; Burke, Andrea; Robinson, Laura F.; von Reden, Karl F.; W. J. Jenkins (Paleoceanography, 2011)
Radiocarbon analyses of carbonate materials provide critical information for understanding the last glacial cycle, recent climate history and paleoceanography. Methods that reduce the time and cost of radiocarbon ((14)C) analysis are highly desirable for large sample sets and reconnaissance type studies. We have developed a method for rapid radiocarbon analysis of carbonates using a novel continuous-flow accelerator mass spectrometry (CFAMS) system. We analyzed a suite of deep-sea coral samples and compared the results with those obtained using a conventional AMS system. Measurement uncertainty is
id: 1915; PT: J; UT: WOS:000296649300001

Rapid wetland expansion during European settlement and its implication for marsh survival under modern sediment delivery rates - Kirwan, M. L.; Murray, A. B.; Donnelly, J. P.; Corbett, D. R. (Geology, 2011)
Fluctuations in sea-level rise rates are thought to dominate the formation and evolution of coastal wetlands. Here we demonstrate a contrasting scenario in which land-use-related changes in sediment delivery rates drive the formation of expansive marshland, and vegetation feedbacks maintain their morphology despite recent sediment supply reduction. Stratigraphic analysis and radiocarbon dating in the Plum Island Estuary (Massachusetts, United States) suggest that salt marshes expanded rapidly during the eighteenth and nineteenth centuries due to increased rates of sediment delivery following deforestation associated with European settlement. Numerical modeling coupled with the stratigraphic observations suggests that existing marshland could survive, but not form under the low suspended sediment concentrations observed in the estuary today. These results suggest that many of the expansive marshes that characterize the modern North American coast are metastable relicts of high nineteenth century sediment delivery rates, and that recent observations of degradation may represent a slow return to pre-settlement marsh extent. In contrast to ecosystem management practices in which restoring pre-anthropogenic conditions is seen as a way to increase ecosystem services, our results suggest that widespread efforts to restore valuable coastal wetlands actually prevent some systems from returning to a natural state.
id: 846; 748TX Times Cited:2 Cited References Count:31under reviewY

Rates and Mechanisms of Mineral Carbonation in Peridotite: Natural Processes and Recipes for Enhanced, in situ CO 2 Capture and Storage - Kelemen, Peter B.; Matter, Juerg; Streit, Elisabeth E.; Rudge, John F.; Curry, William B.; Blusztajn, Jerzy (Annual Review of Earth and Planetary Sciences, 2011)
Near-surface reaction of CO2-bearing fluids with silicate minerals in peridotite and basalt forms solid carbonate minerals. Such processes form abundant veins and travertine deposits, particularly in association with tectonically exposed mantle peridotite. This is important in the global carbon cycle, in weathering, and in understanding physical-chemical interaction during retrograde metamorphism. Enhancing the rate of such reactions is a proposed method for geologic CO2 storage, and perhaps for direct capture of CO2 from near-surface fluids. We review, synthesize, and extend inferences from a variety of sources. We include data from studies on natural peridotite carbonation processes, carbonation kinetics, feedback between permeability and volume change via reaction-driven cracking, and proposed methods for enhancing the rate of natural mineral carbonation via in situ processes ("at the outcrop") rather than ex situ processes ("at the smokestack").

A regional-scale climate reconstruction of the last 4000 years from lakes in the Nebraska Sand Hills, USA - Schmieder, J.; Fritz, S.C.; Swinehart, J.B.; Shinneman, A.L.C.; Wolfe, A.P.; Miller, G.; Daniels, N.; Jacobs, K.C.; Grimm, E.C. (Quaternary Science Reviews, 2011)
High-resolution paleohydrological reconstructions were carried out in five shallow lakes in the Nebraska Sand Hills across an eastewest transect in order to 1) determine whether long-term droughts of the past 4000 years were spatially and temporally coherent across the region, 2) distinguish local variation in climate or hydrology from regional patterns of change, and 3) compare the paleolimnological results with the existing dune-inferred drought records. Diatom-inferred lake-level was reconstructed for all sites and compared with other regional records. Alterations between high and low lake-levels were frequent during the past 4000 years, which suggests that shifts between dry and wet periods were prevalent across the Sand Hills. Extended multi-decadal to centennial-scale droughts were more common prior to 2000 years BP, while the last two millennia were hydrologically more variable and climate conditions alternated on shorter timescales. Despite some discrepancies among the five records, the paleohydrological reconstructions refine the Holocene drought history of the Nebraska Sand Hills, particularly between w2200 and 4000 cal a BP. Many of the observed drought events are contemporaneous with severe droughts documented at sites in the northern Great Plains and Rocky Mountains, lending support for the severity and regional significance of these events in western North America.
Keywords: diatoms; Droughts; Great Plains; Holocene; lakes; Nebraska Sand Hills; paleolimnology

Repeated century-scale droughts over the past 13,000 yr near the Hudson River watershed, USA - Newby, Paige E.; Shuman, Bryan N.; Donnelly, Jeffrey P.; MacDonald, Dana (Quaternary Research, 2011)
Long-term sediment and ground-penetrating radar data from Davis Pond, a small lake near the Hudson River valley, reveal past droughts in a historically humid region that presently supplies water to millions of people in and around New York City. A minimum of eleven sandy paleoshoreline deposits in the lake date from 13.4 to 0.6 cal ka BP. The deposits span 1500 to 200 yr between bracketing radiocarbon ages, and intrude into lacustrine silts up to 9.0 m below the modern lake surface in a transect of six sediment cores. Three low stands, ca. 13.4–10.9, 9.2 and 8.2 cal ka BP indicate low regional moisture balance when low temperatures affected the North Atlantic region. Consistent with insolation trends, water levels rose from ca. 8.0 cal ka BP to present, but five low stands interrupted the rise and are likely associated with ocean–atmosphere interactions. Similar to evidence from other studies, the data from Davis Pond indicate repeated multi-century periods of prolonged or frequent droughts super-imposed on long-term regional trends toward high water levels. The patterns indicate that water supplies in this heavily populated region have continuously varied at multiple time scales and confirm that humid regions such as the northeastern United States are more prone to severe drought than historically expected.
id: 2183

Retreat of the East Antarctic ice sheet during the last glacial termination RID F-5711-2011 - Mackintosh, Andrew; Golledge, Nicholas; Domack, Eugene; Dunbar, Robert; Leventer, Amy; White, Duanne; Pollard, David; DeConto, Robert; Fink, David; Zwartz, Dan; Gore, Damian; Lavoie, Caroline (Nature Geoscience, 2011)
The retreat of the East Antarctic ice sheet at the end of the last glacial period has been attributed to both sea-level rise and warming of the ocean at the margin of the ice sheet, but it has been challenging to test these hypotheses. Given the lack of constraints on the timing of retreat, it has been difficult to evaluate whether the East Antarctic ice sheet contributed to meltwater pulse 1a, an abrupt sea-level rise of approximately 20 m that occurred about 14,700 years ago. Here we use terrestrial exposure ages and marine sedimentological analyses to show that ice retreat in Mac. Robertson Land, East Antarctica, initiated about 14,000 years ago, became widespread about 12,000 years ago, and was completed by about 7,000 years ago. We use two models of different complexities to assess the forcing of the retreat. Our simulations suggest that, although the initial stage of retreat may have been forced by sea-level rise, the majority of the ice loss resulted from ocean warming at the onset of the Holocene epoch. In light of our age model we conclude that the East Antarctic ice sheet is unlikely to have been the source of meltwater pulse 1a, and, on the basis of our simulations, suggest that Antarctic ice sheets made an insignificant contribution to eustatic sea-level rise at this time.
id: 2003; PT: J; UT: WOS:000287802300021

Siliceous productivity changes in Gulf of Ancud sediments (42°S, 72°W), southern Chile, over the last ∼150 years - Rebolledo, Lorena; González, Humberto E.; Muñoz, Praxedes; Iriarte, José L.; Lange, Carina B.; Pantoja, Silvio; Salamanca, Marco (Fjord Oceanography of the Chilean Patagonia, 2011)
We evaluated changes in siliceous export production and the source of organic matter preserved in sediment core MD07-3109H recovered from the Gulf of Ancud, Chiloé Inner Sea (42°S, 72°W, water column depth: 328 m), southern Chile. We analyzed the abundance of siliceous microfossils (diatoms, silicoflagellates, sponge spicules, Chrysophyte cysts, phytoliths), geochemical proxies (weight percent silicon %SiOPAL, organic carbon, total nitrogen, C/N molar), and sediment stable isotopes (δ13Corg, δ15N). Chronology based on 210Pb and 14C provided an accumulated age of 144 years at the base of the core. Sediments of core MD07-3109H are predominantly marine in origin, averaging δ13Corg=–20.75‰±0.82, δ15N=8.7±0.35‰, and C/N=8.76±0.36. Marine diatoms compose 94% of the total assemblage of siliceous microfossils. Our record of productivity based on the mass accumulation rates of organic carbon, total nitrogen, SiOPAL, and total diatoms showed high values between 1863 and 1869 AD followed by a declining trend until 1921 AD, a transition period from 1921 to 1959 AD with fluctuating values, and a clear decreasing pattern from 1960 AD to the present. This marked reduction in productivity was associated with decreased precipitation and Puelo River streamflow (41°S), as well as a warmer and more stratified water column, especially since the 1980s.
id: 2191

Solar modulation of North Atlantic central Water formation at multidecadal timescales during the late Holocene - Morley, Audrey; Schulz, Michael; Rosenthal, Yair; Mulitza, Stefan; Paul, André; Rühlemann, Carsten (Earth and Planetary Science Letters, 2011)
Understanding natural climate variability in the North Atlantic region is essential not only to assess the sensitivity of atmosphere–ocean climate signal exchange and propagation, but also to help distinguish between natural and anthropogenic climate change. The North Atlantic Oscillation is one of the controlling modes in recent variability of atmosphere–ocean linkages and ice/freshwater fluxes between the Polar and North Atlantic Ocean. Through these processes the NAO influences water mass formation and the strength of the Atlantic Meridional Overturning circulation and thereby variability in ocean heat transport. However, the impact of the NAO as well as other forcing mechanisms on multidecadal timescales such as total solar irradiance on Eastern North Atlantic Central Water production, central water circulation, and climate signal propagation from high to low latitudes in the eastern subpolar and subtropical basins remains uncertain. Here we use a 1200 yr long benthic foraminiferal Mg/Ca based temperature and oxygen isotope record from a ~ 900 m deep sediment core off northwest Africa to show that atmosphere–ocean interactions in the eastern subpolar gyre are transferred at central water depth into the eastern boundary of the subtropical gyre. Further we link the variability of the NAO (over the past 165 yrs) and solar irradiance (Late Holocene) and their control on subpolar mode water formation to the multidecadal variability observed at mid-depth in the eastern subtropical gyre. Our results show that eastern North Atlantic central waters cooled by up to ~ 0.8 ± 0.7 °C and densities decreased by σθ = 0.3 ± 0.2 during positive NAO years and during minima in solar irradiance during the Late Holocene. The presented records demonstrate the sensitivity of central water formation to enhanced atmospheric forcing and ice/freshwater fluxes into the eastern subpolar gyre and the importance of central water circulation for cross-gyre climate signal propagation during the Late Holocene.
id: 2175

Trace metal enrichments in Lake Tanganyika sediments: Controls on trace metal burial in lacustrine systems - Brucker, Rebecca Poulson; McManus, James; Severmann, Silke; Owens, Jeremy; Lyons, Timothy W. (Geochimica et Cosmochimica Acta, 2011)
We investigate the distributions of several key diagenetic reactants (C, S, Fe) and redox-sensitive trace metals (Mo, Cd, Re, U) in sediments from Lake Tanganyika, East Africa. This study includes modern sediments from a chemocline transect, which spans oxygenated shallow waters to sulfidic conditions at depth, as well as ancient sediments from a longer core (∼2 m) taken at ∼900 m water depth. Modern sediments from depths spanning ∼70–335 m are generally characterized by increasing enrichments of C, S, Mo, Cd, and U with increasing water depth but static Fe distributions. It appears that the sedimentary enrichments of these elements are, to varying degrees, influenced by a combination of organic carbon cycling and sulfur cycling. These modern lake characteristics contrast with a period of high total organic carbon (Corg), total sulfur (STot), and trace metal concentrations observed in the 900 m core, a period which follows the most recent deglaciation (∼18–11 ky). This interval is followed abruptly by an interval (∼11–6 ky) that is characterized by lower C, S, U, and Mo. Consistent with other work we suspect that the low concentrations of S, Mo, and U may indicate a period of intense lake mixing, during which time the lake may have been less productive and less reducing as compared to the present. An alternative, but not mutually exclusive, hypothesis is that changes in the lake’s chemical inventory, driven by significant hydrological changes, could be influencing the distribution of sedimentary trace elements through time.
id: 2144

Age and Growth Rate Dynamics of an Old African Baobab Determined by Radiocarbon Dating - Patrut, A.; Mayne, D. H.; von Reden, K. F.; Lowy, D. A.; Venter, S.; McNichol, A. P.; Roberts, M. L.; Margineanu, D. (Radiocarbon, 2010)
In 2008, a large African baobab (Adansonia digitata L.) from Makulu Makete, South Africa, split vertically into 2 sections, revealing a large enclosed cavity. Several wood samples collected from the cavity were processed and radiocarbon dated by accelerator mass spectrometry (AMS) for determining the age and growth rate dynamics of the tree. The C-14 date of the oldest sample was found to be of 1016 +/- 22 BP, which corresponds to a calibrated age of 1000 +/- 15 yr. Thus, the Makulu Makete tree, which eventually collapsed to the ground and died, becomes the second oldest African baobab dated accurately to at least 1000 yr. The conventional growth rate of the trunk, estimated by the radial increase, declined gradually over its life cycle. However, the growth rate expressed more adequately by the cross-sectional area increase and by the volume increase accelerated up to the age of 650 yr and remained almost constant over the past 450 yr.
Sp. Iss. 1696jn Times Cited:2 Cited References Count:21
Keywords: cal kyr bp; Calibration; southern-hemisphere

Aminostratigraphy of surface and subsurface Quaternary sediments, North Carolina coastal plain, USA - Wehmiller, J. F.; Thieler, E. R.; Miller, D.; Pellerito, V.; Keeney, V. B.; Riggs, S. R.; Culver, S.; Mallinson, D.; Farrell, K. M.; York, L. L.; Pierson, J.; Parham, P. R. (Quaternary Geochronology, 2010)
The Quaternary stratigraphy and geochronology of the Albemarle Embayment of the North Carolina (NC) Coastal Plain is examined using amino acid racemization (AAR) in marine mollusks, in combination with geophysical, lithologic, and biostratigraphic analysis of 28 rotasonic cores drilled between 2002 and 2006. The Albemarle Embayment is bounded by structural highs to the north and south, and Quaternary strata thin westward toward the Suffolk paleoshoreline, frequently referred to as the Suffolk Scarp. The Quaternary section is up to similar to 90 m thick, consists of a variety of estuarine, shelf, back-barrier, and lagoonal deposits, and has been influenced by multiple sea-level cycles. The temporal resolution of the amino acid racemization method is tested statistically and with the stratigraphic control provided by this geologic framework, and it is then applied to the correlation and age estimation of subsurface units throughout the region. Over 500 specimens (primarily Mercenaria and Mulinia) from the subsurface section have been analyzed using either gas chromatographic (GC) or reverse-phase liquid chromatographic (RPLC) techniques. The subsurface stratigraphic data are compared with AAR results from numerous natural or excavated exposures from the surrounding region, as well as results from NC beach collections, to develop a comprehensive aminostratigraphic database for the entire Quaternary record within the NC coastal system. Age mixing, recognized in the beach collections, is also seen in subsurface sections, usually where major seismic reflections or core lithology indicate the presence of stratigraphic discontinuities. Kinetic models for racemization are tested within the regional stratigraphic framework, using either radiocarbon or U-series calibrations or comparison with regional biostratigraphy. Three major Pleistocene aminozones [AZ2, AZ3, and AZ4] are found throughout the region, all being found in superposition in several cores. Each can be subdivided, yielding a total of at least eight stratigraphically and statistically distinct aminozones. Kinetic modeling, supplemented with local calibration, indicates that these aminozones represent depositional events ranging from similar to 80 ka to nearly 2 Ma. Three prominent seismic reflections are interpreted to represent the base of the early, middle, and late Pleistocene, respectively, roughly 2 Ma, 800 ka, and 130 ka. The large number of samples and the available stratigraphic control provide new insights into the capabilities and limitations of aminostratigraphic methods in assessing relative and numerical ages of Atlantic Coastal Plain Quaternary deposits. (C) 2009 Elsevier B.V. All rights reserved.
639btTimes Cited:19Cited References Count:82

Application of bacterial glycerol dialkyl glycerol tetraethers (GDGTs) to develop modern and past temperature estimates from New Zealand lakes - Zink, Klaus- G.; Vandergoes, Marcus J.; Mangelsdorf, Kai; Dieffenbacher-Krall, Ann C.; Schwark, Lorenz (Organic Geochemistry, 2010)
Branched isoalkyl glycerol dialkyl glycerol tetraethers (GDGTs) of bacterial origin have been found in high abundance in both modern and glacial sediments of New Zealand South Island freshwater lakes covering a wide range of altitude (101-2000 m). Like isoprenoid GDGTs of archaeal origin, they provide excellent potential for temperature assessment. For this study, their distribution patterns (MBT, methylation ratio and CBT, cyclisation ratio of branched GDGTs) have been successfully used to develop an initial temperature calibration for the study area and to provide preliminary (palaeo)environmental interpretations. MBT data from modern lake sediments correlate well with measured annual air temperature (R(2) 0 74), enabling a regional calibration for reconstructing palaeotemperatures for fossil samples. MBT-derived palaeotemperatures for Alpine Lake, calibrated against mean annual temperature, were determined for the Last Glacial during an early cold phase (between 29,000 and 26,000 years BP) and for later less cold phases (between 23,000 and 18,000 years BP). Compared with the modern temperature regime, the MBT data indicate a decrease of ca 56 and 2 8 degrees C respectively, during this time Modern and past MBT-derived temperatures correlate with chironomid-based temperature reconstructions in the area Archaeal GDGTs, commonly used for the TEX(86) index, are abundant in fossil sediments (Alpine Lake) but scarce in modern sediments, hindering a new local calibration for this palaeotemperature proxy. (C) 2010 Elsevier Ltd All rights reserved
id: 1955; PT: J; CT: 24th International Meeting on Organic Geochemistry; CY: SEP 06-11, 2009; CL: Bremen, GERMANY; UT: WOS:000282671500040

Assessing Microbial Uptake of Petroleum Hydrocarbons in Groundwater Systems Using Natural Abundance Radiocarbon - Ahad, Jason M. E.; Burns, Leanne; Mancini, Silvia; Slater, Greg F. (ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2010)
Carbon sources utilized by the active microbial communities in shallow groundwater systems underlying three petroleum service stations were characterized using natural abundance radiocarbon ((14)C). Total organic carbon (TOC) Delta(14)C values ranged from -314 to -972 parts per thousand and petroleum-extracted residues (EXT-RES) ranged from -293 to -971 parts per thousand. Phospholipid fatty acids (PLFAs)-biomarkers for active microbial populations-ranged from -405 to -885 parts per thousand and a comparison of these values with potential carbon sources pointed to significant microbial assimilation of (14)C-free fossil carbon. The most (14)C depleted PLFAs were found in the samples with the highest concentrations of total petroleum hydrocarbons (TPHs). A radiocarbon mass balance indicated up to 43% of the carbon in microbial PLFAs was derived from TPHs, providing direct evidence for biodegradation at two of three sites. At lower levels of TPHs. Delta(14)C values of PLFAs were generally similar to or more enriched than all other carbon in the system indicating microbial utilization of a more (14)C-enriched carbon source and no resolvable evidence for microbial incorporation of petroleum-derived carbon. Results from this study suggest that it is possible to delineate petroleum biodegradation in groundwater systems using these techniques even in complex situations where there exists a wide range in the ages of natural organic matter (i.e., EXT-RES).

Climatic controls of interannual variability in regional carbon fluxes from top-down and bottom-up perspectives RID B-8211-2009 - Desai, Ankur R.; Helliker, Brent R.; Moorcroft, Paul R.; Andrews, Arlyn E.; Berry, Joseph A. (Journal of Geophysical Research-Biogeosciences, 2010)
Observations of regional net ecosystem exchange (NEE) of CO(2) for 1997-2007 were analyzed for climatic controls on interannual variability (IAV). Quantifying IAV of regional (10(4)-10(6) km(2)) NEE over long time periods is key to understanding potential feedbacks between climate and the carbon cycle. Four independent techniques estimated monthly regional NEE for 10(4) km(2) in a spatially heterogeneous temperate-boreal transition region of the north central United States, centered on the Park Falls, Wisconsin, United States, National Oceanic and Atmospheric Administration tall tower site. These techniques included two bottom-up methods, based on flux tower upscaling and forest inventory based demographic modeling, respectively, and two top-down methods, based on tall tower equilibrium boundary layer budgets and tracer-transport inversion, respectively. While all four methods revealed a moderate carbon sink, they diverged significantly in magnitude. Coherence of relative magnitude and variability of NEE anomalies was strong across the methods. The strongest coherence was a trend of declining carbon sink since 2002. Most climatic controls were not strongly correlated with IAV. Significant controls on IAV were those related to hydrology, such as water table depth, and atmospheric CO(2). Weaker relationships were found with phenological controls such as autumn soil temperature. Hydrologic relationships were strongest with a 1 year lag, potentially highlighting a previously unrecognized predictor of IAV in this region. These results highlight a need for continued development of techniques to estimate regional IAV and incorporation of hydrologic cycling into couple carbon-climate models.
id: 1941; PT: J; UT: WOS:000277259700003

Coastal New England pilot study to determine fossil and biogenic formaldehyde source contributions using radiocarbon - Shen, Haiwei; Heikes, Brian G.; Merrill, John T.; McNichol, Ann P.; Xu, Li (JOURNAL OF GEOPHYSICAL RESEARCH-ATMOSPHERES, 2010)
Compound specific radiocarbon analyses of atmospheric formaldehyde are reported as fraction modern (Fm) for a limited number of winter and summer air samples collected in coastal southern New England in 2007. The 11 of 13 samples with Fm < 0.2 were collected under the influence of the semipermanent Bermuda high-pressure system with transport from the Washington, D. C., to New York City urban corridor. The two samples with Fm > 0.2 (max similar to 0.35) were collected on days with strong northwesterly flow and the least urban impact. The Fm data were combined with VOC observations from the Rhode Island Department of Environmental Management, estimates of oxygenated VOC (OVOC), and back trajectories to interpret the relative contributions of biogenic and fossil carbon sources. It is argued that CH2O sources were dominated by pollutant VOCs and OVOCs from upwind coastal cities as opposed to more local biogenic VOCs at the times of sample collection.

Comparative AMS radiocarbon dating of pretreated versus non-pretreated tropical wood samples - Patrut, Adrian; von Reden, Karl F.; Lowy, Daniel A.; Mayne, Diana H.; Elder, Kathryn E.; Roberts, Mark L.; McNichol, Ann P. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2010)
Several wood samples collected from Dorslandboom, a large iconic African baobab (Adansonia digitata L.) from Namibia, were investigated by AMS radiocarbon dating subsequent to pretreatment and, alternatively, without pretreatment. The comparative statistical evaluation of results showed that there were no significant differences between fraction modern values and radiocarbon dates of the samples analyzed after pretreatment and without pretreatment, respectively. The radiocarbon date of the oldest sample was 993 +/- 20 BP. Dating results also revealed that Dorslandboom is a multi-generation tree, with several stems showing different ages. (C) 2009 Elsevier B.V. All rights reserved.
id: 2083; PT: J; CT: 11th International Conference on Accelerator Mass Spectrometry; CY: SEP 14-19, 2008; CL: Rome, ITALY; SP: Univ Salento, CEDAD, Second Univ Naples, CIRCE, INNOVA, Ist Nazl Fis Nucl, LABEC, Abdus Salam Int Ctr Theoret Phys; UT: WOS:000277462300058

A Continuous-Flow Gas Chromatography C-14 Accelerator Mass Spectrometry System - McIntyre, C. P.; Galutschek, E.; Roberts, M. L.; von Reden, K. F.; McNichol, A. P.; Jenkins, W. J. (Radiocarbon, 2010)
Gas-accepting ion sources for radiocarbon accelerator mass spectrometry (AMS) have permitted the direct analysis of CO2 gas, eliminating the need to graphitize samples. As a result, a variety of analytical instruments can be interfaced to an AMS system, processing time is decreased, and smaller samples can be analyzed (albeit with lower precision). We have coupled a gas chromatograph to a compact C-14 AMS system fitted with a microwave ion source for real-time compound-specific C-14 analysis. As an initial test of the system, we have analyzed a sample of fatty acid methyl esters and biodiesel. Peak shape and memory was better then existing systems fitted with a hybrid ion source while precision was comparable. C-14/C-12 ratios of individual components at natural abundance levels were consistent with those determined by conventional methods. Continuing refinements to the ion source are expected to improve the performance and scope of the instrument.
Sp. Iss. 1696jn Times Cited:4 Cited References Count:24
Keywords: ams system; gc-ams; negative-ion source; RADIOCARBON ANALYSIS

Contrasting multiproxy reconstructions of surface ocean hydrography in the Agulhas Corridor and implications for the Agulhas Leakage during the last 345,000 years - Martinez-Mendez, Gema; Zahn, Rainer; Hall, Ian R.; Peeters, Frank J. C.; Pena, Leopoldo D.; Cacho, Isabel; Negre, Cesar (PALEOCEANOGRAPHY, 2010)
Planktonic delta(18)O and Mg/Ca-derived sea surface temperature (SST) records from the Agulhas Corridor off South Africa display a progressive increase of SST during glacial periods of the last three climatic cycles. The SST increases of up to 4 degrees C coincide with increased abundance of subtropical planktonic foraminiferal marker species which indicates a progressive warming due to an increased influence of subtropical waters at the core sites. Mg/Ca-derived SST maximizes during glacial maxima and glacial Terminations to values about 2.5 degrees C above full-interglacial SST. The paired planktonic delta(18)O and Mg/Ca-derived SST records yield glacial seawater delta(18)O anomalies of up to 0.8%, indicating measurably higher surface salinities during these periods. The SST pattern along our record is markedly different from a U(37)(K')-derived SST record at a nearby core location in the Agulhas Corridor that displays SST maxima only during glacial Terminations. Possible explanations are lateral alkenone advection by the vigorous regional ocean currents or the development of SST contrasts during glacials in association with seasonal changes of Agulhas water transports and lateral shifts of the Agulhas retroflection. The different SST reconstructions derived from U(37)(K') and Mg/Ca pose a significant challenge to the interpretation of the proxy records and demonstrate that the reconstruction of the Agulhas Current and interocean salt leakage is not as straightforward as previously suggested.

Controls on the age of terrigenous organic matter in Black Sea sediments - Kusch, Stephanie; Rethemeyer, Janet; Schefuß, Enno; Mollenhauer, Gesine (Geochimica et Cosmochimica Acta, 2010)
id: 885

Deepwater Formation in the North Pacific During the Last Glacial Termination - Okazaki, Y.; Timmermann, A.; Menviel, L.; Harada, N.; Abe-Ouchi, A.; Chikamoto, M. O.; Mouchet, A.; Asahi, H. (Science, 2010)
Between ~17,500 and 15,000 years ago, the Atlantic meridional overturning circulation weakened substantially in response to meltwater discharges from disintegrating Northern Hemispheric glacial ice sheets. The global effects of this reorganization of poleward heat flow in the North Atlantic extended to Antarctica and the North Pacific. Here we present evidence from North Pacific paleo surface proxy data, a compilation of marine radiocarbon age ventilation records, and global climate model simulations to suggest that during the early stages of the Last Glacial Termination, deep water extending to a depth of ~2500 to 3000 meters was formed in the North Pacific. A switch of deepwater formation between the North Atlantic and the North Pacific played a key role in regulating poleward oceanic heat transport during the Last Glacial Termination.

Eurasian Pastoralists And Their Shifting Regional Interactions at the Steppe Margin: Settlement History At Mukri, Kazakhstan - Frachetti, M.; Benecke, N.; Mar’yashev, A. N.; Doumani, P. (World Archaeology, 2010)
id: 1880In Press

Fire History of a Giant African Baobab Evinced by Radiocarbon Dating - Patrut, A.; Mayne, D. H.; von Reden, K. F.; Lowy, D. A.; van Pelt, R.; McNichol, A. P.; Roberts, M. L.; Margineanu, D. (Radiocarbon, 2010)
The article reports the first radiocarbon dating of a live African baobab (Adansonia digitata L.), by investigating wood samples collected from 2 inner cavities of the very large 2-stemmed Platland tree of South Africa. Some 16 segments extracted from determined positions of the samples, which correspond to a depth of up to 15-20 cm in the wood, were processed and analyzed by accelerator mass spectrometry (AMS). Calibrated ages of segments are not correlated with their positions in the stems of the tree. Dating results indicate that the segments originate from new growth layers, with a thickness of several centimeters, which cover the original old wood. Four new growth layers were dated before the reference year AD 1950 and 2 layers were dated post-AD 1950, in the post-bomb period. Formation of these layers was triggered by major damage inside the cavities. Fire episodes are the only possible explanation for such successive major wounds over large areas or over the entire area of the inner cavities of the Platland tree, able to trigger regrowth.
Sp. Iss. 1696jn Times Cited:11 Cited References Count:28
Keywords: age calibration; bomb c-14 data; bombacaceae; cal kyr bp; southern-hemisphere; system

Freshwater Outburst from Lake Superior as a Trigger for the Cold Event 9300 Years Ago - Yu, Shi-Yong; Colman, Steven M.; Lowell, Thomas V.; Milne, Glenn A.; Fisher, Timothy G.; Breckenridge, Andy; Boyd, Matthew; Teller, James T. (Science, 2010)
Paleoclimate proxy records reveal a pervasive cooling event with a Northern Hemispheric extent similar to 9300 years ago. Coeval changes in the oceanic circulation of the North Atlantic imply freshwater forcing. However, the source, magnitude, and routing of meltwater have remained unknown. Located in central North America, Lake Superior is a key site for regulating the outflow of glacial meltwater to the oceans. Here, we show evidence for an similar to 45-meter rapid lake-level fall in this basin, centered on 9300 calibrated years before the present, due to the failure of a glacial drift dam on the southeast corner of the lake. We ascribe the widespread climate anomaly similar to 9300 years ago to this freshwater outburst delivered to the North Atlantic Ocean through the Lake Huron-North Bay-Ottawa River-St. Lawrence River valleys.
id: 1950; PT: J; UT: WOS:000278318600030

Geology of Lonar Crater, India - Maloof, A. C.; Stewart, S. T.; Weiss, B. P.; Soule, S. A.; Swanson-Hysell, N. L.; Louzada, K. L.; Garrick-Bethell, I.; Poussart, P. M. (Geological Society of America Bulletin, 2010)
Lonar Crater, India, is one of the youngest and best preserved impact structures on Earth. The 1.88-km-diameter simple crater formed entirely within the Deccan traps, making it a useful analogue for small craters on the basaltic surfaces of the other terrestrial planets and the Moon. In this study, we present a meter-scale-resolution digital elevation model, geological map of Lonar Crater and the surrounding area, and radiocarbon ages for histosols beneath the distal ejecta. Impact-related deformation of the target rock consists of upturned basalt flows in the upper crater walls and recumbent folding around rim concentric, subhorizontal, non-cylindrical fold axes at the crater rim. The rim-fold hinge is preserved around 10%-15% of the crater. Although tearing in the rim-fold is inferred from field and palcomagnetic observations, no tear faults are identified, indicating that large displacements in the crater walls are not characteristic of small craters in basalt. One significant normal fault structure is observed in the crater wall that offsets slightly older layer-parallel slip faults. There is little fluvial erosion of the continuous ejecta blanket. Portions of the ejecta blanket are overlain by aerodynamically and rotationally sculpted glassy impact spherules, in particular in the eastern and western rim, as well as in the depression north of the crater known as Little Lonar. The emplacement of the continuous ejecta blanket can be likened to a radial ground-hugging debris flow, based on the preserved thickness distribution of the ejecta, the efficient exchange of clasts between the ejecta flow and the underlying histosol, and the lack of sorting and stratification in the bulk of the ejecta. The ejecta profile is thickened at the distal edge and similar to fluidized ejecta structures observed on Mars.
id: 1846; 539YI Times Cited:0 Cited References Count:100Y

Growth rates, stable oxygen isotopes (delta(18)O), and strontium (Sr/Ca) composition in two species of Pacific sclerosponges (Acanthocheatetes wellsi and Astrosclera willeyana) with delta(18)O calibration and application to paleoceanography - Grottoli, Andrea G.; Adkins, Jess F.; Panero, Wendy R.; Reaman, Daniel M.; Moots, Kate (Journal of Geophysical Research-Oceans, 2010)
The isotopic and elemental composition of sclerosponge skeletons is used to reconstruct paleoceanographic records. Yet few studies have systematically examined the natural variability in sclerosponge skeletal delta(18)O, growth, and Sr/Ca, and how that may influence the interpretation of sclerosponge proxy records. Here, we analyzed short records in seven specimens of Acanthocheatetes wellsi (high-Mg calcite, 21 mol% Mg) from Palau, four A. wellsi (high-Mg calcite, 21 mol% Mg) from Saipan, and three Astrosclera willeyana (aragonite) sclerosponges from Saipan, as well as one long record in an A. wellsi specimen from Palau spanning 1945-2001.5. In Saipan, species-specific and mineralogical effects appear to have a negligible effect on sclerosponge delta(18)O, facilitating the direct comparison of delta(18)O records between species at a given location. At both sites, A. wellsi delta(18)O and growth rates were sensitive to environmental conditions, but Sr/Ca was not sensitive to the same conditions. High-resolution delta(18)O analyses confirmed this finding as both A. wellsi and A. willeyana deposited their skeleton in accordance with the trends in isotopic equilibrium with seawater, though with a 0.27% offset in the case of A. willeyana. In the high-Mg-calcite species A. wellsi, Mg may be interfering with Sr incorporation into the skeleton. On multidecadal timescales, A. wellsi sclerosponge delta(18)O in Palau tracked the Southern Oscillation Index variability post-1977, but not pre-1977, coincident with the switch in the Pacific Decadal Oscillation (PDO) at similar to 1976. This suggests that water mass circulation in the region is influenced by El Nino-Southern Oscillation variability during positive PDO phases, but not during negative ones.
id: 1962; PT: J; UT: WOS:000278735700001

A High-Performance (14)c Accelerator Mass Spectrometry System - Roberts, M. L.; Burton, J. R.; Elder, K. L.; Longworth, B. E.; McIntyre, C. P.; von Reden, K. F.; Han, B. X.; Rosenheim, B. E.; W. J. Jenkins; Galutschek, E.; McNichol, A. P. (Radiocarbon, 2010)
A new and unique radiocarbon accelerator mass spectrometry (AMS) facility has been constructed at the Woods Hole Oceanographic Institution. The defining characteristic of the new system is its large-gap optical elements that provide a larger-than-standard beam acceptance. Such a system is ideally suited for high-throughput, high-precision measurements of (14)C. Details and performance of the new system are presented.
id: 2095; PT: J; CT: 20th International Radiocarbon Conference; CY: MAY 31-JUN 05, 2009; CL: Big Isl, HI; SI: 1; UT: WOS:000285437800005

Implications for chloro- and pheopigment synthesis and preservation from combined compound-specific δ13C, δ15N, and Δ14C analysis - Kusch, S.; Kashiyama, Y.; Ogawa, N. O.; Altabet, M.; Butzin, M.; Friedrich, J.; Ohkouchi, N.; Mollenhauer, G. (Biogeosciences, 2010)
Chloropigments and their derivative pheopigments preserved in sediments can directly be linked to photosynthesis. Their carbon and nitrogen stable isotopic compositions have been shown to be a good recorder of recent and past surface ocean environmental conditions tracing the carbon and nitrogen sources and dominant assimilation processes of the phytoplanktonic community. In this study we report results from combined compound-specific radiocarbon and stable carbon and nitrogen isotope analysis to examine the time-scales of synthesis and fate of chlorophyll-a and its degradation products pheophytin-a, pyropheophytin-a, and 132,173-cyclopheophorbide-a-enol until burial in Black Sea core-top sediments. The pigments are mainly of marine phytoplanktonic origin as implied by their stable isotopic compositions. Pigment delta15N values indicate nitrate as the major uptake substrate but 15N-depletion towards the open marine setting indicates either contribution from N2-fixation or direct uptake of ammonium from deeper waters. Radiocarbon concentrations translate into minimum and maximum pigment ages of approximately 40 to 1200 years. This implies that protective mechanisms against decomposition such as association with minerals, storage in deltaic anoxic environments, or eutrophication-induced hypoxia and light limitation are much more efficient than previously thought. Moreover, seasonal variations of nutrient source, growth period, and habitat and their associated isotopic variability are likely at least as strong as long-term trends. Combined triple isotope analysis of sedimentary chlorophyll and its primary derivatives is a powerful tool to delineate biogeochemical and diagenetic processes in the surface water and sediments, and to assess their precise time-scales.

Investigating the influence of hydrogeomorphic setting on the response of lake sedimentation to climatic changes in the Uinta Mountains, Utah, USA - Corbett, Lee B.; Munroe, Jeffrey S. (Journal of Paleolimnology, 2010)
Reader Lake and Elbow Lake, two high-altitude lakes in the Uinta Mountains of Utah, are located approximately 2 km apart, at similar elevations, and within identical vegetation communities. Loss on ignition, carbon to nitrogen ratios, biogenic silica, and sediment grain size were analyzed throughout percussion cores retrieved from both lakes to construct continuous time series spanning 14 to ca. 2 ka BP. Given the proximity of the lakes, it is assumed that both were subjected to the same climatic forcing over this time. Accordingly, the first goal of this study was to consider these two multiproxy datasets in concert to yield an integrated paleoclimate record for this region. Close inspection of the records identified discrepancies indicating that the lakes responded to climate changes in different ways despite their proximity and similar setting. Clarifying these differences and understanding why the two lakes behaved differently at certain times was the second goal of this study. Overall, the paleoclimatic records document lake formation in the latest Pleistocene following glacier retreat. Buried glacier ice at the location of Reader Lake may have persisted through the Younger Dryas. Both lakes became biologically productive ca. 11.5 ka BP, and the first appearance of conifer needles indicates that trees had replaced alpine tundra in these watersheds by 10.5 ka BP. The interval from 10 to 6 ka BP was marked by a dramatic increase in precipitation, perhaps related to enhanced monsoonal circulation driven by the insolation maximum. The two lakes recorded this event in notably contrasting ways given their differing hydrogeomorphic settings. Precipitation decreased from 6 to 4 ka BP, and low water levels and drought conditions marked the interval from 4.0 to 2.7 ka BP. The integrated paleoclimate record developed from these cores provides a useful point of comparison with other records from the region. The differences between the records from these closely spaced lakes underscore the need to consider hydrogeomorphic setting when evaluating the suitability of a lake for a paleolimnological study.
id: 2013; PT: J; UT: WOS:000277939200023

Late-twentieth-century warming in Lake Tanganyika unprecedented since AD 500 - Tierney, Jessica E.; Mayes, Marc T.; Meyer, Natacha; Johnson, Christopher; Swarzenski, Peter W.; Cohen, Andrew S.; Russell, James M. (Nature Geoscience, 2010)
Instrumental observations suggest that Lake Tanganyika, the largest rift lake in East Africa, has become warmer, increasingly stratified and less productive over the past 90 years (refs 1,2). These trends have been attributed to anthropogenic climate change. However, it remains unclear whether the decrease in productivity is linked to the temperature rise(3,4), and whether the twentieth-century trends are anomalous within the context of longer-term variability. Here, we use the TEX(86) temperature proxy, the weight per cent of biogenic silica and charcoal abundance from Lake Tanganyika sediment cores to reconstruct lake-surface temperature, productivity and regional wildfire frequency, respectively, for the past 1,500 years. We detect a negative correlation between lake-surface temperature and primary productivity, and our estimates of fire frequency, and hence humidity, preclude decreased nutrient input through runoff as a cause for observed periods of low productivity. We suggest that, throughout the past 1,500 years, rising lake-surface temperatures increased the stratification of the lake water column, preventing nutrient recharge from below and limiting primary productivity. Our records indicate that changes in the temperature of Lake Tanganyika in the past few decades exceed previous natural variability. We conclude that these unprecedented temperatures and a corresponding decrease in productivity can be attributed to anthropogenic global warming, with potentially important implications for the Lake Tanganyika fishery.
id: 2043; PT: J; UT: WOS:000278134100019

Long-term stability in the production of a NW Mediterranean Posidonia oceanica (L.) Delile meadow - Mateo, M. A.; Renom, P.; Michener, R. H. (Palaeogeography Palaeoclimatology Palaeoecology, 2010)
Long-term changes in leaf net production of the seagrass Posidonia oceanica (L) Defile. and in the irradiance arriving at the meadow canopy, were investigated in a NW Mediterranean meadow using a palaeoecological approach. We conducted in situ shade experiments to find the relationships between the carbon stable isotope ratio (delta(13)C) of plant tissues, leaf net production, and ambient irradiance. The relationships were highly significant and fitted the Michaelis-Menten equation and power functions. These functions were used to reconstruct light and net production using the delta(13)C of P. oceanica detritus as a palaeoecological proxy along a 150 cm core of P. oceanica matte (a peat-like deposit formed by this endemic seagrass species). The delta(13)C values of sheath detritus along the core (i.e.. the net leaf production) showed a weak but significant decrease towards the present time (R = 0.308: P = 0.02) probably as a result of (1) an increase in DIC availability, and/or (2) a progressive change in the carbon isotopic signature of DIC, both of which are consistent with a rise in anthropogenic atmospheric CO(2). The canopy irradiance, reconstructed for the last 1200 years, showed a mean value of 128 mu E m(-2) s(-1) with a range of 12.5-280 mu E m(-2) s(-1). The reconstruction of the net leaf production for the same period yielded a mean value of 2.5 mg dw day(-1) shoot(-1) with a range of 2.0-2.7 mg dw day(-1) shoot(-1). Both ranges are within the values reported in the literature for present day studies. The absence of significant fluctuations or sudden changes through time suggests remarkable ecosystem stability during the last millennium. (C) 2010 Elsevier B.V. All rights reserved.
id: 1911; 611AI Times Cited:3 Cited References Count:116Y

Microbial carbon cycling in oligotrophic regional aquifers near the Tono Uranium Mine, Japan as inferred from delta(13)C and Delta(14)C values of in situ phospholipid fatty acids and carbon sources - Mills, Christopher T.; Amano, Yuki; Slater, Gregory F.; Dias, Robert F.; Iwatsuki, Teruki; Mandernack, Kevin W. (Geochimica et Cosmochimica Acta, 2010)
Microorganisms are ubiquitous in deep subsurface environments, but their role in the global carbon cycle is not well-understood. The natural abundance delta(13)C and Delta(14)C values of microbial membrane phospholipid fatty acids (PLFAs) were measured and used to assess the carbon sources of bacteria in sedimentary and granitic groundwaters sampled from three boreholes in the vicinity of the Tono Uranium Mine, Gifu, Japan. Sample storage experiments were performed and drill waters analyzed to characterize potential sources of microbial contamination. The most abundant PLFA structures in all waters sampled were 16:0,16:1 omega 7c, cy17:0, and 18:1 omega 7c. A PLFA biomarker for type 11 methanotrophs, 18:1 omega 8c, comprised 3% and 18% of total PLFAs in anoxic sedimentary and granitic waters, respectively, sampled from the KNA-6 borehole. The presence of this biomarker was unexpected given that type II methanotrophs are considered obligate aerobes. However, a bacterium that grows aerobically with CH(4) as the sole energy source and which also produces 56% of its total PLFAs as 18:1 omega 8c was isolated from both waters, providing additional evidence for the presence of type II methanotrophs. The Delta(14)C values determined for type II methanotroph PLFAs in the sedimentary (-86 parts per thousand) and granite (-867 parts per thousand) waters were very similar to the Delta(14)C values of dissolved inorganic carbon (DIC) in each water (similar to-850 parts per thousand). This suggests that type II methanotrophs ultimately derive all their carbon from inorganic sources, whether directly from DIC and/or from CH4 produced by the reduction of DIC. In contrast, delta(13)C values of type II PLFAs in the sedimentary (-93 parts per thousand) and granite (-60 parts per thousand) waters indicate that these organisms use different carbon assimilation schemes in each environment despite very similar delta(13)C(CH4) values (-similar to 95 parts per thousand) for each water. The delta(13)C(PLFA) values (-28 parts per thousand to -45 parts per thousand) of non-methanotrophic bacteria in the KNA-6 LTL water do not clearly distinguish between heterotrophic and autotrophic metabolisms, but Delta(14)C(PLFA) values indicate that >65% of total bacteria filtered from the KNA-6 LTL water are heterotrophs. Ancient Delta(14)C values (similar to-1000 parts per thousand) of some PLFAs suggest that many heterotrophs utilize ancient organic matter, perhaps from lignite seams within the sedimentary rocks. The more negative range of delta(13)C(PLFA) values determined for the KNA-6 granitic water (-42 parts per thousand to -66 parts per thousand) are likely the result of a microbial ecosystem dominated by chemolithoautotrophy, perhaps fuelled by abiogenic H(2). Results of sample storage experiments showed substantial shifts in microbial community composition and delta(13)C(PLFA) values (as much as 5 parts per thousand) during 2-4 days of dark, refrigerated, aseptic storage. However, water samples collected and immediately filtered back in the lab from freshly drilled MSB-2 borehole appeared to maintain the same relative relationships between delta(13)C(PLFA) values for sedimentary and granitic host rocks as observed for samples directly filtered under artesian flow from the KNA-6 borehole of the Tono Uranium Mine. (C) 2010 Elsevier Ltd. All rights reserved.
id: 2057; PT: J; UT: WOS:000278510300008

Mineral carbonation in peridotite and basalt for CO2 capture and storage - Kelemen, P. B.; Matter, J. M.; Streit, L. (Annual Reviews of Earth & Planetary Sciences, 2010)
id: 845not submitted

Molecular and Isotopic Analysis of Motor Oil from a Biodiesel-Driven Vehicle - Peacock, E. E.; Arey, J. S.; DeMello, J. A.; McNichol, A. P.; Nelson, R. K.; Reddy, C. M. (Energy & Fuels, 2010)
Biodiesel, a mixture of fatty acid methyl esters (FAMEs), is increasingly recognized as a renewable fuel. While some environmental impacts of biodiesel usage have been investigated, accumulation of organic compounds in motor oil, which can subsequently leak onto roads, has not been studied. Because studies have shown that toxic polycyclic aromatic hydrocarbons (PAHs) accumulate in the motor oil of engines fueled with fossil diesel or gasoline, the objective of this study was to determine if this also occurs for engines fueled with biodiesel. Here, we sampled and analyzed motor oil of a biodiesel-powerd 2005 Volkswagen Passat Wagon over 3240 km for personal-use driving. Using gas chromatography with flame ionization detection (GC-FID), we found a total of 0.5% FAMEs in the motor oil after 3240 km. We also used gas chromatography-mass spectrometry and comprehensive two-dimensional gas chromatography and did not detect PAHs or other organic compounds not present in the initial motor oil. Using natural radiocarbon analysis, a powerful technique capable of detecting biodiesel-derived carbon that would be otherwise undetectable by gas chromatography, we found a total of 0.68% biodiesel-derived carbon after 3240 km. This is similar to the amount of FAMEs found in these samples with GC-FID, indicating that the primary source of biodiesel-derived carbon in the motor oil is FAMEs (and not PAHs or other carbonaceous species). This result suggests that used motor oil of biodiesel vehicles can be less toxic based on PAH content than vehicles fueled with fossil diesel or gasoline.
id: 816; 555MH Times Cited:0 Cited References Count:63; YY

No signature of abyssal carbon n intermediate waters off Chile during deglaciation - dePol-Holz, R.; Keigwin, L.; Southon, J.; Hebbeln, D.; Mohtadi, M. (Nature Geosciences, 2010)
id: 772; YY

The Passage of the Bomb Radiocarbon Pulse into the Pacific Ocean - Jenkins, W. J.; Elder, K. L.; McNichol, A. P.; von Reden, K. (Radiocarbon, 2010)
We report and compare radiocarbon observations made on 2 meridional oceanographic sections along 150 degrees W in the South Pacific in 1991 and 2005. The distributions reflect the progressive penetration of nuclear weapons-produced (14)C into the oceanic thermocline. The changes over the 14 yr between occupations are demonstrably large relative to any possible drift in our analytical standardization. The computed difference field based on the gridded data in the upper 1600 m of the section exhibits a significant decrease over time (approaching 40 to 50 parts per thousand in Delta(14)C) in the upper 200-300 m, consistent with the decadal post-bomb decline in atmospheric (14)C levels. A strong positive anomaly (increase with time), centered on the low salinity core of the Antarctic Intermediate Water (AAIW), approaches 50-60 parts per thousand in Delta(14)C, a clear signature of the downstream evolution of the (14)C transient in this water mass. We use this observation to estimate the transit time of AAIW from its "source region" in the southeast South Pacific and to compute the effective reservoir age of this water mass. The 2 sections show small but significant changes in the abyssal (14)C distributions. Between 1991 and 2005, Delta(14)C has increased by 9 parts per thousand below 2000 m north of 55 degrees S. This change is accompanied overall by a modest increase in salinity and dissolved oxygen, as well as a slight decrease in dissolved silica. Such changes are indicative of greater ventilation. Calculation of "phosphate star" also indicates that this may be due to a shift from the Southern Ocean toward North Atlantic Deep Water as the ventilation source of the abyssal South Pacific.
Sp. Iss. 2696jo Times Cited:7 Cited References Count:38
Keywords: AMS; antarctic intermediate water; anthropogenic co2; atlantic; c-14 data; carbon; distributions; graphite; south-pacific; tritium

Postglacial changes in El Nino and La Nina behavior - Makou, Matthew C.; Eglinton, Timothy I.; Oppo, Delia W.; Hughen, Konrad A. (Geology, 2010)
Paleoclimate reconstructions suggest distinctive changes in the Ell Nino-Southern Oscillation (ENSO), the dominant mode of tropical climate variability, over the last glacial cycle and throughout the Holocene. However, to the best of our knowledge, no studies provide parallel reconstructions of warm (El Nino) and cold (La Nina) phase variability, thus precluding distinction between variations in ENSO activity and the mean state of the tropical Pacific. Here we provide the first such records, generated using molecular organic geochemical proxies in a sediment core from the Peru margin region. The opposing influences of El Nino and La Nina on coastal upwelling and phytoplankton community structure produce distinct sedimentary sterol records describing the evolution of each ENSO phase. We document changes in surface ocean productivity on the Peru margin over the past 16 ka that indicate enhanced La Nina-like conditions alone during deglaciation, but concomitant increases in both El Nino and La Nina activity during the past 2 ka. We propose that the preponderance of La Nina-like conditions prior to 11.5 ka reflects the influence of waning glacial boundary conditions. By contrast, warm and cold phase covariability during the late Holocene suggests centennial-scale changes in ENSO activity, rather than the Pacific mean state, driven by tropical insolation.
id: 1985; PT: J; UT: WOS:000273346200011

The radiocarbon age of organic carbon in marine surface sediments - Griffith, David R.; Martin, William R.; Eglinton, Timothy I. (GEOCHIMICA ET COSMOCHIMICA ACTA, 2010)
Long-term carbon cycling and climate change are strongly dependent on organic carbon (OC) burial in marine sediments. Radiocarbon ((14)C) has been widely used to constrain the sources, sinks, and processing of sedimentary OC. To elucidate the dominant controls on the radiocarbon content of total organic carbon ((14)C(TOC)) accumulating in surface sediments we construct a box model that predicts (14)C(TOC) in the sediment mixed layer (measured as fraction modern, Fm). Our model defines three distinct OC pools ({''}degradable,{''} ``semi-labile,{''} and ``refractory{''}) and assumes that (14)C(TOC) flux to sediments is exclusively derived from surface ocean primary productivity, and hence follows a ``generic{''} surface ocean dissolved inorganic carbon (DIC) bomb curve. Model predictions are compared to a set of 75 surface sediment samples, which span a wide geographic range and reflect diverse water column and depositional conditions, and for which sedimentation rate and mixed-layer depth are well characterized. Our model overestimates the Fm value for a majority (65%) of these sites, especially at shallow water depths and for sites characterized by depleted delta(13)C(TOC) values. The model is most sensitive to sedimentation rate and mixed-layer depth. Therefore, slight changes to these parameters can lead to a match between modeled and measured Fm values at many sites. Yet, in some cases, we find that measured Fm values cannot be simulated without large and unrealistic changes to sedimentation rate and mixed-layer depth. These results point to sources of pre-aged OC to surface sediments and implicate soil-derived terrestrial OC, reworked marine OC, and/or anthropogenic carbon as important components of the organic matter present in surface sediments. This approach provides a valuable framework within which to explore controls on sedimentary organic matter composition and carbon burial over a range of spatial and temporal scales. (C) 2010 Elsevier Ltd. All rights reserved.

Radiocarbon Dating of Individual Lignin Phenols: A New Approach for Establishing Chronology of Late Quaternary Lake Sediments - Hou, Juzhi; Huang, Yongsong; Brodsky, Corynn; Alexandre, Marcelo R.; McNichol, Ann P.; King, John W.; Hu, Feng Sheng; Shen, Ji (ANALYTICAL CHEMISTRY, 2010)
The reliability of chronology is a prerequisite for meaningful paleoclimate reconstructions from sedimentary archives. The conventional approach of radiocarbon dating bulk organic carbon in lake sediments is often hampered by the old carbon effect, i.e., the assimilation of ancient dissolved inorganic carbon (DIC) derived from carbonate bedrocks or other sources. Therefore, radiocarbon dating is ideally performed on organic compounds derived from land plants that use atmospheric CO(2) and rapidly delivered to sediments. We demonstrate that lignin phenols isolated from lake sediments using reversed phase high performance liquid chromatography (HPLC) can serve as effective (14)C dating materials for establishing chronology during the late Quaternary. We developed a procedure to purify lignin phenols, building upon a published method. By isolating lignin from standard wood reference substances, we show that our method yields pure lignin phenols and consistent ages as the consensus ages and that our procedure does not introduce radiocarbon contamination. We further demonstrate that lignin phenol ages are compatible with varve counted and macrofossil dated sediment horizons in Steel Lake and Fayetteville Green Lake. Applying the new method to lake sediment cores from Lake Qinghai demonstrates that lignin phenol ages in Lake Qinghai are consistently younger than bulk total organic carbon (TOC) ages which are contaminated by old carbon effect. We also show that the age offset between lignin and bulk organic carbon differs at different Lake Qinghai sedimentary horizons, suggesting a variable hard water effect at different times and that a uniform age correction throughout the core is inappropriate.

Radiocarbon in the Canada Basin: Carbon Transfer Processes in the Changing Arctic - McNichol, A P; Xu, L; Griffith, D R; Eglinton, T I; Macdonald, R; McLaughlin, F A (Proceedings from the 2010 AGU Ocean Sciences Meeting, 2010)
We are developing full water column depth [delta]14C profiles for dissolved inorganic carbon (DIC), dissolved organic carbon (DOC) and suspended particulate organic carbon (POC) collected in 2008 from the Canada Basin in the Arctic Ocean. These samples provide an opportunity to study the current distribution of radiocarbon in different carbon pools and set a baseline for future investigations of the carbon cycle in this key oceanic region where climate change is anticipated to have a major and imminent impact on carbon storage and cycling. Our first DI14C depth profile from 75, 150 is similar to one taken in 1992 (Jones et al. 1994) in demonstrating a well-ventilated surface layer overlying an older but recently ventilated deeper basin. Significant increases in DI14C, up to 30 ppt, are observed in the mid-depth region between 500 to 1500 m, roughly coincident with a warm layer underlying cold surface waters. The differences that have occurred over 16 years may lend insight to the observed warming of Atlantic water in the Canada Basin over the past decades. We will present the first DO14C profile from the central Canada Basin. Measurements are being made using a UV oxidation system established at NOSAMS. Most of the samples collected for DO14C measurement were acidified to preserve them. Results from frozen duplicates for a few of the samples will be compared to validate the preservation technique. In most regions of the ocean, the shape of DO14C depth profiles parallel those of DI14C profiles but are shifted to significantly older values. This reflects the fact that general oceanographic circulation and remineralization processes dominate the overall profile, but that the sources of carbon to the DOC pool are more complex than those of DIC. It is unknown whether this will be the case in the Arctic Ocean which, while representing only ~1% of the worlds ocean volume, receives approximately 13% of the global flux of terrigeneous DOC. Jones, G. A. et al. (1994). NIMS B, 92, 426-430.
Date revised - 2010-09-01SuppNotes - Abstracts AvailableLast updated - 2016-12-22
Keywords: and modeling; Biogeochemical cycles; carbon cycling; processes; Radioactivity and radioisotopes

Rapid Climatic Signal Propagation from Source to Sink in a Southern California Sediment-Routing System - Covault, J. A.; Romans, B. W.; Fildani, A.; McGann, M.; Graham, S. A. (Journal of Geology, 2010)
Terrestrial source areas are linked to deep-sea basins by sediment-routing systems, which only recently have been studied with a holistic approach focused on terrestrial and submarine components and their interactions. Here we compare an extensive piston-core and radiocarbon-age data set from offshore southern California to contemporaneous Holocene climate proxies in order to test the hypothesis that climatic signals are rapidly propagated from source to sink in a spatially restricted sediment-routing system that includes the Santa Ana River drainage basin and the Newport deep-sea depositional system. Sediment cores demonstrate that variability in rates of Holocene deep-sea turbidite deposition is related to complex ocean-atmosphere interactions, including enhanced magnitude and frequency of the North American monsoon and El Nino-Southern Oscillation cycles, which increased precipitation and fluvial discharge in southern California. This relationship is evident because, unlike many sediment-routing systems, the Newport submarine canyon-and-channel system was consistently linked to the Santa Ana River, which maintained sediment delivery even during Holocene marine transgression and highstand. Results of this study demonstrate the efficiency of sediment transport and delivery through a spatially restricted, consistently linked routing system and the potential utility of deep-sea turbidite depositional trends as paleoclimate proxies in such settings.
id: 875; 574IR Times Cited:0 Cited References Count:55Y

Reconnaissance dating A new radiocarbon method applied to assessing the temporal distribution of Southern Ocean deep-sea corals - Burke, Andrea; Robinson, Laura F.; McNichol, Ann P.; W. J. Jenkins; Scanlon, Kathryn M.; Gerlach, Dana S. (Deep-Sea Research Part I-Oceanographic Research Papers, 2010)
We have developed a rapid reconnaissance method of preparing graphite for (14)C/(12)C analysis Carbonate (similar to 15 mg) is combusted using an elemental analyzer and the resulting CO(2) is converted to graphite using a sealed tube zinc reduction method Over 85% (n=45 replicates on twenty-one individual corals) of reconnaissance ages measured on corals ranging in age from 500 to 33 000 radiocarbon years (Ryr) are within two standard deviations of ages generated using standard hydrolysis methods on the same corals and all reconnaissance ages are within 300 Ryr of the standard hydrolysis ages Replicate measurements on three individual aragonitic corals yielded ages of 1076 +/- 35 Ryr (standard deviation n=5) 10 739 +/- 47 Ryr (n=8) and 40 146 +/- 3500 Ryr (n=9) No systematic biases were found using different cleaning methods or variable sample sizes Analysis of (13)C/(12)C was made concurrently with the (14)C/(12)C measurement to correct for natural fractionation and for fractionation during sample processing and analysis This technique provides a new rapid method for making accurate percent-level (14)C/(12)C analyses that may be used to establish the rates and chronology of earth system processes where survey-type modes of age estimation are desirable For example applications may include creation of sediment core-top maps preliminary age models for sediment cores and growth rate studies of marine organisms such as corals or mollusks We applied the reconnaissance method to more than 100 solitary deep-sea corals collected in the Drake Passage in the Southern Ocean to investigate their temporal and spatial distribution The corals used in this study are part of a larger sample set and the subset that was dated was chosen based on species as opposed to preservation state so as to exclude obvious temporal biases Similar to studies in other regions the distribution of deep-sea corals is not constant through time across the Drake Passage Most of the corals from the Burdwood Bank (continental shelf of Argentina) have ages ranging between 0 and 2500 calendar years whereas most of the corals from the Sars Seamount in the Drake Passage have ages between 10 000 and 12 500 calendar years Such differences may be caused in part by sampling biases but may also be caused by changes in larval transport nutrient supply or other environmental pressures (C) 2010 Elsevier Ltd All rights reserved
id: 1924; PT: J; UT: WOS:000284750700012

Reduced North Atlantic Central Water formation in response to early Holocene ice-sheet melting - Bamberg, A.; Rosenthal, Y.; Paul, A.; Heslop, D.; Mulitza, S.; Ruhlemann, C.; Schulz, M. (Geophysical Research Letters, 2010)
Central waters of the North Atlantic are fundamental for ventilation of the upper ocean and are also linked to the strength of the Atlantic Meridional Overturning Circulation (AMOC). Here, we show based on benthic foraminiferal Mg/Ca ratios, that during times of enhanced melting from the Laurentide Ice Sheet (LIS) between 9.0-8.5 thousand years before present (ka) the production of central waters weakened the upper AMOC resulting in a cooling over the Northern Hemisphere. Centered at 8.54 +/- 0.2 ka and 8.24 +/- 0.1 ka our dataset records two similar to 150-year cooling events in response to the drainage of Lake Agassiz/Ojibway, indicating early slow-down of the upper AMOC in response to the initial freshwater flux into the subpolar gyre (SPG) followed by a more severe weakening of both the upper and lower branches of the AMOC at 8.2 ka. These results highlight the sensitivity of regional North Atlantic climate change to the strength of central-water overturning and exemplify the impact of both gradual and abrupt freshwater fluxes on eastern SPG surface water convection. In light of the possible future increase in Greenland Ice Sheet melting due to global warming these findings may help us to better constrain and possibly predict future North Atlantic climate change. Citation: Bamberg, A., Y. Rosenthal, A. Paul, D. Heslop, S. Mulitza, C. Ruhlemann, and M. Schulz (2010), Reduced North Atlantic Central Water formation in response to early Holocene ice-sheet melting, Geophys. Res. Lett., 37, L17705, doi: 10.1029/2010GL043878.
id: 874; 649FZ Times Cited:3 Cited References Count:32submittedY

Regional seismic stratigraphy and controls on the Quaternary evolution of the Cape Hatteras region of the Atlantic passive margin, USA - Mallinson, D. J.; Culver, S. J.; Riggs, S. R.; Thieler, E. R.; Foster, D.; Wehmiller, J.; Farrell, K. M.; Pierson, J. (Marine Geology, 2010)
Seismic and core data, combined with amino acid racemization and strontium-isotope age data, enable the definition of the Quaternary stratigraphic framework and recognition of geologic controls on the development of the modern coastal system of North Carolina, U.S.A. Seven regionally continuous high amplitude reflections are defined which bound six seismic stratigraphic units consisting of multiple regionally discontinuous depositional sequences and parasequence sets, and enable an understanding of the evolution of this margin. Data reveal the progressive eastward progradation and aggradation of the Quaternary shelf. The early Pleistocene inner shelf occurs at a depth of ca. 20-40 m beneath the western part of the modern estuarine system (Pamlico Sound). A mid- to outer shelf lowstand terrace (also early Pleistocene) with shelf sand ridge deposits comprising parasequence sets within a transgressive systems tract, occurs at a deeper level (ca. 45-70 m) beneath the modern barrier island system (the Outer Banks) and northern Pamlico Sound. Seismic and foraminiferal paleoenvironmental data from cores indicate the occurrence of lowstand strandplain shoreline deposits on the early to middle Pleistocene shelf. Middle to late Pleistocene deposits occur above a prominent unconformity and marine flooding surface that truncates underlying units, and contain numerous filled fluvial valleys that are incised into the early and middle Pleistocene deposits. The stratigraphic framework suggests margin progradation and aggradation modified by an increase in the magnitude of sea-level fluctuations during the middle to late Pleistocene. expressed as falling stage, lowstand, transgressive and highstand systems tracts. Thick stratigraphic sequences occur within the middle Pleistocene section, suggesting the occurrence of high capacity fluvial point sources debouching into the area from the west and north. Furthermore, the antecedent topography plays a significant role in the evolution of the geomorphology and stratigraphy of this marginal system. (C) 2009 Elsevier B.V. All rights reserved.
id: 1862; 556RX Times Cited:0 Cited References Count:71Y

The role of glacio-eustasy in sequence formation: Mid-Atlantic Continental Margin, USA - McHugh, Cecilia M.; Hartin, Corinne A.; Mountain, Gregory S.; Gould, Helene M. (Marine Geology, 2010)
Previous studies of the Mid-Atlantic Continental Margin had shown the lack of correlation between Pleistocene glacio-eustatic oscillations and sequence boundaries. This study documents late Pleistocene to Holocene paleoenvironments within a seismic stratigraphic sequence in order to characterize sequence formation and the development of unconformities in response to glacio-eustatic oscillations. The data, high-resolution CHIRP subbottom profiling and 28 vibracores, were collected in water depths of 38 m to 145 m as part of the R/V Endeavor cruise 370 survey to the Mid-Atlantic Continental Margin. Sediment sources, sedimentary and seismic facies associated with the last major glaciation, and oxygen isotope stages OIS 5 to OIS 1 were examined and a chronology was constructed from mollusk assemblages of intertidal origin that allowed tracking the paleoshoreline from 19 to 6 ka BP. The maximum extent of the Last Glacial Maximum (LGM) paleoshoreline at 17 ka BP was documented near the 120 m modern isobath. The shoreline was marked by sediment mounds up to 5 m high and troughs 15 m deep and 1 km wide (interpreted as shoreface and tidal inlet or lagoons) formed from 17 to 15 ka BP. Five kilometers seaward from the LGM shoreline and the head of the Hudson Canyon is a wedge-shaped feature interpreted as a lowstand delta. Sediments older than the last glacial, possibly OIS 3 or OIS 5, onlap a basal unconformity. We correlate this unconformity to a previously identified sequence boundary. Approximately 20 m to 30 m of sediment accumulated on the outer shelf NE of the Hudson Canyon during the last glacial and little deposition has occurred since ~ 11 ka BP. The modern outershelf is covered by ~ 1 m of mollusk-rich glauconitic sand deposited from latest Pleistocene to early Holocene, 15 to 11 ka BP. These results showed a close correspondence between depositional environments and glacio-eustasy but sequence development and sequence boundary formation appeared to be influenced by the incomplete filling of accommodation space due to poor preservation during OIS 2 and low accumulation during the Holocene.
Keywords: Hudson Canyon; Hudson Shelf Valley; Last glacial maximum; Mid-Atlantic Continental Margin; paleoshoreline; sequence stratigraphy

Sources of CO2 evasion from two subtropical rivers in North America - Zeng, F. W.; Masiello, C. A. (Biogeochemistry, 2010)
We directly measured the partial pressure of dissolved CO2 (pCO(2)) in two humid subtropical rivers in coastal Texas, one highly urbanized (Buffalo Bayou) and one relatively undeveloped (Spring Creek), and analyzed carbon isotopic signatures (Delta C-14 and delta C-13) of riverine dissolved inorganic carbon (DIC) to determine carbon sources sustaining river respiration. Both rivers were highly supersaturated with CO2 at all study sites and on all dates sampled from June 2007 to February 2009. Mean riverine pCO(2) values are 3,052 +/- A 1,364 and 4,702 +/- A 1,980 mu atm for Buffalo Bayou and Spring Creek, respectively. Calculated CO2 emission fluxes per ha of water surface area from these rivers are intermediate between those in tropical and temperate rivers, indicating that globally, humid subtropical rivers may be a significant source of atmospheric CO2. Carbon isotopic signatures revealed that CO2 supersaturation is supported by different carbon sources for the two rivers. In the relatively undeveloped river (Spring Creek), young terrestrial organic matter (OM) is the predominant C source fueling river heterotrophic respiration. In the highly urbanized river (Buffalo Bayou), the high concentration of riverine CO2 is additionally supported by dissolution of CaCO3 likely from pedogenic carbonate, and crushed limestone/dolomite and oyster shells imbedded in old roads in the watershed. Because urban sources of acidity can include HNO3 and H2SO4, whether the limestone/dolomite and shells used by humans act as a net sink or source of atmospheric CO2 needs further study.
646uoTimes Cited:17Cited References Count:55

The southern Svalbard Margin sedimentary system: preliminary results from EGLACOM cruise 2008 - Melis, R.; Lucchi, R. G.; Giorgetti, G.; Persico, D.; BÁRcena, M. A. A.; Caburlotto, A.; MacrÌ, P.; Villa, G.; Sagnotti, L.; Rebesco, M. (European Geosciences Union, General Assembly 2010, 2010)
id: 873

Submarine Mass Transport Within Monterey Canyon: Benthic Disturbance Controls on the Distribution of Chemosynthetic Biological Communities - Paull, C. K.; Schlining, B.; Ussler, W.; Lundste, E.; Barry, J. P.; Caress, D. W.; Johnson, J. E.; McGann, M. (Submarine mass movements and their consequences, 4th International Symposium:, 2010)
Documenting mass transport within Monterey Canyon and Fan has been a focus of remotely operated vehicle (ROV) observations, sampling, monitoring, and multibeam mapping studies. These efforts indicate that major mass transport events occur within upper Monterey Canyon (2 km water depths) and onto Monterey Fan for ~100 years. Simultaneous efforts to document the distribution of benthic taxa observed in the video records from 668 ROV dives conducted by the Monterey Bay Aquarium Research Institute (MBARI) provide a uniquely detailed record of the occurrence of chemosynthetic biological communities (CBC). The combined results of these studies provide an understanding of the relationship between disturbance caused by episodic mass wasting events and the distribution of CBC. CBC are common within the canyon's axis below ~2.5 km water depth, but have not been found within the canyon's axis at depths shallower than 2 km. Moreover, CBC occur on the canyon walls at essentially any depth, primarily within young (~hundreds of years old) slump scars. The distribution of CBC provides evidence about the disturbance history of the seafloor. Major mass transport events will destroy communities that lie in their path. Erosion associated with major mass transport events can create environments to support CBC by exposing methane-bearing strata. This can happen as a result of slumping events on the sidewalls of the canyon or where major gravity flow events have excavated the base of canyon walls. Once fresh strata are exposed, geochemical conditions to support CBC will persist for a few centuries. Because CBC are composed of slow-growing and long-lived organisms, it will take decades for these communities to be established. Their existence indicates that environmental stability has occurred over a similar time scale.
id: 879

Synchronous Deglacial Overturning and Water Mass Source Changes - Roberts, N. L.; Piotrowski, A. M.; McManus, J. F.; Keigwin, L. D. (Science, 2010)
Understanding changes in ocean circulation during the last deglaciation is crucial to unraveling the dynamics of glacial-interglacial and millennial climate shifts. We used neodymium isotope measurements on postdepositional iron-manganese oxide coatings precipitated on planktonic foraminifera to reconstruct changes in the bottom water source of the deep western North Atlantic at the Bermuda Rise. Comparison of our deep water source record with overturning strength proxies shows that both the deep water mass source and the overturning rate shifted rapidly and synchronously during the last deglacial transition. In contrast, any freshwater perturbation caused by Heinrich event 1 could have only affected shallow overturning. These findings show how changes in upper-ocean overturning associated with millennial-scale events differ from those associated with whole-ocean deglacial climate events.

Temperature and salinity changes in the deglacial North Atlantic - Benway, H.M.; McManus, J.F.; Oppo, D.W.; Cullen, J.F. (Quaternary Science Reviews, 2010)

Timescales of lateral sediment transport in the Panama Basin as revealed by radiocarbon ages of alkenones, total organic carbon and foraminifera - Kusch, Stephanie; Eglinton, Timothy I.; Mix, Alan C.; Mollenhauer, Gesine (Earth and Planetary Science Letters, 2010)
id: 882Y

Variations in the distribution and radiocarbon age of lignin phenols exported by large river systems - Feng, X. J.; Montlucon, D. B.; Eglinton, T. I. (Geochimica Et Cosmochimica Acta, 2010)
Suppl. 1676tl Times Cited:0 Cited References Count:0

A 2000 year midge-based paleotemperature reconstruction from the Canadian Arctic archipelago - Porinchu, D.; MacDonald, G.; Rolland, N. (Journal of Paleolimnology, 2009)
A lake sediment core recovered from Lake V57 on Victoria Island, Nunavut, Canada, spanning the last 2000 years, was analyzed for sub-fossil midge remains and organic-matter content (estimated by loss-on-ignition (LOI)). Significant changes in midge community composition occurred during the last 2000 years, with a distinct midge community appearing after 1600 AD. The chironomid community between 0 and 1600 AD was dominated by Heterotrissocladius, Tanytarsus, Abiskomyia, and Paracladius. At approximately 1600 AD, Heterotrissocladius decreased in relative abundance and taxa such as Corynocera ambigua, C. oliveri, Psectrocladius sordidellus type, and Pentanneurini increased in relative abundance. Previously published midge-based inference models for average July air temperature (AJAT) and summer surface-water temperature (SSWT) were applied to the subfossil midge stratigraphy. The AJAT reconstruction indicates relatively cool conditions existed between 1100 and 1600 AD, with exceptional warming occuring after 1600 AD, as lake productivity inferred from organic-matter content increased concomitantly with midge-inferred AJAT and SSWT. The cooler conditions between 1200 and 1600 AD, and the pattern of warming over recent centuries inferred from Lake V57 is broadly consistent with temperature-sensitive biogenic silica records from other sites in the central Canadian Arctic and the treeline zone to the south suggesting a regionally synchronous response to climate forcing.
id: 1863; 395EF Times Cited:3 Cited References Count:57Y

5000 year sedimentary record of hurricane strikes on the central coast of Belize - McCloskey, T. A.; Keller, G. (Quaternary International, 2009)
The central coast of Belize has been subject to hurricane strikes throughout recorded history with immense human and material cost to the Belizean people. What remains unknown is the long-term frequency of hurricane strikes and the effects such storms may have had on the ancient Maya civilization. Our sedimentary study of major hurricane strikes over the past 5000 years provides preliminary insights. We calculate that over the past 500 years major hurricanes have struck the Belize coast on average once every decade. One giant hurricane with probably particularly catastrophic consequences struck Belize sometime before AD 1500. A temporal clustering of hurricanes suggests two periods of hyperactivity between similar to 4500 and 2500 (14)Cyr BP, which supports a regional model of latitudinal migration of hurricane strike zones. Our preliminary hurricane data, including the extreme apparent size of the giant event, suggest that prehistoric hurricanes were capable of having exerted significant environmental stress in Maya antiquity. (c) 2008 Elsevier Ltd and INQUA. All rights reserved.
id: 2008; PT: J; CT: Workshop on Hurricanes and Typhoons - From the Field Records to the Forecast; CY: SEP 25-28, 2006; CL: Lafayette, LA; SP: United Nat Int Geosci Program, Int Geosphere-Biosphere Programme Past Global Changes; UT: WOS:000263692000006

Atlantic hurricanes and climate over the past 1,500 years - Mann, M. E.; Woodruff, J. D.; Donnelly, J. P.; Zhang, Z. H. (Nature, 2009)
Atlantic tropical cyclone activity, as measured by annual storm counts, reached anomalous levels over the past decade(1). The short nature of the historical record and potential issues with its reliability in earlier decades, however, has prompted an ongoing debate regarding the reality and significance of the recent rise(2-5). Here we place recent activity in a longer-term context by comparing two independent estimates of tropical cyclone activity over the past 1,500 years. The first estimate is based on a composite of regional sedimentary evidence of landfalling hurricanes, while the second estimate uses a previously published statistical model of Atlantic tropical cyclone activity driven by proxy reconstructions of past climate changes. Both approaches yield consistent evidence of a peak in Atlantic tropical cyclone activity during medieval times (around AD 1000) followed by a subsequent lull in activity. The statistical model indicates that the medieval peak, which rivals or even exceeds (within uncertainties) recent levels of activity, results from the reinforcing effects of La-Nina-like climate conditions and relative tropical Atlantic warmth.
id: 1893; ISI Document Delivery No.: 483CB Times Cited: 2 Cited Reference Count: 37 Cited References: BOLDT K, MAR GEOL UNPUB COBB KM, 2003, NATURE, V424, P271, DOI 10.1038/nature01779 DONNELLY JP, 2001, GEOL SOC AM BULL, V113, P714 DONNELLY JP, 2001, GEOLOGY, V29, P615 DONNELLY JP, 2004, MAR GEOL, V210, P107, DOI 10.1016/j.margeo.2004.05.005 DONNELLY JP, 2007, NATURE, V447, P465, DOI 10.1038/nature05834 ELSNER JB, 2008, J APPL METEOROL CLIM, V47, P368, DOI 10.1175/2007JAMC1692.1 GARCIAHERRERA R, 2005, J GEOPHYS RES-ATMOS, V110, ARTN D03109 GRAHAM NE, 2007, CLIMATIC CHANGE, V83, P241, DOI 10.1007/s10584-007-9239-2 HIPPENSTEEL SP, 2005, GEOL SOC AM BULL, V117, P250, DOI 10.1130/B25535.1 HOLLAND GJ, 2007, PHIL T R SOC A, DOI 10.1098/RSTA.2007.2083 JONES PD, 1997, INT J CLIMATOL, V17, P1433 KAPLAN A, 1998, J GEOPHYS RES-OCEANS, V103, P18567 KEIGWIN LD, 1996, SCIENCE, V274, P1504 KNUTSON TR, 2008, NAT GEOSCI, V1, P359, DOI 10.1038/ngeo202 LAMBERT WJ, 2003, T GULF COAST ASS GEO, V53, P443 LANDSEA CW, 2007, EOS T AGU, V88, P197, DOI 10.1029/2007E0180001 LIU KB, 2000, QUATERNARY RES, V54, P238 LUTERBACHER J, 2002, ATMOS SCI LETT, V2, P114, DOI 10.1006/ASLE.2001.0044 MANN ME, SCIENCE UNPUB MANN ME, 2005, J CLIMATE, V18, P447 MANN ME, 2007, EOS, V88, P349, DOI 10.1029/2007E0360002 MANN ME, 2007, GEOPHYS RES LETT, V34, ARTN L22707 MANN ME, 2008, GEOPHYS RES LETT, V35, DOI 10.1029/2008GL034716 NEU U, 2008, NATURE, V451, E5, DOI 10.1038/nature06576 NYBERG J, 2007, NATURE, V447, P698, DOI 10.1038/nature05895 OTVOS EG, 2002, QUATERNARY RES, V57, P425 RAYNER NA, 2003, J GEOPHYS RES-ATMOS, V108, ARTN 4407 RICHEY JN, 2007, GEOLOGY, V35, P423, DOI 10.1130/G23507A.1 SABBATELLI TA, J GEOPHYS RES UNPUB SABBATELLI TA, 2007, J GEOPHYS RES-ATMOS, V112, ARTN D17114 SCILEPPI E, 2007, GEOCHEM GEOPHY GEOSY, V8, P1 SCOTT DB, 2003, GEOL SOC AM BULL, V115, P1027 SMITH TM, 2003, J CLIMATE, V16, P1495 VECCHI GA, 2007, GEOPHYS RES LETT, V34, ARTN L08702 WOODRUFF JD, 2008, GEOCHEM GEOPHY GEOSY, V9, DOI 10.1029/2008GC002043 WOODRUFF JD, 2008, GEOLOGY, V36, P391, DOI 10.1130/G24731A.1 Mann, Michael E. Woodruff, Jonathan D. Donnelly, Jeffrey P. Zhang, Zhihua National Science Foundation [ATM-0542356, EAR-0519118, OCE-0402746]; YY

Black carbon in marine particulate organic carbon: Inputs and cycling of highly recalcitrant organic carbon in the Gulf of Maine - Flores-Cervantes, D. X.; Plata, D. L.; MacFarlane, J. K.; Reddy, C. M.; Gschwend, P. M. (Marine Chemistry, 2009)
To increase our understanding of the roles of black carbon (BC), a highly sorptive and recalcitrant material, we measured BC concentrations and fluxes in marine particulate organic carbon (POC) out of the water column in the Gulf of Maine (GoM), a representative coastal area downwind of important BC sources of the Northeastern United States. Concentrations ranged from
id: 1865; 440SC Times Cited:0 Cited References Count:85; YY

Bomb dating and age determination of skates (family Rajidae) off the eastern coast of Canada - McPhie, R. P.; Campana, S. E. (Ices Journal of Marine Science, 2009)
Recent declines in abundance of skates off the eastern coast of Canada have heightened the need for validated age and growth estimates in the region. In all, 502 winter (Leucoraja ocellata), little (Leucoraja erinacea), thorny (Amblyraja radiata), and smooth (Malacoraja senta) skate vertebral centra collected seasonally between 1999 and 2004 were sectioned using a mass processing method, then used to reconstruct growth in each species. Bomb rediocarbon (Delta C-14) analysis was used to provide evidence of annual band-pair deposition in thorny skates. Estimates of L-infinity from traditional von Bertalanffy growth models (VBGM) ranged from 60.6 cm (little skate) to 89.7 cm (thorny skate), and K estimates from 0.07 (thorny skate) to 0.19 (little skate). A modified two-parameter VBGM (L-MAX = 94.1 cm) fitted to winter skate lenght-at-age data yielded a value of K to 0.15. Maximum observed ages ranged from 12 (little skate) to 19 years in both winter and thorny skates. The year-specific incorporation of Delta C-14 milled from thorny and winter skate vertebral sections closely resembled shark-derived reference chronology values from the Northwest Atlantic. Pre-bomb Delta C-14 in a thorny skate collected in 1988 and aged at 23 years appeared to validate age interpretations and suggested that thorny skate reach an absolute age of at least 28 years, the oldest validated age reported for any species of batoid.
id: 1856; 421XR Times Cited:3 Cited References Count:82Y

A chronology of hurricane landfalls at Little Sippewissett Marsh, Massachusetts, USA, using optical dating - Madsen, A. T.; Duller, G. A. T.; Donnelly, J. P.; Roberts, H. M.; Wintle, A. G. (Geomorphology, 2009)
Optical dating has been applied to sediments preserved in Little Sippewissett Marsh, Massachusetts, USA, which are associated with overwashing of the beach barrier during hurricane strikes on the coast. The aims were to determine the hurricane landfall frequency, and make comparisons with independent age control and the historical record. Written sources of hurricane activity along the American east coast are only considered reliable back to the mid 19th century, but the sedimentary record is potentially much longer. Optical dating was applied to quartz grains extracted from thirteen samples within a sediment core from the salt-marsh. Variability in the luminescence characteristics between aliquots was observed and similar to 33% of the measured aliquots were discarded based upon the ratio of the fast component to the medium component. The majority of the samples gave normal dose distributions implying homogeneous resetting of the luminescence signal at the time of deposition, but three of the samples required application of the minimum age model (MAM). Ages ranging between 20 +/- 2 and 594 +/- 38 years were obtained and are broadly in agreement with independent chronologies, thus demonstrating the potential of optical dating in this setting. The hurricane record based upon optical dating extends approximately 300 years further back in time than the official National Oceanic Atmospheric Administration (NOAA) record. The localised nature of hurricane landfalls means that it will be necessary to collect multiple cores from a number of different sites in order to build up a complete hurricane record for this part of the coast. (C) 2009 Elsevier B.V. All rights reserved.
id: 861; ISI Document Delivery No.: 465RS Times Cited: 1 Cited Reference Count: 47 Cited References: *NOAA NOS COOPS, 2006, VER HIST WAT LEV DAT AITKEN MJ, 1985, THERMOLUMINESCENCE D ANDERSON TW, 1974, CAN J EARTH SCI, V11, P678 BAILEY RM, 1997, RADIAT MEAS, V27, P123 BAILEY SD, 2001, QUATERNARY SCI REV, V20, P701 BALLARINI M, 2003, QUATERNARY SCI REV, V22, P1011, DOI 10.1016/S0277-3791(03)00043-X BERGER GW, 2003, QUATERNARY SCI REV, V22, P1043, DOI 10.1016/S0277-3791(03)00017-9 BOOSE ER, 2001, ECOL MONOGR, V71, P27 BOSSAK BH, 2003, EARLY 19 CENTURY US BOTTERJENSEN L, 1988, NUCL TRACKS RAD MEAS, V14, P187 BOTTERJENSEN L, 1997, RADIAT MEAS, V27, P749 CHOI JH, 2003, QUATERNARY SCI REV, V22, P407 DIVIGALPITIYA WMR, 1982, THESIS S FRASER U BU DONNELLY JP, 2001, GEOL SOC AM BULL, V113, P714 DONNELLY JP, 2001, GEOLOGY, V29, P615 DONNELLY JP, 2004, HURRICANES TYPHOONS, P58 DONNELLY JP, 2004, MAR GEOL, V210, P107, DOI 10.1016/j.margeo.2004.05.005 DULLER GAT, 2004, J QUATERNARY SCI, V19, P183, DOI 10.1002/jqs.809 EMANUEL K, 2005, NATURE, V436, P686, DOI 10.1038/nature03906 GALBRAITH RF, 1999, ARCHAEOMETRY 2, V41, P339 GOLDENBERG SB, 2001, SCIENCE, V293, P474 HENDERSONSELLERS A, 1998, B AM METEOROL SOC, V79, P19 HUNTLEY DJ, 1994, ANCIENT TL, V12, P41 JAGGER TH, 2006, J CLIMATE, V19, P3220 JAIN M, 2005, RADIAT MEAS, V39, P309 LANDSEA CW, 2004, HURRICANES TYPHOONS, P177 LANDSEA CW, 2006, SCIENCE, V313, P452, DOI 10.1126/science.1128448 LIAN OB, 2006, QUATERNARY SCI REV, V25, P2449, DOI 10.1016/j.quascirev.2005.11.013 LIU KB, 1993, GEOLOGY, V21, P793 LIU KB, 2000, QUATERNARY RES, V54, P238 LUDLUM DM, 1963, EARLY AM HURRICANES MADSEN AT, 2005, MAR GEOL, V214, P251, DOI 10.1016/j.margeo.2004.10.034 MADSEN AT, 2007, J COASTAL RES, V23, P1259, DOI 10.2112/05-0471.1 MADSEN AT, 2007, MAR GEOL, V242, P221, DOI 10.1016/j.margeo.2007.03.001 MANN ME, 2006, EOS, V87, P233 MURRAY AS, 2000, RADIAT MEAS, V32, P57 MURRAY AS, 2002, GEOCHRONOMETRIA, V21, P1 MURRAY AS, 2003, RADIAT MEAS, V37, P377, DOI 10.1016/S1350-4487(03)00053-2 NEUMANN CJ, 1993, NCDC NHC HIST CLIMAT, V6 PIELKE RA, 1998, WEATHER FORECAST 2, V13, P621 PRESCOTT JR, 1988, NUCL TRACKS RAD MEAS, V14, P223 PRESCOTT JR, 1994, RADIAT MEAS, V23, P497 RHODES EJ, 2000, RADIAT MEAS, V32, P595 STUIVER M, 1998, RADIOCARBON, V40, P1041 TRENBERTH KE, 2006, GEOPHYS RES LETT, V33, ARTN L12704 WEBSTER PJ, 2005, SCIENCE, V309, P1844, DOI 10.1126/science.1116448 WINTLE AG, 2006, RADIAT MEAS, V41, P369, DOI 10.1016/j.radmeas.2005.11.001 Madsen, A. T. Duller, G. A. T. Donnelly, J. P. Roberts, H. M. Wintle, A. G. National Science Foundation [0519118] The authors wish to acknowledge Dana MacDonald for pollen analysis. This work was supported by National Science Foundation award #0519118. Elsevier science bv Amsterdam Sp. Iss. SI; YY

Coarse-grained sediment delivery and distribution in the Holocene Santa Monica Basin, California: Implications for evaluating source-to-sink flux at millennial time scales - Romans, B. W.; Normark, W. R.; McGann, M. M.; Covault, J. A.; Graham, S. A. (Geological Society of America Bulletin, 2009)
Utilizing accumulations of coarse-grained terrigenous sediment from deep-marine basins to evaluate the relative contributions of and history of controls on sediment flux through a source-to-sink system has been difficult as a result of limited knowledge of event timing. In this study, six new radiocarbon (C-14) dates are integrated with five previously published dates that have been recalibrated from a 12.5-m-thick turbidite section from Ocean Drilling Program (ODP) Site 1015 in Santa Monica Basin, offshore California. This borehole is tied to high-resolution seismic-reflection profiles that cover an 1100 km(2) area of the middle and lower Hueneme submarine fan and most of the basin plain. The resulting stratigraphic framework provides the highest temporal resolution for a thick-bedded Holocene turbidite succession to date, permitting an evaluation of source-to-sink controls at millennial (1000 yr) scales. The depositional history from 7 ka to present indicates that the recurrence interval for large turbidity-current events is relatively constant (300-360 yr), but the volume of sediment deposited on the fan and in the basin plain has increased by a factor of 2 over this period. Moreover, the amount of sand per event on the basin plain during the same interval has increased by a factor of 7. Maps of sediment distribution derived from correlation of seismic-reflection profiles indicate that this trend cannot be attributed exclusively to autogenic processes (e.g., progradation of depocenters). The observed variability in sediment accumulation rates is thus largely controlled by allogenic factors, including: (1) increased discharge of Santa Clara River as a result of increased magnitude and frequency of El Nino-Southern Oscillation (ENSO) events from ca. 2 ka to present, (2) an apparent change in routing of coarse-grained sediment within the staging area at ca. 3 ka (i.e., from direct river input to indirect, littoral cell input into Hueneme submarine canyon), and (3) decreasing rates of sea-level rise (i.e., rate of rise slowed considerably by ca. 3 ka). The Holocene history of the Santa Clara River-Santa Monica Basin source-to-sink system demonstrates the ways in which varying sediment flux and changes in dispersal pathways affect the basinal stratigraphic record.
id: 876; 478QZ Times Cited:1 Cited References Count:90Y

Compound-specific radiocarbon analysis – analytical challenges and applications - Mollenhauer, G.; Rethemeyer, Janet (IOP conference proceedings: Earth and Environmental Sciences, 2009)
id: 884Y

Distribution of artificial radionuclides in deep sediments of the Mediterranean Sea - Garcia-Orellana, J.; Pates, J. M.; Masque, P.; Bruach, J. M.; Sanchez-Cabeza, J. A. (Science of the Total Environment, 2009)
Artificial radionuclides enter the Mediterranean Sea mainly through atmospheric deposition following nuclear weapons tests and the Chernobyl accident, but also through the river discharge of nuclear facility effluents. Previous studies of artificial radionuclides impact of the Mediterranean Sea have focussed on shallow, coastal sediments. However, deep sea sediments have the potential to store and accumulate pollutants, including artificial radionuclides. Deep sea marine sediment cores were collected from Mediterranean Sea abyssal plains (depth >2000 m) and analysed for Pu-239,Pu-240 and Cs-137 to elucidate the concentrations, inventories and sources of these radionuclides in the deepest areas of the Mediterranean. The activity - depth profiles of Pb-210, together with 14 C dating, indicate that sediment mixing redistributes the artificial radionuclides within the first 2.5 cm of the sedimentary column. The excess Pb-210 inventory was used to normalize Pu-239,Pu-240 and Cs-137 inventories for variable sediment fluxes. The Pu-239,Pu-240/Pb-210(xs) ratio was uniform across the entire sea, with a mean value of 1.24 x 10(-3), indicating homogeneous fallout of Pu-239,Pu-240. The Cs-137/Pb-210(xs) ratio showed differences between the eastern (0.049) and western basins (0.030), clearly significant impact of deep sea sediments from the Chernobyl accident. The inventory ratios of Pu-239,Pu-240/Cs-137 were 0.041 and 0.025 in the western and eastern basins respectively, greater than the fallout ratio, 0.021, showing more efficient scavenging of Pu-231,Pu-210 in the water column and major sedimentation of Cs-137 in the eastern basin. Although areas with water depths of >2000 m constitute around 40% of the entire Mediterranean basin, the sediments in these regions only contained 2.7% of the Pu-239,Pu-240 and 0.95% of the Cs-137 deposited across the Sea in 2000. These data show that the accumulation of artificial radionuclides in deep Mediterranean environments is much lower than predicted by other studies from the analysis of continental shelf sediments. (C) 2008 Elsevier B.V, All rights reserved.
id: 871; 389FH Times Cited:2 Cited References Count:63Y

Dynamics of particle export on the Northwest Atlantic margin - Hwang, J.; Manganini, S. J.; Montlucon, D. B.; Eglinton, T. I. (Deep-Sea Research Part I-Oceanographic Research Papers, 2009)
The Northwest Atlantic margin is characterized by high biological productivity in shelf and slope surface waters. In addition to carbon supply to underlying sediments, the persistent, intermediate depth nepheloid layers emanating from the continental shelves, and bottom nepheloid layers maintained by strong bottom currents associated with the southward flowing Deep Western Boundary Current (DWBC), provide conduits for export of organic carbon over the margin and/or to the interior ocean. As a part of a project to understand dynamics of particulate organic carbon (POC) cycling in this region, we examined the bulk and molecular properties of time-series sediment trap samples obtained at 968 m, 1976 m, and 2938 m depths from a bottom-tethered mooring on the New England slope (water depth, 2988 m). Frequent occurrences of higher fluxes in deep relative to shallower sediment traps and low Delta C-14 values of sinking POC together provide strong evidence for significant lateral transport of aged organic matter over the margin. Comparison of biogeochemical properties such as aluminum concentration and flux, and iron concentration between samples intercepted at different depths shows that particles collected by the deepest trap had more complex sources than the shallower ones. These data also suggest that at least two modes of lateral transport exist over the New England margin. Based on radiocarbon mass balance, about 30% (+/- 10%) of sinking POC in all sediment traps is estimated to be derived from lateral transport of resuspended sediment. A strong correlation between Delta C-14 values and aluminum concentrations suggests that the aged organic matter is associated with lithogenic particles. Our results suggest that lateral transport of organic matter, particularly that resulting from sediment resuspension, should be considered in addition to vertical supply of organic matter derived from primary production, in order to understand carbon cycling and export over continental margins. (C) 2009 Elsevier Ltd. All rights reserved.
id: 1829; 490AT Times Cited:0 Cited References Count:61Y

Evidence of centennial-scale drought from southeastern Massachusetts during the Pleistocene/Holocene transition - Newby, P. E.; Donnelly, J. P.; Shuman, B. N.; MacDonald, D. (Quaternary Science Reviews, 2009)
A principal method for studying past hydroclimatic change is the reconstruction of paleo-lake levels. Here, we provide high-resolution lake-level records from New Long Pond and Rocky Pond in southeastern Massachusetts, which each contain evidence for multiple, sub-centennial-to-millennial scale low stands during the transition between the Late Pleistocene (15.0 ka) and Middle Holocene (ca 7.0 ka). Data from New Long Pond also demonstrate sedimentary evidence for a drop in water levels in the early to mid AD 20th century, when long-term trends in instrumental data show lower-than-average precipitation in the northeastern United States. Local data show the most precipitous declines in precipitation and groundwater levels are concurrent with the most severe drought in the AD 1960s, which occurred during a period of low sea-surface temperatures in the western North Atlantic. Ground penetrating radar and sediment core data indicate five intervals with numerous paleo-shoreline deposits between ca 15.0 and 7.0 ka, similar to the layer deposited in the AD 1960s. Many of the intervals of low lake levels coincide with proposed meltwater release events or abrupt climate oscillations in the circum North Atlantic. For example, we document at least three low stands during the Younger Dryas (12.9-11.6 ka) and in association with the "9.2" and "8.2" ka events. The combined evidence of (1) concurrent paleo-droughts in southeastern New England with documented North Atlantic abrupt cooling events and (2) recent drought with the modern association of low sea-surface temperatures indicates that freshening and cooling of the western North Atlantic is a viable mechanism for decreasing moisture within the region. Large-scale changes in seasonality and ice sheet extent also may have increased the susceptibility of the northeast to dry conditions triggered by changes in the North Atlantic. (C) 2009 Elsevier Ltd. All rights reserved.
id: 858; ISI Document Delivery No.: 484ZD Times Cited: 1 Cited Reference Count: 97 Cited References: ALLEY RB, 1993, NATURE, V362, P527 ALLEY RB, 1997, GEOLOGY, V25, P483 ALLEY RB, 2000, P NATL ACAD SCI USA, V97, P1331 ALLEY RB, 2004, IGBP PAGES WORLD DAT ALLEY RB, 2005, QUATERNARY SCI REV, V24, P1123, DOI 10.1016/j.quascirev.2004.12.004 ALLEY RB, 2007, ANNU REV EARTH PL SC, V35, P241 ALMQUIST H, 2001, HOLOCENE, V11, P189 BARBER DC, 1999, NATURE, V400, P344 BJORCK S, 1998, J QUATERNARY SCI, V13, P283 BOND G, 2001, SCIENCE, V294, P2130 BRADLEY RS, 2008, QUATERNARY RES, V70, P1, DOI 10.1016/j.yqres.2008.03.002 BROECKER WS, 1985, NATURE, V315, P21 BROECKER WS, 1989, NATURE, V341, P318 BROECKER WS, 2006, SCIENCE, V312, P1146, DOI 10.1126/science.1123253 CAME RE, 2007, GEOLOGY, V35, P315, DOI 10.1130/G23455A.1 CLARK PU, 2001, SCIENCE, V293, P283 CLARK PU, 2002, NATURE, V415, P863 DEAN WE, 1974, J SEDIMENT PETROL, V44, P242 DIEFENDORF AF, 2006, QUATERNARY RES, V65, P78, DOI 10.1016/j.yqres.2005.08.001 DIEFFENBACHERKRALL AC, 2005, J PALEOLIMNOL, V34, P283, DOI 10.1007/s10933-005-4958-8 DIGERFELDT G, 1986, HDB HOLOCENE PALAEOE, P127 DONNELLY JP, 2001, GEOL SOC AM BULL, V113, P714 DONNELLY JP, 2001, P NATL ACAD SCI USA, V98, P14218 DONNELLY JP, 2005, GEOLOGY, V33, P89, DOI 10.1130/G21043.1 ELLISON CRW, 2006, SCIENCE, V312, P1929, DOI 10.1126/science.1127213 FIRESTONE RB, 2007, P NATL ACAD SCI USA, V104, P16016, DOI 10.1073/pnas.0706977104 FISHER TG, 2002, QUATERNARY SCI REV, V21, P873 FLEITMANN D, 2008, PALEOCEANOGRAPHY, V23, P1 GUILESELLIS K, 2004, J PALEOLIMNOL, V31, P343 HALD M, 1998, GEOLOGY, V26, P615 HANSEN BP, 1992, 904204 US GEOL SURV HARRISON SP, 1989, CLIM DYNAM, V3, P157 HOU J, 2006, GEOCHEM GEOPHY GEOSY, V7, P1 HUA Q, 2004, RADIOCARBON, V46, P1273 HUANG YS, 2002, GEOLOGY, V30, P1103 JOHNSEN SJ, 1992, NATURE, V359, P311 KARL TR, 1990, NDP019R NOAA NAT CLI KEIGWIN LD, 2005, PALEOCEANOGRAPHY, V20, P1 KENNETT DJ, 2009, SCIENCE, V323, P94, DOI 10.1126/science.1162819 KIRBY ME, 2002, GEOLOGICAL SOC AM B, V114, P1327 KLEIVEN HF, 2008, SCIENCE, V319, P60, DOI 10.1126/science.1148924 KUTZBACH JE, 1988, SCIENCE, V241, P1043 LARSON GJ, 1982, LATE WISCONSINAN GLA, P101 LAVOIE M, 2000, HOLOCENE, V10, P621 LEGRANDE AN, 2006, P NATL ACAD SCI USA, V103, P837 LEVESQUE AJ, 1993, NATURE, V361, P623 LEVESQUE AJ, 1997, NATURE, V385, P423 LI YX, 2006, HOLOCENE, V16, P1043 LICCIARDI JM, 1999, GEOPH MONOG SERIES, V112, P177 LOWELL TV, 2005, EOS, V86, P365, DOI 10.1029/2005EO400001 MAGNY M, 2004, QUATERNARY RES, V61, P181, DOI 10.1016/j.yqres.2003.12.003 MARSHALL JD, 2007, GEOLOGY, V35, P639, DOI 10.1130/G23498A.1 MCMANUS JF, 2004, NATURE, V428, P834, DOI 10.1038/nature02494 MEISSNER KJ, 2006, GEOPHYS RES LETT, V33, P1 MOTT RJ, 1986, GEOLOGICAL SURVEY CA, V86, P289 MULLER SD, 2003, PALAEOGEOGR PALAEOCL, V193, P51, DOI 10.1016/S0031-0182(02)00710-1 NAMIAS J, 1966, MON WEA REV, V94, P543 NEWBY PE, 2000, QUATERNARY RES, V53, P352 PACHAURI RK, 2007, CLIMATE CHANGE 2007 PETEET DM, 1990, QUATERNARY RES, V33, P219 RAHMSTORF S, 1995, NATURE, V378, P145 RASMUSSEN SO, 2006, J GEOPHYS RES, V111, P1 RASMUSSEN SO, 2007, QUATERNARY SCI REV, V26, P1907, DOI 10.1016/j.quascirev.2007.06.015 RAYNER NA, 2003, J GEOPHYS RES, V108, P1 REIMER PJ, 2004, RADIOCARBON, V46, P1029 REIMER PJ, 2004, RADIOCARBON, V46, P1299 RICHARD PJH, 2005, QUATERNARY RES, V63, P353, DOI 10.1016/j.yqres.2005.02.003 RIDGE JC, 2003, NEW YORK STATE MUSEU, V497, P15 RIND D, 1986, CLIM DYNAM, V1, P3 ROBINSON GR, 2003, GEN LITHOLOGY LITHOG ROHLING EJ, 2005, NATURE, V434, P975, DOI 10.1038/nature03421 RUDDIMAN WF, 1981, PALAEOGEOGR PALAEOCL, V35, P145 SHEMESH A, 1998, GEOPHYS RES LETT, V25, P1935 SHUMAN B, 2001, QUATERNARY RES, V56, P401 SHUMAN B, 2002, QUATERNARY SCI REV, V21, P1793 SHUMAN B, 2005, ANN ASSOC AM GEOGR, V95, P237 SHUMAN B, 2006, QUATERNARY RES, V65, P44, DOI 10.1016/j.yqres.2005.09.001 SHUMAN BN, 2009, QUATERNARY SCI REV, V28, P1693, DOI 10.1016/j.quascirev.2009.04.005 STANFORD JD, 2006, PALEOCEANOGRAPHY, V21, P1 STUIVER M, 2000, QUATERNARY RES, V53, P277 SWAIN PC, 2001, LASSIFICATION NATUR TELLER JT, 2002, QUATERNARY SCI REV, V21, P879 TELLER JT, 2004, GEOL SOC AM BULL, V116, P729, DOI 10.1130/B25316.1 TELLER JT, 2005, QUATERNARY SCI REV, V24, P1890, DOI 10.1016/j.quascirev.2005.01.008 VANGEEL B, 1999, QUATERNARY SCI REV, V18, P331 VESKI S, 2004, GEOLOGY, V32, P681, DOI 10.1130/G20683-1 WANDLE WS, 1991, US GEOLOGICAL SURVEY, V2375, P327 WEBB RS, 1988, QUATERNARY RES, V30, P284 WEBB RS, 1990, THESIS BROWN U PROVI WEBB RS, 1993, QUATERNARY RES, V40, P213 WEBB T, 1993, GLOBAL CLIMATES LAST, P415 WIERSMA AP, 2006, CLIM DYNAM, V27, P831, DOI 10.1007/s00382-006-0166-0 WIERSMA AP, 2006, QUATERNARY SCI REV, V25, P63, DOI 10.1016/j.quascirev.2005.07.009 WINKLER MG, 1985, QUATERNARY RES, V23, P235 YU ZC, 1998, SCIENCE, V282, P2235 YU ZC, 2001, EARTH-SCI REV, V52, P333 YU ZC, 2001, GEOGR PHYS QUATERN, V55, P171 Newby, Paige E. Donnelly, Jeffrey P. Shuman, Bryan N. MacDonald, Dana Pergamon-elsevier science ltd Oxford Sp. Iss. SI; YY

Evidence of paleo-cold seep activity from the Bay of Bengal, offshore India - Mazumdar, A.; Dewangan, P.; Joao, H. M.; Peketi, A.; Khosla, V. R.; Kocherla, M.; Badesab, F. K.; Joshi, R. K.; Roxanne, P.; Ramamurty, P. B.; Karisiddaiah, S. M.; Patil, D. J.; et al. (Geochemistry Geophysics Geosystems, 2009)
We report evidence of paleo-cold seep associated activities, preserved in methane-derived carbonates in association with chemosynthetic clams (Calyptogena sp.) from a sediment core in the Krishna-Godavari basin, Bay of Bengal. Visual observations and calculations based on high-resolution wet bulk density profile of a core collected on board R/V Marion Dufresne (May 2007) show zones of sharp increase in carbonate content (10-55 vol%) within 16-20 meters below seafloor (mbsf). The presence of Calyptogena clam shells, chimneys, shell breccias with high Mg calcite cement, and pyrite within this zone suggest seepage of methane and sulfide-bearing fluid to the seafloor in the past. Highly depleted carbon isotopic values (delta C-13 ranges from -41 to -52% VPDB) from these carbonates indicate carbon derived via anaerobic oxidation of methane. Extrapolated mean calendar age (similar to 58.7 ka B. P.) of the clastic sediments at a depth of 16 mbsf is close to the upper limit of the U-Th based depositional age (46.2 +/- 3.7 and 53.0 +/- 1.6 ka) of authigenic carbonates sampled from this level, thereby constraining the younger age limit of the carbonate deposition/methane expulsion events. The observed carbonate deposition might have resulted from the flow of methane-enriched fluids through the fracture network formed because of shale diapirism.
id: 794; 458FC Times Cited:0 Cited References Count:80Y

Field Survey and Geological Effects of the 15 November 2006 Kuril Tsunami in the Middle Kuril Islands - MacInnes, B. T.; Pinegina, T. K.; Bourgeois, J.; Razhigaeva, N. G.; Kaistrenko, V. M.; Kravchunovskaya, E. A. (Pure and Applied Geophysics, 2009)
The near-field expression of the tsunami produced by the 15 November 2006 Kuril earthquake (M-w 8.1-8.4) in the middle Kuril Islands, Russia, including runup of up to 20 m, remained unknown until we conducted a post-tsunami survey in the summer of 2007. Because the earthquake occurred between summer field expeditions in 2006 and 2007, we have observations, topographic profiles, and photographs from three months before and nine months after the tsunami. We thoroughly surveyed portions of the islands of Simushir and Matua, and also did surveys on parts of Ketoi, Yankicha, Ryponkicha, and Rasshua. Tsunami runup in the near-field of the middle Kuril Islands, over a distance of about 200 km, averaged 10 m over 130 locations surveyed and was typically between 5 and 15 m. Local topography strongly affected inundation and somewhat affected runup. Higher runup generally occurred along steep, protruding headlands, whereas longer inundation distances occurred on lower, flatter coastal plains. Sediment transport was ubiquitous where sediment was available-deposit grain size was typically sand, but ranged from mud to large boulders. Wherever there were sandy beaches, a more or less continuous sand sheet was present on the coastal plain. Erosion was extensive, often more extensive than deposition in both space and volume, especially in areas with runup of more than 10 m. The tsunami eroded the beach landward, stripped vegetation, created scours and trim lines, cut through ridges, and plucked rocks out of the coastal plain.
id: 831; 418XP Times Cited:2 Cited References Count:46Y

Fish scales in sediments from off Callao, central Peru - Diaz-Ochoa, J. A.; Lange, C. B.; Pantoja, S.; De lange, G. J.; Gutierrez, D.; Munoz, P.; Salamanca, M. (DEEP-SEA RESEARCH PART II-TOPICAL STUDIES IN OCEANOGRAPHY, 2009)
We study fish scales as a proxy of fish abundance and preservation biases together with phosphorus from fish remains (P(fish)) in a sediment core retrieved off Callao, Peru (12 degrees 1'S, 77 degrees 42'W; water depth = 179 m; core length = 52 cm). We interpret our results as a function of changing redox conditions based on ratios of redox-sensitive trace elements (Cu/Al, Mo/Al, Ni/Al, Zn/Al, V/Al), terrigenous indicators (Fe in clays, Ti, Al), and biogenic proxies (CaCO(3), biogenic opal, total nitrogen, organic carbon, barite Ba). The core covers roughly 700 years of deposition, based on (210)Pb activities extrapolated downcore and (14)C dating at selected intervals. Our fish-scale record is dominated by anchovy (Engraulis ringens) scales followed by hake (Merluccius gayii) scales. The core presented an abrupt lithological change at 17 cm (corresponding to the early 19th century). Above that depth, it was laminated and was more organic-rich (10-15% organic carbon) than below, where the core was partly laminated and less organic-rich (< 10%). The lithological shift coincides with abrupt changes in dry bulk density and in the contents of terrigenous and redox-sensitive trace elements, biogenic proxies, and fish scales. The remarkable increase in redox-sensitive trace elements in the upper 17 cm of the core suggests more reducing conditions when compared with deeper and older horizons, and is interpreted as an intensification of the oxygen minimum zone off Peru beginning in the early 19th century. Higher fish-scale contents and higher P(fish)/P(total) ratios were also observed within the upper 17 cm of the core. The behavior of biogenic proxies and redox-sensitive trace elements was similar; more reduced conditions corresponded to higher contents of CaCO(3), C(org), total nitrogen and fish scales, suggesting that these proxies might convey an important preservation signal. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Callao; Clupeoid fish; Molybdenum; Oxygen minimum zone; Peru; Redox-sensitive trace elements

High mitogenomic evolutionary rates and time dependency - Subramanian, Sankar; Denver, Dee R.; Millar, Craig D.; Heupink, Tim; Aschrafi, Angelique; Emslie, Steven D.; Baroni, Carlo; Lambert, David M. (Trends in Genetics, 2009)
Using entire modern and ancient mitochondrial genomes of Adelie penguins (Pygoscelis adeliae) that are up to 44000 years old, we show that the rates of evolution of the mitochondrial genome are two to six times greater than those estimated from phylogenetic comparisons. Although the rate of evolution at constrained sites, including nonsynonymous positions and RNAs, varies more than twofold with time (between shallow and deep nodes), the rate of evolution at synonymous sites remains the same. The time-independent neutral evolutionary rates reported here would be useful for the study of recent evolutionary events.
id: 1917; PT: J; NR: 27; TC: 19; J9: TRENDS GENET; PG: 5; GA: 518TW; UT: WOS:000271717800004

High-sensitivity measurement of diverse vascular plant-derived biomarkers in high-altitude ice cores - Makou, Matthew C.; Thompson, Lonnie G.; Montluçon, Daniel B.; Eglinton, Timothy I. (GEOPHYSICAL RESEARCH LETTERS, 2009)
Semi-volatile organic compounds derived from burned and fresh vascular plant sources and preserved in high-altitude ice fields were detected and identified through use of recently developed analytical tools. Specifically, stir bar sorptive extraction and thermal desorption coupled with gas chromatography/time-of-flight mass spectrometry allowed measurement of multiple biomarkers in small sample volumes (<= 30 ml). Among other compounds of interest, several diterpenoids, which suggest inputs from conifers and conifer burning, were identified in post-industrial era and older Holocene ice from the Sajama site in the Bolivian Andes, but not in a glacial period sample, consistent with aridity changes. Differences in biomarker assemblages between sites support the use of these compounds as regionally constrained recorders of vegetation and climate change. This study represents the first application of these analytical techniques to ice core research and the first indication that records of vegetation fires may be reconstructed from diterpenoids in ice. Citation: Makou, M. C., L. G. Thompson, D. B. Montlucon, and T. I. Eglinton (2009), High-sensitivity measurement of diverse vascular plant-derived biomarkers in high-altitude ice cores, Geophys. Res. Lett., 36, L13501, doi: 10.1029/2009GL037643.

Holocene sea-level changes along the North Carolina Coastline and their implications for glacial isostatic adjustment models - Horton, B. P.; Peltier, W. R.; Culver, S. J.; Drummond, R.; Engelhart, S. E.; Kemp, A. C.; Mallinson, D.; Thieler, E. R.; Riggs, S. R.; Ames, D. V.; Thomson, K. H. (Quaternary Science Reviews, 2009)
We have synthesized new and existing relative sea-level (RSL) data to produce a quality-controlled, spatially comprehensive database from the North Carolina coastline. The RSL database consists of 54 sea-level index points that are quantitatively related to an appropriate tide level and assigned an error estimate, and a further 33 limiting dates that confine the maximum and minimum elevations of RSL The temporal distribution of the index points is very uneven with only five index points older than 4000 cal a BP, but the form of the Holocene sea-level trend is constrained by both terrestrial and marine limiting dates. The data illustrate RSL rapidly rising during the early and mid Holocene from an observed elevation of -35.7 +/- 1.1 m MSL at 11062-10576 cal a BP to -4.2 m +/- 0.4 m MSL at 4240-3592 cal a BP. We restricted comparisons between observations and predictions from the ICE-5G(VM2) with rotational feedback Glacial Isostatic Adjustment (GIA) model to the Late Holocene RSL (last 4000 cal a BP) because of the wealth of sea-level data during this time interval. The ICE-5G(VM2) model predicts significant spatial variations in RSL across North Carolina, thus we subdivided the observations into two regions. The model forecasts an increase in the rate of sea-level rise in Region 1 (Albemarle, Currituck, Roanoke, Croatan, and northern Pamlico sounds) compared to Region 2 (southern Pamlico, Core and Bogue sounds, and farther south to Wilmington). The observations show Late Holocene sea-level rising at 1.14 +/- 0.03 mm year(-1) and 0.82 +/- 0.02 mm year(-1) in Regions 1 and 2, respectively. The ICE-5G(VM2) predictions capture the general temporal trend of the observations, although there is an apparent misfit for index points older than 2000 cal a BR It is presently unknown whether these misfits are caused by possible tectonic uplift associated with the mid-Carolina Platform High or a flaw in the CIA model. A comparison of local tide gauge data with the Late Holocene RSL trends from Regions 1 and 2 support the spatial variation in RSL across North Carolina, and imply an additional increase of mean sea level of greater than 2 mm year(-1) during the latter half of the 20th century; this is in general agreement with historical tide gauge and satellite altimetry data. (C) 2009 Elsevier Ltd. All rights reserved.
id: 814; Sp. Iss. SI 484ZD Times Cited:1 Cited References Count:108Y

Human impacts, climate change, and aquatic ecosystem response during the past 2000 yr at Lake Wandakara, Uganda - Russell, James M.; McCoy, S. J.; Verschuren, D.; Bessems, I.; Huang, Y. (Quaternary Research, 2009)
Analyses of carbon and hydrogen isotope ratios of terrestrial leaf waxes and the carbon and nitrogen abundance. ratio, and isotopic composition of bulk sediments from Like Wandakara, a crater lake in western Uganda, East Africa. document human and climatic controls on the aquatic system and oil the Surrounding terrestrial vegetation during the past two millennia Our data indicate that Wandakara was a relatively stable, productive lake Surrounded by C(3) vegetation from AD 70 to 1000. Abrupt changes in the delta(13)C of terrestrial leaf waxes indicate a series of abrupt shifts in the relative abundance of C(3) and C(4) vegetation caused by a combination of climate change and human activities around Wandakara beginning at AD 1000. Abrupt shifts in bulk sediment organic geochemistry. particularly C/N ratios and delta(15)N, indicate that human activities at this time caused permanent changes in the limnology of Lake Wandakara. including eutrophication Our results suggest that the biogeochemistry of Like Wandakara was more sensitive to shifting human impacts than to climate variations during the past millennium, highlighting the importance of understanding the intensity of pre-colonial human impacts on Africa's aquatic ecosystems (C) 2009 University of Washington Published by Elsevier Inc All rights reserved
id: 2052; PT: J; UT: WOS:000271254000002

Intcal09 and Marine09 Radiocarbon Age Calibration Curves, 0-50,000 Years Cal Bp Rid F-4952-2011 Rid B-7298-2008 - Reimer, P. J.; Baillie, M. G. L.; Bard, E.; Bayliss, A.; Beck, J. W.; Blackwell, P. G.; Ramsey, C. Bronk; Buck, C. E.; Burr, G. S.; Edwards, R. L.; Friedrich, M.; Grootes, P. M.; et al. (Radiocarbon, 2009)
The IntCal04 and Marine04 radiocarbon calibration curves have been updated from 12 cal kBP (cal kBP is here defined as thousands of calibrated years before AD 1950), and extended to 50 cal kBP, utilizing newly available data sets that meet the IntCal Working Group criteria for pristine corals and other carbonates and for quantification of uncertainty in both the (14)C and calendar timescales as established in 2002. No change was made to the curves from 0-12 cal kBP. The curves were constructed using a Markov chain Monte Carlo (MCMC) implementation of the random walk model used for IntCal04 and Marine04. The new curves were ratified at the 20th International Radiocarbon Conference in June 2009 and; ire available in the Supplemental Material at www.radiocarbon.org.
id: 1983; PT: J; UT: WOS:000274407500002

Interpreting Nd isotope and Pa-231/Th-230 records in the deep Western North Atlantic - Roberts, N. L.; Piotrowski, A. M.; McManus, J. F.; Keigwin, L. D. (Geochimica Et Cosmochimica Acta, 2009)
Suppl. S460ys Times Cited:0 Cited References Count:3
Keywords: circulation

A late Holocene paleo-productivity record in the western Gulf of Maine, USA, inferred from growth histories of the long-lived ocean quahog (Arctica islandica) - Wanamaker, Alan D. Jr.; Kreutz, Karl J.; Schoene, Bernd R.; Maasch, Kirk A.; Pershing, Andrew J.; Borns, Harold W.; Introne, Douglas S.; Feindel, Scott (INTERNATIONAL JOURNAL OF EARTH SCIENCES, 2009)
To investigate environmental variability during the late Holocene in the western Gulf of Maine, USA, we collected a 142-year-old living bivalve (Arctica islandica) in 2004, and three fossil A. islandica shells of the Medieval Warm Period (MWP) and late MWP / Little Ice Age (LIA) period (corrected C-14(AMS) = 1030 +/- A 78 ad; 1320 +/- A 45 ad; 1357 +/- A 40 ad) in 1996. We compared the growth record of the modern shell with continuous plankton recorder (CPR) time-series (1961-2003) from the Gulf of Maine. A significant correlation (r (2) = 0.55; p < 0.0001) exists between the standardized annual growth index (SGI) of the modern shell and the relative abundance of zooplankton species Calanus finmarchicus. We therefore propose that SGI data from A. islandica is a valid proxy for paleo-productivity of at least one major zooplankton taxa. SGIs from these shells reveal significant periods of 2-6 years (NAO-like) based on wavelet analysis, multitaper method (MTM) analysis and singular spectrum analysis (SSA) during the late Holocene. Based on established physical oceanographic observation in the Gulf of Maine, we suggest that slope water variability coupled with North Atlantic Oscillation (NAO) dynamics is primarily responsible for the observed SGI variability.
Keywords: Arctica islandica; Climate variability; Gulf of Maine; North Atlantic Oscillation (NAO); Paleo-productivity; Shell growth

Late Quaternary foraminiferal assemblages from western Ross Sea (Antarctica) in relation to the main glacial and marine lithofacies - Melis, R.; Salvi, G. (Marine Micropaleontology, 2009)
investigations oil foraminifers from Upper Pleistocene-Holocene sediments were carried Out On twelve cores from the western Ross Sea continental margin (Drygalski, Joides, North Victoria Land Basins) as part of a "Progetto Nazionale di Ricerche in Antartide" (P.N.R.A.) multidisciplinary project. Data on the foraminiferal frequency, species diversity, tests abundance and their state of preservation were presented as a synthesis of 404 core samples to establish their relationships with the main glacial and marine lithofacies of this area. A total of 126 benthic species. pertaining to 73 genera have been identified; just few taxa, such as Cibicides spp., Globocassidulina spp., Trifarina angulosa and Miliammina spp. being the most ubiquitous and in some cases the dominant species of these paleoenvironments. Two variants of Neogloboquadrina pachyderma, including thin and thick-shelled forms have been recovered. We propose to use these results to provide the degree of glacial control during the Last Glacial Maximum and the following Holocene retreat of the ice sheets. High test fragmentation, low diversity and density tests reflect higher glacial influence of the ice sheet in the Drygalski Basin, whereas the decreasing percentage of fragmentation and a relative increase of density and diversity in Drygalski, Joides and North Victoria Land Basins indicate the paleoenvironmental passage from the ice sheet to the ice shelf condition. The ice shelf retreat is well evidenced in the Joides Basin by a succession of levels barren of foraminifers alternating with high-density levels, rich in T angulosa, followed by a total disappearance of the calcareous foraminifers. Open-marine settings indicative of lower glacial influence and increased corrosiveness of the water masses is testified by the Miliammina foraminiferal assemblage during the Holocene in Drygalski and Joides Basins cores. On the contrary, rich and abundant benthic and planktonic assemblages characterize the Holocene paleoenvironment of the North Victoria Land area, indicating that the water masses were less corrosive with respect to the other areas. In addition to the glacial reworking of the tests, and the dissolution due to the corrosive water mass conditions, the volcaniclastic sediments recovered in the North Victoria Land Basin cores also affected the condition of test preservation. In volcaniclastic sediments, older than about 20 ka BP, the foraminifers concentration tends to zero and, when present, their tests are highly damaged or completely broken. (c) 2008 Elsevier B.V. All rights reserved.
id: 1879; 405HR Times Cited:0 Cited References Count:66Y

Late Quaternary sediment-accumulation rates within the inner basins of the California Continental Borderland in support of geologic hazard evaluation - Normark, William R.; McGann, Mary; Sliter, Ray W. (Geological Society of America Special Papers, 2009)
An evaluation of the geologic hazards of the inner California Borderland requires determination of the timing for faulting and mass-movement episodes during the Holocene. Our effort focused on basin slopes and turbidite systems on the basin floors for the area between Santa Barbara and San Diego, California. Dating condensed sections on slopes adjacent to fault zones provides better control on fault history where high-resolution, seismic-reflection data can be used to correlate sediment between the core site and the fault zones. This study reports and interprets 147 radiocarbon dates from 43 U.S. Geological Survey piston cores as well as 11 dates from Ocean Drilling Program Site 1015 on the floor of Santa Monica Basin. One hundred nineteen dates from 39 of the piston cores have not previously been published. Core locations were selected for hazard evaluation, but despite the nonuniform distribution of sample locations, the dates obtained for the late Quaternary deposits are useful for documenting changes in sediment-accumulation rates during the past 30 ka. Cores from basins receiving substantial sediment from rivers, i.e., Santa Monica Basin and the Gulf of Santa Catalina, show a decrease in sediment supply during the middle Holocene, but during the late Holocene after sea level had reached the current highstand condition, rates then increased partly in response to an increase in El Ni√±o‚ÄìSouthern Oscillation events during the past 3.5 ka.
id: 1906; 10.1130/2009.2454(2.6)

Mangrove ecosystem changes during the Holocene at Spanish Lookout Cay, Belize - Monacci, N. M.; Meier-Grunhagen, U.; Finney, B. P.; Behling, H.; Wooller, M. J. (Palaeogeography Palaeoclimatology Palaeoecology, 2009)
Mangroves are halophytic plants living at the land-sea interface and are therefore natural trackers of sea-level. Multiple proxies of a continuous (8 m) mangrove peat core (BT-79) from Spanish Lookout Cay, Belize illustrate mangrove ecosystem changes during the Holocene. Radiocarbon measurements show this site was colonized by mangroves similar to 8000 cal. yrs BP, with a significant decrease in the peat accumulation rate from similar to 6000 to 1000 cal. yrs BR Stratigraphic characteristics of this peat core such as bulk density, magnetic susceptibility, and loss on ignition show relative uniformity, inferring an uninterrupted mangrove ecosystem during a majority of the Holocene. This is supported by pollen data from BT-79 that show that the site has been consistently dominated by Rhizophora mangle (red mangrove), with Avicennia germinans (black mangrove) and Laguncularia racemosa (white mangrove) present as well. Subfossil R. mangle leaves are used for stable nitrogen, carbon, and oxygen isotope (delta N-15, delta C-13, and delta O-18) analyses. delta N-15 and delta C-13 values provide a proxy of this plant's past physiology and stand structure showing that dwarf (delta N-15
id: 1834; 496QP Times Cited:1 Cited References Count:50Y

Moderate rates of late Quaternary slip along the northwestern margin of the Basin and Range Province, Surprise Valley fault, northeastern California - Personius, Stephen F.; Crone, Anthony J.; Machette, Michael N.; Mahan, Shannon A.; Lidke, David J. (Journal of Geophysical Research-Solid Earth, 2009)
The 86-km-long Surprise Valley normal fault forms part of the active northwestern margin of the Basin and Range province in northeastern California. We use trench mapping and radiocarbon, luminescence, and tephra dating to estimate displacements and timing of the past five surface-rupturing earthquakes on the central part of the fault near Cedarville. A Bayesian OxCal analysis of timing constraints indicates earthquake times of 18.2 +/- 2.6, 10.9 +/- 3.2, 8.5 +/- 0.5, 5.8 +/- 1.5, and 1.2 +/- 0.1 ka. These data yield recurrence intervals of 7.3 +/- 4.1, 2.5 +/- 3.2, 2.7 +/- 1.6, and 4.5 +/- 1.5 ka and an elapsed time of 1.2 +/- 0.1 ka since the latest surface-rupturing earthquake. Our best estimate of latest Quaternary vertical slip rate is 0.6 +/- 0.1 mm/a. This late Quaternary rate is remarkably similar to long-term (8-14 Ma) minimum vertical slip rates (>0.4-0.5 +/- 0.3 mm/a) calculated from recently acquired seismic reflection and chronologic and structural data in Surprise Valley and the adjacent Warner Mountains. However, our slip rate yields estimates of extension that are lower than recent campaign GPS determinations by factors of 1.5-4 unless the fault has an unusually shallow (30 degrees-35 degrees) dip as suggested by recently acquired seismic reflection data. Coseismic displacements of 2-4.5 +/- 1 m documented in the trench and probable rupture lengths of 53-65 km indicate a history of latest Quaternary earthquakes of M 6.8-7.3 on the central part of the Surprise Valley fault.
id: 2021; PT: J; UT: WOS:000270058200001

Molecular and isotopic constraints on the sources of suspended particulate organic carbon on the northwestern Atlantic margin - Hwang, J.; Montlucon, D.; Eglinton, T. I. (Deep-Sea Research Part I-Oceanographic Research Papers, 2009)
The abundance, carbon isotopic composition (Delta C-14 and delta C-13), and lipid biomarker (alkenones and saturated fatty acids) distributions of suspended particulate organic matter were investigated at three stations centered on the 2000, 3000, and 3500 m isobaths over the New England slope in order to assess particulate carbon sources and dynamics in this highly productive and energetic region. Transmissometry profiles reveal that particle abundances exhibit considerable fine structure, with several distinct layers of elevated suspended particulate matter concentration at intermediate water depths in addition to the presence of a thick bottom nepheloid layer at each station. Excluding surface water samples, the Delta C-14 values of particulate organic carbon (POC) indicated the presence of a pre-aged component in the suspended POC pool (Delta C-14
id: 774; 471WJ Times Cited:1 Cited References Count:73Y

A multi-proxy paleolimnological reconstruction of Holocene climate conditions in the Great Basin, United States - Reinemann, Scott A.; Porinchu, David F.; Bloom, Amy M.; Mark, Bryan G.; Box, Jason E. (Quaternary Research, 2009)
A sediment core spanning ~†7000†cal yr BP recovered from Stella Lake, a small sub-alpine lake located in Great Basin National Park, Nevada, was analyzed for subfossil chironomids (non-biting midges), diatoms, and organic content (estimated by loss-on-ignition (LOI)). Subfossil chironomid analysis indicates that Stella Lake was characterized by a warm, middle Holocene, followed by a cool "Neoglacial" period, with the last two millennia characterized by a return to warmer conditions. Throughout the majority of the core the Stella Lake diatom-community composition is dominated by small, periphytic taxa which are suggestive of shallow, cool, alkaline, oligotrophic waters with extensive seasonal ice cover. A reconstruction of mean July air temperature (MJAT) was developed by applying a midge-based inference model for MJAT (two-component WA-PLS) consisting of 79 lakes and 54 midge taxa (rjack2†=†0.55, RMSEP†=†0.9∞C). Comparison of the chironomid-inferred temperature record to existing regional paleoclimate reconstructions suggests that the midge-inferred temperatures correspond well to regional patterns. This multi-proxy record provides valuable insight into regional Holocene climate and environmental conditions by providing a quantitative reconstruction of peak Holocene warmth and aquatic ecosystem response to these changes in the Great Basin, a region projected to experience increased aridity and higher temperatures.
id: 880Y

A new look at old carbon in active margin sediments RID F-1809-2010 - Drenzek, Nicholas J.; Hughen, Konrad A.; Montluçon, Daniel B.; Southon, John R.; dos Santos, Guaciara M.; Druffel, Ellen R. M.; Giosan, Liviu; Eglinton, Timothy I. (Geology, 2009)
Recent studies suggest that as much as half of the organic carbon (OC) undergoing burial in the sediments of tectonically active continental margins may be the product of fossil shale weathering. These estimates rely on the assumption that vascular plant detritus spends little time sequestered in intermediate reservoirs such as soils, freshwater sediments, and river deltas, and thus only minimally contributes to the extraneously old (14)C ages of total organic matter often observed on adjacent shelves. Here we test this paradigm by measuring the (14)C and delta(13)C values of individual higher plant wax fatty acids as well as the d13C values of extractable alkanes isolated from the Eel River margin (California). The isotopic signatures of the long chain fatty acids indicate that vascular plant material has been sequestered for several thousand years before deposition. A coupled molecular isotope mass balance used to reassess the sedimentary carbon budget indicates that the fossil component is less abundant than previously estimated, with pre-aged terrestrial material instead composing a considerable proportion of all organic matter. If these findings are characteristic of other continental margins proximal to small mountainous rivers, then the importance of petrogenic OC burial in marine sediments may need to be reevaluated.
id: 1987; PT: J; UT: WOS:000263842200012

Oceanographic and climatologic controls on the compositions and fluxes of biogenic materials in the water column and sediments of the Cariaco Basin over the Late Holocene - Goñi, M. A.; Aceves, H.; Benitez-Nelson, B.; Tappa, E.; Thunell, R.; Black, D. E.; Muller-Karger, F.; Astor, Y.; Varela, R. (Deep-Sea Research Part I-Oceanographic Research Papers, 2009)
Materials collected by sediment traps over a 3-y period and sedimentary horizons from a gravity core covering the last 6000y were used to investigate the effects of climate-related processes such as wind-driven upwelling and regional rainfall on the production, export and burial of particulate organic matter in the Cariaco Basin. A variety of chemical analyses, including organic carbon and nitrogen, biogenic opal, calcite, lithogenic contents, stable carbon isotopic ratios of organic matter and the yields of CuO reaction products derived from distinct biochemicals such as amino acids, fatty acids and lignins, were carried out for this purpose. Principal component analyses were used to investigate the trends in this multivariate data set. These analyses reveal marked temporal differences in the composition of the materials sinking through the water column, which were related to distinct oceanographic and climatic forcings. For example, autorchthonous fluxes, characterized by elevated contents of organic carbon and opal as well as high yields of amino acid and fatty acid reaction products, displayed peaks during periods of intense wind-driven upwelling. In contrast, allochthonous materials, characterized by elevated lithogenic contents and elevated yields of lignin-derived products, were more important during periods of high rainfall, low wind and enhanced stratification. In addition to the strong seasonal contrasts, there was significant temporal variability at both shorter (monthly) and longer (inter-annual) time scales. Hence, other factors, such as zooplankton grazing and El Nino effects on local climatology, may also be important. Examination of the gravity core record yielded several significant trends. For example, there was a marked increase in sediment accumulation rates from 5000 to ca. 700 y before present with concomitant increases in the concentrations of organic carbon, opal and most biomarkers. These results suggest that the Cariaco Basin experienced a marked increase in primary productivity and particle flux to the underlying sediments since the Holocene Thermal Maximum. Also within the sedimentary record, we observed distinct variations in the relative contributions of autochthonous and allochthonous organic matter. The frequency of these variations is roughly 1500y and appears to match ice-rafted debris records from the North Atlantic. Such coincidence indicates cold periods within the Holocene, which are related to minima in insolation, may have led to the southern migration of the inter-tropical convergence zone and the enhancement of wind-driven upwelling, primary productivity and autochthonous organic matter flux to the seabed in the Cariaco Basin. Alternatively, during warm periods, the opposite climatic conditions would have increased both the thermal stratification of the water column and average rainfall in the Cariaco Basin, leading to elevated inputs of allochthonous materials. (C) 2008 Elsevier Ltd. All rights reserved.
id: 1871; 430SK Times Cited:0 Cited References Count:69Y

Palaeoecological potential of the marine organic deposits of Posidonia oceanica: A case study in the NE Iberian Peninsula - López-Sáez, J. A.; Lopez-Merino, L.; Mateo, M. A.; Serrano, O.; Perez-Diaz, S.; Serrano, L. (Palaeogeography Palaeoclimatology Palaeoecology, 2009)
A high-resolution sedimentary sequence sampled from the Portlligat Bay (NE Iberian Peninsula) has been studied in order to assess its palaeoecological potential. This sedimentary sequence is considered a very particular one, as it is a peat-like deposit derived from the accumulation of the belowground dead parts of the marine phanerogam Posidonia oceanica through the last 1600 years. This study represents the first attempt to explore the palaeoecological potential of such deposits from a palynological point of view, and has allowed the reconstruction of the vegetation dynamics and changes, human impact and the palaeoclimatic characteristics, demonstrating the value of these sedimentary records in palaeopalynological studies. (C) 2008 Elsevier B.V. All rights reserved.
402ksTimes Cited:20Cited References Count:55

Partitioning of organic matter in continental margin sediments among density fractions - Wakeham, S. G.; Canuel, E. A.; Lerberg, E. J.; Mason, P.; Sampere, T. P.; Bianchi, T. S. (Marine Chemistry, 2009)
Hydrodynamic processes sort and redistribute organic matter (OM) and minerals on continental margins. Density fractionations were conducted on sediments from diverse margins (Mexico margin, Gulf of Mexico, Mississippi River delta, Eel River margin) to investigate the nature, provenance and age of OM among density fractions. Mass. elemental (C and N), lignin, and surface area distributions, as well as stable carbon and radiocarbon isotopic compositions were measured, The lowest density fractions (2.5 g cm(-3)) were OC-poor (%OC -200 parts per thousand). Ratios of vanillic acid to vanillin (Ad/Al)v among lignin oxidation products increase with increasing particle density suggesting variable lignin sources or selective degradation of lignin among the different density fractions. (C) 2009 Elsevier B.V. All rights reserved.
id: 1844; 521ZI Times Cited:0 Cited References Count:99Y

Permanent storage of carbon dioxide in geological reservoirs by mineral carbonation - Matter, J. M.; Kelemen, P. B. (Nature Geoscience, 2009)
Anthropogenic greenhouse-gas emissions continue to increase rapidly despite efforts aimed at curbing the release of such gases. One potentially long-term solution for offsetting these emissions is the capture and storage of carbon dioxide. In principle, fluid or gaseous carbon dioxide can be injected into the Earth's crust and locked up as carbonate minerals through chemical reactions with calcium and magnesium ions supplied by silicate minerals. This process can lead to near-permanent and secure sequestration, but its feasibility depends on the ease and vigour of the reactions. Laboratory studies as well as natural analogues indicate that the rate of carbonate mineral formation is much higher in host rocks that are rich in magnesium-and calcium-bearing minerals. Such rocks include, for example, basalts and magnesium-rich mantle rocks that have been emplaced on the continents. Carbonate mineral precipitation could quickly clog up existing voids, presenting a challenge to this approach. However, field and laboratory observations suggest that the stress induced by rapid precipitation may lead to fracturing and subsequent increase in pore space. Future work should rigorously test the feasibility of this approach by addressing reaction kinetics, the evolution of permeability and field-scale injection methods.
id: 844; 525TO Times Cited:10 Cited References Count:49Y

Photochemical changes in chemical markers of sedimentary organic matter source and age - Mayer, L. M.; Schick, L. L.; Bianchi, T. S.; Wysocki, L. A. (Marine Chemistry, 2009)
Several chemical markers of organic matter source and age are shown to be susceptible to light-induced alteration. To test for the photochemical lability of markers previously employed for sediments from the Louisiana Coastal zone, we subjected sediments under resuspension conditions to Simulated Sunlight, and monitored changes in ON and Br:OC ratios, delta C-13, Delta C-14, and lignin composition. Markers of terrigenous origin (high C:N, lignin) decreased and delta C-13 became enriched in sediments containing primarily terrigencrus organic matter, while a marker of marine organic matter (Br:OC) decreased in samples containing significant contributions from this source. Preferential loss of C-14 from all sediments indicated enhanced photochemical lability of organic matter of relatively recent origin, consistent with the changes in chemical markers. Most, but not all, experimental alterations are consistent with field distributions of these markers. Relatively small experimental changes in the markers in combination with confounding processes in the environment, however. prevent these parallel trends from providing any more than a consistency test for the importance of photochemical reactions in this region. (C) 2009 Elsevier B.V. All rights reserved.
id: 793; 425QO Times Cited:0 Cited References Count:40Y

Pre-Columbian settlement of Carriacou, West Indies - Fitzpatrick, S. M.; Kappers, M.; Kaye, Q.; Giovas, C. M.; LeFebvre, M. J.; Harris, M. H.; Burnett, S.; Pavia, J. A.; Marsaglia, K.; Feathers, J. (Journal of Field Archaeology, 2009)
id: 830

Proxy Records of Paleohurricanes for the Western and Southern Caribbean - McCloskey, T. A. (Louisiana State University, 2009)

Radiocarbon Analysis of Atmospheric Formaldehyde Using Cystamine Derivatization - Shen, Haiwei; McNichol, Ann P.; Xu, Li; Gagnon, Alan; Heikes, Brian G. (ANALYTICAL CHEMISTRY, 2009)
A compound specific radiocarbon analysis method was developed to evaluate the C-14 composition of atmospheric formaldehyde. In this method, gaseous formaldehyde was collected with a high-volume air sampler using glass-fiber filters pretreated with sodium bisulfite. Collected formaldehyde was then released into water and derivatized with cysteamine to thiazolidine. The thiazolidine was extracted into dichloromethane and concentrated by evaporation. Concentrated thiazolidine was separated from other compounds using preparative capillary gas chromatography and uniquely collected as a phosphate salt with a fraction collector. The C-14 composition of the salt was analyzed by accelerator mass spectrometry after combustion to CO2 and subsequent reduction to graphite. In a pilot study, ambient formaldehyde samples collected on the roof of the CACS building at Narragansett Bay Campus, Narragansett, RI, showed a significantly larger fraction of fossil carbon than modern carbon.

Recently exposed vegetation reveals Holocene changes in the extent of the Quelccaya Ice Cap, Peru - Buffen, Aron M.; Thompson, Lonnie G.; Mosley-Thompson, Ellen; Huh, Kyung In (QUATERNARY RESEARCH, 2009)
Radiocarbon dating of well-preserved, in-place vegetation exposed by the retreating Quelccaya Ice Cap of southeastern Peru constrains the last time the ice cap's extent was smaller than at present. Seventeen plant samples from two sites along the central western margin collectively date to 4700 and 5100 cal yr BP and strongly indicate that current ice cap retreat is unprecedented over the past similar to 5 millennia. Seventeen vegetation samples interbedded in a nearby clastic sedimentary sequence suggest ice-free conditions at this site from similar to 5200 to at least similar to 7000 cal yr BP, and place minimum constraint on early- to mid-Holocene ice cap extent. (C) 2009 University of Washington. Published by Elsevier Inc. All rights reserved.
Keywords: 14C dating; Andes; Climate change; Glacier retreat; Holocene; Peru; Quelccaya Ice Cap; South America; Tropical glaciers

Using foraminifera to recognize former flood-tide deltas in the Holocene stratigraphic record: examples from the Outer Banks, North Carolina - Smith, C. G.; Culver, S. J.; Mallinson, D. J.; Riggs, S. R.; Corbett, D. R. (Stratigraphy, 2009)
id: 851

Benthic foraminiferal faunal and isotopic changes as recorded in Holocene sediments of the northwest Indian Ocean - Gupta, Anil K.; Das, Moumita; Clemens, Steven C.; Mukherjee, Baidehi (Paleoceanography, 2008)
Historically, the Holocene has been considered an interval of relatively stable climate. However, recent studies from the northern Arabian Sea (Netherlands Indian Ocean Program 905) suggested high-amplitude climate shifts in the early and middle Holocene based on faunal and benthic isotopic proxy records. We examined benthic foraminiferal faunal and stable isotopic data from Ocean Drilling Program (ODP) Site 723 and total organic carbon data from ODP Site 724, Oman Margin (808 and 593 m water depths, respectively). At Site 723 the mid-Holocene shift in delta(18)O values of infaunal benthic species Uvigerina peregrina (1.4 parts per thousand) is 3 times larger than that of epifaunal benthic species Cibicides kullenbergi recorded at Site NIOP 905 off Somalia. However, none of the five other benthic species we measured at Hole 723A exhibits such a shift in delta(18)O. We speculate that the late Holocene delta(18)O decrease in U. peregrina represents species-specific changes in ecological habitat or food preference in response to changes in surface and deep ocean circulation. While the stable isotopic data do not appear to indicate a middle Holocene climatic shift, our total organic carbon and benthic faunal assemblage data do indicate that the early Holocene deep Arabian Sea was influenced by increased ventilation perhaps by North Atlantic Deep Water and/or Circumpolar Deep Water incursions into the Indian Ocean, leading to remineralization of organic matter and a relatively weak early Holocene oxygen minimum zone in the northwest Arabian Sea in spite of strong summer monsoon circulation.
id: 1964; PT: J; UT: WOS:000256362400001

Biodiesel effects on particulate radiocarbon (C-14) emissions from a diesel engine - Bennett, Maren; Volckens, John; Stanglmaier, Rudy; McNichol, Ann P.; Ellenson, William D.; Lewis, Charles W. (JOURNAL OF AEROSOL SCIENCE, 2008)
The relative amount of C-14 in a sample of atmospheric particulate matter (PM), defined as percent modern carbon (pMC), allows the Environmental Protection Agency (EPA) to infer the fraction of PM derived from anthropogenic pollution sources. With increased use of biofuels that contain C-14, the main assumption of the two-source model, that C-14 is solely derived from biogenic emissions, may become invalid. The goal of this study was to determine the C-14 content of PM emitted from an off-highway diesel engine running on commercial grade biodiesel. Tests were conducted with an off-highway diesel engine running at 80% load fueled by various blends of soy-based biodiesel. A dilution tunnel was used to collect PM10 emissions on quartz filters that were analyzed for their C-14 content using accelerator mass spectrometry. A mobility particle sizer and 5-gas analyzer provided supporting information on the particle size distribution and gas-phase emissions. The pMC of PM10 aerosol increased linearly with the percentage of biodiesel present in the fuel. Therefore, PM emissions resulting from increased combustion of biodiesel fuels will likely affect contemporary C-14 apportionment efforts that attempt to split biogenic vs. anthropogenic emissions based on aerosol C-14 content. Increasing the biodiesel fuel content also reduced emissions of total hydrocarbons (THC), PM10 mass, and particulate elemental carbon. Biodiesel had variable results on oxides of nitrogen (NOx) emissions. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: biofuel; EC; OC; PM; source apportionment

Changes in the composition of organic matter from prodeltaic sediments after a large flood event (Po River, Italy) - Tesi, T.; Langone, L.; Goñi, M. A.; Miserocchi, S.; Bertasi, F. (Geochimica et Cosmochimica Acta, 2008)
The Po River (Italy) experienced a 100-year flood in October 2000. Surface sediments (0-1 cm) from cross-shelf transects were collected in the Po prodelta area (Adriatic Sea) in December 2000, in order to describe the distribution of organic matter (OM) along the main sediment dispersal system immediately after the flood event. Stations were subsequently reoccupied in October 2001 and April 2002. This sampling program provided a special opportunity to characterize the initial surficial flood deposit and the evolution of its associated OM over the course of 2 years. CuO oxidation, elemental, delta C-13, Delta C-14, and grain-size analyses were carried out to characterize the source, age, and spatial variability of sedimentary OM. Statistical analysis (PERMANOVA) was then applied to investigate temporal changes in different portions of the Po prodelta area. Isotopic and biomarker data suggest that the sedimentary OM in the flood deposit was initially dominated by aged (Delta C-14(Dec-00) = -298.7 +/- 56.3%,), lignin-poor OM (Lambda(Dec-00) = 1.96 +/- 0.33 mg/100 mg OC), adsorbed on the fine material (clay(Dec-00) = 72.1 +/- 4.8%) delivered by the flood. In the 2 years following the flood, post-depositional processes significantly increased the content of lignin (Lambda(Oct-01) = 2.19 +/- 0.51 mg/100 mg OC; Lambda(Apr-02) = 2.61 +/- 0.63 mg/100 mg OC); and coarse material (silt and sand), while decreasing the contributions from aged OC (Delta C-14(Oct-01) = -255.7 +/- 32.8%.; Delta C-14(Apr-02) = -213.2 +/- 30.4%.) and fine fraction (clay(Oct-01) = 54.8 +/- 9.5%; clay(Apr-02) = 44.6 +/- 13.3%). The major changes were observed in the northern and central portions of the prodelta. (c) 2008 Elsevier Ltd. All rights reserved.
id: 888; 290IO Times Cited:4 Cited References Count:66Y

Constraints on the Pleistocene chronology of sediments from the Lomonosov Ridge - O'Regan, M.; King, J.; Backman, J.; Jakobsson, M.; Palike, H.; Moran, K.; Heil, C.; Sakamoto, T.; Cronin, T. M.; Jordan, R. W. (Paleoceanography, 2008)
[1] Despite its importance in the global climate system, age-calibrated marine geologic records reflecting the evolution of glacial cycles through the Pleistocene are largely absent from the central Arctic Ocean. This is especially true for sediments older than 200 ka. Three sites cored during the Integrated Ocean Drilling Program's Expedition 302, the Arctic Coring Expedition ( ACEX), provide a 27 m continuous sedimentary section from the Lomonosov Ridge in the central Arctic Ocean. Two key biostratigraphic datums and constraints from the magnetic inclination data are used to anchor the chronology of these sediments back to the base of the Cobb Mountain subchron ( 1215 ka). Beyond 1215 ka, two best fitting geomagnetic models are used to investigate the nature of cyclostratigraphic change. Within this chronology we show that bulk and mineral magnetic properties of the sediments vary on predicted Milankovitch frequencies. These cyclic variations record "glacial'' and "interglacial'' modes of sediment deposition on the Lomonosov Ridge as evident in studies of ice-rafted debris and stable isotopic and faunal assemblages for the last two glacial cycles and were used to tune the age model. Potential errors, which largely arise from uncertainties in the nature of downhole paleomagnetic variability, and the choice of a tuning target are handled by defining an error envelope that is based on the best fitting cyclostratigraphic and geomagnetic solutions.
id: 868; 281YL Times Cited:22 Cited References Count:55; YY

Coupled North Atlantic slope water forcing on Gulf of Maine temperatures over the past millennium - Wanamaker, Alan D.; Kreutz, Karl J.; öne, Bernd R.; Pettigrew, Neal; Borns, Harold W.; Introne, Douglas S.; Belknap, Daniel; Maasch, Kirk A.; Feindel, Scott (Climate Dynamics, 2008)
To investigate ocean variability during the last millennium in the Western Gulf of Maine (GOM), we collected a 142-year-old living bivalve (Arctica islandica L.) in 2004, and three fossil A. islandica shells (calibrated 14CAMS = 1030 ± 78 ad; 1320 ± 45 ad; 1357 ± 40 ad) for stable isotope and growth increment analysis. A statistically significant relationship exists between modern GOM temperature records [shell isotope-derived (30 m) (r = −0.79; P < 0.007), Prince 5 (50 m) (r = −0.72; P < 0.019), Boothbay Harbor SST (r = −0.76; P < 0.011)], and Labrador Current (LC) transport data from the Eastern Newfoundland Slope during 1993–2003. In all cases, as LC transport increased, GOM water temperatures decreased the following year. Decadal trends in the North Atlantic Oscillation (NAO) and the Atlantic Multidecadal Oscillation (AMO) influence GOM water temperatures in the most recent period, with water temperatures decreasing during NAO and AMO negative modes most likely linked to LC transport and Gulf Stream interaction. Mean shell-derived isotopic changes (δ18Oc) during the last 1,000 years were +0.47‰ and likely reflect a 1–2°C cooling from 1000 ad to present. Based on these results, we suggest that observed cooling in the GOM during the last millennium was due to increased transport and/or cooling of the LC, and decreased Gulf Stream influence on the GOM.

Episodic reductions in bottom-water currents since the last ice age - Praetorius, S. K.; McManus, J. F.; Oppo, D. W.; Curry, W. B. (Nature Geoscience, 2008)
Past changes in the freshwater balance of the surface North Atlantic Ocean are thought to have influenced the rate of deep-water formation, and consequently climate(1,2). Although water-mass proxies are generally consistent with an impact of freshwater input on meridional overturning circulation(3), there has been little dynamic evidence to support this linkage. Here we present a 25,000 year record of variations in sediment grain size from south of Iceland, which indicates vigorous bottom-water currents during both the last glacial maximum and the Holocene period. Together with reconstructions of North Atlantic water-mass distribution, vigorous bottom currents suggest a shorter residence time of northern-source waters during the last glacial maximum, relative to the Holocene period. The most significant reductions in flow strength occur during periods that have been associated with freshening of the surface North Atlantic. The short-term deglacial oscillations in bottom current strength are closely coupled to changes in Greenland air temperature, with a minimum during the Younger Dryas cold reversal and a maximum at the time of rapid warming at the onset of the Holocene. Our results support a strong connection between ocean circulation and rapid climate change.
id: 1896; ISI Document Delivery No.: 331AG Times Cited: 9 Cited Reference Count: 34 Cited References: ALLEY RB, 1997, GEOLOGY, V25, P483 BARBER DC, 1999, NATURE, V400, P344 BARD E, 1994, EARTH PLANET SC LETT, V126, P275 BIANCHI GG, 1999, NATURE, V397, P515 BIANCHI GG, 1999, SEDIMENTOLOGY, V46, P1001 BOND G, 1992, NATURE, V360, P245 BOYLE EA, 1987, NATURE, V330, P35 BROECKER WS, 1989, GEOCHIM COSMOCHIM AC, V53, P2465 BROECKER WS, 1989, NATURE, V341, P318 CAME RE, 2007, GEOLOGY, V35, P315, DOI 10.1130/G23455A.1 CURRY WB, 2005, PALEOCEANOGRAPHY, V20, ARTN PA1017 DUPLESSY JC, 1980, NATURE, V286, P479 DUPLESSY JC, 1988, PALEOCEANOGRAPHY, V3, P343 ELLISON CRW, 2006, SCIENCE, V312, P1929, DOI 10.1126/science.1127213 FIRESTONE RB, 2007, P NATL ACAD SCI USA, V104, P16016, DOI 10.1073/pnas.0706977104 GHERARDI JM, 2005, EARTH PLANET SC LETT, V240, P710, DOI 10.1016/j.epsl.2005.09.061 GROOTES PM, 1993, NATURE, V366, P552 HALL IR, 2004, QUATERNARY SCI REV, V23, P1529, DOI 10.1016/j.quascirev.2004.04.004 KENNETT JP, 2007, EOS T AGU JOINT AS S, V88, UNSP PP41A05 KROOPNICK P, 1980, EARTH PLAN, V49, P469 LEGRAND P, 1995, PALEOCEANOGRAPHY, V10, P1011 MANABE S, 1995, NATURE, V378, P165 MCCARTNEY MS, 1996, OCEANUS, V39, P19 MCCAVE IN, 1995, NATURE, V374, P149 MCCAVE IN, 1995, PALEOCEANOGRAPHY, V10, P593 MCCAVE IN, 2006, GEOCHEM GEOPHY GEOSY, V7, P37 MCMANUS JF, 2004, NATURE, V428, P824 OPPO DW, 1993, SCIENCE, V259, P1148 ROHLING EJ, 2005, NATURE, V434, P975, DOI 10.1038/nature03421 RUDDIMAN WF, 1981, PALAEOGEOGR PALAEOCL, V35, P145 SARNTHEIN M, 1994, PALEOCEANOGRAPHY, V9, P209 TARASOV L, 2005, NATURE, V435, P662, DOI 10.1038/nature03617 WORTHINGTON LV, 1976, N ATLANTIC CIRCULATI YU EF, 1996, NATURE, V379, P689 Praetorius, Summer K. McManus, Jerry F. Oppo, Delia W. Curry, William B. Nature publishing group New york; YY

Eruptive history, geochronology, and magmatic evolution of the Puyehue-Cordon Caulle volcanic complex, Chile - Singer, B. S.; Jicha, B. R.; Harper, M. A.; Naranjo, J. A.; Lara, L. E.; Moreno-Roa, H. (Geological Society of America Bulletin, 2008)
Forty-three Ar-40/Ar-39 age determinations of lava flows, domes, ignimbrites, and dikes, plus C-14 dates from seven distal tephra layers, combined with stratigraphy, geochemistry, and Sr and Th isotope data, establish an eruptive chronology for the Puyehue-Cordon Caulle volcanic complex at 40.5 degrees S in the Andean southern volcanic zone (SVZ). The complex preserves similar to 131 km(3) of lava and tephra that erupted from numerous vents widely separated in time and space. Approximately 80% of the total volume consists of basaltic to andesitic lava that formed two broad shield volcanoes between 314 and 70 ka. The modern Puyehue stratovolcano was built on the southerly shield during the past 69 k.y. following a hiatus of 25 k.y. Puyehue has erupted similar to 15 km(3) of basaltic to rhyolitic magma that spans the entire compositional range found in the southern SVZ and evolved via at least six phases including: (1) basaltic andesitic to dacitic lavas between 69 and 32 ka, (2) a shift to bimodal magma compositions that is first expressed by a rhyodacite mingled with inclusions of MgO-rich basaltic andesite at 34 ka, (3) dacitic to rhyolitic flows and domes from 19 to 12 ka, (4) basaltic to basaltic andesitic flows between 15 and 12 ka, (5) subsequent rhyolitic dome growth in several effusive and explosive stages between 7 and 5 ka, followed by (6) a powerful series of phreatomagmatic and sub-Plinian eruptions at ca. 1.1 ka that obliterated the preceding rhyolite domes and formed the present 2.5-km-diameter, 280-m-deep summit crater. Along the Cordon Caulle fissure zone, similar to 5 km(3) of rhyodacitic to rhyolitic lavas, domes, and cones have formed during the past similar to 16.5 k.y., including explosive and effusive eruptions in 1921-1922 and 1960.Eruptive rates were nonuniform over time, with background growth at 0.04 km(3)/k.y. or less, punctuated by spurts at up to 0.90 km(3)/ k.y. The time-averaged rate, 0.42 km(3)/k.y., is nearly double that at the Tatara-San Pedro complex 500 km to the north during the past 300 k.y. These findings indicate that within a single are the magmatic and eruptive fluxes at individual frontal volcanoes can be highly variable. The last three stratocone-building events on Puyehue began during periods of deglaciation, suggesting a relationship between unloading of ice and ease of magma ascent. Puyehue basalt exhibits subtle changes in U-238-Th-230, Sr-87/Sr-86, and trace element composition over time that signal shifts in the composition and degree of melting of the mantle wedge, or the extent to which basalt was modified by assimilation of heterogeneous crustal melts. The complex has become exceptionally bimodal and more explosive over time with recent rhyolites evolving by extreme crystal fractionation of malic magma and lesser volumes of andesite and dacite created via mixing of rhyolite and basalt. Despite the high flux of basalt during the past 300 k.y., no large silicic magma reservoir formed in the upper crust. Instead, U-238-Th-230 data favor rapid ascent of several small bodies of basaltic and silicic magma from the lower crust, promoted perhaps by conduits that reflect strike-slip faulting beneath the complex.
300ujTimes Cited:61Cited References Count:55

The impact of vegetation on sedimentary organic matter composition and PAH desorption - Nichols, Elizabeth Guthrie; Gregory, Samuel T.; Musella, Jennifer S. (Environmental Pollution, 2008)
Relationships between sedimentary organic matter (SOM) composition and PAH desorption behavior were determined for vegetated and non-vegetated refinery distillate waste sediments. Sediments were fractionated into size, density, and humin fractions and analyzed for their organic matter content. Bulk sediment and humin fractions differed more in organic matter composition than size/density fractions. Vegetated humin and bulk sediments contained more polar organic carbon, black carbon, and modern (plant) carbon than non-vegetated sediment fractions. Desorption kinetics of phenanthrene, pyrene, chrysene, and C(3)-phenanthrene/anthracenes from humin and bulk sediments were investigated using Tenax (R) beads and a two-compartment, first-order kinetic model. PAH desorption from distillate waste sediments appeared to be controlled by the slow clesorbing fractions of sediment; rate constants were similar to literature values for k(slow) and k(very) (slow). After several decades of plant colonization and growth (Phragmites australis), vegetated sediment fractions more extensively desorbed PAHs and had faster desorption kinetics than non-vegetated sediment fractions. (C) 2008 Elsevier Ltd. All rights reserved.
id: 2024; PT: J; UT: WOS:000261678700045

In situ carbonation of peridotite for CO2 storage - Kelemen, P. B.; Matter, J. (Proceedings of the National Academy of Sciences of the United States of America, 2008)
The rate of natural carbonation of tectonically exposed mantle peridotite during weathering and low-temperature alteration can be enhanced to develop a significant sink for atmospheric CO2. Natural carbonation of peridotite in the Samail ophiolite, an uplifted slice of oceanic crust and upper mantle in the Sultanate of Oman, is surprisingly rapid. Carbonate veins in mantle peridotite in Oman have an average C-14 age of approximate to 26,000 years, and are not 30-95 million years old as previously believed. These data and reconnaissance mapping show that approximate to 10(4) to 10(5) tons per year of atmospheric CO2 are converted to solid carbonate minerals via peridotite weathering in Oman. Peridotite carbonation can be accelerated via drilling, hydraulic fracture, input of purified CO2 at elevated pressure, and, in particular, increased temperature at depth. After an initial heating step, CO2 pumped at 25 or 30 degrees C can be heated by exothermic carbonation reactions that sustain high temperature and rapid reaction rates at depth with little expenditure of energy. In situ carbonation of peridotite could consume > 1 billion tons of CO2 per year in Oman alone, affording a low-cost, safe, and permanent method to capture and store atmospheric CO2.
id: 779; 373OP Times Cited:12 Cited References Count:37Y

In situ carbonation of peridotite for CO2 storage - Kelemen, P. B.; Matter, J. (Proceedings of the National Academy of Sciences, 2008)
The rate of natural carbonation of tectonically exposed mantle peridotite during weathering and low-temperature alteration can be enhanced to develop a significant sink for atmospheric CO2. Natural carbonation of peridotite in the Samail ophiolite, an uplifted slice of oceanic crust and upper mantle in the Sultanate of Oman, is surprisingly rapid. Carbonate veins in mantle peridotite in Oman have an average 14C age of ≈26,000 years, and are not 30–95 million years old as previously believed. These data and reconnaissance mapping show that ≈104 to 105 tons per year of atmospheric CO2 are converted to solid carbonate minerals via peridotite weathering in Oman. Peridotite carbonation can be accelerated via drilling, hydraulic fracture, input of purified CO2 at elevated pressure, and, in particular, increased temperature at depth. After an initial heating step, CO2 pumped at 25 or 30 °C can be heated by exothermic carbonation reactions that sustain high temperature and rapid reaction rates at depth with little expenditure of energy. In situ carbonation of peridotite could consume >1 billion tons of CO2 per year in Oman alone, affording a low-cost, safe, and permanent method to capture and store atmospheric CO2.
Keywords: alteration and weathering; carbon capture; carbon sequestration; exothermic; MINERAL

The last reconnection of the Marmara Sea (Turkey) to the World Ocean: A paleoceanographic and paleoclimatic perspective - McHugh, C. M. G.; Gurung, D.; Giosan, L.; Ryan, W. B. F.; Mart, Y.; Sancar, U.; Burckle, L.; Cagatay, M. N. (Marine Geology, 2008)
During the late glacial, marine isotope Stage 2, the Marmara Sea transformed into a brackish lake as global sea-level fell below the sill in the Dardanelles Strait. A record of the basin's reconnection to the global ocean is preserved in its sediments permitting the extraction of the paleoceanographic and paleoclimatic history of the region. The goal of this study is to develop a high-resolution record of the lacustrine to marine transition of Marmara Sea in order to reconstruct regional and global climatic events at a millennia] scale. For this purpose, we mapped the paleoshorelines of Marmara Sea along the northern, eastern, and southern shelves at Cekmece. Prince Islands, and Imrali, using data from multibeam bathymetry, high-resolution subbottom profiling (chirp) and ten sediment cores. Detailed sedimentologic, biostratigraphic (foraminifers, mollusk, diatoms), X-ray fluorescence geochemical scanning, and oxygen and carbon stable isotope analyses correlated to a calibrated radiocarbon chronology provided evidence for cold and city conditions prior to 15 ka BP, warm conditions of the Bolling-Allerod from similar to 15 to 13 ka BP, a rapid marine incursion at 12 ka BP, still stand of Marmara Sea and sediment reworking of the paleoshorelines during the Younger Dryas at similar to 11.5 to 10.5 ka BP, and development of strong stratification and influx of nutrients as Black Sea waters spilled into Marmara Sea at 9.2 ka BR Stable environmental conditions developed in Marmara Sea after 6.0 ka BP as sea-level reached its present shoreline and the basin floors filled with sediments achieving their present configuration. (C) 2008 Elsevier B.V. All rights reserved.
id: 801; 370ED Times Cited:4 Cited References Count:104; YY

Late Quaternary vegetation reconstruction from the Eastern Arc Mountains, Tanzania - Mumbi, C. T.; Marchant, R.; Hooghiemstra, H.; Wooller, M. J. (Quaternary Research, 2008)
Pollen, spore, macrofossil and stable isotope (C and N) analyses from a 266-cm sediment core collected from a swamp on the Eastern Arc Mountains, Tanzania, are used to reconstruct vegetation and environmental history. An estimated time scale based on five C-14 ages records approximately 38,000 yr. This palaeorecord is the first from this biodiversity hotspot and importantly extends through the last glacial maximum (LGM). The altitudinal transition from montane to upper montane forest shifted from 1700-1800 in (38,000 C-14 yr BP) to 1800-1900 in (35,000-29,000 C-14 yr BP). From 29,000 to 10,000 C-14 yr BP, it shifted from 1850-1950 in across the LGM to 1750-1800 in (during 10,000-3500 C-14 yr BP), and to present-day elevations at 2000 in during the last 3500 C-14 yr BP. The relative ecosystem stability across the LGM may be explained by the Indian Ocean's influence in maintaining continuous moist forest cover during a period of East African regional climate aridity. During the late Holocene, presence of abundant coprophilous fungi and algal blooms demonstrates increasing human impact. Neurospora spores indicate frequent fires, coinciding with clear signals of decline in Podocarpus and Psychotria trees that possibly represent selective logging. (C) 2007 University of Washington. All rights reserved.
id: 1836; 285PB Times Cited:6 Cited References Count:105Y

Lateral organic carbon supply to the deep Canada Basin - Hwang, J.; Eglinton, T. I.; Krishfield, R. A.; Manganini, S. J.; Honjo, S. (Geophysical Research Letters, 2008)
Understanding the processes driving the carbon cycle in the Arctic Ocean is important for assessing the impacts of the predicted rapid and amplified climate change in this region. We analyzed settling particle samples intercepted by a time-series sediment trap deployed in the abyssal Canada Basin ( at 3067 m) in order to examine carbon export to the deep Arctic Ocean. Strikingly old radiocarbon ages ( apparent mean 14 C age = similar to 1900 years) of the organic carbon, abundant lithogenic material (similar to 80%), and mass flux variations temporally decoupled from the cycle of primary productivity in overlying surface waters together suggest that, unlike other ocean basins, the majority of the particulate organic carbon entering the deep Canada Basin is supplied from the surrounding margins.
id: 1830; 314KU Times Cited:7 Cited References Count:33Y

Life on the edge: early maritime cultures of the Pacific Coast of North America - Erlandson, Jon M.; Moss, Madonna L.; Des Lauriers, Matthew (Quaternary Science Reviews, 2008)
A variety of evidence suggests that the Americas may have been colonized, at least in part, by maritime peoples moving around the North Pacific Rim near the end of the Pleistocene. Understanding the geography of late glacial and early postglacial landscapes and the antiquity of human societies along the Pacific Coast continues to be a challenge, however, due to geological dynamics associated with glaciation, tectonism, submergence of coastal lowland landscapes by rising postglacial seas, and coastal erosion. Nonetheless, archaeological research has Pushed back the antiquity of human settlement along the Pacific Coast of North America to the terminal Pleistocene or early Holocene, providing important new data on the nature of the earliest coastal peoples in the Pacific Northwest, Alta California, and Baja California. In this paper, we summarize what is known about the earliest peoples of the Pacific Coast of North America and evaluate the Current viability of the coastal migration theory via a Pacific Rim route. Archaeological evidence now shows that Palaeocoastal peoples occupied each major region of the Pacific Coast by at least 13,000-11,500 calendar years ago (cal BP) (13-11.5 ka), essentially contemporaneous with Clovis and Folsom peoples of the interior. Although it is too early to conclude that the initial human colonization of the Americas took place via a migration by maritime or coastal peoples, it seems increasingly likely that such a migration played a role in the early peopling of the Americas. (c) 2008 Elsevier Ltd. All rights reserved.
id: 2062; PT: J; SI: SI; UT: WOS:000261715500012

Loess record of the Pleistocene-Holocene transition on the northern and central Great Plains, USA - Mason, Joseph A.; Miao, Xiaodong; Hanson, Paul R.; Johnson, William C.; Jacobs, Peter M.; Goble, Ronald J. (Quaternary Science Reviews, 2008)
Various lines of evidence support conflicting interpretations of the timing, abruptness. and nature of climate change in the Great Plains during the Pleistocene-Holocene transition. Loess deposits and paleosols on both the central and northern Great Plains provide a valuable record that can help address these issues. A synthesis of new and previously reported optical and radiocarbon ages indicates that the Brady Soil, which marks the boundary between late Pleistocene Peoria Loess and Holocene Bignell Loess, began forming after a reduction in the rate of Peoria Loess accumulation that most likely occurred between 13.5 and 15 cal ka. Brady Soil formation spanned all or part of the Bolling-Allerod episode (approximately 14.7-12.9 cal ka) and all of the Younger Dryas episode (12.9-11.5 cal ka) and extended at least 1000 years beyond the end of the Younger Dryas. The Brady Soil was buried by Bignell Loess sedimentation beginning around 10.5-9 cal ka, and continuing episodically through the Holocene. Evidence for a brief increase in loess influx during the Younger Dryas is noteworthy but very limited. Most late Quaternary loess accumulation in the central Great Plains was nonglacigenic and was under relatively direct climatic control. Thus, Brady Soil formation records climatic conditions that minimized eolian activity and allowed effective pedogenesis, probably through relatively high effective moisture. Optical dating of loess in North Dakota supports correlation of the Leonard Paleosol on the northern Great Plains with the Brady Soil. Thick loess in North Dakota was primarily derived from the Missouri River floodplain; thus, its stratigraphy may in part reflect glacial influence on the Missouri River. Nonetheless, the persistence of minimal loess accumulation and soil formation until 10 cal ka at our North Dakota study site is best explained by a prolonged interval of high effective moisture correlative with the conditions that favored Brady Soil formation. Burial of both the Brady Soil and the Leonard Paleosol by renewed loess influx probably represents eolian system response that occurred when gradual change toward a drier climate eventually crossed the threshold for eolian activity. Overall, the loess-paleosol sequences of the central and northern Great Plains record a broad peak of high effective moisture across the late Pleistocene to Holocene boundary, rather than well-defined climatic episodes corresponding to the Bolling-Allerod and Younger Dryas episodes in the North Atlantic region. (C) 2008 Elsevier Ltd. All rights reserved.
id: 1993; PT: J; UT: WOS:000260545800008

Matrix protected organic matter in a river dominated margin: A possible mechanism to sequester terrestrial organic matter? - Mead, R. N.; Goñi, M. A. (Geochimica Et Cosmochimica Acta, 2008)
The provenance of organic matter in surface sediments from the northern Gulf of Mexico was investigated by analyzing the compositions of lipid biomarkers (n-alkanes, fatty acids, sterols) liberated after a series of chemical treatments designed to remove different organo-mineral matrix associations (i.e. freely extractable, base-hydrolyzable, unhydrolyzable). Bulk analyses of the organic matter (carbon content, carbon:nitrogen ratios, stable and radiocarbon isotopic analyses) were also performed on the intact sediments and their non-hydrolyzable, demineralized residue. We found recognizable lipids from distinct sources, including terrestrial vascular plants, bacteria and marine algae and zooplankton, within each of the isolated fractions. Based on the lipid signatures and bulk compositions, the organic matter within the unhydrolyzable fractions appeared to be the most diagenetically altered, was the oldest in age, and had the highest abundance of terrigenous lipids. In contrast, the base-hydrolyzable fraction was the most diagentically unaltered, had the youngest ages and was most enriched in N and marine lipids. Our results indicate that fresh, autochthonous organic matter is the most important contributor to base-hydrolyzable lipids, whereas highly altered allochthonous sources appear to be predominant source of unhydrolyzable lipids in the surface sediments from the Atchafalaya River shelf. Overall, the lipid biomarker signatures of intact sediments were biased towards the autochthonous source because many of the organic compounds indicative of degraded, terrigenous sources were protected from extraction and saponification by organo-mineral matrices. It is only after these protective matrices were removed by treatment with HCl and HF that these compounds became evident. (C) 2008 Elsevier Ltd. All rights reserved.
id: 827; 309MK Times Cited:5 Cited References Count:71Y

Micropaleontologic record of late pliocene and quaternary paleoenvironments in the northern Albemarle embayment, North Carolina, USA - Culver, S. J.; Farrell, K. M.; Mallinson, D. J.; Horton, B. P.; Willard, D. A.; Thieler, E. R.; Riggs, S. R.; Snyder, S. W.; Wehmiller, J. F.; Bernhardt, C. E.; Hillier, C. (Palaeogeography Palaeoclimatology Palaeoecology, 2008)
Micropaleontological data provide a strong actualistic basis for detailed interpretations of Quaternary paleoenvironmental change. The 90 m-thick Quaternary record of the Albemarle Embayment in the mid-Atlantic coastal plain of the USA provides an excellent opportunity to use such an approach in a region where the details of Quaternary environmental change are poorly known. The foraminiferal record in nine cores from the northern Outer Banks, east of Albemarle Sound, North Carolina, indicates the deposition of subhorizontal, mostly open-marine early to late Pleistocene units unconformably upon a basement of late Pliocene reduced-oxygen, fine-grained, shelf-basin deposits. Pollen data record several warm-cool fluctuations within the early to mid-Pleistocene deposits. Diatom data indicate that some fresh and brackish-water units occur within the generally open-marine Pleistocene succession. A channel cut by the paleo-Roanoke River during the last glacial sea-level lowstand occurs in the northern part of the study area. Pollen indicates that the basal fluvial valley fill accumulated in cooler than modern climate conditions in the latest Pleistocene. Overlying silts and muds accumulated under cool climatic, estuarine conditions according to diatom and pollen data. Radiocarbon ages from the estuarine deposits indicate that the bulk of these sediments accumulated during the latest Pleistocene. The estuarine channel-fill deposits are overlain by Holocene open-marine sands deposited as the rising sea transgressed into the estuary approximately 8.5 to 9.0 kyr BR Within the barrier island drill cores of this study, fully marine sedimentation occurred throughout the Holocene. However, immediately west of the present barrier island, mid- to late Holocene estuarine deposits underlie the modern Albemarle Sound. The islands that currently form a continuous barrier across the mouth of Albemarle Sound have a complex history of Holocene construction and destruction and large portions of them may be less than 3 kyr old. The barrier island sands overlie open-marine sands of Colington Shoal in the north and to the south overlie fluvial and marine sand filling paleo-Roanoke tributary valleys. The Pleistocene sediments underlying the northern Outer Banks study area are mainly of open inner to midshelf origin. If, as is likely, sea level continues to rise, a return to such environmental conditions is likely in the near future. (c) 2008 Elsevier B.V. All rights reserved.
id: 815; 331MZ Times Cited:2 Cited References Count:79Y

Mineralization of ancient carbon i the subsurface of riparian forests - Gurwick, Noel P.; McCorkle, Daniel M.; Groffman, Peter M.; Gold, Arthur J.; Kellogg, D. Q.; Seitz-Rundlett, Peter (Journal of Geophysical Research, 2008)
id: 1193

Mutation and evolutionary rates in adelie penguins from the antarctic - Millar, C. D.; Dodd, A.; Anderson, J.; Gibb, G. C.; Ritchie, P. A.; Baroni, C.; Woodhams, M. D.; Hendy, M. D.; Lambert, D. M. (Plos Genetics, 2008)
Precise estimations of molecular rates are fundamental to our understanding of the processes of evolution. In principle, mutation and evolutionary rates for neutral regions of the same species are expected to be equal. However, a number of recent studies have shown that mutation rates estimated from pedigree material are much faster than evolutionary rates measured over longer time periods. To resolve this apparent contradiction, we have examined the hypervariable region (HVR I) of the mitochondrial genome using families of Adelie penguins (Pygoscelis adeliae) from the Antarctic. We sequenced 344 bps of the HVR I from penguins comprising 508 families with 915 chicks, together with both their parents. All of the 62 germline heteroplasmies that we detected in mothers were also detected in their offspring, consistent with maternal inheritance. These data give an estimated mutation rate (micro) of 0.55 mutations/site/Myrs (HPD 95% confidence interval of 0.29-0.88 mutations/site/Myrs) after accounting for the persistence of these heteroplasmies and the sensitivity of current detection methods. In comparison, the rate of evolution (k) of the same HVR I region, determined using DNA sequences from 162 known age sub-fossil bones spanning a 37,000-year period, was 0.86 substitutions/site/Myrs (HPD 95% confidence interval of 0.53 and 1.17). Importantly, the latter rate is not statistically different from our estimate of the mutation rate. These results are in contrast to the view that molecular rates are time dependent.
id: 1195; Millar, Craig D Dodd, Andrew Anderson, Jennifer Gibb, Gillian C Ritchie, Peter A Baroni, Carlo Woodhams, Michael D Hendy, Michael D Lambert, David M PLoS Genet. 2008 Oct 3;4(10):e1000209.2546446

Origins of archaeal tetraether lipids in sediments: Insights from radiocarbon analysis RID A-6723-2009 - Shah, Sunita R.; Mollenhauer, Gesine; Ohkouchi, Naohiko; Eglinton, Timothy I.; Pearson, Ann (Geochimica et Cosmochimica Acta, 2008)
Understanding the supply and preservation of glycerol dibiphytanyl glycerol tetraethers (GDGTs) in marine sediments helps inform their use in paleoceanography. Compound-specific radiocarbon measurements of sedimentary alkenones from multiple environments have been used to gain insight into processes that affect U-37(K') paleotemperature reconstructions. Similar analyses are warranted to investigate how analogous processes affecting GDGTs impact TEX86 paleotemperatures. Here we present radiocarbon measurements on individual GDGTs from Bermuda Rise and Santa Monica Basin sediments and discuss the results in the context of previous studies of co-depositional alkenones and foraminifera. The C-14 contents of GDGTs and planktonic foraminifera in Bermuda Rise are very similar, suggesting a local source; and TEX86-derived temperatures agree more closely with foraminiferal temperatures than do U-37(K') temperatures. In contrast, GDGTs in Santa Monica Basin are depleted in C-14 relative to both alkenones and foraminifera, and TEX86 temperatures agree poorly with known surface water values. We propose three possible factors that could explain these results: (i) GDGTs may be labile relative to alkenones during advective transport through oxic waters; (ii) archaeal production deep in the water column may contribute C-14-depleted GDGTs to sediments; and (iii) some GDGTs also may derive from sedimentary archaeal communities. Each of these three processes is likely to occur with varying relative importance depending on geographic location. The latter two may help to explain why TEX86 temperature reconstructions from Santa Monica Basin do not appear to reflect actual sea surface temperatures. Terrigenous GDGTs are unlikely to be major contributors to Bermuda Rise or Santa Monica Basin sediments, based on values of the BIT index. The results also indicate that the crenarchaeol regioisomer is governed by processes different from other GDGTs. Individual measurements of the crenarchaeol regioisomer are significantly depleted in C-14 relative to co-occurring GDGTs, indicating an alternative origin for this compound that presently remains unknown. Re-examination of the contribution of crenarchaeol regioisomer to the TEX86 index shows that it is a significant influence on the sensitivity of temperature reconstructions. (C) 2008 Elsevier Ltd. All rights reserved.
id: 2051; PT: J; UT: WOS:000259107700010

A radiocarbon-based assessment of the preservation characteristics of crenarchaeol and alkenones from continental margin sediments - Mollenhauer, G.; Eglinton, T. I.; HopmanSd, E. C.; Damste, J. S. S. (Organic Geochemistry, 2008)
Crenarchaeotal glycerol dibiphytanyl glycerol tetraether (GDGT) lipids and alkenones are two types of biomarkers, derived from planktonic marine microorganisms, which are used for reconstruction of sea surface temperature. We determined the radiocarbon contents of the archaeal GDGT crenarchaeol and of alkenones isolated from continental margin sediments. Systematic differences were found between the two biomarkers, with higher radiocarbon content in crenarchaeol than in the phytoplankton-derived alkenones. These differences can be explained by variable contributions of pre-aged, laterally-advected material to the core sites. Crenarchaeol appears to be more efficiently degraded during transport in oxygen-replete environments than alkenones. Whether this reflects the influence of chemical structure or mode of protection (e.g., particle association) is not known. (C) 2008 Elsevier Ltd. All rights reserved.
id: 883; 344AQ Times Cited:11 Cited References Count:33Y

Reconstructing relative flooding intensities responsible for hurricane-induced deposits from Laguna Playa Grande, Vieques, Puerto Rico - Woodruff, J. D.; Donnelly, J. P.; Mohrig, D.; Geyer, W. R. (Geology, 2008)
Extreme coastal flooding, primarily during hurricane strikes, has deposited sand-rich layers in Laguna Playa Grande, a back-barrier lagoon located on the island of Vieques, Puerto Rico. Silici-clastic grain-size distributions within these overwash deposits fine landward (away from the barrier and toward the mainland). A simple advective-settling model can explain this pattern of lateral sorting and is used to constrain the relative magnitude of past flooding events. A deposit associated with the A.D. 1928 San Felipe hurricane is used as a modern analogue to test the technique, which produces reasonable estimates for wave heights that exceed the barrier during the event. A 5000 yr reconstruction of local flooding intensity is developed that provides a measure of the competence for each overwash event to transport coarser-grained sediment a fixed distance into the lagoon. This reconstruction indicates that although the Laguna Playa Grande record exhibits large-scale changes in hurricane frequency on centennial to millennial time scales, the magnitude of these events has stayed relatively constant. Over the last 5000 yr, no evidence exists for an anomalously large hurricane or tsunami event with a competence for sediment transport greater than historical hurricane events.
id: 865; ISI Document Delivery No.: 300VM Times Cited: 3 Cited Reference Count: 19 Cited References: BALDOCK TE, 2005, COAST ENG, V52, P633, DOI 10.1016/j.coastaleng.2005.04.002 BOOSE ER, 2004, ECOL MONOGR, V74, P335 DONNELLY C, 2006, J COASTAL RES, V22, P965, DOI 10.2112/04-0431.1 DONNELLY JP, 2001, GEOLOGY, V29, P615 DONNELLY JP, 2007, NATURE, V447, P465, DOI 10.1038/nature05834 FERGUSON RI, 2004, J SEDIMENT RES, V74, P933 HAUG GH, 2001, SCIENCE, V293, P1304 HOLLAND TK, 2001, COASTAL SEDIMENTS 91, P489 JAFFE BE, 2007, SEDIMENT GEOL, V200, P347, DOI 10.1016/j.sedgeo.2007.01.013 LIU KB, 1993, GEOLOGY, V21, P793 MERCADO A, 1994, NAT HAZARDS, V10, P235, DOI 10.1007/BF00596144 MEYERPETER E, 1948, 2ND P C IAHR STOCKH, V2, P39 MOORE AL, 2007, SEDIMENT GEOL, V200, P336, DOI 10.1016/j.sedgeo.2007.01.012 NOTT J, 2004, ENVIRON INT, V30, P433, DOI 10.1016/j.cnvint.2003.09.010 NYBERG J, 2001, QUATERNARY RES, V56, P87, DOI 10.1006/qres.2001.2249 RUESSINK BG, 1998, J GEOPHYS RES-OCEANS, V103, P3111 SOLA EM, 1995, HISTORIA HURACANES P STOCKDON HF, 2006, COAST ENG, V53, P573, DOI 10.1016/j.coastaleng.2005.12.005 VISSER PJ, 1998, BREACH GROWTH SAND D Woodruff, Jonathan D. Donnelly, Jeffrey P. Mohrig, David Geyer, Wayne R. Geological soc amer, inc Boulder; YY

Reply to Comment on "The timing and evolution of the post-glacial transgression across the Sea of Marmara shelf south of Istanbul" by Hiscott et al., Marine Geology 248, 228-236 - Eris, K. K.; Ryan, W. B. F.; Cagatay, M. N.; Lericolais, G.; Sancar, U.; Menot, G.; Bard, E. (Marine Geology, 2008)
In their comment Hiscott and co-authors adhere rigidly to ages and sources for sedimentary units in the subsurface of the Marmara shelf that they have previously reported in their publications from 2002 through 2007. This adherence is in spite of a superior age-depth model from our 13 m-long sediment core that penetrated deeply into the deposits under consideration and in disregard to the results of subsequent more-detailed and full-coverage mapping of the region under scrutiny. The age revisions are dismissed by the authors of the comment as representing sediments severely disturbed during coring. We rebut this criticism. The Bosporus source attributed by them to the sedimentary units sampled and dated by us appears to be driven by their conception that the Black Sea had a persistent outflow prior to its two-way connection with Marmara. Irrespective of whether the outflow was persistent, our reply shows that the drawing of the isopachs of the sedimentary units by Hiscott and coauthors was accomplished in a fashion to promote the Bosporus source hypothesis regardless of the geographic limits of their survey. The ages assigned to the units are equally indeterminate because the cores used by them have missing core tops of unknown lengths that are not discussed in their publications. Furthermore, the sub-bottom reflectors at the sites where the reflectors were calibrated to their only core without a missing top are actually hidden by the finite width of the bottom reflecting wavelet. (C) 2008 Elsevier B.V. All rights reserved.
id: 784; 377ZE Times Cited:0 Cited References Count:33Y

Software development for continuous-gas-flow AMS - von Reden, K. F.; Roberts, M. L.; W. J. Jenkins; Rosenheim, B. E.; McNichol, A. P.; Schneider, R. J. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2008)
The National Ocean Sciences Accelerator Mass Spectrometry (NOSAMS) Facility at Woods Hole Oceanographic institution is presently completing installation of a novel continuous-flow AMS system. A multi-year development of an AMS microwave gas ion source in collaboration with Atomic Energy Canada Limited (AECL), Chalk River, has preceded this final step of an implementation that is expected to add a new dimension to (14)C AMS. National Instruments, NIM, and CAMAC modules have been programmed with Lab-VIEW on a Windows XP platform to form the basis for data acquisition. In this paper we discuss possible applications and include simulations of expected data acquisition scenarios like real-time AMS analysis of chromatograms. Particular attention will have to be given to issues of synchronization between rapidly changing input amplitudes and signal processing cycles in hardware and software. (C) 2008 Elsevier B.V. All rights reserved.
id: 2091; PT: J; CT: 9th European Conference on Accelerators in Applied Research and Technology; CY: SEP 03-07, 2007; CL: Florence, ITALY; SP: Univ Florence, Dept Phys, Ist Nazl Fis Nucl; UT: WOS:000257185600033

Source and composition of organic matter in the Bari canyon (Italy): Dense water cascading versus particulate export from the upper ocean - Tesi, T.; Langone, L.; Goñi, M. A.; Turchetto, M.; Miserocchi, S.; Boldrin, A. (Deep-Sea Research Part I-Oceanographic Research Papers, 2008)
Recent studies in the southern Adriatic Sea have shown that dense water cascading is an effective off-shelf transport mechanism. In order to evaluate the relative importance of different processes affecting the down-slope transfer of organic matter (OM), a multi-proxy biogeochemical study was carried out in the southern Adriatic. Three sediment traps were deployed on the southern slope in March 2004 for 1 year at 35 m above the seabed. Surficial sediments were collected on the shelf and slope along a shore-normal transect. Suspended material in the water column at different water depths was collected along nine shore-normal transects. Organic carbon (OC), total nitrogen (TN), carbon isotopic composition (delta C-13 and Delta C-14) and CuO reaction products were used to identify the OM sources and to asses the relative importance of vertical and lateral particulate fluxes. Both sinking particulates from the euphotic zone and advected material from the seafloor were collected by the moored instrumentations. During low-mass fluxes, the trapped material exhibited the highest Delta C-14 values (from -162.0 parts per thousand to +42.3 parts per thousand) and OC contents (from 1.13% to 2.17%) while the lignin displayed the lowest content (from 0.160 to 0.285 mg 100 mg(-1) OC). However, during dense water cascading events, the down-slope particulate flux showed different compositional features. In this period the trapped material displayed the most depleted Delta C-14 values (from -275.3 parts per thousand to -171.3 parts per thousand.), the lowest OC content (from 0.87% to 1.31%), and the highest lignin content (from 0.230 to 379 mg 100 mg(-1) OC). Holocene sea-level rise has drastically reduced sediment availability to the Bari canyon, and this in turn has affected the OC composition of the material funneled toward the deep Adriatic Sea. Parameters based on lignin CuO products suggest that the terrestrial material exported down the slope is very different from riverine inputs and inner shelf sediments. This indicates that neither river floods nor sediment resuspension from the inner shelf contributes directly to the down-slope flux. Rather, the material collected in the sediment traps exhibits an OM composition comparable to the surface sediments collected in the southern outer shelf. This correspondence suggests that resuspension of sediments by bottom currents in the southern outer shelf significantly contribute to down-slope OM transfer. Finally, the presence of lignin phenols in all cups indicates that lateral fluxes were constantly active on the slope throughout the deployment. (C) 2008 Elsevier Ltd. All rights reserved.
id: 828; 330FL Times Cited:4 Cited References Count:87Y

Terrigenous organic matter in sediments from the Fly River delta-clinoform system (Papua New Guinea) - Goñi, M. A.; Monacci, N.; Gisewhite, R.; Crockett, J.; Nittrouer, C.; Ogston, A.; Alin, S. R.; Aalto, R. (Journal of Geophysical Research-Earth Surface, 2008)
Although an inordinate fraction of the global sediment flux to the ocean occurs in tropical mountainous river margins, little is known regarding the sources and fate of organic matter in these systems. To address these knowledge gaps, the distribution and composition of organic matter in sediments from the Fly River delta-clinoform were examined in the context of the source-to-sink study of the Papuan Continuum. The significant contrasts in the texture of seabed sediments measured across the study area coincided with stark contrasts in concentration and composition of the sedimentary organic matter. Coarser sediments displayed significantly lower organic carbon and nitrogen contents, more enriched stable carbon and nitrogen compositions, lower lignin product yields, and distinctly different lignin and nonlignin product compositions than their fine-textured counterparts. Compositional differences were also measured between high-and low-density fractions of selected sediment samples. Subsurface sediments showed marked compositional variations that were predominantly associated with changes in the texture of the deposits. Most sediments were characterized by moderate carbon loadings (0.5-1.0 mg C m(-2)), although several samples from the outer topset region, an area of sediment bypass, were characterized by lower carbon loadings indicative of enhanced carbon losses. Overall, the organic matter in both surface and subsurface sediments appeared to have predominantly a terrigenous origin, with no evidence for dilution and/or replacement by marine carbon. The measured compositions were consistent with contributions from modern vascular plant detritus, aged soil organic matter, and very old or fossil organic matter devoid of recognizable biochemicals.
id: 826; 257VD Times Cited:8 Cited References Count:78Y

Very high-resolution seismo-acoustic imaging of seagrass meadows (Mediterranean Sea): Implications for carbon sink estimates - Lo Iacono, C.; Mateo, M. A.; Gracia, E.; Guasch, L.; Carbonell, R.; Serrano, L.; Serrano, O.; Danobeitia, J. (Geophysical Research Letters, 2008)
Posidonia oceanica is a widespread coastal Mediterranean seagrass which accumulates in its subsurface large quantities of organic material derived from its roots, rhizomes and leaf sheaths embedded in sandy sediments. These organic deposits may be up to several meters thick as they accumulate over thousands of years forming the matte, whose high content in organic carbon plays a major role in the global ocean carbon cycle. In this study, very highresolution seismo-acoustic methods were applied to image the subsurface features of a P. oceanica seagrass meadow at Portlligat (Cadaque's, Girona, Spain), in the NW-Mediterranean Sea. Our findings yield fresh insights into the settling of the P. oceanica meadow in the study area, and define with unprecedented detail the potential volume occupied by the matte. A strong reflector, located from 4.3 to 11.7 m depth, was recognized in several seismo-acoustic profiles as the substratum on which P. oceanica first settled in the study area. A 3D bathymetric model of this substratum allowed us to reconstruct the Portlligat palaeo-environment prior to the settling of P. oceanica, which corresponded to a shallow coastal setting protected from the open sea. A core drilled in the meadow at Portlligat revealed the presence of a 6 m thick dense matte composed of medium to coarse sandy sediments mixed with plant debris and bioclasts. Radiocarbon datings revealed a constant accretion rate of the matte of about 1.1 m/kyr. Gravelly bioclastic deposits observed at the base of the core correspond to the base of the matte and gave a date of 5616 +/- 46 Cal yr BP. For the first time, very high-resolution marine geophysical techniques allowed us to accurately define the volume occupied by P. oceanica matte, which in the study area reaches up to almost 220,000 +/- 17,400 m(3). This result is an important step forward in our efforts to estimate the size of the carbon sink represented by P. oceanica meadows along the Mediterranean coasts significantly contributing to the biosphere carbon cycle.
id: 896; 351AE Times Cited:1 Cited References Count:14
Keywords: cycle

A 28-ka history of sea surface temperature, primary productivity and planktonic community variability in the western Arabian Sea - Pourmand, Ali; Marcantonio, Franco; Bianchi, Thomas S.; Canuel, Elizabeth A.; Waterson, Elizabeth J. (Paleoceanography, 2007)
Uranium series radionuclides and organic biomarkers, which represent major groups of planktonic organisms, were measured in western Arabian Sea sediments that span the past 28 ka. Variability in the past strength of the southwest and northeast monsoons and its influence on primary productivity, sea surface temperature (SST), and planktonic community structure were investigated. The average alkenone-derived SST for the last glacial period was ∼3°C lower than that measured for the Holocene. Prior to the deglacial, the lowest SSTs coincide with the highest measured fluxes of organic biomarkers, which represent primarily a planktonic suite of diatoms, coccolithophorids, dinoflagellates, and zooplankton. We propose that intensification of winter northeast monsoon winds during the last glacial period resulted in deep convective mixing, cold SSTs and enhanced primary productivity. In contrast, postdeglacial (<17 ka) SSTs are warmer during times in which biomarker fluxes are high. Associated with this transition is a planktonic community structure change, in which the ratio of the average cumulative flux of diatom biomarkers to the cumulative flux of coccolithophorid biomarkers is twice as high during the deglacial and Holocene than the average ratio during the last glacial period. We suggest that this temporal transition represents a shift from a winter northeast monsoon-dominated (pre-17 ka) to a summer southwest monsoon-dominated (post-17 ka) wind system.

Aging of marine organic matter during cross-shelf lateral transport in the Benguela upwelling system revealed by compound-specific radiocarbon dating - Mollenhauer, G.; Inthorn, M.; Vogt, T.; Zabel, M.; Damste, J. S. S.; Eglinton, T. I. (Geochemistry Geophysics Geosystems, 2007)
Organic matter accumulation and burial on the Namibian shelf and upper slope are spatially heterogeneous and strongly controlled by lateral transport in subsurface nepheloid layers. Much of the material deposited in depo-centers on the slope ultimately derives from the shelf. Supply of organic matter from the shelf involves selective transport of organic matter. We studied these selective transport processes by analyzing the radiocarbon content of co-occurring sediment fractions. Here we present radiocarbon data for total organic carbon as well as three tracers of surface ocean productivity (phytoplankton-derived alkenones, membrane lipids of pelagic crenarchaeota (crenarchaeol), and calcareous microfossils of planktic foraminifera) in core-top and near-surface sediment samples. The samples were collected on the Namibian margin along a shelf-slope transect (85 to 1040 m) at 24 degrees S and from the upper slope depo-center at 25.5 degrees S. In core-top sediments, alkenone ages gradually increased from modern to 3490 radiocarbon years with distance from shore and with water depth. Crenarchaeol, while younger than alkenones, also increased in age with distance offshore. It was concluded that the observed ages were a consequence of cross-shelf transport and associated aging of organic matter. Radiocarbon ages of preserved lipid biomarkers in sediments thus at least partially depend on the relative amount of laterally supplied, pre-aged material present in a sample, highlighting the importance of nepheloid transport for the sedimentation of organic matter over the Namibian margin.
213qvTimes Cited:3 Cited References Count:60
Keywords: alkenones; atlantic-ocean; burial; carbon accumulation; coastal; compound-specific radiocarbon dating; continental-margin; ionization mass-spectrometry; membrane-lipids; namibia; sea sediments; Sediment transport

Amplitude and timing of temperature and salinity variability in the subpolar North Atlantic over the past 10 k.y. - Came, R. E.; Oppo, D. W.; McManus, J. F. (Geology, 2007)
Paired planktic foraminiferal δ18O and Mg/Ca data reveal trends of increasing temperatures (∼3 °C) and salinities in the subpolar North Atlantic over the course of the Holocene, which were punctuated by abrupt events. The trends likely reflect an insolation-forced northward retreat of the boundary between polar and North Atlantic subsurface waters. The superimposed variability does not appear to be periodic, but tends to recur within a broad millennial band. The records provide convincing evidence of open-ocean cooling (nearly 2 °C) and freshening during the 8.2 ka event, and suggest similar conditions at 9.3 ka. However, the two largest temperature oscillations in our record (∼2 °C) occurred during the past 4 k.y., suggesting a recent increase in temperature variability relative to the mid-Holocene, perhaps in response to neoglaciation, which began at about this time.
id: 983
Keywords: Björn Drift; Mg/Ca; Neogloboquadrina pachyderma dextral; Ocean Drilling Program Site 984; paleotemperature

Atlantic meridional overturning circulation during the Last Glacial Maximum - Lynch-Stieglitz, J.; Adkins, J. F.; Curry, W. B.; Dokken, T.; Hall, I. R.; Herguera, J. C.; Hirschi, J. J. M.; Ivanova, E. V.; Kissel, C.; Marchal, O.; Marchitto, T. M.; McCave, I. N.; et al. (Science, 2007)
The circulation of the deep Atlantic Ocean during the height of the last ice age appears to have been quite different from today. We review observations implying that Atlantic meridional overturning circulation during the Last Glacial Maximum was neither extremely sluggish nor an enhanced version of present-day circulation. The distribution of the decay products of uranium in sediments is consistent with a residence time for deep waters in the Atlantic only slightly greater than today. However, evidence from multiple water-mass tracers supports a different distribution of deep-water properties, including density, which is dynamically linked to circulation.
id: 1897; ISI Document Delivery No.: 153XD Times Cited: 46 Cited Reference Count: 61 Cited References: ADKINS JF, 1997, NATURE, V390, P154 ADKINS JF, 1999, RECONSTRUCTING OCEAN, P103 ADKINS JF, 2003, EARTH PLANET SC LETT, V216, P109, DOI 10.1016/S0012-821X(03)00502-8 BACON MP, 1982, J GEOPHYS RES, V87, P2045 BICKERT T, 2004, S ATLANTIC LATE QUAT, P671 BOYLE EA, 1982, SCIENCE, V218, P784 BROECKER W, 1988, RADIOCARBON, V30, P261 CHASE Z, 2002, EARTH PLANET SC LETT, V204, P215 CLARK PU, 2002, NATURE, V415, P863 CONKRIGHT ME, 2002, WORLD OCEAN ATLAS 20 CURRY WB, 1982, QUATERNARY RES, V18, P218 CURRY WB, 2005, PALEOCEANOGRAPHY, V20, ARTN PA1017 DUPIESSY JC, 1980, NATURE, V286, P479 DUPLESSY JC, 1988, PALEOCEANOGRAPHY, V3, P343 DUPLESSY JC, 1989, RADIOCARBON, V31, P493 ELDERFIELD H, 2006, EARTH PLANET SC LETT, V250, P633, DOI 10.1016/j.epsl.2006.07.041 EMILIANI C, 1955, J GEOL, V63, P538 GANACHAUD A, 2000, NATURE, V408, P453 GEBBIE G, 2006, GEOCHEM GEOPHY GEOSY, V7, ARTN Q11N07 GHERARDI JM, 2005, EARTH PLANET SC LETT, V240, P710, DOI 10.1016/j.epsl.2005.09.061 HALL IR, 2006, GEOPHYS RES LETT, V33, ARTN L16616 HALL MM, 1982, DEEP-SEA RES, V29, P339 HEWITT CD, 2003, CLIM DYNAM, V20, P203, DOI 10.1007/s00382-002-0272-6 HIRSCHI JJM, 2006, GEOCHEM GEOPHY GEOSY, V7, ARTN Q10N04 HUYBERS P, 2007, J PHYS OCEANOGR, V37, P394, DOI 10.1175/JPO3018.1 KEIGWIN LD, 2004, PALEOCEANOGRAPHY, V19, ARTN PA4012 KISSEL C, 1999, EARTH PLANET SC LETT, V171, P489 KITOH A, 2001, GEOPHYS RES LETT, V28, P2221 KUCERA M, 2005, QUATERNARY SCI REV, V24, P951, DOI 10.1016/j.quascirev.2004.07.014 KUMAR N, 1993, NATURE, V362, P45 LEGRAND P, 1995, PALEOCEANOGRAPHY, V10, P1011 LEGRANDE AN, 2006, P NATL ACAD SCI USA, V103, P837 LYNCHSTIEGLITZ J, 1999, PALEOCEANOGRAPHY, V14, P360 LYNCHSTIEGLITZ J, 2001, GEOCHEM GEOPHY GEOSY, V2, DOI 10.1029/2001GC000208 LYNCHSTIEGLITZ J, 2003, TREATISE GEOCHEMISTR, V6, P433 LYNCHSTIEGLITZ J, 2006, GEOCHEM GEOPHY GEOSY, V7, ARTN Q10N03 MANABE S, 1988, J CLIMATOL, V1, P841 MANGINI A, 1998, NATURE, V392, P347 MARCHAL O, 2000, PALEOCEANOGRAPHY, V15, P625 MARCHITTO TM, 2000, PALEOCEANOGRAPHY, V15, P299 MARCHITTO TM, 2006, GEOCHEM GEOPHY GEOSY, V7, ARTN Q12003 MAROTZKE J, 1999, J GEOPHYS RES-OCEANS, V104, P29529 MATSUMOTO K, 1999, PALEOCEANOGRAPHY, V14, P149 MCCAVE IN, 2006, GEOCHEM GEOPHY GEOSY, V7, ARTN Q10N05 MCMANUS JF, 2004, NATURE, V428, P834, DOI 10.1038/nature02494 MIX AC, 2001, QUATERNARY SCI REV, V20, P627 OTTOBLIESNER BL, 2006, J CLIMATE, V19, P2526 PAUL A, 2003, PALEOCEANOGRAPHY, V18, ARTN 1058 PIOTROWSKI AM, 2005, SCIENCE, V307, P1933, DOI 10.1126/science.1104883 ROBINSON LF, 2005, SCIENCE, V310, P1469, DOI 10.1126/science.1114832 ROEMMICH D, 1985, DEEP-SEA RES, V32, P619 SARNTHEIN M, 1994, PALEOCEANOGRAPHY, V9, P209 SCHMITTNER A, 2005, GLOBAL BIOGEOCHEM CY, V19, ARTN GB3004 SHACKLETON NJ, 1988, NATURE, V335, P708 SHIN SI, 2003, CLIM DYNAM, V20, P127, DOI 10.1007/s00382-002-0260-x STOMMEL H, 1961, TELLUS, V13, P224 STREETER SS, 1979, SCIENCE, V203, P168 VELLINGA M, 2002, CLIMATIC CHANGE, V54, P251 WUNSCH C, 2003, QUATERNARY SCI REV, V22, P371 YU EF, 1996, NATURE, V379, P689 ZHANG R, 2005, J CLIMATE, V18, P1853 Lynch-Stieglitz, Jean Adkins, Jess F. Curry, William B. Dokken, Trond Hall, Ian R. Herguera, Juan Carlos Hirschi, Joel J. -M. Ivanova, Elena V. Kissel, Catherine Marchal, Olivier Marchitto, Thomas M. McCave, I. Nicholas McManus, Jerry F. Mulitza, Stefan Ninnemann, Ulysses Peeters, Frank Yu, Ein-Fen Zahn, Rainer Amer assoc advancement science Washington; YY

Biomarker evidence for the co-occurrence of three races (A, B and L) of Botryococcus braunii in El Junco Lake, Galapagos - Zhang, Z. H.; Metzger, P.; Sachs, J. P. (Organic Geochemistry, 2007)
In spite of the fact that individual races of Botryococcus braunii are widely distributed in lakes, reports of the co-existence of different chemical races are rare. Here we report biomarker evidence for the co-occurrence of three different races of B. braunii (A, B and L) in the water column and sediments of El Junco Lake, a freshwater crater lake at 700 m elevation on San Cristobal Island, Galapagos. We also show the existence of lycopadienes and lycopatrienes in suspended particles and sediments. Biomarker indicators of the three races were: cis and trans C-25-C-31 n-alkadienes and a C-29 triene for race A, a series of C34H58 botryococcenes for race B, and a C40H78 hydrocarbon, trans, trans-lycopadiene accompanied by minor amounts of isomers for race L. Epoxides derived from n-alkadienes and trans, trans-lycopadiene, specific to races A and L respectively, were also detected. Several previously unreported lycopadienes and lycopatrienes were identified in both the water column and sediment, and are believed to represent by-products and intermediates, respectively, of trans, trans-lycopadiene synthesis. Botryococcene and lycopadiene concentrations reached 16.7 and 0.8 mg/g dry sediment in near-surface sediments, and varied over more than three orders of magnitude, while n-alkadienes were present in trace quantities. Pyrolysates from the kerogen fraction of sediment contained lycopadiene and alkadiene related lipids along with chemically resistant polymers of R braunii cell walls. Apparently n-alkadienes, botryococcenes and lycopadienes and -trienes can survive in oxic sediments for several decades, and the down core variation in these lipids likely reflects changes in lake hydrology, alternately favoring the bloom or near-extinction of R braunii race B. (C). 2007 Elsevier Ltd. All rights reserved.
id: 590; 218MC Times Cited:7 Cited References Count:72

Carbon isotope variation in modern soils of the tallgrass prairie: Analogues for the interpretation of isotopic records derived from paleosols - Johnson, W. C.; Willey, K. L.; Macpherson, G. L. (Quaternary International, 2007)
Use of stable carbon isotope data from paleosols to reconstruct past plant community structure (C-3 vs. C-4) has become commonplace. In an effort to improve our ability to make isotope-based reconstructions and to better appreciate the pitfalls, investigations were conducted on both modern soils and paleosols in the Kansas grasslands.Stable carbon isotope data were derived from soils and vegetation on the near-pristine, C-4-dominated grassland of the Konza Tallgrass Prairie Long-Term Ecological Research (LTER) site in northeastern Kansas. In order to evaluate variation of delta C-13 within the landscape, two levels of sampling were employed: 2 m-deep upland cores extracted to assess variation with depth in the soil profile, and, to assess variability across the landscape, surface samples along two transects and from within a 660 x 690 m grid. For transect and grid points, both the upper 2cm of sediment and the aboveground biomass were collected. Core samples taken at Konza reveal that soil organic carbon was depleted in C-13 within the upper 10-20cm relative to the remainder of the soil solum below, a phenomenon previously reported. In transects and the sample grid, soil organic carbon from soil surfaces was consistently more depleted in C-13 than aboveground tissue of associated vegetation samples. Slope, azimuth, and insolation were computed from field data and a highresolution DEM of the sample grid, but these variables offered no significant explanation of the spatial variability in delta C-13 data from soil organic carbon. The observation that modern landscape position has little effect on delta C-13 over short distances, at least in a C4-dominated community, lends support to the application of delta C-13 analysis to buried soils for paleoenvironmental reconstruction where paleolandscape position is often unknown.Stable carbon isotope data were derived from paleosols at from the Beisel-Steinle site located to the west of Konza in central Kansas. Three soils were examined: the interstadial paleosol within the Gilman Canyon Formation (c. 38-27k cal yr BP), the Late Pleistocene-Holocene Brady Soil, and the modern surface soil. With the exception of isotopic depletion at the top of the surface soil, all three soils exhibited similar delta C-13 values of about14 parts per thousand, the same value realized in the soil cores from Konza, suggesting close similarity among the plant communities of the interstade, the Late Pleistocene-Early Holocene transition, and pristine prairie of today.This investigation emphasizes the need for additional research into the variation in stable carbon isotope signals vertically within the profile and across the landscape. Issues include the source of the near-surface depletion zone, the relationship between isotopic values in the soil versus those of the vegetation, and variation in Soil delta 13C values delta 13C throughout the landscape. (c) 2006 Elsevier Ltd and INQUA. All rights reserved.
158nkTimes Cited:9Cited References Count:144

Carbon nanotube foils for electron stripping in tandem accelerators - von Reden, K.; Zhang, M.; Meigs, M.; Sichel, E.; Fang, S.; Baughman, R. (Nucl. Inst. & Meth. in Physics Research B., 2007)
id: 690

Chapter B--Field Trip Day 2: Quaternary Geology of Lake Alamosa and the Costilla Plain, southern Colorado - Machette, M. N.; Marchetti, D. W.; Thompson, R. A.; Kirkham, R. M. (Quaternary geology of the San Luis Basis, southern Colorado and Northern New Mexico--Rocky Mountain Section Friends of the Pleistocene Guidebook: U. S. Geological Survey Open-File Report 2007-1193, 2007)
id: 626

Chapter E--Holocene sand deposits in the San Luis Basin, east of Alamosa Colorado - Machette, M. N.; Puseman, K. (Quaternary geology of the San Luis Basis, southern Colorado and Northern New Mexico--Rocky Mountain Section Friends of the Pleistocene Guidebook: U. S. Geological Survey Open-File Report 2007-1193, 2007)
id: 627

Chapter F--Late Pleistocene to early Holocene paleoecology of the "Mr. Peat" wetland deposit, Alamosa County, Colorado - Schumann, R. R.; Machette, M. N. (Quaternary geology of the San Luis Basin, southern Colorado and Northern New Mexico--Rocky Mountain Section Friends of the Pleistocene Guidebook: U. S. Geological Survey Open-File Report 2007-1193, 2007)
id: 628

Constraining global air-sea gas exchange for CO2 with recent bomb 14C measurements - Sweeney, C.; Gloor, E.; Jacobson, A. J.; Key, R. M.; McKinley, G.; Sarmiento, J. L.; Wanninkhof, R. (Global Biogeochemical Cycles, 2007)
id: 1052

Constraints on the origin of sedimentary organic carbon in the Beaufort Sea from coupled molecular 13C and 14C measurements - Drenzek, Nicholas J.; Montluçon, Daniel B.; Yunker, Mark B.; Macdonald, Robie W.; Eglinton, Timothy I. (Marine Chemistry, 2007)
id: 1030

Diagenetic and sedimentological controls on the composition of organic matter preserved in California Borderland Basin sediments - Mollenhauer, G.; Eglinton, T. I. (Limnology and Oceanography, 2007)
Compound-specific radiocarbon (C-14) contents, stable carbon isotopes, and abundances of phytoplankton and vascular plant derived lipid biomarkers (alkenones and fatty acids) were obtained from Santa Barbara Basin and Santa Monica Basin sediments, along with radiocarbon contents of planktic foraminifera and total organic carbon. We investigated core-top and prebomb sediment intervals at sites from the flanks and depocenters of the basins deposited under contrasting bottom water oxygen concentrations. Bulk organic matter generally has the lowest radiocarbon levels of all sediment constituents measured, whereas planktic foraminifera tend to be the most radiocarbon enriched. Alkenones are systematically depleted in radiocarbon with respect to foraminifera. Short-chain (C-14, C-16, C-18) fatty acids decrease rapidly in absolute abundance and relative to longer-chain (> C-24) homologues from core-top to prebomb samples. The loss of short-chain fatty acids with depth is associated with C-13 depletion of short-chain fatty acids, indicating preferential preservation of terrestrially derived fatty acids. Short-chain fatty acids tend to be more C-14-enriched relative to alkenones in core-top sediments, whereas longer-chain homologues are generally the most radiocarbon depleted of the lipids studied here. Less refractory compounds (e.g., short-chain fatty acids) are thus enriched in radiocarbon with respect to more recalcitrant biomarkers (alkenones, long-chain fatty acids). The lower C-14 content of more refractory compounds reflects a larger proportion of laterally supplied, preaged material. Greater preservation of labile organic compounds observed at the depocenters than in flank sediments results in the presence of "younger" biomarkers, underlining the important influence of selective degradation of labile compounds on their radiocarbon ages.
149kgTimes Cited:43 Cited References Count:67
Keywords: c-14 measurements; compound-specific radiocarbon; continental-margin; fatty-acids; marine-sediments; monica basin; oxic degradation; oxygen exposure time; santa-barbara basin; surface sediments

Evaluation of gas chromatographic isotope fractionation and process contamination by carbon in compound-specific radiocarbon analysis - Zencak, Z.; Reddy, C. M.; Teuten, E. L.; Xu, L.; McNichol, A. P.; Gustafsson, O. (Analytical Chemistry, 2007)
The relevance of both modern and fossil carbon contamination as well as isotope fractionation during preparative gas chromatography for compound-specific radiocarbon analysis (CSRA) was evaluated. Two independent laboratories investigated the influence of modern carbon contamination in the sample cleanup procedure and preparative capillary gas chromatography (pcGC) of a radiocarbon-dead 3,3',4,4',5,5'-hexachlorobiphenyl (PCB 169) reference. The isolated samples were analyzed for their C-14/C-12 ratio by accelerator mass spectrometry. Sample Delta C-14 values of -996 +/- 20 and -985 +/- 20% agreed with a Delta C-14 of -995 +/- 20% for the unprocessed PCB 169, suggesting that no significant contamination by nonfossil carbon was introduced during the sample preparation process at either laboratory. A reference compound containing a modern C-14/C-12 ratio (vanillin) was employed to evaluate process contamination from fossil C. No negative bias due to fossil C was observed (sample Delta C-14 value of 165 +/- 20% agreed with Delta C-14 of 155 +/- 12% for the unprocessed vanillin). The extent of isotopic fractionation that can be induced during pcGC was evaluated by partially collecting the vanillin model compound of modern C-14/C-12 abundance. A significant change in the delta C-13 and delta C-14 values was observed when only parts of the eluting peak were collected (delta C-13 values ranged from -15.75 to -49.91% and delta C-14 values from -82.4 to +4.71%). Delta C-14 values, which are normalized to a delta C-13 of -25%, did not deviate significantly (-58.9 to -5.8%, considering the uncertainty of similar to +/- 20%). This means that normalization of radiocarbon results to a delta C-13 of -25%, normally performed to remove effects of environmental isotope fractionation on C-14-based age determinations, also cor-rects sufficiently for putative isotopic fractionation that may occur during pcGC isolation of individual compounds for CSRA.
id: 615; 140ID Times Cited:11 Cited References Count:32

Evolution and latitudinal diversity gradient: Speciation, extinction, and biogeography - Mittelbach, G. G.; Schemske, D. W.; Cornell, H. V.; Allen, A. P.; Brown, J. M.; Bush, M. B. (Ecology Letters, 2007)
id: 456

Exploring relationships between watershed properties and holocene loss-on-ignition records in high-elevation lakes, southern uinta mountains, Utah, USA - Munroe, Jeffrey S. (Arctic Antarctic and Alpine Research, 2007)
Sediment cores were retrieved from 12 lakes in the southern Uinta Mountains ranging in elevation from 2960 to 3475 m. Organic content was determined by loss-on-ignition (LOI) at 1-cm intervals (n = 2850), corresponding to 20 to similar to 100 yrs per sample. This data set was used to explore relationships between watershed variables and LOI records. Average LOI values are strongly correlated with lake elevation, elevation of the watershed, extent of late-lying snow and bare rock in the watershed, and the area of upstream lakes. Average LOI values are not significantly correlated with lake depth, or with lake or watershed area. The 12 LOI records can be visually divided into 3 groups with contrasting patterns: Steady, Trending, and Rising. Steady lakes have the lowest average LOI values, and are located in watersheds with the highest maximum elevations and the largest area of upstream lakes and late-lying snow. The most significant determinant on average LOI and LOI pattern is hydrologic through-flow as revealed by the configuration and number of inlets and outlets. The repetition of Steady, Trending, and Rising LOI patterns in different parts of the range, combined with contrasting LOI patterns in adjacent lakes, suggests that watershed characteristics strongly influence organic sedimentation.
id: 2014; PT: J; CT: Uinta Interdisciplinary Assessment Symposium (UINTAS 2006); CY: MAY , 2006; CL: Snowbird, UT; UT: WOS:000250962500006

Flux and age of dissolved organic carbon exported to the Arctic Ocean: A carbon isotopic study of the five largest arctic rivers RID C-4087-2009 RID C-5396-2008 - Raymond, Peter A.; McClelland, J. W.; Holmes, R. M.; Zhulidov, A. V.; Mull, K.; Peterson, B. J.; Striegl, R. G.; Aiken, G. R.; Gurtovaya, T. Y. (Global Biogeochemical Cycles, 2007)
The export and Delta C-14-age of dissolved organic carbon (DOC) was determined for the Yenisey, Lena, Ob', Mackenzie, and Yukon rivers for 2004 - 2005. Concentrations of DOC elevate significantly with increasing discharge in these rivers, causing approximately 60% of the annual export to occur during a 2-month period following spring ice breakup. We present a total annual flux from the five rivers of similar to 16 teragrams (Tg), and conservatively estimate that the total input of DOC to the Arctic Ocean is 25 - 36 Tg, which is similar to 5-20% greater than previous fluxes. These fluxes are also similar to 2.5 x greater than temperate rivers with similar watershed sizes and water discharge. Delta C-14-DOC shows a clear relationship with hydrology. A small pool of DOC slightly depleted in Delta C-14 is exported with base flow. The large pool exported with spring thaw is enriched in D14C with respect to current-day atmospheric Delta C-14-CO2 values. A simple model predicts that similar to 50% of DOC exported during the arctic spring thaw is 1 - 5 years old, similar to 25% is 6 - 10 years in age, and 15% is 11 - 20 years old. The dominant spring melt period, a historically undersampled period, exports a large amount of young and presumably semilabile DOC to the Arctic Ocean.
id: 2033; PT: J; UT: WOS:000250704000002

Flux and fate of Yangtze river sediment delivered to the East China Sea - Liu, J. P.; Xu, K. H.; Li, A. C.; Milliman, J. D.; Velozzi, D. M.; Xiao, S. B.; Yang, Z. S. (Geomorphology, 2007)
Numerous cores and dating show the Yangtze River has accumulated about 1.16 x 10(12) t sediment in its delta plain and proximal subaqueous delta during Holocene. High-resolution seismic profiling and coring in the southern East China Sea during 2003 and 2004 cruises has revealed an elongated (similar to 800 km) distal subaqueous mud wedge extending from the Yangtze River mouth southward off the Zhejiang and Fujian coasts into the Taiwan Strait. Overlying what appears to be a transgressive sand layer, this distal clinoform thins offshore, from similar to 40 in thickness between the 20 and 30 m water depth to < 1-2 in between 60 and 90 m water depth, corresponding to an across shelf distance of less than 100 km. Total volume of this distal mud wedge is about 4.5 x 10(11) m(3), equivalent to similar to 5.4 x 10(11) t of sediment. Most of the sediment in this mud wedge comes from the Yangtze River, with some input presumably coming from local smaller rivers. Thus, the total Yangtze-derived sediments accumulated in its deltaic system and East China Sea inner shelf have amounted to about 1.7 x 10(12) t. Preliminary analyses suggest this longshore and across-shelf transported clinoform mainly formed in the past 7000 yrs after postglacial sea level reached its mid-Holocene highstand, and after re-intensification of the Chinese longshore current system. Sedimentation accumulation apparently increased around 2000 yrs BP, reflecting the evolution of the Yangtze estuary and increased land erosion due to human activities, such as fanning and deforestation. The southward-flowing China Coastal Current, the northward-flowing Taiwan Warm Current, and the Kuroshio Current appear to have played critical roles in transporting and trapping most of Yangtze-derived materials in the inner shelf, and hence preventing the sediment escape into the deep ocean. (c) 2006 Elsevier B.V. All rights reserved.
244vyTimes Cited:286Cited References Count:84

High-resolution proxy record of Holocene climate from a loess section in Southwestern Nebraska, USA - Miao, Xiaodong; Mason, Joseph A.; Johnson, William C.; Wang, Hong (Palaeogeography Palaeoclimatology Palaeoecology, 2007)
Multi-proxy analysis was used to produce a high-resolution paleoclimatic record from an exceptionally thick section of the Holocene Bignell Loess near Wauneta, Southwestern Nebraska, in the central Great Plains. The Wauneta section has excellent age control, based on optically stimulated luminescence (OSL) and radiocarbon dating, and records multiple episodes of rapid loess deposition alternating with slower deposition and soil formation. The lowermost and uppermost OSL ages obtained from the Bignell Loess are 10,250 +/- 610 years (5.9 in depth) and 100 +/- 10 years (0.1 in depth), respectively. As a result, the Holocene has been temporally confined. Stratigraphically, the Bignell Loess overlies the Late Pleistocene Peoria Loess (deposited similar to 21-14 ka), and the two units are separated by the Brady Soil which is distinguished by its color and other pedogenic features. L*a*b* color parameters and organic carbon content of Bignell Loess are sensitive proxies to differentiate drought-induced aeolian sediment layers from the intercalated soil horizons. Soil organic carbon-derived delta(13)C data suggest that the C(3)-dominated floral environment during Peoria Loess deposition shifted dramatically to a C(4)-dominated environment during Brady Soil formation in response to a warming trend. Even greater C(4) abundance characterized the late Holocene. High-resolution delta(13)C data support the contention that C(3) vs. C(4) vegetation change in the Holocene reflects ecosystem response to frequent vegetation disturbance under and conditions. Time series analysis reveals that delta(13)C and color parameters display high frequency variation with periodicities of 103-118 years and 103 years, respectively. Similar periodicities were also reported in studies of North Dakota takes, though the physical mechanism responsible is uncertain. Comparison of Bignell Loess color and tropical Pacific sea surface temperatures (SSTs) allows evaluation of a proposed teleconnection between drought in the Great Plains and La Nina-like conditions in the tropical Pacific. The loess color index and eastern tropical Pacific SST display broad similarities through the late Pleistocene and Holocene that are consistent with this teleconnection. On the other hand, drought centered at 3800 years ago is not consistent with the teleconnection, and the end of early Holocene aridity at the Wauneta section, around 6500 years ago, is much earlier than the corresponding rise in SST and increase in El Nino frequency in the eastern tropical Pacific. (c) 2006 Elsevier B.V. All rights reserved.
id: 1994; PT: J; UT: WOS:000245026900004

Holocene sea-level oscillations and environmental changes on the Eastern Black Sea shelf - Ivanova, E. V.; Murdmaa, I. O.; Chepalyga, A. L.; Cronin, T. M.; Pasechnik, I. V.; Levchenko, O. V.; Howe, S. S.; Manushkina, A. V.; Platonova, E. A. (Palaeogeography Palaeoclimatology Palaeoecology, 2007)
A multi-proxy study of four sediment cores from the Eastern (Caucasian) Black Sea shelf revealed five transgressive-regressive cycles overprinted on the general trend of glacioeustatic sea-level rise during the last 11,000 C-14 yr. These cycles are well represented in micro-and macrofossil assemblages, sedimentation rates, and gain size variations. The oldest recovered sediments were deposited in the Neoeuxinian semi-freshwater basin (similar to 10,500-9000 C-14 yr BP) and contain a Caspian-type mollusk fauna dominated by Dreissena rostriformis. Low delta O-18 and delta C-13 values are measured on this species. The first appearance of marine mollusks and ostracodes from the Mediterranean is established in this part of the Black Sea at similar to 8200 C-14 yr BP, i.e., about 1000-2000 yr later than the appearance of marine microfossils in the deeper part of the sea. The Early Holocene (Bugazian to Vityazevian) condensed section of shell and shelly mud sediments with at least two hiatuses represent a high-energy shelf-edge facies. It contains a transitional assemblage representing a mixture of Caspian and Mediterranean fauna. This pattern suggests a dual-flow regime via the Bosphorus after 8200 C-14 yr BR Caspian species disappear and oligolialine species decrease in abundance during the Vityazevian-Prekalamitian cycle. Later, during the Middle to Late Holocene, low sea-level stands are characterized by shell layers, whereas silty mud with various mollusk and ostracode assemblages rapidly accumulated during transgressions. Restricted mud accumulation, as well as benthic faunal composition and abundance, suggest high-energy and well-ventilated bottom water during low sea-level stands. A trend of O-18 enrichment in mollusk shells points to an increase in bottom-water salinity during the Vityazevian to Kalamitian transgressions (similar to 7000 to 5700 C-14 yr BP) due to a more open connection with the Mediterranean, while a pronounced increase in polyhaline species abundance is established during the Kalamitian to Djemetean transgressions (similar to 6400 to 2700 C-14 yr BP). However, the composition of the faunal assemblage indicates that bottom-water salinity never exceeded modem values of 18-20 psu. (c) 2006 Elsevier B.V. All rights reserved.
156gzTimes Cited:22Cited References Count:51

Last millennia sedimentary record on a micro-tidal, low-accumulation prodelta (Tet NW Mediterranean) - Bourrin, F.; Monaco, A.; Aloisi, J. C.; Sanchez-Cabeza, J. A.; Lofi, J.; Heussner, S.; de Madron, X. D.; Jeanty, G.; Buscail, R.; Saragoni, G. (Marine Geology, 2007)
Statistical sequential analysis was performed on a series of sediment cores collected from the Tet prodelta in the Gulf of Lions, northwestern Mediterranean Sea, between October 2003 and October 2004. Seabed changes during that period were correlated to hydrodynamic conditions (waves and currents) and river discharge. Low sediment supply prevents full preservation of new sediment strata on this low-accumulation prodelta located on a microtidal, storm-dorninated inner shelf. Severe meteorological events caused a rapid succession of erosion and deposition phases. For example, the December 2003 flood and storm produced a flood layer deposit that persisted for 2 months with only slight transformations due to early diagenesis and/or bioturbation, until a new, storm event eroded this layer. A typical sedimentary sequence was observed for the secular deposits composed of a 10-cm-thick sandy layer overlaying siltyclayey layers. These characteristic features were used to analyse the last millennia sedimentary record of the Tet prodelta. The low preservation of freshly deposited sediments and variable sedimentation rates during the last millennia period yield a sedimentary sequence formed by the outcropping of muddy prodeltaic units intersected by heterogeneous siltysandy units similar to those formed under present day hydrodynamic conditions. No flood layer was found related to catastrophic flooding of the last century in the sedimentary record. The Little lee Age (similar to 1550-1850 AD) probably favoured the formation of a well-developed muddy prodelta in the mouth of the Tet River. Later on, the decrease of sediment supply by rivers due to climate change and/or human activities (damming, irrigation), and the increase of the number of high-energy storms reaching the coast, induced a coarsening of the top sediment layer on this prodelta. This modem change of the substrate is also observed in the composition of benthic biota found in the substrate. (c) 2007 Elsevier B.V All rights reserved.
id: 1904; 210TU Times Cited:8 Cited References Count:68Y

Late Holocene barrier island collapse; Outer Banks, North Carolina, USA - Culver, Stephen J.; Grand Pre, Candace A.; Mallinson, David J.; Riggs, Stanley R.; Corbett, D. Reide; Foley, Jennifer; Hale, Michael; Metger, Lauren; Ricardo, John; Rosenberger, Jeb; Smith, Christopher G.; Smith, Curtis W.; et al. (The Sedimentary Record, 2007)
We document here the threat of large scale destruction (collapse) of barrier islands based on the study of many cores taken along the Outer Banks and in Pamlico Sound, North Carolina.Around 1,100 cal yr BP, probably as the result of hurricane activity, portions of the southern Outer Banks must have collapsed to allow normal salinity waters to bathe southern Pamlico Sound for several hundred years. Such collapse could occur again during our current regime of global warming, rising sea level and increased tropical cyclone activity. The economic effect of barrier island break collapse on Outer Banks communities would be devastating.
id: 1887; ISSN: 1543-8740 Language: English References: 16; illus. incl. strat. col., geol. sketch map United States (USA) Latitude:N350000,N353000 Longitude:W0753000,W0760000
Keywords: 24, Quaternary geology; algae; assemblages; barrier islands; Cenozoic; changes; clastic sediments; cores; diatoms; erosion; Foraminifera; geologic hazards; Holocene; hurricanes; Invertebrata; landform evolution; lithofacies; littoral; microfossils; North Carolina; Outer Banks; Pamlico Sound; Plantae; preservation; Protista; Quaternary; salinity; sand; sea-level; sediments; United States; upper Holocene; Vibroseis

Late Holocene fine-grained sediments of the Balearic Abyssal Plain, Western Mediterranean Sea - Zuniga, D.; Garcia-Orellana, J.; Calafat, A.; Price, N. B.; Adatte, T.; Sanchez-Vidal, A.; Canals, M.; Sanchex-Cabeza, J. A.; Masque, P.; Fabres, J. (Marine Geology, 2007)
The Late Holocene fine-grained sedimentation in the deep central Balearic Abyssal Plain, Western Mediterranean Sea, has been studied after the analysis of high quality sediment cores from three multicoring stations, named A, B and C. The coring stations are 25 km apart from each other and form a triangle that is at the greatest distance from the nearest landmasses. The sediments consist of foraminifer-pteropod oozes (layers U1 and U4 from bottom to top), two pteropod oozes (U2 and U5) and a turbidite layer (U3). The same sequence has been identified in the three cores. The turbidite layer U3 that lies on top of U2 (C-14 AMS dated at 1814 cal yrs BP) ranges from 5 to I I cm thick and is clearly distinguished from the dominating hemipelagic sediments by colour variations, higher water content and the absence of planktonic foraminifer shells. Rather uniform values of organic carbon and nitrogen are also characteristic of the U3 turbidite unit, likely because of homogenisation during transport and emplacement. In addition, U3 unit shows higher contents of terrigenous elements such as K and Fe. Otherwise, the presence of zeolites in the turbidite layer supports the hypothesis of the Sardinian continental margin, where pyroclastic deposits are known, as the most likely source area for U3. Our results demonstrate the ability of turbidity currents originating on the margins surrounding the Balearic Abyssal Plain to reach the very centre of the basin during high sea level still stands as the present one. (c) 2006 Elsevier B.V. All rights reserved.
id: 624; 139VA Times Cited:6 Cited References Count:57

Late quaternary paleoseismology of the southern Steens fault zone, northern Nevada - Personius, Stephen F.; Crone, Anthony J.; Machette, Michael N.; Mahan, Shannon A.; Kyung, Jai Bok; Cisneros, Hector; Lidke, David J. (Bulletin of the Seismological Society of America, 2007)
The 192-km-long Steens fault zone is the most prominent normal fault system in the northern Basin and Range province of western North America. We use trench mapping and radiometric dating to estimate displacements and timing of the last three surface-rupturing earthquakes (E1-E3) on the southern part of the fault south of Denio, Nevada. Coseismic displacements range from 1.1 to 2.2 +/- 0.5 m, and radiometric ages indicate earthquake times of 11.5 +/- 2.0 ka (E3), 6.1 +/- 0.5 ka (E2), and 4.6 +/- 1.0 ka (E1). These data yield recurrence intervals of 5.4 +/- 2.1 k.y. between E3 and E2, 1.5 +/- 1.1 k.y. between E2 and E1, and an elapsed time of 4.6 +/- 1.0 k.y. since El. The recurrence data yield variable interval slip rates (between 0.2 +/- 0.22 and 1.5 +/- 2.3 mm/yr), but slip rates averaged over the past similar to 18 k.y. (0.24 +/- 0.06 mm/year) are similar to long-term (8.5-12.5 Ma) slip rates (0.2 +/- 0.1 mm/yr) measured a few kilometers to the north. We infer from the lack of significant topographic relief across the fault in Bog Hot Valley that the fault zone is propagating southward and may now be connected with a fault at the northwestern end of the Pine Forest Range. Displacements documented in the trench and a rupture length of 37 km indicate a history of three latest Quaternary earthquakes with magnitudes of M 6.6-7.1 on the southern part of the Steens fault zone.
id: 2022; PT: J; UT: WOS:000249930900021

Late-glacial through Holocene stratigraphy and lake-level record ofRangeley Lake, Western Maine - Metcalfe, Elisabet (University of Maine, 2007)

Long-term settlement, mobility, and landscape formation of Eastern Eurasian pastoralists from 2500 CAL B.C - Frachetti, M. D.; Mar’yashev, A. N. (Journal of Field Archaeology, 2007)
id: 1881

Marine radiocarbon evidence for the mechanism of deglacial atmospheric CO2 rise - Marchitto, T. M.; Lehman, S. J.; Ortiz, J. D.; Fluckiger, J.; van Geen, A. (Science, 2007)
We reconstructed the radiocarbon activity of intermediate waters in the eastern North Pacific over the past 38,000 years. Radiocarbon activity paralleled that of the atmosphere, except during deglaciation, when intermediate-water values fell by more than 300 per mil. Such a large decrease requires a deglacial injection of very old waters from a deep-ocean carbon reservoir that was previously well isolated from the atmosphere. The timing of intermediate-water radiocarbon depletion closely matches that of atmospheric carbon dioxide rise and effectively traces the redistribution of carbon from the deep ocean to the atmosphere during deglaciation.
Marchitto, Thomas MLehman, Scott JOrtiz, Joseph DFluckiger, Jacquelinevan Geen, AlexanderengResearch Support, U.S. Gov't, Non-P.H.S.2007/05/15 09:00Science. 2007 Jun 8;316(5830):1456-9. Epub 2007 May 10.

Mobilization pathways of organic carbon from permafrost to arctic rivers in a changing climate - Guo, L. D.; Ping, C. L.; Macdonald, R. W. (Geophysical Research Letters, 2007)
[1] Arctic warming may cause the release of vast amounts of soil organic carbon (SOC) from permafrost, which will manifest itself in the fluxes and composition of organic carbon in northern rivers and Arctic coastal regions. To elucidate the transport pathways of SOC, radiocarbon composition was measured for dissolved organic carbon (DOC), particulate organic carbon (POC), sediments and SOC from the Mackenzie, Sagavanirktok, and Yukon river basins, and soil leaching experiments were conducted. The radiocarbon ages of riverine suspended POC and sediments ranged from 4430 to similar to 7970 yr BP, while DOC was much younger (390-1440 yr BP) except samples from the Sag River. Soil leaching experiments released
id: 773; 187WS Times Cited:23 Cited References Count:29Y

A multiproxy peat record of Holocene mangrove palaeoecology from Twin Cays, Belize - Wooller, Matthew J.; Morgan, Rebecca; Fowell, Sarah; Behling, Hermann; Fogel, Marilyn (The HoloceneThe Holocene, 2007)
The extent and function of coastal mangrove ecosystems are likely to be influenced by future changes in sea level. Multiple proxies of past mangrove ecosystems preserved in a 780 cm long peat core (TCC2) taken from Twin Cays, Belize, record palaeoecological changes since ~8000 cal. yr BP. The proxies included pollen and the stable-isotope (C, N and O) compositions of mangrove leaf fragments. Rhizophora mangle (red mangrove) has been dominant at this site on Twin Cays for over ~8000 years. Variations in δ13 C and δ15N suggest past changes in stand structure between dwarf, transition and tall R. mangle through the Holocene. Marked changes in the δ18O (up to ~4?) of mangrove leaf fragments throughout TCC2 most likely record variations in the proportion of seawater versus precipitation taken up by past mangroves, reflecting the degree of inundation of the site with seawater resulting from changes in the rate of Holocene sea-level rise. Notably, a decline in peat accumulation rate at ~7200 cal. yr BP correlates with a decrease in the rate of rise in sea level. This was not accompanied by a marked change in the pollen assemblages. However, changes in assemblage composition began to occur ~6300 cal. yr BP, with an increase in Myrsine-type and Avicennia germinans (black mangrove) pollen. An increase in the δ18O between 6100 and 5300 cal. yr BP, which correlates with other records from Central America, indicates a significant increase in the rate of rise in sea level.The extent and function of coastal mangrove ecosystems are likely to be influenced by future changes in sea level. Multiple proxies of past mangrove ecosystems preserved in a 780 cm long peat core (TCC2) taken from Twin Cays, Belize, record palaeoecological changes since ~8000 cal. yr BP. The proxies included pollen and the stable-isotope (C, N and O) compositions of mangrove leaf fragments. Rhizophora mangle (red mangrove) has been dominant at this site on Twin Cays for over ~8000 years. Variations in δ13 C and δ15N suggest past changes in stand structure between dwarf, transition and tall R. mangle through the Holocene. Marked changes in the δ18O (up to ~4?) of mangrove leaf fragments throughout TCC2 most likely record variations in the proportion of seawater versus precipitation taken up by past mangroves, reflecting the degree of inundation of the site with seawater resulting from changes in the rate of Holocene sea-level rise. Notably, a decline in peat accumulation rate at ~7200 cal. yr BP correlates with a decrease in the rate of rise in sea level. This was not accompanied by a marked change in the pollen assemblages. However, changes in assemblage composition began to occur ~6300 cal. yr BP, with an increase in Myrsine-type and Avicennia germinans (black mangrove) pollen. An increase in the δ18O between 6100 and 5300 cal. yr BP, which correlates with other records from Central America, indicates a significant increase in the rate of rise in sea level.

Oceanic dispersal and accumulation of river sediment - Sommerfield, C. K.; Agston, A. S.; Mullenbach, B. L.; Drake, D. E.; Alexander, C. R.; Nittrouer, C. A.; Borgeld, J. C.; Wheatcroft, R. A.; Leithold, E. L. (Continental-Margin Sedimentation: from Sediment Transport to Sequence Stratigraphy, 2007)
id: 1119

Organic matter origin and distribution in suspended particulate materials and surficial sediments from the western Adriatic Sea (Italy) - Tesi, T.; Miserocchi, S.; Goñi, M. A.; Langone, L.; Boldrin, A.; Turchetto, M. (Estuarine Coastal and Shelf Science, 2007)
In this study, organic carbon (OC), total nitrogen (TN), stable carbon isotopic (delta C-13(OC)) and CuO reaction product compositions were used to identify the sources of organic matter (OM) and to quantify the relative importance of allochthonous and autochthonous contributions to the western Adriatic Sea, Italy. Suspended particulate material (195 samples) and surficial sediments (0- 1 cm, 70 samples) from shallow cross-shelf transects were collected in February and May 2003, respectively. Vertical water column profiles were acquired along the same transects. Data include depth, potential temperature, salinity, density and chlorophyll fluorimetry. Along the western Adriatic shelf in the near-shore region, the phytoplankton growth was influenced by dynamics of the buoyant plumes from the Po and Appennine rivers. A small amount of very fine terrigenous material remained suspended within the coastal current and was exported southward along the shelf to the slope. High variability in the bulk composition was detected in the Po prodelta surficial sediments, whereas the western Adriatic shelf, although a larger area, exhibited a narrower range of values. A significant decoupling was observed between suspended particles in the water column and surficial deposits. The organic material collected in the water column was compositionally heterogeneous, with contributions from marine phytoplankton, riverine-estuarine phytoplankton and soil-derived OM. Frequent physical reworking of surficial sediments likely leads to the efficient oxidation of marine OC, resulting in the observed accumulation and preservation of refractory soil-derived OC delivered by the Po and Appennine rivers. (c) 2007 Elsevier Ltd. All rights reserved.
id: 1869; 179HX Times Cited:12 Cited References Count:61Y

Paleoseismology of the Nephi segment of the Wasatch fault zone, Juab County, Utah--Preliminary results from two large exploratory trenches at Willow Creek - Machette, M. N.; Crone, A. J.; Personius, S. F.; Dart, R. L.; Lidke, D. J.; Mahan, S. A.; Olig, S. S. (U. S. Geological Survey, 2007)
id: 1116; Investigations Map 2966, 2 oversize plates

The power of radiocarbon in biogeochemical studies of the marine carbon cycle: insights from studies of dissolved and particulate organic carbon (DOC and POC) - McNichol, A. P.; Aluwihare, L. I. (Chem Rev, 2007)
McNichol, Ann PAluwihare, Lihini IengResearch Support, U.S. Gov't, Non-P.H.S.Review2007/02/16 09:00Chem Rev. 2007 Feb;107(2):443-66.

Preliminary geologic map of the north-central part of the Alamosa 1/2 degree x 1 degree quadrangle, Alamosa and Conejos Counties, Colorado - Machette, M. N.; Thompson, R. A. (U. S. Geological Survey Open-File Report, 2007)
id: 629; 1 sheet, 1:50,000 scale

Quantity, C-14 age and lability of desorbed soil organic carbon in fresh water and seawater - Butman, D.; Raymond, P. A.; Oh, N. H.; Mull, K. (Organic Geochemistry, 2007)
Soil organic carbon (OC) resulting from terrestrial photosynthesis is one of the largest reactive pools of sequestered atmospheric CO2. As an intermediate storage mechanism for organic material through time, the vertical distribution of carbon in a soil profile generally shows an age continuum with depth. Aged soil carbon is often the result of sorptive preservation, a physical mechanism that protects organic matter (OM) from microbial decay. Sorptive preservation is, however, a reversible process. Upon desorption, previously protected OM could be available for decomposition. Here we present simple fresh and salt water desorption experiments designed to determine the amount, 14C age and lability of “reversible” OM. Results suggest that 1.1–3.9% and 1.5–6.7% of OC, and 0.7–3% and 0.6–5% of total soil nitrogen can be desorbed using fresh and salt water, respectively. Radiocarbon data suggest this desorbed carbon is Δ14C-enriched compared to the bulk soil, with Δ14C values close to modern atmospheric Δ14CO2 at the soil surface, and aging with depth. Of this extractable aged carbon, upwards of 23–56% is labile across all treatments and with depth. Additional carbon is extracted with salt water compared to fresh water and this surplus is non-labile and younger than the labile component. Radiocarbon dating shows that the 14C age of soil carbon increases with depth and that there is a pool of Δ14C-depleted OC that is readily remineralized upon entering an aquatic/marine environment. These results indicate that eroded soil particles can release OC and organic N when entering rivers and oceans and that up to 50% of this carbon is available for aquatic metabolism.
id: 1161

Quaternary depositional patterns and sea-level fluctuations, northeastern North Carolina - Parham, P. R.; Riggs, S. R.; Culver, S. J.; Mallinson, D. J.; Wehmiller, J. F. (Quaternary Research, 2007)
A detailed record of late Quaternary sea-level oscillations is preserved within the upper 45 in of deposits along an eight kin transect across Croatan Sound, a drowned tributary of the Roanoke/Albemarle drainage system, northeastern North Carolina. Drill-hole and seismic data reveal nine relatively complete sequences filling an antecedent valley comprised of discontinuous middle and early Pleistocene deposits. On interfluves, lithologically similar marine deposits of different sequences occur stacked in vertical succession and separated by ravinement surfaces. Within the paleo-drainage, marine deposits are separated by fluvial and/or estuarine sediments deposited during periods of lowered sea level. Foraminiferal and molluscan fossil assemblages indicate that marine facies were deposited in a shallow-marine embayment with open connection to shelf waters. Each sequence modifies or truncates portions of the preceding sequence or sequences. Sequence boundaries are the product of a combination of fluvial, estuarine, and marine erosional processes. Stratigraphic and age analyses constrain the ages of sequences to late Marine Isotope Stage (MIS) 6 and younger (similar to 140 ka to present), indicating multiple sea-level oscillations during this interval. Elevations of highstand deposits associated with late MIS 5 and MIS 3 imply that sea level was either similar to present during those times, or that the region may have been influenced by glacio-isostatic uplift and Subsidence. (c) 2006 University of Washington. All rights reserved.
131tvTimes Cited:18Cited References Count:56

Quaternary geology of the San Luis Basin, southern Colorado and Northern New Mexico--Rocky Mountain Section Friends of the Pleistocene Guidebook - Machette, M. N.; Coates, M. M.; Johnson, M. J. (U. S. Geological Survey Open-File Report 2007-1193, 2007)
id: 625

Radiocarbon age of late glacial deep water from the equatorial Pacific - Broecker, W.; Clark, E.; Barker, S.; Hajdas, I.; Bonani, G.; Moreno, E. (Paleoceanography, 2007)
Radiocarbon age differences for pairs of coexisting late glacial age benthic and planktic foraminifera shells handpicked from 10 sediment samples from a core from a depth of 2.8 km in the western equatorial Pacific are not significantly different from that of 1600 years calculated from measurements on prenuclear seawater. This places a lower limit on the depth of the interface for the hypothetical radiocarbon-depleted glacial age seawater reservoir required to explain the 190% drop in the (14)C/C for atmospheric CO(2), which occurred during the mystery interval (17.5 to 14.5 calendar years ago). These measurements restrict the volume of this reservoir to be no more than 35% that of the ocean. Further, (14)C measurements on a single Last Glacial Maximum age sample from a central equatorial Pacific core from a depth of 4.4 km water fail to reveal evidence for the required 5- to 7-kyr age difference between benthic and planktic foraminifera shells if the isolated reservoir occupied only one third of the ocean. Nor does the (13)C record for benthic forams from this abyssal core yield any evidence for the excess respiration CO(2) expected to be produced during thousands of years of isolation. Nor, as indicated by the presence of benthic foraminifera, was the dissolved oxygen used up in this abyssal water.
id: 413; 165MC Times Cited:10 Cited References Count:18

Radiocarbon analysis confirms the annual nature of sagebrush growth rings - Biondi, F.; Strachan, S. D. J.; Mensing, S.; Piovesan, G. (Radiocarbon, 2007)
In the Great Basin of North America, big sagebrush (Artemisia tridentata Nutt.) growth rings can be used to reconstruct environmental changes with annual resolution in areas where there is otherwise little such information available. We tested the annual nature of big sagebrush wood layers using accelerator mass spectrometry (AMS) radiocarbon dating. Four cross-sections from 3 sagebrush plants were collected near Ely, Nevada, USA, and analyzed using dendrochronological methods. Ten C-14 measurements were then used to trace the location of the 1963-64 "bomb spike." Although the number of rings on each section did not exceed 60, crossdating was possible within a section and between sections. Years assigned to individual wood layers by means of crossdating aligned with their expected C-14 values, matching the location of the C-14 peak. This result confirmed the annual nature of growth rings formed by big sagebrush, and will facilitate the development of spatially explicit, well-replicated proxy records of environmental change, such as wildfire regimes, in Great Basin valleys.
258usTimes Cited:9Cited References Count:48

Radiocarbon and stable isotope geochemistry of organic matter in the Amazon headwaters, Peruvian Andes - Townsend-Small, A.; Noguera, J. L.; McClain, M. E.; Brandes, J. A. (Global Biogeochemical Cycles, 2007)
[1] We used delta C-13, delta N-15, and Delta C-14 to determine the sources of riverine organic matter in the Pozuzo River, a tributary of the Pachitea River located in the mountainous headwaters of the Amazon. Particulate organic matter (POM) Delta C-14 decreased downstream, suggesting that young organic matter (OM) introduced in small headwaters is respired preferentially in rivers or is diluted downstream with older material. The delta C-13 and delta N-15 of POM in headwater rivers were heterogeneous and also isotopically distinct from the main stem, suggesting that differences in landscape processes in small catchments impact the concentration and composition of POM in streams. The delta C-13 of dissolved organic matter (DOM) closely mirrored that of POM in the headwaters, with an apparent decoupling of dissolved and particulate OM in the river main stem. The delta C-13 of POM sampled in 2004 had a much different relationship with altitude than observed during previous years: In 2004, a very dry year, we observed enrichment from the headwaters to the main stem, and the opposite pattern in 2002, when rain fell heavily throughout the sampling campaign. This suggests that during dry conditions, in-stream processes ( such as resuspension or photosynthesis) may control riverine POM composition as opposed to terrestrial processes, which dominate during high runoff. Thus a decrease in runoff in Andean headwaters could result in less terrestrial POM transfer to rivers in the Andes foothills and lowland Amazon with a corresponding decrease in aquatic CO2 evasion.
185aaTimes Cited:12 Cited References Count:37
Keywords: amino-acids; atlantic-ocean; carbon; drainage-basin; land-use; nitrogen; particulate; river system; sediments; streams

Radiocarbon and Th-230 data reveal temperal changes in sediment focusing at ODP site 984, Poster - Mollenhauer, Gesine; McManus, J. F.; Wagner, T.; McCave, I. N.; Eglinton, T. I. (EGU General Assembly, 2007)
id: 547

Radiocarbon dating of a very large African baobab - Patrut, A.; von Reden, K. F.; Pohlman, J. W.; Wittmann, R.; Mitchell, C. S.; Lowy, D. A.; Alberts, A. H.; Gerlach, D.; Xu, L. (Tree Physiology, 2007)
In late 2004, Grootboom, probably the largest known African baobab (Adansonia digitata L.), collapsed unexpectedly in northeastern Namibia. Ten wood samples collected from different areas of the trunk were processed and investigated by accelerator mass spectrometry radiocarbon dating. The radiocarbon dates of three samples were greater than 1000 years BP (radiocarbon years before present, i.e., before AD 1950). The corresponding calibrated calendar age of the oldest sample was 1275 +/- 50 years, making Grootboom the oldest known angiosperm tree with reliable dating results. Variations in radiocarbon dates among the wood samples indicated that, morphologically, Grootboom was a quintuple tree, whereas genetically, it was a single individual. Ages of extreme lateral samples revealed that, over the past 500-600 years, Grootbooom had almost ceased growing, providing information about climate changes in central southern Africa. The sudden demise of Grootboom coincided with the spread of the poorly studied baobab disease, which has become epidemic in Namibia.
230afTimes Cited:35 Cited References Count:43
Keywords: Adansonia digitata; Age; Age determination; amazonia; c-14 content; cal kyr bp; Calibration; dendrochronology; dendroclimatology; holocene logs; location-dependent differences; southern-hemisphere; tasmanian conifers; Trees; tropical trees

Report of archaeological field research in 2006, including geological descriptions of archaeological locales - Fitzhugh, B.; Etnier, M.; MacInnes, B.; Phillips, S. C.; Taylor, J. W. (Kuril Biocomplexity Project (NSF 0508109, PI: Fitzhugh), 2007)
id: 833Unpublished project report

Sedimentary iron cycling and the origin and preservation of magnetization in platform carbonate muds, Andros Island, Bahamas - Maloof, A. C.; Kopp, R. E.; Grotzinger, J. P.; Fike, D. A.; Bosak, T.; Vali, H.; Poussart, P. M.; Weiss, B. P.; Kirschvink, J. L. (Earth and Planetary Science Letters, 2007)
Carbonate muds deposited on continental shelves are abundant and well-preserved throughout the geologic record because shelf strata are difficult to subduct and peritidal carbonate units often form thick, theologically strong units that resist penetrative deformation. Much of what we know about pre-Mesozoic ocean chemistry, carbon cycling, and global change is derived from isotope and trace element geochemistry of platform carbonates. Paleomagnetic data from the same sediments would be invaluable, placing records of paleolatitude, paleogeography, and perturbations to the geomagnetic field in the context and relative chronology of chemostratigraphy. To investigate the depositional and early diagenetic processes that contribute to magneitzation in carbonates, we surveyed over 500 core and surface samples of peritidal, often microbially bound carbonate muds spanning the last similar to 1000 yr and deposited on top of Pleistocene aeolianites in the Triple Goose Creek region of northwest Andros Island, Bahamas. Sedimentological, geochemical, magnetic and ferromagnetic resonance properties divide the sediment columns into three biogeochemical zones. In the upper sediments, the dominant magnetic mineral is magnetite, produced by magnetotactic bacteria and dissimiliatory microbial iron metabolism. At lower depths, above or near mean tide level, microbial iron reduction dissolves most of the magnetic particles in the sediment. In some cores, magnetic iron sulfides precipitate in a bottom zone of sulfate reduction, likely coupled to the oxidation of decaying mangrove roots. The remanent magnetization preserved in all oriented samples appears indistinguishable from the modem local geomagnetic field, which reflects the post-depositional origin of magnetic particles in the lower zone of the parasequence. While we cannot comment on the effects of late-stage diagenesis or metamorphism on remanence in carbonates, we postulate that early-cemented, thin-laminated parasequence tops in ancient peritidal carbonates are mostly likely to preserve syn-depositional paleomagnetic directions and magnetofossil stratigraphies. (c) 2007 Published by Elsevier B.V.
id: 787; 197DX Times Cited:9 Cited References Count:47Y

Selective degradation of organic compounds in sediments from the California Borderland Basins: evidence from compound specific Delta 14C and delta 13C analyses - Mollenhauer, Gesine; Eglinton, Timothy I. (Limnology and Oceanography, 2007)
id: 544

Source, transport and fate of terrestrial organic carbon on the western Mediterranean Sea, Gulf of Lions, France - Tesi, T.; Miserocchi, S.; Goñi, M. A.; Langone, L. (Marine Chemistry, 2007)
As part of the EuroSTRATAFORM project, a multi-proxy study was conducted in order to investigate origin, transport and deposition of riverine organic matter in the Gulf of Lions. Surface sediments (0-1 cm) from the Rhone prodelta area and along the sediment dispersal system were collected in September 2004 and in April 2005. Lignin, elemental and stable carbon isotopic analyses were carried out to characterize the source of sedimentary organic material and to facilitate evaluation of temporal and spatial variability. Large contrasts in the organic matter composition of prodelta sediments were observed as a result of the preferential transport of the finest material. In our hypothesis, woody debris, rich in organic matter, hydraulically behaves like very fine sand and is retained within the prodelta area. In contrast, the organic matter adsorbed onto finer particles is selectively transported away from the prodelta along the sediment dispersal system, explaining the distinct organic matter composition observed in the offshore regions. (c) 2007 Elsevier B.V. All rights reserved.
id: 825; 176SJ Times Cited:15 Cited References Count:70Y

Stable-and radiocarbon isotopes in corals and adjacent natural waters: reconstructing land-use change and the land-ocean carbon cycle - Moyer, R. P.; Grottoli, A. G. (ASLO, 2007)
id: 654

Stratigraphy and environmental reconstruction at the middle Wisconsinan Gilman Canyon Formation type locality, Buzzard's Roost, southwestern Nebraska, USA - Johnson, W. C.; Willey, K. L.; Mason, J. A.; May, D. W. (Quaternary Research, 2007)
The middle Wisconsinan Gilman Canyon Formation at the Buzzard's Roost type locality in southwestern Nebraska was investigated to document the stratigraphy and to reconstruct the environmental and climate record. The Gilman Canyon Formation was subdivided into three loess units and three soils, with radiocarbon ages constraining it between about 40 ka and 25 ka. Stable carbon isotope ratios, magnetic susceptibility, and carbon content were used to define and characterize soils within both the Gilman Canyon Formation and underlying Illinoian Loveland Loess. At the height of soil development within the Gilman Canyon Formation, climate was supporting C-4-dominated grassland, with July temperatures equal to or exceeding those of today. Soil-forming intervals within the Loveland Loess, including the Sangamon Soil, also exhibited relative increases in C-4 biomass. Climate, as recorded in the Gilman Canyon Formation, is corroborated by regional proxy data. The formation accumulated during MIS 3, and concurrent soil formation coincided with a summer insolation maximum. (c) 2007 University of Washington. All rights reserved.
160ruTimes Cited:17Cited References Count:115

Is there a thorium-230 deficit in Arctic sediments? - Hoffmann, S. S.; McManus, J. F. (Earth and Planetary Science Letters, 2007)
id: 711

The timing and evolution of the post-glacial transgression across the Sea of Marmara shelf south of Istanbul - Eris, K. K.; Ryan, W. B. F.; Cagatay, M. N.; Sancar, U.; Lericolais, G.; Menot, G.; Bard, E. (Marine Geology, 2007)
High-resolution seismic reflection profiles and analyses of the sedimentary substrate at the Sea of Marmara (SoM) entrance to the Strait of Istanbul (Sol, Bosphorus) provide a detailed record of the transgression that took place after the SoM reconnected with the Mediterranean. The sediments progressively fill a paleo shelf valley that incised the margin from the Sol to the shelf break at the time of the pre-Holocene lowstand. We map seven seismic reflection units that can be confidently correlated to sediment cores by lithology and physical properties. Sediments in the cores are dated by radiocarbon methods. Early channel and levee deposits within the paleo valley belong to the Younger Dryas cold stage and record outflow from the Black Sea via the Sol. Small clinoform packages on the valley margin formed in proximity to climbing paleo shorelines. The elevations of these deposits conform to the sealevel history recorded in Barbados corals. The younger part of the succession includes a subaqueous prodelta sourced from the Kurbagalidere River. Its relatively young age when the Holocene sea had almost reached its modem level suggests that the thick progradational and aggradational clinoform development was primarily a response to sediment supply rather than the filling of expanding accommodation space. Our findings refute the hypothesis of Aksu et al. (Aksu, A.E., Hiscott, R.N., Mudie., P.J., Rochon, A., Kaminski, M.A., Abrojano, T., Yasar, D., 2002a. Persistent Holocene outflow fromn the Black Sea to the Eastern Mediterranean contradicts Noah's Flood hypothesis, GSA Today 10,(6), 3-7., Aksu, A.E., Hiscott, R.N., Kaminski, M.A., Mudie, P.J., Gillespie, H., Abrojano, T., Yasar, D., 2002b. Last glacial-Holocene paleoceanography of the Black Sea and Marmara Sea: stable isotopic, foraminiferal and coccolith evidence. Mar. Geol., 190, 119-149.) and Hiscott et al. (Hiscott, R.N., Aksu, A.E., Yasar, D., Kaminski, M.A., Mudie, P.J., Kostylev, V.E., MacDonald, J.C. Isler, F.I., Lord, A.R., 2002. Deltas south of the Bosphorus Strait record persistent Black Sea outflow to the Marmara Sea since similar to 10 ka, Mar. Geol., 190,95-118., Hiscott, R.N., Aksu, A.E., Mudie., P.J., Kaminski, M.A., Abrajano, T, Yasar, D., Rochon, A., 2007. The Marmara Sea gateway since similar to 16 ky BP: non-catastrophic causes of paleoceanographic events in the Black Sea at 8.4 and 7.15 ky BR In Yanko-Hombach,V, Gilbert, A.S., Dolukhanov, P.M. (Eds.), The Black Sea Flood Question, Springer, The Netherlands, 89-117.) that this deposit was supplied from the Sol and that its presence requires a persistent Black Sea outflow since 10 C-14 ka bp (not corrected from the reservoir age or calibrated). (c) 2007 Elsevier B.V All rights reserved.
210tuTimes Cited:36Cited References Count:52

14C methane and DIC in the deep terrestrial subsurface: implications for microbial methanogenesis - Slater, Greg F.; Lippmann-Pipke, Johanna; Moser, Duane P.; Reddy, Christopher M.; Onstott, T. C.; Lacrampe-Couloume, Georges; Lollar, Barbara Sherwood (Geomicrobiology Journal, 2006)
id: 1100

Abrupt tropical climate change: past and present - Thompson, L. G.; Mosley-Thompson, E.; Brecher, H.; Davis, M.; Leon, B.; Les, D.; Lin, P. N.; Mashiotta, T.; Mountain, K. (Proc Natl Acad Sci U S A, 2006)
Three lines of evidence for abrupt tropical climate change, both past and present, are presented. First, annually and decadally averaged delta(18)O and net mass-balance histories for the last 400 and 2,000 yr, respectively, demonstrate that the current warming at high elevations in the mid- to low latitudes is unprecedented for at least the last 2 millennia. Second, the continuing retreat of most mid- to low-latitude glaciers, many having persisted for thousands of years, signals a recent and abrupt change in the Earth's climate system. Finally, rooted, soft-bodied wetland plants, now exposed along the margins as the Quelccaya ice cap (Peru) retreats, have been radiocarbon dated and, when coupled with other widespread proxy evidence, provide strong evidence for an abrupt mid-Holocene climate event that marked the transition from early Holocene (pre-5,000-yr-B.P.) conditions to cooler, late Holocene (post-5,000-yr-B.P.) conditions. This abrupt event, approximately 5,200 yr ago, was widespread and spatially coherent through much of the tropics and was coincident with structural changes in several civilizations. These three lines of evidence argue that the present warming and associated glacier retreat are unprecedented in some areas for at least 5,200 yr. The ongoing global-scale, rapid retreat of mountain glaciers is not only contributing to global sea-level rise but also threatening freshwater supplies in many of the world's most populous regions.
Thompson, Lonnie GMosley-Thompson, EllenBrecher, HenryDavis, MaryLeon, BlancaLes, DonLin, Ping-NanMashiotta, TracyMountain, KeithengResearch Support, Non-U.S. Gov'tResearch Support, U.S. Gov't, Non-P.H.S.2006/07/04 09:00Proc Natl Acad Sci U S A. 2006 Jul 11;103(28):10536-43. Epub 2006 Jun 30.

Absence of 14C in PM2.5 Emissions from Gasohol Combustion in Small Engines - Lewis, C. W.; Volkens, J.; Braddock, J. N.; Crews, W. S.; Lonneman, W. A.; McNichol, A. P. (Aerosol Science and Technology, 2006)
id: 1699

Bioreactivity of estuarine dissolved organic matter: A combined geochemical and microbiological approach - McCallister, S. L.; Bauer, J. E.; Canuel, E. A. (Limnology and Oceanography, 2006)
An integrated multidisciplinary study utilizing geochemical and microbial ecological approaches was conducted to characterize the origins, chemical nature, and quantities of dissolved and particulate organic matter (OM) utilized by heterotrophic bacteria in a temperate estuary. C: N, stable isotope (delta C-13), and lipid biomarker analyses revealed differences in the inferred reactivity of autochthonous versus allochthonous OM sources. Isotopic comparison of OM size fractions and bacterial nucleic acids suggests that high-molecular-weight dissolved OM (DOM) is consistently linked to bacterial biomass synthesis along the estuarine salinity gradient. Polyunsaturated fatty acids (as percent of total fatty acids, FA) were a reliable predictor of DOM decomposition in bioassays, thus providing an indicator directly linking DOM reactivity to its composition. Significant positive correlations between FA diagnostic of bacterial sources and lipid biomarker compounds diagnostic of planktonic origin indicate a systematic bacterial response to autochthonous DOM sources along the estuarine continuum. These findings further suggest that, although the geochemical signature of algal-derived OM in the dissolved phase may appear quantitatively insignificant, this fraction may nevertheless represent a principal source of bioreactive OM to heterotrophic bacteria in estuarine waters.
040scTimes Cited:39 Cited References Count:32
Keywords: acids; bacteria; bay; bioavailability; carbon-isotope analysis; extraction; food webs; sediments

Bomb dating and age validation using the spines of spiny dogfish (Squalus acanthias) - Campana, S. E.; Jones, C.; McFarlane, G. A.; Myklevoll, S. (Environmental Biology of Fishes, 2006)
Bomb radiocarbon has previously been used to validate the age of large pelagic sharks based on incorporation into vertebrae. However, not all sharks produce interpretable vertebral growth bands. Here we report the first application of bomb radiocarbon as an age validation method based on date-specific incorporation into spine enamel. Our results indicate that the dorsal spines of spiny dogfish, Squalus acanthias, recorded and preserved a bomb radiocarbon pulse in growth bands formed during the 1960s with a timing which was very similar to that of marine carbonates. Using radiocarbon assays of spine growth bands known to have formed in the 1960s and 1970s as a dated marker, we confirm the validity of spine enamel growth band counts as accurate annual age indicators to an age of at least 45 year. Radiocarbon incorporation into northeast Atlantic dogfish spines occurred in similar years as those in the northwest Atlantic and northeast Pacific, although the amount of radiocarbon differed in keeping with the radiocarbon content of the different water masses. Published reports suggesting that Pacific dogfish are longer lived and slower growing than their Atlantic counterparts appear to be correct, and are not due to errors in interpreting the spine growth bands. Radiocarbon assays of fin spine enamel appears to be well suited to the age validation of sharks with fin spines which inhabit the upper 200 m of the ocean.
107bsTimes Cited:38Cited References Count:25

Carbon flow in salt marsh sediments: Natural-level radiocarbon as a tracer for incorporation of petroleum-derived carbon into bacteria - Wakeham, S. G.; McNichol, A. P.; Kostka, J.; Pease, T. K. (Geochim. Cosmochim. Acta, 2006)
id: 762

Carbon flux in seagrass ecosystems - Mateo, M. A.; Cebrián, J.; Dunton, K.; Mutchler, T. (Seagrasses: Biology, Ecology and Conservation., 2006)
id: 2006

Cross-shelf lateral transport in the Benguela Upwelling System: Aging of marine organic matter in the benthic boundary layer - Mollenhauer, Gesine; Inthorn, Maik; Zabel, Matthias; Damste, Jaap Sinninghe; Eglinton, Timothy I. (Ocean Sciences Meeting, 2006)
id: 545

Determination of carbon dioxide, hydrographic and chemical parameters during the R/V Nathaniel B. Palmer cruise in the southern Indian Ocean (WOCE section S041) - Takahashi, R.; Millero, F. J.; Key, R. M.; Chipman, D.; Peltola, E.; Rubin, S.; Sweeney, C.; Sutherland, S. (2006)
id: 1053

Diageneitc and sedimentological controls on the composition of organic matter preserved in California Borderland Basin sediments - Mollenhauer, Gesine; Eglinton, Timothy I. (Limnology & Oceanography Paleoceanography, submitted, 2006)
id: 1705

Effects of differential degradation of marine organic compounds on preserved radiocarbon ages and biomarker-based SST reconstructions, Poster - Mollenhauer, Gesine; Sinninghe, Jaap S.; Eglinton, Timothy I. (EGU General Assembly, 2006)
id: 1072

Evaluation of ageing accuracy of bocaccio (Sebastes paucispinis) rockfish using bomb radiocarbon - Piner, K. R.; Wallace, J. R.; Hamel, O. S.; Mikus, R. (Fisheries Research, 2006)
The accuracy of bocaccio rockfish age assignments was evaluated using radiocarbon levels measured in otoliths collected from fish taken off the coast of Washington state (USA). Otoliths from 24 randomly selected fish with estimated birth years from 1950 to 1977, based on paired otolith age estimates, were used in this study. The level of radiocarbon measured in the core of each otolith was compared to a reference radiocarbon chronology based on radiocarbon levels in otoliths from known-age Pacific halibut. The degree of graphical phase correspondence between the two series was sufficient to support the hypothesis that the annuli were formed yearly in bocaccio otoliths but were somewhat difficult to identify. Statistical analysis of the ageing errors could not document a bias in production ageing of bocaccio. Pre-bomb radiocarbon levels measured in otolith cores confirm that bocaccio can live at least 37 years. Published by Elsevier B.V.
011qtTimes Cited:10Cited References Count:40

An evolutionary model for the origins of agriculture on the Pacific coast of southern Mexico - Kennett, D. J.; Voorhies, B.; Martorana, D. (Behavioral Ecology and the Transition to Agriculture, 2006)
id: 465

Foraminiferal and sedimentary record of Late Holocene barrier island evolution, Pea Island, North Carolina: The role of storm overwash, inlet processes, and anthropogenic modification - Culver, S. J.; Ames, D. V.; Corbett, D. R.; Mallinson, D. J.; Riggs, S. R.; Smith, C. G.; Vance, D. J. (Journal of Coastal Research, 2006)
Foraminiferal and sedimentary data, supplemented with geochemical dating and ground-penetrating radar transects, show that the barrier island at Pea Island National Wildlife Refuge just north of Rodanthe, North Carolina, has been dominated by a combination of inlet and overwash processes for at least 1000 years. The stratigraphic record of several vibracores does not preserve every, or even many, overwash events but, instead, is characterized by three to four fining-upward sequences. The last three commence with overwash sand or gravel that is overlain by a variety of finer-grained estuarine, inlet, and marsh deposits. The dynamic nature of this segment of the Outer Banks was muted in the late 1930s by construction of artificial barrier dune ridges, extensive planting of grass and shrubs, and construction of Highway 12 in 1953. Subsequently, the road and barrier dune ridge were rebuilt and relocated several times following storm events.
070tkTimes Cited:19Cited References Count:33

MAGic: A Phanerozoic model for the geochemical cycling of major rock-forming components - Arvidson, R. S.; Mackenzie, F. T.; Guidry, M. (American Journal of Science, 2006)
A dynamical model (MAGic) is presented that describes the elemental cycling of sedimentary materials involving sodium, potassium, calcium, magnesium, chloride, carbon, oxygen, iron, sulfur and phosphorous through much of the Phanerozoic. The model incorporates the basic reactions controlling atmospheric carbon dioxide and oxygen concentrations, continental and seafloor weathering of silicate and carbonate rocks, net ecosystem productivity, basalt-seawater exchange reactions, precipitation and diagenesis of chemical sediments and authigenic silicates, oxidation-reduction reactions involving carbon, sulfur, and iron, and subduction-decarbonation reactions. Although MAGic contains feedback and forcing functions adapted from the GEOCARB models (Berner, 1991, 1994; Berner and Kothavala, 2001), these functions are incorporated in a reservoir-reaction scheme that is considerably more detailed. Coupled reservoirs include shallow and deep cratonic silicate and carbonate rocks and sediments, seawater, atmosphere, oceanic sediments and basalts, and the shallow mantle. Model results are reasonably consistent with recently published constraints provided by fluid inclusion, isotopic, floral, and mineralogical records. We have used these results to evaluate sensitivity to uncertainties in the history of the earth-ocean-atmosphere system over the past 500 Ma: the advent of pelagic carbonate sedimentation, the importance of burial versus early diagenetic dolomite formation, the importance of reverse weathering, and the relationship of these processes to seafloor spreading rates. Results include a general pattern of dolomite abundance during periods of elevated seafloor spreading and alkalinity production, elevated atmospheric CO2 concentrations for most of the Phanerozoic similar to those predicted by GEOCARB, and covariance of seawater sulfate to calcium ratios with magnesium to calcium ratios. These trends are broadly consistent with proxies for seawater composition and the mass-age data of the rock record itself.
53
Keywords: ATMOSPHERIC CARBON-DIOXIDE; CENOZOIC EVOLUTION; Clay minerals; CO2; DOLOMITE PROBLEM; marine-sediments; REVISED MODEL; SEAWATER CHEMISTRY; SECULAR VARIATION; time

Meridional overturning circulation in the South Atlantic at the last glacial maximum - Lynch-Stieglitz, J.; Curry, W. B.; Oppo, D. W.; Ninneman, U. S.; Charles, C. D.; Munson, J. (Geochemistry Geophysics Geosystems, 2006)
The geostrophic shear associated with the meridional overturning circulation is reflected in the difference in density between the eastern and western margins of the ocean basin. Here we examine how the density difference across 30 degrees S in the upper 2 km of the Atlantic Ocean ( and thus the magnitude of the shear associated with the overturning circulation) has changed between the last glacial maximum and the present. We use oxygen isotope measurements on benthic foraminifera to reconstruct density. Today, the density in upper and intermediate waters along the eastern margin in the South Atlantic is greater than along the western margin, reflecting the vertical shear associated with the northward flow of surface and intermediate waters and the southward flowing North Atlantic Deep Waters below. The greater density along the eastern margin is reflected in the higher delta(18)O values for surface sediment benthic foraminifera than those found on the western margin for the upper 2 km. For the last glacial maximum the available data indicate that the eastern margin foraminifera had similar delta(18)O to those on the western margin between 1 and 2 km and that the gradient was reversed relative to today with the higher delta(18)O values in the western margin benthic foraminifera above 1 km. If this reversal in benthic foraminifera delta(18)O gradient reflects a reversal in seawater density gradient, these data are not consistent with a vigorous but shallower overturning cell in which surface waters entering the Atlantic basin are balanced by the southward export of Glacial North Atlantic Intermediate Water.
092siTimes Cited:17Cited References Count:46

A multiproxy palaeoecological record of Holocene lake sediments from the Rio Tapajos, eastern Amazonia - Irion, G.; Bush, M. B.; de Mello, J. A. N.; Stuben, D.; Neumann, T.; Muller, G.; De, J. O.; Junk, J. W. (Palaeogeography Palaeoclimatology Palaeoecology, 2006)
Two sediment cores up to 42 m in length were raised from the wide, deep, section of the lower Tapajos River, Amazonia, referred to as Lago Tapajos. These cores reveal a history of subtle environmental change that began with the formation of Lago Tapajos as sea level rose about 11,000 years ago. The sediments of the lake were deposited fairly quickly-at a rate of ca. 4 m per millennium and are uniformly fine grained, with low organic content. The fossil pollen record derived from these sediments reveals that forest surrounded this site throughout the Holocene. The largest change in the core took place between ca. 5500 and 4200 cal. years BP and reflects a transition from coarser to finer sediments. Coincident with the change in sediment is a slight transition in the pollen spectra with an increase in Poaceae abundance at the expense of the pioneer tree Cecropia cecropia. A tentative explanation is offered in which increased human activity, possibly spurred by climatic change, resulted in the formation of some local grasslands. However, despite the apparent actions of humans, there is no indication of basin-wide transformation of landscapes in this record. The Holocene persistence of forest as the dominant landscape matrix around Lago Tapajos is supported by low delta C-13 values and by the constant geochemistry and mineralogy of the lake sediments. (c) 2006 Elsevier B.V. All rights reserved.
097fbTimes Cited:40Cited References Count:78

Natural abundance radiocarbon as a tracer of assimilation of petrolleum carbon by bacteria in salt marsh sediments - Wakeham, S. G.; McNichol, A. P.; Kostka, J.; Pease, T. K. (Geochim. Cosmochim. Acta, 2006)
id: 520

Natural-abundance radiocarbon as a tracer of assimilation of petroleum carbon by bacteria in salt marsh sediments - Wakeham, S. G.; McNichol, A. P.; Kostka, J. E.; Pease, T. K. (Geochimica Et Cosmochimica Acta, 2006)
The natural abundance of radiocarbon ((14)C) provides unique insight into the source and cycling of sedimentary organic matter. Radiocarbon analysis of bacterial phospholipid lipid fatty acids (PLFAs) in salt-marsh sediments of southeast Georgia (USA)-one heavily contaminated by petroleum residues-was used to assess the fate of petroleum-derived carbon in sediments and incorporation of fossil carbon into microbial biomass. PLFAs that are common components of eubacterial cell membranes (e.g., branched C(15) and C(17), 10-methyl-C(16)) were depleted in (14)C in the contaminated sediment (mean Delta(14)C value of +25 +/- 19 parts per thousand for bacterial PLFAs) relative to PLFAs in uncontaminated "control" sediment (Delta(14)C = +101 +/- 12 parts per thousand). We suggest that the (14)C-depletion in bacterial PLFAs at the contaminated site results from microbial metabolism of petroleum and subsequent incorporation of petroleum-derived carbon into bacterial membrane lipids. A mass balance calculation indicates that 6-10% of the carbon in bacterial PLFAs at the oiled site could derive from petroleum residues. These results demonstrate that even weathered petroleum may contain components of sufficient lability to be a carbon source for biomass production by marsh sediment microorganisms. Furthermore, a small but significant fraction of fossil carbon is assimilated even in the presence of a much larger pool of presumably more-labile and faster-cycling carbon substrates. (c) 2006 Elsevier Inc. All rights reserved.
030olTimes Cited:27Cited References Count:65

Non-pollen palynomorphs from organic deposits of Posidonia oceanica: a new tool for palaeoenvironmental studies in marine peat-like deposits - López-Sáez, J. A.; López-García, P.; Pozuelo, R.; Mateo, M. A.; Renom, P.; Garrido, D. (Palyno-Bulletin, 2006)
The in situ accumulation of large quantities of biogenic materials over millennia is very relevant and occurs only in a limited number of ecosystems. Peat bogs are probably the bestknown example among terrestrial ecosystems (e.g. Aaby & Berglund, 1986) and coral reefs among marine ecosystems (e.g. Clausen & Roth, 1975). In situ organic accumulations in the marine environment are rare, having been described for mangroves and seagrass species. The Mediterranean seagrass Posidonia oceanica accumulates large quantities of organic debris. Roots, rhizomes and leaf sheaths are progressively buried fonning a bioconstruction called 'matte'. The organic material remains with little morphological alteration for millennia (Mateo et aI. , 1997), constitnting a marine peat-like deposit with a great interest from a palaeoenvironmental point of view. The present paper evaluates the palaeoecological potential of the organic deposits generated by the marine phanerogame Posidonia oceanica in the Bay of Port Lligat, Girona, NE Spain. This stndy discusses the detailed evolution of the vegetation in the landscape of the area.
id: 2005

The North Anatolian fault in the Gulf of Izmit (Turkey): Rapid vertical motion in response to minor bends of a non-vertical continental transform - Cormier, M. H.; Seeber, L.; McHugh, C. M. G.; Polonia, A.; Cagatay, M. N.; Emre, O.; Gasperini, L.; Gorur, N.; Bortoluzzi, G.; Bonatti, E.; Ryan, W. B. F.; Newman, K. R. (Journal of Geophysical Research, 2006)
id: 532

Origin of PCDD in ball clay assessed with compound-specifric chlorine isotope analysis and radiocarbon dating - Holmstrand, H. D.; Gadomski, D.; Mandalakis, M.; Tysklind, M.; Irvine, R.; Andersson, P.; Gustafsson, O. (Environmental Science and Technology, 2006)
id: 1040

Pedological properties of the eroding coastline along the Beaufort Sea, Alaska - Ping, C. L.; Dou, F.; Jorgenson, G.; Michaelson, J.; Lynn, L. A.; Shur, Y.; Kanevsky, M. (Eos Trans. AGU Fall Meeting Supplement, 2006)
id: 1002

Rapid lateral particle transport in the Argentine Basin: Molecular 14C and 230Th evidence - Mollenhauer, Gesine; McManus, Jerry F.; Benthien, Albert; Muller, Peter J.; Eglinton, Timothy I. (Deep-Sea Research I, 2006)
id: 543

Rapid subsidence and sedimentation from oblique slip near a bend on the North Anatolian transform fault in the Marmara Sea, Turkey - Seer, L.; Cormier, M. H.; McHugh, C.; Emre, O.; Polonia, A.; Sorlien, C. (Geology, 2006)
id: 533

Sea-level variation during the holocene deduced from the morphologic and stratigraphic evolution of Morgan Peninsula, Alabama, USA - Rodriguez, A. B.; Meyer, C. T. (Journal of Sedimentary Research, 2006)
Recent Gulf of Mexico shoreline studies interpret middle to late Holocene sea level as failing from a level above present elevation or stable at present elevation; however, the architecture of Morgan Peninsula, Alabama, does not support this. Morgan Peninsula is a beach-ridge strandplain composed of two obliquely aligned Holocene beach-ridge sets. Ground-penetrating radar profiles discriminate between parallel, even to wavy reflectors of the eolian dune environment and the underlying seaward-dipping, complex sigmoidal-oblique reflectors of the foreshore and upper-shoreface environment. The contact between foreshore and eolian facies in beach ridges can be used as a sea-level indicator. The average elevation of this contact in Morgan Peninsula rises throughout shoreline accretion, which occurred throughout the last 5.4 ka, suggesting that there was continual sea-level rise during this time. Morgan Peninsula is a useful modern analog to ancient shoreface-shelf parasequences and demonstrates the significant internal complexities that can exist in these deposits. Erosional discontinuities imaged in the Holocene foreshore-upper shoreface environment are laterally continuous, extend to elevations above mean sea level, and correlate to beach ridges and the transition between beach-ridge sets. An increase in the wave regime or fluctuations in sediment supply appear to be likely mechanisms for forming erosional discontinuities below beach ridges. The erosional surface separating beach-ridge sets may have formed by increased storm activity and associated barrier breaching, or a reconfiguration of the Mobile Bay tidal-delta complex superimposed on a gradual rate of sea-level rise. This boundary is recognized by a change in beach-ridge orientation at the surface and an increase in the aggradational component of shoreline accretion.
id: 2040; PT: J; UT: WOS:000235746800018

Sedimentary features of the Yangtze River-derived along-shelf clinoform deposit in the East China Sea - Liu, J. P.; Li, A. C.; Xu, K. H.; Veiozzi, D. M.; Yang, Z. S.; Milliman, J. D.; DeMaster, D. (Continental Shelf Research, 2006)
A predominant sigmoidal clinoform deposit extends from the Yangtze River mouth southwards 800 kin along the Chinese coast. This clinoform is thickest (similar to 40m) between the 20 and 30 m isobaths and progressively thins offshore, reaching water depths of 60 and 90 m and distances up to 100 km offshore. Clay mineral, heavy metal, geochemical and grain-size analyses indicate that the Yangtze River is the primary source for this longshore-transported clinoform deposit. (210)Pb chronologies show the highest accumulation rates (> 3 cm/yr) occur immediately adjacent to the Yangtze subaqueous delta (north of 30 degrees N), decreasing southward alongshore and eastward offshore. The interaction of strong tides, waves, the China Coastal Current, winter storms, and offshore upwelling appear to have played important roles in trapping most Yangtze-derived sediment on the inner shelf and transporting it to the south. (c) 2006 Elsevier Ltd. All rights reserved.
109ueTimes Cited:158Cited References Count:62

Source and transport of terrigenous organic matter of the upper Yukon River: evidence from isotope (13C, 14C and 15N) composition of dissolved, colloidal and particulate phases - Guo, L.; Macdonald, R. W. (Global Biogeochemical Cycles, 2006)
id: 1129

Sources and potential transformation of estuarine dissolved and particulate organic matter: a multi-tracer approach - McCallister, S. L.; Bauer, J. E.; Ducklow, H. W.; Canuel, E. A. (Organic Geochemistry, 2006)
id: 597

Stable carbon isotopes in coastal Puerto Rico corals and adjacent natural waters: implications for land-ocean connectivity and land-use history - Moyer, R. P.; Grottoli, A. G. (Ocean Sciences Meeting, 2006)
id: 655

Submarine earthquake geology along the North Anatolia Fault in the Marmara Sea, Turkey: A model for transform basin sedimentation - McHugh, C. M. G.; Seeber, L.; Cormier, M. H.; Dutton, J.; Cagatay, N.; Polonia, A.; Ryan, W. B. F.; Gorur, N. (Earth and Planetary Science Letters, 2006)
The submerged portions of the North Anatolia Fault system beneath the Marmara Sea were studied with high-resolution multibeam bathymetry, subbottom profiling and sediment cores. The major objectives were to learn about the seismic and tectonic history of the fault from the stratigraphic record at a scale similar to paleoseismic studies on land and to develop tools for submarine earthquake geology that can be applied to fault-controlled basins in general. We focused on Holocene sediment in several Marmara Sea basins of different sizes. The approach was to test whether: (1) the depocenters of the larger basins contain a record of all historic Ms > 7 earthquakes within the Marmara Sea region; (2) the small transform basins record earthquakes that rupture through them; (3) vertical and strike-slip Holocene deformation can be quantified; and (4) the effects of an earthquake generally includes both primary structural features due to rupture of the sea floor, such as strata offset, scarps and tilting, as well as secondary effects due to shaking, such as mass-wasting and gravitational flows. We found evidence of earthquakes that we correlate with historic events in 181 AD, 740 AD, 1063 AD, 1343 AD, 1509 AD, 1766 AD, 1894 AD and 1912 AD. The geologic evidence is primarily from those basins adjacent to the rupture as inferred from historic data. This suggests that coseismic deformation of the sea floor along the rupture is a critical factor in the sedimentary record. We propose a qualitative sedimentation model that relates this coseismic deformation to mass-wasting of the slope, scour of the basin floor, seiche motions and homogenite deposition. Frequent earthquake activity sheds sediments from the flanks, contributes to the much thicker sediment on the basin floor and decreases the likelihood of sediment failures in response to normal marine gravity-driven processes. The surveying techniques and approaches used have therefore the potential of documenting earthquake ruptures of fault segments and to extend the earthquake record far before the known history, thus improving hazard evaluations and the fundamental understanding of earthquake process. (c) 2006 Elsevier B.V. All rights reserved.
085kgTimes Cited:55Cited References Count:98

Two ecological shifts in Long Island Sound during the industrial period - Thomas, E.; Varekamp, J. C.; Mecray, E. L.; Buchholtzten-Brink, M. R. L.; Cooper, S.; Brinkhuis, H.; Sangioirgio, F. (Long Island Sound Research Center, 2006)
id: 751

Variability in the character, age and reactivity of organic matter exported from rivers and estuaries to ocean margins - Bauer, J. E.; Cole, J. J.; Caraco, N. F.; Raymond, P. A.; Keesee, E. J.; Fernald, S.; Mull, K. (Ocean Sciences Meeting, 2006)
id: 476

Age and origin of Late Quaternary eolianite, Kaiehu Point (Moomomi), Molokai, Hawaii - Fletcher, C. H.; Murray-Wallace, C. V.; Glenn, C. R.; Sherman, C. E.; Popp, B.; Hessler, A. (Journal of Coastal Research, 2005)
A well-preserved, vertically stacked succession of two genetically distinct eolianites and associated caliche paleosol units, capped by modern and Holocene coastal dunes, occurs at Kaiehu Point, west Molokai, Hawaii. The Pleistocene eolianite facies comprise well-cemented, medium grained skeletal carbonate sand and their morphostratigraphic context implies formation at times of lower than present sea level. Amino acid racernization (AAR) evidence suggests eolianite formation late in marine Oxygen Isotope Stage (OIS) 5, but lacks the precision to uniquely define in which isotopic substage the deposits formed. Coupled with the AAR results, the morphostratigraphic evidence, would suggest that the Lower Eolianite formed in OIS 5c and the Middle Eolianite during 5a with their superposed caliche paleosols having formed in subsequent stadial stages. The unconsolidated coastal sand dunes of Holocene age contain reworked Late Pleistocene skeletal carbonate sand based on AAR evidence. The most likely source of the reworked carbonate is from the erosion of the eolianites at Kaiehu Point. The Pleistocene eolianite-caliche paleosol sediments reveal variable Mg-content, stable isotope ratios and petrological characteristics consistent with changing degrees of weathering intensity and meteoric diagenesis. These changes are attributed to orographic effects resulting from relative sea-level changes. Accordingly, a two-phase model is favored for the formation of the eolianite-paleosol successions at Kaiehu Point, west Molokai. Eolianite sedimentation is initiated at times of marginally lower sea levels promoting the landward migration of bioclastic sand to form extensive eolian sandsheets. This is followed by a more pronounced phase of pedogenesis associated with a further fall in sea level and concomitant increased rainfall due to enhanced orographic effects.
Sp. Iss. 42947fu Times Cited:3 Cited References Count:50
Keywords: Amino acid racemization; aminostratigraphy; bermuda; carbonate lithofacies; cementation; cliche paleosols; eolianite; hawaii; island; Late Quaternary; limestone petrology; Marine; molokai; oahu; precipitation; sea level; sea-level; south-australia; Stable isotopes; stratigraphy

Age validation of canary rockfish (Sebastes pinniger) from off the Oregon coast (USA) using the bomb radiocarbon method - Piner, K. R.; Hamel, O. S.; Menkel, J. L.; Wallace, J. R.; Hutchinson, C. E. (Canadian Journal of Fisheries and Aquatic Sciences, 2005)
The alternating translucent and opaque banding pattern in canary rockfish (Sebastes pinniger) otoliths, aged using a break-and-burn methodology, are annual markings. To validate age assignment, we compared measured radiocarbon levels in canary rockfish otolith cores with a reference chronology developed from known age Pacific halibut (Hippoglossus stenolepis). An average 2- to 3-year phase shift was detected between the canary rockfish and a Pacific halibut reference chronology that was likely the result of differences in the regional oceanography or underageing bias. The assumption of ageing bias consistency was tested with two sampling designs. The first design controled for age-related ageing error, and the second design related birth year to estimated age. No change in the magnitude of ageing bias as a function of age was detected.
932zxTimes Cited:27Cited References Count:27

Contribution of biomass burning to polycyclic aromatic hydrocarbons in European background aerosols - Mandalakis, M.; Gustafsson, O.; Alsberg, T.; Reddy, C.; Xu, L.; Klanova, J.; Holoubek, I.; Stephanou, E. (Environmental Science and Technology, 2005)
id: 510

Cross-formational flow and salinity sources inferred from a combined study of helium concentrations, isotopic ratios, and major elements in the Marshall aquifer, southern Michigan - Ma, L.; Castro, M. C.; Hall, C. M.; Walter, L. M. (Geochemistry Geophysics Geosystems, 2005)
Helium data and major ion chemistry are presented for the shallow Marshall aquifer in southern Michigan. This data set is subsequently analyzed in conjunction with major element data sets from deeper and shallower water levels previously collected in this area. He excesses and isotopic ratios suggest the presence of tritiogenic He-3 in young waters in the Marshall aquifer. He excesses in old groundwater samples are mostly of crustal origin although the presence of a significant mantle He component in some samples cannot be ruled out. He excesses in the Marshall aquifer are unusually high for such shallow depths ( <= 300 m) and reach over two and three orders of magnitude above those of air- saturated water ( ASW) for He-3 and He-4, respectively. He isotopes require a source external to the aquifer, partly supplied by underlying formations within the sedimentary sequence, partly from the crystalline basement. Calibration of He concentrations observed in the Marshall aquifer requires He fluxes of 1 x 10(-13) and 1.6 x 10(-6) cm(3) STP cm(-2) yr(-1) for He-3 and He-4, respectively. These He fluxes are far greater than those reported in other sedimentary basins around the world ( e. g., Paris Basin, Gulf Coast Basin) at similar and far greater depths. Such high He fluxes present at such shallow depths within the Michigan Basin strongly suggest the presence of a dominant vertical water flow component and further indicate that impact of recharge water at depth is minor. Upward cross- formational flow is also likely responsible for the extremely high salinities present in the shallow subsurface of the Michigan Basin. The observed positive correlation between helium and bromide strongly suggests that these two very distinct conservative tracers both originate at greater depths and further suggests that advection is the dominant transport mechanism within the basin. The occurrence of large- scale cross- formational flow is also consistent with the evolution displayed by the major ion chemistry throughout most of the sedimentary sequence, indicating that solutes from shallow levels carry the signature of deep formation brines.
973vwTimes Cited:18Cited References Count:63

Effects of natural sunlight on decomposition of estuarine dissolved organic C, N and P and bacterial growth - McCallister, S. L.; Bauer, J. E.; Kelly, J.; Ducklow, H. W. (Aquatic Microbial Ecology, 2005)
id: 1101

An evaluation of 14C age relationships between co-occurring foraminifera, alkenones, and total organic carbon in continental margin sediments - Mollenhauer, Gesine; Kienast, Markus; Lamy, Frank; Meggers, Helge; Schneider, Ralph R.; Hayes, John M.; Eglinton, Timothy I. (Paleoceanography, 2005)
id: 492

Evidence from the Northeastern Atlantic basin for variability in the rate of the meridional overturning circulation through the last deglaciation - Gherardi, J. M.; Labeyrie, L.; McManus, J. F.; Francois, R.; Skinner, L. C.; Cortijo, E. (Earth and Planetary Science Letters, 2005)
A first study from the subtropical western Atlantic, using Pa-231/Th-230 ratios as a kinematic proxy for deep water circulation, provided compelling evidence for a strong link between climate and the rate of Meridional Overturning Circulation (MOC) over the last deglaciation. However, these results warrant confirmation from additional locations and water depths because the interpretation of the sedimentary Pa-231/Th-230 ratio in terms of circulation vigor can be biased by variations in particle flux and composition. We have measured Pa-231/Th-230 in a core from the Iberian margin, in the Northeastern Atlantic basin, and have compared these new results to the data from the western Atlantic basin. We find that the reduction in the circulation during H1 and YD and the subsequent increases first recognized in the sediment deposited on Ben-nuda Rise are also evident in the eastern basin, in a totally different sedimentary regime, confirming that sedimentary Pa-231/Th-230 ratios record basin-wide changes in deep water circulation. However, some differences between the eastern and western records are also recognized, providing preliminary evidence to differentiate between renewal rates in the two North Atlantic basins and between shallower and deeper overturning. Our results suggest the possible existence of two sources of Glacial North Atlantic Intermediate Deep Water (GNAIW), one in the south Labrador Sea and another west of Rockall Plateau. Both sources contributed to the meridional overturning but the two had different sensitivity to meltwater from the Laurentide and the Fermoscandian ice sheets during the deglaciation. These results indicate that additional information on the geometry and strength of the ventilation of the deep Atlantic can be obtained by contrasting the evolution of sediment Pa-231/Th-230 in different sections of the Atlantic Ocean. (C) 2005 Elsevier B.V. All rights reserved.
995vhTimes Cited:93Cited References Count:69

Fluctuations in export productivity over the last century from sediments of a southern Chilean fjord (44 degrees S) - Sepulveda, J.; Pantoja, S.; Hughen, K.; Lange, C.; Gonzalez, F.; Munoz, P.; Rebolledo, L.; Castro, R.; Contreras, S.; Avila, A.; Rossel, P.; Lorca, G.; et al. (Estuarine Coastal and Shelf Science, 2005)
Here we present the first reconstruction of changes in surface primary production during the last century from the Puyuhuapi fjord in southern Chile, using a variety of parameters (diatoms, biogenic silica, total organic carbon, chlorins, and proteins) as productivity proxies. Two sediment cores from the head and the center of the fjord were analyzed and compared to gain insights on past changes in productivity in these two different depositional environments. Higher sedimentation rates found at the head of the fjord result from the combination of a shallower water column and a restricted circulation by the occurrence of a sill. Additionally, sediment mixing depths estimated from (210)Pb data suggest that suboxic conditions may dominate the bottom water and the sediment-water interface in this location.Productivity of the Puyuhuapi fjord during the last century was characterized by a constant increase from the late 19th century to the early 1980s, then decreased until the late 1990s, and then rose again to present-day values. The influence of rainfall on productivity was most noticeable during periods of low rainfall, which coincided with decreased overall productivity within the Puyuhuapi fjord. Simultaneous variations in productivity and rainfall in the study area suggest that marine productivity could respond to atmospheric-oceanic interactions at a local scale. At a regional scale, marine productivity of the area may be related to other large-scale processes such as the El Nino Southern Oscillation. (c) 2005 Elsevier Ltd. All rights reserved.
975sfTimes Cited:22Cited References Count:53

Geochemical and hydrogeological contrasts between shallow and deeper aquifers in two villages of Araihazar, Bangladesh: Implications for deeper aquifers as drinking water sources - Zheng, Y.; van Geen, A.; Stute, M.; Dhar, R.; Mo, Z.; Cheng, Z.; Horneman, A.; Gavrieli, I.; Simpson, H. J.; Versteeg, R.; Steckler, M.; Grazioli-Venier, A.; et al. (Geochimica et Cosmochimica Acta, 2005)
Sediment and groundwater profiles were compared in two villages of Bangladesh to understand the geochemical and hydrogeological factors that regulate dissolved As concentrations in groundwater. In both villages, fine-grained sediment layers separate shallow aquifers ( 50 ka ago and a groundwater age of thousands of years. In the other village (Bay), the sediment is
id: 604; 999UZ Times Cited:59 Cited References Count:49

Global methane emission through mud volcanoes and its past and present impact on the Earth's climate-a comment - Milkov, A. V.; Etiope, G. (International Journal of Earth Sciences, 2005)
940vyTimes Cited:11Cited References Count:15

Global ocean data analysis project (GLODAP): Results and data, ORNL/CDIAC-145, NDP-145 - Sabine, C. L.; Key, R. M.; Kozyr, A.; Feely, R. A.; Wanninkhof, R.; Millero, F. J.; Peng, T. H.; Bullister, J. L.; Lee, K. (2005)
id: 529

Impact of millennial-scale Holocene climate variability on eastern North American terrestrial ecosystems: pollen-based climatic reconstruction - Willard, D. A.; Bernhardt, C. E.; Korejwo, D. A.; Meyers, S. R. (Global and Planetary Change, 2005)
We present paleoclimatic evidence for a series of Holocene millennial-scale cool intervals in eastern North America that occurred every similar to 1400 years and lasted similar to 300-500 years, based on pollen data from Chesapeake Bay in the mid-Atlantic region of the United States. The cool events are indicated by significant decreases in pine pollen, which we interpret as representing decreases in January temperatures of between 0.2 degrees and 2 degrees C. These temperature decreases include excursions during the Little Ice Age (similar to 1300-1600 AD) and the 8 ka cold event. The timing of the pine minima is correlated with a series of quasi-periodic cold intervals documented by various proxies in Greenland, North Atlantic, and Alaskan cores and with solar minima interpreted from cosmogenic isotope records. These events may represent changes in circumpolar vortex size and configuration in response to intervals of decreased solar activity, which altered jet stream patterns to enhance meridional circulation over eastern North America. (c) 2004 Elsevier B.V All rights reserved.
944zeTimes Cited:48Cited References Count:68

An investigation of accurate gas exchange measurements for determing a large river carbon isotope mass balance - Raymond, P. A.; McGillis, W. R.; Bauer, J. E.; Caraco, N. F.; Cole, J. J. (37th Liege International Colloquium on Gas Transfer at Water Survaces, 2005)
id: 490

Lacustrine loss-on-ignition recrods from the southern Uinta Mountains - Munroe, Jeffrey S. (Geological Society of America Abstracts with Programs, 2005)
id: 694

Late neogene and quaternary evolution of the northern Albermarle Embayment (mid-Atlantic continental margin, USA) - Mallinson, D.; Riggs, S.; Culver, S.; Thieler, R.; Foster, D. R.; Corbett, D. R.; Farrell, K.; J, Wehmiller (Marine Geology, 2005)
id: 1160

Long term calibration of the Noble gas temperature system in a shallow unconfined Pleistocene aquifer - Hall, C. M.; Castro, M. C.; Lohmann, K. C.; Ma, L. (Eos Trans. AGU Fall Meeting Supplement, 2005)
id: 438

Mid-Holocene hydrologic change and hypolimnion formation in Lake Erie - Clotts, R. A.; McCambridge, C. E.; Barrera, E.; Saylor, B. Z.; Palmer, D. F.; Coakley, J. P. (Journal of Great Lakes Research, 2005)
id: 688

Molecular and stable isotope compositions of natural gas hydrates: A revised global dataset and basic interpretations in the context of geological settings - Milkov, A. V. (Organic Geochemistry, 2005)
A global dataset of molecular and stable isotope compositions of gases released from 209 different specimens of natural gas hydrate is presented and discussed. The 26 hydrate-bearing areas from 21 geographic regions are grouped into high gas flux (HGF) settings, low gas flux (LGF) settings and hydrated gas accumulations (HGA). Methane (CH4) is the most abundant hydrate-bound gas, while CO2 and C2+ hydrocarbon gases are frequently present in small amounts. Non-hydrocarbon gases, such as H2S, are uncommon. The stable isotope composition of hydrate-bound gases varies significantly (e.g., delta(13)C of CH4 from -74.7 to -39.60 parts per thousand), suggesting that gases of both microbial and thermogenic origin form gas hydrates. Hydrate-bound gases are derived from autochthonous [Located predominantly within the gas hydrate stability zone (GHSZ)] and allochthonous (located in deep sediments) sources. The occurrence and concentration of gas hydrates in sediments are controlled not by the origin of gases, but rather by their sources, which in turn strongly depend on geological setting. Allochthonous gases (microbial and/or thermogenic) dominate in HGF and HGA settings where they are focused in the shallow GHSZ along faults, within mud volcanoes, in permeable carrier beds and other geological features from underlying petroleum systems. Relatively high concentrations of gas hydrate (average 5-15% of pores and locally up to 100 parts per thousand of volume) occurring over small areas are typical of HGF and HGA settings. In contrast, autochthonous and diffuse allochthonous gases (mostly microbial) occur in stratigraphically and structurally simple LGF settings and result in relatively low concentrations of gas hydrate (average similar to 2% of pores in the GHSZ) spread over large areas. The major implication of this finding is that successful prediction of resource and geohazard potential of gas hydrates is possible only if regional petroleum systems extending well below the GHSZ are properly evaluated. In addition to the diagnosis of origins and sources of hydrate-bound gases, molecular and isotopic data help to better identify hydrate-bearing intervals and provide valuable insights into the dynamics of hydrate-bearing sites. (C) 2005 Elsevier Ltd. All rights reserved.
929dvTimes Cited:101Cited References Count:138

Natural variability in skeletal growth rate, stable isotopes, and Sr/Ca composition in two species of Pacific sclerosponges (Acnathocheatetes wellsi and Astroclera welleyana) - Grottoli, A. G.; Adkins, J. F.; Moots, K. (Benthic Ecology Meetings, 2005)
id: 1135

Noble gases and stable isotopes in a shallow aquifer in southern Michigan: Implications for noble gas paleotemperature reconstructions for cool climates - Hall, C. M.; Castro, M. C.; Lohmann, K. C.; Ma, L. (Geophysical Research Letters, 2005)
Noble gas data from the Glacial Drift, the shallowest aquifer in southern Michigan confirm findings by Ma et al. (2004) that modern noble gas temperatures (NGTs) are systematically below the current mean annual air temperature (MAAT) which, in turn, is similar to the ground temperature of these recharge waters. By tracking noble gas concentrations as well as stable isotope ratios through an autumn, winter, spring and into summer, we show that although water in this aquifer is modern, noble gases do not track the atmosphere on a short time scale. Specifically, excess He-3 and He-4 indicate that the gas environment at the water table is integrating conditions over years or decades rather than weeks or months. Our results are interpreted using various NGT interpretational models and possible mechanisms for the production of low apparent NGTs are discussed.
968qnTimes Cited:26 Cited References Count:14
Keywords: water

Once spilled, still found: metal contamination in Connecticut wetlands and Long Island Sound sediment from historic industries, Chapter 9 - Varekamp, J. C.; Mecray, E. L.; Zierzow, T. (Our Changing Coasts, 2005)
id: 724

One-year record of organic and elemental carbon in fine particles in downtown Beijing and Shanghai - Yang, F.; He, K.; Ye, B.; Chen, X.; Cha, L.; Cadle, S. H.; Chan, T.; Mulawa, P. A. (Atmospheric Chemistry and Physics, 2005)
Weekly PM2.5 samples were collected for one year ( 1999 - 2000) in Beijing and Shanghai and the carbonaceous species analyzed to investigate and compare their time series patterns and possible sources in the two biggest cities of China. Weekly carbonaceous concentrations varied in wide ranges with 8.6 - 59 mu g m(-3) for OC and 1.5-25.4 mu g m(-3) for EC in Beijing, and with 5.1 - 38.4 mu g m(-3) for OC and 2.3 - 13.0 mu g m(-3) for EC in Shanghai. Similar weekly and seasonal variations of OC and EC concentrations were found in each city though major combustion sources presented source-dependent emission characteristics and seasonal differences in emission amount for carbonaceous species. Both OC and EC maintained much higher concentrations in late fall through winter, probably due to enhanced emissions coupled with unfavorable meteorological conditions. In Beijing, the C-14 analysis of limited samples suggested there was a significant contribution ( 33 - 48%) of modern carbon to the total fine carbonaceous PM burden with higher fractions in the harvest seasons. The high mass ratios of excessive potassium to EC in both Beijing and Shanghai also indicated that biomass burning had important contribution to fine carbonaceous particles.
936dsTimes Cited:77Cited References Count:45

Radiocarbon dating of alkenones from marine sediments: I. Isolation protocol - Ohkouchi, N.; Xu, L.; Reddy, C. M.; Montlucon, D.; Eglinton, T. I. (Radiocarbon, 2005)
The chemical and isotopic compositions of long-chain (C-36-C-39) unsaturated ketones (alkenones), a unique class of algal lipids, encode surface ocean properties useful for paleoceanographic reconstruction. Recently, we have sought to extend the utility of alkenones as oceanic tracers through measurement of their radiocarbon contents. Here. we describe a method for isolation of alkenones from sediments as a compound class based on a sequence of wet chemical techniques. The steps involved, which include silica gel column chromatography, urea adduction, and silver nitrate-silica gel column chromatography, exploit various structural attributes of the alkenones. Amounts of purified alkenones estimated by GC/FID measurements were highly correlated with CO2 yields after sample combustion, indicating purities of greater than 90% for samples containing >= 100 mu g C. The degree of alkenone unsaturation (U-37(K')) also varied minimally through the procedure. We also describe a high-performance liquid chromatography (HPLC) method to isolate individual alkenones for molecular-level structural and isotopic determination.
993nkTimes Cited:13 Cited References Count:22
Keywords: AMS; carbon; indicators; proxy; records; tool

Radiocarbon dating of alkenones from marine sediments: II. Assessment of carbon process blanks - Mollenhauer, G.; Montlucon, D.; Eglinton, T. I. (Radiocarbon, 2005)
We evaluate potential process blanks associated with radiocarbon measurement of microgram to milligram quantities of alkenones at the National Ocean Sciences Accelerator Mass Spectrometry (NOSAMS) facility. Two strategies to constrain the contribution of blanks to alkenone C-14 dates were followed: 1) dating of samples of known age and 2) multiple measurements of identical samples. We show that the potential contamination associated with the procedure does not lead to a systematic bias of the results of alkenone dating to either younger or older ages. Our results indicate that alkenones record Delta(14)C of ambient DIC with an accuracy of approximately 10 parts per thousand. A conservative estimate of measurement precision is 17 parts per thousand for modern samples. Alkenone C-14 ages are expected to be reliable within 500 yr for samples younger than 10,500 C-14 yr.
993nkTimes Cited:13 Cited References Count:20
Keywords: c-14 ams; organic-compounds; records; samples; system; tool

Rapid lateral particle transport in the Argintine Basin: Th-230 and molecular C-14 Evidence, Poster - Mollenhauer, Gesine; McManus, J. F.; Benthien, A.; Muller, P. J.; Eglinton, T. I. (EGU General Assembly, 2005)
id: 548

Rapid viscoelastic uplift in southeast Alaska caused by post-Little Ice Age glacial retreat - Larsen, C. F.; Motyka, R. J.; Freymueller, J. T.; Echelmeyer, K. A.; Ivins, E. R. (Earth and Planetary Science Letters, 2005)
Our observations show that extreme uplift in southeast Alaska began about 1770 AD, with relative sea level (RSL) change to 5.7 m and current uplift rates to 32 mm/yr. This region experienced widespread glacial melting following the Little Ice Age (LIA), with the collapse of the Glacier Bay Icefield alone equivalent to 8 mm of global sea level rise. Geodynamic modelling links the uplift to post-LIA isostatic rebound, with the extreme uplift signal and a priori knowledge of ice load changes requiring the presence of a low viscosity asthenosphere (3.7 X 10(18) Pa s). These crustal deformations are triggered by climate change through glacier wastage. (c) 2005 Elsevier B.V. All rights reserved.
968ijTimes Cited:109Cited References Count:44

On the sedimentological origin of downcore variations of bulk sedimentary nitrogen isotope ratios - Kienast, M.; Higginson, M. J.; Mollenhauer, G.; Eglinton, T. I.; Chen, M. T.; Calvert, S. E. (Paleoceanography, 2005)
The bulk sedimentary nitrogen isotopic composition of two cores from nearby sites on the northern slope of the South China Sea (Site 17940 and Ocean Drilling Program (ODP) Site 1144) differs by up to >2‰ during the last glacial period. Given their close proximity, both core sites are located in the same biogeographic zone and nutrient regime, and it is thus unlikely that this offset is due to a true gradient in surface ocean conditions. In an attempt to resolve this offset, we have investigated the possible effects of two sedimentological parameters that can affect bulk sedimentary δ15N, namely, the variable contribution of inorganic N to bulk N in the sediment and the grain-size dependence of bulk δ15N. We find that neither effect, singly or in combination, is sufficient to explain the significant δ15N offset between the two down-core records. By elimination the most likely explanation for the observed discrepancy is a different origin of both the organic and inorganic nitrogen at each site. This study adds to the growing body of evidence highlighting the complex nature and origin of the sedimentary components in sediment drifts, such as ODP Site 1144.
id: 1066

Status of the U. S. canary rockfish resource in 2005 - Methot, R.; Stewart, I. J. (Status of the Pacific Coast Groundfish Fishery Through 2005, Stock Assessment and Fishery Evaluation: Stock Assessments and Rebuilding Analyses, 2005)
id: 539

Subducting oceanic crust: The source of deep diamonds - Tappert, R.; Stachel, T.; Harris, J. W.; Muehlenbachs, K.; Ludwig, T.; Brey, G. P. (Geology, 2005)
Inclusions of majoritic garnet in diamonds from the Jagersfontein kimberlite formed at unusually great depths of similar to 250 to > 500 km in the asthenosphere and transition zone. The original host rocks were derived from a much shallower, basaltic (eclogitic) source. The presence of negative Eu anomalies in all majoritic garnets requires a crustal origin, thereby linking these very deep diamond sources to subducting oceanic crust. The carbon isotope values (delta(13)C) of the host diamonds fall within a narrow range at similar to -20%, which is fundamentally different from the broad range (-24% to -2%) and bimodal distribution of carbon isotopes of Jagersfontein diamonds that formed in the shallower lithosphere. This indicates that majoritic garnet-bearing diamonds at Jagersfontein inherited their light carbon isotopic composition directly from organic matter contained in a subducting slab. These diamonds were likely formed by direct conversion from graphite, well within the diamond stability field.
938hnTimes Cited:65Cited References Count:26

The supply and preservation of ancient and modern components of organic carbon on the Canadian Beaufort Shelf of the Arctic Ocean - Goñi, M. A.; Yunker, M. B.; Macdonald, R. W.; Eglinton, T. I. (Marine Chemistry, 2005)
id: 757

Toward a Neoproterozoic composite carbon-isotope record - Halverson, G. P.; Hoffman, P. F.; Schrag, D. P.; Maloof, A. C.; Rice, A. H. N. (Geological Society of America Bulletin, 2005)
Glacial deposits of Sturtian and Marinoan age occur in the well-studied Neoproterozoic successions of northern Namibia, South Australia, and northwestern Canada. In all three regions, the Marinoan glaciation is presaged by a large negative delta(13)C anomaly, and the cap carbonates to both glacial units share a suite of unique sedimentological, stratigraphic, and geochemical features. These global chronostratigraphic markers are the bases of a new correlation scheme for the Neoproterozoic that corroborates radiometric data that indicate that there were three glacial epochs between ca. 750 and 580 Ma. Intraregional correlation of Neoproterozoic successions in the present-day North Atlantic region suggests that glacial diamictite pairs in the Polarisbreen Group in northeastern Svalbard and the Tillite Group in eastern Greenland were deposited during the Marinoan glaciation, whereas the younger of a pair of glacials (Mortensnes Formation) in the Vestertana Group of northern Norway was deposited during the third (Gaskiers) Neoproterozoic glaciation. Gaskiers-aged glacial deposits are neither globally distributed nor overlain by a widespread cap carbonate but are associated with an extremely negative delta(13)C anomaly. The chronology developed here provides the framework for a new, high-resolution model carbon-isotope record for the Neoproterozoic comprising new delta(13)C (carbonate) data from Svalbard (Akademikerbreen Group) and Namibia (Otavi Group) and data in the literature from Svalbard, Namibia, and Oman. A new U-Pb zircon age of 760 +/- 1 Ma from an ash bed in the Ombombo Subgroup in Namibia provides the oldest direct time-calibration point in the compilation, but the time scale of this preliminary delta(13)C record remains poorly constrained.
960jtTimes Cited:414Cited References Count:174

Unusually high helium fluxes in the shallow Marshall aquifer in southern Michigan: implications for cross-formational flow and salinity sources - Ma, L.; Castro, M. C.; Hall, C. M.; Walter, L. M. (Eos Trans. AGU Fall Meeting Supplement, 2005)
id: 437

14C activity and global carbon cycle changes over the past 50,000 years - Hughen, K.; Lehman, S.; Southon, J.; Overpeck, J.; Marchal, O.; Herring, C.; Turnbull, J. (Science, 2004)
A series of 14C measurements in Ocean Drilling Program cores from the tropical Cariaco Basin, which have been correlated to the annual-layer counted chronology for the Greenland Ice Sheet Project 2 (GISP2) ice core, provides a high-resolution calibration of the radiocarbon time scale back to 50,000 years before the present. Independent radiometric dating of events correlated to GISP2 suggests that the calibration is accurate. Reconstructed 14C activities varied substantially during the last glacial period, including sharp peaks synchronous with the Laschamp and Mono Lake geomagnetic field intensity minimal and cosmogenic nuclide peaks in ice cores and marine sediments. Simulations with a geochemical box model suggest that much of the variability can be explained by geomagnetically modulated changes in 14C production rate together with plausible changes in deep-ocean ventilation and the global carbon cycle during glaciation.
Hughen, KLehman, SSouthon, JOverpeck, JMarchal, OHerring, CTurnbull, Jeng2004/01/13 05:00Science. 2004 Jan 9;303(5655):202-7.

14C Measurements - Tanner, R. L.; Parkhurst, W. J.; McNichol, A. P. (Aerosol Science & Technol, 2004)
id: 972

Abrupt tropical vegetation response to rapid climate changes - Hughen, K. A.; Eglinton, T. I.; Xu, L.; Makou, M. (Science, 2004)
Identifying leads and lags between high- and low-latitude abrupt climate shifts is needed to understand where and how such events were triggered. Vascular plant biomarkers preserved in Cariaco basin sediments reveal rapid vegetation changes in northern South America during the last deglaciation, 15,000 to 10,000 years ago. Comparing the biomarker records to climate proxies from the same sediment core provides a precise measure of the relative timing of changes in different regions. Abrupt deglacial climate shifts in tropical and high-latitude North Atlantic regions were synchronous, whereas changes in tropical vegetation consistently lagged climate shifts by several decades.
Hughen, Konrad AEglinton, Timothy IXu, LiMakou, MatthewengResearch Support, Non-U.S. Gov't2004/05/25 05:00Science. 2004 Jun 25;304(5679):1955-9. Epub 2004 May 20.

Advective controls on the age of marine sedimentary organic matter - Mollenhauer, Gesine; Eglinton, Timothy I.; Hayes, John M. (Gordon Research Conference Organic Geochemistry, 2004)
id: 1068

Age of the Palos Verdes submarine debris avalanche, southern California - Normark, W. R.; McGann, M.; Sliter, R. (Marine Geology, 2004)
id: 990

AMS 14C measurement and preparative techniques at NIES-TERRA - Yoneda, Minoru; Shibata, Yasuyuki; Tanaka, Atsushi; Uehiro, Takashi; Morita, Masatoshi; Uchida, Masao; Kobayashi, Toshiyuki; Kobayashi, Chiaki; Suzuki, Ryo; Miyamoto, Keisuke; Hancock, Boze; Dibden, Chris; et al. (Nuclear Instruments and Methods in Physics Research B, 2004)
The AMS facility at the National Institute for Environmental Studies (NIES) has now been operating for five years since 1997. This AMS-dedicated facility named NIES-TERRA (Tandem accelerator for Environmental Research and Radiocarbon Analysis) consists of a 5MV tandem Pelletron (15SDH-2), a solid ion source with sequential injection system, a gas ion source with a simultaneous injection system, and a gas ionization detector. Typical precision with 14C measurements is around 0.5% and the background level has been achieved at around 50 kBP. Our main target is radiocarbon in environmental sciences, while other cosmogenic isotopes (10Be and 26Al) have been measured. Recently we have improved our preparation laboratory to increase sample throughput. CO2 production and purification using a commercial elemental analyzer connected to cryogenic traps (EA–CT) were investigated. We used a modified elemental analyzer with a chemical trap for separation and this is expected to reduce memory effect and background in comparison with an analyzer using gas-chromatography. This newly designed EA–CT system showed high precision and accuracy. Source of background contamination was also discussed based on the analysis of various amounts of standard materials.
id: 1492

Artifacts from a submerged prehistoric site on the Coos Bay Estuary, southern Oregon coast - Minor, Rick; Nelson, Alan R. (Journal of California and Great Basin Anthropology, 2004)
id: 993

Assessing sources and agesof organic matter supporting river and estuarine bacterial production: a multiple isotope (Delta14C, delta13C and delta15N) approach - McCallister, S. L.; Bauer, J. E.; Cherrier, J. C.; Ducklow, H. W. (Limnology and Oceanography, 2004)
id: 1153

Backbarrier sedimentary records of intense hurricane landfalls in the northeastern United States - Donnelly, J. P.; Iii, Webb T. (Hurricanes and Typhoons: Past, Present, and Potential, 2004)
id: 500

Chronology of sediment deposition in Upper Klamath Lake, Oregon - Colman, S. M.; Bradbury, J. P.; McGeehin, J. P.; Holmes, C. W.; Sarna-Wojcicki, A. M.; Edgington, D. (Journal of Paleolimnology, 2004)
A combination of tephrochronology and 14C, 210Pb, and 137Cs measurements provides a robust chronology for sedimentation in Upper Klamath Lake during the last 45 000 years. Mixing of surficial sediments and possible mobility of the radio-isotopes limit the usefulness of the 137Cs and 210Pb data, but 210Pb profiles provide reasonable average sediment accumulation rates for the last 100–150 years. Radiocarbon ages near the top of the core are somewhat erratic and are too old, probably as a result of detrital organic carbon, which may have become a more common component in recent times as surrounding marshes were drained. Below the tops of the cores, radiocarbon ages in the center of the basin appear to be about 400 years too old, while those on the margin appear to be accurate, based on comparisons with tephra layers of known age.Taken together, the data can be combined into reasonable age models for each site. Sediments have accumulated at site K1, near the center of the basin, about 2 times faster than at site CM2, on the margin of the lake. The rates are about 0.10 and 0.05 cm/yr, respectively. The chronological data also indicate that accumulation rates were slower during the early to middle Holocene than during the late Holocene, consistent with increasing wetness in the late Holocene.
id: 182

The CO2-He-Ar-H2O systematics of the Manus back-arc basin: Resolving source composition from degassing and contamination effects - Shaw, A. M.; Hilton, D. R.; Macpherson, C. G.; Sinton, J. M. (Geochimica Et Cosmochimica Acta, 2004)
We report new stepped heating He, Ar, CO2 and water data on a petrogenetically diverse suite of lavas from the Manus back-arc basin, where a plume component has previously been identified. The aim of this study is to evaluate the superimposed effects of degassing and contamination in order to identify mantle source characteristics. CO2 abundances and carbon isotopes in both the vesicle ([CO2] up to 180ppm; delta(13)C as low as -33.6 parts per thousand) and glass ([CO2] up to 270ppm; delta(13)C as low as -34.3parts per thousand) phases reveal that samples have been modified by varying degrees of degassing. High water concentration samples (back-arc basin basalts (BABB) and arc type samples) show the highest degrees of degassing (i.e. lower delta(13)C values and lower CO2 contents). The results are modelled for both the glass and vesicle phases using batch and fractional degassing models. Parental melt compositions can be constrained to show the following CO2 concentration trend: are-type > BABB s.r. (southern rift) > MORB-2, E-MORB, X-BABB (extreme BABB), BABB > MORB-1 and MORB-smt. He-4/Ar-40* ratios of samples (14.6-1100) are consistent with residual volatiles from a degassed source. Variations in CO2/(3) He values are likely due to degassing, followed by contamination from a crustal source (either the subducting Solomon Sea Plate or the pre-existing crust through which the lavas erupt), as evidenced by high K2O/TiO2 ratios and low delta(13)C. The CO2/(3) He of the Manus plume is best estimated by the MORB-smt and MORB-1 samples at 3.1 +/- 0.6 X 10(9). This value is similar to previous estimates of plume CO2/(3) He values, which are either equal to or slightly greater than the upper mantle average of 2 X 10(9). Copyright (C) 2004 Elsevier Ltd.
813fdTimes Cited:30Cited References Count:76

Collapse and rapid resumption of Atlantic meridional circulation linked to deglacial climate changes - McManus, J. F.; Francois, R.; Gherardi, J. M.; Keigwin, L. D.; Brown-Leger, S. (Nature, 2004)
The Atlantic meridional overturning circulation is widely believed to affect climate. Changes in ocean circulation have been inferred from records of the deep water chemical composition derived from sedimentary nutrient proxies, but their impact on climate is difficult to assess because such reconstructions provide insufficient constraints on the rate of overturning. Here we report measurements of 231Pa/230Th, a kinematic proxy for the meridional overturning circulation, in a sediment core from the subtropical North Atlantic Ocean. We find that the meridional overturning was nearly, or completely, eliminated during the coldest deglacial interval in the North Atlantic region, beginning with the catastrophic iceberg discharge Heinrich event H1, 17,500 yr ago, and declined sharply but briefly into the Younger Dryas cold event, about 12,700 yr ago. Following these cold events, the 231Pa/230Th record indicates that rapid accelerations of the meridional overturning circulation were concurrent with the two strongest regional warming events during deglaciation. These results confirm the significance of variations in the rate of the Atlantic meridional overturning circulation for abrupt climate changes.
McManus, J FFrancois, RGherardi, J-MKeigwin, L DBrown-Leger, SengResearch Support, Non-U.S. Gov'tResearch Support, U.S. Gov't, Non-P.H.S.England2004/04/23 05:00Nature. 2004 Apr 22;428(6985):834-7.

Enhanced marine productivity off western North America during warm climate intervals of the past 52 kyr - Ortiz, J. D.; O'Connell, S.; DelViscio, J.; Dean, W. E.; Carriquiry, J.; Marchitto, T. M.; Zheng, Y.; van Geen, A. (Geology, 2004)
id: 603

The eutrophication of Long Island Sound, abstract - Varekamp, J. C.; Lugolobi, F.; Thomas, E.; Mecray, E.; Buchholtz ten Brink, M. R. (EOS Trans. AGU, 2004)
id: 740

Evaluation of ocean carbon cycle models with data-based metrics - Matsumoto, K.; Sarmiento, J. L.; Key, R. M.; Aumont, O.; Bullister, J. L.; Caldeira, K.; Campin, J. M.; Doney, S. C.; Drange, H.; Dutay, J. C.; Follows, M.; Gao, Y.; et al. (Geophysical Research Letters, 2004)
New radiocarbon and chlorofluorocarbon-11 data from the World Ocean Circulation Experiment are used to assess a suite of 19 ocean carbon cycle models. We use the distributions and inventories of these tracers as quantitative metrics of model skill and find that only about a quarter of the suite is consistent with the new data-based metrics. This should serve as a warning bell to the larger community that not all is well with current generation of ocean carbon cycle models. At the same time, this highlights the danger in simply using the available models to represent the state-of-the-art modeling without considering the credibility of each model.
811adTimes Cited:110 Cited References Count:17
Keywords: anthropogenic co2; pacific-ocean; radiocarbon

Glacial intermediate water ventilation in the northwestern Pacific based on AMS radiocarbon dating - Ohkushi, K.; Uchida, M.; Ahagon, N.; Mishima, T.; Kanematsu, T. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2004)
C-14 ages of benthic foraminifera and planktonic foraminifera in sediment core PC4 (41degrees07.10'N, 142degrees24.17'E) collected from the northwestern Pacific were measured by accelerator mass spectrometry. The purpose of this study was to investigate the changes in intermediate water ventilation in the northwestern Pacific during the last glacial period. We used age differences between benthic foraminifera and planktonic foraminifera from the same sediment horizons to estimate the ventilation time of intermediate water. Planktonic C-14 ages show that the core recorded paleoenvironmental changes during the last 35 kyr. Glacial benthic-planktonic age differences were smaller in the early deglacial period (15000-17000 cal yr BP) than in the period (19000-30000 cal yr BP) before and during the last glacial maximum. The results at intermediate depths are consistent with those from a Pacific deep-water site. (C) 2004 Elsevier B.V. All rights reserved.
852jtTimes Cited:7Cited References Count:13

A global ocean carbon climatology: Results from global data analysis project (GLODAP) - Kay, R. M.; Kozyr, A.; Sabine, C. L.; Lee, K.; Wanninkhof, R.; Bullister, J. L.; Feely, R. A.; Millero, F. J.; Mordy, C.; Peng, T. H. (Global Biogeochemical Cycles, 2004)
id: 527

H2-rich fluids from serpentinization: geochemical and biotic implications - Sleep, N. H.; Meibom, A.; Fridriksson, T.; Coleman, R. G.; Bird, D. K. (Proc Natl Acad Sci U S A, 2004)
Metamorphic hydration and oxidation of ultramafic rocks produces serpentinites, composed of serpentine group minerals and varying amounts of brucite, magnetite, and/or FeNi alloys. These minerals buffer metamorphic fluids to extremely reducing conditions that are capable of producing hydrogen gas. Awaruite, FeNi3, forms early in this process when the serpentinite minerals are Fe-rich. Olivine with the current mantle Fe/Mg ratio was oxidized during serpentinization after the Moon-forming impact. This process formed some of the ferric iron in the Earth's mantle. For the rest of Earth's history, serpentinites covered only a small fraction of the Earth's surface but were an important prebiotic and biotic environment. Extant methanogens react H2 with CO2 to form methane. This is a likely habitable environment on large silicate planets. The catalytic properties of FeNi3 allow complex organic compounds to form within serpentinite and, when mixed with atmospherically produced complex organic matter and waters that circulated through basalts, constitutes an attractive prebiotic substrate. Conversely, inorganic catalysis of methane by FeNi3 competes with nascent and extant life.
Sleep, N HMeibom, AFridriksson, ThColeman, R GBird, D KengResearch Support, U.S. Gov't, Non-P.H.S.2004/08/25 05:00Proc Natl Acad Sci U S A. 2004 Aug 31;101(35):12818-23. Epub 2004 Aug 23.

Holocene development of the Yellow River's subaqueous delta, North Yellow Sea - Liu, J. P.; Milliman, J. D.; Gao, S.; Cheng, P. (Marine Geology, 2004)
id: 650

A late Pleistocene-Holocene noble gas paleotemperature record in southern Michigan - Ma, L.; Castro, M. C.; Hall, C. M. (Geophysical Research Letters, 2004)
Noble gas temperatures (NGTs) and C-14 derived ages in groundwaters of the Michigan Basin reveal a ground temperature of similar to1degreesC toward the end of the Last Glacial Maximum (LGM) suggesting that groundwater recharge occurred under the Laurentide Ice Sheet (LIS) cover. In addition to the general warming observed since the LGM, the NGT record indicates an abrupt warming event between similar to12.8 and 11.1 kyrs BP, correlative to the Bolling-Allerod (BOA) warm phases. Ice-sheet-linked changes in freshwater delivery to the North Atlantic, together with changes in the North Atlantic Deep Water (NADW) circulation are possible causes of such abrupt climate shifts in northeastern US. Pleistocene waters yielding the lowest NGTs have the highest delta(18)O and deltaD values, suggesting an atmospheric circulation pattern distinct from today, with a stronger moisture component from the Gulf of Mexico, possibly due to the presence of the LIS which weakened the Pacific westerly flow.
881pcTimes Cited:31Cited References Count:24

Late Quaternary deposition in the Inner Basins of the California Continental Borderland: Part A. Santa Monica Basin - Normark, W. R.; McGann, M. (U. S. Geological Survey Scientific Investigations Report 2004, 2004)
id: 417

Natural Radiocarbon Distribution in the Deep Ocean - Matsumoto, Katsumi; Key, Robert M. (Global Environmental Change in the Ocean and on Land, 2004)

Natural radiocarbon distribution in the deep ocean - Matsumoto, K.; Key, R. M. (Global Environmental Change in the Ocean and on Land, 2004)
id: 1050

Oceanic ventilation and biogeochemical cycling: Understanding the physical mechanisms that produce realistic distributions of tracers and productivity - Gnanadesikan, A.; Dunne, J. P.; Key, R. M.; Matsumoto, K.; Sarmiento, J. L.; Slater, R. D.; Swathi, P. S. (Global Biogeochemical Cycles, 2004)
[1] Differing models of the ocean circulation support different rates of ventilation, which in turn produce different distributions of radiocarbon, oxygen, and export production. We examine these fields within a suite of general circulation models run to examine the sensitivity of the circulation to the parameterization of subgridscale mixing and surface forcing. We find that different models can explain relatively high fractions of the spatial variance in some fields such as radiocarbon, and that newer estimates of the rate of biological cycling are in better agreement with the models than previously published estimates. We consider how different models achieve such agreement and show that they can accomplish this in different ways. For example, models with high vertical diffusion move young surface waters into the Southern Ocean, while models with high winds move more young North Atlantic water into this region. The dependence on parameter values is not simple. Changes in the vertical diffusion coefficient, for example, can produce major changes in advective fluxes. In the coarse-resolution models studied here, lateral diffusion plays a major role in the tracer budget of the deep ocean, a somewhat worrisome fact as it is poorly constrained both observationally and theoretically.
867xpTimes Cited:66 Cited References Count:42
Keywords: Biogeochemical cycles; bottom water formation; circulation models; diffusion; particle export; pycnocline; sensitivity; Temperature; vertical exchange; weddell sea; World Ocean

Organic carbon accumulation in the South Atlantic Ocean: 1st modern, mid-Holocene and Last Glacial distribution - Mollenhauer, Gesine; Schneider, Ralph R.; Jennerjahn, Tim; Muller, Peter J.; Wefer, Gerold (Global and Planetary Change, 2004)
id: 1704

Paleoclimate. A better radiocarbon clock - Bard, E.; Rostek, F.; Menot-Combes, G. (Science, 2004)
id: 974; Bard, Edouard Rostek, Frauke Menot-Combes, Guillemette New York, N.Y. Science. 2004 Jan 9;303(5655):178-9.

Plans for Expanded 14C Analyses at the NOSAMS Facility--a status and progress report. 9th International Conference on Accelerator Mass Spectrometry, Nagoya, Japan, 9/2002 - von Reden, K.; Donoghue, J.; Elder, K.; Gagnon, A.; Gerlach, D.; Griffin, V. S.; Healy, R.; Long, P.; McNichol, A. P.; Percy, D.; Roberts, M. L.; Schneider, R. J.; et al. (Nuclear Instruments and Methods in Physics Research, 2004)
id: 1810

Present status of radiocarbon calibration and comparison records based on Polynesian corals and Iberian Margin sediments - Bard, E.; Menot-Combes, G.; Rostek, F. (Radiocarbon, 2004)
In this paper, we present updated information and results of the radiocarbon records based on Polynesian corals and on Iberian Margin planktonic foraminifera. The latter record was first published by Bard et al. (2004a,b), with the subsequent addition of some data by Shackleton et al. (2004). These data sets are compared with the IntCal98 record (Stuiver et al. 1998) and with data sets based on other archives, such as varves of Lake Suigetsu (Kitagawa and van der Plicht 1998, 2000), speleothems from the Bahamas (Beck et al. 2001), and Cariaco sediments (Hughen et al. 2004). Up to 26,000 cal BP, the Iberian Margin data agree within the errors of the other records. By contrast, in the interval between 33,000 and 41,000 cal BP, the Iberian Margin record runs between the Lake Suigetsu and Bahamian speleothem data sets, but it agrees with the few ImCal98 coral data and the Cariaco record.
956zfTimes Cited:30Cited References Count:33

Quartz content and the quartz-to-plagioclase ratio determined by X-ray diffraction: a proxy for ice rafting in the northern North Atlantic? - Moros, M.; McManus, J. F.; Rasmussen, T.; Kuijpers, A.; Dokken, T.; Snowball, I.; Jansen, E.; Neilsen, T. (Earth and Planetary Science Letters, 2004)
id: 713

Quaternary sea level history of the United States - Muhs, D. R.; Wehmiller, J. F.; Simmons, K. R.; York, L. L. (The Quaternary period in the United States, Developments in Quaternary science, 2004)
id: 706

Radiocarbon ages of marine bimarkers and co-occurring foraminifera: evidence for differential particle transport on continental margins, Poster - Mollenhauer, Gesine; Eglinton, Timothy I.; Hayes, John M.; Kienast, Markus; Lamy, Frank; Meggers, Helge; Schneider, Ralph R. (Eighth International Conference on Palaeoceanography, 2004)
id: 549

Radiocarbon apportionment of fossil versus biofuel combustion sources of polycyclic aromatic hydrocarbons in the Stockholm metropolitan area - Mandalakis, M.; Gustafsson, O.; Reddy, C. M.; Xu, L. (Environ Sci Technol, 2004)
Source-diagnostic markers and the isotopic composition of polycyclic aromatic hydrocarbons (PAHs) were examined in surface sediments from the greater Stockholm waterways to deduce the contribution from biomass sources to the environmental PAH load. The summed concentration of 20 PAHs ranged from 0.8 to 45.1 microg/g (dry weight) and exhibited a steep decline with increasing distance from the city center evidencing that sources within the metropolitan area of Stockholm dominate its PAH burden. Several diagnostic PAH ratios indicated an overwhelming predominance of pyrogenic sources over the petrogenic ones, while retene and 1,7-dimethylphenanthrene were unable to correctly evaluate the contribution from biomass combustion. The stable carbon isotope composition (delta13C) of individual PAHs ranged from -24.8 to -27.0% but also was proved inefficient to discriminate between different types of fuels due to the overlapping signals in various sources. The delta14C values of PAHs ranged between -550.4 and -934.1%, indicating a clear predominance of fossil fuel sources. By using an isotopic mass balance approach, we estimated that on average 17+/-9% of PAHs derived from biomass combustion. This radiocarbon apportionment, in conjunction with detailed energy statistics for the Stockholm region, revealed that the ambient PAH burden is roughly similar, per unit energy produced, from fossil fuels and biofuels. Societies' shifting energy policies toward a larger reliance on biofuels may thus not lead to further deterioration of air quality and respiratory ailments for the urban population.
Mandalakis, ManolisGustafsson, Orjan Reddy, Christopher M Xu, Li eng Comparative Study Research Support, Non-U.S. Gov't Research Support, U.S. Gov't, Non-P.H.S. 2004/11/17 09:00 Environ Sci Technol. 2004 Oct 15;38(20):5344-9.
Keywords: *Bioelectric Energy Sources; *Fossil Fuels; Biomass; Carbon Radioisotopes; Cities; Environmental Monitoring; Fresh Water; Geologic Sediments/*analysis; Polycyclic Aromatic Hydrocarbons/*analysis/isolation & purification; Sweden; Water Pollutants, Chemical/*analysis/isolation & purification

Radiocarbon calibration beyond 20,000 B.P. by means of planktonic foraminifera of the Iberian Margin - Bard, E.; Rostek, F.; Menot-Combes, G. (Quaternary Research, 2004)
We present a new set of 14C ages obtained by accelerator mass spectrometry (AMS) on planktonic foraminifera from a deep-sea core collected off the Iberian Margin (MD952042). This site, at 37°N, is distant from the high-latitude zones where 14C reservoir age is large and variable. Many independent proxies — alkenones, magnetic susceptibility, ice-rafted debris, foraminifera stable isotopes, abundances of foraminifera, pollen, and dinoflagellates — show abrupt changes correlative with Dansgaard-Oeschger and Heinrich events of the last glacial period. The good stratigraphic agreement of all proxies — from the fine to the coarse-size fractions — indicates that the foraminifera 14C ages are representative of the different sediment fractions. To obtain reliable 14C ages of foraminifera beyond 20,000 14C yr B.P., we leached the shells prior to carbonate hydrolysis and subsequent analysis. For a calendar age scale, we matched the Iberian Margin U37K′ profile with that of Greenland Summit δ18O. Both are proxies for temperature, which in models varies synchronously in the two areas. The match creates no spurious jumps in sedimentation rate and requires only a limited number of tie points. Except for ages older than 40,000 14C yr B.P., Greenland's GISP2 and GRIP records yield similar calendars. The 14C and imported calendar ages of the Iberian Margin record are then compared to data — from lacustrine annual varves and from corals and speleothems dated by U–Th — previously used to extend the calibration beyond 20,000 14C yr B.P. The new record follows a smooth pattern between 23,000 and 50,000 cal yr B.P. We find good agreement with the previous data sets between 23,000 and 31,000 cal yr B.P. In the interval between 33,000 and 41,000 cal yr B.P., for which previous records disagree by up to 5000 cal yr, the Iberian Margin record closely follows the polynomial curve that was previously defined by an interpolation of the coral ages and runs between the Lake Suigetsu and the Bahamian speleothem data sets.
id: 401
Keywords: Dansgaard-Oeschger events; Heinrich events; Laschamp magnetic excursion; Last glacial cycle; North Atlantic; Radiocarbon calibration

Radiocarbon content of alkenones, foraminifera and bulk OC in oxic and anoxic sediments from the California Borderland Basins, Poster - Mollenhauer, Gesine; Eglinton, Timothy I. (Gordon Research Conference Organic Geochemistry, 2004)
id: 550

Reconsidering Melt-water Pulses 1A and 1B: Global impacts of rapid sea-level rise - Liu, J. P.; Milliman, J. D. (Journal of Ocean University of China, 2004)
id: 649

Spatial variations in a condensed interval between estuarine and open-marine settings: Holocene Hudson River estuary and adjacent continental shelf - McHugh, C. M. G.; Pekar, S. F.; Christie-Blick, N.; Ryan, W. B. F.; Carbotte, S.; Bell, R. (Geology, 2004)
An interval of stratigraphic condensation extending for 300 km from the fluvially dominated Hudson River estuary to the adjacent continental shelf reveals stratal relationships within an unconformity-rellated depositional sequence that are commonly difficult to resolve in seismic reflection profiles and outcrop. High-resolution side-scan sonar and bathymetry, more than 100 sediment cores similar to2 m long, and radioisotope (C-14, Cs-137) age control show that much of the valley was filled by ca. 3 to 1 ka. The present rate of sediment accumulation averages 1 mm/yr, corresponding with a sea-level rise of similar to1.2 mm/yr relative to local bedrock. Condensation is manifested today by sedimentary bypass in most parts of the estuary and by the trapping of available sediment (1.2-5.6 x 10(5) t/yr [metric tons]) along narrow reaches and primarily in the vicinity of the estuarine turbidity maximum, a part of the estuary located upstream of the salinity intrusion similar to25 km from the mouth (3.0 x 10(5) t/yr). Shelf condensation is due to sediment starvation. The condensed interval merges updip with a nascent sequence boundary as the estuary reaches its final filling phase and downdip with the sequence boundary that developed at the Last Glacial Maximum. Delta progradation may take place as available shelf accommodation is filled, but such sediments are expected to be removed once sea level begins to fall. This sedimentation pattern, in which a condensed interval merges with different sequence boundaries, is consistent with the stratigraphic record of the Atlantic margin back to the Paleogene and may be typical of sediment-starved margins.
772lcTimes Cited:10Cited References Count:30

Stable carbon isotope ratios in lake and swamp sediments as a proxy for prehistoric forest clearance and crop cultivation in the Neotropics - Lane, C. S.; Horn, S. P.; Mora, C. I. (Journal of Paleolimnology, 2004)
Close correspondence between stable carbon isotope ratios (delta(13)C), pollen, and charcoal profiles in sediment cores from Laguna Zoncho and Machita swamp, Costa Rica, shows that prehistoric forest clearance and crop cultivation can be detected in the stable carbon isotope ratios of total organic carbon (delta(13)C(TOC)). Analyses of delta(13)C(TOC) complement evidence from pollen, charcoal, and phytoliths and provide a proxy that is sensitive to the intensity and/or proximity to core sites of prehistoric forest clearance and agriculture in watersheds. Stable carbon isotope analyses are particularly useful in situations in which other evidence of forest clearance and agriculture is limited.
881ycTimes Cited:30Cited References Count:36

Vegetation and climate changes around the Lama Lake, Taymyr Peninsula, Russia during the Late Pleistocene and Holocene - Andreev, A.A.; Tarasov, P.E.; Klimanov, V.A.; Melles, M.; Lisitsyna, O.M.; Hubberten, H.-W. (HIgh resolution lake sediment records in climate and Environment variability studies:European lake drilling program, 2004)
A continuous lacustrine sequence from the western part of Lama Lake (69°32′N, 90°12′E), complemented by a peat sequence from the lake catchment provides the first detailed environmental reconstruction for the Late Glacial and Holocene on the Taymyr Peninsula. Scarce steppe-like communities with Artemisia, Poaceae, and Cyperaceae dominated during the Late Glacial. Tundra-like communities with Betula nana, Dryas, and Salix grew on more mesic sites. There are distinct climatic signals, which may be correlated with the Bølling and Allerød warming and Middle and Younger Dryas cooling. The Late Glacial/Preboreal transition, at about 10,000 14C yr BP, was characterized by changes from predominantly open herb communities to shrub tundra ones. Larch forest might have been established as early as 9700–9600 14C yr BP, whilst shrub alder came to the area ca 9500–9400 14C yr BP, and spruce did not reach area before ca 9200 14C yr BP. Spruce-larch forests with shrub alder and tree birch dominated the vegetation around the Lama Lake from ca 9000 14C yr BP. Dwarf birch communities were also broadly distributed. The role of spruce in the forest gradually decreased after 4500 14C yr BP. The vegetation cover in the Lama Lake area became similar to the modern larch-spruce forest ca 2500 14C yr BP. A pollen-based biome reconstruction supports a quantitative interpretation of the pollen spectra. Climate reconstructions obtained with information-statistical and plan-functional-type methods show very similar trends in reconstructed July temperature since ca 12,300 14C yr BP, while precipitation anomalies are less coherent, especially during the Late Glacial–Holocene transition.

14C activity and global carbon cycle changes over the past 50,000 years - Hughen, K. A.; Lehman, S. J.; Southon, J.; Overpeck, J. T.; Marchal, O.; Herring, C.; Turnbull, J. (Abstracts, 18th International Radiocarbon Conf., 2003)
id: 1079

Alkenone radiocarbon stratigraphy at high resolution continental margin sites - Mollenhauer, Gesine; Eglinton, Timothy I.; Freudenthal, Tim; Lamy, Frank (EGS-AGU-EUG Joint Assembly, 2003)
id: 1071

Analog for Holocene and future Climate? - McManus, J. F.; Oppo, D. W.; Cullen, J. L.; Healey, S. L. (Geophysical Monograph 137, Earth's Climate and Orbital Eccentricity: The Marine Isotope State 11 Questions, 2003)
id: 1166

Asynchronous alkenone and foraminifera records from the Benguela Upwelling System - Mollenhauer, Gesine; Eglinton, Timothy I.; Ohkouchi, Naohiko; Schneider, Ralph R.; Muller, Peter J.; Grootes, Pieter M.; Rullkotter, Jurgen (Geochimica et Cosmochimica Acta, 2003)
id: 1067

Calcium carbonate budget in the Atlantic Ocean based on water column inorganic carbon chemistry - Chung, S. N.; Lee, K.; Feely, R. A.; Sabine, C. L.; Millero, F. J.; Wanninkhof, R.; Bullister, J. L.; Key, R. M.; Peng, T. H. (Global Biogeochemical Cycles, 2003)
[1] Recent independent lines of evidence suggest that the dissolution of calcium carbonate (CaCO3) particles is substantial in the upper ocean above the calcite 100% saturation horizon. This shallow-water dissolution of carbonate particles is in contrast with the current paradigm of the conservative nature of pelagic CaCO3 at shallow water depths. Here we use more than 20,000 sets of carbon measurements in conjunction with CFC and C-14 data from the WOCE/JGOFS/OACES global CO2 survey to estimate in situ dissolution rates of CaCO3 in the Atlantic Ocean. A dissolution rate is estimated from changes in alkalinity as a parcel of water ages along an isopycnal surface. The in situ CaCO3 dissolution increases rapidly at the aragonite 100% saturation horizon. Estimated dissolution rates north of 40degreesN are generally higher than the rates to the south, which is partly attributable to the production of exported CaCO3 being higher in the North Atlantic than in the South Atlantic. As more CaCO3 particles move down the water column, more particles are available for in situ dissolution. The total water column CaCO3 dissolution rate in the Atlantic Ocean is determined on an annual basis by integrating estimated dissolution rates throughout the entire water column and correcting for alkalinity input of approximately 5.6 x 10(12) mol C yr(-1) from CaCO3-rich sediments. The resulting water column dissolution rate of CaCO3 for the Atlantic Ocean is approximately 11.1 x 10(12) mol C yr(-1). This corresponds to about 31% of a recent estimate (35.8 x 10(12) mol C yr(-1)) of net CaCO3 production by Lee [2001] for the same area. Our calculation using a large amount of high-quality water column alkalinity data provides the first basin-scale estimate of the CaCO3 budget for the Atlantic Ocean.
732egTimes Cited:44 Cited References Count:73
Keywords: alkalinity; anthropogenic co2; caco3 dissolution; calcium carbonate budget; chemical lysocline; Deep-sea; dioxide system; dissociation-constants; dissolution kinetics; dissolution of calcium carbonate; eastern north-atlantic; ocean carbon cycle; organic-carbon; pacific-ocean; saturation state of seawater

Carbon cycling in Long Island Sound over the last 1000 years - Lugolobi, F.; Varekamp, J. C.; Thomas, E.; Buchholtz ten Brink, M. L.; Mecray, E. (AGU, Fall meeting, 2003)
id: 1179

Changes in the 13C/12C of dissolved inorganic carbon in the ocean as a tracer of anthropogenic CO2 uptake - Quay, P.; Sonnerup, R.; Westby, T.; Stutsman, J.; McNichol, A. (Global Biogeochemical Cycles, 2003)
id: 1546

Changes of the 13C/12C of dissolved inorganic carbon in the ocean as a tracer of anthropogenic C)2 uptake - Quay, P. D.; Sonnerup, T.; Westby, J.; Stutsman, J.; McNichol, A. P. (Global Biogeochemical Cycles, 2003)
id: 1689

Compound specific radiocarbon dating of alkenones: methodological considerations and applications in paleoceanography - Mollenhauer, Gesine; Eglinton, Timothy I.; Schneider, Ralph R.; Meggers, Helge; Lamy, Frank; Ohkouchi, Nao; Hayes, John M. (18th International Radiocarbon Conference, 2003)
id: 1070

Evolution of Sedimentary Rocks - Veizer, J.; Mackenzie, F. T. (Treatise on Geochemistry, 2003)
id: 1604

Fossil Sources of Ambient Aerosol Carbon Based on 14C Measurements - Tanner, R. L.; Parker, W. J.; McNichol, A. P. (Aerosol Science and Technology, 2003)
id: 1690

La colonisation et les fortifications de Rapa - Kennett, D. J.; Anderson, A. J.; Prebble, M.; Conte, E. (Bilan de la recherche archeologique en Polynesie francaise, 2003)
id: 471

Map and data for Quaternary faults and folds in Washington State - Lidke, D. J.; Johnson, S. Y.; McCory, P. A.; Personius, S. F.; Nelson, A. R.; Dart, R. L.; Bradley, L. A.; Haller, K. M.; Machette, M. N. (Geological Survey Open-File Report, 2003)
id: 997

Mercury contamination chronologies from Connecticut wetlands and Long Island Sound sediments - Varekamp, J. C.; Kreulen, B.; ten Brink, M. R. B.; Mecray, E. L. (Environmental Geology, 2003)
Sediment cores were used to investigate the mercury deposition histories of Connecticut and Long Island Sound. Most cores show background (pre-1800s) concentrations (50-100 ppb Hg) below 30-50 cm depth, strong enrichments up to 500 ppb Hg in the core tops, with lower Hg concentrations in the surface sediments (200-300 ppb Hg). A sediment core from the Housatonic River has peak levels of 1,500 ppb Hg, indicating the presence of a Hg point source in this watershed. The Hg records were translated into Hg contamination chronologies through Pb-210 dating. The onset of Hg contamination occurred in similar to1840-1850 in eastern Connecticut, whereas in the Housatonic River the onset is dated at around 1820. The mercury accumulation profiles show periods of peak contamination at around 1900 and at 1950-1970. Peak Hg* (Hg* = Hg measured minus Hg background) accumulation rates in the salt marshes vary; dependent on the sediment character, between 8 and 44 ng Hg/cm(2) per year, whereas modern Hg* accumulation rates range from 4-17 ng Hg/cm(2) per year; time-averaged Hg* accumulation rates are 15 ng Hg/cm(2) per year. These Hg* accumulation rates in sediments are higher than the observed Hg atmospheric deposition rates (about 1-2 ng Hg/cm(2) per year), indicating that contaminant Hg from the watershed is focused into the coastal zone. The Long Island Sound cores show similar Hg profiles as the marsh cores, but time-averaged Hg* accumulation rates are higher than in the marshes (26 ng Hg/cm(2) a year) because of-the different sediment characteristics. In-situ atmospheric deposition of Hg in the marshes and in Long Island Sound is only a minor component of the total Hg budget. The 1900 peak of Hg contamination is most likely related to climatic factors (the wet period of the early 1900s) and the 1950-1970 peak was caused by strong anthropogenic Hg emissions at that time. Spatial trends in total Hg burdens in cores are largely related to sedimentary parameters (amount of clay) except for the high inventories of the Housatonic River, which are related to Hg releases from hat-making in the town of Danbury. Much of the contaminated sediment transport in the Housatonic River Basin occurs during floods; creating distinct layers of Hg-contaminated sediment in western Long Island Sound. The drop of about 40% in Hg accumulation rates between the 1960s and 1990s seems largely the result of reduced Hg emissions and to a much lesser extent of climatic factors.
643lmTimes Cited:22Cited References Count:45

Mid-depth circulation in the northwest Pacific during the last deglaciation: Evidence from foraminiferal radiocarbon ages - Ahagon, N.; Ohkushi, K.; Uchida, M.; Mishima, T. (Geophysical Research Letters, 2003)
Sediment cores (MR01-K03 PC4/PC5, 1366 m water depth) collected from off northern Japan were studied using coexisting planktonic and benthic foraminiferal radiocarbon measurements to reconstruct the history of mid-depth circulation in the northwest Pacific. Reconstructed ventilation ages indicate that, consistent with data from a previous radiocarbon study at a shallower site, there was significant variation in mid-depth circulation during the last deglaciation, especially in the Bolling-Allerod (13-15 ka) and Younger Dryas (11.5-13 ka) intervals. Our record indicates that the ventilation changes in the North Pacific were antiphase to those of the North Atlantic, suggesting that atmospheric moisture transport associated with the Asian Monsoon might have played a great role in millennium-scale ventilation changes in the North Pacific during the last deglaciation.
id: 405; 742FU Times Cited:19 Cited References Count:23

Palaeo-oceanography: Deepwater variability in the Holocene epoch - Oppo, D. W.; McManus, J. F.; Cullen, J. L. (Nature, 2003)
Oppo, Delia WMcManus, Jerry FCullen, James LengEngland2003/03/21 04:00Nature. 2003 Mar 20;422(6929):277.

Persistence of Gulf Stream separation during the Last Glacial Period: Implications for current separation theories - Matsumoto, K.; Lynch-Stieglitz, J. (Journal of Geophysical Research-Oceans, 2003)
[1] We present stable oxygen isotope ratio (delta(18)O) measurements on deep-dwelling planktonic foraminifera from the western margin of the North Atlantic in order to reconstruct the latitude at which the Gulf Stream separated from the western boundary of the Atlantic Ocean in the past. The modern separation latitude can be reconstructed within one degree from delta(18)O measured on the fossil shells of deep-dwelling planktonic foraminifera Globorotalia truncatulinoides from the Holocene sediments representing the past 10,000 years of mild climate conditions similar to today. The separation latitude is captured in a sharp delta(18)O gradient, which reflects the prominent hydrographic change across the boundary between the warm waters south and east of the Gulf Stream and the cold Slope Water to the north. The latitudinal delta(18)O profile from approximately the Last Glacial Maximum shows that the Gulf Stream separated from the coast near Cape Hatteras at almost the same latitude as it does today. We assess our finding in light of existing Gulf Stream separation theories and conclude that one of the theories, the wind-induced separation mechanism, is not consistent with our paleoceanographic reconstruction.
690nvTimes Cited:14 Cited References Count:56
Keywords: cape-hatteras; deep-ocean; gulf stream separation; Last glacial maximum; marine sediment cores; north-atlantic; Ocean circulation; oxygen isotope composition; oxygen isotopic composition; past 21,000 years; planktonic foraminifera; planktonic-foraminifera; SARGASSO SEA; western boundary current; western boundary undercurrent; wind-driven

A possible record of the Younger Dryas event in deep-sea sediments of the Southern Ocean (Pacific sector) - Morigi, C.; Capotondi, L.; Giglio, F.; Langone, L.; Brilli, M.; Turi, B.; Ravaioli, M. (Palaeogeography Palaeoclimatology Palaeoecology, 2003)
The oxygen isotope record combined with radiocarbon dating from two deep-sea cores collected along a transect between New Zealand and the Ross Sea are used to establish a reliable chronostratigraphy for the last 14 kyr. After an integrated geochemical and micropaleontological analysis in this timeframe we detected a cooling interval dated between 12.5 cal kyr BP and 11.4 cal kyr BP. The age control suggests that this event started 1.5 kyr after the onset of the Antarctic Cold Reversal previously observed in several Antarctic ice cores. We infer that the observed cool event corresponds to the Younger Dryas event defined in Northern Europe. This suggests that climate change recorded in this sector of the Southern Hemisphere still shows some synchronicity with Northern Hemisphere variations and that the decoupling of climate change between the two hemispheres likely occurred south of the Polar Front. (C) 2003 Elsevier B.V. All rights reserved.
723feTimes Cited:15Cited References Count:55

Post little ice age uplift at Juneau, Alaska reconstructed from dendrochronology and geomorphology - Motyka, R. J. (Quaternary Research, 2003)
id: 698

Radiocarbon ages of marine biomarkers and co-occurring foraminifera: evidence for differential particle transport on continental margins - Mollenhauer, Gesine; Eglinton, Timothy I.; Hayes, John M.; Keinast, Markus; Lamy, Frank; Meggers, Helge; Schneider, Ralph R. (AGU Fall Meeting 2003, 2003)
id: 1069

Sea-level changes and depositional environments in the Izmit Gulf, eastern Marmara Sea, during the late glacial-Holocene period - Cagatay, M. N.; Gorur, N.; Polonia, A.; Demirbag, E.; Sakinc, M.; Cormier, M. H.; Capotondi, L.; McHugh, C.; Emre, O.; Eris, K. (Marine Geology, 2003)
Offshore and onshore stratigraphic studies, together with high-resolution shallow seismic reflection profiling and multibeam bathymetric mapping, were carried out in the western and central part of the Izmit Gulf. These studies indicate that the Izmit Gulf was a lacustrine environment as part of the Marmara 'Lake' during the late glaciation and early deglaciation until similar to12 kyr BP, when the Marmara Basin was inundated by the Mediterranean waters. Correlation of C-14-dated onshore and offshore stratigraphic units in the Western Izmit Gulf indicates that generally coarse late glacial sediments overlie a marked erosional surface formed during the low water level of the Marmara 'Lake'. These coarse sediments are succeeded by 10.4-7 kyr BP old transgressive, and by late Holocene post-transgression mud units. The bathymetry and sub-bottom Chirp profiles clearly show that the paleoshoreline of the Gulf was located at -85 m, having been controlled by the bedrock sill depth of the Canakkale Strait. Another paleoshoreline observed at -65 m on the northern margin of the Western Izmit and Karamursel basins was probably formed during the Younger Dryas sea-level stillstand. The shelf areas during this time were colonized by bioherms, which were subsequently drowned and disappeared after a further rise of the sea level. The presence of a -65 in marine paleoshoreline in the Karamursel Basin indicates that the sill restricting this basin to the west was much deeper than its present -55 in level and was located further south. The Golcuk Basin, restricted by a -38 in sill to its west, was probably not flooded by marine waters until similar to9 kyr BP. (C) 2003 Published by Elsevier B.V.
749gpTimes Cited:52Cited References Count:30

The Antarctic ice sheet during the last glacial maximum and its subsequent retreat histroy: a review - Anderson, J. B.; Shipp, S. S.; Lowe, A. L.; Wellner, J. S.; Mosola, A. (Quaternary Science Reviews, 2002)
An emerging body of evidence from studies of the last glacial/interglacial cycle suggests that the East and West Antarctic ice sheets have not advanced and retreated in concert. The West Antarctic ice sheet advanced to the outer shelf in most regions during the Last Glacial Maximum (LGM). The retreat from the shelf commenced shortly after the LGM and continued into the late Holocene. The West Antarctic Ice Sheet in Ross and Amundsen seas slid across a deforming bed, at least during the final phases of extended glaciation. This implies that at this time the ice sheet had a low profile. Differences in the number and locations of grounding-zone wedges and smaller grounding zone features from trough to trough imply that individual West Antarctic Ice Sheet ice streams retreated episodically. Details concerning the expansion, retreat, and behavior of the East Antarctic Ice Sheet (EAIS) are more sparse. The picture emerging is that the EAIS did not expand to the continental shelf edge during the LGM; rather, it achieved a maximum extent of a mid-shelf position in some locations, while in other areas the ice terminus was situated near its present location. The timing of retreat along sectors within the EAIS appears diachronous, and in places occurred prior to the LGM. The Antarctic Peninsula shelf contained considerably more ice during the LGM than previously proposed. The results presented in this paper support more recent published ice-sheet models that call for greater contributions of melting ice from West Antarctica, including the Antarctic Peninsula, to the post-glacial rise in sea level.
id: 1126

Bomb dating and age determination of large pelagic sharks - Campana, S. E.; Natanson, L. J.; Myklevoll, S. (Canadian Journal of Fisheries and Aquatic Sciences, 2002)
Despite their notoriety and role as apex predators, the longevity of large pelagic sharks such as the porbeagle (Lamna nasus) and shortfin mako (Isurus oxyrinchus) is unknown. Vertebral growth bands provide an accurate indicator of age in young porbeagle, but age validation has never been reported for any large shark species past the age of sexual maturity. Here, we report the first application of bomb radiocarbon as an age validation method for long-lived sharks based on date-specific incorporation of radiocarbon into vertebral growth bands. Our results indicate that porbeagle vertebrae recorded and preserved a bomb radiocarbon pulse in growth bands formed during the 1960s. Through comparison of radiocarbon assays in young, known-age porbeagle collected in the 1960s with the corresponding growth bands in old porbeagle collected later, we confirm the validity of porbeagle vertebral growth band counts as accurate annual age indicators to an age of at least 26 years. The radiocarbon signatures of porbeagle vertebral growth bands appear to be temporally and metabolically stable and derived mainly from the radiocarbon content of their prey. Preliminary radiocarbon assays of shortfin mako vertebrae suggest that current methods for determining shortfin mako age are incorrect.
548ceTimes Cited:98Cited References Count:16

Bomb radiocarbon and anthropogenic CO2 in ocean biogeochemical models - Matsumoto, K.; Sarmiento, J.; Key, R.; Slater, C.; Sabine, C. (AGU/ASLO Conference, 2002)
id: 320

Challenges in radiocarbon dating organic carbon in opal-rich marine sediments - Zheng, Y.; Anderson, R. F.; Froelich, P. N.; Beck, W.; McNichol, A. P.; Guilderson, T. (Radiocarbon, 2002)
We explored the reliability of radiocarbon ages obtained on organic carbon phases in opal-rich Southern Ocean sediments. Paired biogenic carbonate and total organic carbon (TOC) C-14 analyses for three Southern Ocean cores showed that the TOC ages were systematically younger than the carbonate ages. Carbonate ages were consistent with oxygen isotopic and bio-stratigraphy, indicating error in TOC ages that could be explained by 5-24% of modern carbon contamination of TOC samples. Two possible sources of contamination are: 1) adsorption of atmospheric CO2 or volatile organic compounds to reactive opal surface sites, and 2) fixation of atmospheric CO2 by chemosynthetic bacteria during core storage. In an effort to reduce the modem carbon contamination, diatoms were separated from sediments, purified, and pre-oxidized by concentrated nitric and perchloric acids to permit dating of opal-intrinsic organic carbon (similar to0.1-0.3% by weight). C-14 ages of chemically pre-oxidized opal showed a significant amount of modem carbon contamination, from 11 to 32%, indicating adsorption from the atmosphere of modem carbon onto opal surfaces that were previously cleaned by acid oxidation. Several experiments designed to eliminate the modern C contamination were attempted, but so far we have not been able to obtain a radiocarbon age on C-14-dead Southern Ocean opal-rich sediments, either bulk TOC or purified diatom opal samples, as old as our procedural blank.
591keTimes Cited:13Cited References Count:28

Changes in the 13C/12C of dissolved inorganic carbon in the ocean as a tracer of anthropogenic CO2 uptake - Quay, P. D.; Sonnerup, R.; Westby, T.; Stutsman, J.; McNichol, A. P. (Global Biogeochemical Cycles, 2002)
id: 1715

Composition, age, provenance of organic matter in N. W. African dust over the Atlantic Ocean - Eglinton, T. I.; Eglinton, G.; Dupont, L.; Montlucon, D.; Sholkovitz, E.; Reddy, C. M. (Geochemistry, Geophysics, Geosystems G3, 2002)
id: 611

Converting AMS data to radiocarbon values: considerations and conventions - McNichol, A. P.; Jull, A. J. T.; Burr, G. S. (Radiocarbon, 2002)
id: 1818

A Critical Evaluation of Interlaboratory Data on Total, Elemental, and Isotopic Carbon in the Carbonaceous Particle Reference Material, NIST SRM 1649a - Currie, L. A.; Benner, B. A., Jr.; Kessler, J. D.; Klinedinst, D. B.; Klouda, G. A.; Marolf, J. V.; Slater, J. F.; Wise, S. A.; Cachier, H.; Cary, R.; Chow, J. C.; Watson, J.; et al. (J Res Natl Inst Stand Technol, 2002)
Because of increased interest in the marine and atmospheric sciences in elemental carbon (EC), or black carbon (BC) or soot carbon (SC), and because of the difficulties in analyzing or even defining this pervasive component of particulate carbon, it has become quite important to have appropriate reference materials for intercomparison and quality control. The NIST "urban dust" Standard Reference Material((R)) SRM 1649a is useful in this respect, in part because it comprises a considerable array of inorganic and organic species, and because it exhibits a large degree of ((14)C) isotopic heterogeneity, with biomass carbon source contributions ranging from about 2 % (essentially fossil aliphatic fraction) to about 32 % (polar fraction). A primary purpose of this report is to provide documentation for the new isotopic and chemical particulate carbon data for the most recent (31 Jan. 2001) SRM 1649a Certificate of Analysis. Supporting this is a critical review of underlying international intercomparison data and methodologies, provided by 18 teams of analytical experts from 11 institutions. Key results of the intercomparison are: (1) a new, Certified Value for total carbon (TC) in SRM 1649a; (2) (14)C Reference Values for total carbon and a number of organic species, including for the first time 8 individual PAHs; and (3) elemental carbon (EC) Information Values derived from 13 analytical methods applied to this component. Results for elemental carbon, which comprised a special focus of the intercomparison, were quite diverse, reflecting the confounding of methodological-matrix artifacts, and methods that tended to probe more or less refractory regions of this universal, but ill-defined product of incomplete combustion. Availability of both chemical and (14)C speciation data for SRM 1649a holds great promise for improved analytical insight through comparative analysis (e.g., fossil/biomass partition in EC compared to PAH), and through application of the principle of isotopic mass balance.
Currie, L ABenner, B A JrKessler, J DKlinedinst, D BKlouda, G AMarolf, J VSlater, J FWise, S ACachier, HCary, RChow, J CWatson, JDruffel, E R MMasiello, C AEglinton, T IPearson, AReddy, C MGustafsson, OQuinn, J GHartmann, P CHedges, J IPrentice, K MKirchstetter, T WNovakow, TPuxbaum, HSchmid, Heng2002/01/01 00:00J Res Natl Inst Stand Technol. 2002 Jun 1;107(3):279-98. doi: 10.6028/jres.107.022. Print 2002 May-Jun.

Data report: Australian Bight - Hine, A. C.; Brooks, G. R.; Mallinson, D.; Brunner, C. A.; James, N. P.; Feary, D. A.; Holbourn, A. E.; Drexler, T. M.; Howd, P. (Proc. ODP, Sci. Results, 2002)
id: 271

El Nino-like pattern in Ice Age Tropical Pacific Sea surace temperature - Koutavas, Athanasios; Lynch-Stieglitz, Jean; Marchitto, Thomas M.; Sachs, Julian P. (Science, 2002)
Sea surface temperatures (SSTs) in the cold tongue of the eastern equatorial Pacific exert powerful controls on global atmospheric circulation patterns. We examined climate variability in this region from the Last Glacial Maximum (LGM) to the present, using a SST record reconstructed from magnesium/calcium ratios in foraminifera from sea-floor sediments near the Galápagos Islands. Cold-tongue SST varied coherently with precession-induced changes in seasonality during the past 30,000 years. Observed LGM cooling of just 1.2°C implies a relaxation of tropical temperature gradients, weakened Hadley and Walker circulation, southward shift of the Intertropical Convergence Zone, and a persistent El Niño–like pattern in the tropical Pacific. This is contrasted with mid-Holocene cooling suggestive of a La Niña–like pattern with enhanced SST gradients and strengthened trade winds. Our results support a potent role for altered tropical Pacific SST gradients in global climate variations.
id: 644

Foragers of the Congo: the early settlement of the Ituri forest - Mercader, J. (Under the Canopy: The Archaeology of Tropical Rain Forests, 2002)
id: 1197

Fossil sources of PM2.5 aerosol carbon based on 14C measurements - Tanner, R. L.; Parkhurst, W. J.; McNichol, A. P. (PM2.5 and electric power generation: recent findings and implications, 2002)
id: 353

A high-resolution paleoclimate record spanning the past 25,000 years in southern East Africa - Johnson, T. C.; Brown, E. T.; McManus, J.; Barry, S.; Barker, P.; Gasse, F. (Science, 2002)
High-resolution profiles of the mass accumulation rate of biogenic silica and other geochemical proxies in two piston cores from northern Lake Malawi provide a climate signal for this part of tropical Africa spanning the past 25,000 years. The biogenic silica mass accumulation rate was low during the relatively dry late Pleistocene, when the river flux of silica to the lake was suppressed. Millennial-scale fluctuations, due to upwelling intensity, in the late Pleistocene climate of the Lake Malawi basin appear to have been closely linked to the Northern Hemisphere climate until 11 thousand years ago. Relatively cold conditions in the Northern Hemisphere coincided with more frequent north winds over the Malawi basin, perhaps resulting from a more southward migration of the Intertropical Convergence Zone.
Johnson, Thomas CBrown, Erik TMcManus, JamesBarry, SylviaBarker, PhilipGasse, FrancoisengResearch Support, U.S. Gov't, Non-P.H.S.2002/04/06 10:00Science. 2002 Apr 5;296(5565):113-32.

The historical record of water quality in Long Island Sound - Varekamp, J. C.; Thomas, E.; Mecray, E. L.; Buchholtz ten Brink, M. F. (Long Island Sound workshop, 2002)
id: 726

Holocene chronology of a continental shelf mudbelt off southwestern Africa - Meadows, M. E.; Rogers, J.; Lee-Throp, J. A.; Bateman, M. D.; Dingle, R. V. (The Holocene, 2002)
The Holocene lithostratigraphy and geochronology of sediments on an inner continental-shelf mudbelt off the west coast of southern Africa is presented. Based on a study of seven large gravity cores, numerous grab samples and two vibracores, two distinctive sections of the mudbelt have been identi” ed. The northern section is associated with the Orange River prodelta, and is dominated by laminated clay-rich sediments, while the southern section off Namaqualand is associated with more homogeneous muds. AMS radiocarbon ages of 31 samples from these cores are problematic due to the absence of expected modern material at the sedimentocean interface and numerous age reversals and inconsistencies in some of the cores. Possible mechanisms to explain the apparently anomalously old surface and near-surface samples are suggested. Most likely expla nations appear to lie in a combination of sediment-retrieval problems, the periodic loss of ” ne particulate organic carbon from within the water column, the sampling of possible relic sediments and, most likely of all, the incorporation into the sediments of 14C-depleted terrigenous organic matter. The age reversals are especially evident in the laminated sediments, and the entrainment of ‘old’ carbon from the terrestrial source of these sediments is offered as the most parsimonious explanation. Stable carbon isotope analyses and a single lumi nescence age support the contention that radiocarbon date inconsistencies are a consequence of terrestrial inputs of carbon which is non-contemporaneous with the actual time of sedimentation. In studies of offshore accumulations of terrigenous material, the marine-derived organic fraction may therefore prove a more reliable measure of radiocarbon chronology.
id: 220

Holocene moisture changes and fire frequency at Rio Rubens Bog, Southern Patagonia - Huber, U. M.; Markgraf, V. (Fire History, 2002)
id: 233

In situ calcium carbonate dissolution in the Pacific Ocean - Feely, R. A.; Sabine, C. L.; Lee, K.; Millero, F. J.; Lamb, M. F.; Greeley, D.; Bullister, J. L.; Key, R. M.; Peng, T. H.; Kozyr, A.; Ono, T.; Wong, C. S. (Global Biogeochemical Cycles, 2002)
Over the past several years researchers have been working to synthesize the WOCE/JGOFS global CO(2) survey data to better understand carbon cycling processes in the oceans. The Pacific Ocean data set has over 35,000 sample locations with at least two carbon parameters, oxygen, nutrients, CFC tracers, and hydrographic parameters. In this paper we estimate the in situ CaCO(3) dissolution rates in the Pacific Ocean water column. Calcium carbonate dissolution rates ranging from 0.01-1.1 mumol kg(-1) yr(-1) are observed in intermediate and deepwater beginning near the aragonite saturation horizon. In the North Pacific Intermediate Water between 400 and 800 m, CaCO(3) dissolution rates are more than 7 times faster than observed in middle and deep water depths (average=0.051 m mol kg(-1) yr(-1)). The total amount of CaCO(3) that is dissolved within the Pacific is determined by integrating excess alkalinity throughout the water column. The total inventory of CaCO(3) added by particle dissolution in the Pacific Ocean, north of 40degreesS, is 157 Pg C. This amounts to an average dissolution rate of approximately 0.31 Pg C yr(-1). This estimate is approximately 74% of the export production of CaCO(3) estimated for the Pacific Ocean. These estimates should be considered to be upper limits for in situ carbonate dissolution in the Pacific Ocean, since a portion of the alkalinity increase results from inputs from sediments.
649rqTimes Cited:86 Cited References Count:60
Keywords: anthropogenic co(2); anthropogenic co2; aragonite saturation; atmospheric carbon; caco(3) dissolution; calcite saturation; carbonate lysocline; chemical lysocline; coccolithophore emiliania-huxleyi; indian-ocean; north pacific; organic-matter; Pacific Ocean; panama basin; particulate matter

Influence of Vegetation Change on Watershed Hydrology: Implications for Paleoclimatic Interpretation of Lacustrine d180 Records - Rosenmeier, M. F.; Hodell, D. A.; Brenner, M.; Curtis, J. H.; Martin, J. B.; Anselmetti, F. S.; Ariztegui, D.; Guilderson, T. P. (Journal of Paleolimnology, 2002)
id: 1386

Kilimanjaro ice core records: evidence of holocene climate change in tropical Africa - Thompson, L. G.; Mosley-Thompson, E.; Davis, M. E.; Henderson, K. A.; Brecher, H. H.; Zagorodnov, V. S.; Mashiotta, T. A.; Lin, P. N.; Mikhalenko, V. N.; Hardy, D. R.; Beer, J. (Science, 2002)
Six ice cores from Kilimanjaro provide an approximately 11.7-thousand-year record of Holocene climate and environmental variability for eastern equatorial Africa, including three periods of abrupt climate change: approximately 8.3, approximately 5.2, and approximately 4 thousand years ago (ka). The latter is coincident with the "First Dark Age," the period of the greatest historically recorded drought in tropical Africa. Variable deposition of F- and Na+ during the African Humid Period suggests rapidly fluctuating lake levels between approximately 11.7 and 4 ka. Over the 20th century, the areal extent of Kilimanjaro's ice fields has decreased approximately 80%, and if current climatological conditions persist, the remaining ice fields are likely to disappear between 2015 and 2020.
Thompson, Lonnie GMosley-Thompson, EllenDavis, Mary EHenderson, Keith ABrecher, Henry HZagorodnov, Victor SMashiotta, Tracy ALin, Ping-NanMikhalenko, Vladimir NHardy, Douglas RBeer, Jurgeng2002/10/19 04:00Science. 2002 Oct 18;298(5593):589-93.

Los Cerritos: an early fishing-farming community on the Pacific Coast of Mexico - Kennett, D. J.; Voorhies, B.; McClure, S. B. (Antiquity, 2002)
id: 473

The Middle Stone Age occupation of Atlantic central Africa: new evidence from Equatorial Guinea and Cameroon - Mercader, J.; Marti, R. (Under the Canopy: The Archaeology of Tropical Rain Forests, 2002)
id: 1196

The nature of 'stone-lines' in the African Quaternary record: archaeological resolution at the rainforest site of Mosumu, Equatorial Guinea - Mercader, J.; Marti, R.; Martinez, J. L.; Brooks, A. (Quaternary International, 2002)
'Stone-lines' are widespread Quaternary features that appear in tropical and subtropical regions. They have a diverse nature and genesis, and are frequently associated with archaeological assemblages. However, archaeological deposition and 'stone-line' configuration may be unrelated geological events separated by thousands of years. The energetics involved in 'stone-line' formation, coarse and fine material translocation across space and in depth, and overall assemblage integrity vary from one site to another. This paper presents quantitative and spatial geoarchaeological data from the site of Mosumu, in the tropical rain forest of continental Equatorial Guinea. Mosumu yielded Middle and Later Stone Age assemblages dated to at least the last 30,000 years in a 'stone-line' context. Special attention to the study of vertical and horizontal variations of artifacts, sedimentary features, and taphonomic indicators allows analysis of the nature, meaning, and archeological resolution at this site. The results are placed in the wider debate over the meaning of 'stone-lines' in the African Quaternary record. (C) 2002 Elsevier Science Ltd and INQUA. All rights reserved.
536zcTimes Cited:15 Cited References Count:89
Keywords: Age; behavior; cameroon; congo; ituri; layers; origin; tools; vegetation

Noble gases and volatile recycling at subduction zones - Hilton, D. R.; Fischer, T. P.; Marty, B. (Noble Gases in Geochemistry and Cosmochemistry, 2002)
Bw12hTimes Cited:243Cited References Count:219Reviews in Mineralogy & Geochemistry

Organic carbon deposition on the North Carolina continental slope off Cape Hatteras (USA) - Thomas, C. J.; Blair, N. E.; Alperin, M. J.; DeMaster, D. J.; Jahnke, R. A.; Martens, C. S.; Mayer, L. (Deep-Sea Research Part Ii-Topical Studies in Oceanography, 2002)
The continental slope off Cape Hatteras, NC is a region of high sediment accumulation and organic matter deposition. Sediment accumulation rates range from 3 to 151 cm kyr(-1). Organic carbon deposition rates are 5-13 moles C m(-2) yr(-1), the highest reported for the slope off the eastern US. Burial efficiencies are 3-40%. The organic matter deposited is marine in origin and a mix of old and young particles. High organic carbon deposition rates support remineralization throughout the upper 2-3 m of sediment. Deep bioirrigation to depths of 60-100 cm within the seabed affects the biogeochemistry of the sediments by extending the zone of sulfate reduction and by steepening DIC porewater gradients through the non-local exchange of porewater. Stable and radiocarbon isotope mixing curves for porewater dissolved inorganic carbon (DIC) indicate that the dominant source of DIC accumulating in the upper 2-3 m of the seabed is of nearly uniform delta(13)C (-21.10parts per thousand) and Delta(14)C (-546parts per thousand.). (C) 2002 Elsevier Science Ltd. All rights reserved.
607kxTimes Cited:31 Cited References Count:77
Keywords: anaerobic methane oxidation; early diagenesis; margin; marine-sediments; MATTER; middle-atlantic-bight; sea-floor; shelf; south; waters

Plans for expanded 14C analyses at the NOSAMS facility - a status and progress report - von Reden, K. F.; Donoghue, J.; Elder, K.; Gagnon, A.; Gerlach, D.; Griffin, V.; Healy, R.; Long, P.; McNichol, A.; Percy, D.; Roberts, M. L.; Schneider, R. J.; et al. (International Conference on Accelerator Mass Spectrometry, 2002)
id: 1685

Pleistocene chronology of continental margin sedimentation: New insights into traditional models, New Jersey - McHugh, C. M. G.; Olson, H. C. (Marine Geology, 2002)
Commonly accepted models for the evolution of continental margins link sediment erosion, transport and deposition to eustasy. To test these models, we constructed an oxygen isotope record from 520 m of Pleistocene sediment recovered by the Ocean Drilling Program Leg 174A from the New Jersey continental slope. The delta(18)O record was calibrated to SPECMAP oxygen isotope time scale [Imbrie et al. (1984), in: Berger et al. (Eds.), Milankovitch and Climate, 269-305] with radiocarbon ages, nannoplankton biostratigraphy, magnetostratigraphy, and opal and calcium carbonate stratigraphy. Sixteen glacial/interglacial fluctuations of global ice volume have been recorded in the Pleistocene: oxygen isotope stages (OIS) 1 (partial), 2-4, 5 (partial) and 8 throughout 18. Contrary to predicted sedimentation models, a classification of mass-wasting deposits, based on variations in the styles of soft-sediment deformation and grain size, shows that: (1) mass-wasting is not restricted to glacial times but is present during both glacial and interglacial stages; (2) glacial stages are dominated by fine-grained sediments some of which were deposited by gravity flows; and (3) the transitions from glacial to interglacial stages are characterized by the deposition of coarse sands. The sedimentary record shows large-scale trends that do not fit the traditional models of higher glacial sedimentation rates since there is no consistent variation in sediment accumulation between glacial and interglacial stages. Instead there are longer-term sedimentation patterns. Uniform sedimentation rates of 62 cm/kyr characterize the early middle Pleistocene (OIS 12-18), followed by varying rates from low to very high for three consecutive time periods: OIS 11 to 9 (98-560 cm/kyr), OIS 8 (52-560 cm/kyr), and OIS 5 to 2 (37-353 cm/kyr). Each of these depositional units is contained within one seismic-stratigraphic sequence and bounded by sequence boundaries. Their deposition was influenced by the supply of sediment rather than eustasy. Sediment supply was modulated by: (1) the transition from the dominance of obliquity to that of eccentricity (OIS 18-12 to OIS 11-1); and (2) the proximity of the ice sheet (located similar to 150 km away from the paleoshoreline during the last glacial maximum). (C) 2002 Elsevier Science B.V. All rights reserved.
582qnTimes Cited:33 Cited References Count:89
Keywords: baltimore canyon; coastal-plain; glacioeustasy; global sea-level; isotopes; late quaternary sedimentation; mass-wasting; new-york; north-atlantic; northwest atlantic; passive margin; Pleistocene; sedimentary processes; sequence stratigraphy; shelf; slope

Radiocarbon as a tool to apportion the sources of polycyclic aromatic hydrocarbons and black carbon in environmental samples - Reddy, C. M.; Pearson, A.; Xu, L.; McNichol, A. P.; Benner, B. A.; Wise, S. A.; Klouda, G. A.; Currie, L. A.; Eglinton, T. I. (Environmental Science & Technology, 2002)
To determine the relative inputs of polycyclic aromatic hydrocarbons (PAHs) and black carbon (BC) in environmental samples from the combustion of fossil fuels and biomass we have developed two independent analytical methods for determining the C-14 abundance of PAHs and BC. The 5730 yr half-life of C-14 makes it an ideal tracer for identifying combustion products derived from fossil fuels (C-14-free) versus those stemming from modern biomass (contemporary C-14). The C-14 abundance of PAHs in several environmental Standard Reference Materials was measured by accelerator mass spectrometry after extraction and then purification by high-performance liquid chromatography and preparative capillary gas chromatography. This method yields pure compounds that allow for a high degree of confidence in the C-14 results. The PAHs data were then used to compare and evaluate results from an operationally defined thermal oxidation method used to isolate a BC fraction. The C-14 compositions of PAHs and BC were very similar and suggest that the thermal oxidation method employed for isolating BC is robust and free from interferences by non-BC components. In addition, these data indicate that both the PAHs and the BC species derive mostly from fossil fuels and/or their combustion products.
541gfTimes Cited:133Cited References Count:59

Radiocarbon dates bason on organic matter in diatom frustules, Abstract - Donoghue, Joanne C.; Hayes, John M.; Manganini, Steven J.; Francois, Roger (EOS. Trans. AGU, 2002)
OS42E-156
id: 1720

Radiocarbon Dates of Corals, Gastropods and Forminifers from Saurashtra Peninsula, Gujarat and Their Implications for Sea-level Studies - Mathur, U. B.; Pandey, D. K. (Journal Geological Society of India, 2002)
id: 1219

Radiocarbon dating, chronologic framework, and changes in accumulation rates of Holocene estuarine sediments from Chesapeake Bay - Colman, S. M.; Baucom, P. C.; Bratton, J. F.; Cronin, T. M.; McGeehin, J. P.; Willard, D.; Zimmerman, A. R.; Vogt, P. R. (Quaternary Research, 2002)
Rapidly accumulating Holocene sediments in estuaries commonly are difficult to sample and date. In Chesapeake Bay, we obtained sediment cores as much as 20 m in length and used numerous radiocarbon ages measured by accelerator mass spectrometry methods to provide the first detailed chronologies of Holocene sediment accumulation in the bay. Carbon in these sediments is a complex mixture of materials from a variety of sources. Analyses of different components of the sediments show that total organic carbon ages are largely unreliable, because much of the carbon (including coal) has been transported to the bay from upstream sources and is older than sediments in which it was deposited. Mollusk shells (clams, oysters) and foraminifera appear to give reliable results, although reworking and burrowing are potential problems. Analyses of museum specimens collected alive before atmospheric nuclear testing suggest that the standard reservoir correction for marine samples is appropriate for middle to lower Chesapeake Bay. The biogenic carbonate radiocarbon ages are compatible with (210)Pb and (137)Cs data and pollen stratigraphy from the same sites.Post-settlement changes in sediment transport and accumulation is an important environmental issue in many estuaries, including the Chesapeake. Our data show that large variations in sediment mass accumulation rates occur among sites. At shallow water sites, local factors seem to control changes in accumulation rates with time. Our two relatively deep-water sites in the axial channel of the bay have different long-term average accumulation rates, but the history of sediment accumulation at these sites appears to reflect overall conditions in the bay. Mass accumulation rates at the two deep-water sites rapidly increased by about fourfold coincident with widespread land clearance for agriculture in the Chesapeake watershed.
517wpTimes Cited:57Cited References Count:33

Radiocarbon dating of alkenones in sediments from the Namibian continental margin - Mollenhauer, Gesine; Eglinton, Timothy I.; Ohkouchi, Nao; Grootes, Pieter M.; Muller, Peter J.; Rullkotter, Jurgen; Schneider, Ralph R. (European Geophysical Society, XXVII General Assembly, 2002)
id: 546

Rates of evolution in ancient DNA from Adelie penguins - Lambert, D. M.; Ritchie, P. A.; Millar, C. D.; Holland, B.; Drummond, A. J.; Baroni, C. (Science, 2002)
Well-preserved subfossil bones of Adelie penguins, Pygoscelis adeliae, underlie existing and abandoned nesting colonies in Antarctica. These bones, dating back to more than 7000 years before the present, harbor some of the best-preserved ancient DNA yet discovered. From 96 radiocarbon-aged bones, we report large numbers of mitochondrial haplotypes, some of which appear to be extinct, given the 380 living birds sampled. We demonstrate DNA sequence evolution through time and estimate the rate of evolution of the hypervariable region I using a Markov chain Monte Carlo integration and a least-squares regression analysis. Our calculated rates of evolution are approximately two to seven times higher than previous indirect phylogenetic estimates.
Lambert, D MRitchie, P AMillar, C DHolland, BDrummond, A JBaroni, CengResearch Support, Non-U.S. Gov'tResearch Support, U.S. Gov't, P.H.S.2002/03/23 10:00Science. 2002 Mar 22;295(5563):2270-3.

The Shandong mud wedge and post-glacial sediment accumulation in the Yellow Sea - Liu, J. P.; Milliman, J. D.; Gao, S. (Geo-Marine Letters, 2002)
Two well-defined deltaic sequences in the Bohai Sea and in the South Yellow Sea represent post-glacial accumulation of Yellow River-derived sediments. Another prominent depocenter on this epicontinental shelf, a pronounced clinoform in the North Yellow Sea, wraps around the northeastern and southeastern end of the Shandong Peninsula, extending into the South Yellow Sea. This Shandong mud wedge is 20 to 40 m thick and contains an estimated 300 km(3) of sediment. Radiocarbon dating, shallow seismic profiles, and regional sea-level history suggest that the mud wedge formed when the rate of post-glacial sea-level rise slackened and the summer monsoon intensified, at about 11 ka. Geomorphic configuration and mineralogical data indicate that present-day sediment deposited on the Shandong mud wedge comes not only from the Yellow River but also from coastal erosion and local rivers. Basin-wide circulation in the North Yellow Sea may transport and redistribute fine sediments into and out of the mud wedge.
538tcTimes Cited:56Cited References Count:34

Slip rates of the Karakorum fault, Ladakh, India, determined using cosmic ray exposure dating of debris flows and moraines - Brown, E. T.; Bendick, R.; Bourles, D. L.; Gaur, V.; Molnar, P.; Raisbeck, G. M.; Yiou, F. (Journal of Geophysical Research-Solid Earth, 2002)
We measure an average slip rate of 4+/-1 mm yr(-1) along the Karakorum fault, heretofore considered one of Earth's greatest strike-slip faults and thought by many to play a key role in Asian deformation kinematics. Levees of a debris flow, and contours of the fan on which it was deposited, have been displaced 40+/-5 m. Concentrations of Be-10 in boulders from the debris flow yield ages of 11-14 ka, implying a slip rate of 4+/-1 mm yr(-1) during that period. A fresher debris flow has been offset 2-2.5 m since 1-2 ka, implying the occurrence of an earthquake with Msimilar to7 since that time. Concentrations of Be-10 in boulders on the crest of the most extensive moraine near Leh imply that the most recent major glacial advance occurred at 90+/-15 ka. This is consistent with the inference of others that alpine glaciers in this region have not necessarily expanded in concert with Northern Hemisphere continental ice sheets. If features, including lateral moraines, that Liu inferred to have been offset 300-350 m by the Karakorum fault date from the same period, they too imply a slip rate of 3-4 mm yr(-1). This slip rate is comparable to rates of extension across grabens within Tibet. With recent evidence that slip along the Altyn Tagh fault occurs at similar to10 mm yr(-1), our rate suggests that slip along the boundaries of Tibet is not significantly more rapid than extension within the plateau. Hence, plate tectonics, in the strictest sense, ought not be applied to Tibet, because Tibet does not behave as a rigid plate.
634wuTimes Cited:104Cited References Count:72

An unexplored sedimentary record for the study of environmental change in Mediterranean environments: Posidonia oceanica (L.) Delile peats - Mateo, M. A.; Renom, P.; Julià, R.; Romero, J.; Michener, R. (The Study of Environmental Change Using Isotope Techniques. IAEA C&S Papers Series, 2002)
id: 351

Were glacial iceberg surges in the North Atlantic triggered by global climatic warming? - Moros, M.; Kuijpers, A.; Snowball, I.; Lassen, S.; Backstrom, D.; Gingele, F.; McManus, J. F. (Marine Geology, 2002)
id: 712

WOCE radiocarbon IV: Pacific Ocean results; P10, P13N, P14C, P18, P19 & S4P - Key, R. M.; Quay, P. D.; Schlosser, P.; McNichol, A. P.; von Reden, K. F.; Schneider, R. J.; Elder, K. L.; Stuiver, M.; Ostlund, H. G. (Radiocarbon, 2002)
The World Ocean Circulation Experiment, carried out between 1990 and 1997, provided the most comprehensive oceanic survey of radiocarbon to date. Approximately 10,000 samples were collected in the Pacific Ocean by U.S. investigators for both conventional large volume P counting and small volume accelerator mass spectrometry analysis techniques. Results from six cruises are presented. The data quality is as good or better than previous large-scale surveys. The C-14 distribution for the entire WOCE Pacific data set is graphically described using mean vertical profiles and sections, and property-property plots.
591keTimes Cited:33Cited References Count:56

Woodlands in ancient and modern times in the territory of Sagalassos - Vermoere, M.; Vanhecke, L.; Paulissen, E.; Waelkens, M.; Smets, E. (Sagalassos VI. Report on the survey and excavation campaigns of 1998, 1999 and 2000, 2002)
id: 346

Abrupt climate change and pre-Columbian cultural collapse - Brenner, M.; Hodell, D. A.; Curtis, J. H.; Rosenmeier, M.; Binford, M. W.; Abbott, M. B. (Interhemispheric Climate Linkages, 2001)
id: 1408

Across forests and savannas: Later Stone Age assemblages from Ituri and Semliki, Northeast Domacratic Republic of Congo - Mercader, J.; Brooks, A. (Journal of Antropological Research, 2001)
id: 1217

Benthic remineralization and burial of biogenic SiO2, CaCO3, organic carbon, and detrital material in the Southern Ocean along a transect at 170oW - Sayles, F. L.; Martin, W. R.; Chase, Z.; Anderson, R. F. (Deep-Sea Res., 2001)
id: 276

Biogenic silica and organic carbon in sediments from the Pacific Sector of the Southern Ocean - Giglio, F.; Langone, L.; Morigi, C.; Frignani, M.; Ravaioli, M. (Antarctic Earth Sciences at the close of a Millenium: Proceedings 8th International Symposium on Artarctic Earth Sciences, 2001)
id: 284

Bomb 14C versus anthropogenic CO2 in OCMIP ocean biogeochemical models - Matsumoto, K.; Sarmiento, J. L.; Key, R. M.; Slater, R. D.; Sabine, C. L. (Global Change Open Science Conference, 2001)
id: 1446

Brachiopod shell taphonomy in subtropical siliciclastic environments: preliminary field results - Simoes, M. G.; Kowalewski, M.; Carroll, M.; Rodland, D. L.; Mello, L. H. C. (Reuniao Anal de Sociedade Brasileira de Paleontologia, Paleo-2001, 2001)
id: 281

Carbon isotope geochemistry of the Santa Clara River - Masiello, C. A.; Druffel, E. R. M. (Global Biogeochemical Cycles, 2001)
The Santa Clara River is a prototypical small mountainous river, with a headwater height greater than 1000 m and a basin area smaller than 10,000 m(2). Although individual small mountainous rivers export trivial amounts of sediment and carbon to the ocean, as a group these rivers may export a major fraction las much as 50%) of the total global river sediment flux [Milliman and Syvitski, 1992], making their geochemistry relevant the study of the ocean's carbon cycle. In addition, many small rivers export sediment in a few high flux events, causing massive, sporadic discharge of carbon onto coastal shelves, discharge conditions very different from those of large rivers. This class of rivers is an end-member of the river-ocean carbon exchange system, opposite the Earth's largest river, the Amazon. The carbon mass and isotopic properties of the Santa Clara River are significantly different from previously studied large rivers. During the 1997-1998 winter, all Santa Clara carbon pools were old, with flux-weighted average Delta (14)C values of -428 +/- 76 parts per thousand for particulate organic carbon, -73 +/- 31 parts per thousand for dissolved organic carbon, and -644 +/- 58 parts per thousand for black carbon. The age of exported carbon is primarily due to the deep erosion of old soils and not to inclusion of fossil fuel carbon. Additionally, the delta (13)C signatures of exported carbon pools were high relative to terrestrial carbon, bearing a signature quite similar to marine carbon (average particulate organic carbon (POC) delta (13)C = -22.2 +/- 0.8 parts per thousand). The Santa Clara's estuary is small and drains onto the narrow eastern Pacific coastal margin, exporting this old soil organic matter directly into the ocean. If the Santa Clara export patterns are representative of this class of rivers, they may be a significant source of refractory terrestrial carbon to the ocean.
441mbTimes Cited:116Cited References Count:34

Composition of hydrothermal vent microbial communities as revealed by analyses of signature lipids, stable carbon isotopes, and Aquificales cultures - Jahnke, Linda L.; Eder, Wolfgang; Huber, Robert; Hope, Janet M.; Hinrichs, Kai-Uwe; Hayes, John M.; Des Marais, David J.; Cady, Sherry L.; Summons, Roger E. (Applied and Environmental Microbiology, 2001)
id: 1783

Converting AMS data to radiocarbon values: Considerations and conventions - McNichol, A. P.; Jull, A. J. T.; Burr, G. S. (Radiocarbon, 2001)
We summarize the basic operation of accelerator mass spectrometry (AMS) systems used to measure radiocarbon and discuss the calculations used to convert AMS output to C-14 data.
1531yc Times Cited:24 Cited References Count:19
Keywords: accelerator mass-spectrometry; NOSAMS; ratio

On the d13C:PO4 relationahip in the modern and glacial ocean - Toggweiler, J. R.; Key, R. M.; McNeil, B. (Fall AGU Meeting, 2001)
id: 1447

Development of a Carbon Isotope-Based Tracer of Groundwater Fluxes into Estuaries and the Coastal Ocean - McCorkle, D. C.; Gramling, C. M.; Mulligan, A. E.; Woods, T. L. (EOS, 2001)
id: 1409

The Effect of Different Acid Treatments on the Radiocarbon Age of Sedimentary Organic Matter - Batista, F; McNichol, A P; Gerlach, D S (EOS, Transactions, American Geophysical Union, 2001)
To date the bulk organic carbon in marine sediments it is necessary to first remove any inorganic carbon present by acidification. We tested three different acid treatments to see how the different methods affected the stable and radio-carbon isotopic values of the remaining organic matter. The standard NOSAMS method is to react the sediment with repeated aliquots of1.2N HCl until no visible dissolution reaction is present. The remaining sediment is then rinsed with distilled water. This method leaves a carbonate-free sediment that is easy to combust but suffers from the possible removal of acid-soluble organic matter. We compared this method to two methods that do not require rinsing of the sediments after acid treatment--a vapor phase acidification method using concentrated HCl (Hedges and Stern, 1984) and an in situ acidification with sulfurous acid (Verardo et al., 1990). Scaling these methods up to deal with the amount of sediment required for a radiocarbon date can present challenges that are not evident when dealing with the small quantities required for a percent organic carbon measurement. Vapor phase acidification of high carbonate sediments leaves hygroscopic salts that can impede sample combustion. Sulfurous acid is a weak acid and it is very difficult to determine when all the carbonate has been removed from a sediment sample. We tested sediments from 6 locations in (or near) the Atlantic Ocean that represented riverine, estuarine, and marine environments as well as a range of both organic and inorganic concentrations. We will present the isotopic results for these sediments and evaluate what is the most appropriate method to use. Hedges J.I. and J.H. Stern (1984) Limnol. Oceanogr. 29, 657-663. Verardo D.J., P.N. Froelich and A. McIntyre (1990) Deep-Sea Res. 37, 157-165.
Date revised - 2007-02-01SuppNotes - Session: OS41A 9 The Truth About Paleoceanographic Proxies - What Are They Really Telling Us III Posters.Last updated - 2016-05-27
Keywords: A, Atlantic; Acidification; Brackish; Brackishwater environment; carbon cycling; Chronostratigraphy; Estuarine sedimentation; organic carbon; organic matter; Palaeoceanography; Radioactivity and radioisotopes; Radiocarbon dating; Sediment chemistry; Stable isotopes

Estimates of anthropogenic carbon uptake from four three-dimensional global ocean models - Orr, J. C.; Maier-Reimer, E.; Mikolajewicz, U.; Monfray, P.; Sarmiento, J. L.; Toggweiler, J. R.; Taylor, N. K.; Palmer, J.; Gruber, N.; Sabine, C. L.; Le Quere, C.; Key, R. M.; et al. (Global Biogeochemical Cycles, 2001)
We have compared simulations of anthropogenic CO2 in the four three-dimensional ocean models that participated in the first phase of the Ocean Carbon-Cycle Model Intercomparison Project (OCMIP), as a means to identify their major differences. Simulated global uptake agrees to within +/- 19%, giving a range of 1.85 +/-0.35 Pg C yr(-1) for the 1980-1989 average, Regionally, the Southern Ocean dominates the present-day air-sea flux of anthropogenic CO2 in all models, with one third to one half of the global uptake occurring south of 30 degreesS. The highest simulated total uptake in the Southern Ocean was 70% larger than the lowest. Comparison with recent data-based estimates of anthropogenic CO2 suggest that most of the models substantially overestimate storage in the Southern Ocean; elsewhere they generally underestimate storage by less than 20%. Globally, the OCMIP models appear to bracket the real ocean's present uptake, based on comparison of regional data-based estimates of anthropogenic CO2 and bomb C-14. Column inventories of bomb C-14 have become more similar to those for anthropogenic CO2 with the time that has elapsed between the Geochemical Ocean Sections Study (1970s) and World Ocean Circulation Experiment (1990s) global sampling campaigns. Our ability to evaluate simulated anthropogenic CO2 would improve if systematic errors associated with the data-based estimates could be provided regionally.
417rwTimes Cited:187Cited References Count:64

Geometry, numerical models and revised slip rates for the Reelfoot blind thrust and truishear fault-propagation fold, New Medrid Seismic zone - Champion, J.; Mueller, K.; Tate, A.; Guccione, M. J. (Engineering Geology, 2001)
The geometry and structural relief of late Holocene sediments folded across the Reelfoot scarp are characterized with trench excavations, shallow borings, a digital elevation model (DEM) of topography and Reelfoot Lake (RL) bathymetry. Results suggest the scarp forms by heterogeneous shear in the forelimb of a fault-propagation fold. Seismic data and the accompanying structural analysis support the argument that the Reelfoot fault does not offset the surface, and that the Reelfoot scarp is a fold limb. Structural relief measured across the Reelfoot scarp is slightly higher than previous determinations and varies from 7 to 11 m along the western shoreline of RL. Numerical models based on trishear kinematics constrain growth of the Reelfoot monocline and indicate that the underlying Reelfoot thrust fault is steeply dipping. The shallowest portion of the central Reelfoot thrust segment dips 75° where the fault tip has propagated upward from 911 m to its current location 465 m beneath the surface. The models indicate that the shallowest section of the southern thrust segment in the Reelfoot thrust system dips even more steeply at 80° but has propagated upward only a few tens of meters to its present location 1016 m beneath the surface. The thrust is flatter at deeper levels based on the location of earthquake hypocenters. Strain across the Reelfoot scarp is partitioned into two or three separate fold scarps that collectively record a late Holocene fault slip rate of 3.9±0.1 mm/yr. The slip rate is based on 9 m of structural relief, the 2290±60 ybp age of folded sediment and a 75° dip for the fault. This implies a rate of horizontal contraction in the seismic zone of ∼1.0 mm/yr. This rate is strongly dependent on the dip of the thrust calculated by the structural analysis. The numerical models argue for reactivation of faults that previously offset Paleozoic strata.
id: 1381

Holocene–late Pleistocene non-tropical carbonate sediments and tectonic history of the western rift basin margin of the southern Gulf of California - Halfar, J.; Godinez-Orta, L.; Goodfriend, G. A.; Mucciarone, D. A.; Ingle, J. C.; Holden, P. (Sedimentary Geology, 2001)
Using high-resolution seismic reflection profiling and dating of (1) shallow marine vibracores and (2) sediments collected from uplifted marine terraces we reconstruct the tectonic history and sediment accumulation patterns of Holocene to late Pleistocene warm-temperate to subtropical carbonates in the southern Gulf of California, Mexico. The study was conducted in the vicinity of La Paz where carbonates form along the fault bounded narrow western shelf of the tectonically active Gulf of California rift basin. The non-tropical nature of the setting is responsible for (1) poor cementation of the bioclastic carbonates, and (2) a composition which is dominated by rhodoliths (coralline red algae), corals and mollusks. Unrimmed carbonate flats forming in small pocket bays and a rhodolith bioherm, which has a surface area of more than 20 km2 and is up to 16 m thick, constitute the major carbonate factories. Holocene carbonate accumulation rates were deduced from seismic and core data and are highest on the rhodolith bioherm (260 cm/ka) and in subtidal zones of pocket bays (210 cm/ka), and lowest on the inner and middle shelf (100 cm/ka). Taken together, rates of carbonate accumulation are intermediate in magnitude between higher rates recorded in fully tropical carbonate settings and lower rates typical of cool-water carbonates. Seismic reflection profiles demonstrate that Isla Espiritu Santo in the center of the study area is a west dipping fault block, which is tectonically influenced by two distinct faults, the La Paz and Espiritu Santo faults. The latter fault accommodates at least 700 m of east-side down normal offset, and forms a steep eastern escarpment leading into the La Paz slope basin. Some of the sediments produced in the shallow carbonate factories of the narrow La Paz shelf are transported across this escarpment and are redeposited in the slope basin at a water depth of 750 m. Uranium-series dates of marine terraces exposed on Isla Espiritu Santo indicate that late Pleistocene uplift along the eastern side of the island could be as high as 310 mm/ka whereas downdropping along the western side of the island occurred at a rate of up to 15 mm/ka. Isla Espiritu Santo therefore constitutes part of the uplifted shoulder of the western margin of the Gulf of California rift basin. Patterns of vertical tectonic movements of Isla Espiritu Santo together with fault offsets on the surrounding seafloor and slump features on steep submarine slopes, point to continuous activity of the La Paz and Espiritu Santo faults. Results of this study will assist in recognizing and interpreting similar settings along ancient non-tropical rift basin margins worldwide and especially in the Neogene of the Gulf of California.
id: 1316

Hypothesized climate forcing time series for the last 500 years - Robertson, A.; Overpeck, J.; Rind, D.; Mosley-Thompson, E.; Zielinski, G.; Lean, J.; Koch, D.; Penner, J.; Tegen, I.; Healy, R. (Journal of Geophysical Research-Atmospheres, 2001)
A new compilation of annually resolved time series of atmospheric trace gas concentrations, solar irradiance, tropospheric aerosol optical depth, and stratospheric (volcanic) aerosol optical depth is presented for use in climate modeling studies of the period 1500 to 1999 A.D. Atmospheric CO2 CH4, and N2O concentrations over this period are well established on the basis of fossil air trapped in ice cores and instrumental measurements over the last few decades. Estimates of solar irradiance, ranging between 1364.2 and 1368.2 W/m(2), are presented using calibrated historical observations of the Sun back to 1610, along with cosmogenic isotope variations extending back to 1500. Tropospheric aerosol distributions are calculated by scaling the modern distribution of sulfate and carbonaceous aerosol optical depths back to 1860 using reconstructed regional CO2 emissions; prior to 1860 the anthropogenic tropospheric aerosol optical depths are assumed to be zero. Finally, the first continuous, annually dated record of zonally averaged stratospheric (volcanic) optical depths back to 1500 is constructed using sulfate flux data from multiple ice cores from both Greenland and Antarctica, in conjunction with historical and instrumental (satellite and pyrheliometric) observations. The climate forcings generated here are currently being used as input to a suite of transient (time dependent) paleoclimate model simulations of the past 500 years. These forcings are also available for comparison with instrumental and proxy paleoclimate data of the same period.
456yeTimes Cited:108Cited References Count:89

The impact of sea ice concentration accuracies on climate model simulations with the GISS GCM - Parkinson, C. L.; Rind, D.; Healy, R. J.; Martinson, D. G. (Journal of Climate, 2001)
The Goddard Institute for Space Studies global climate model (GISS GCM) is used to examine the sensitivity of the simulated climate to sea ice concentration specifications in the type of simulation done in the Atmospheric Model Intercomparison Project (AMIP), with specified oceanic boundary conditions. Results show that sea ice concentration uncertainties of +/-7% can affect simulated regional temperatures by more than 6 degreesC, and biases in sea ice concentrations of +7% and -7% alter simulated annually averaged global surface air temperatures by -0.10 degrees and +0.17 degreesC, respectively, over those in the control simulation. The resulting 0.27 degreesC difference in simulated annual global surface air temperatures is reduced by a third, to 0.18 degreesC, when considering instead biases of +4% and -4%. More broadly, least squares fits through the temperature results of 17 simulations with ice concentration input changes ranging from increases of 50% versus the control simulation to decreases of 50% yield a yearly average global impact of 0.0107 degreesC warming for every 1% ice concentration decrease, that is, 1.07 degreesC warming for the full +50% to -50% range. Regionally and on a monthly average basis, the differences can be far greater, especially in the polar regions, where wintertime contrasts between the +50% and -50% cases can exceed 30 degreesC. However, few statistically significant effects are found outside the polar latitudes, and temperature effects over the nonpolar oceans tend to be under 1 degreesC, due in part to the specification of an unvarying annual cycle of sea surface temperatures. The +/-7% and +/-4% results provide bounds on the impact (on GISS GCM simulations making use of satellite data) of satellite-derived ice concentration inaccuracies, +/-7% being the current estimated average accuracy of satellite retrievals and +/-4% being the anticipated improved average accuracy for upcoming satellite instruments. Results show that the impact on simulated temperatures of imposed ice concentration changes is least in summer, encouragingly the same season in which the satellite accuracies are thought to be worst. Hence, the impact of satellite inaccuracies is probably less than the use of an annually averaged satellite inaccuracy would suggest.
id: 1944; PT: J; UT: WOS:000169239100008

Initiation of the Australian summer monsoon 14,000 years ago - Wyrwoll, K. H.; Miller, G. H. (Quaternary International, 2001)
Definitive evidence for the onset of monsoon moisture in northern Australia following the and phase of the Last Glacial Maximum has been elusive, in large part due to the lack of long, continuous sediment records. Here we report new evidence from two separate drainage basins in the Kimberley region of monsoonal northwestern Australia. At both sites, radiocarbon ages on (basal) biogenic materials in flood deposits indicate stream flow, as high or higher than maximum historic levels, began about 14 cal ka BP. These results suggest that the Australian summer monsoon was fully active several millennia earlier than previously expected. The early onset of the monsoon and the widespread evidence for diminished monsoon activity in the late Holocene cannot be reconciled with primary forcing of the Australian monsoon by changes in low-latitude summer insolation over Australia. (C) 2001 Elsevier Science Ltd and INQUA. All rights reserved.
478pnTimes Cited:78Cited References Count:42

Isotopic Evolution of the Biogeochemical Carbon Cycle During the Precambrian - Des Marais, David J. (Reviews in Mineralogy & Geochemistry, Stable Isotope Geochemistry, 2001)
id: 1556

The last interglacial to glacial transition, Togiak Bay, Southwestern Alaska - Kaufman, D. S.; Manley, W. F.; Wolfe, A. P.; Hu, F. S.; Preece, S. J.; Westgate, J. A.; Forman, S. L. (Quaternary Research, 2001)
An 18-m-high coastal bluff at Togiak Bay (northwestern Bristol Bay, southwestern Alaska) exposes marine, lacustrine, fluvial, glacial, volcanic, and organic deposits that record the ∼50,000-year-long transition from the peak of the last interglaciation to the early Wisconsin glaciation. The base of the section is dominated by stratified sand and silt extending up to 4.3 m above sea level; marine diatoms are present, and pollen assemblages are characterized by relatively high percentages of Picea, Alnus, and Betula and low percentages of Poaceae and Cyperaceae. The marine sediment was probably deposited during the peak of marine oxygen-isotope stage (OIS) 5e. An infrared stimulated luminescence (IRSL) age of 151,000±13,000 yr from near the base of the exposure is permissive of this correlation. The marine sand and silt are overlain by 0.8 m of peaty silt with diatoms that record a transition from marine to lacustrine conditions. During this interval, Poaceae and Cyperaceae dominate the pollen assemblages, and Picea and shrubs are nearly absent, suggesting that herb tundra occupied the landscape. This interval probably encompasses OIS 5d on the basis of the herb tundra and an IRSL age of 119,000±10,000 yr from 60 cm below the marine/lacustrine transition. The organic mud is overlain by 3.1 m of stratified sand and organic silt that apparently record shallowing of the lake; reappearance of spruce and shrubs (=OIS 5c?); and subsequent deepening of the lake (=OIS 5b?); followed by aggradation of a floodplain (=OIS 5a?), which was dry at the time basaltic lava buried the site. Thermoluminescence analyses on lava-baked sediment indicate that the eruption occurred 70,000±10,000 yr ago. Sometime thereafter, but prior to 53,600 14C yr B.P. an outlet of the Ahklun Mountains ice cap advanced over the site and deposited ∼7 m of bouldery ice-contact drift. The sedimentary sequence contains at least four tephra beds. Major- and trace-element chemistry provide a basis for correlating two of the tephras with tephra beds at nearby sites. The tephras, luminescence ages, and correlations with marine isotope stages provide the geochronological control to place the Togiak Bay section into a global context. The site serves as an important new reference section for late Pleistocene paleoenvironmental change in eastern Beringia.
id: 1392

Multiple anthropogenic tracer distributions in the ocean - Sabine, C. L.; Key, R. M.; Bullister, J. L.; Feely, R. A.; Lamb, M. F.; Millero, F. J.; Wanninkhof, R.; Peng, T. H.; Lee, K.; Kozyr, A.; Gruber, N. (Sixth International CO2 Conference, 2001)
id: 319

New records show pronounced changes in Arctic Ocean circulation and climate (cover article) - Darby, D.; Bischof, J.; Cutter, G.; de Vernal, A.; Hillaire-Marcel, C.; Dwyer, G.; McManus, J.; Polyak, L.; Osterman, L.; Poore, R. (EOS, Transactions, American Geophysical Union, 2001)
id: 332

Oceanic changes in the southern Pacific Ocean during the last deglaciation time, as recorded by planktic foraminifers and oxigen isotopes. --Extended abstract - Morigi, C.; Capotondi, L.; Giglio, F.; Langone, L.; Brilli, M.; Turi, B.; Ravaioli, M. (ANTOSTRAT Symposium on "The geologic record of the Antarctic ice sheet from drilling, coring and seismic studies", 2001)
id: 1428

Origins of lipid biomarkers in Santa Monica Basin surface sediment: A case study using compound-specific D14C analysis - Pearson, A.; McNichol, A. P.; Benitez-Nelson, B. C.; Hayes, J. M.; Eglinton, T. I. (Geochimica et Cosmochimica Acta, 2001)
id: 1419

Paleoceanographic changes in the Southern Ocean, during the last deglaciation time, as recorded by planktic foraminifers and oxygen isotopes--Poster - Morigi, C.; Capotondi, L.; Giglio, F.; Langone, L.; Turi, B.; Brilli, M.; Ravaioli, M. (ANTOSTRAT Symposium on "The geologic record of the Antarctic ice sheet from drilling, coring and seismic studies"--Poster, 2001)
id: 1424

Persistent solar influence on North Atlantic climate during the Holocene - Bond, G.; Kromer, B.; Beer, J.; Muscheler, R.; Evans, M. N.; Showers, W.; Hoffmann, S.; Lotti-Bond, R.; Hajdas, I.; Bonani, G. (Science, 2001)
Surface winds and surface ocean hydrography in the subpolar North Atlantic appear to have been influenced by variations in solar output through the entire Holocene. The evidence comes from a close correlation between inferred changes in production rates of the cosmogenic nuclides carbon-14 and beryllium-10 and centennial to millennial time scale changes in proxies of drift ice measured in deep-sea sediment cores. A solar forcing mechanism therefore may underlie at least the Holocene segment of the North Atlantic's "1500-year" cycle. The surface hydrographic changes may have affected production of North Atlantic Deep Water, potentially providing an additional mechanism for amplifying the solar signals and transmitting them globally.
id: 1397; Bond, G Kromer, B Beer, J Muscheler, R Evans, M N Showers, W Hoffmann, S Lotti-Bond, R Hajdas, I Bonani, G New York, N.Y. Science. 2001 Dec 7;294(5549):2130-6. Epub 2001 Nov 15.

Pleistocene glacial history of the southern Ahklun Mountains, southwestern Alaska: Soil-development, morphometric, and radiocarbon constraints - Manley, W. F.; Kaufman, D. S.; Briner, J. P. (Quaternary Science Reviews, 2001)
Four new AMS ages, glacial mapping, and measurements of soil development, loess thickness, and moraine morphology constrain the age and extent of at least three Quaternary advances by outlet lobes of an ice cap over the Ahklun Mountains of southwestern Alaska. The relative-age data are from 107 sites correlated to 25 ice-marginal positions in the Kanektok, Goodnews, Togiak, and Kulukak River valleys and along the southeastern flank of the range. Radiocarbon ages provide minimum ages for six — and a maximum age for one — of the former ice margins. Soil and morphometric parameters subdivide the ice limits into three relative-age groups. One to three pre-Wisconsin advances, probably middle Pleistocene in age, are represented by drift with relatively thick B horizons (60±5 cm, with Bt horizons), thick loess caps (80±12 cm), and broad moraines (135±134 m) with gentle side slopes (7±5°). An extensive early Wisconsin (sensu lato, s.l.) advance, >39.9 ka, and three associated stillstands or readvances are characterized by intermediate soil and morphometric parameters (Bw and weak Bt horizons with thicknesses of 40±11 cm; loess thicknesses of 69±46 cm; crest widths of 38±13 m; and slope angles of 14±4°). The maximum late Wisconsin advance, >16.9 ka, and two readvances or stillstands are associated with thin (20±5 cm), weakly to moderately developed Bw horizons, thin loess caps (28±8 cm), narrow crest widths (28±9 m), and steep slope angles (18±3°). The data confirm that early-Wisconsin glaciers in southeast Beringia were much more extensive than late Wisconsin glaciers, which were apparently limited by availability of moisture.
id: 1204

Possible record of the yunger dryas event in sediments of the southern ocean (Pacific sector)--abstract - Morigi, C.; Capotondi, L.; Langone, L.; Giglio, F.; Ravaioli, M. (AUG, 2001)
id: 1427

Possible record of the yunger dryas event in sediments of the Southern Ocean (Pacific Sector)--Poster - Morigi, C.; Capotondi, L.; Langone, L.; Giglio, F.; Ravaioli, M. (AUG, 2001)
id: 1423

Pre-late Wisconsin glacial history, coastal Ahklun Mountains, southwestern Alaska-New amino acid, thermoluminescence, and 40Ar/30Ar results - Kaufman, D. S.; Manley, W. F.; Forman, S. L.; Layer, P. (Quaternary Science Reviews, 2001)
New stratigraphic and geochronologic data from the Togiak Bay area of southwestern Alaska indicate that glaciers advanced from the southern Ahklun Mountains at least three and as many as six times prior to the late Wisconsin. The oldest glaciations are represented by glacial–marine sediment in coastal exposures on Hagemeister Island. The extent of amino acid (isoleucine) epimerization in fossil molluscs indicates that at least one, and possibly four, older middle Pleistocene glacial intervals are represented, with age estimates spanning ∼500–280 ka and averaging ∼400±100 ka. The youngest glacial-marine drift on Hagemeister Island may correlate with the eruption of the Togiak tuya. A new 40Ar/39Ar age on basalt that overlies pillow lava indicates that the volcano erupted through glacial ice at least 300 m thick 263±22 ka. The youngest drift in the region overlies the Old Crow tephra (140±10 ka) and a 70±10 ka basaltic lava flow dated by thermoluminescence analysis of underlying baked sediment. The drift delimits flat piedmont lobes that spread out onto the continental shelf and terminated >100 km from their source areas during the early Wisconsin (sensu lato). The glacial-geologic evidence suggests that major expansions of glaciers were out of phase with global ice volume.
id: 1203

Radiocarbon Dating of Wood Samples and Plutonium Sediment Disturbance Studies at the Queen Anne's Revence Wreck Site - Martens, Christopher S.; McNichol, Ann P. (Southeastern Geology, 2001)
id: 1200

Subdivision of glacial deposits in southeastern Peru based on pedogenic development and radiometric ages - Goodman, A. Y.; Rodbell, D. T.; Seltzer, G. O.; Mark, B. G. (Quaternary Research, 2001)
The Cordillera Vilcanota and Quelccaya Ice Cap region of southern Peru (13 degrees 30'-14 degrees 00'S; 70 degrees 40'-71 degrees 25'W) contains a detailed record of late Quaternary glaciation in the tropical Andes, Quantification of soil development on 19 moraine crests and radiocarbon ages are used to reconstruct the glacial history. Secondary iron and day increase linearly in Quelccaya soils and clay accumulates at a linear rate in Vilcanota soils, which may reflect the semicontinuous addition of eolian dust enriched in secondary iron to all soils. In contrast, logarithmic rates of iron buildup in soils in the Cordillera Vilcanota reflect chemical weathering; high concentrations of secondary iron in Vilcanota tills may mask the role of eolian input to these soils. Soil-age estimates from extrapolation of field and laboratory data suggest that the most extensive late Quaternary glaciation occurred >70,000 yr B.P. This provides one of the first semiquantitative age estimates for maximum ice extent in southern Peru and is supported by a minimum-limiting age of similar to 41,520 C-14 yr B.P. A late glacial readvance culminated similar to 16,650 cal yr B.P. in the Cordillera Vilcanota, Following rapid deglaciation of unknown extent, an advance of the Quelccaya Ice Cap occurred between similar to 13,090 and 12,800 cal yr B.P., which coincides approximately with the onset of the Younger Dryas cooling in the North Atlantic region. Moraines deposited <394 cal yr B.P. in the Cordillera Vilcanota and <300 cal yr B.P. on the west side of the Quelccaya Ice Cap correlate with Little Ice Age moraines of other regions. (C) 2001 University or Washington.
452lzTimes Cited:27Cited References Count:51

Thirty thousand year record of climate from the Galapagos Islands and links with high latitudes - Koutavas, A.; Lynch-Stieglitz, J.; Sachs, J. P.; Marchitto, T. M. (EOS, 2001)
Fall Meeting Supplement F737
id: 255

Were Rhyolitic Glasses in the Vedde Ash and in the North Atlantic's Ash Zone 1 produced by the Same Volcanic Eruption? - Bond, G. C.; Mandeville, C.; Hoffmann, S. (Quaternary Science Reviews, 2001)
New evidence from North Atlantic deep-sea sediment cores suggests that rhyolitic glass shards in Ash Zone 1 and in the Vedde Ash may not have been produced by the same eruption as has been widely assumed. Our argument is based on (1) a marine ice-rafted deposit approximately 1000 years older than the Vedde Ash contains rhyolitic shards with the same major element chemistry as the Vedde Ash itself and (2) coincidence of Ash Zone 1 with an abrupt increase in discharge of glacial icebergs into the North Atlantic. Hence, we cannot rule out the possibility that Vedde-like rhyolitic glasses were erupted onto Icelandic glaciers before eruption of the Vedde Ash, stored in the glacial ice, then dispersed by icebergs into the North Atlantic and deposited partly or entirely as Ash Zone 1. While not disproving that Ash Zone 1 and the Vedde Ash came from the same eruption, our findings indicate that further study is needed to establish the exact relation between the two ash deposits.
id: 253

Black carbon in lacustrine and coastal marine sediments, Thesis - Muri, G. (University of Ljubljana, Slovenia, 2000)

Characterising the Namaqualand mudbelt of southern Africa: chronology, palynology and palaeoenvironments - Gray, C. E. D.; Meadows, M. E.; Lee-Thorp, J. A.; Rogers, J. (South African Geographical Journal, 2000)
id: 219

Chesapeake Bay sedimentary record of Holocene climatic variability and human ecosystem disturbance - Cronin, T.; Willard, D.; Karlsen, A.; Ishman, S.; Verardo, S.; McGeehin, J.; Kerhin, R.; Holmes, C.; Colman, S. M.; Zimmerman, A. (Geology, 2000)
id: 184

Climate, fire, and vegetation between about 13,000 and 9,200 14C yr. B. P - Moreno, P. I. (Quaternary Research, 2000)
id: 237

An estimate of the anthropogenic offset of oceanic d13CDIC based on the ventilation of the California Current at 42N - Ortiz, J. D.; Mix, A. C.; Wheeler, P.; Key, R. M. (Global Biogeochem. Cycles, 2000)
id: 307

Glacial-Interglacial variations in the accumulation rates of major biogenic components in the Southern Pacific Ocean sediments--Abstract - Giglio, F.; Langone, L.; Ravaioli, M.; Frignani, M.; Mangini, A.; Fonti, P. (Third International SO-JGOFS Symposium, 2000)
id: 287

Gulf of Mexico Intraslope Basins (BIB) Phase 1 Project Atlas - Damuth, J. E.; Olson, H. C.; Moss, G. (Institute for Geophysics, University of Texas at Austin Department of Geology and Geophysics, University of Texas at Arlington, 2000)
id: 354

Holocene cirque glacier activity in Western Spitsbergen, Svalbard: sediment records from pro-glacial Linnevatnet - Snyder, J. A.; Werner, A.; Miller, G. H. (The Holocene, 2000)
id: 234

Holocene lake sediment records of Arctic hydrology - MacDonald, G. M.; Felzer, B.; Finney, B. P.; Forman, S. L. (Journal of Paleolimnology, 2000)
Although paleoclimatic research in the Arctic has most often focused on variations in temperature, the Arctic has also experienced changes in hydrologic balance. Changes in Arctic precipitation and evaporation rates affects soils, permafrost, lakes, wetlands, rivers, ice and vegetation. Changes in Arctic soils, permafrost, runoff, and vegetation can influence global climate by changing atmospheric methane and carbon dioxide concentrations, thermohaline circulation, and high latitude albedo. Documenting past variations in Arctic hydrological conditions is important for understanding Arctic climate and the potential response and role of the Arctic in regards to future climate change. Methods for reconstructing past changes in Arctic hydrology from the stratigraphic, isotopic, geochemical and fossil records of lake sediments are being developed, refined and applied in a number of regions. These records suggest that hydrological variations in the Arctic have been regionally asynchronous, reflecting the impacts of different forcing factors including orbitally controlled insolation changes, changes in geography related to coastal emergence, ocean currents, sea ice extent, and atmospheric circulation. Despite considerable progress, much work remains to be done on the development of paleohydrological proxies and their application to the Arctic.
id: 375
Keywords: Arctic; Climate change; Holocene; paleohydrology; paleolimnology

Ice Core Paleoclimate Records in Tropical South America Since the Last Glacial Maximum - Thompson, L. G.; Mosley-Thompson, E.; Henderson, K. A. (Journal of Quaternary Science, 2000)
id: 245

The Indian Ocean 13C Suess effect - Sonnerup, R. E.; Quay, P. D.; McNichol, A. P. (Global Biogeochemical Cycles, 2000)
id: 1816

Late Quaternary sedimentary fluctuations of biogenic fluxes driven by climatic changes in the Southern Ocean--abstract - Langone, L.; Giglio, F.; Ravaioli, M.; Frignani, M.; Marozzi, G.; Rovatti, G. (XXV General Assembly of European Geophysical Society, 2000)
id: 288

Low-level (submicromole) environmental 14C metrology - Currie, L. A.; Kessler, J. D.; Marolf, J. V.; McNichol, A. P.; Stuart, D. R.; Donoghue, J. C. (Nucl. Instr. and Meth. in Phys. Res., 2000)
id: 1713

The NOSAMS sample preparation laboratory in the next millenium: Progress after the WOCE program - Gagnon, A. R.; McNichol, A. P.; Donoghue, J. C.; Stuart, D. R.; von Reden, K. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2000)
Since 1991, the primary charge of the National Ocean Sciences AMS (NOSAMS) facility at the Woods Hole Oceanographic Institution has been to supply high throughput, high precision AMS C-14 analyses for seawater samples collected as part of the World Ocean Circulation Experiment (WOCE). Approximately 13,000 samples taken as part of WOCE should be fully analyzed by the end of Y2K. Additional sample sources and techniques must be identified and incorporated if NOSAMS is to continue in its present operation mode.A trend in AMS today is the ability to routinely process and analyze radiocarbon samples that contain tiny amounts (<100 <mu>g) of carbon. The capability to mass-produce small samples for C-14 analysis has been recognized as a major facility goal. The installation of a new 134-position MC-SNICS ion source, which utilizes a smaller graphite target cartridge than presently used, is one step towards realizing this goal. New preparation systems constructed in the sample preparation laboratory (SPL) include an automated bank of 10 small-volume graphite reactors, an automated system to process organic carbon samples, and a multi-dimensional preparative capillary gas chromatograph (PCGC). (C) 2000 Elsevier Science B.V. All rights reserved.
372jrTimes Cited:20Cited References Count:12

Oceanic uptake of CO2 re-estimated through d13C in WOCE samples - Lerperger, M.; McNichol, A. P.; Peden, J.; Gagnon, A. R.; Elder, K. L.; Kutschera, W.; Rom, W.; Steier, P. (Nuclear Instruments and Methods in Physics Research, 2000)
id: 1817

An Ocean-Wide DIC-13 Data Set - McNichol, A P; Quay, P D; Stuart, D R; Sonnerup, R E; Key, R M (2000 Ocean Sciences Meeting, San Antonio, TX (USA), 24-28 Jan 2000, 2000)
High quality DIC-13 measurements were made throughout the world's oceans at the University of Washington (UW) and the National Ocean Sciences Accelerator Mass Spectrometry (NOSAMS) Facility during both the OACES and WOCE programs. We are currently merging these two data sets which represent 25000 individual DIC- 13 measurements from 1260 stations. We will present the inter-laboratory calibration and standardization data. Based on 135 measurements on CO2 gas extracted at UW, the mean offset between the two labs is 0.01 o/oo, similar to the offset observed from an exchange of DIC standards (0.012 o/oo). Stations measured by both laboratories will also be examined for offsets, although one comparison in the Indian Ocean shows no significant differences. We will present our progress towards a global atlas of DIC-13, primarily maps of the merged data sets in the Pacific, Southern, and Indian Oceans. In this poster we will concentrate on regions that have been under-sampled in the past, e.g. the Southern Ocean. Additionally, we will examine the relationship of DIC-13 to PO4 and to DIC-14. A preliminary analysis of DIC-13 and PO4 from three WOCE lines in the Pacific indicates that the expected relationship is observed in the deep waters and that the data from different water masses occupy well-defined regions of the graph. We are examining the potential for using the relationship between DIC-14 and DIC-13 to improve our understanding of the penetration of bomb radiocarbon into the ocean as well as fundamental processes in the deep ocean. The relationship is complex yet the data from shallow to intermediate depths (100 to 1000m) follow two distinct parallel lines that are related to the hemisphere in which
Date revised - 2007-04-01SuppNotes - Abstracts available.Last updated - 2016-12-21
Keywords: carbon cycling; Carbon dioxide; Deep water; dissolved inorganic carbon; ISW, Indian Ocean; Marine; Mass Spectrometry; Ocean circulation; Phosphates; PS, Antarctic Ocean; Q2 09146:TSD distribution, water masses and circulation; Stable isotopes; Standardization; Water masses; World Ocean; World Ocean Circulation Experiment (WOCE)

An ocean-wide DIC-13 data set - McNichol, A. P.; Quay, P. D.; Stuart, D. R.; Sonnerup, R. E.; Key, R. M. (AGU Ocean Sciences Meeting, 2000)
id: 1444

An organic tracer for surface ocean radiocarbon - Pearson, A.; Eglinton, T. I.; McNichol, A. P. (Paleoceanography, 2000)
The Delta(14)C of surface water dissolved inorganic carbon (DIC) in the Southern California Eight was compared to Delta(14)C as recorded by the sterols in Santa Monica and Santa Barbara Basin sediments. All of the C-26, C-27, C-28, and C-29 sterols as well as dinosterol had C-14 concentrations equal to surface water DIG, indicating that all of the major sterols were derived from phytoplanktonic production. There is no detectable terrestrial component. Their tracer capability was confirmed by comparing the "bomb C-14"-derived change in surface water Delta(14)C(DIC) With the change in Delta(14)C(sterol). The "prebomb" Delta(14)C(DIC) was similar to 82 parts per thousand, and prebomb sterols averaged -75 +/- 19 parts per thousand. The Delta(14)C value in 1996 was +71 parts per thousand, Eighteen measurements representing eight different sterols from the sediment-water interface of both Santa Monica and Santa Barbara Basins averaged +62 +/- 23 parts per thousand. When three of these values were eliminated because of suspected contamination, the remaining data averaged +71 +/- 12 parts per thousand. The entire compound class could serve as an excellent proxy for the C-14 concentration of ocean surface waters.
358wyTimes Cited:37Cited References Count:58

Organogenic dolomitization in peritidal to deep-sea sediments - Mazzullo, S. J. (Journal of Sedimentary Research, 2000)
Presumed barriers to early dolomitization in normal seawater-derived pore fluids at earth-surface temperatures appear to be overcome within some anoxic, organic-rich sediments as a result of bacterial sulfate reduction and methanogenesis, These processes may promote early dolomitization, particularly during methanogenesis and late stages of sulfate reduction, by concurrently raising and sustaining high pH and high total alkalinity and CO32- concentrations in pore fluids, and by simultaneously either decreasing Mg and Ca hydration or by promoting crystal surface reactions with less hydrated Mg-Ca neutral ion pairs. Volumetrically significant quantities of dolomite are associated with sulfate reduction and/or methanogenesis within peritidal, shallow-marine, and deep-sea deposits. Average concentrations of organogenic dolomite are as much as 70% in some Holocene peritidal deposits, and 28% in Mesozoic to Quaternary deep-sea sediments.Organogenic dolomites are mainly cements, and contain relatively low concentrations of Sr and Mn, Sulfate-reduction dolomites generally are Fe-deficient because of concurrent pyrite precipitation, whereas methanogenetic dolomites may be somewhat more ferroan as Fe substitutes for depleting Mg. Sources of Mg and Ca for dolomite are diffusion from overlying seawater and/or dissolution of precursor carbonate sediments. Dolomites are characterized by a wide range in delta(13)C values wherein those of sulfate reduction versus methanogenetic origin typically are C-13-depleted and C-13-enriched, respectively. The extent of C-13 depletion or enrichment, however, depends on the extent of organodiagenetic reactions and amount of C-13 contributed by seawater diffusion, and commonly results in overlap of delta(13)C(dolomite) values. The range of delta(18)O(dolomite) values is somewhat more restricted, and generally reflects differences in pore-fluid temperature and salinity. Some of the unresolved issues in organogenic dolomitization are: the relative efficiencies of sulfate reduction versus methanogenesis in promoting dolomitization, depths of dolomite formation inferred on the basis of delta(18)O(dolomite) values and probable sources of Mg and Ca, and the mode of dolomitization with progressive burial into methanogenetic zones.
A287nxTimes Cited:125Cited References Count:106

The origin of Antarctic precipitation: a modelling approach - Delaygue, G.; Masson, V.; Jouzel, J.; Koster, R. D.; Healy, R. J. (Tellus Series B-Chemical and Physical Meteorology, 2000)
The contribution of different moisture sources to Antarctic precipitation for present-day and glacial conditions is estimated with the NASA/GISS Atmospheric General Circulation Model. Despite its low horizontal resolution (8 degrees x 10 degrees), this model simulates reasonably well the broad features of the observed present-day hydrological cycle. Simulated present-day Antarctic precipitation is dominated throughout the year by moisture from a subtropical/midlatitude band (30 degrees S-60 degrees S). The moisture supplied to a given coastal area of Antarctica originates mostly in the adjacent oceanic basin; closer to the pole, other oceanic basins can also contribute significantly. Replacing the present-day sea surface temperatures (SSTs) and sea ice cover in the GCM with those from the CLIMAP oceanic reconstruction for the last glacial maximum (LGM), greatly increases the simulated latitudinal temperature gradient, with the consequence of slightly enhancing the contribution of low latitude moisture to Antarctic precipitation. It also changes the seasonality of the different contributions and thus their budget, particularly in coastal regions. Because the nature of LGM tropical SSTs is still under debate, Ne performed an additional LGM simulation in which the tropical SSTs are reduced relative to those of CLIMAP. The resulting decrease in the latitudinal gradient brings the relative contributions to Antarctic precipitation more in line with those of the present-day simulation.
id: 1942; PT: J; UT: WOS:000085432600002

Osmium isotopes demonstrate distal trnasport of contaminated sediments in Chesapeake Bay - Helz, G. R.; Adelson, J. M.; Miller, C. V.; Cornwell, J. C.; Hill, J. M.; Horan, M.; Walker, R. J. (Environmental Science Technology, 2000)
id: 1371

Paleoceanographic changes in the Southern Ocean (Pacific sector) during the last 14 Ka.--Poster - Morigi, C.; Capotondi, L.; Ravaioli, M.; Giglio, F.; Turi, B.; Brilli, M.; Langone, L. (Third International SO-JGOFS Symposium, 2000)
id: 1422

Postglacial climate and vegetation history, north-central Kola Peninsula, Russia: pollen and diatom records from Lake Yarnyshnoe-3 - Snyder, J. A.; MacDonald, G. M.; Forman, S. L.; Tarasov, G. A.; Mode, W. N. (Boreas, 2000)
A sediment core from Lake Yamyshnoe-3 (69 degrees 04'N; 36 degrees 04'E), an emerged coastal lake from the tundra of the north-central Kola Peninsula, has been analyzed for fossil pollen and diatoms. The pollen record shows the Younger Dryas event marked by increasing Artemisia coupled with decreases in Poaceae, Cyperaceae and Salix at c. 10 700 to 10 000 BP. This core provides the first well-defined palynological record of the Younger Dryas event on the Kola Peninsula. Stomates from Pinus were recovered from the core interval between 8000 and 6000 BP. The stomates, coupled with elevated values of pine pollen, indicate that Pinus sylvestris grew near the arctic coastline of the central Kola Peninsula in the middle Holocene. However, the small number of stomates suggests that pines were not plentiful. The diatom record from the core reflects basin isolation from the sea and indicates additional limnological changes during the climate transition between c. 5000 and 4000 BP. The broadly similar climate and vegetation history on the north-central Kola Peninsula and in Fennoscandia demonstrates the propagation of late glacial and Holocene climate events from the North Atlantic region into the Eurasian Arctic.
378dxTimes Cited:28 Cited References Count:82
Keywords: atlantic; finnish lapland; Holocene; late pleistocene; norway; sea; sediments; varanger-peninsula; western part; younger-dryas

Quaternary palaeohydrological evolution of a playa lake: Salada Mediana, central Ebro Basin, Spain - Valero-Garces, B. L.; Delgado-Huertas, A.; Navas, A.; Machin, J.; Gonzalez-Samperiz, P.; Kelts, K. (Sedimentology, 2000)
Sedimentary features, mineralogy, bulk geochemical composition, stable isotope analyses and pollen data from sediment cores were used to reconstruct the Late Quaternary depositional evolution of the Salada Mediana playa lake (central Ebro Basin, northeastern Spain). The 150-cm-long sediment core sequence is composed of gypsum- and dolomite-rich muds (Lower and Middle sections) and black, laminated, calcite-bearing sediments (Upper section). The Salada Mediana formed as a karstic depression in the Miocene gypsum substratum during the Late Pleistocene. The Lower section was deposited in a sulphate-carbonate saline lake that ended with a period of desiccation and basin floor deflation. Subsequent deposition (Middle section) took place in a playa-lake system. Two cycles of lower water table and expanded saline mud flats occurred. The Holocene sequence is missing, probably as a result of aeolian erosion. Sedimentation resumed only a few centuries ago, and saline pan environments dominated until modern times. The Salada Mediana facies succession was mainly governed by fluctuations in the hydrological balance, brine composition, and salinity; however, aeolian processes (detrital input and deflation) and recycling of previously precipitated salts also played a significant role.
383xwTimes Cited:31Cited References Count:76

The radiocarbon age of calcite dissolving at the sea floor: Estimates from pore water data - Martin, W. R.; McNichol, A. P.; McCorkle, D. C. (Geochimica Et Cosmochimica Acta, 2000)
We measured the radiocarbon content and stable isotopic composition of pore water and bottom water Sigma CO2, sedimentary organic carbon, and CaCO3 at two sites on the Ceara Rise, one underlying bottom water that is supersaturated with respect to calcite (Site B), the other underlying undersaturated bottom water (Site G). The results were combined with pore water O-2, Sigma CO2, and Ca2+ profiles (Martin and Sayles, 1996) to estimate the radiocarbon content of the CaCO3 that is dissolving in the sediment mixed layer. At Site G, the CaCO3 that is dissolving in the upper 2 cm of the sediments is clearly younger (richer in C-14) than the bulk sedimentary CaCO3, indicating that nonhomogeneous CaCO3 dissolution occurs there. The case for nonhomogeneous dissolution is much weaker at the site underlying supersaturated bottom water. The results indicate that nonhomogeneous dissolution occurs in sediments underlying undersaturated bottom water, that the dissolution is rapid relative to the rate of homogenization of the CaCO3 in the mixed layer by bioturbation, and that the dissolution rate of CaCO3 decreases as it ages in the sediment mixed layer. The results support the hypothesis, based on solid phase analyses, that the preferential dissolution of young (i.e., radiocarbon-rich) CaCO3 leads to a pattern of increasing radiocarbon age of mixed-layer CaCO3 as the degree of undersaturation of bottom water increases (Keir, 1984; Broecker et al., 1991). Copyright (C) 2000 Elsevier Science Ltd.
303ueTimes Cited:26Cited References Count:31

The radiocarbon content of individual lignin-derived phenols: Technique and initial results - McNichol, A. P.; Ertel, J. R.; Eglinton, T. I. (Radiocarbon, 2000)
We present a method for the isolation of phenolic compounds derived from lignin for radiocarbon analysis. These phenols are generated by chemical oxidation of polymeric materials and derivatized for separation and recovery by preparative capillary gas chromatography (PCGC). This technique yields tens of micrograms of pure, stable compounds that can he converted to graphite and analyzed by accelerator mass spectrometry (AMS). Analysis of model flavor compounds and dated woods indicates that, in most cases, the radiocarbon (C-14) contents of the individual compounds, corrected for the contribution of the derivative, agree with that of the bulk material to within 20 parts per thousand.
365vkTimes Cited:19 Cited References Count:17
Keywords: AMS; isotope-ratio; NOSAMS; oxidation-products

Radiocarbon dated Pinus sylvertis L. wood from beyond treeline on the Kola Peninsula, Russia - MacDonald, G. M.; Gervalis, B.; Snyder, J. A.; Tarasov, G. A.; Borisova, O. A. (The Holocene, 2000)
Radiocarbon dates were obtained from 24 samples of Pinus sylvestris L. (Scots pine) wood recovered from sites beyond the modern conifer tree-line on the Kola Peninsula of Russia. Twenty-one of the samples came from the shallow waters and eroding peats at the edges of two small lakes at 68°439N, 35°109E, located north of the modern conifer tree-line. Three samples came from a small pond located above the modern elevational limits of Pinus sylvestris at 68°259N, 35°199E. The radiocarbon dates indicate that pine trees grew approximately 20 km north of the mapped modern limits of the species from 6680 BP to 3830 BP. Pine trees were also growing some 40 m above their modern elevational limits between 5890 BP and 3450 BP. Nineteen of the samples date from 6680 BP to 5070 BP, suggesting that the density of trees north of the modern tree-line was greatest between 7000 and 5000 BP. The timing of tree-line advance and greatest density on the Kola Peninsula are in agreement with the results of similar studies from northern Fennoscandia which indicate that maximum northern and elevational extension of tree-line occurred between 7000 BP and 4000 BP. The general agreement between tree-line reconstructions suggests that the climatic changes that promoted mid-Holocene tree-line extension along the North Atlantic margins in northern Fennoscandia propagated eastward to the Kola Peninsula. The late timing of initial pine expansion on the Kola and in adjacent northern Fennoscandia remains problematic and may relate to lower winter insolation, temperature regimes in the adjacent oceans or slow rates of migration.
id: 376

The radiocarbon gradient at the Antarctic Polar Front - Schneider, R. J.; McNichol, A. P.; von Reden, K. F.; Elder, K. L.; Gagnon, A. R.; Key, R. M.; Quay, P. D.; Schlosser, P. M. (AGU Ocean Sciences Meeting, 2000)
id: 317

Radiocarbon-Based Estimates of the Groundwater Contribution to Estuarine Freshwater Budgets: An Example from Pages Creek, North Carolina - McCorkle, D. C.; Gramling, C. M.; Mulligan, A. E.; Woods, T. L.; Lott, D. E. (EOS, 2000)
id: 1315

Responces of a saline lake ecosystems in semi-arid regions to irrigation and climate variability. The history of Salada Chiprana, Central Ebro Basin, Spain - Valero-Garces, B. L.; Navas, A.; Machin, J.; Stevenson, T.; Davis, B. (Ambio, 2000)
id: 385

Shared Technologies: Later Stone Age Forager-Farmer Interaction and Metallurgy in the Ituri Rainforest, Democratic Republic of Congo - Mercader, J.; Rovira, S.; Gomez, P. (Azania, 2000)
id: 396

Stable- and radio-carbon isotopic composition of porewater DOC in an organic-rich marine sediment - Alperin, M. J.; Hee, C. A.; Albert, D. A.; Martens, C. S. (EOS, 2000)
id: 1438

Stable chlorine isotopic compositions of aroclors and aroclor-contaminated sediments - Reddy, C. M.; Heraty, L. J.; Holt, B. D.; Sturchio, N. C.; Eglinton, T. I.; Drenzek, N. J.; Xu, L.; Lake, J. L.; Maruya, K. A. (Environmental Science & Technology, 2000)
An exploratory investigation was conducted to evaluate if stable chlorine isotopic ratios of polychlorinated biphenyls (PCBs) could be useful in studying the processes that determine their transport and fate in the environment First, we determined the variability of delta(37)Cl in the source materials for PCBs. Second, we determined if the delta(37)Cl values of contaminated environmental samples fell outside the range in source variability. The isotopic variability among the source materials (Aroclors) was rather small; delta(37)- Cl values ranged from -3.37 to -2.11% (mean and standard deviation, -2.78 +/- 0.39%, n = 12). There was no correlation between the delta(37)Cl values and percentages of chlorine in the mixtures. We also found very similar values in several Clophen mixtures and one Phenoclor. The delta(37)Cl values in the total PCBs isolated from Aroclor-contaminated sediments from the Hudson River, New Bedford Harbor, and Turtle River Estuary ranged from -4.54 to -2.25% (n = 19). While most of the delta(37)Cl values were within 2 standard deviations of the mean Aroclor value (our assumed estimate for overall source variability), two of the PCB contaminated sediment samples from New Bedford Harbor did appear to be isotopically distinct. The PCBs in these sediments had lower amounts of less chlorinated congeners (when compared to the source material) and were likely isotopically affected by alteration processes that preferentially removed these congeners. Compound specific measurements of two congeners in Aroclor 1268 suggest that there are no large congener-specific differences in the stable chlorine isotope ratios in Aroclors. This study shows that the delta(37)Cl Values of PCBs may be a potentially useful diagnostic tool in studying the transport and fate of PCBs and indicates that additional research is warranted.
330rcTimes Cited:39Cited References Count:16

Ten years after - the WOCE AMS radiocarbon program - McNichol, A. P.; Schneider, R. J.; von Reden, K. F.; Gagnon, A. R.; Elder, K. L.; Key, R. M.; Quay, P. D. (Accelerator Mass Spectrometer Conference, 2000)
id: 316

Ten years after - The WOCE AMS radiocarbon program - McNichol, A. P.; Schneider, R. J.; von Reden, K. F.; Gagnon, A. R.; Elder, K. L.; Key, R. M.; Quay, P. D. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2000)
The National Ocean Sciences Accelerator Mass Spectrometry (NOSAMS) Facility is measuring all of the samples collected as part of the US WOCE Program - over 13,000 samples. We designed our extraction lines so that we also measure precise, oceanographically useful delta C-13-Sigma CO2 values. We have completed the analysis of samples from the Pacific and Southern Oceans and are processing those from the Indian Ocean now. At present, this constitutes the world's largest AMS data set. Reviews of the Pacific radiocarbon data are available and demonstrate the increased penetration of the "bomb signal" into the water column since the 1970s. Stable isotope data are being combined with those collected as part of NOAA's Ocean-Atmosphere Carbon Exchange Study to study the ocean's role in the anthropogenic CO2 cycle. The relationship of delta C-13 to other chemical tracers, e.g., PO4, O-2 and chlorofluorocarbons, will further our understanding of basic oceanographic processes. We present preliminary results from these studies as well as investigate the relationship of C-14 to C-13 in the ocean. (C) 2000 Elsevier Science B.V. All rights reserved.
372jrTimes Cited:14Cited References Count:12

Un registro de 8,000 anos del paleoclima del noroeste de Yucatan, Mexico - Brenner, M.; Leyden, B. W.; Curtis, J. H.; Medina-Gonzalez, R. M.; Dahlin, B. H. (Revista de la Universidad Autonoma de Yucatan, 2000)
id: 264
Keywords: Ciencias de la atmósfera; Geología; México; Paleoclima; Península de Yucatán; Yucatán

What can paired measurements of foraminifera d13C and sedimentary 231 Pa/230Th tell us about the link between thermohaline circulation and rapid climate oscillations? - McManus, J. F.; Francois, R.; Marchal, O. (EOS, 2000)
id: 169

A 0.5-million-year record of millennial-scale climate variability in the north atlantic - McManus, J. F.; Oppo, D. W.; Cullen, J. L. (Science, 1999)
Long, continuous, marine sediment records from the subpolar North Atlantic document the glacial modulation of regional climate instability throughout the past 0.5 million years. Whenever ice sheet size surpasses a critical threshold indicated by the benthic oxygen isotope (delta18O) value of 3.5 per mil during each of the past five glaciation cycles, indicators of iceberg discharge and sea-surface temperature display dramatically larger amplitudes of millennial-scale variability than when ice sheets are small. Sea-surface temperature oscillations of 1 degrees to 2 degreesC increase in size to approximately 4 degrees to 6 degreesC, and catastrophic iceberg discharges begin alternating repeatedly with brief quiescent intervals. The glacial growth associated with this amplification threshold represents a relatively small departure from the modern ice sheet configuration and sea level. Instability characterizes nearly all observed climate states, with the exception of a limited range of baseline conditions that includes the current Holocene interglacial.
McManusOppo Cullen eng 1999/02/12 03:03 Science. 1999 Feb 12;283(5404):971-5.

The Antarctic Radiocarbon Storage Ring - Schneider, Robert J.; McNichol, Ann P.; von Reden, Karl F.; Elder, Kathryn L.; Gagnon, Alan R.; Key, Robert M.; Quay, Paul D. (8th International Conference on Accelerator Mass Spectrometry, 1999)
id: 1791

Biogenic silica and organic carbon in sediments from the Pacific sector of the Southern Ocean.--Abstract - Giglio, F.; Frignani, M.; Langone, L.; Morigi, C.; Pianosi, G.; Ravaioli, M. (8th International Symposium on Antarctic Earch Sciences, 1999)
id: 286

Carbon isotopes as tracers of groundwater discharge into the coastal ocean: A preliminary study of saltmarsh groundwater from North Inlet, SC - Gramling, C. M.; McCorkle, D. C. (EOS, 1999)
id: 1314

Evidence for Late Pleistocene-Holocene Intermediate-Water variability in the North Atlantic - McManus, J. F.; Oppo, D. W.; Curry, W.; Marchitto, T.; Cullen, J. L. (EOS, 1999)
id: 172

Extreme 13C carb enrichment in ca. 2.0 Ga magnesite-stromatolite--dolomite--"red beds" association in a global context: a case for the world-wide signal enhanced by a local environment - Melezhik, Victor A.; Fallick, Anthony E.; Medvedev, Pavel V.; Makarikhin, Vladimir V. (Earth-Science Reviews, 1999)
id: 1567

Fault slip rates in the modern new madrid seismic zone - Mueller, K.; Champion, J.; Guccione, M.; Kelson, K. (Science, 1999)
Structural and geomorphic analysis of late Holocene sediments in the Lake County region of the New Madrid seismic zone indicates that they are deformed by fault-related folding above the blind Reelfoot thrust fault. The widths of narrow kink bands exposed in trenches were used to model the Reelfoot scarp as a forelimb on a fault-bend fold; this, coupled with the age of folded sediment, yields a slip rate on the blind thrust of 6.1 +/- 0.7 mm/year for the past 2300 +/- 100 years. An alternative method used structural relief across the scarp and the estimated dip of the underlying blind thrust to calculate a slip rate of 4.8 +/- 0.2 mm/year. Geometric relations suggest that the right lateral slip rate on the New Madrid seismic zone is 1.8 to 2.0 mm/year.
MuellerChampion Guccione Kelson eng 1999/11/05 Science. 1999 Nov 5;286(5442):1135-8.

The geochemistry of redox sensitive trace metals in sediments - Morford, J. L.; Emerson, S. (Geochimica Et Cosmochimica Acta, 1999)
We analyzed the redox sensitive elements V, Mo, U, Re and Cd in surface sediments from the Northwest African margin, the U.S. Northwest margin and the Arabian Sea to determine their response under a range of redox conditions. Where oxygen penetrates 1 cm or less into the sediments, Mo and V diffuse to the overlying water as Mn is reduced and remobilized. Authigenic enrichments of U, Re and Cd are evident under these redox conditions. With the onset of sulfate reduction, all of the metals accumulate authigenically with Re being by far the most enriched. General trends in authigenic metal accumulation are described by calculating authigenic fluxes for the 3 main redox regimes: oxic, reducing where oxygen penetrates less than or equal to 1 cm, and anoxic conditions. Using a simple diagenesis model and global estimates of organic carbon rain rate and bottom water oxygen concentrations, we calculate the area of sediments below 1000 m water depth in which oxygen penetration is less than or equal to 1 cm to be 4% of the ocean floor. We conclude that sediments where oxygen penetrates less than or equal to 1 cm release Mn, V and Mo to seawater at rates of 140%-260%, 60%-150% and 5%-10% of their respective riverine fluxes, using the authigenic metal concentrations and accumulation rates from this work and other literature. These sediments are sinks for Re, Cd and U, with burial fluxes of 70%-140%, 30%-80% and 20%-40%, respectively, of their dissolved riverine inputs. We modeled the sensitivity of the response of seawater Re, Cd and V concentrations to changes in the area of reducing sediments where oxygen penetrates less than or equal to 1 cm. Our analysis suggests a negligible change in seawater Re concentration, whereas seawater concentrations of Cd and V could have decreased and increased, respectively, by 5%-10% over 20 kyr if the area of reducing sediments increased by a factor of 2 and by 10%-20% if the area increased by a factor of 3. The concentration variations for a factor of 2 increase in the area of reducing sediments are at about the level of uncertainty of Cd/Ca and V/Ca ratios observed in foraminifera shells over the last 40 kyr. This implies that the area of reducing sediments in the ocean deeper than 1000 m (4%) has not been greater than twice the present value in the recent past. Copyright (C) 1999 Elsevier Science Ltd.
227ktTimes Cited:455Cited References Count:92

The Geochemistry of Redox Sensitive Trace Metals: Thesis - Morford, J. L. (University of Washington, 1999)

Glacial modulation of rapid climate change during the last 0.5 million years - McManus, J. F.; Oppo, D. W.; Cullen, J. L. (PAGES newsletter, 1999)
id: 168

Holocene Environmental changes in the Lake Erie Basis - Kepthorne, R. A.; Barrera, E.; Coakley, J. P.; Tevesz, M. J. S.; Miller, B. B. (International Association for Great Lakes Research Program and Abstract, 1999)
id: 249

Installation and First Results of a 134-Sample MC-SNICS Ion Source at NOSAMS - von Reden, K. F.; Schneider, R. J.; McNichol, A. P.; Elder, K. F.; Gagnon, A. R. (8th International Conference on Accelerator Mass Spectrometry, 1999)
id: 1802

Late Pleistocene-Holocene sea-level change and the New Jersey coastline - Miller, K. G.; Sugarman, P. J.; Sheridan, R. E.; Ashley, G. M. (Trans. Am. Geophys. Un., 1999)
id: 163

Late Quaternary stratigraphy of Marresale, Yamal Peninsula, Russia: new constraints on the footprint of the Eurasian ice sheet - Forman, S. L.; Ingolfsson, O.; Manley, W. F.; Lokrantz, H. (Geology, 1999)
id: 370

Millennial-scale climate changes in ventilation of the thermocline, intermediate and deep waters of the glacial North Atlantic - Curry, W. B.; Marchitto, T. M.; McManus, J. F.; Oppo, D. W.; L, Laarkamp K. (Geophysical Monograph series, 1999)
id: 207

New Developments at the NOSAMS Facility - von Reden, K. F.; Schneider, R. J.; McNichol, A. P.; Hayes, J. M.; Pearson, A.; Eglinton, T. I. (Proceeding of the International Workshop on Frontiers in Accelerator Mass Spectrometry, 1999)
id: 1723(JISTEC)

New Developments at the NOSAMS Facility - von Reden, K. F.; Schneider, R. J.; McNichol, A. P.; Hayes, J. M.; Pearson, A.; Eglinton, T. I. (International Workshop on Frontiers in Accelerator Mass Spectrometry, 1999)
id: 1679

Paleoceanographic changes in the Southern Ocean (Pacific Sector) during the last 14 ka.- -Abstract - Morigo, C.; Capotondi, L.; Ravaioli, M.; Giglio, F.; Turi, B.; Brilli, M.; Langone, L. (Third International SO-JGOFS Symposium, 1999)
id: 1426

Paleoenvironmental changes during the last 17,000 years in western Patagonia - Markgraf, V.; Bianchi, M. M. (Bamberger Geographische Schriften, 1999)
id: 1382

Paleoenvironments of Capitol Reef National Park reconstructed from fossil packrate middens - Cole, K. L.; Murray, L. K. (4th biennial Conference on Research on the Colorado Plateau, 1999)
id: 1369

Planktic foraminifera and oxygen isotope as proxies for paleoceanographic reconstruction in the Southern Ocean during the last deglacial time--Abstract - Morigi, C.; Capotondi, L.; Ravaioli, M.; Giglio, F.; Turi, B.; Brilli, M.; Frignani, M.; Langone, L. (Convegno Glaciologia e Paleoclima, 1999)
id: 1425

Reconstructing the oceanic 13C Suess effect - Sonnerup, R. E.; Quay, P. D.; McNichol, A. P.; Bullister, J. L.; Westby, T. A.; Anderson, H. L. (Global Biogeochemical Cycles, 1999)
id: 1710

Sedimentological and carbon-isotopic record of late Holocene climate in the sediments of Soda Lake Carrizo Plain, California. Abstracts - Eigenbrode, J. L.; Pratt, L. M.; Rhodes, D. D.; Arrowsmith, J. R.; Mora, G. (Geological Society of America, Annual Meeting, 1999)
id: 224

Sedimentological, carbon-isotopic, and molecular records of late Holocene climate in the sediments of Soda Lake, Carrizo Plain, California. Thesis - Eigenbrode, J.L.; Pratt, L.M.; Rhodes, D.D.; Arrowsmith, J.R.; Mora, G. (Indiana University, 1999)

Similar glacial and Holocene deep water circulation inferred from southeast Pacific benthic foraminiferal carbon isotope composition - Matsumoto, K.; Lynch-Stieglitz, J. (Paleoceanography, 1999)
We present Holocene and last glacial maximum (LGM) oxygen and carbon isotope measurements on Planulina wuellerstorfi in six southeast Pacific cores. Sedimentation rates are low in this part of the ocean, acid measurements were made on individual foraminiferal shells in order to identify the Holocene and glacial individuals on the basis of their extreme delta(18)O. The new delta(13)C data were combined with previous P. wuellerstorfi data for interpretation of global thermohaline circulation. Data from the Southern Ocean were examined closely for regional coherency and a few anomalous delta(13)C values suspected of having productivity overprint were removed. The resulting global delta(13)C distributions and gradients indicate that the deep water circulation was similar during the Holocene and LGM. This interpretation brings delta(13)C data to a better agreement with Cd/Ca data and marks a sharp contrast with a widely held view based on delta(13)C measurements that the glacial Southern Ocean was the terminus of the thermohaline circulation. The proposed presence of glacial North Atlantic Deep Water does not necessarily contradict the postulated presence of Glacial North Atlantic Intermediate Water.
179kdTimes Cited:61Cited References Count:90

Spatial distribution of carbon and oxygen isotopes in laterally extensive carbonate-cemented layers: Implications for mode of growth and subsurface identification - Klein, J. S.; Mozley, P.; Campbell, A.; Cole, R. (Journal of Sedimentary Research, 1999)
Carbonate concretions and laterally extensive cemented layers are common features in the Prairie Canyon Member of the Mancos Shale at its type locality in western Colorado. Stable-isotope and petrographic data were obtained from these cemented zones in an attempt to determine: (1) how the cemented layers form, (2) whether or not they can be chemically correlated, and (3) if it is possible to differentiate them from concretions in the subsurface. The cement in both the layers and concretions consists of ferroan dolomite and lesser amounts of stoichiometric dolomite and ankerite. Samples for stable-isotope analysis were drilled from 10 grids, with a typical grid spacing of 10 cm x 10 cm, Gridded samples were obtained from two continuous cemented layers at several locations along the layers (2.3 m to 1.5 km apart on the same layer), and from isolated and stratabound concretions,Taken together, all the cements (regardless of spatial position) show a remarkably linear correlation (R-2 = 0.98) between delta(13)C and delta(18)O, Systematic center-to-edge decreases in both delta(13)C and delta(18)O occur in each of the cemented zones and are persistent over lateral intervals of at least 1.5 km, The cores of the cemented zones have positive delta(13)C values (up to > 10 parts per thousand PDB), which result from incorporation of C-13-enriched carbon during methanogenesis. The edges of the cemented zones have negative delta(13)C values (down to < -9 parts per thousand PDB), which suggests incorporation of C-13-depleted carbon from thermocatalytic decarboxylation reactions. Oxygen isotope paleothermometry indicates that precipitation may have started at moderate temperatures (similar to 25 degrees C) and ended at temperatures as high as 92 degrees C,The spatial distribution of the isotopic data in the cemented layers can be explained as resulting from the coalescence of stratabound concretions, followed by growth above and below the coalesced concretions. Such growth may have occurred in a complex: manner, in which early cements precipitated throughout the thickness of the layer but were more abundant in the core zone. Given the lateral persistence of the pattern of isotopic variation in the cemented layers, geochemical correlation of the layers may be possible in the subsurface. In addition, because laterally persistent cemented layers in the Prairie Canyon Member exhibit patterns of isotopic variation different from concretions (layers have a more asymmetrical vertical distribution), it should be possible to distinguish between the two styles of cementation from subsurface core data alone.
A157gxTimes Cited:36Cited References Count:39

Ten Years After--The WOCE AMS Radiocarbon Program - McNichol, A.; Schneider, R.; von Reden, K.; Gagnon, A.; Elder, K.; Key, R.; Quay, P. (8th International Conference on Accelerator Mass Spectrometry, 1999)
id: 1757

Terrace Construction in Northern Chihuahua, Mexico at 1150 B.C. and the Present - Hard, R.; Roney, J.; Zapata, J.; Moses, B. (Journal of Field Archaeology, 1999)
id: 238

Variability in shallow- and intermediate-water hydrography during the last climate cycle of the Quaternary - McManus, J. F.; Healey, S. L.; Oppo, D. W.; Curry, W. B. (EOS, 1999)
id: 170

A 25,000-year tropical climate history from bolivian ice cores - Thompson, L. G.; Davis, M. E.; Mosley-Thompson, E.; Sowers, T. A.; Henderson, K. A.; Zagorodnov, V. S.; Lin, P.; Mikhalenko, V. N.; Campen, R. K.; Bolzan, J. F.; Cole-Dai, J.; Francou, B. (Science, 1998)
Ice cores that were recovered from the summit of Sajama mountain in Bolivia provide carbon-14-dated tropical records and extend to the Late Glacial Stage (LGS). Oxygen isotopic ratios of the ice decreased 5.4 per mil between the early Holocene and the Last Glacial Maximum, which is consistent with values from other ice cores. The abrupt onset and termination of a Younger Dryas-type event suggest atmospheric processes as the probable drivers. Regional accumulation increased during the LGS, during deglaciation, and over the past 3000 years, which is concurrent with higher water levels in regional paleolakes. Unlike polar cores, Sajama glacial ice contains eight times less dust than the Holocene ice, which reflects wetter conditions and extensive snow cover.
ThompsonDavis Mosley-Thompson Sowers Henderson Zagorodnov Lin Mikhalenko Campen Bolzan Cole-Dai Francou eng 1998/12/04 03:02 Science. 1998 Dec 4;282(5395):1858-64.

AMS measurement of - von Reden, K. F.; McNichol, A. P.; Pearson, A.; Schneider, R. J. (Sixteenth International Radiocarbon Conference, 1998)
id: 1643

AMS Measurement of small samples with high-current system: (Proceedings of the 16th International Radiocarbon Conference, 1997) - von Reden, K. F.; McNichol, A.; Pearson, A.; Schneider, R. (Radiocarbon, 1998)
id: 1815

Carbon cycling in sediments from the western equatorial Atlantic: Stable and radiocarbon isotopes in pore waters on the Ceara Rise - McNichol, A. P.; McCorkle, D. C.; Martin, W. R.; Berry, J. N. (EOS, 1998)
id: 108

Challenges in application of radiocarbon dating of organic carbon phases in opal-rich marine sediments from the Southern Ocean - Zheng, Y.; Anderson, R. F.; Froelich, P. N.; Beck, W.; McNichol, A. P.; Guilderson, T. (Trans. AGU 79, 1998)
id: 266

CO2 fluxes from mid-ocean ridges, arcs and plumes - Marty, B.; Tolstikhin, I. N. (Chemical Geology, 1998)
Estimates of CO2 emissions at spreading centres, convergent margins, and plumes have been reviewed and upgraded using observed CO2/He-3 ratios in magmatic volatiles, He-3 content estimates in the magmatic sources, and magma emplacement rates in the different tectonic settings. The effect of volatile fractionation during magma degassing, investigated using new rare gas and CO2 abundances determined simultaneously for a suite of Mid-Ocean Ridge (MOR) basalt glasses, is not the major factor controlling the spread of data, which mainly result from volatile heterogeneity in the mantle source. The computed C flux at ridges (2.2 +/- 0.9) x 10(12) mol/a, is essentially similar to previous estimates based on a mon restricted data base. Variation of the C flux in the past can be simply scaled to that of spreading rate since the computed C depends mainly on the volatile content of the mantle source, which can be considered constant during the last 10(8) a. The flux of CO2 from arcs may be approximated using the CO2/He-3 ratios of volcanic gases at arcs and the magma emplacement rate, assuming that the He-3 content of the mantle end-member is that of the MORE source. The resulting flux is similar to 2.5 x 10(12) mol/a, with approx. 80% of carbon being derived from the subducting plate. The flux of CO2 from plumes, based on time-averaged magma production rates and on estimated contributions of geochemical sources to plume magmatism, is less than or equal to 3 x 10(12) mol/a. Significant enhancements of the CO2 flux from plumes might have occurred in the past during giant magma emplacements, depending on the duration of these events, although the time-integrated effect does not appear important. The global magmatic flux of CO2 into the atmosphere and the hydrosphere is found to be 6 x 10(12) mol/a, with a range of (4-10) x 10(12) mol/a. Improvement on the precision of this estimate is linked to a better understanding of the volatile inventory at arcs on one hand, and on the dynamics of plumes and their mantle source contribution on the other hand. (C) 1998 Elsevier Science B.V. All rights reserved.
Zv404Times Cited:212Cited References Count:109

The concentration and isotopic composition of dissolved inorganic carbon in ground water and submarine ground water discharge: Preliminary results from Onslow Bay, NC and North Inlet, SC - McCorkle, D. C.; Gramling, C. (Conference on Southeast Coastal Ocean Research, 1998)
id: 1313

Controls of chemical and isotopic composition of Lake water, Peten, Guatemala and implications for Holocene climatic variability in Central America. Abstracts with Programs - Martin, J. B.; Rosenmeier, M. F.; Hodell, D. A.; Brenner, M.; Curtis, J. H. (Geological Society of America Annual Meeting, 1998)
id: 140

A Correction for Aberrations in the Woods Hole Recombinator. Symposium of North-Eastern Accelerator Personnel - Schneider, Robert J.; McNichol, Ann P.; von Reden, Karl F.; Elder, Kathryn L.; Gagnon, Allan R.; Key, Robert M.; Quay, Paul D. (World Scientific, 1998)
id: 1664

Early to middle Holocene climatic variability in Central America: evidence from lacustrine sediments in the Peten, Guatemala - Rosenmeier, M. F.; Hodel, D. A.; Martin, J. B.; Brenner, M.; Curtis, J. H. (EOS: Transactions American Geophysical Union, 1998)
id: 1209

Evaluating reproducibility of seawater, inorganic and organic carbon 14C results at the National Ocean Sciences AMS Facility (NOSAMS) - Elder, K. L.; McNichol, A. P.; Gagnon, A. R. (Radiocarbon, 1998)

Evidence for episodic calcium-carbonate dissolution in the subpolar North Atlantic during the last glaciation - McManus, J. F.; Lohmann, G. P. (EOS, 1998)
id: 171

High-precision Measurements of 14C as a Circulation Tracer in the Pacific, Indian, and Southern Oceans with Accelerator Mass Spectrometry (AMS) - von Reden, K. F.; Peden, J. C.; Schneider, R. J.; Bellino, M.; Donoghue, J.; Elder, K. L.; Gagnon, A. R.; Long, P.; McNichol, A. P.; Morin, T.; Stuart, D.; Hayes, J. M.; et al. (8th International Conference on Heavy Ion Accelerator Technology, 1998)
id: 1636

Holocene Evolution of Lake Erie Environments: inferrences from stable isotopes of cored sediments offshore Fairport Harbor, Ohio--Thesis - McCambridge, Constance (University of Akron, 1998)

How much deep water is formed in the Southern Ocean? - Broecker, W. S.; Peacock, S. L.; Walker, S.; Weiss, R.; Fahrbach, E.; Schroeder, M.; Mikolajewicz, U.; Heinze, C.; Key, R.; Peng, T. H.; Rubin, S. (Journal of Geophysical Research-Oceans, 1998)
Three tracers are used to place constraints on the production rate of ventilated deep water in the Southern Ocean. The distribution of the water mass tracer PO4* ("phosphate star") in the deep sea suggests that the amount of ventilated deep water produced in the Southern Ocean is equal to or greater than the outflow of North Atlantic Deep Water from the Atlantic. Radiocarbon distributions yield an export flux of water from the North Atlantic which has averaged about 15 Sv over the last several hundred years. CFC inventories are used as a direct indicator of the current production rate of ventilated deep water in the Southern Ocean. Although coverage is as yet sparse, it appears that the CFC inventory is not inconsistent with the deep water production rate required by the distributions of PO4* and radiocarbon. It has been widely accepted that the major part of the deep water production in the Southern Ocean takes place in the Weddell Sea. However, our estimate of the Southern Ocean ventilated deep water flux is in conflict with previous estimates of the flux of ventilated deep water from the Weddell Sea, which lie in the range 1-5 Sv. Possible reasons for this difference are discussed.
Zz547Times Cited:115Cited References Count:44

Impact of human activity on regional forest composition and dynamics in central New England - Fuller, T. L.; Foster, D. R.; McLachlan, T. S.; Drake, N. (Ecosystems, 1998)
Historical and ecological data from north-central Massachusetts suggest that widespread and intensive human disturbance after European settlement led to a shift in forest composition and obscured regional patterns of species abundance. A paleoecological approach was required to place recent forest dynamics in a long-term context. Pollen and charcoal data from 11 small lakes in north-central Massachusetts were used to reconstruct local vegetation dynamics and fire histories across the region over the past 1000 years. The sites are located across an environmental gradient. Paleoecological data indicate that prior to European settlement, there was regional variation in forest composition corresponding to differences in climate, substrate, and fire regime. Oak, chestnut, and hickory were abundant at low elevations, whereas hemlock, beech, sugar maple, and yellow birch were common at high elevations. Fire appears to have been more frequent and/or intense at lower elevations, maintaining high abundances of oak, and archaeological data suggest Native American populations were greater in these areas. A change in forest composition at higher elevations, around 550 years before present, may be related to the Little Ice Age (a period of variable climate), fire, and/or activity by Native Americans, and led to regional convergence in forest composition. After European settlement, forest composition changed markedly in response to human disturbance and there was a sharp increase in rates of vegetation change. Regional patterns were obscured further, leading to homogenization of broad-scale forest composition. There is no indication from the pollen data that forests are returning to pre-European settlement forest composition, and rates of vegetation change remain high, reflecting continuing disturbance on the landscape, despite regional reforestation.
Keywords: awenda provincial park; eastern north-america; european settlement; forest dynamics; history; human disturbance; lake sediment; land-use; new england; paleoecology; patterns; rates of change; united-states; vegetation dynamics

Late Holocene climatic variability in Central America: evidence from lacustrine sediments in the Peten, Guatemala and implications for Maya cultural evolution; Procedings of the PEP 1 - Rosenmeier, M. F.; Hodell, D. A.; Martin, J. B.; Brenner, M.; Curtis, J. H. (PEP 1 (Pole-Equator-Pole, Paleoclimate of the Americas), 1998)
id: 141

Microscale AMS 14C Measurement at NOSAMS - Pearson, Ann; McNichol, Ann P.; Schneider, Robert J.; von Reden, Karl F. (16th International 14C Conference, 1998)
id: 1502

Microscale AMS 14C measurements at NOSAMS - Pearson, A.; McNichol, A. P.; Schneider, R. J.; von Reden, K. F.; Zheng, Y. (Radiocarbon, 1998)
id: 1621

Microscale AMS 14C measurements at NOSAMS: (Proceedings of the 16th International Radiocarbon Conference, 1997) - Pearson, A.; McNichol, A. P.; Schneider, R. J.; von Reden, K. F.; Zheng, Y. (Radiocarbon, 1998)
id: 1814

Microscale AMS (super 14) C measurement at NOSAMS - Pearson, Ann; McNichol, Ann P.; Schneider, Robert J.; von Reden, Karl F.; Zheng, Yan (University of Arizona, Department of Geosciences, Tucson, AZ, United States (USA), 1998)
Techniques for making precise and accurate radiocarbon accelerator mass spectrometry (AMS) measurements on samples containing less than a few hundred micrograms of carbon are being developed at the NOSAMS facility. A detailed examination of all aspects of the sample preparation and data analysis process shows encouraging results. Small quantities of CO (sub 2) are reduced to graphite over cobalt catalyst at an optimal temperature of 605 degrees C. Measured (super 14) C/ (super 12) C ratios of the resulting targets are affected by machine-induced isotopic fractionation, which appears directly related to the decrease in ion current generated by the smaller sample sizes. It is possible to compensate effectively for this fractionation by measuring samples relative to small standards of identical size. Examination of the various potential sources of background (super 14) C contamination indicates that the sample combustion process is the largest contributor, adding ca. 1 mu g of carbon with a less-than-modern (super 14) C concentration.
id: 2237; Source type: conferencepapers&proceedings; Object type: Article; Object type: Conference Paper; Copyright: GeoRef, Copyright 2007, American Geological Institute.; CSAUnique: 1999-044438; AccNum: 1999-044438; ISSN: 0033-8222; CODEN: RACAAT
Keywords: 03; absolute age; accelerator mass spectroscopy; accuracy; C-14; C-14/C-12; carbon; Carbon dioxide; combustion; data processing; Geochronology; graphite; isotope fractionation; isotopes; mass spectroscopy; mathematical methods; methods; native elements; radioactive isotopes; sample preparation; size; spectroscopy; Stable isotopes

Millennial-scale changes in North Atlantic circulation since the last glaciation - Marchitto, T. M.; Curry, W. B.; Oppo, D. W. (Nature, 1998)
Ocean circulation is closely linked to climate change on glacial-interglacial and shorter timescales. Extensive reorganizations in the circulation of deep and intermediate-depth waters in the Atlantic Ocean have been hypothesized for both the last glaciation(1-6) and the subsequent Younger Dryas cold interval(3,6-10), but there has been little palaeoceanographic study of the subtropical gyres(11-13). These gyres are the dominant oceanic features of wind-driven circulation, and as such they reflect changes in climate and are a significant control on nutrient cycling and, possible, atmospheric CO2 concentrations. Here we present Cd/Ca ratios in the shells of benthic foraminifera from the Bahama banks that confirm previous suggestions(11,12) that nutrient concentrations in the North Atlantic subtropical gyre were much lower during the Last Glacial Maximum than they are today (up to 50% lower according to our data). These contrasting nutrient burdens imply much shorter residence times for waters within the thermocline of the Last Glacial Maximum. Below the glacial thermocline, nutrient concentrations were reduced owing to the presence of Glacial North Atlantic Intermediate Water. A high-resolution Cd/Ca record from an intermediate depth indicates decreased nutrient concentrations during the Younger Dryas interval as well, mirroring opposite changes at a nearby deep site(3,9). Together, these observations suggest that the formation of deep and intermediate waters-North Atlantic Deep Water and Glacial North Atlantic Intermediate Water, respectively-wax and wane alternately on both orbital and millennial timescales.
Zt988Times Cited:106Cited References Count:30

North Atlantic gyre ventilation and intermediate water formation during the last glaciation and Younger Dryas - Marchitto, T. M.; Curry, W. B.; W, Oppo D. (Nature, 1998)
id: 208

The NOSAMS Sample Preparation Laboratory: Systems and graphite performance analysis - Gagnon, A. R.; McNichol, A. P.; Donaghue, J. C.; Morin, T. J.; Peden, J. C. (16th International 14C Conference, 1998)
id: 1628

Overview of the eruption of Soufriere Hills volcano, Montserrat, 18 July 1995 to December 1997 - Young, S. R.; Sparks, R. S. J.; Aspinall, W. P.; Lynch, L. L.; Miller, A. D.; Robertson, R. E. A.; Shepherd, J. B. (Geophysical Research Letters, 1998)
The onset of phreatic volcanic activity at the Soufriere Hills volcano, Montserrat on 18 July 1995 followed a three-year period of heightened volcano-seismic activity beneath the island. Phreatic explosions gave way to continuous eruption of juvenile andesitic magma in the form of a lava dome on or around 15 November 1995. Magma production rate has varied, leading to changes in eruptive style. An explosive eruption on 17 September 1996 followed a period of enhanced dome growth and large-scale gravitational collapses from its eastern flank. Increasing dome volume led to stressing and overtopping of the confining crater walls to the southwest, north and west during early 1997. Sustained high magma production rate since June 1997 has led to three periods of major gravitational dome collapses followed by vulcanian explosive eruptions. Dome growth re-started immediately after the cessation of the latest of these explosive phases in October 1997 and continues as of December 1997.
119mkTimes Cited:102Cited References Count:7

Physical controls on dissolved inorganic radiocarbon variability in the California Current - Masiello, C. A.; Druffel, E. R. M.; Bauer, J. E. (Deep-Sea Research Part Ii-Topical Studies in Oceanography, 1998)
We present depth profiles of Delta(14)C and delta(13)C Of dissolved inorganic carbon (DIC) at Station M in the Eastern North Pacific. Several seasonal profiles are presented for the time period between 1991 and 1996. Comparison with GEOSECS data clearly shows changes in ocean radiocarbon profiles since 1973. The Delta(14)C Of DIC shows the most variability at depths of 450, 85, and 25 m, and the lowest variability at depths of 1600 and 2500 m. The largest variability in DIC Delta(14)C occurs at 450 m, a depth marked by large fluctuations in the radiocarbon signatures of the source waters. The likely controls of DIC Delta(14)C variability are physical changes in the circulation of the California Current System. A simple two-box model is used to show the importance of wind driven mixing at the surface. We discuss the likely effects of mesoscale eddies and ENSO on the DIC Delta(14)C values at this site. We also show that remineralization of organic carbon (dissolved or particulate) is not responsible for the variability in the Delta(14)C Of DIC observed at Station M. (C) 1998 Elsevier Science Ltd. All rights reserved.
102ttTimes Cited:21Cited References Count:43

Preparation for continuous flow accelerator mass spectrometry Radiocarbon - Schneider, R. J.; Hayes, J. M.; von Reden, K. F.; McNichol, A. P.; Eglinton, T.; Wills, J. S. C. (Radiocarbon, 1998)
id: 1623

Radiometrically determined sedimentary fluxes in the sub-polar North Atlantic during the last 140,000 years - McManus, J. F.; Anderson, R. F.; Broecker, W. S.; Fleisher, M. Q.; Higgins, S. M. (Earth and Planetary Science Letters, 1998)
We have examined the record of sediment input during the last 140000 years in a deep-sea core from 49 degrees 27'N, 22 degrees 16'W in the eastern North Atlantic. Using uranium-series disequilibria to constrain time, we have calculated mass fluxes of total sediment, as well as mass and particle fluxes of major sedimentary components. Sediment accumulation rates were generally lower and relatively constant during broadly defined interglacial intervals, driven primarily by the burial of biogenic material. Accumulation rates were higher and more variable during glacial intervals, and were influenced primarily by terrigenous material. Peaks in bulk mass fluxes were associated with particular episodes (Heinrich events) within the last glacial and during each of the last two deglaciations. The flux of ice-rafted debris, as uniquely identified by coarse detrital fragments, was higher during layers representing each of the glacial Heinrich events, with modest increases during events H3 and H6 and dramatic increases during the others, confirming the widespread interpretation of these layers as episodes of enhanced iceberg delivery. The burial flux of foraminifera was markedly lower during each of the glacial Heinrich events, also confirming the original identification of these layers as barren intervals. Ice-rafting events within marine isotope stage 5 left neither a large detrital nor biogenic flux imprint at our study site. Variations in the burial rates of non-carbonate sediments were largely responsible for overall changes in sediment accumulation throughout the last climate cycle. Ice-rafting was apparently an important delivery mechanism for this terrigenous material. The instantaneous chronometer established here for the last 140000 years in the subpolar North Atlantic allows the transformation of existing and subsequent data from relative values to absolute burial fluxes. (C) 1998 Elsevier Science B.V.
Ze160Times Cited:70Cited References Count:55

Reproducibility of seawater, inorganic and organic 14C results at NOSAMS - Elder, K. L.; McNichol, A. P.; Gagnon, A. R. (Sixteenth International 14C Conference, 1998)
id: 1625

Status Report of the National Ocean Sciences AMS Facility at Woods Hole Oceanographic Institution: Operations and Recent Developments - Bellino, M.; von Reden, K. F.; Schneider, R. J.; Peden, J. C.; Donoghue, J.; Elder, K. L.; Gagnon, A. R.; Long, P.; McNichol, A. P.; Odegaard, A. P.; Stuart, D.; Handwork, S.; et al. (15th International Conference on the Applications of Accelerators in Research and Industry, 1998)
id: 1647

(super 14) C AMS measurements of - von Reden, Karl F.; McNichol, Ann P.; Pearson, Ann; Schneider, Robert J. (University of Arizona, Department of Geosciences, Tucson, AZ, United States (USA), 1998)
The NOSAMS facility at Woods Hole Oceanographic Institution has started to develop and apply techniques for measuring very small samples on a standard Tandetron accelerator mass spectrometry (AMS) system with high-current hemispherical Cs sputter ion sources. Over the past year, results on samples ranging from 7 to 160 mu g C showed both the feasibility of such analyses and the present limitations on reducing the size of solid carbon samples. One of the main factors affecting the AMS results is the dependence of a number of the beam optics parameters on the extracted ion beam current. The extracted currents range from 0.5 to 10 mu A of (super 12) C (super -) for the sample sizes given above. We here discuss the setup of the AMS system and methods for reliable small-sample measurements and give the AMS-related limits to sample size and the measurement uncertainties.
id: 2239; Source type: conferencepapers&proceedings; Object type: Article; Object type: Conference Paper; Copyright: GeoRef, Copyright 2007, American Geological Institute.; CSAUnique: 1999-044459; AccNum: 1999-044459; ISSN: 0033-8222; CODEN: RACAAT
Keywords: 03; absolute age; accelerator mass spectroscopy; C-14; carbon; dilution; Geochronology; ions; isotopes; mass spectroscopy; precision; radioactive isotopes; sample preparation; spectroscopy; volume

Target preparation for continuous flow accelerator mass spectrometry - Schneider, R. J.; Hayes, J. M.; von Reden, K. F.; McNichol, A. P.; Eglinton, T. I.; Wills, J. S. C. (Radiocarbon, 1998)
For very small samples, it is difficult to prepare graphitic targets that will yield a useful and steady sputtered ion beam. Working with materials separated by preparative capillary gas chromatography, we have succeeded with amounts as small as 20 mu g C. This seems to be a practical limit, as it involves 1) multiple chromatographic runs with trapping of effluent fractions, 2) recovery and combustion of the fractions, 3) graphitization and 4) compression of the resultant graphite/cobalt matrix into a good sputter target. Through such slow and intricate work, radiocarbon ages of lignin derivatives and hydrocarbons from coastal sediments have been determined. If this could be accomplished as an "online" measurement by flowing the analytes directly into a microwave gas ion source, with a carrier gas, then the number of processing steps could be minimized. Such a system would be useful not just for chromatographic effluents, but for any gaseous material, such as CO2 produced from carbonates. We describe tests using such an ion source.
1 Sp. Iss. SI113kt Times Cited:11 Cited References Count:10
Keywords: gas; ion-source

Technology revolutionizes tracer oceanography during WOCE - Key, R. M.; McNichol, A. (International WOCE Newsletter, 1998)
id: 324

Un registro de 6,000 anos de manifestaciones intensas del fenomeno de El Nino en sedimentos de lagunas de las Islas Galapagos - Steinitz-Kannan, M.; Riedinger, M. A.; Last, W. M.; Brenner, M.; Miller, M. C. (Bulletin de l'Institut Francais d'Etudes Andines, 1998)
id: 196

14C AMS measurement of C AMS measurement of C AMS measurement of - von Reden, K.; McNichol, A.; Pearson, A.; Schneider, R. (16th International Radiocarbon Conference, Groningen, 1997)
id: 952

An abrupt drowning of the Black Sea shelf - Ryan, W. B. F.; Pitman, W. C.; Major, C. O.; Shimkus, K.; Moskalenko, V.; Jones, G. A.; Dimitrov, P.; Gorur, N.; Sakinc, M.; Yuce, H. (Marine Geology, 1997)
During latest Quaternary glaciation, the Black Sea became a giant freshwater lake. The surface of this lake drew down to levels more than 100 m below its outlet. When the Mediterranean rose to the Bosporus sill at 7,150 yr BP1, saltwater poured through this spillway to refill the lake and submerge, catastrophically, more than 100,000 km(2) of its exposed continental shelf. The permanent drowning of a vast terrestrial landscape may possibly have accelerated the dispersal of early neolithic foragers and farmers into the interior of Europe at that time. (C) 1997 Elsevier Science B.V.
Xj245Times Cited:283Cited References Count:35

AMS measurements of the 14C distribution in the Pacific Ocean - von Reden, K. F.; McNichol, A. P.; Peden, J. C.; Elder, K. L.; Gagnon, A. R.; Schneider, R. J. (Nuclear Instruments and Methods in Physics Research, 1997)
id: 1673

AMS measurements of the 14C distribution in the Pacific Ocean - von Reden, K. F.; McNichol, A. P.; Peden, J. C.; Elder, K. L.; Gagnon, A. R.; Schneider, R. J. (Proceedings of the Seventh International Conference on Accelerator Mass Spectrometry, 1997)
id: 1644; B123

Biostratigraphy and sedimentation rates of the Amazon Deep Sea Fan - Mikkelsen, N.; Maslin, M.; Firaudeau, J.; Showers, W. J. (Proceedings of the Ocean Drilling Program: Scientific Results, 1997)
id: 71

Carbon isotopic fractionation associated with lipid biosynthesis by a cyanobacterium: relevance for interpretation of biomarker records - Sakata, S.; Hayes, J. M.; McTaggart, A. R.; Evans, R. A.; Leckrone, K. J.; Togasaki, R. K. (Geochim Cosmochim Acta, 1997)
For the cyanobacterium Synechocystis UTEX 2470, grown photoautotrophically to a logarithmic stage of growth, the total lipid extract is depleted in 13C by 4.8% relative to average biomass. Depletions observed for acetogenic (straight-chain) lipids range from 7.6 (hexadecanoic acid) to 9.9% (a C16 n-alkyl chain bound in a polar-lipid fraction), with a mass-weighted average of 9.1%. Polyisoprenoid lipids fall into two isotopic groups, with phytol, diplopterol, and diploptene depleted by 6.4-6.9% and bishomohopanol (produced from the extracts by the preparative degradation of bacteriohopanepolyol) depleted by 8.4%. Analysis of the pattern of depletions indicates that two carbon positions in each C5 biomonomer leading to polyisoprenoid products are probably depleted in 13C relative to average biomass. The depletion of bacteriohopanepolyol relative to other polyisoprenoids can be ascribed to changes that occur over the life of each cell: (1) the 13C content of carbon flowing to lipid biosynthesis decreases as the cell size increases and (2) a greater proportion of the bacteriohopanepolyol which, unlike other polyisoprenoids, is present mainly in the cytoplasm rather than in membranes and is synthesized when cells are larger. Chlorophyll a is depleted relative to average biomass by O.7%. Given the observed depletion of 13C in phytol, the heteroaromatic, chlorophyllide portion of chlorophyll must be enriched in 13C by 2.7%. This enrichment is large relative to that in chlorophyllides produced by eukaryotes and may be related to a parallel enrichment of 13C in cyanobacterial glutamic acid. As in many previous investigations of cyanobacterial lipids, long-chain n-alkanes (C22-C29) are found in the extracts. They are, however, enriched in 13C relative to biomass and have isotopic compositions suggesting that they are contaminants of petrochemical origin. Available results indicate that cyanobacterial lipids will be depleted relative to dissolved CO2 that has served as a carbon source by 22-30% and that a wider range of depletions will be characteristic of eukaryotic products. The absence of long-chain n-alkanes in cyanobacteria reduces the possibility that petroleum ever formed from pre-eukaryotic sedimentary debris.
Sakata, SHayes, J M McTaggart, A R Evans, R A Leckrone, K J Togasaki, R K eng Research Support, U.S. Gov't, Non-P.H.S. 1997/01/01 00:00 Geochim Cosmochim Acta. 1997;61(24):5379-89.
Keywords: *Biomass; Acetic Acid/metabolism; Alkanes/*analysis/chemistry; Biomarkers/chemistry; carbon isotopes; Carbon/*chemistry; Chlorophyll/metabolism; Cyanobacteria/chemistry/*metabolism; Geologic Sediments/*chemistry; Lipids/*biosynthesis; NASA Discipline Exobiology; Non-NASA Center; Palmitic Acid/metabolism; Phytol/metabolism; Pigments, Biological/metabolism

Consistent Fractionation of 13C in Nature and in the Laboratory: Growth-rate Effects in Some Haptophyte Algae - Bidigare, Robert R.; Fluegge, Arnim; Freeman, Katherine H.; Hanson, Kristi L.; Hayes, John M.; Hollander, David; Jasper, John P.; King, Linda L.; Laws, Edward A.; Milder, Jeffrey; Millero, Frank J.; Pancost, Richard; et al. (Global Biogeochemical Cycles, 1997)
The carbon isotopic fractionation accompanying formation of biomass by alkenone-producing algae in natural marine environments varies systematically with the concentration of dissolved phosphate. Specifically, if the fractionation is expressed by єP ≈ δe − δp, where δe and δp are the δ13C values for dissolved CO2 and for algal biomass (determined by isotopic analysis of C37 alkadienones), respectively, and if Ce is the concentration of dissolved CO2, μmol kg−1, then b = 38 + 160*[PO4], where [PO4] is the concentration of dissolved phosphate, μM, and b = (25 − єp)Ce. The correlation found between b and [PO4] is due to effects linking nutrient levels to growth rates and cellular carbon budgets for alkenone-containing algae, most likely by trace-metal limitations on algal growth. The relationship reported here is characteristic of 39 samples (r2 = 0.95) from the Santa Monica Basin (six different times during the annual cycle), the equatorial Pacific (boreal spring and fall cruises as well as during an iron-enrichment experiment), and the Peru upwelling zone. Points representative of samples from the Sargasso Sea ([PO4] ≤ 0.1 μM) fall above the b = f[PO4] line. Analysis of correlations expected between μ (growth rate), єp, and Ce shows that, for our entire data set, most variations in єp result from variations in μ rather than Ce. Accordingly, before concentrations of dissolved CO2 can be estimated from isotopic fractionations, some means of accounting for variations in growth rate must be found, perhaps by drawing on relationships between [PO4] and Cd/Ca ratios in shells of planktonic foraminifera.
id: 1727

Determination of the radiocarbon ages of individual PAH extracted from urban aerosol and marine sediment - Pearson, A.; Eglinton, T. I.; McNichol, A. P.; Currie, L. A.; Schneider, R. J.; von Reden, K. F.; Benner, B. A.; Wise, S. A. (16th International Radiocarbon Conference, 1997)
id: 951

Detritus dynamics in the seagrass Posidonia oceanica: Elements for an ecosystem carbon and nutrient budget - Mateo, M. A.; Romero, J. (Marine Ecology-Progress Series, 1997)
Leaf decay, leaf Litter export, burial in belowground sinks, and respiratory consumption of detritus were examined at 2 different depths in a Posidonia oceanica (L.) Delile meadow off the Medes Islands, NW Mediterranean. At 5 m, the amount of exported leaf Litter represented carbon, nitrogen and phosphorus losses of 7, 9 and 6 % of the plant primary production, respectively. About 26 % of the carbon produced by the plant in 1 yr was immobilized by burial in the belowground compartment, i.e. as roots and rhizomes. Annual nitrogen and phosphorus burial in the sediment was 8 and 5 % of total N and P needs, respectively. Respiratory consumption (aerobic) of carbon leaf detritus represented 17% of the annual production. An additional, but very substantial, loss of carbon as very fine particulate organic matter has been estimated at ca 48%. At 13 m the pattern of carbon losses was similar, but the lesser effect of wave action (relative to that at 5 m) reduced exportation, hence increasing the role of respiratory consumption. Data on carbon losses indicated that only a small part of the plant production was actually available to fuel the food web of this ecosystem. Total nutrient losses were in the range of 21 to 47 % of annual needs. From differences found in N and P concentrations between living and dead tissues, it is suggested that important nutrient recycling (50 to 70%) may be due either to reclamation or to leaching immediately after plant death.
id: 2004; PT: J; UT: WOS:A1997XE68700005

Evaluating reproducibility of seawater, inorganic and organic carbon 14C results at the National Ocean Sciences AMS Facility (NOSAMS) - Elder, K. L.; McNichol, A. P.; Gagnon, A. R. (16th International Radiocarbon Conference, 1997)
id: 956

The first trans-Arctic 14C section: comparison of the mean ages of the deep waters in the Eurasian and Canadian basins fo the Arctic Ocean - Schlosser, Peter; Kromer, Bernd; Ekwurzel, Brenda; Bonisch, Gerhard; McNichol, Ann; Schneider, Robert; von Reden, Karl; Ostlund, H. G.; Swift, J. H. (Nuclear Instruments and Methods in Physics Research, 1997)
id: 67

The first trans-Arctic 14C section: comparison of the mean ages of the deep waters in the Eurasian and Canadian Basins of the Arctic Ocean; in Proceedings of the 7th International Conference on Accelerator Mass Spectrometry - Schlosser, P.; Kromer, B.; Ekwurzel, B.; Bonisch, G.; McNichol, A.; Schneider, R.; von Reden, K.; Ostlund, H.; Swift, J. (Nuclear Instruments and Methods, 1997)
id: 1751

Holocene Evolution of Lake Erie Environments - McCambridge, C.; Barrera, E.; Tevesz, M.; Fuller, J. (Geological Society of America, Abstracts with Programs, 1997)
id: 250

Isotopic stratigraphy of Amazon Fan sediments - Showers, W. J.; Schneider, R.; Mikkelsen, N.; Maslin, M. (Proceedings of the Ocean Drilling Program: Scientific Results, 1997)
id: 1277

Late Quaternary Western Atlantic Paleoceanography and terrigenous sedimentation on the Amazon Fan: a view from delta d180 and d13C of planktonic foraminifera and bulk organic matter d13C - Schneider, R. R.; Muller, P. J.; Schlunz, B.; Segl, M.; Showers, W. J.; Wefer, G. (Proceedings of the Ocean Drilling Program: Scientific Results, 1997)
id: 1278

Mass transport deposits of Amazon Fans - Piper, D. J.; Pirmez, C.; Flood, R.; Long, D.; Manely, P.; Normark, W.; Showers, W. (Proceedings of the Ocean Drilling Program: Scientific Results, 1997)
id: 1279

The National Ocean Sciences AMS (NOSAMS) Sample Preparation Laboratory: Systems and Graphite Performance Analysis - Gagnon, A. R.; McNichol, A. P.; Donoghue, J. C.; Morin, T. J.; Peden, J. C. (International Radiocarbon Conference, 1997)
id: 962

The NOSAMS sample preparation laboratory: overview of systems and techniques - Gagnon, A. R.; McNichol, A.; Donoghue, J. C.; Merkle, K. M.; Morin, T. J. (16th International Radiocarbon Conference, 1997)
id: 955

Paleoclimatic implications of silicieous microfossil succession in late Quaternary sediments in Lake Baikal, Siberia - Julius, M. L.; Stoermer, E. F.; Colman, S. M.; Moore, T. C. (Journal of Paleolimnology, 1997)
id: 1354

Postglacial relative sea level history from sediment and diatom rcords of emerged coastal lakes, north-central Kola Peninsula, Russia - Snyder, J. A.; Forman, S. L.; Mode, W. N.; Tarasov, G. A. (Boreas, 1997)
id: 379

Precise temporal correlation of Holocene mollusc shells using sclerochronology - Marchitto, T. M.; Jones, G. A.; Goodfriend, G. A.; Weidman, C. R.; Jirikowic, J. (Palaeogeography, Paleoclimatology, Paleoecology, 1997)
id: 1293

Preliminary results of the first drilling on Lake Baikal, Buguldeika site, southeastern Siberia - Baikal Members, B. D. Drilling Project (Quaternary International, 1997)
The Baikal Drilling Project (BDP) is a multinational effort to investigate the paleoclimatic history and tectonic evolution of the Baikal sedimentary basin during the Late Neogene. In March 1993 the Baikal drilling system was successfuly deployed from a barge frozen into position over a topographic high, termed the Buguldeika saddle, in the southern basin of Lake Baikal. The BDP-93 scientific team, made up of Russian, American and Japanese scientists, successfully recovered the first long (>100 m) hydraulic piston cores from two holes in 354 m of water. High quality cores of 98 m (Hole 1) and 102 m (Hole 2), representing sedimentation over the last 500,000 years, were collected in 78 mm diameter plastic liners with an average recovery of 72% and 90%, respectively. Magnetic susceptibility logging reveals an excellent hole-to-hole correlation. In this report the scientific team describes the preliminary analytical results from BDP-93 hole 1 cores. Radiocarbon dating by accelerator mass spectrometry provides an accurate chronology for the upper portion of Hole 1. Detailed lithologic characteristics, rock magnetic properties and inorganic element distributions show a significant change to the depositional environment occuring at 50 m subbottom depth, approximately 250,000 BP. This change may be due to uplift and rotation of the horst block in the Buguldeika saddle. The sedimentary section above 50 m is pelitic with varve-like laminae, whereas the section below 50 m contains a high proportion of sand and gravel horizons often organized into turbidite sequences. Accordingly, high resolution seismic records reveal a change in sonic velocity at this depth. It is inferred that sedimentation prior to 250 ka BP was from the west via the Buguldeika river system. After 250 ka BP the Buguldeika saddle reflects an increase in hemipelagic sediments admixed with fine-grained material from the Selenga River drainage basin, east of Lake Baikal. Variations in the spore-pollen assemblage, diatoms, biogenic silica content, rock magnetic properties, clay mineralogy and organic carbon in the upper 50 m of BDP-93-1 reveal a detailed record of climate change over approximately the last 250,000 years. These variables alternate in a pattern characteristic of glacial/interglacial climatic fluctuations. The present age model suggests that the climate signal recorded in Lake Baikal sediments is similar to Late Quaternary signals recorded in Chinese loess sections and in marine sediments.
id: 188

Preliminary results of the first scientific drilling on Lake Baikal, Buguldeika site, southeastern Siberia - Colman, S.; Grachev, M.; Hearn, P.; Horie, S.; Kawai, T.; Kuzmin, M.; Logachov, N.; Fialkov, V.; Gorigljad, A.; Tomilov, B.; Khakhaev, B.; Kochikov, S.; et al. (Quaternary International, 1997)
The Baikal Drilling Project (BDP) is a multinational effort to investigate the paleoclimatic history and tectonic evolution of the Baikal sedimentary basin during the Late Neogene. In March 1993 the Baikal drilling system was successfuly deployed from a barge frozen into position over a topographic high, termed the Buguldeika saddle, in the southern basin of Lake Baikal. The BDP-93 scientific team, made up of Russian, American and Japanese scientists, successfully recovered the first long (>100 m) hydraulic piston cores from two holes in 354 m of water. High quality cores of 98 m (Hole 1) and 102 m (Hole 2), representing sedimentation over the last 500,000 years, were collected in 78 mm diameter plastic liners with an average recovery of 72% and 90%, respectively. Magnetic susceptibility logging reveals an excellent hole-to-hole correlation. In this report the scientific team describes the preliminary analytical results from BDP-93 hole 1 cores. Radiocarbon dating by accelerator mass spectrometry provides an accurate chronology for the upper portion of Hole 1. Detailed lithologic characteristics, rock magnetic properties and inorganic element distributions show a significant change to the depositional environment occuring at 50 m subbottom depth, approximately 250,000 BP. This change may be due to uplift and rotation of the horst block in the Buguldeika saddle. The sedimentary section above 50 m is pelitic with varve-like laminae, whereas the section below 50 m contains a high proportion of sand and gravel horizons often organized into turbidite sequences. Accordingly, high resolution seismic records reveal a change in sonic velocity at this depth. It is inferred that sedimentation prior to 250 ka BP was from the west via the Buguldeika river system. After 250 ka BP the Buguldeika saddle reflects an increase in hemipelagic sediments admired with fine-grained material from the Selenga River drainage basin, east of Lake Baikal. Variations in the spore-pollen assemblage, diatoms, biogenic silica content, rock magnetic properties, clay mineralogy and organic carbon in the upper 50 m of BDP-93-1 reveal a detailed record of climate change over approximately the last 250,000 years. These variables alternate in a pattern characteristic of glacial/interglacial climatic fluctuations. The present age model suggests that the climate signal recorded in Lake Baikal sediments is similar to Late Quaternary signals recorded in Chinese loess sections and in marine sediments. Copyright (C) 1996 INQUA/Elsevier Science Ltd
Vq100Times Cited:44 Cited References Count:29
Keywords: asia; tectonics

Radiocarbon chronology of Namaqualand mudbelt sediments: problems and prospects - Meadows, M. E.; Dingle, R. V.; Rogers, J.; Mills, E. G. (South African Journal of Science, 1997)
This paper presents the first radiocarbon-dated chronology of the mudbelt which occupies the continental shelf around southern Africa. The results confirm the Holocene age of the superficial deposits and suggest that laminations in the sediments of the mudbelt off the Orange River mouth are recent and terrestrially derived. Two anomalies are, however, apparent in the chronology. First, the surface sediments do not provide recent or contemporary radiocarbon ages, as would be expected. Second, the laminated sediments yield ages which are not in stratigraphic sequence and appear to be clustered around the period 1000 to 1700 sri Possible reasons for these anomalies are discussed together with alternative means of deriving a more accurate and reliable chronology for the mudbelt sediments.
Yb537Times Cited:7 Cited References Count:18
Keywords: accumulation rates; ages; Marine

Reproducibility of 14C AMS analyses at NOSAMS - Elder, K. L.; Gagnon, A. R.; McNichol, A. P. (16th International Radiocarbon Conference, 1997)
id: 961

Sedimentology of terrigenous mud from the Orange River delta and the inner shelf off Namaqualand, South Africa - Mabote, M.; Rogers, J.; Meadows, M. E. (South African Geographical Journal, 1997)
Sediment cores, from the inner shelf off the Namaqualand continental shelf have been examined using radiographic and grain-size techniques. Size-frequency distributions reveal that the sediments are poly modal, with a dominant very fine-silt mode being between 8-4μm, and suggest that the weak, poleward-flowing De Decker Current causes southward dispersal of terrigenous mud off the Orange River mouth. It appears that this current is not strong enough to transport material coarser than very fine silt. Material >63μm in size is rare, but may be indicative of storm events. Quartz and mica in the sediments are related to the semi-arid climate of Namaqualand, where they are entrained by adiabatic Berg winds moving offshore from the interior. Sponge spicules indicate the presence of filter-feeding animals (epifauna). Planktonic foraminifera may be indicative of relatively high productivity associated with nutrient-rich upwelling waters, which support an enormous population of plankton. The presence of faecal pellets is associated with the presence of burrowing infauna. Authigenic gypsum is associated with the presence of anaerobic conditions in the sediments. Two of the lithofacies identified in these fine-grained deposits are: (a) laminated mud and (b) homogeneous mud. Primary sedimentary structures are present, particularly in the portion of the mudbelt closest to the Orange Delta, where the mud is well laminated. Laminations decrease in abundance southward from the delta, where the muddy sediment is increasingly bioturbated (burrowed) by infauna, probably by polychaete worms.
id: 218

Target preparation for continuous flow accelerator mass spectrometry - Schneider, R. J.; Hayes, J. M.; Eglinton, T. I.; McNichol, A. P.; von Reden, K. F. (16th International Radiocarbon Conference, 1997)
id: 953

Target preparation for continuous flow accelerator mass spectrometry - Schneider, R. J.; Hayes, J. M.; von Reden, K. F.; McNichol, A. P.; Eglinton, T. I. (Radiocarbon, 1997)
id: 1661

Target preparation for continuous flow accelerator mass spectrometry: (Proceedings of the 16th International Radiocarbon Conference, 1997) - Schneider, R. J.; Hayes, J. M.; von Reden, K. F.; McNichol, A. P.; Eglinton, T. (Radiocarbon, 1997)
id: 1752

Variability in radiocarbon ages of individual organic compounds from marine sediments - Eglinton, T. I.; BenitezNelson, B. C.; Pearson, A.; McNichol, A. P.; Bauer, J. E.; Druffel, E. R. M. (Science, 1997)
Organic carbon (OC) from multiple sources can be delivered contemporaneously to aquatic sediments. The influence of different OC inputs on carbon-14-based sediment chronologies is illustrated in the carbon-14 ages of purified, source-specific (biomarker) organic compounds from near-surface sediments underlying two contrasting marine systems, the Black Sea and the Arabian Sea, In the Black Sea, isotopic heterogeneity of n-alkanes indicated that OC was contributed from both fossil and contemporary sources. Compounds reflecting different source inputs to the Arabian Sea exhibit a 10,000-year range in conventional carbon-14 ages. Radiocarbon measurements of biomarkers of marine photoautotrophy enable sediment chronologies to be constructed independent of detrital OC influences.
Xq247Times Cited:175Cited References Count:37

AMS measurements of the 14C distribution in the Pacific Ocean - von Reden, K. F.; McNichol, A. P.; Schneider, R. J. (7th International Conference on Accelerator Mass Spectrometry, 1996)
id: 950; 1

Automated systems and techniques utilized at the NOSAMS sample preparation laboratory: An update of productivity and quality issues - Gagnon, A. R.; McNichol, A. P.; Hutton, D. L.; Osborne, E. A.; Donoghue, J. C. (Radiocarbon, 1996)
id: 959

Cape May site report - Miller, K. G.; Liu, C.; Browning, J. V.; Pekar, S.; Sugarman, P.; Van Fossen, M. C.; Mullikin, L.; Queen, D.; Feigenson, M. D.; Aubry, M. P.; Burckle, L. D.; Powars, D.; et al. (Proc. ODP, Init. Repts, 1996)
id: 55

Catastrophic discharge of fluvial sediment to the ocean; evidence of jokulhlaups events in the Alsek Sea Valley, Southeast Alaska (USA) - Milliman, J. D.; Snow, J.; Jaeger, J.; Nittrouer, C. A. (International symposium on Erosion and sediment yield; global and regional perspectives, 1996)
id: 28

Character, paleoenvironment, rate of accumulation, and evidence for seismic triggering of Holocene turbidites, Canada Abyssal Plain, Arctic Ocean - Grantz, A.; Phillips, R. L.; Mullen, M. W.; Starratt, S. W.; Jones, G. A.; Naidu, A. S.; Finney, B. P. (Marine Geology, 1996)
Four box cores and one piston core show that Holocene sedimentation on the southern Canada Abyssal Plain for the last 8010 +/- 120 yr has consisted of a continuing rain of pelagic organic and ice-rafted elastic sediment with a net accumulation rate during the late Holocene of less than or equal to 10 mm/1000 yr, and episodically emplaced turbidites 1-5 m thick deposited at intervals of 830 to 3450 yr (average 2000 yr). The average net accumulation rate of the mixed sequence of turbidites and thin pelagite interbeds in the cores is about 1.2 m/1000 yr.Physiography suggests that the turbidites originated on the Mackenzie Delta or its clinoform, and delta(13)C values of -27 to -25 parts per thousand in the turbidites are compatible with a provenance on a delta. Extant displaced neritic and lower slope to basin plain calcareous benthic foraminifers coexist in the turbidite units. Their joint occurence indicates that the turbidites originated on the modern continental shelf and entrained sediment from the slope and rise enroute to their final resting place on the Canada Abyssal Plain. The presence of Middle Pleistocene diatoms in the turbidites suggests, in addition, that the turbidites may have originated in shallow submarine slides beneath the upper slope or outer shelf. Small but consistent differences in organic carbon content and delta(13)C values between the turbidite units suggest that they did not share an identical provenance, which is at least compatible with an origin in slope failures.The primary provenance of the ice-rafted component of the pelagic beds was the glaciated terrane of northwestern Canada; and the provenance of the turbidite units was Pleistocene and Holocene sedimentary deposits on the outer continental shelf and upper slope of the Mackenzie Delta. Largely local derivation of the sediment of the Canada Abyssal Plain indicates that sediment accumulation rates in the Arctic Ocean are valid only for regions with similar depositional sources and processes, and that these rates cannot be extrapolated regionally. The location of an elliptical zone of active seismicity over the inferred provenance of the turbidites suggests that they were triggered by large earthquakes.Distal turbidite sediment accumulation rates were more than two orders of magnitude greater than pelagic sediment accumulation rates on the Canada Abyssal Plain during the last 8000 years. This disparity reconciles the discrepancy between the high accumulation rates assumed by some for the Arctic Ocean because of the numerous major rivers and large ice sheets that discharge into this small mediterranean basin and the low pelagic sedimentation rates that have been reported from the Arctic Ocean.
Uy014Times Cited:36Cited References Count:46

Chemical weathering and controls on atmospheric O2 and CO2: Fundamental principles were enunciated by J. J. Ebelmen in 1845 - Berner, Robert A.; Maasch, Kirk A. (Geochimica et Cosmochimica Acta, 1996)
id: 1533

A comparison of methods for the measurement of dissolved organic carbon in natural waters - Peltzer, E. T.; Fry, B.; Doering, P. H.; McKenna, J. H.; Norrman, B.; Zweifel, U. L. (Marine Chemistry, 1996)
A small suite of natural samples spanning a wide range of DOC concentrations and salinities were analyzed by three high-temperature combustion (HTC) techniques and persulfate oxidation, One of the HTC techniques, sealed-tube combustion (STC), served as a referee method, Using this method, it was possible to obtain absolute DOC concentrations for the natural samples free of any analytical blank offset, Prior to the comparison of samples, an exchange of carbon-free water and calibration standards showed that all methods were equally well calibrated, Linear correlation analysis was used to differentiate whether the differences observed between methods was due to variable oxidation yields or to an artifact of the instrument blank, Agreement among the various methods was quite good, but yields for all methods decreased compared to the STC technique at concentrations of > 400 mu M C. Persulfate results were found to be very similar to HTC results. Finally, carbon-free distilled water prepared by UV/H2O2 oxidation or Milli-Q systems had near-zero DOC concentrations and was adequate for blank correction of all the various techniques yielding DOC concentrations in excellent agreement with the referee method.
Vj296Times Cited:50Cited References Count:49

Compound specific radiocarbon analysis as a tool to quantitatively apportion modern and fossil sources of polycyclic aromatic hydrocarbons in environmental matrices. - Eglinton, T. I.; Pearson, A.; McNichol, A. P.; Currie, L. A.; Benner, B. A.; Wise, S. A. (Abstracts of Papers of the American Chemical Society, 1996)
1Va915 Times Cited:0 Cited References Count:0

Concentrations of carbonyl compounds and the carbon isotopy of formaldehyde at a coastal site in Nova Scotia during the NARE summer intensive - Tanner, Roger L.; Zielinska, Barbara; Uberna, Ewa; Harshfield, Gregory; McNichol, Ann P. (Journal of Geophysical Research: AtmospheresJ. Geophys. Res., 1996)
Keywords: 0315 Biosphere/atmosphere interactions; 0345 Pollution: urban and regional; 0365 Troposphere: composition and chemistry; 0394 Instruments and techniques

Concentrations of carbonyl compounds and the carbon isotopy of formaldehyde at a coastal site in Nova Scotia during the NARE summer intensive - Tanner, R. L.; Zielinska, B.; Uberna, E.; Harshfield, G.; McNichol, A. P. (Journal of Geophysical Research-Atmospheres, 1996)
The concentrations of gaseous atmospheric carbonyl compounds have been measured at a coastal site on the southern tip of Nova Scotia during August 1993 as part of the National Oceanic and Atmospheric Administration's North Atlantic Regional Experiment (NARE) summer intensive. The DNPH-cartridge technique was used for sampling, with analysis by HPLC with UV absorbance detection. The carbon isotopic content of formaldehyde was measured using a novel collection technique on bisulfite-coated fillers followed by accelerator mass spectrometric determination of C-14 content and C-13/C-12 isotopic ratios. Results from this study indicate that quantifiable levels above about 100 parts per trillion by volume were found at the Chebogue Point, Nova Scotia, site for several carbonyls, formaldehyde, acetaldehyde, acetone, propionaldehyde, methyl ethyl ketone, and benzaldehyde, for most 6-hour sampling periods. Six-hour averaged formaldehyde levels of <0.5 to about 3.5 parts per billion were found during periods of local influence and during influence of continental air masses crossing eastern Canada and northeastern US. In contrast, background levels of formaldehyde of 200-400 pptv were found under conditions of predominantly marine back trajectories. Large fractions of contemporary carbon (of the order of 80%) were found in collected formaldehyde samples for all transport regimes and formaldehyde concentrations, suggesting that biogenic sources of hydrocarbon precursors to formaldehyde predominated during the summer season.
Vz788Times Cited:38Cited References Count:42

Deep water formation and exchange rates in the Arctic Ocean: Implications from the distribution of 14C - Schlosser, P.; Kromer, B.; Ekwurzel, B.; Boenisch, G.; McNichol, A.; Schneider, R.; von Reden, K.; Oestlund, G. (7th International Conference on Accelerator Mass Spectrometry, 1996)
id: 947; 1

Effects of turbidity flows on organic matter accumulation, sulfate reduction, and methane generation in deep-sea sediments on the Iberia Abyssal Plain - Meyers, P. A.; Silliman, J. E.; Shaw, T. J. (Organic Geochemistry, 1996)
Non-steady-state sedimentation has affected preservation of organic matter in a Pliocene-Pleistocene turbidite sequence sampled by the Ocean Drilling Program at four closely spaced drill sites on the Iberia Abyssal Plain. Organic carbon concentrations average ca. 0.7% in sediments from Sites 897 and 898 and ca. 0.4% at Sites 899 and 900. Headspace concentrations of interstitial methane exceed 100,000 ppm in sediments from Sites 897 and 898 but are essentially zero in those from Sites 899 and 900. Methane concentrations do not rise until interstitial sulfate concentrations are virtually depleted, suggesting the presence of deep in situ methanogenic bacterial activity at Sites 897 and 898 and its absence at Sites 899 and 900. Two factors associated with the turbidity flows that created the sedimentary sequence evidently influenced post-depositional diagenesis at these sites. The principal factor is that the rapidly deposited turbidite sequences at Sites 897 and 898 protected organic matter from early oxic degradation and thereby permitted subsequent anoxic degradation to proceed. In contrast, organic matter in the more slowly deposited turbidites at Sites 899 and 900 was oxidized soon after deposition and was therefore not available for later microbial utilization. A lesser factor is that the turbidity flows may have obtained their entrained organic matter from different environments and consequently delivered organic matter with different characteristics. Both factors contributed to heterogeneity of the types and amounts of organic matter that accumulated in these deep-sea sediments, and this variability has influenced subsequent sulfate reduction and methanogenesis. Copyright (C) 1996 Elsevier Science Ltd.
Wd943Times Cited:22Cited References Count:33

Expanded Small Sample Capabilities at NOSAMS: Preparation and Analysis of Conventional Graphite Targets Containing 0.15 mg Carbon - Pearson, A.; McNichol, A. P.; Schneider, R. J.; von Reden, K. F. (7th International Conference on Accelerator Mass Spectrometry, 1996)
id: 946; 1

Forcing of Atlantic Equatorial and Subpolar Millennial Cycles by Precession - McIntyre, A.; Molfino, B. (Science, 1996)
Abundance cycles of the marine alga Florisphaera profunda centered on a period of 7600 carbon-14 years (8400 calendar years) are present in high-resolution records from the equatorial Atlantic spanning 0 to 45,000 years ago. These cycles correlate with Heinrich events 1 through 5, which document rapid changes in continental ice melting around the subpolar North Atlantic. These variations in F. profunda are a direct response to modulation in zonal wind-driven divergence produced by a precessional component of orbital variation during a time of reduced eccentricity modulation.
McIntyreMolfino eng 1996/12/13 Science. 1996 Dec 13;274(5294):1867-70.

Gas chromatographic isolation of individual compounds from complex matrices for radiocarbon dating - Eglinton, T. I.; Aluwihare, L. I.; Bauer, J. E.; Druffel, E. R.; McNichol, A. P. (Anal Chem, 1996)
This paper describes the application of a novel, practical approach for isolation of individual compounds from complex organic matrices for natural abundance radiocarbon measurement. This is achieved through the use of automated preparative capillary gas chromatography (PCGC) to separate and recover sufficient quantities of individual target compounds for (14)C analysis by accelerator mass spectrometry (AMS). We developed and tested this approach using a suite of samples (plant lipids, petroleums) whose ages spanned the (14)C time scale and which contained a variety of compound types (fatty acids, sterols, hydrocarbons). Comparison of individual compound and bulk radiocarbon signatures for the isotopically homogeneous samples studied revealed that Delta(14)C values generally agreed well (+/-10%). Background contamination was assessed at each stage of the isolation procedure, and incomplete solvent removal prior to combustion was the only significant source of additional carbon. Isotope fractionation was addressed through compound-specific stable carbon isotopic analyses. Fractionation of isotopes during isolation of individual compounds was minimal (<5 per thousand for delta(13)C), provided the entire peak was collected during PCGC. Trapping of partially coeluting peaks did cause errors, and these results highlight the importance of conducting stable carbon isotopic measurements of each trapped compound in concert with AMS for reliable radiocarbon measurements. The addition of carbon accompanying derivatization of functionalized compounds (e.g., fatty acids and sterols) prior to chromatographic separation represents a further source of potential error. This contribution can be removed using a simple isotopic mass balance approach. Based on these preliminary results, the PCGC-based approach holds promise for accurately determining (14)C ages on compounds specific to a given source within complex, heterogeneous samples.
Eglinton, T IAluwihare, L IBauer, J EDruffel, E RMcNichol, A Peng1996/03/01 00:00Anal Chem. 1996 Mar 1;68(5):904-12. doi: 10.1021/ac9508513.

Isolation of Individual Organic Compounds for AMS Radiocarbon Analysis--A Novel Approach - Eglinton, T. I.; McNichol, A. P.; Benitez-Nelson, B. C.; Pearson, A.; von Reden, K. F.; Schneider, R. J.; Bauer, J. E.; Druffel, E. R. M. (Radiocarbon, 1996)
id: 1650

Isolation of Individual Organic Compounds for AMS Radiocarbon Analysis -- A Novel Approach - Eglinton, T. I.; McNichol, A. P.; Benitez-Nelson, B. C.; Pearson, A.; von Reden, K. F.; Schneider, R. J.; Bauer, J. E.; Druffel, E. R. M. (7th International Conference on Accelerator Mass Spectrometry, 1996)
id: 1800; 1

Kinematic Effects in the Sputtering of Carbon Isotopes - Schneider, R. J.; Hartman, J.; von Reden, K. F.; McNichol, A. P. (7th International Conference on Accelerator Mass Spectrometry, 1996)
id: 1801; 1

Kinematic Effects in the Sputtering of Carbon Isotopes - Schneider, R. J.; Hartman, J.; von Reden, K. F.; McNichol, A. P. (Radiocarbon, 1996)
id: 1660

A long pollen record from lowland Amazonia: Forest and cooling in glacial times - Colinvaux, P. A.; DeOliveira, P. E.; Moreno, J. E.; Miller, M. C.; Bush, M. B. (Science, 1996)
A continuous pollen history of more than 40,000 years was obtained from a lake in the lowland Amazon rain forest. Pollen spectra demonstrate that tropical rain forest occupied the region continuously and that savannas or grasslands were not present during the last glacial maximum. The data suggest that the western Amazon forest was not fragmented into refugia in glacial times and that the lowlands were not a source of dust. Glacial age forests were comparable to modern forests but also included species now restricted to higher elevations by temperature, suggesting a cooling of the order of 5 degrees to 6 degrees C.
Vk748Times Cited:350Cited References Count:42

Preparative capillary gas chromatographic isolation of individual compounds from complex matrices for radiocarbon dating - Eglinton, T. I.; Aluwihare, L. I.; Bauer, J. E.; Druffel, E. R. M.; McNichol, A. P. (Analytical Chemistry, 1996)
id: 1340

Progress of the NOSAMS Facility WOCE 14C Data Analysis - von Reden, K. F.; McNichol, A. P.; Schneider, R. J. (Radiocarbon, 1996)
id: 1672

Progress of the NOSAMS Facility WOCE 14C data analysis - von Reden, K. F.; McNichol, A. P.; Schneider, R. J. (7th International Conference on Accelerator Mass Spectrometry, 1996)
id: 948; 1

Progress of the NOSAMS Facility WOCE 14C Data Analysis - von Reden, K. F.; McNichol, A. P.; Schneider, R. J. (Workshop on Applications of AMS to Global Climate Change, 1996)
id: 1768; 1

Progress of the NOSAMS Facility WOCE 14C Data Analysis, Workshop on Applications of AMS to Global Climate Change - von Reden, K. F.; McNichol, A. P.; Schneider, R. J. (Workshop on Applications of AMS to Global Climate Change, 1996)
id: 954; 8

Progress of the NOSAMS facility WOCE (super 14) C data analysis - von Reden, K. F.; McNichol, A. P.; Schneider, Robert J. (University of Arizona, Department of Geosciences, Tucson, AZ, United States (USA), 1996)
id: 2242; Source type: conferencepapers&proceedings; Object type: Article; Object type: Conference Paper; Copyright: GeoRef, Copyright 2007, American Geological Institute.; CSAUnique: 1999-071631; AccNum: 1999-071631; ISSN: 0033-8222; CODEN: RACAAT
Keywords: 02D; 07; accelerator mass spectroscopy; C-14; carbon; Isotope geochemistry; isotopes; mass spectroscopy; Oceanography; Pacific Ocean; progress report; radioactive isotopes; report; sea water; spectroscopy

Sedimentology of the Krakatau 1883 submarine pyroclastic deposits - Mandeville, C. W.; Carey, S.; Sigurdsson, H. (Bulletin of Volcanology, 1996)
The majority of tephra generated during the paroxysmal 1883 eruption of Krakatau volcano, Indonesia, was deposited in the sea within a 15-km radius of the caldera. Two syneruptive pyroclastic facies have been recovered in SCUBA cores which sampled the 1883 subaqueous pyroclastic deposit. The most commonly recovered facies is a massive textured, poorly sorted mixture of pumice and lithic lapilli-to-block-sized fragments set in a silty to sandy ash matrix. This facies is indistinguishable from the 1883 subaerial pyroclastic flow deposits preserved on the Krakatau islands on the basis of grain size and component abundances. A less common facies consists of well-sorted, planar-laminated to low-angle cross-bedded, vitric-enriched silty ash. Entrance of subaerial pyroclastic flows into the sea resulted in subaqueous deposition of the massive facies primarily by deceleration and sinking of highly concentrated, deflated components of pyroclastic flows as they traveled over water. The basal component of the deposit suggests no mixing with seawater as inferred from retention of the fine ash fraction, high temperature of emplacement, and lack of traction structures, and no significant hydraulic sorting of components. The laminated facies was most likely deposited from low-concentration pyroclastic density currents generated by shear along the boundary between the submarine pyroclastic flows and seawater. The Krakatau deposits are the first well-documented example of true submarine pyroclastic flow deposition from a modern eruption, and thus constitute an important analog for the interpretation of ancient sequences where subaqueous deposition has been inferred based on the facies characteristics of encapsulating sedimentary sequences.
Uk310Times Cited:57Cited References Count:59

Stable and radio-carbon isotope measurements in the Pacific Ocean: Contribution from NOSAMS - McNichol, A. P.; Key, R.; Jones, G. (Supplement to Trans. Amer. Geophysical Union, 1996)
id: 1266

Stable and radio-carbon isotope measurements in the Pacific Ocean; contributions from NOSAMS - McNichol, A. P.; von Reden, K. F.; Schneider, R. J.; Key, R. M.; Jones, G. A. (American Geophysical Union, Washington, DC, United States (USA), 1996)
id: 2240; Source type: conferencepapers&proceedings; Object type: Article; Object type: Conference Paper; Copyright: GeoRef, Copyright 2007, American Geological Institute.; CSAUnique: 1997-047916; AccNum: 1997-047916; ISSN: 0096-3941; CODEN: EOSTAJ
Keywords: 02D; 07; accelerator mass spectroscopy; C-13/C-12; C-14; carbon; chemical analysis; geochemical indicators; high-resolution methods; Isotope geochemistry; isotope ratios; isotopes; marine geology; mass spectroscopy; National Ocean Sciences Accelerator Mass Spectrometry; NOSAMS; Oceanography; Pacific Ocean; radioactive isotopes; radioactive tracers; sampling; sea water; spectroscopy; Stable isotopes; tracers; Woods Hole Oceanographic Institution

Stable and radiocarbon isotope measurements in the Pacific Ocean: Contributions from NOSAMS - McNichol, A. P.; von Reden, K. F.; Schneider, R. J.; Key, R. M.; Jones, G. A. (AGU/ASLO 1996 Ocean Sciences Meeting, 1996)
id: 960

WOCE AMS Radiocarbon I: Pacific Ocean results (P6, P16, and P17) - Key, R. M.; Quay, P. D.; Jones, G. A.; McNichol, A. P.; von Reden, K. F.; Schneider, R. J. (Radiocarbon, 1996)
AMS radiocarbon results from the World Ocean Circulation Experiment in the Pacific Ocean show dramatic changes in the inventory and distribution of bomb-produced 14C since the time of the GEOSECS survey (8/73-6/74). Nearsurface 4C values for the eastern portion of both the northern and southern subtropical gyres decreased by 25-50%, with the change being greater in the north. Equatorial near-surface values have increased by ca. 25%. Changes in the 250-750-m depth range are dramatically different between the northern and southern basins. The intermediate and mode waters of the southern basin have increased by as much as 75%o since GEOSECS. Waters of similar density in the northern hemisphere are not exposed to the Southern Ocean circulation regime and are significantly less ventilated, showing maximum changes of ca. 50%.
id: 38

Improvements in procedural blanks at NOSAMS: Reflections of improvements in sample preparation and accelerator operation - McNichol, A. P.; Gagnon, A. R.; Osborne, E. a; Hutton, D. L.; von Reden, K. F.; Schneider, R. J. (15th International 14C Conference, 1995)
id: 1641; 15th International Radiocarbon Conference, Glasgow, Scotland, August 15-19, 1994

Improvements in procedural blanks at NOSAMS: Reflections of improvements in sample preparation and accelerator operation - McNichol, A. P.; Gagnon, A. R.; Osborne, E. A.; Hutton, D. L.; vonReden, K. F.; Schneider, R. J. (Radiocarbon, 1995)
During the four years the Sample Preparation Laboratory (SPL) at the National Ocean Sciences Accelerator Mass Spectrometer (NOSAMS) Facilty has been in operation we have accumulated much data from which we can assess our progress. We evaluate our procedural blanks here and describe modifications in our procedures that have improved our analyses of older samples. In the SPL, we convert three distinct types of samples-seawater, CaCO3 and organic carbon-to CO2 prior to preparing graphite for the accelerator and have distinct procedural blanks for each procedure. Dissolved inorganic carbon (Sigma CO2) is extracted from acidified seawater samples by sparging with a nitrogen carrier gas. We routinely analyze ''line blanks'' by processing CO2 from a C-14-dead source through the entire stripping procedure. Our hydrolysis blank, IAEA C-1, is prepared by acidifying in vacuo with 100% H3PO4 at 60 degrees C overnight, identical to our sample preparation. We use a dead graphite, NBS-21, or a commercially available carbon powder for our organic combustion blank; organic samples are combusted at 850 degrees C for 5 h using CuO to provide the oxidant. Analysis of our water stripping data suggests that one step in the procedure contributes the major portion of the line blank. At present, the contribution from the line blank has no effect on our seawater analyses (fraction modern (fm) between 0.7 and 1.2). Our hydrolysis blanks can have an fm value as low as 0.0006, but are more routinely between 0.0020 and 0.0025. The fm of our best organic combustion blanks is higher than those routinely achieved in other laboratories and we are currently altering our methods to reduce it.
Ud868Times Cited:16 Cited References Count:6
Keywords: SPECTROMETRY

Measurements of the OX-II/OX-1 ratio as a quality control parameter at NOSAMS - Schneider, R. J.; McNichol, A. P.; Nadeau, M. J.; von Reden, K. F. (Radiocarbon, 1995)
id: 1630

Measurements of the OX-II/OX-I ratio as a quality control parameter at NOSAMS - Schneider, R. J.; McNichol, A. P.; Nadeau, M. J.; von Reden, K. F. (15th International Radiocarbon Conference, 1995)
id: 944

Origin of Carbon in Fumarolic Gas from Island Arcs - Sano, Y.; Marty, B. (Chemical Geology, 1995)
We have measured He-3/He-4 ratios, delta(13)C-values and CO2/He-3 ratios of fumaroles and hot spring gases in three volcanic areas in Japan. The He-3/He-4 ratios, delta(13)C-values and CO2/He-3 ratios vary from 2.02 R(atm) to 7.55 R(atm) -9.7 parts per thousand to -2.7 parts per thousand and from 7.74.10(9) to 1.18.10(11), respectively. Based on these data and those in the literature, we present the first quantitative estimates of the upper mantle, sediment and limestone including slab components in CO2 of volcanic and hydrothermal fluids from subduction zones. Taking compiled C isotopic data of limestone and organic sediment, assuming that the CO2/He-3 ratio and delta(13)C-value of mid-ocean ridge basalt (MORB) are representative of the upper-mantle component, and that later isotopic and elemental fractionations are minimal, it is possible to deconvolve each fraction of C on the basis of simple mixing equations. Up to 20% of the carbon in high-temperature volcanic gases in subduction zones is derived from a MORB-type source, while the major fraction of the gases is attributable to CO2 produced by decarbonation of subducted marine limestone and slab carbonate.
Qc329Times Cited:227Cited References Count:46

Systematic decrease of high delta 13C values with burial in late archaean (2.8 Ga) diagenetic dolomite: evidence for methanogenesis from the Crixas Greenstone Belt, Brazil - Dix, G. R.; Thomson, M. L.; Longstaffe, F. J.; McNutt, R. H. (Precambrian Research, 1995)
id: 1589

Using sclerochronology of the mollusc Arctica islandica as a paleoceanographic tool - Marchitto, T. M.; Jones, G. A.; Goodfriend, G. A.; Weidman, C. R.; Jirikowic, J. (5th International Conference on Paleoceanography, 1995)
id: 1294

The Application of AMS to Organic Geochemistry--Constraints Imposed by Sample Preparation and Machine Operations - McNichol, A. P.; von Reden, K. F.; Schneider, R. J.; Jones, G. A. (EOS, Transactions of the American Geophysical Union, 1994)
id: 1798

Automated Sample Processing at the National Ocean Sciences Ams Facility - Cohen, G. J.; Hutton, D. L.; Osborne, E. A.; vonReden, K. F.; Gagnon, A. R.; McNichol, A. P.; Jones, G. A. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 1994)
The high throughput and high precision requirements for the NOSAMS facility have made it essential to automate many of the stages in sample processing. These automated procedures increase the sample capacity for the lab while reducing errors in sample preparation. Automation has also allowed sample histories to be recorded and saved in Sybase, a relational data base.
Nv547Times Cited:9Cited References Count:1

Comparative-Study of Fe-C Bead and Graphite Target Performance with the National-Ocean-Science-Ams (Nosams) Facility Recombinator Ion-Source - Klinedinst, D. B.; McNichol, A. P.; Currie, L. A.; Schneider, R. J.; Klouda, G. A.; vonReden, K. F.; Verkouteren, R. M.; Jones, G. A. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 1994)
An accelerator mass spectrometry (AMS) experiment was designed to investigate C-14 target performance for two target types over a range of isotopic concentrations and sample sizes, with a special focus on the ability to measure C-14 in environmental samples having only microgram amounts of carbon. The findings were positive, showing that precision, accuracy, and stability were adequate to determine C-14 to 1% or better in samples containing as little as 25 mug carbon. Satisfactory Poisson uncertainty and target stability were demonstrated down to a level of 7 mug carbon, but experimental data showed that accurate measurements at that level require detailed knowledge of blank variability and mass dependence of the modern carbon calibration factor.
Nv547Times Cited:23Cited References Count:13

Constraints Imposed by Sample Preparation and Machine Operations - McNichol, A. P.; von Reden, K. F.; Schneider, R. J.; Jones, G. A. (EOS, Transactions of the American Geophysical Union, 1994)
id: 937

Glacial/interglacial slope sedimentation changes on the Pleistocene NJ margin, ODP Site 904A - Christensen, B. A.; Thunell, R.; Miller, K. G.; Smith, N.; Cockrell, K. (Eos, Transactions, American Geophysical Union, 1994)
id: 54

High Precision Sea Water 14C Analyses at the National Ocean Sciences AMS Facility - von Reden, K. F.; Jones, G. A.; Schneider, R. J.; McNichol, A. P. (EOS, Transactions of the American Geophysical Union, 1994)
id: 939

High resolution sediment changes on the Pleistocene NJ upper slope - Christensen, B. A.; Hoppie, B. W.; Miller, K. G.; Thunell, R. C.; Le, J. (Eos, Transactions, American Geophysical Union, 1994)
id: 53

High-precision AMS radiocarbon measurements of central Arctic Ocean seawaters - Jones, G. A.; Gagnon, A. R.; Schneider, R. J.; von Reden, K. F.; McNichol, A. P. (Nuclear Instruments and Methods in Physics Research, 1994)
id: 52

High-precision sea water 14C analyses by accelerator mass spectrometry. 15th International Radiocarbon Conference, Glasgow, Scotland, August 15-19 - von Reden, K. F.; Jones, G. A.; Schneider, R. J.; McNichol, A. P. (EOS, Transactions of the American Geophysical Union, 1994)
id: 941

High-Resolution Climate Records from the North-Atlantic during the Last Interglacial - McManus, J. F.; Bond, G. C.; Broecker, W. S.; Johnsen, S.; Labeyrie, L.; Higgins, S. (Nature, 1994)
THE two deep ice cores recovered by the GRIP(1) and GISP(2) projects at Summit, Greenland, agree in detail over the past 100,000 years(3) and demonstrate dramatic climate variability in the North Atlantic region during the last glacial, before the current period of Holocene stability. This glacial climate instability has subsequently been documented in the marine sedimentary record of surface-ocean conditions in the North Atlantic(4). Before 100 kyr ago the two ice core records are discrepant, however, casting doubt on whether the oxygen isotope fluctuations during the last interglacial (Eemian) seen in the GRIP core(1,5) represent a true climate signal. Here we present high-resolution records of foraminiferal assemblages and ice-rafted detritus from two North Atlantic cores for the interval 65 kyr to 135 kyr ago, extending the surface-ocean record back to the Eemian. The correlation between our records and the Greenland ice-core records is good throughout the period in which the two ice cores agree, suggesting a regionally coherent climate response. During the Eemian, our marine records show a more stable climate than that implied by the GRIP ice core, suggesting that localized phenomena may be responsible for the variability in the latter record during the Eemian.
Ph254Times Cited:313Cited References Count:25

Internal and External Checks in the Nosams Sample Preparation Laboratory for Target Quality and Homogeneity - Osborne, E. A.; McNichol, A. P.; Gagnon, A. R.; Hutton, D. L.; Jones, G. A. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 1994)
In the NOSAMS sample preparation laboratory (SPL) we have developed rigorous internal procedures aimed at ensuring that sample preparation introduces as little error into our analyses as possible and identifying problems rapidly. Our three major CO2 preparation procedures are: stripping inorganic carbon from seawater, hydrolyzing CaCO3, and oxidizing organic matter. For seawater, approximately 10% of our analyses are standards or blanks which we use to demonstrate extraction of virtually all the inorganic carbon. Analysis of the stable carbon isotopic composition of the CO2 extracted from our standards indicates a precision of better than 0.15-0.20 parts per thousand. We also routinely process C-14-free CO2 in our stripping lines to demonstrate the absence of a significant process-dependent blank. For organic combustions and CaCO3 hydrolyses, we use the carbon yield (% organic carbon (OC) or % CaCO3 by weight) as a check on our sample procedures. We have analyzed the blank contribution of these procedures as a function of sample size. Our organic carbon blank is constant at approximately 0.4% modem for samples containing greater than 1 mg C and our carbonate blank is less than 0.2% modern for samples containing more than 0.5 mg C. We use a standard Fe/H-2 catalytic reduction to prepare graphite from CO2. We check the completeness of our reactions with the pressure data stored during the reaction as well as use a robot to determine a gravimetric yield. All graphite undergoes a visual inspection and is rejected if any heterogeneities are present. We have recombusted graphite made from CO2 with deltaC-13 values ranging from -42 to 1 parts per thousand and determined that the deltaC-13 of the recombusted carbon agrees with that from the pure gas to within 0.05 parts per thousand, demonstrating little or no fractionation during the treatment of the sample. The deltaC-13 we measure on the CO2 generated from more than 75% of our samples is compared to the deltaC-13 measured on the AMS as a further check of our procedures. As further external checks, we analyzed the International Atomic Energy Association (IAEA) samples during the establishment of our laboratory and are presently participating in the third international radiocarbon intercalibration (TIRI) exercise.
Nv547Times Cited:14Cited References Count:5

La Curva Di Risalta Del Mare Tirreno Negli Ultimi 40 KA Ottenuta Mediante Datazioni Di Speleotemi Sommersi E Dati Archeologici - Alessio, M.; Allegri, L.; Antonioli, F.; Belluomini, G.; Improta, S.; Manfra, L.; Martinez, M. P. (International Meeting on Underwater Geology, 1994)
id: 899

Latest Quaternary Sedimentation in the Kerch Strait Area of the Black Sea Shelf: Response to Glacial Sea Level Fluctuation - Major, C. O.; Ryan, W. B. F.; Pitman, W. C., III; Shimkus, K. M.; Jones, G. A.; O'Connell, S. (EOS,Transactions,American Geophysical Union, 1994)
id: 914

Methods for Data Screening, Flagging and Error Analysis at the National-Ocean-Sciences-Ams-Facility - Schneider, R. J.; Jones, G. A.; McNichol, A. P.; vonReden, K. F.; Elder, K. L.; Huang, K.; Kessel, E. D. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 1994)
All data collection, from sample submittal through processing into targets and AMS analysis, is integrated within a large relational database (Sybase). Over 50 tables are linked through key fields. Through structured queries, the information is analysed and presented for a wide variety of applications. Benefits include enhanced quality control, more complete reports to users and more accurate transfer of data among the several laboratories on the network.
Nv547Times Cited:14Cited References Count:4

The National Ocean Sciences Accelerator Mass Spectrometry Facility: Recent Developments - Schneider, R. J.; Jones, G. A.; von Reden, K. F.; McNichol, A. P. (EOS, Transactions of the American Geophysical Union, 1994)
id: 938

ODP Initial Reports, Leg 150X - Miller, K. G.; Liu, C.; Browning, J. V.; Pekar, S. F.; Sugarman, P. J.; Van Fossen, M. C.; Mullikin, L.; Queen, D.; Feigenson, M. D.; Aubry, M. P.; Burckle, L. D.; Powars, D.; et al. (Ocean Drilling Program, 1994)
id: 1347

Radiocarbon Dating of Marine Deposits on Submerged Speleothems and Sea-Level Oscillation - Alessio, M.; Allegri, L.; Antonioli, F.; Belluomini, G.; Improta, S.; Manfra, L. (15th International Radiocarbon Conference, 1994)
id: 900

Rapid analysis of seawater samples at the National Ocean Sciences Accelerator Mass Spectrometry Facility, Woods Hole, MA - McNichol, A. P.; Jones, G. A.; Hutton, D. L.; Gagnon, A. R.; Key, R. M. (Radiocarbon, 1994)
id: 305

The Rapid Preparation of Seawater Sigma-Co2 for Radiocarbon Analysis at the National Ocean Sciences Ams Facility - McNichol, A. P.; Jones, G. A.; Hutton, D. L.; Gagnon, A. R.; Key, R. M. (Radiocarbon, 1994)
We have established a laboratory for extracting Sigma CO2 from seawater samples for AMS analysis of the radiocarbon content. The seawater samples are collected at sea, poisoned and stored until analysis in the laboratory. Each sample is acidified; the inorganic carbon is stripped out as CO2 with an inert carrier gas and then converted to graphite. We present results for Buzzards Bay surface H2O and Na2CO3 standards that demonstrate we strip > 98% of inorganic carbon from seawater. Stable isotope analyses are performed to better than 0.2 parts per thousand, and the reproducibility of C-14 measurements on Buzzards Bay seawater is better than 13 parts per thousand. Finally, we compare data from samples collected in 1991 to those collected in the 1970s and to large volume samples.
Pz926Times Cited:61 Cited References Count:14
Keywords: accelerator mass-spectrometry; C-14; samples

Thermocline Ventilation Rates in the North Pacific - Sonnerup, R. E.; Quay, P. D.; Bullister, J. L.; Key, R. M.; McNichol, A. P.; Jones, G. A. (American Geophysical Union, San Francisco, 1994)
id: 917

Tic, Toc, Dic, Doc, Pic, Poc - Unique Aspects in the Preparation of Oceanographic Samples for C-14 Ams - McNichol, A. P.; Osborne, E. A.; Gagnon, A. R.; Fry, B.; Jones, G. A. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 1994)
The radiocarbon content of discrete carbon pools (total (T), dissolved (D), and particulate (P) inorganic (I) and organic (O) carbon (C)) is a useful tracer of carbon cycling within the modem and past ocean. The isolation of different carbon pools in the ocean environment and conversion to CO2 presents unique analytical problems for the radiocarbon chemist. In general, isolation and preparation of inorganic carbon presents few problems; dissolved carbon is easily extracted by acidifying the sample and stripping with an inert gas. Carbon is also readily isolated from particulate carbonate samples; in this case, CO2 is prepared by hydrolysis of the substrate with phosphoric acid. The isolation and preparation of organic carbon presents a much greater problem. Dissolved organic carbon (DOC) must first be isolated from DIC and then oxidized in the presence of very high salt concentrations. We present results from a closed-tube combustion method in which the DIC-free seawater is evaporated to dryness, transferred to a clean combustion tube, and oxidized overnight at 550-degrees-C. Combustion of total organic carbon (TOC) in sediments with a high inorganic carbon content is also difficult. Removal of CaCO3 with acid leaves severely deliquescent salts which, if not thoroughly dried, cause combustion tubes to explode. Removal of the salts by rinsing can also remove significant amounts of organic matter. Finally, we present results from a local coastal region.
Nv547Times Cited:82Cited References Count:9

Comparative study of Fe-C Bead vs. graphite target performance with the NOSAMS Facility recombinator ion source - Kleindinst, D. B.; McNichol, A. P.; Currie, L. A.; Jones, G. A.; Verkouteren, R. M.; von Reden, K. F.; Klouda, G. A.; Schneider, R. J. (6th International Conference on Accelerator Mass Spectrometry, 1993)
id: 931

The high-precision AMS 14C program on seawater at the National Ocean Sciences AMS Facility - von Reden, K. F.; Jones, G. A.; Schneider, R. J.; McNichol, A. P. (European Community Workshop on Development of Ocean Tracer Measurements, 1993)
id: 1767

High-precision AMS radiocarbon measurements of seawater at the National Ocean Sciences AMS Facility - Jones, G. A.; Schneider, R. J.; McNichol, A. P.; von Reden, K. F. (6th International Conference on Accelerator Mass Spectrometry, 1993)
id: 929

Internal and external checks in the NOSAMS Sample Preparation Laboratory for target quality and homogeneity - McNichol, A. P.; Gagnon, A. R.; Osborne, E. A.; Hutton, D. L.; Jones, G. A. (6th International Conference on Accelerator Mass Spectrometry, 1993)
id: 958

Laboratory automation at the National Ocean Sciences AMS Facility - Cohen, G. J.; Hutton, D. L.; von Reden, K. F.; Osborne, E. A.; McNichol, A. P.; Jones, G. A. (6th Internation Conference on Accelerator Mass Spectrometry, 1993)
id: 927

Methods for data screening, flagging and error analysis at the National Ocean Sciences AMS Facility - Schneider, R. J.; Jones, G. A.; McNichol, A. P.; von Reden, K. F.; Elder, K. L.; Kessel, E. D. (6th International Conference on Accelerator Mass Spectrometry, 1993)
id: 933

The National Ocean Sciences Accelerator Mass Spectrometry Facility - Jones, G. A.; McNichol, A. P.; von Reden, K. F.; Schneider, R. J. (WOCE Notes, 1993)
id: 1639

The National Ocean Sciences Accelerator Mass Spectrometry Facility and the WOCE Hydrographic Program. Measurement of 14C in seawater by AMS - McNichol, A. P.; Jones, G. A.; Schneider, R. J.; von Reden, K. F.; Key, R. M. (Third Scientific Meeting, Oceanography Society, 1993)
id: 1656

The National Ocean Sciences Accelerator Mass Spectrometry Facility (WOCE) - Jones, G. A.; McNichol, A. P.; von Reden, K. F.; Schneider, R. J. (WOCE Notes, 1993)
id: 1651

The National Ocean Sciences AMS Facility at Woods Hole Oceanographic Institution - Jones, G. A.; Schneider, R. J.; von Reden, K. F.; McNichol, A. P.; Gagnon, A. R.; Cohen, G. J.; Osborne, E. A.; Hutton, D. L.; Kessel, E. D.; Elder, K. L. (6th International Conference on Accelerator Mass Spectrometry, 1993)
id: 930

The National Ocean Sciences AMS System at Woods Hole Oceanographic Institution - von Reden, K. F.; Jones, G. A.; Schneider, R. J.; McNichol, A. P. (European Community Workshop on Tracers in Physical Oceanography, 1993)
id: 935

Putting Ourselves to the Test: Analysis of the IAEA Intercomparison Samples - McNichol, A. P. (AMS Pulse, 1993)
id: 1612

Role of the United States National Ocean Sciences Accelerator Mass Spectrometry Facility in Global Climate Change Studies - Jones, G. A.; Schneider, R. J.; von Reden, K. F.; McNichol, A. P. (International Symposium on Applications of Isotope Techniques in Studying Past and Current Environmental Change in the Hydrosphere and the Atmosphere, 1993)
id: 928

Abundances and Isotopic Compositions of Carbon and Sulfur Species in Whole Rock and Kerogen Samples - Strauss, H.; Moore, T. B. (The Proterozoic Biosphere, 1992)
id: 1599

Application of AMS to Oceanography: Progress at the National Ocean Sciences AMS Facility (abstract) - McNichol, A. P.; Jones, G. A.; Schneider, R. J.; von Reden, K. F. (AMS Symposium Division of Nuclear Chemistry and Technology, 203rd American Chemical Society National Meeting, 1992)
id: 1796

Illumination of a Black-Box - Analysis of Gas-Composition during Graphite Target Preparation - McNichol, A. P.; Gagnon, A. R.; Jones, G. A.; Osborne, E. A. (Radiocarbon, 1992)
We conducted a study of relative gas composition changes of CO2, CO and CH4 during the formation of graphite targets using different temperatures, catalysts and methods. Reduction with H-2 increases the reaction rate without compromising the quality of the AMS target produced. Methane is produced at virtually any temperature, and the amount produced is greater at very low temperatures. The reduction of CO to graphite is very slow when H-2 is not included in the reaction.
Kf389Times Cited:63 Cited References Count:10
Keywords: deposition

The National Ocean Sciences Accelerator Mass Spectrometer for Precision C-14 at Woods Hole Oceanographic Institution -- Status and new results - von Reden, K. F.; Jones, G. A.; Schneider, R. J.; McNichol, A. P.; Cohen, G. J. (EOS, Transactions of the American Geophysical Union, 1992)
id: 926

The new National Ocean Sciences Accelerator Mass Spectrometer Facility at Woods Hole Oceanographic Institution-Progress and first results (Proceedings of the 14th International Radiocarbon Conference, 1991) - von Reden, K. F.; Jones, G. A.; Schneider, R. J.; McNichol, A. P.; Cohen, G. J.; Purser, K. H. (Radiocarbon, 1992)
id: 1787

The new National Ocean Sciences Accelerator Mass Spectrometer Facility at Woods Hole Oceanographic Institution - Progress and First Results - von Reden, K. F.; Jones, G. A.; Schneider, R. J.; McNichol, A. P.; Cohen, G. J.; Purser, K. H. (14th International Radiocarbon Conference 1991, 1992)
id: 1618

Oceanic Crustal Thickness from Seismic Measurements and Rare-Earth Element Inversions - White, R. S.; Mckenzie, D.; Onions, R. K. (Journal of Geophysical Research-Solid Earth, 1992)
Seismic refraction results show that the igneous section of oceanic crust averages 7.1 +/- 0.8 km thick away from anomalous regions such as fracture zones and hot-spots, with extremal bounds of 5.0-8.5 km. Rare earth element inversions of the melt distribution in the mantle source region suggest that sufficient melt is generated under normal oceanic spreading centers to produce an 8.3 +/- 1.5 km thick igneous crust. The difference between the thickness estimates from seismics and from rare earth element inversions is not significant given the uncertainties in the mantle source composition, though it is of the magnitude that would be expected if partial melt fractions of about 1% remain in the mantle and are not extracted to the overlying crust. The inferred igneous thickness increases to 10.3 +/- 1.7 km (seismic measurements) and 10.7 +/- 1.6 km (rare earth element inversions) where spreading centers intersect the regions of hotter than normal mantle surrounding mantle plumes. This is consistent with melt generation by decompression of the hotter mantle as it rises beneath spreading centers. Maximum inferred melt volumes are found on aseismic ridges directly above the central rising cores of mantle plumes, and average 20 +/- 1 and 18 +/- 1 km for seismic profiles and rare earth element inversions respectively. Both seismic measurements and rare earth element inversions show evidence for variable local crustal thinning beneath fracture zones, though some basalts recovered from fracture zones are indistinguishable geochemically from those generated on normal ridge segments away from fracture zones. This is consistent with a model where the melt generated beneath spreading ridges is redistributed to intrusive centers along the ridge axis, from where it may flow laterally along the axis at crustal or surface levels. The melt may sometimes flow into the bathymetric lows associated with fracture zones. Oceanic crust created at very slow-spreading ridges, and in regions adjacent to some continental margins where rifting was initially very slow, exhibits anomalously thin crust from seismic measurements and unusually small amounts of melt generation from rare earth element inversions. We attribute the decreased mantle melting on very slow-spreading ridges to the conductive heat loss that enables the mantle to cool as it rises beneath the rift.
Kd951Times Cited:645Cited References Count:119

Rapid Analysis of Seawater Inorganic Carbon at the National Ocean Sciences AMS Facility: Progress and Preliminary Results (abstract) - McNichol, A. P.; Jones, G. A.; Schneider, R. J.; von Reden, K. F.; Key, R. M. (EOS, Transactions of the American Geophysical Union Meeting, 1992)
id: 1655

Variability of the delta13C of dissolved inorganic carbon at a site in the North Pacific Ocean - McNichol, A. P.; Druffel, E. R. M. (Geochimica et Cosmochimica Acta, 1992)
id: 1746

Carbon cycling in coastal sediments: 2. An investigation of the sources of CO2 to pore water using carbon isotopes - McNichol, A. P.; Druffel, E. R. M.; Lee, C. (Organic Substances and Sediments in Water, Processes and Analytical, 1991)
id: 1743

Carbon cycling in coastal sediments: 2. Estimating remineralization in Buzzards Bay, MA--A comment - Rowe, G. T.; McNichol, A. P. (Geochimica et Cosmochimica, 1991)
id: 1786

Carbon isotope anomalies in carbonates of the Karelian Complex - Yudovich, Y. E.; Makarikhin, V. V.; Medvedev, P. V.; Sukhanov, N. V. (Geochemistry International, 1991)
id: 1607

Illumination of a black box: Gas composition changes during graphite target preparation for AMS (Proceedings of the 14th International Radiocarbon Conference, 1991) - McNichol, A. P.; Gagnon, A. R.; Jones, G. A.; Osborne, E. A. (Radiocarbon, 1991)
id: 1745

Measuring 14C in seawater by Accelerator Mass Spectrometry - McNichol, A. P.; Jones, G. A. (WOCE Hydrographic Programme Office/Woods Hole Oceanographic Institution, 1991)
id: 1610

The optimization of target production for AMS - McNichol, A. P.; Gagnon, A. R.; Jones, G. A.; Schneider, R. J.; von Reden, K. F. (14th International Radiocarbon Conference, 1991)
id: 922

Quantification and characterization of porewater organic colloids - Chin, Y. P.; McNichol, A. P.; Gschwend, P. M. (Organic Substances and Sediments in Water. Processes and Analytical, 1991)
id: 1744